3D-Visualization of Neurovascular Compression at the Ventrolateral Medulla in Patients with Arterial Hypertension - Manava, Panagiota; Naraghi, Ramin; Schmieder, Roland; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael M.; Buchfelder, Michael; Hastreiter, Peter (Clinical Neuroradiology, 2020)
Purpose: Controversy exists on the association of arterial hypertension (HTN) and neurovascular compression (NVC) at the ventrolateral medulla (VLM). No standardized and reproducible technique has been introduced yet for detection of NVC in HTN. This study aimed to generate, analyze and compare different results of exact reproducible anatomical 3D-representations of the VLM in patients with HTN, based on magnetic resonance imaging (MRI). Methods: A 3T scanner provided MRI (T2-constructive interference in steady state (CISS) high resolution imaging and three-dimensional Time-of-flight (3D-TOF) angiography) from the posterior fossa of 44 patients with clinical treatment-resistant HTN. Image processing consists of segmentation of the CISS data, registration and fusion of the CISS and TOF data and visualization. For each patient two 3D-visualizations (before and after fusion) were obtained. The reproduction quality of the vessels, flow-related signal variability and pulsation artifacts were analyzed and compared, using a ranking score. Results: Integrating vascular information from TOF into CISS data reduced artifacts in 3D-visualizations of exclusively processed CISS data. The quality of 3D-visualization of the vessels near the brain stem was significantly improved (p = 0.004). The results were reproducible and reliable. The quality of the 3D-presentations of neurovascular relationships at the VLM improved significantly (p < 0.001). Conclusion: The 3D-visualization of fused image data provides an excellent overview of the relationship between cranial nerves and vessels at the VLM and simplifies the detection of NVC in HTN. It provides a powerful tool for future clinical and scientific research. Although microvascular decompression (MVD) in treatment resistant HTN is not a standard procedure, it can be discussed in selected patients with intractable severe HTN.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Cranial nerves; Image fusion; Image processing; MRI; Posterior fossa; Vascular compression disorders

4D DSA for Dynamic Visualization of Cerebral Vasculature: A Single-Center Experience in 26 Cases - Lang, Stefan; Gölitz, Philipp; Struffert, Tobias; Roesch, J.; Roessler, Karl; Kowarschik, M.; Strother, C.; Dörfler, Arnd (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: 4D DSA allows acquisition of time-resolved 3D reconstructions of cerebral vessels by using C-arm conebeam CT systems. The aim of our study was to evaluate this new method by qualitative and quantitative means. MATERIALS AND METHODS: 2D and 4D DSA datasets were acquired in patients presenting with AVMs, dural arteriovenous fistulas, and cerebral aneurysms. 4D DSA was compared with 2D DSA in a consensus reading of qualitative and quantitative parameters of AVMs (eg, location, feeder, associated aneurysms, nidus size, drainage, Martin-Spetzler Score), dural arteriovenous fistulas (eg, fistulous point, main feeder, diameter of the main feeder, drainage), and cerebral aneurysms (location, neck configuration, aneurysmal size). Identifiability of perforators and diameters of the injection vessel (ICA, vertebral artery) were analyzed in 2D and 4D DSA. Correlation coefficients and a pairedttest were calculated for quantitative parameters. The effective patient dose of the 4D DSA protocol was evaluated with an anthropomorphic phantom. RESULTS: In 26 patients, datasets were acquired successfully (AVM = 10, cerebral aneurysm = 10, dural arteriovenous fistula = 6). Qualitative and quantitative evaluations of 4D DSA in AVMs (nidus size:r= 0.99,P= .001), dural arteriovenous fistulas (diameter of the main feeder:r= 0.954,P= .03), and cerebral aneurysms (aneurysmal size:r= 1,P= .001) revealed nearly complete accordance with 2D DSA. Perforators were comparably visualized with 4D DSA. Measurement of the diameter of the injection vessel in 4D DSA was equivalent to that in 2D DSA (P= .039). The effective patient dose of 4D DSA was 1.2 mSv. CONCLUSIONS: 4D DSA is feasible for imaging of AVMs, dural arteriovenous fistulas, and cerebral aneurysms. 4D DSA offers reliable visualization of the cerebral vasculature and may improve the understanding and treatment of AVMs and dural arteriovenous fistulas. The number of 2D DSA acquisitions required for an examination may be reduced through 4D DSA.
EVALuna2:33141

7 Tesla Hippocampal Subfield Analyses In Patients With Medically Refractory Epilepsy And Hippocampal Sclerosis - Roessler, K.; Roesch, Johannes; Coras, R.; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan; Mennecke, Angelika (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

A brave new framework for glioma drug development - Hotchkiss, Kelly M.; Karschnia, Philipp; Schreck, Karisa C.; Geurts, Marjolein; Cloughesy, Timothy F.; Huse, Jason; Duke, Elizabeth S.; Lathia, Justin; Ashley, David M.; Nduom, Edjah K.; Long, Georgina; Singh, Kirit; et al. (Lancet Oncology, 2024)
Patients with brain tumours are motivated to participate in clinical trials involving repeat tissue sampling. Normalising the use of neoadjuvant and staged surgical trials necessitates collaboration among patients, regulatory agencies, and researchers. Initial and repetitive tissue sampling plays a crucial role in enhancing our understanding of resistance mechanisms and vulnerabilities in brain tumour therapy. Standardising biopsy techniques and ensuring technical uniformity across institutions are vital for effective interinstitutional collaboration. Although liquid biopsy technologies hold promise, they are not yet ready to replace tissue analysis. Clear communication about the risks and benefits of biopsies is essential, particularly regarding potential postoperative deficits. Changes in mindset and neurosurgical culture are imperative to achieve much needed breakthroughs in the development of new, effective therapies for brain tumours.
CRIS-Team Scopus Importer:2024-10-11

Abstract: Deep Learning-based Quantification of Pulmonary Hemosiderophages in Cytology Slides - Marzahl, Christian; Aubreville, Marc; Bertram, Christof A.; Stayt, Jason; Jasensky, Anne Katherine; Bartenschlager, Florian; Fragoso, Marco; Barton, Ann K.; Elsemann, Svenja; Jabari, Samir; Krauth, Jens; Madhu, Prathmesh; et al. (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2021-04-19

A Clarion Call for Neuroinflammatory Assays in Brain Stimulation for Chronic Pain - Kinfe, Thomas Mehari; Zhao, Yining; Viviani, Barbara (Brain Sciences, 2022)
CRIS-Team Scopus Importer:2022-04-01
Keywords: Adipokine; Brain stimulation; Brain–immune communication; Chronic pain disorders; Cytokine; Neuroinflammation

A Comparison of Single- and Multiparametric MRI Models for Differentiation of Recurrent Glioblastoma from Treatment-Related Change - Eisenhut, Felix; Engelhorn, Tobias; Arinrad, Soheil; Brandner, Sebastian; Coras, Roland; Putz, Florian; Fietkau, Rainer; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2021)
To evaluate single- and multiparametric MRI models to differentiate recurrent glioblastoma (GBM) and treatment-related changes (TRC) in clinical routine imaging. Selective and unselective apparent diffusion coefficient (ADC) and minimum, mean, and maximum cerebral blood volume (CBV) measurements in the lesion were performed. Minimum, mean, and maximum ratios(CBV) (CBVlesion to CBVhealthy white matter) were computed. All data were tested for lesion discrimination. A multiparametric model was compiled via multiple logistic regression using data demonstrating significant difference between GBM and TRC and tested for its diagnostic strength in an independent patient cohort. A total of 34 patients (17 patients with recurrent GBM and 17 patients with TRC) were included. ADC measurements showed no significant difference between both entities. All CBV and ratios(CBV) measurements were significantly higher in patients with recurrent GBM than TRC. A minimum CBV of 8.5, mean CBV of 116.5, maximum CBV of 327 and ratio(CBV) (minimum) of 0.17, ratio(CBV) (mean) of 2.26 and ratio(CBV) (maximum) of 3.82 were computed as optimal cut-off values. By integrating these parameters in a multiparametric model and testing it in an independent patient cohort, 9 of 10 patients, i.e., 90%, were classified correctly. The multiparametric model further improves radiological discrimination of GBM from TRC in comparison to single-parameter approaches and enables reliable identification of recurrent tumors.
CRIS-Team WoS Importer:2022-01-07

A critical comparison between the semisitting and the supine positioning in vestibular schwannoma surgery: Subgroup analysis of a randomized, multicenter trial - Scheller, Christian; Rampp, Stefan; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver; Bischoff, Barbara; Matthies, Cordula; Westermaier, Thomas; Pedro, Maria Teresa; Rohde, Veit; von Eckardstein, Kajetan; et al. (Journal of Neurosurgery, 2020)
OBJECTIVE Patient positioning in vestibular schwannoma (VS) surgery is a matter of ongoing discussion. Factors to consider include preservation of cranial nerve functions, extent of tumor resection, and complications. The objective of this study was to determine the optimal patient positioning in VS surgery. METHODS A subgroup analysis of a randomized, multicenter trial that investigated the efficacy of prophylactic nimodipine in VS surgery was performed to investigate the impact of positioning (semisitting or supine) on extent of resection, functional outcomes, and complications. The data of 97 patients were collected prospectively. All procedures were performed via a retrosigmoid approach. The semisitting position was chosen in 56 patients, whereas 41 patients were treated while supine. RESULTS Complete resection was obtained at a higher percentage in the semisitting as compared to the supine position (93% vs 73%, p = 0.002). Logistic regression analysis revealed significantly better facial nerve function in the early postoperative course in the semisitting group (p = 0.004), particularly concerning severe facial nerve paresis (House-Brackmann grade IV or worse; p = 0.002). One year after surgery, facial nerve function recovered. However, there was still a tendency for better facial nerve function in the semisitting group (p = 0.091). There were no significant differences between groups regarding hearing preservation rates. Venous air embolism with the necessity to terminate surgery occurred in 2 patients in the semisitting position (3.6%). Supplementary analysis with a 2-tailed permutation randomization with 10,000 permutations of treatment choice and a propensity score matching showed either a tendency or significant results for better facial nerve outcomes in the early postoperative course and extent of resection in the semisitting group. CONCLUSIONS Although the results of the various statistical analyses are not uniform, the data indicate better results concerning both a higher rate of complete removal (according to the intraoperative impression of the surgeon) and facial nerve function after a semisitting as compared to the supine position. These advantages may justify the potential higher risk for severe complications of the semisitting position in VS surgery. The choice of positioning has to consider all individual patient parameters and risks carefully.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Acoustic neuroma; Facial nerve; Semisitting position; Supine position; Vestibular schwannoma

Acromegaly Disease Control Maintained After Switching From Injected Somatostatin Receptor Ligands to Oral Paltusotine - Gadelha, Mônica R.; Casagrande, Alessandra; Strasburger, Christian J.; Bidlingmaier, Martin; Snyder, Peter J.; Guitelman, Mirtha A.; Boguszewski, Cesar L.; Buchfelder, Michael; Shimon, Ilan; Raverot, Gerald; Tóth, Miklós; Mezősi, Emese; et al. (Journal of Clinical Endocrinology and Metabolism, 2024)
CONTEXT: Paltusotine is a nonpeptide selective somatostatin receptor 2 agonist in development as once-daily oral treatment for acromegaly. OBJECTIVE: To evaluate the efficacy and safety of paltusotine in the treatment of patients with acromegaly previously controlled with injected somatostatin receptor ligands (SRLs). METHODS: This phase 3, randomized, double-blind, placebo-controlled trial enrolled adults with acromegaly who had IGF-I ≤1.0 times the upper limit of normal (×ULN) while receiving a stable dose of depot octreotide or lanreotide. Patients were switched from injected SRLs and randomized to receive paltusotine or placebo orally for 36 weeks. The primary endpoint was proportion of patients maintaining IGF-I ≤1.0× ULN. Secondary endpoints were change in IGF-I level, change in Acromegaly Symptom Diary score, and maintenance of mean 5-sample GH <1.0 ng/mL. RESULTS: The primary endpoint was met: 83.3% (25/30) of patients receiving paltusotine and 3.6% (1/28) receiving placebo maintained IGF-I ≤1.0× ULN (odds ratio, 126.53; 95% CI, 13.73->999.99; P < .0001). Paltusotine was also superior to placebo for all secondary endpoints: mean (± SE) change in IGF-I of 0.04 ± 0.09× ULN vs 0.83 ± 0.1× ULN (P < .0001); mean (± SE) change in Acromegaly Symptom Diary score of -0.6 ± 1.5 vs 4.6 ± 1.6 (P = .02); mean GH maintained at <1.0 ng/mL in 20/23 (87.0%) vs 5/18 (27.8%) patients (odds ratio, 16.61; 95% CI, 2.86-181.36; P = .0003). The most common adverse events were acromegaly symptoms and gastrointestinal effects characteristic of SRLs. CONCLUSION: Replacement of injected SRLs by once-daily oral paltusotine was effective in maintaining both biochemical and symptom control in patients with acromegaly and was well tolerated.
CRIS-Team Scopus Importer:2025-02-04
Keywords: acromegaly; clinical trial; IGF-I; paltusotine; somatostatin; somatostatin receptor 2

A C-terminal HSP90 inhibitor restores glucocorticoid sensitivity and relieves a mouse allograft model of Cushing disease - Riebold, Mathias; Kozany, Christian; Freiburger, Lee; Sattler, Michael; Buchfelder, Michael; Hausch, Felix; Stalla, Guenter K.; Paez-Pereda, Marcelo (Nature Medicine, 2015)
One function of the glucocorticoid receptor (GR) in corticotroph cells is to suppress the transcription of the gene encoding proopiomelanocortin (POMC), the precursor of the stress hormone adrenocorticotropin (ACTH). Cushing disease is a neuroendocrine condition caused by partially glucocorticoid-resistant corticotroph adenomas that excessively secrete ACTH, which leads to hypercortisolism. Mutations that impair GR function explain glucocorticoid resistance only in sporadic cases. However, the proper folding of GR depends on direct interactions with the chaperone heat shock protein 90 (HSP90, refs. 7,8). We show here that corticotroph adenomas overexpress HSP90 compared to the normal pituitary. N- and C-terminal HSP90 inhibitors act at different steps of the HSP90 catalytic cycle to regulate corticotroph cell proliferation and GR transcriptional activity. C-terminal inhibitors cause the release of mature GR from HSP90, which promotes its exit from the chaperone cycle and potentiates its transcriptional activity in a corticotroph cell line and in primary cultures of human corticotroph adenomas. In an allograft mouse model, the C-terminal HSP90 inhibitor silibinin showed anti-tumorigenic effects, partially reverted hormonal alterations, and alleviated symptoms of Cushing disease. These results suggest that the pathogenesis of Cushing disease caused by overexpression of heat shock proteins and consequently misregulated GR sensitivity may be overcome pharmacologically with an appropriate HSP90 inhibitor.
EVALuna2:22853

Activation and regulation of endogenous retroviral genes in the human pituitary gland and related endocrine tumours - Buslei, R.; Strissel, Pamela; Henke, Christine; Schey, Regina; Lang, Nadine; Ruebner, M.; Stolt, Claus; Fabry, Ben; Buchfelder, Michael; Strick, Reiner (Neuropathology and Applied Neurobiology, 2015)
Adenohypophysis (AH) hormone-producing cells represent the origin of diverse groups of pituitary adenomas (PA). Deregulation of hypothalamic hormone receptors, growth factors and cAMP signalling have been implicated in the aetiology of PA. Endogenous retroviruses (ERVs) are derived from past exogenous retroviral infections and represent more than 8% of the human genome. Some ERV genes encode open reading frames and produce functional proteins, for example, the ERVW-1 envelope gene Syncytin-1, essential for placentogenesis, but also deregulated in human tumours. Data concerning ERV expression in the AH and related endocrine tumours are missing.Syncytin-1 protein was analysed in normal AH (n = 15) and compared with five PA subtypes (n = 117) by immunohistochemistry. Absolute gene expression of 20 ERV functional envelope genes and ERVW-5 gag was measured. PA tissues were examined for Syncytin-1 and the cAMP signalling marker phospho-CREB-Ser133 using immunohistochemistry. Isolated primary human PA cells were treated with different hormones. Murine embryonic and adult pituitary gland ERV expressions were compared with human AH.Syncytin-1 protein colocalized with corticotropic cells of AH. In contrast, all PA demonstrated significant Syncytin-1 protein overexpression, supporting deregulation. All other ERV genes showed significant up-regulations in different PA subtypes. Phospho-CREB-Ser133 and Syncytin-1 colocalized in PA cells. Cultivated primary PA cells with ACTH or CRH induced their respective receptors and ERV genes. Syncytin-A/-B, murine orthologues to human Syncytin-1/-2, localized to embryonic and adult pituitary glands demonstrating functional mammalian conservation.Deregulated ERV genes may contribute to PA development via cAMP signalling.
EVALuna2:4955

Adamantinomatous and papillary craniopharyngiomas are characterized by distinct epigenomic as well as mutational and transcriptomic profiles - Hoelsken, Annett; Sill, Martin; Merkle, Jessica; Schweizer, Leonille; Buchfelder, Michael; Flitsch, Joerg; Fahlbusch, Rudolf; Metzler, Markus; Kool, Marcel; Pfister, Stefan M.; Von Deimling, Andreas; Capper, David; et al. (Acta Neuropathologica Communications, 2016)
Craniopharyngiomas (CP) are rare epithelial tumors of the sellar region. Two subtypes, adamantinomatous (adaCP) and papillary CP (papCP), were previously identified based on histomorphological and epidemiological aspects. Recent data indicates that both variants are defined by specific genetic alterations, and influenced by distinct molecular pathways and particular origins. The fact that CP is an uncommon tumor entity renders studies on large cohorts difficult and exceptional. In order to achieve further insights distinguishing CP variants, we conducted whole genome methylation (450 k array) and microarray-based gene expression studies in addition to CTNNB1 and BRAF mutation analysis using a comprehensive cohort of 80 adaCP and 35 papCP.BRAF V600E mutations were solely found in the papCP subgroup and were not detectable in adaCP samples. In contrast, CTNNB1 mutations were exclusively detected in adaCP. The methylome fingerprints assigned DNA specimens to entity-specific groups (papCP (n = 18); adaCP (n = 25)) matching perfectly with histology-based diagnosis, suggesting that they represent truly distinct biological entities. However, we were not able to detect within the adaCP group (including 11 pediatric and 14 adult cases) a significant difference in methylation signature by age. Integrative comparison of the papCP with the adaCP group based on differential gene expression and methylation revealed a distinct upregulation of Wnt- and SHH signaling pathway genes in adaCP.AdaCP and papCP thus represent distinct tumor subtypes that harbor mutually exclusive gene mutations and methylation patterns, further reflected in differences in gene expression. This study demonstrates that DNA methylation analyses are an additional method to classify CP into subtypes, and implicates a role of epigenetic mechanisms in the genesis of the respective CP variants. Detection of tumor-specific signaling pathway activation enables the possibility of target-oriented intervention.
EVALuna2:7314

Adamantinomatous craniopharyngiomas express tumor stem cell markers in cells with activated Wnt signaling: further evidence for the existence of a tumor stem cell niche? - Hölsken, Annett; Stache, Christina; Schlaffer, Sven-Martin; Flitsch, Joerg; Fahlbusch, Rudolf; Buchfelder, Michael; Buslei, Rolf (Pituitary, 2014)
Early disease onset, clinical manifestation, histomorphology, and increased tendency to relapse distinguish the adamantinomatous craniopharyngioma (adaCP) from the more favorable papillary variant (papCP). A molecular hallmark of adaCP is the activated Wnt signaling pathway indicated by nuclear ?-catenin accumulation in a subset of tumor cells. A mouse model recently illustrated that these cells are the driving force in tumorigenesis of adaCP. This observation and the peculiar growth pattern points to the existence of a specific tumor stem cell (TSC) population in human CP.To prove this hypothesis, the TSC markers CD133 (Prominin1) and CD44 were examined in papCP (n = 8) and adaCP (n = 25) on mRNA level using quantitative real time PCR of total tumor RNA. Furthermore, we investigated protein expression performing immunohistochemical analyses of formalin-fixed paraffin embedded tumor samples.PapCP revealed a homogenous CD44 expression pattern predominantly at the cell membrane, whereas CD133 labeling was hardly detectable. In adaCP, on the other hand all markers were consistently and predominantly co-expressed in nuclear ?-catenin accumulating cell clusters, which was confirmed by double immunofluorescence staining. Overall expression of CD44 was significantly decreased in adaCP versus papCP, whereas CD133 showed significantly higher protein and mRNA levels in adaCP.Our results indicate tumor stem cell-like characteristics of ?-catenin accumulating cell clusters in adaCP, which may represent a tumor stem cell niche and might contribute to tumor recurrence. The potential impact of these special cell groups in regard to future CP management, including postoperative follow-up and additional treatment remains to be explored.
EVALuna2:7205

Adaptive Immune Response to and Survival Effect of Temozolomide- and Valproic Acid-induced Autophagy in Glioblastoma - Proske, Judith; Walter, Lisa; Bumes, Elisabeth; Hutterer, Markus; Vollmann-Zwerenz, Arabel; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai E.; Seliger, Corinna; Hau, Peter; Uhl, Martin; Walter, Lisa (Anticancer Research, 2016)
The combination of radiotherapy, temozolomide and valproic acid (VPA) has shown some promise in retrospective analyses of patients with glioblastoma, although their mechanisms of action remain unknown.We investigated the in vitro and in vivo effects of pretreating glioma cells with temozolomide and VPA as an immunization strategy to boost an adaptive immune response in a syngeneic mouse model.Temozolomide and VPA induced autophagy in GL261 glioma cells, and caused tumor antigen-specific T-cells to become activated effector T-cells. Mice with a pre-existing glioma showed no improvement in clinical outcome when immunized with temozolomide- and VPA-treated glioma cells.Although temozolomide and VPA treatment of glioma cells can boost the adaptive immune response, in the context of a vaccine therapy, additional factors are necessary to eradicate the tumor and improve survival.
EVALuna2:22525

A deep learning-based histopathology classifier for Focal Cortical Dysplasia - Vorndran, Jörg; Neuner, Christoph; Coras, Roland; Hoffmann, Lucas; Geffers, Simon; Honke, Jonas; Herms, Jochen; Roeber, Sigrun; Hamer, Hajo; Brandner, Sebastian; Hartlieb, Till; Pieper, Tom; et al. (Neural Computing & Applications, 2023)
A light microscopy-based histopathology diagnosis of human brain specimens obtained from epilepsy surgery remains the gold standard to confirm the underlying cause of a patient’s focal epilepsy and further inform postsurgical patient management. The differential diagnosis of neocortical specimens in the realm of epilepsy surgery remains, however, challenging. Herein, we developed an open access, deep learning-based classifier to histopathologically assess whole slide microscopy images (WSI) and to automatically recognize various subtypes of Focal Cortical Dysplasia (FCD), according to the ILAE consensus classification update of 2022. We trained a convolutional neuronal network (CNN) with fully digitalized WSI of hematoxylin–eosin stainings obtained from 125 patients covering the spectrum of mild malformation of cortical development (mMCD), mMCD with oligodendroglial hyperplasia in epilepsy (MOGHE), FCD ILAE Type 1a, 2a and 2b using 414 formalin-fixed and paraffin-embedded archival tissue blocks. An additional series of 198 postmortem tissue blocks from 59 patients without neurological disorders served as control to train the CNN for homotypic frontal, temporal and occipital areas and heterotypic Brodmann areas 4 and 17, entorhinal cortex and dentate gyrus. Special stains and immunohistochemical reactions were used to comprehensively annotate the region of interest. We then programmed a novel tile extraction pipeline and graphical dashboard to visualize all areas on the WSI recognized by the CNN. Our deep learning-based classifier is able to compute 1000 × 1000 µm large tiles and recognizes 25 anatomical regions and FCD categories with an accuracy of 98.8% (F1 score = 0.82). Microscopic review of regions predicted by the network confirmed these results. This deep learning-based classifier will be made available as online web application to support the differential histopathology diagnosis in neocortical human brain specimens obtained from epilepsy surgery. It will also serve as blueprint to build a digital histopathology slide suite addressing all major brain diseases encountered in patients with surgically amenable focal epilepsy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Classification; Convolutional neuronal network; Cortex; Deep learning; Digital pathology; Epilepsy; FCD1; FCD2; mMCD; MOGHE

A direct spinal cord–computer interface enables the control of the paralysed hand in spinal cord injury - Souza de Oliveira, Daniela; Ponfick, Matthias; Braun, Dominik; Oßwald, Marius; Sierotowicz, Marek; Chatterjee, Satyaki; Weber, Douglas J.; Eskofier, Björn; Castellini, Claudio; Farina, Dario; Kinfe, Thomas Mehari; Del Vecchio, Alessandro (Brain, 2024)
The paralysis of the muscles controlling the hand dramatically limits the quality of life of individuals living with spinal cord injury (SCI). Here, with a non-invasive neural interface, we demonstrate that eight motor complete SCI individuals (C5-C6) are still able to task-modulate in real-time the activity of populations of spinal motor neurons with residual neural pathways. In all SCI participants tested, we identified groups of motor units under voluntary control that encoded various hand movements. The motor unit discharges were mapped into more than 10 degrees of freedom, ranging from grasping to individual hand-digit flexion and extension. We then mapped the neural dynamics into a real-time controlled virtual hand. The SCI participants were able to match the cue hand posture by proportionally controlling four degrees of freedom (opening and closing the hand and index flexion/extension). These results demonstrate that wearable muscle sensors provide access to spared motor neurons that are fully under voluntary control in complete cervical SCI individuals. This non-invasive neural interface allows the investigation of motor neuron changes after the injury and has the potential to promote movement restoration when integrated with assistive devices.<br
Keywords: spinal cord injury; motor neuron; motor unit; high density surface electromyography; neural interface

Advanced MRI in neuro-oncology: Can we proceed without inclusion of energy metabolism? - Stadlbauer, Andreas; Buchfelder, Michael; Dörfler, Arnd; Oberndorfer, Stefan (Oncotarget, 2019)
CRIS-Team Scopus Importer:2019-07-09
Keywords: Glioblastoma; Intratumoral heterogeneity; Magnetic resonance imaging; Tumor microenvironment; Warburg effect

Advantages of magnetoencephalography, neuronavigation and intraoperative MRI in epilepsy surgery re-operations - Shawarba, Julia; Kaspar, Burkhard; Rampp, Stefan; Winter, Fabian; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2021)
Objective: Management of patients after failed epilepsy surgery is still challenging. Advanced diagnostic and intraoperative tools including magneto-encephalography (MEG) as well as neuronavigation and intraoperative magnetic resonance imaging (iopMRI) may contribute to a better postoperative seizure outcome in this patient group. Methods: We retrospectively analyzed consecutive patients after reoperation of failed epilepsy surgery for medically refractory epilepsy at the University of Erlangen between 1988 and 2017. Inclusion criteria for patients were available MEG, neuronavigation and iopMRI data. The Engel scale was used to categorize seizure outcome. Results: We report on 27 consecutive patients (13 female/14 male mean age at first surgery 29.4 years) who had operative revision of the first resection after failed epilepsy surgery. An improved seizure outcome postoperatively was observed in 78% of patients (p < 0.001) with 55% seizure free (Engel I) patients after a mean follow-up time of 4.9 years. In detail, 80% of lesional cases were seizure free compared to 59% of MRI negative patients. Localizing MEG spike activity in the vicinity of the first resection cavity was present in 12 of 27 patients (44%) corresponding to 83% (10/12) of MEG localizing spike patients having advanced seizure outcome after operative revision. Conclusion: Re-operation after failed surgery in refractory epilepsy may lead to a better seizure outcome in the majority of patients. Preoperative MEG may support the decision for surgery and may facilitate targeting epileptogenic tissue for re-resection by employing navigation and iopMR imaging.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Failed epilepsy surgery; intraoperative MR imaging; MEG; neuronavigation; reoperation; seizure outcome

A Frameless Stereotactic Implantation Technique for Depth Electrodes in Refractory Epilepsy Using Intraoperative Magnetic Resonance Imaging - Roessler, Karl; Sommer, Bjoern; Merkel, Andreas; Rampp, Stefan; Gollwitzer, Stephanie; Hamer, Hajo; Buchfelder, Michael (World Neurosurgery, 2016)
Various complex techniques for depth electrode insertion in refractory epilepsy using preoperative imaging have been investigated. We evaluated a simple, accurate, cost-effective, and timesaving method using intraoperative magnetic resonance imaging (MRI).A neuronavigation-guided insertion tube attached to bone facilitated the placement of stereotactic percutaneous drill holes, bolt implantation, and frameless stereotactic insertion of depth electrodes. Image registration was carried out by head coil fiducials with trajectory planning and intraoperative electrode correction.In 6 patients with refractory epilepsy (3 women and 3 men; mean age, 30.0 years; range, 20-37 years), 58 depth electrodes (9-11 per patient) were placed. The mean length of the inserted electrodes was 37.3 mm ± 8.8 (mean ± SD) (range, 22.1-84.4 mm). The overall target point accuracy was 3.2 mm ± 2.2 (range, 0-8.6 mm), which was significantly different from the overall entry point accuracy of 1.4 mm ± 1.2 (P < 0.0001). All electrodes functioned perfectly, enabling high-quality stereo-electroencephalography recordings over a period of 7.3 days ± 0.5 (range, 7-8 days). The mean implantation time for 9-11 electrodes per patient was 115 minutes ± 36.3 (range, 75-160 minutes; 12 minutes for 1 electrode on average) including the intraoperative MRI (T1 three-dimensional magnetization-prepared rapid acquisition gradient echo, T2, and diffusion tensor imaging). There was no hemorrhage, infection, or neurologic deficit related to the procedure.Our frameless technique of depth electrode insertion using intraoperative MRI guidance is an accurate, reliable, cost-effective, and timesaving method for stereo-electroencephalography.
EVALuna2:22491

Afterdischarges elicited by cortical electric stimulation in humans: When do they occur and what do they mean? - Gollwitzer, Stephanie; Hopfengaertner, Ruediger; Roessler, Karl; Müller, Tamara; Olmes, David Gerhard; Lang, Johannes; Koehn, Julia; Onugoren, Muejgan Dogan; Heyne, Jana; Schwab, Stefan; Hamer, Hajo (Epilepsy and Behavior, 2018)
INTRODUCTION: Afterdischarges (ADs) are a common and unwanted byproduct of direct cortical stimulation during invasive electroencephalography (EEG) recordings. Brief pulse stimulation (BPS) can sometimes terminate ADs. This study investigated AD characteristics and their relevance for emergence of stimulation seizures. In addition, AD response to BPS was analyzed. MATERIAL AND METHODS: Invasive EEG recordings including mapping with direct cortical stimulation in patients with refractory epilepsy at the Erlangen Epilepsy Center were retrospectively reviewed. Afterdischarge defined as stimulation-induced rhythmic epileptiform discharges of more than a two-second duration were analyzed regarding incidence, localization, duration, propagation pattern, morphology, and seizure emergence. In addition, the influence of AD characteristics and stimulation settings on BPS success rate was studied. RESULTS: A number of 4261 stimulation trials in 20 patients were investigated. Afterdischarge occurred in 518 trials (14.2%) and lasted 12.4 s (standard deviation [SD]: 8.6 s) on average. We elicited ADs in the seizure onset zone (SOZ) (n = 64; 19.4%), the irritative zone (n = 105, 20.0%), and outside the irritative area (n = 222, 12.5%). Rhythmic spikes (30.5%) and spike-wave complexes (30.3%) represented predominant morphologies. Afterdischarge morphology in the SOZ and hippocampus differed from other areas with polyspikes and sequential spikes being the most common types there (p = 0.0005; p < 0.0001 respectively). Hippocampal ADs were particularly frequent (n = 50, 38.2%) and long-lasting (mean: 16.6, SD: 8.3 s). Brief pulse stimulation was applied in 18.1% of the AD trials (n = 94) and was successful in 37.4% (n = 40). Success rates were highest when BPS was delivered within 9.5 s (p = 0.0048) and in ADs of spike-wave morphology (p = 0.0004). Fifteen clinical seizures emerged from ADs (3.55%), mostly evolving from sequential spikes. Afterdischarges in patients with stimulation seizures appeared more widespread (p < 0.0001) and lasted longer (mean duration 7.0 s) than in those without (mean duration 21.0 s, p = 0.0054). CONCLUSION: Afterdischarges appear in the epileptogenic and nonepileptogenic cortex. Duration and propagation patterns can help to quantify the risk of stimulation seizures, with sequential spikes being most susceptible to seizure elucidation. The hippocampus is highly sensitive to AD release. Brief pulse stimulation is a safe and efficacious way to terminate ADs, especially when delivered quickly after AD onset.
EVALuna2:34938

Age-dependent increase of perineuronal nets in the human hippocampus and precocious aging in epilepsy - Lehner, Annika; Hoffmann, Lucas; Rampp, Stefan; Coras, Roland; Paulsen, Friedrich; Frischknecht, Renato; Hamer, Hajo; Walther, Katrin; Brandner, Sebastian; Hofer, Wiebke; Pieper, Tom; Reisch, Lea Marie; et al. (Epilepsia Open, 2024)
Objective: Perineuronal nets (PNN) are specialized extracellular matrix (ECM) components of the central nervous system, frequently accumulating at the surface of inhibitory GABAergic interneurons. While an altered distribution of PNN has been observed in neurological disorders including Alzheimer's disease, schizophrenia and epilepsy, their anatomical distribution also changes during physiological brain maturation and aging. Such an age-dependent shift was experimentally associated also with hippocampal engram formation during brain maturation. Our aim was to histopathologically assess PNN in the hippocampus of adult and pediatric patients with temporal lobe epilepsy (TLE) compared to age-matched post-mortem control subjects and to compare PNN-related changes with memory impairment observed in our patient cohort. Methods: Sixty-six formalin-fixed and paraffin-embedded tissue specimens of the human hippocampus were retrieved from the European Epilepsy Brain Bank. Twenty-nine patients had histopathologically confirmed hippocampal sclerosis (HS), and eleven patients suffered from TLE without HS. PNN were immunohistochemically visualized using an antibody directed against aggrecan and manually counted from hippocampus subfields and the subiculum. Results: PNN density increased with age in both human controls and TLE patients. However, their density was significantly higher in all HS patients compared to age-matched controls. Intriguingly, TLE patients presented presurgically with better memory when their hippocampal PNN density was higher (p < 0.05). Significance: Our results were compatible with age-dependent ECM specialization in the human hippocampus and its precocious aging in the epileptic condition. These observations confirm recent experimental animal models and also support the notion that PNN play a role in memory formation in the human brain. Plain Language Summary: “Perineuronal nets” (PNN) are a specialized compartment of the extracellular matrix (ECM), especially surrounding highly active neurons of the mammalian brain. There is evidence that PNN play a role in memory formation, brain maturation, and in some pathologies like Alzheimer's disease, schizophrenia or epilepsy. In this study, we investigated the role of PNN in patients suffering from drug-resistant focal epilepsy compared to controls. We found that with increasing age, more neurons are surrounded by PNN. Similarly, all epilepsy patients but especially patients with better memory performance also had more PNN. This study raises further interest in studying ECM molecules in the human brain under physiological and pathophysiological conditions.
CRIS-Team Scopus Importer:2024-06-21
Keywords: brain; extracellular matrix; hippocampal sclerosis; maturation; neuropathology

A Generalized Framework for the Study of Spinal Motor Neurons Controlling the Human Hand During Dynamic Movements - Cakici, Andre L.; Oßwald, Marius; Souza de Oliveira, Daniela; Braun, Dominik; Simpetru, Raul C.; Kinfe, Thomas Mehari; Eskofier, Björn; Del Vecchio, Alessandro (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2022)
The human hand possesses a large number of degrees of freedom. Hand dexterity is encoded by the discharge times of spinal motor units (MUs). Most of our knowledge on the neural control of movement is based on the discharge times of MUs during isometric contractions. Here we designed a noninvasive framework to study spinal motor neurons during dynamic hand movements with the aim to understand the neural control of MUs during sinusoidal hand digit flexion and extension at different rates of force development. The framework included 320 high-density surface EMG electrodes placed on the forearm muscles, with markerless 3D hand kinematics extracted with deep learning, and a realistic virtual hand that displayed the motor tasks. The movements included flexion and extension of individual hand digits at two different speeds (0.5 Hz and 1.5 Hz) for 40 seconds. We found on average 4.7-1.7 MUs across participants and tasks. Most MUs showed a biphasic pattern closely mirroring the flexion and extension kinematics. Indeed, a factor analysis method (non-negative matrix factorization) was able to learn the two components (flexion/extension) with high accuracy at the individual MU level (R=0.87-0.12). Although most MUs were highly correlated with either flexion or extension movements, there was a smaller proportion of MUs that was not task-modulated and controlled by a different neural module (7.1% of all MUs with R < 0.3). This work shows a noninvasive visually guided framework to study motor neurons controlling the movement of the hand in human participants during dynamic hand digit movements.
CRIS-Team Scopus Importer:2022-10-14

A Generalized Framework for the Study of Spinal Motor Neurons Controlling the Human Hand During Dynamic Movements - Cakici, Andre; Oßwald, Marius; Souza de Oliveira, Daniela; Braun, Dominik; Simpetru, Raul; Kinfe, Thomas Mehari; Eskofier, Björn; Del Vecchio, Alessandro (44th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBC 2022, 2022)
The human hand possesses a large number of degrees of freedom. Hand dexterity is encoded by the discharge times of spinal motor units (MUs). Most of our knowledge on the neural control of movement is based on the discharge times of MUs during isometric contractions. Here we designed a noninvasive framework to study spinal motor neurons during dynamic hand movements with the aim to understand the neural control of MUs during sinusoidal hand digit flexion and extension at different rates of force development. The framework included 320 high-density surface EMG electrodes placed on the forearm muscles, with markerless 3D hand kinematics extracted with deep learning, and a realistic virtual hand that displayed the motor tasks. The movements included flexion and extension of individual hand digits at two different speeds (0.5 Hz and 1.5 Hz) for 40 seconds. We found on average 4.7 +- 1.7 MUs across participants and tasks. Most MUs showed a biphasic pattern closely mirroring the flexion and extension kinematics. Indeed, a factor analysis method (non-negative matrix factorization) was able to learn the two components (flexion/extension) with high accuracy at the individual MU level (R = 0.87 +- 0.12). Although most MUs were highly correlated with either flexion or extension movements, there was a smaller proportion of MUs that was not task-modulated and controlled by a different neural module (7.1% of all MUs with R < 0.3). This work shows a noninvasive visually guided framework to study motor neurons controlling the movement of the hand in human participants during dynamic hand digit movements.

Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Aggressive pituitary neuroendocrine tumors: current practices, controversies, and perspectives, on behalf of the EANS skull base section - Ng, Sam; Messerer, Mahmoud; Engelhardt, Julien; Bruneau, Michael; Cornelius, Jan Frederick; Cavallo, Luigi Maria; Cossu, Giulia; Froelich, Sebastien; Meling, Torstein R.; Paraskevopoulos, Dimitrios; Schroeder, Henry W. S.; Tatagiba, Marcos; et al. (Acta Neurochirurgica, 2021)
Aggressive pituitary neuroendocrine tumors (APT) account for 10% of pituitary tumors. Their management is a rapidly evolving field of clinical research and has led pituitary teams to shift toward a neuro-oncological-like approach. The new terminology “Pituitary neuroendocrine tumors” (PitNet) that was recently proposed to replace “pituitary adenomas” reflects this change of paradigm. In this narrative review, we aim to provide a state of the art of actual knowledge, controversies, and recommendations in the management of APT. We propose an overview of current prognostic markers, including the recent five-tiered clinicopathological classification. We further establish and discuss the following recommendations from a neurosurgical perspective: (i) surgery and multi-staged surgeries (without or with parasellar resection in symptomatic patients) should be discussed at each stage of the disease, because it may potentialize adjuvant medical therapies; (ii) temozolomide is effective in most patients, although 30% of patients are non-responders and the optimal timeline to initiate and interrupt this treatment remains questionable; (iii) some patients with selected clinicopathological profiles may benefit from an earlier local radiotherapy and/or chemotherapy; (iv) novel therapies such as VEGF-targeted therapies and anti-CTLA-4/anti-PD1 immunotherapies are promising and should be discussed as 2nd or 3rd line of treatment. Finally, whether neurosurgeons have to operate on “pituitary adenomas” or “PitNets,” their role and expertise remain crucial at each stage of the disease, prompting our community to deal with evolving concepts and therapeutic resources.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Aggressive pituitary adenoma; Atypical pituitary adenoma; Endocrine tumors; Neuro-oncology; PitNet; Pituitary carcinoma; Radiotherapy; Temozolomide; Transsphenoidal surgery

A guideline for head volume conductor modeling in EEG and MEG - Vorwerk, Johannes; Cho, Jae-Hyun; Rampp, Stefan; Hamer, Hajo; Knoesche, Thomas R.; Wolters, Carsten H. (NeuroImage, 2014)
For accurate EEG/MEG source analysis it is necessary to model the head volume conductor as realistic as possible. This includes the distinction of the different conductive compartments in the human head. In this study, we investigated the influence of modeling/not modeling the conductive compartments skull spongiosa, skull compacta, cerebrospinal fluid (CSF), gray matter, and white matter and of the inclusion of white matter anisotropy on the EEG/MEG forward solution. Therefore, we created a highly realistic 6-compartment head model with white matter anisotropy and used a state-of-the-art finite element approach. Starting from a 3-compartment scenario (skin, skull, and brain), we subsequently refined our head model by distinguishing one further of the above-mentioned compartments. For each of the generated five head models, we measured the effect on the signal topography and signal magnitude both in relation to a highly resolved reference model and to the model generated in the previous refinement step. We evaluated the results of these simulations using a variety of visualization methods, allowing us to gain a general overview of effect strength, of the most important source parameters triggering these effects, and of the most affected brain regions. Thereby, starting from the 3-compartment approach, we identified the most important additional refinement steps in head volume conductor modeling. We were able to show that the inclusion of the highly conductive CSF compartment, whose conductivity value is well known, has the strongest influence on both signal topography and magnitude in both modalities. We found the effect of gray/white matter distinction to be nearly as big as that of the CSF inclusion, and for both of these steps we identified a clear pattern in the spatial distribution of effects. In comparison to these two steps, the introduction of white matter anisotropy led to a clearly weaker, but still strong, effect. Finally, the distinction between skull spongiosa and compacta caused the weakest effects in both modalities when using an optimized conductivity value for the homogenized compartment. We conclude that it is highly recommendable to include the CSF and distinguish between gray and white matter in head volume conductor modeling. Especially for the MEG, the modeling of skull spongiosa and compacta might be neglected due to the weak effects; the simplification of not modeling white matter anisotropy is admissible considering the complexity and current limitations of the underlying modeling approach.
EVALuna2:22293

Alpha power decrease in quantitative EEG detects development of cerebral infarction after subarachnoid hemorrhage early - Müller, Tamara; Gollwitzer, Stephanie; Hopfengartner, Ruediger; Rampp, Stefan; Lang, Johannes; Stritzelberger, Jenny; Madzar, Dominik; Reindl, Caroline; Sprügel, Maximilian; Onugoren, Muejgan Dogan; Mühlen, Iris; Kuramatsu, Joji; et al. (Clinical Neurophysiology, 2021)
Objective: In subarachnoid hemorrhage (SAH), transcranial Doppler/color-coded-duplex sonography (TCD/TCCS) is used to detect delayed cerebral ischemia (DCI). In previous studies, quantitative electroencephalography (qEEG) also predicted imminent DCI. This study aimed to compare and analyse the ability of qEEG and TCD/TCCS to early identify patients who will develop later manifest cerebral infarction. Methods: We analysed cohorts of two previous qEEG studies. Continuous six-channel-EEG with artefact rejection and a detrending procedure was applied. Alpha power decline of ≥ 40% for ≥ 5 hours compared to a 6-hour-baseline was defined as significant EEG event. Median reduction and duration of alpha power decrease in each channel was determined. Vasospasm was diagnosed by TCD/TCCS, identifying the maximum frequency and days of vasospasm in each territory. Results: 34 patients were included (17 male, mean age 56 ± 11 years, Hunt and Hess grade: I–V, cerebral infarction: 9). Maximum frequencies in TCD/TCCS and alpha power reduction in qEEG were correlated (r = 0.43; p = 0.015). Patients with and without infarction significantly differed in qEEG parameters (maximum alpha power decrease: 78% vs 64%, p = 0.019; summed hours of alpha power decline: 236 hours vs 39 hours, p = 0.006) but showed no significant differences in TCD/TCCS parameters. Conclusions: There was a moderate correlation of TCD/TCCS frequencies and qEEG alpha power reduction but only qEEG differentiated between patients with and without cerebral infarction. Significance: qEEG represents a non-invasive, continuous tool to identify patients at risk of cerebral infarction.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Delayed cerebral ischemia; Quantitative EEG; Subarachnoid hemorrhage; Vasospasm

Amyloid‐β processing in aged s100b transgenic mice is sex dependent - Wartchow, Krista Minéia; Rodrigues, Leticia; Swierzy, Izabela; Buchfelder, Michael; de Souza, Diogo Onofre; Gonçalves, Carlos Alberto; Kleindienst, Andrea (International Journal of Molecular Sciences, 2021)
(1) Background: Calcium‐binding protein S100B is involved in neuroregeneration but has also been associated with neurodegeneration. These contrasting effects may result from concentration or duration of exposure. We investigated the effect of long‐term increased S100B levels on am-yloid‐β processing in one‐year‐old transgenic (tg) mice with 12 copies of the murine S100B gene with specific consideration of sex and specific brain regions. (2) Methods: S100B and amyloid‐β 42 (Aβ42) were quantified in serum, cerebrospinal fluid (CSF), adipose tissue, and different brain regions by ELISA in wild‐type (wt) and S100Btg mice (each n = 7 per group). Thioflavin T (ThT) and Aβ immunostaining were performed for visualization of Aβ deposition. (3) Results: S100B in serum, CSF, and brain was significantly increased in S100Btg mice of both sexes. Aβ42 was significantly increased in the hippocampus of male S100Btg mice (p = 0.0075), and the frontal cortex of female S100Btg mice (p = 0.0262). ThT and Aβ immunostaining demonstrated Aβ deposition in different brain regions in S100Btg mice of both sexes and female wt. (4) Conclusion: Our data validate this experimental model for studying the role of S100B in neurodegeneration and indicate that Aβ processing is sex‐dependent and brain region‐specific, which deserves further investigation of signaling pathways and behavioral responses.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Alzheimer’s disease; Amyloid‐β processing; Neurodegeneration; S100B; Transgenic mice

Analysis of 1386 epileptogenic brain lesions reveals association with DYRK1A and EGFR - Boßelmann, Christian M.; Leu, Costin; Brünger, Tobias; Hoffmann, Lucas; Baldassari, Sara; Chipaux, Mathilde; Coras, Roland; Kobow, Katja; Hamer, Hajo; Delev, Daniel; Rössler, Karl; Bien, Christian G.; et al. (Nature Communications, 2024)
Lesional focal epilepsy (LFE) is a common and severe seizure disorder caused by epileptogenic lesions, including malformations of cortical development (MCD) and low-grade epilepsy-associated tumors (LEAT). Understanding the genetic etiology of these lesions can inform medical and surgical treatment. We conducted a somatic variant enrichment mega-analysis in brain tissue from 1386 individuals who underwent epilepsy surgery, including 599 previously unpublished individuals with ultra-deep ( > 1600x) targeted panel sequencing. Here we confirm four known associations (BRAF, SLC35A2, MTOR, PTPN11), support eight associations without prior statistical support (FGFR1, PIK3CA, AKT3, NF1, PTEN, RHEB, KRAS, NRAS), and identify novel associations for two genes, DYRK1A and EGFR. Both novel genes show specific histopathological phenotypes, interact with LFE genes and pathways, and may represent promising candidates as biomarkers and potentially druggable target

Analysis of continuous neuronal activity evoked by natural speech with computational corpus linguistics methods - Schilling, Achim; Tomasello, Rosario; Henningsen-Schomers, Malte R.; Zankl, Alexandra; Surendra, Kishore; Haller, Martin; Karl, Valerie; Uhrig, Peter; Maier, Andreas; Krauß, Patrick (Language, Cognition and Neuroscience, 2020)
In the field of neurobiology of language, neuroimaging studies are generally based on stimulation paradigms consisting of at least two different conditions. Designing those paradigms can be very time-consuming and this traditional approach is necessarily data-limited. In contrast, in computational and corpus linguistics, analyses are often based on large text corpora, which allow a vast variety of hypotheses to be tested by repeatedly re-evaluating the data set. Furthermore, text corpora also allow exploratory data analysis in order to generate new hypotheses. By drawing on the advantages of both fields, neuroimaging and computational corpus linguistics, we here present a unified approach combining continuous natural speech and MEG to generate a corpus of speech-evoked neuronal activity.
CRIS-Team Scopus Importer:2020-08-21
Keywords: computational corpus linguistics; MEG/EEG; natural language processing (NLP); naturalistic continuous speech stimuli; neurobiology of language

Anatomical location of the vocal cords in relation to cervical vertebrae: A new predictor of difficult laryngoscopy? - Münster, Tino; Hoffmann, Melanie; Schlaffer, Sven-Martin; Ihmsen, Harald; Schmitt, Heike; Tzabazis, Alexander (European Journal of Anaesthesiology, 2016)
Several anatomical factors, such as prognathism, sex, short thyromental distance and others are known to make direct laryngoscopy difficult.We investigated the hypothesis that the anatomical position of the vocal cords in relation to the cervical vertebrae correlates with difficult laryngoscopy. Existing MRI was used to identify the position of the vocal cords relative to the cervical spine in patients with and without difficult laryngoscopy.Observational study with adaptive enrichment.University hospital.A total of 142 adult patients, 91 with easy (Cormack-Lehane class 1 or 2) and 51 with difficult (Cormack-Lehane class 3 or 4) laryngoscopy.Position of the vocal cords relative to cervical vertebrae in patients with easy vs. difficult laryngoscopy.In patients with difficult laryngoscopy, we found a higher incidence of cranial position of the vocal cords in relation to the cervical spine compared with patients with easy laryngoscopy (P < 0.001).Anaesthesiologists should take advantage of existing imaging of the cervical spine when assessing the patient's airway.
EVALuna2:16726

Anatomy and microsurgical relevance of the outer arachnoid envelope around the olfactory bulb based on endoscopic cadaveric observations - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Adib, Sasan Darius; Barany, Laszlo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background: Surgical approaches to the anterior cranial fossa have great risk of damaging the olfactory tract and bulb. The goal of this study was to describe the outer arachnoid envelope around the olfactory bulb which plays significant role in the approach-related injury of the nerve. Material and Methods: A total of 20 fresh human cadaveric heads were examined as a following: 5 cadaveric heads were used to describe a gross overview of the topographic anatomy of the outer arachnoid cover of the olfactory bulb. In 15 cadaveric heads endoscopic surgical approaches were performed to examine the in situ undisrupted anatomy of the outer arachnoid around the olfactory bulb. Four cadaveric heads were used for lateral subfrontal approach, 5 heads for medial subfrontal, 3 heads for median subfrontal approach and 3 heads for anterior interhemispheric approach. Results: The outer arachnoid membrane of the frontal lobe attaches the olfactory bulb strongly to the above lying olfactory sulcus. Only the most rostral portion of the olfactory bulb became slightly detached from the frontal lobe. The outer arachnoid forms a decent protrusion around the tip of the olfactory bulbs. The fila olfactoria have their own outer arachnoid cover as a continuation of the same layer of the olfactory bulb. The effect of brain retraction and manipulation forces on the olfactory bulb and the role of the here located arachnoid membranes were visually analysed and described in detail through the performed four different neurosurgical approaches. Conclusion: The results of our observations provide important anatomical details for the preservation of smelling during neurosurgical procedures.
CRIS-Team Scopus Importer:2024-12-16
Keywords: arachnoid membranes; endoscopic anatomy; microsurgical anatomy; olfactory bulb

A new functional classification system (FGA/B) with prognostic value for glioma patients - Friedlein, Katharina; Bozhkov, Yavor; Hore, Nirjhar; Merkel, Andreas; Sommer, Bjoern; Brandner, Sebastian; Buchfelder, Michael; Savaskan, Nicolai E.; Eyüpoglu, Ilker Yasin (Scientific Reports, 2015)
Despite advances in multimodal treatments, malignant gliomas remain characterized by a short survival time. Surgical treatment is accepted to be the first line of therapy, with recent studies revealing that maximal possible tumor reduction exerts significant impact on patient outcome. Consideration of tumor localization in relation to functionally eloquent brain areas has been gaining increasing importance. Despite existing assessment methods, the availability of a simple but reliable preoperative grading based on functional data would therefore prove to be indispensable for the prediction of postoperative outcome and hence for overall survival in glioma patients. We performed a clinical investigation comprising 322 patients with gliomas and developed a novel classification system of preoperative tumor status, which considers tumor operability based on two graduations (Friedlein Grading - FG): FGA with lesions at safe distance to eloquent regions which can be completely resected, and FGB referring to tumors which can only be partially resected or biopsied. Investigation of outcome revealed that FGA were characterized by a significantly longer overall survival time compared to FGB. We offer the opportunity to classify brain tumors in a dependable and reproducible manner. The FGA/B grading method provides high prognostic value with respect to overall survival time in relation to the extent of location-dependent tumor resection.
EVALuna2:22845

Angiographic CT with intravenous contrast agent application for monitoring of intracranial flow diverting stents - Saake, Marc; Struffert, Tobias; Gölitz, Philipp; Ott, Sabine; Seifert, Frank; Ganslandt, Oliver; Dörfler, Arnd (Neuroradiology, 2012)
Introduction: Intracranial flow diverting devices are increasingly used to treat cerebral aneurysms. A reliable, noninvasive follow-up modality would be desirable. Our aim was to compare intra-arterial digital subtraction angiography (ia DSA) to angiographic computed tomography with intravenous contrast agent application (iv ACT) in the visualisation of flow diverting devices and aneurysm lumina. Methods: Follow-up monitoring by iv ACT (n=36) and ia DSA (n=25) in 14 patients treated with flow diverting devices for intracranial aneurysms was evaluated retrospectively. Images were evaluated by two neuroradiologists in anonymous consensus reading regarding the device deployment, wall apposition, neck coverage of the aneurysm, opacification of the vessel and device lumen, as well as the degree of aneurysm occlusion. Results: Corresponding ia DSA and iv ACT images were scored identically in all patients regarding the stent deployment, wall apposition and neck coverage, as well as the degree of aneurysm occlusion and patency status of the device and parent artery. Opacification of the parent vessel lumen and perfused parts of the aneurysm was considered slightly inferior for iv ACT in comparison with ia DSA (seven of 36 cases), without impact on diagnosis. Conclusions: We demonstrated the feasibility and diagnostic value of iv ACT in follow-up imaging of intracranial flow diverting devices. Due to its high spatial resolution and non-invasive character, this novel technique might become a valuable imaging modality in these patients. © Springer-Verlag 2011.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Computed tomography; Flat detector; Flow diverting stent; Follow-up; Intravenous

Angiographic CT with intravenous contrast injection compared with conventional rotational angiography in the diagnostic work-up of cerebral aneurysms - Gölitz, Philipp; Struffert, Tobias; Knossalla, F.; Saake, Marc; Ott, Sabine; Ganslandt, Oliver; Dörfler, Arnd (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Noninvasive imaging of cerebral aneurysms is still considered inferior to conventional angiography. The purpose of this study was to evaluate the diagnostic accuracy of ivACT in the assessment of intracranial aneurysms compared with 3D-DSA. MATERIALS AND METHODS: We included 13 patients with 15 incidental unruptured saccular aneurysms scheduled for diagnostic angiographic work-up in our study. In each patient, we performed an ivACT and a conventional angiography including a 3D rotational run. During postprocessing, MPR images were generated for each technique. Maximal aneurysm diameter, neck diameter, aneurysm height, maximum width, bulge height, parent artery diameter, and angle between the parent artery and aneurysm apex were measured for each aneurysm. RESULTS: 3D-DSA and ivACT both provided images of high quality without artificial disturbances (ie, motion artifacts). Measurements of all parameters resulted in comparable values for both modalities with a strong correlation (P ≤ .001). CONCLUSIONS: ivACT is feasible for the noninvasive visualization of saccular cerebral aneurysms and may provide reliable diagnostic information for the assessment of aneurysm size and geometry comparable with conventional intra-arterial 3D rotational angiography. These preliminary results might be a first promising step to replacing conventional angiography in preinterventional aneurysm imaging.
CRIS-Team Scopus Importer:2022-08-05

An Investigation of Feature-based Nonrigid Image Registration using Gaussian Process - Bayer, Siming; Spiske, Ute; Geimer, Tobias; Luo, Jie; Wells III, William M.; Ostermeier, Martin; Fahrig, Rebecca; Arya, Nabavi; Bert, Christoph; Eyüpoglu, Ilker Yasin; Maier, Andreas (Algorithmen – Systeme – Anwendungen. Proceedings des Workshops, 2020)
For a wide range of clinical applications, such as adaptive treatment planning or intraoperative image update, feature-based deformable registration (FDR) approaches are widely employed because of their simplicity and low computational complexity. FDR algorithms estimate a dense displacement field by interpolating a sparse field, which is given by the established correspondence between selected features. In this paper, we consider the deformation field as a Gaussian Process (GP), whereas the selected features are regarded as prior information on the valid deformations. Using GP, we are able to estimate the both dense displacement field and a corresponding uncertainty map at once. Furthermore, we evaluated the performance of different hyperparameter settings for squared exponential kernels with synthetic, phantom and clinical data respectively. The quantitative comparison shows, GP-based interpolation has performance on par with state-of-the-art B-spline interpolation. The greatest clinical benefit of GP-based interpolation is that it gives a reliable estimate of the mathematical uncertainty of the calculated dense displacement map.<br

A novel method for calibrating head models to account for variability in conductivity and its evaluation in a sphere model - Schrader, S.; Antonakakis, M.; Rampp, Stefan; Engwer, Christian; Wolters, C. H. (Physics in Medicine and Biology, 2020)
The accuracy in electroencephalography (EEG) and combined EEG and magnetoencephalography (MEG) source reconstructions as well as in optimized transcranial electric stimulation (TES) depends on the conductive properties assigned to the head model, and most importantly on individual skull conductivity. In this study, we present an automatic pipeline to calibrate head models with respect to skull conductivity based on the reconstruction of the P20/N20 response using somatosensory evoked potentials and fields. In order to validate in a well-controlled setup without interplay with numerical errors, we evaluate the accuracy of this algorithm in a 4-layer spherical head model using realistic noise levels as well as dipole sources at different eccentricities with strengths and orientations related to somatosensory experiments. Our results show that the reference skull conductivity can be reliably reconstructed for sources resembling the generator of the P20/N20 response. In case of erroneous assumptions on scalp conductivity, the resulting skull conductivity parameter counterbalances this effect, so that EEG source reconstructions using the fitted skull conductivity parameter result in lower errors than when using the standard value. We propose an automatized procedure to calibrate head models which only relies on non-invasive modalities that are available in a standard MEG laboratory, measures under in vivo conditions and in the low frequency range of interest. Calibrated head modeling can improve EEG and combined EEG/MEG source analysis as well as optimized TES.
CRIS-Team WoS Importer:2021-01-15

Anterior Temporal Spikes Source: A Study Of Simultaneous Scalp And Intracranial Stereo-EEG - Unnwongse, K.; Rampp, Stefan; Parpaley, Y.; Wellmer, J.; Wehner, T. (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

A patient-specific, interactive, multiuser, online mixed-reality neurosurgical training and planning system - Wang, Jingyue; Zhao, Yining; Xu, Xinghua; Wang, Qun; Li, Fangye; Zhang, Shiyu; Gan, Zhichao; Xiong, Ruochu; Zhang, Jiashu; Chen, Xiaolei (Neurosurgical Focus, 2024)
OBJECTIVE: Mixed-reality simulation is an emerging tool for creating anatomical models for preoperative planning. Its use in neurosurgical training (NT) has been limited because of the difficulty in real-time interactive teaching. This study describes the development of a patient-specific, interactive mixed-reality NT system. The authors took cases of intracranial tumor resection or neurovascular compression (NVC) as examples to verify the technical feasibility and efficacy of the mixed-reality NT system for residents' training and preoperative planning. METHODS: This study prospectively enrolled 40 patients who suffered from trigeminal neuralgia, hemifacial spasms, or intracranial tumors. The authors used a series of software programs to process the multimodal imaging data, followed by uploading the holographic models online. They used a HoloLens or a standard iOS device to download and display the holographic models for training. Ten neurosurgical residents with different levels of surgical experience were trained with this mixed-reality NT system. Change in surgical strategy was recorded, and a questionnaire survey was conducted to evaluate the efficacy of the mixed-reality NT system. RESULTS: The system allows the trainer and trainee to view the mixed-reality model with either a HoloLens or an iPad/iPhone simultaneously online at different locations. Interactive manipulation and instant updates were able to be achieved during training. A clinical efficacy validation test was conducted. The surgeons changed their exploration strategy in 48.3% of the NVC cases. For residents with limited experience in surgery, the exploration strategy for 75.0% of all patients with NVC was changed after the residents were trained with the mixed-reality NT system. Of the 60 responses for intracranial tumors, the trainee changed the surgical posture in 19 (31.7%) cases. The change of the location (p = 0.0338) and size (p = 0.0056) of craniotomy are significantly related to the experience of the neurosurgeons. CONCLUSIONS: The mixed-reality NT system is available for local or real-time remote neurosurgical resident training. It may effectively help neurosurgeons in patient-specific training and planning of surgery for cases of NVC and intracranial tumor. The authors expect the system to have a broader application in neurosurgery in the near future.
CRIS-Team Scopus Importer:2024-01-19
Keywords: mixed reality; neurosurgery; patient-specific training system; resident training

Application of functional imaging, neuronavigation, and intraoperative MR imaging in the surgical treatment of brain cavernomas - Winter, Fabian; Blair, Lisa; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2020)
Objective: The aim of this study was to investigate whether preoperative functional imaging and intraoperative magnetic resonance imaging (iMRI) facilitate surgery and improve outcomes in the surgical treatment of cavernous malformations of the brain (CM). Materials and Methods: Retrospective data analysis was performed for consecutive patients diagnosed with a CM who underwent surgical treatment at a single academic institution during a 12 year period. A total of 91 patients was eligible for analysis with a mean age of 38.8 ± 15 years (range 2–72 years). Altogether, 89.0% of CM had supratentorial and 11% infratentorial location. Results: Neuronavigation and iMRI was used in 69 (75.8%) patients with 28 (30.8%) of them together with functional MRI (fMRI) all in the supratentorial location. In 4.3% (3 cases) an intraoperative second-look surgery was performed. Altogether, a complete resection was achieved in 93% of the patients. In supratentorial surgeries, surgical times were significantly shorter in the fMRI group (p = 0.036), but altogether, infratentorial CM surgery took significantly longer (p = 0.014). Moreover, in the fMRI group, reduction of seizure medication was achieved significantly more often (p = 0.026). At an FU of 6.1± 3.1 years, 96% of the patients were assessed modified Rankin Scale 0 or 1. Conclusion: Neuronavigation together with intraoperative and functional MRI had a significant impact on resection amount, surgical time, and neurological and seizure outcome of supratentorial CM. In addition, iMRI was beneficial in few-selected cases.
CRIS-Team Scopus Importer:2020-11-27
Keywords: brain cavernomas; Functional imaging; intraoperative magnetic resonance imaging; neuronavigation

A pragmatic algorithm to select appropriate antiseizure medications in patients with epilepsy - Asadi-Pooya, Ali A.; Beniczky, Sandor; Rubboli, Guido; Sperling, Michael R.; Rampp, Stefan; Perucca, Emilio (Epilepsia, 2020)
Objective: Antiseizure medications (ASMs) are the first-line treatment for epilepsy. Many ASMs are available; this offers the opportunity to improve therapy by tailoring it to individual characteristics, but also increases the possibility of healthcare professionals making inappropriate treatment choices. To assist healthcare professionals, we developed a pragmatic algorithm aimed at facilitating medication selection for individuals whose epilepsy begins at age 10 years and older. Methods: Utilizing available evidence and a Delphi panel−based consensus process, a group of epilepsy experts developed an algorithm for selection of ASMs, depending on the seizure type(s) and the presence of relevant clinical variables (age, gender, comorbidities, and comedications). The algorithm was implemented into a web-based application that was tested and improved in an iterative process. Results: The algorithm categorizes ASMs deemed to be appropriate for each seizure type or combination of seizure types into three groups, with group 1 ASMs considered preferred, group 2 considered second line, and group 3 considered third line. Depending on the presence of relevant clinical variables, the ranking of individual ASMs is adjusted in the prioritization scheme to tailor recommendations to the characteristics of the individual. The algorithm is available on a web-based application at: https://epipick.org/#/. Significance: The proposed algorithm is user-friendly, requires less than 2 minutes to complete, and provides the user with a range of appropriate treatment options from which to choose. This should facilitate its broad utilization and contribute to improve epilepsy management for healthcare providers who desire advice, particularly those who lack special expertise in the field.
CRIS-Team Scopus Importer:2020-07-31
Keywords: algorithm; drug; epilepsy; seizure; treatment

A prognostic neural epigenetic signature in high-grade glioma - Drexler, Richard; Khatri, Robin; Sauvigny, Thomas; Mohme, Malte; Maire, Cecile L.; Ryba, Alice; Zghaibeh, Yahya; Dührsen, Lasse; Salviano-Silva, Amanda; Lamszus, Katrin; Westphal, Manfred; Gempt, Jens; et al. (Nature Medicine, 2024)
Neural–tumor interactions drive glioma growth as evidenced in preclinical models, but clinical validation is limited. We present an epigenetically defined neural signature of glioblastoma that independently predicts patients’ survival. We use reference signatures of neural cells to deconvolve tumor DNA and classify samples into low- or high-neural tumors. High-neural glioblastomas exhibit hypomethylated CpG sites and upregulation of genes associated with synaptic integration. Single-cell transcriptomic analysis reveals a high abundance of malignant stemcell-like cells in high-neural glioblastoma, primarily of the neural lineage. These cells are further classified as neural-progenitor-cell-like, astrocyte-like and oligodendrocyte-progenitor-like, alongside oligodendrocytes and excitatory neurons. In line with these findings, high-neural glioblastoma cells engender neuron-to-glioma synapse formation in vitro and in vivo and show an unfavorable survival after xenografting. In patients, a high-neural signature is associated with decreased overall and progression-free survival. High-neural tumors also exhibit increased functional connectivity in magnetencephalography and resting-state magnet resonance imaging and can be detected via DNA analytes and brain-derived neurotrophic factor in patients’ plasma. The prognostic importance of the neural signature was further validated in patients diagnosed with diffuse midline glioma. Our study presents an epigenetically defined malignant neural signature in high-grade gliomas that is prognostically relevant. High-neural gliomas likely require a maximized surgical resection approach for improved outcomes.
CRIS-Team Scopus Importer:2024-05-24

Arachnoid Membranes Around the Cisternal Segment of the Trigeminal Nerve: A Cadaveric Anatomic Study and Intraoperative Observations During Minimally Invasive Microvascular Decompression Surgery - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo (World Neurosurgery, 2019)
Objective: The minimally invasive microvascular decompression (MVD) for trigeminal neuralgia is technically a more challenging operation compared with the standard retrosigmoidal approach. Endoscopic assistance could help to widen the field of view of the microscope during MVD. An extended view around the cisternal segment of the trigeminal nerve can be achieved only with the targeted dissection of the arachnoid membranes. The goal of our study was to analyze the three-dimensional organization of these membranes around the trigeminal nerve. Methods: Microsurgical, endoscopic, and macroscopic anatomic examinations were performed on 50 fresh human cadaveric specimens. Retrospective analysis of the video documentations of 50 MVDs was performed to describe the surgical relevance of the examined membranes. Results: The trigeminal nerve is surrounded circumferentially by 4 inner arachnoid membranes: laterally and caudally by the trigeminal membrane (TM), cranially by the superior cerebellar membrane (SCM), and medially by the junction between the cranial edge of the anterior pontine membrane and the lateral edge mesencephalic leaf of the Liliequist membrane complex. The superior cerebellar artery was located in every case cranial from the SCM. This membrane served as a safety plane to dissect the vessel from the nerve. The SCM was laterally adherent to the TM, which made the arachnoid dissection challenging. The superior petrosal vein was located cranially and laterally from the described inner arachnoid membranes, but the transverse pontine vein was embedded into the membrane complex. Conclusions: Knowledge of the described anatomy of the arachnoid membranes around the trigeminal nerve is essential to safely perform an MVD.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Arachnoid membranes; Endoscopic anatomy; Microvascular decompression; Posterior fossa; Retrosigmoid keyhole approach; Trigeminal nerve; Trigeminal neuralgia

Are Transventricular Approaches Associated With Increased Hemorrhage? A Comparative Study in a Series of 624 Deep Brain Stimulation Surgeries - Runge, Joachim; Nagel, Johanna M.; Ascencao, Luisa Cassini; Blahak, Christian; Kinfe, Thomas Mehari; Schrader, Christoph; Wolf, Marc E.; Saryyeva, Assel; Krauss, Joachim K. (Operative Neurosurgery, 2022)
BACKGROUND:Deep brain stimulation (DBS) surgery has advanced tremendously, for both clinical applications and technology. Although DBS surgery is an overall safe procedure, rare side effects, in particular, hemorrhage, may result in devastating consequences. Although there are certain advantages with transventricular trajectories, it has been reasoned that avoidance of such trajectories would likely reduce hemorrhage.OBJECTIVE:To investigate the possible impact of a transventricular trajectory as compared with a transcerebral approach on the occurrence of symptomatic and asymptomatic hemorrhage after DBS electrode placement.METHODS:Retrospective evaluation of 624 DBS surgeries in 582 patients, who underwent DBS surgery for movement disorders, chronic pain, or psychiatric disorders. A stereotactic guiding cannula was routinely used for DBS electrode insertion. All patients had postoperative computed tomography scans within 24 hours after surgery.RESULTS:Transventricular transgression was identified in 404/624 DBS surgeries. The frequency of hemorrhage was slightly higher in transventricular than in transcerebral DBS surgeries (15/404, 3.7% vs 6/220, 2.7%). While 7/15 patients in the transventricular DBS surgery group had a hemorrhage located in the ventricle, 6 had an intracerebral hemorrhage along the electrode trajectory unrelated to transgression of the ventricle and 2 had a subdural hematoma. Among the 7 patients with a hemorrhage located in the ventricle, only one became symptomatic. Overall, a total of 7/404 patients in the transventricular DBS surgery group had a symptomatic hemorrhage, whereas the hemorrhage remained asymptomatic in all 6/220 patients in the transcerebral DBS surgery group.CONCLUSION:Transventricular approaches in DBS surgery can be performed safely, in general, when special precautions such as using a guiding cannula are routinely applied.
CRIS-Team WoS Importer:2023-02-17

Assessment of conformity of actual thoraco-lumbar pedicle screw dimensions to manufacturers’ specifications - Banas, Marian; Hore, Nirjhar; Buchfelder, Michael; Brandner, Sebastian (Science Progress, 2021)
Although correct selection of pedicle screw dimensions is indispensable to achieving optimum results, manufacturer-specified or intended dimensions may differ from actual dimensions. Here we analyzed the reliability of specifications made by various manufacturers by comparing them to the actual lengths and diameters of pedicle screws in a standardized experimental setup. We analyzed the actual length and diameter of pedicle screws of five different manufacturers. Four different screw lengths and for each length two different diameters were measured. Measurements were performed with the pedicle screws attached to a rod, with the length determined from the bottom of the tulip to the tip of the screw and the diameters determined at the proximal and distal threads. Differences in length of > 1 mm were found between the manufacturers’ specifications and our actual measurements in 24 different pedicle screws. The highest deviation of the measured length from the manufacturers’ specification was 3.2 mm. The difference in length between the shortest and longest screw with identical specifications was 3.4 mm. The highest deviation of the measured proximal thread diameters and the manufacturer’s specifications was 0.5 mm. The diameter of the distal thread depends on the shape of the pedicle screw and hence varies between manufacturers in conical screws. We found clear differences in the length of pedicle screws with identical manufacturer specifications. Since differences between the actual dimensions and the dimensions indicated by the manufacturer may vary, this needs to be taken into account during the planning of spine instrumentation.
CRIS-Team Scopus Importer:2021-08-27
Keywords: biomechanics; Pedicle screws; spinal instrumentation

Association between tissue hypoxia, perfusion restrictions, and microvascular architecture alterations with lesion-induced impairment of neurovascular coupling - Stadlbauer, Andreas; Kinfe, Thomas Mehari; Zimmermann, Max; Eyüpoglu, Ilker Yasin; Brandner, Nadja; Buchfelder, Michael; Zaiß, Moritz; Dörfler, Arnd; Brandner, Sebastian (Journal of Cerebral Blood Flow and Metabolism, 2020)
Functional magnetic resonance imaging (fMRI) has been mainly utilized for the preoperative localization of eloquent cortical areas. However, lesion-induced impairment of neurovascular coupling (NVC) in the lesion border zone may lead to false-negative fMRI results. The purpose of this study was to determine physiological factors impacting the NVC. Twenty patients suffering from brain lesions were preoperatively examined using multimodal neuroimaging including fMRI, magnetoencephalography (MEG) during language or sensorimotor tasks (depending on lesion location), and a novel physiologic MRI approach for the combined quantification of oxygen metabolism, perfusion state, and microvascular architecture. Congruence of brain activity patterns between fMRI and MEG were found in 13 patients. In contrast, we observed missing fMRI activity in perilesional cortex that demonstrated MEG activity in seven patients, which was interpreted as lesion-induced impairment of NVC. In these brain regions with impaired NVC, physiologic MRI revealed significant brain tissue hypoxia, as well as significantly decreased macro- and microvascular perfusion and microvascular architecture. We demonstrated that perilesional hypoxia with reduced vascular perfusion and architecture is associated with lesion-induced impairment of NVC. Our physiologic MRI approach is a clinically applicable method for preoperative risk assessment for the presence of false-negative fMRI results and may prevent severe postoperative functional deficits.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Blood-oxygen-level-dependent contrast; functional magnetic resonance imaging; hypoxia; magnetoencephalography; neurovascular coupling

A statistical method for analyzing and comparing spatiotemporal cortical activation patterns - Krauß, Patrick; Metzner, Claus; Schilling, Achim; Tziridis, Konstantin; Traxdorf, Maximilian; Wollbrink, Andreas; Rampp, Stefan; Pantev, Christo; Schulze, Holger (Scientific Reports, 2018)
Information in the cortex is encoded in spatiotemporal patterns of neuronal activity, but the exact nature of that code still remains elusive. While onset responses to simple stimuli are associated with specific loci in cortical sensory maps, it is completely unclear how the information about a sustained stimulus is encoded that is perceived for minutes or even longer, when discharge rates have decayed back to spontaneous levels. Using a newly developed statistical approach (multidimensional cluster statistics (MCS)) that allows for a comparison of clusters of data points in n-dimensional space, we here demonstrate that the information about long-lasting stimuli is encoded in the ongoing spatiotemporal activity patterns in sensory cortex. We successfully apply MCS to multichannel local field potential recordings in different rodent models and sensory modalities, as well as to human MEG and EEG data, demonstrating its universal applicability. MCS thus indicates novel ways for the development of powerful read-out algorithms of spatiotemporal brain activity that may be implemented in innovative brain-computer interfaces (BCI).
EVALuna2:35749

ATF4 promotes angiogenesis and neuronal cell death and confers ferroptosis in a xCT-dependent manner - Chen, Daishi; Fan, Zheng; Rauh, Manfred; Buchfelder, Michael; Eyupoglu, I. Y.; Savaskan, Nicolai (Oncogene, 2017)
Activating transcription factor 4 (ATF4) is a critical mediator of metabolic and oxidative homeostasis and cell survival. ATF4 is elevated in response to diverse microenvironmental stresses, including starvation, ER stress damages and exposure to toxic factors. Here we show that ATF4 expression fosters the malignancy of primary brain tumors (WHO grade III and IV gliomas) and increases proliferation and tumor angiogenesis. Hence, ATF4 expression promotes cell migration and anchorage-independent cell growth, whereas siRNA-mediated knockdown of ATF4 attenuates these features of malignancy in human gliomas. Further experiments revealed that ATF4-dependent tumor promoting effects are mediated by transcriptional targeting the glutamate antiporter xCT/SCL7A11 (also known as system Xc-). Thus, xCT is elevated as a consequence of ATF4 activation. We further found evidence that ATF4-induced proliferation can be attenuated by pharmacological or genetic xCT inhibition and ferroptosis inducers such as sorafenib, erastin and GPx4 inhibitor RSL3. Further, fostered xCT expression promotes cell survival and growth in ATF4 knockdown cells. Moreover, increased xCT levels ameliorate sorafenib and erastin-induced ferroptosis. Conversely, ATF4 knockdown renders cells susceptible for erastin, sorafenib and RSL3-induced ferroptosis. We further identified that ATF4 promotes tumor-mediated neuronal cell death which can be alleviated by xCT inhibition. Moreover, elevated ATF4 expression in gliomas promotes tumor angiogenesis. Noteworthy, ATF4-induced angiogenesis could be diminished by ferroptosis inducers erastin and by GPx4 inhibitor RSL3. Our data provide proof-of-principle evidence that ATF4 fosters proliferation and induces a toxic microenvironmental niche. Furthermore, ATF4 increases tumor angiogenesis and shapes the vascular architecture in a xCT-dependent manner. Thus, inhibition of ATF4 is a valid target for diminishing tumor growth and vasculature via sensitizing tumor cells for ferroptosis.
EVALuna2:34242

Attentional modulation of the cortical contribution to the frequency-following response evoked by continuous speech - Schüller, Alina; Schilling, Achim; Krauß, Patrick; Rampp, Stefan; Reichenbach, Tobias (The Journal of Neuroscience, 2023)
Selective attention to one of several competing speakers is required for comprehending a target speaker amongst other voices and for successful communication with them. It moreover has been found to involve the neural tracking of low-frequency speech rhythms in the auditory cortex. Effects of selective attention have also been found in subcortical neural activities, in particular regarding the high-frequency neural response at the fundamental frequency of speech, the speech-FFR. Recent investigations have, however, shown that the speech-FFR contains cortical contributions as well. It remains unclear whether these are also modulated by selective attention. Here we employed magnetoencephalography (MEG) to assess the attentional modulation of the cortical contributions to the speech-FFR. We presented both male and female participants with two competing speech signals and analyzed the cortical responses during attentional switching between the two speakers. Our findings revealed robust attentional modulation of the cortical contribution to the speech-FFR: the neural responses were higher when the speaker was attended than when they were ignored. We also found that, regardless of attention, a voice with a lower fundamental frequency elicited a larger cortical contribution to the speech-FFR than a voice with a higher fundamental frequency. Our results show that the attentional modulation of the speech-FFR does not only occur subcortically but extends to the auditory cortex as well.
CRIS-Team Scopus Importer:2023-11-17

A versatile ex vivo technique for assaying tumor angiogenesis and microglia in the brain - Ghoochani, Ali; Yakubov, Eduard; Sehm, Tina; Fan, Zheng; Hock, Stefan; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai E. (Oncotarget, 2016)
Primary brain tumors are hallmarked for their destructive activity on the microenvironment and vasculature. However, solely few experimental techniques exist to access the tumor microenvironment under anatomical intact conditions with remaining cellular and extracellular composition. Here, we detail an ex vivo vascular glioma impact method (VOGIM) to investigate the influence of gliomas and chemotherapeutics on the tumor microenvironment and angiogenesis under conditions that closely resemble the in vivo situation. We generated organotypic brain slice cultures from rats and transgenic mice and implanted glioma cells expressing fluorescent reporter proteins. In the VOGIM, tumor-induced vessels presented the whole range of vascular pathologies and tumor zones as found in human primary brain tumor specimens. In contrast, non-transformed cells such as primary astrocytes do not alter the vessel architecture. Vascular characteristics with vessel branching, junctions and vessel meshes are quantitatively assessable as well as the peritumoral zone. In particular, the VOGIM resembles the brain tumor microenvironment with alterations of neurons, microglia and cell survival. Hence, this method allows live cell monitoring of virtually any fluorescence-reporter expressing cell. We further analyzed the vasculature and microglia under the influence of tumor cells and chemotherapeutics such as Temozolamide (Temodal/Temcad®). Noteworthy, temozolomide normalized vasculare junctions and branches as well as microglial distribution in tumor-implanted brains. Moreover, VOGIM can be facilitated for implementing the 3Rs in experimentations. In summary, the VOGIM represents a versatile and robust technique which allows the assessment of the brain tumor microenvironment with parameters such as angiogenesis, neuronal cell death and microglial activity at the morphological and quantitative level.
EVALuna2:22857

Awake mapping is not an additional surgical technique but an alternative philosophy in the management of low-grade glioma patients - Buchfelder, Michael; Zhao, Yining (Neurosurgical Review, 2018)
EVALuna2:214805

A web-based algorithm to rapidly classify seizures for the purpose of drug selection - Beniczky, Sándor; Asadi-Pooya, Ali A.; Perucca, Emilio; Rubboli, Guido; Tartara, Elena; Meritam Larsen, Pirgit; Ebrahimi, Saqar; Farzinmehr, Somayeh; Rampp, Stefan; Sperling, Michael R. (Epilepsia, 2021)
Objective: To develop and validate a pragmatic algorithm that classifies seizure types, to facilitate therapeutic decision-making. Methods: Using a modified Delphi method, five experts developed a pragmatic classification of nine types of epileptic seizures or combinations of seizures that influence choice of medication, and constructed a simple algorithm, freely available on the internet. The algorithm consists of seven questions applicable to patients with seizure onset at the age of 10 years or older. Questions to screen for nonepileptic attacks were added. Junior physicians, nurses, and physician assistants applied the algorithm to consecutive patients in a multicenter prospective validation study (ClinicalTrials.gov identifier: NCT03796520). The reference standard was the seizure classification by expert epileptologists, based on all available data, including electroencephalogram (EEG), video-EEG monitoring, and neuroimaging. In addition, physicians working in underserved areas assessed the feasibility of using the web-based algorithm in their clinical setting. Results: A total of 262 patients were assessed, of whom 157 had focal, 51 had generalized, and 10 had unknown onset epileptic seizures, and 44 had nonepileptic paroxysmal events. Agreement between the algorithm and the expert classification was 83.2% (95% confidence interval = 78.6%–87.8%), with an agreement coefficient (AC1) of.82 (95% confidence interval =.77–.87), indicating almost perfect agreement. Thirty-two health care professionals from 14 countries evaluated the feasibility of the web-based algorithm in their clinical setting, and found it applicable and useful for their practice (median = 6.5 on 7-point Likert scale). Significance: The web-based algorithm provides an accurate classification of seizure types, which can be used for selecting antiseizure medications in adolescents and adults.
CRIS-Team Scopus Importer:2021-08-27
Keywords: algorithm; classification; epilepsy; seizure; web-based application

A Whole-Slide Image Managing Library Based on Fastai for Deep Learning in the Context of Histopathology: Two Use-Cases Explained - Neuner, Christoph; Coras, Roland; Blümcke, Ingmar; Popp, Alexander; Schlaffer, Sven-Martin; Wirries, Andre; Buchfelder, Michael; Jabari, Samir (Applied Sciences, 2022)
Background: Processing whole-slide images (WSI) to train neural networks can be intricate and labor intensive. We developed an open-source library dealing with recurrent tasks in the processing of WSI and helping with the training and evaluation of neuronal networks for classification tasks. Methods: Two histopathology use-cases were selected and only hematoxylin and eosin (H&E) stained slides were used. The first use case was a two-class classification problem. We trained a convolutional neuronal network (CNN) to distinguish between dysembryoplastic neuroepithelial tumor (DNET) and ganglioglioma (GG), two neuropathological low-grade epilepsy-associated tumor entities. Within the second use case, we included four clinicopathological disease conditions in a multilabel approach. Here we trained a CNN to predict the hormone expression profile of pituitary adenomas. In the same approach, we also predicted clinically silent corticotroph adenoma. Results: Our DNET-GG classifier achieved an AUC of 1.00 for the ROC curve. For the second use case, the best performing CNN achieved an area under the curve (AUC) of 0.97 for the receiver operating characteristic (ROC) for corticotroph adenoma, 0.86 for silent corticotroph adenoma, and 0.98 for gonadotroph adenoma. All scores were calculated with the help of our library on predictions on a case basis. Conclusions: Our comprehensive and fastai-compatible library is helpful to standardize the workflow and minimize the burden of training a CNN. Indeed, our trained CNNs extracted neuropathologically relevant information from the WSI. This approach will supplement the clinicopathological diagnosis of brain tumors, which is currently based on cost-intensive microscopic examination and variable panels of immunohistochemical stainings.
CRIS-Team WoS Importer:2022-02-18

Bariatric Surgery for Hypothalamic Obesity in Craniopharyngioma Patients: A Retrospective, Matched Case-Control Study - Van Santen, Selveta S.; Wolf, Peter; Kremenevski, Natalia; Boguszewski, Cesar L.; Beiglbock, Hannes; Fiocco, Marta; Wijnen, Mark; Wallenius, Ville R.; Van Den Heuvel-Eibrink, Marry M.; Van Der Lely, Aart J.; Johannsson, Gudmundur; Luger, Anton; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: Craniopharyngioma is a sellar tumor associated with high rates of pituitary deficiencies (similar to 98%) and hypothalamic obesity (similar to 50%).
CRIS-Team WoS Importer:2021-11-26

Beyond Functional Impairment: Redefining Favorable Outcome in Patients with Subarachnoid Hemorrhage - Custal, Christina; Koehn, Julia; Borutta, Matthias; Mrochen, Anne; Brandner, Sebastian; Eyupoglu, Ilker Y.; Lücking, Hannes; Hölter, Philip; Kuramatsu, Joji; Kornhuber, Johannes; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2021)
Background: For outcome assessment in patients surviving subarachnoid hemorrhage (SAH), the modified Rankin scale (mRS) represents the mostly established outcome tool, whereas other dimensions of outcome such as mood disorders and impairments in social life remain unattended so far. Objective: The aim of our study was to correlate 12-month functional and subjective health outcomes in SAH survivors. Methods: All SAH patients treated over a 5-year period received outcome assessment at 12 months, including functional scores (mRS and Barthel Index [BI]), subjective health measurement (EQ-5D), and whether they returned to work. Analyses - including utility-weighted mRS - were conducted to detect associations and correlations among different outcome measures, especially in patients achieving good functional outcome (i.e., mRS 0-2) at 12 months. Results: Of 351 SAH survivors, 287 (81.2%) achieved favorable functional outcome at 12 months. Contrary to the BI, the EQ-5D visual analog scale (VAS) showed a strong association with different mRS grades, accentuated in patients with favorable functional outcome. Despite favorable functional outcome, patients reported a high rate of impairments in activities (24.0%), pain (33.4%), and anxiety/depression (42.5%). Further, multivariable analysis revealed (i) impairments in activities (odds ratio [OR] [95% confidence interval CI]: 0.872 [0.817-0.930]), (ii) presence of depression or anxiety (OR [95% CI]: 0.836 [0.760-0.920]), and (iii) return to work (OR [95% CI]: 1.102 [0.1.013-1.198]) to be independently associated with self-reported subjective health. Conclusion: Established stroke scores mainly focusing on functional outcomes do poorly reflect the high rate of subjective impairments reported in SAH survivors, specifically in those achieving good functional outcome. Further studies are needed to investigate whether psychoeducational approaches aiming at improving coping mechanisms and perceived self-efficacy may result in higher subjective health in these patients.
CRIS-Team WoS Importer:2021-08-06

Big data research is everyone's research—Making epilepsy data science accessible to the global community: Report of the ILAE big data commission - Josephson, Colin B.; Aronica, Eleonora; Beniczky, Sandor; Boyce, Danielle; Cavalleri, Gianpiero; Denaxas, Spiros; French, Jacqueline; Jehi, Lara; Koh, Hyunyong; Kwan, Patrick; McDonald, Carrie; Mitchell, James W.; et al. (Epileptic Disorders, 2024)
Epilepsy care generates multiple sources of high-dimensional data, including clinical, imaging, electroencephalographic, genomic, and neuropsychological information, that are collected routinely to establish the diagnosis and guide management. Thanks to high-performance computing, sophisticated graphics processing units, and advanced analytics, we are now on the cusp of being able to use these data to significantly improve individualized care for people with epilepsy. Despite this, many clinicians, health care providers, and people with epilepsy are apprehensive about implementing Big Data and accompanying technologies such as artificial intelligence (AI). Practical, ethical, privacy, and climate issues represent real and enduring concerns that have yet to be completely resolved. Similarly, Big Data and AI-related biases have the potential to exacerbate local and global disparities. These are highly germane concerns to the field of epilepsy, given its high burden in developing nations and areas of socioeconomic deprivation. This educational paper from the International League Against Epilepsy's (ILAE) Big Data Commission aims to help clinicians caring for people with epilepsy become familiar with how Big Data is collected and processed, how they are applied to studies using AI, and outline the immense potential positive impact Big Data can have on diagnosis and management.
CRIS-Team Scopus Importer:2024-11-01
Keywords: artificial intelligence; big data; common data models; epilepsy; ethics

BRAF V600E analysis for the differentiation of papillary craniopharyngiomas and Rathke's cleft cysts - Schweizer, L.; Capper, David; Hoelsken, A.; Fahlbusch, R.; Flitsch, J.; Buchfelder, Michael; Herold-Mende, C.; Von Deimling, Andreas; Buslei, R. (Neuropathology and Applied Neurobiology, 2015)
The differential diagnosis of cystic epithelial masses of the sellar region, especially the histopathological differentiation of craniopharyngiomas and Rathke's cleft cysts, poses a challenge even to experienced diagnosticians. Recently, BRAF V600E mutations have been described as a genetic hallmark of papillary craniopharyngiomas. We investigated a series of 33 Rathke's cleft cysts to determine the frequency of BRAF V600E mutations and its suitability as an additional diagnostic marker for the differentiation of cystic lesions of the sellar region.Thirty-three Rathke's cleft cysts and 18 papillary craniopharyngiomas were analysed for BRAF mutational status by immunohistochemistry using a monoclonal antibody (VE1) that selectively recognizes the BRAF V600E mutant epitope and additional BRAF pyrosequencing in a subset of samples.Thirty of 33 specimens diagnosed as Rathke's cleft cysts were negative by VE1 immunohistochemistry and pyrosequencing, whereas in three cysts and in all the 18 papillary craniopharyngiomas, a BRAF V600E mutation was detected. Clinical and histological re-evaluation of the three BRAF V600E mutated cases formerly diagnosed as Rathke's cleft cysts revealed unusual presentations. Two of them were rediagnosed as papillary craniopharyngiomas. The patient of the third case had a history of craniopharyngioma operated 14 years before, and reoperation showed a cystic epithelial lesion with unclear histology.The determination of BRAF mutational status is recommended in any cystic sellar lesion and can in most cases be provided by VE1 immunohistochemistry even in specimens of low cellularity. Confirmation by (pyro-)sequencing should be attempted whenever sufficient epithelium is available due to variable staining results.
EVALuna2:7254

Burst Motor Cortex Stimulation Evokes Sustained Suppression of Thalamic Stroke Pain: A Narrative Review and Single-Case Overview - Nuessel, Martin; Hamperl, Melanie; Maslarova, Anna; Chaudhry, Shafqat R.; Kohn, Julia; Stadlbauer, Andreas; Buchfelder, Michael; Kinfe, Thomas Mehari (Pain and Therapy, 2020)
Chronic refractory central post-stroke pain (CPSP), one of the most disabling consequences of cerebral stroke, occurs in up to 10% of patients with CPSP. Because a considerable proportion of these patients with chronic pain remain resistant to pharmacological and behavioral therapies, adjunctive invasive and non-invasive brain stimulation therapies are needed. We performed a review of human studies applying burst and conventional motor cortex stimulation (burstMCS and cMCS, respectively) for chronic pain states, on the basis of data sources identified through searches of PubMed, MEDLINE/OVID, and SCOPUS, as well as manual searches of the bibliographies of known primary and review articles. Our aim was to review and discuss clinical data on the indications of burstMCS for various chronic pain states originating from central stroke (excluding trigeminal facial pain). In addition, we assessed the efficacy and safety of burst versus cMCS for central post-stroke pain with an extended follow-up of 5 years in a 60-year-old man. According to our review, uncontrolled observational human cohort studies and one RCT using cMCS waveforms have revealed a meaningful clinical response; however, these studies lacked placebo groups and extended observation periods. In our case report, we found that 3 months of adjunctive cMCS reduced pain levels [visual analog scale (VAS) pre: 9/10 versus VAS post 7/10], whereas the pain decreased further under burstMCS (VAS pre: 7/10 versus VAS post: 2/10); the study involved a follow-up of 5 years and the following parameters: burst rate 40 Hz (500 Hz), 1-1.75 mA, 1 ms, bipolar configuration. To date, only limited evidence exists for the efficacy and safety of burst motor cortex stimulation for the treatment of refractory chronic pain. BurstMCS resulted in significantly decreased post-stroke pain observed after 5 years of cMCS. The available literature suggests similar efficacy as that of conventional (tonic) motor cortex stimulation, although the results are preliminary. Mechanistically, the precise mechanism of action is not fully understood. However, burstMCS may interact with the nociceptive thalamic-cingulate and descending spinal pain networks. To determine the potential utility of this treatment, large-scale sham-controlled trials comparing cMCS and burstMCS are highly recommended.
CRIS-Team WoS Importer:2021-01-01

Cabazitaxel operates anti-metastatic and cytotoxic via apoptosis induction and stalls brain tumor angiogenesis - Ghoochani, Ali; Hatipoglu Majernik, Gökce; Sehm, Tina; Wach, Sven; Buchfelder, Michael; Taubert, Helge; Eyupoglu, Ilker Y.; Savaskan, Nicolai (Oncotarget, 2016)
Taxanes target microtubules and are clinically established chemotherapeutic agents with proven efficacy in human cancers. Cabazitaxel (XRP-6258, Jevtana®) is a second generation semisynthetic taxane with high chemotherapeutic potential in prostate cancer. There, cabazitaxel can overcome docetaxel-resistant prostate cancer. Here, we tested the effects of cabazitaxel on glioma cells, and non-transformed cells such as neurons and astrocytes. Cabazitaxel operates highly toxic in various human glioma cells at nanomolar concentrations. In contrast, primary astrocytes and neurons are not affected by this agent. Cabazitaxel disrupts cytoskeletal F-actin fibers and induces apoptotic cell death in gliomas. Moreover, cabazitaxel displayed highest efficacy in inhibiting glioma cell migration and invasion. Here we demonstrate that cabazitaxel inhibited tumor migration already at 1 nM. We also tested cabazitaxel in the ex vivo VOGiM assay. Cabazitaxel stalled glioma growth and at the same time inhibited tumor-induced angiogenesis. In summary, we found that cabazitaxel operates as an apoptosis-inducing gliomatoxic agent with strongest effects on migration and invasive growth. Thus, our report uncovered cabazitaxel actions on gliomas and on the brain tumor microenvironment. These data reveal novel aspects for adjuvant approaches when applied to brain tumor patients.
EVALuna2:33569

Can Perfusion-Based Brain Tissue Oxygenation MRI Support the Understanding of Cerebral Abscesses In Vivo? - Knott, Michael; Hölter, Philip; Soder, Liam; Schlaffer, Sven-Martin; Hoffmanns, Sophia; Lang, Roland; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2023)
Purpose: The clinical condition of a brain abscess is a potentially life-threatening disease. The combination of MRI-based imaging, surgical therapy and microbiological analysis is critical for the treatment and convalescence of the individual patient. The aim of this study was to evaluate brain tissue oxygenation measured with dynamic susceptibility contrast perfusion weighted imaging (DSC-PWI) in patients with brain abscess and its potential benefit for a better understanding of the environment in and around brain abscesses. Methods: Using a local database, 34 patients (with 45 abscesses) with brain abscesses treated between January 2013 and March 2021 were retrospectively included in this study. DSC-PWI imaging and microbiological work-up were key inclusion criteria. These data were analysed regarding a correlation between DSC-PWI and microbiological result by quantifying brain tissue oxygenation in the abscess itself, the abscess capsula and the surrounding oedema and by using six different parameters (CBF, CBV, CMRO2, COV, CTH and OEF). Results: Relative cerebral blood flow (0.335 [0.18–0.613] vs. 0.81 [0.49–1.08], p = 0.015), relative cerebral blood volume (0.44 [0.203–0.72] vs. 0.87 [0.67–1.2], p = 0.018) and regional cerebral metabolic rate for oxygen (0.37 [0.208–0.695] vs. 0.82 [0.55–1.19], p = 0.022) were significantly lower in the oedema around abscesses without microbiological evidence of a specific bacteria in comparison with microbiological positive lesions. Conclusions: The results of this study indicate a relationship between brain tissue oxygenation status in DSC-PWI and microbiological/inflammatory status. These results may help to better understand the in vivo environment of brain abscesses and support future therapeutic decisions.
CRIS-Team Scopus Importer:2023-11-24
Keywords: brain abscess; brain tissue oxygenation; DSC-PWI

Can we use the dynamic and complex interplay between pain and sleep to quantify neuromodulation responsiveness for chronic pain? - Kinfe, Thomas Mehari; Buchfelder, Michael; Stadlbauer, Andreas (Expert review of neurotherapeutics, 2021)
CRIS-Team Scopus Importer:2021-01-22
Keywords: neuroinflammation; neurostimulation therapies; objective outcome measurement; pain; sleep disorders

Case Report: Consecutive Adrenal Cushing’s Syndrome and Cushing’s Disease in a Patient With Somatic CTNNB1, USP8, and NR3C1 Mutations - Detomas, Mario; Altieri, Barbara; Schlötelburg, Wiebke; Appenzeller, Silke; Schlaffer, Sven-Martin; Coras, Roland; Schirbel, Andreas; Wild, Vanessa; Kroiss, Matthias; Sbiera, Silviu; Fassnacht, Martin; Deutschbein, Timo (Frontiers in Endocrinology, 2021)
The occurrence of different subtypes of endogenous Cushing’s syndrome (CS) in single individuals is extremely rare. We here present the case of a female patient who was successfully cured from adrenal CS 4 years before being diagnosed with Cushing’s disease (CD). The patient was diagnosed at the age of 50 with ACTH-independent CS and a left-sided adrenal adenoma, in January 2015. After adrenalectomy and histopathological confirmation of a cortisol-producing adrenocortical adenoma, biochemical hypercortisolism and clinical symptoms significantly improved. However, starting from 2018, the patient again developed signs and symptoms of recurrent CS. Subsequent biochemical and radiological workup suggested the presence of ACTH-dependent CS along with a pituitary microadenoma. The patient underwent successful transsphenoidal adenomectomy, and both postoperative adrenal insufficiency and histopathological workup confirmed the diagnosis of CD. Exome sequencing excluded a causative germline mutation but showed somatic mutations of the β-catenin protein gene (CTNNB1) in the adrenal adenoma, and of both the ubiquitin specific peptidase 8 (USP8) and the glucocorticoid receptor (NR3C1) genes in the pituitary adenoma. In conclusion, our case illustrates that both ACTH-independent and ACTH-dependent CS may develop in a single individual even without evidence for a common genetic background.
CRIS-Team Scopus Importer:2021-09-17
Keywords: CTNNB1; Cushing’s disease; Cushing’s syndrome; glucocorticoid excess; hypercortisolism; NR3C1; USP8

Case report: practicability of functionally based tractography of the optic radiation during presurgical epilepsy work up - Schmitt, F. C.; Kaufmann, J.; Hoffmann, M. B.; Tempelmann, Claus; Kluge, C.; Rampp, Stefan; Voges, J.; Heinze, H. J.; Buentjen, L.; Grueschow, M. (Neuroscience Letters, 2014)
Pre-operative tractography of the optic radiation (OR) has been advised to assess the risk for postoperative visual field deficit (VFD) in certain candidates for resective epilepsy surgery. Diffusion tensor imaging (DTI) tractography relies on a precise anatomical determination of start and target regions of interest (ROIs), such as the lateral geniculate nucleus (LGN) and the primary visual cortex (V1). The post-chiasmal visual pathway and V1 show considerable inter-individual variability, and in epilepsy patients parenchymatous lesions might further complicate this matter. A functionally based tractography (FBT) seems beneficial for precise OR identification. We assessed practicability of FBT for OR identification in a patient with occipital lobe epilepsy due to a temporo-occipital maldevelopmental tumor. The MRI protocol at 3T included a T1-weighted sagittal 3D scan, a T2-weighted axial 2D scan and a DTI scan using an echo planar spin echo sequence. ROIs for fiber tracking of OR (LGN & V1) were determined with T2*-weighted fMRI-based retinotopic assessment. After DTI pre-processing and fiber tracking, paths with similar properties were combined in clusters for visual presentation and OR localization. Retinotopic phase maps allowed for the identification of V1 and LGN for a precise DTI-based reconstruction of OR, which was distant to the patient's tumor. Location and structure of ORs were comparable in each hemisphere. FBT could thus influence the human research of the extrastriate visual pathway and the risk management of post-operative VFD in epilepsy surgery.
EVALuna2:22362

Cell type-specific mRNA quantitation in non-neoplastic tissues after laser-assisted cell picking. - Kinfe, Thomas Mehari; et al. (Pathobiology, 2000)
Objective: Cell type-specific mRNA quantitation can be reliably performed after harvesting less than 20 cell profiles from haemalaun-stained cryosections by laser-assisted cell picking. Up to now it has been unclear to what extent these techniques can be used to analyze differential gene expression in complex tissues. Methods: Using a rat model of experimental endotoxin priming of the lung various pulmonary cell types were microdissected from isolated perfused and ventilated rat lungs after aerosol lipopolysaccharide/interferon-γ stimulation. Results: Porphobilinogen deaminase housekeeping gene (PBGD) and nitric oxide synthase II (NOSII) mRNA in arterial endothelial cells (AEC), bronchiolar epithelial cells (BEC), alveolar septum containing monocytes/macrophages (AS+), alveolar septum without monocytes/macrophages (AS–) and intraluminar alveolar macrophages (AM) could be quantified by real-time RT-PCR. The strongest upregulation of NOSII mRNA occurred in AM, while minimal NOSII expression was detected in BEC, AS+ and AS–. In AEC NOSII mRNA was not detectable. Conclusion: The combination of laser microdissection and real-time RT-PCR is a valuable tool for the quantitative in situ characterization of differential gene expression within complex tissues.<br
Keywords: Laser-assisted cell picking; RT-PCR; real time; mRNA quantitation; Nitric oxide synthase II mRNA; Endotoxin priming; Lipopolysaccharide; Microdissection

Centromedian-Parafascicular and Somatosensory Thalamic Deep Brain Stimulation for Treatment of Chronic Neuropathic Pain: A Contemporary Series of 40 Patients - Abdallat, Mahmoud; Saryyeva, Assel; Blahak, Christian; Wolf, Marc E.; Weigel, Ralf; Loher, Thomas J.; Runge, Joachim; Heissler, Hans E.; Kinfe, Thomas Mehari; Krauss, Joachim K. (Biomedicines, 2021)
Introduction: The treatment of neuropathic and central pain still remains a major challenge. Thalamic deep brain stimulation (DBS) involving various target structures is a therapeutic option which has received increased re-interest. Beneficial results have been reported in several more recent smaller studies, however, there is a lack of prospective studies on larger series providing long term outcomes. Methods: Forty patients with refractory neuropathic and central pain syndromes underwent stereotactic bifocal implantation of DBS electrodes in the centromedian-parafascicular (CM-Pf) and the ventroposterolateral (VPL) or ventroposteromedial (VPM) nucleus contralateral to the side of pain. Electrodes were externalized for test stimulation for several days. Outcome was assessed with five specific VAS pain scores (maximum, minimum, average pain, pain at presentation, allodynia). Results: The mean age at surgery was 53.5 years, and the mean duration of pain was 8.2 years. During test stimulation significant reductions of all five pain scores was achieved with either CM-Pf or VPL/VPM stimulation. Pacemakers were implanted in 33/40 patients for chronic stimulation for whom a mean follow-up of 62.8 months (range 3-180 months) was available. Of these, 18 patients had a follow-up beyond four years. Hardware related complications requiring secondary surgeries occurred in 11/33 patients. The VAS maximum pain score was improved by >= 50% in 8/18, and by >= 30% in 11/18 on long term follow-up beyond four years, and the VAS average pain score by >= 50% in 10/18, and by >= 30% in 16/18. On a group level, changes in pain scores remained statistically significant over time, however, there was no difference when comparing the efficacy of CM-Pf versus VPL/VPM stimulation. The best results were achieved in patients with facial pain, poststroke/central pain (except thalamic pain), or brachial plexus injury, while patients with thalamic lesions had the least benefit. Conclusion: Thalamic DBS is a useful treatment option in selected patients with severe and medically refractory pain.
CRIS-Team WoS Importer:2021-08-06

Changes in plasma ACTH levels and corticotroph tumor size in patients with Cushing's disease during long-term treatment with the glucocorticoid receptor antagonist mifepristone - Fleseriu, Maria; Findling, James W.; Koch, Christian A.; Schlaffer, Sven-Martin; Buchfelder, Michael; Gross, Coleman (Journal of Clinical Endocrinology and Metabolism, 2014)
Pituitary effects of long-term therapy with mifepristone, a glucocorticoid receptor antagonist, in Cushing's disease (CD) patients are not well understood.Our objective was to report changes in ACTH and pituitary magnetic resonance imaging (MRI) findings during long-term use of mifepristone in CD patients.The Study of the Efficacy and Safety of Mifepristone in the Treatment of Endogenous Cushing's Syndrome (SEISMIC) was a 24-week, open-label study of mifepristone, and its long-term extension (LTE) is a multicenter U.S. study.Forty-three CD patients (mean age 45.3 years) were enrolled in SEISMIC with 27 continuing into the LTE study.Mifepristone (300-1200 mg) was administered once daily.ACTH and pituitary MRI were assessed at baseline and at regular intervals during treatment.A >=2-fold increase in ACTH was observed in 72% of patients treated for a median duration of 11.3 months. The mean peak increase in ACTH was 2.76 ± 1.65-fold during SEISMIC, and mean ACTH concentrations remained stable during the LTE. ACTH was directly correlated with mifepristone dose and declined to near baseline levels after mifepristone discontinuation. Tumor regressed in 2 patients and progressed in 3 patients with macroadenomas. An additional microadenoma was identified after 25 months of treatment after a baseline tumor-negative MRI.In the largest prospective study to date, long-term mifepristone treatment increased ACTH in approximately two-thirds of patients with CD. ACTH elevations were observed within the first few weeks of treatment, were dose-dependent, and generally remained stable over time. Corticotroph tumor progression and regression may occur over time, but patients may have significant increases in ACTH levels without evidence of tumor growth.
EVALuna2:22854

Characterization of a Factual Knowledge-Associated Brain Memory Area by Functional Magnetic Resonance Imaging and Implementation in Tumor and Epilepsy Brain Surgery - Grummich, Peter; Ganslandt, Oliver Thomas; Buchfelder, Michael; Roessler, Karl (World Neurosurgery, 2017)
BACKGROUND: The role of the dominant hippocampus in verbal and episodic memory recall has been extensively investigated. However, there are categories of memory estimated independent of hippocampal function. In particular, factual knowledge is solely constituted from written or spoken input independent on undertaken experience, but the temporal structures involved are not well defined. METHODS: In this retrospective study, we mapped the activity of factual knowledge recall using functional magnetic resonance imaging (fMRI) in 60 patients scheduled for tumor or epilepsy surgery and in 18 patients resected within or close to the left mesial temporal lobe. Memory tests were performed preoperatively and postoperatively to investigate deficit symptoms in factual knowledge retrieval. RESULTS: We found a highly reproducible localized brain area within the parahippocampal gyrus, in the depth of the dorsal collateral sulcus, which was constantly involved in factual knowledge retrieval during fMRI tasks in 93% of patients (56/60) during recall of capital cities or multiplication tasks, in two thirds of the patients mainly on the dominant side. In addition, all 18 patients after surgery within this area showed postoperative factual knowledge deficits (56% permanent, 44% transitory), memory prognosis significantly correlating with the first day's factual knowledge retrieval task results. CONCLUSIONS: Using fMRI, we visualized a circumscribed brain area within the parahippocampal gyrus during factual knowledge retrieval, the lesioning of which led to factual knowledge deficits. Thus, impairment of factual knowledge retrieval may occur if resection is extended into the parahippocampal gyrus. Preoperative fMRI memory maps may contribute to avoiding such deficits.
EVALuna2:102195

Characterization of the murine orthotopic adamantinomatous craniopharyngioma PDX model by MRI in correlation with histology - Hoelsken, Annett; Schwarz, Marc; Gillmann, Clarissa; Pfister, Christina; Uder, Michael; Dörfler, Arnd; Buchfelder, Michael; Schlaffer, Sven-Martin; Fahlbusch, Rudolf; Buslei, Rolf; Bäuerle, Tobias (PLoS ONE, 2018)
PURPOSE: Adamantinomatous craniopharyngiomas (ACP) as benign sellar brain tumors are challenging to treat. In order to develop robust in vivo drug testing methodology, the murine orthotopic craniopharyngioma model (PDX) was characterized by magnetic resonance imaging (MRI) and histology in xenografts from three patients (ACP1-3). METHODS: In ACP PDX, multiparametric MRI was conducted to assess morphologic characteristics such as contrast-enhancing tumor volume (CETV) as well as functional parameters from dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI) including area-under-the-curve (AUC), peak enhancement (PE), time-to-peak (TTP) and apparent diffusion coefficient (ADC). These MRI parameters evaluated in 27 ACP PDX were correlated to histological features and percentage of vital tumor cell content. RESULTS: Qualitative analysis of MRI and histology from PDX revealed a similar phenotype as seen in patients, although the MRI appearance in mice resulted in a more solid tumor growth than in humans. CETV were significantly higher in ACP2 xenografts relative to ACP1 and ACP3 which correspond to respective average vitality of 41%, <10% and 26% determined histologically. Importantly, CETV prove tumor growth of ACP2 PDX as it significantly increases in longitudinal follow-up of 110 days. Furthermore, xenografts from ACP2 revealed a significantly higher AUC, PE and TTP in comparison to ACP3, and significantly increased ADC relative to ACP1 and ACP3 respectively. Overall, DCE-MRI and DWI can be used to distinguish vital from non-vital grafts, when using a cut off value of 15% for vital tumor cell content. CONCLUSIONS: MRI enables the assessment of craniopharyngioma PDX vitality in vivo as validated histologically.
EVALuna2:34588

Characterizing and targeting glioblastoma neuron-tumor networks with retrograde tracing - Tetzlaff, Svenja K.; Reyhan, Ekin; Layer, Nikolas; Bengtson, C. Peter; Heuer, Alina; Schroers, Julian; Faymonville, Anton J.; Langeroudi, Atefeh Pourkhalili; Drewa, Nina; Keifert, Elijah; Wagner, Julia; Soyka, Stella J.; et al. (Cell, 2025)
Glioblastomas are invasive brain tumors with high therapeutic resistance. Neuron-to-glioma synapses have been shown to promote glioblastoma progression. However, a characterization of tumor-connected neurons has been hampered by a lack of technologies. Here, we adapted retrograde tracing using rabies viruses to investigate and manipulate neuron-tumor networks. Glioblastoma rapidly integrated into neural circuits across the brain, engaging in widespread functional communication, with cholinergic neurons driving glioblastoma invasion. We uncovered patient-specific and tumor-cell-state-dependent differences in synaptogenic gene expression associated with neuron-tumor connectivity and subsequent invasiveness. Importantly, radiotherapy enhanced neuron-tumor connectivity by increased neuronal activity. In turn, simultaneous neuronal activity inhibition and radiotherapy showed increased therapeutic effects, indicative of a role for neuron-to-glioma synapses in contributing to therapeutic resistance. Lastly, rabies-mediated genetic ablation of tumor-connected neurons halted glioblastoma progression, offering a viral strategy to tackle glioblastoma. Together, this study provides a framework to comprehensively characterize neuron-tumor networks and target glioblastoma.
CRIS-Team Scopus Importer:2025-01-31
Keywords: brain tumor networks; brain tumors; cancer neuroscience; glioblastoma; invasion; neuron-to-glioma synapse; retrograde tracing; therapeutic rabies virus; therapeutic resistance

Chemical hybridization of sulfasalazine and dihydroartemisinin promotes brain tumor cell death - Ackermann, Annemarie; Capci Karagöz, Aysun; Buchfelder, Michael; Tsogoeva, Svetlana; Savaskan, Nicolai (Scientific Reports, 2021)
Gliomas are primary brain tumors with still poor prognosis for the patients despite a combination of cytoreduction via surgery followed by a radio-chemotherapy. One strategy to find effective treatment is to combine two different compounds in one hybrid molecule via linker to add to or at best potentiate their impact on malignant cells. Here, we report on the effects of a newly synthesized hybrid of sulfasalazine (SAS) and dihydroartemisinin (DHA), called AC254. In previous studies, both SAS and DHA have already proved to have anti-tumor properties themselves and to have sensitizing respectively potentiating effects on other treatments against malignant tumors. We investigated the impact of individual drugs SAS and DHA, their 1:1 combination and a novel SAS-DHA hybrid compound (AC254) on rodent and human glioma cells. In our study SAS alone showed no or only a mild effect on glioma, whereas DHA led to a significant reduction of cell viability in a dose-dependent manner. Next we compared the efficacy of the hybrid AC254 to the combinational treatment of its parent compounds SAS and DHA. The hybrid was highly efficient in combating glioma cells compared to single treatment strategies regarding cell viability and cell death. Interestingly, AC254 showed a remarkable advantage over the combinational treatment with both parent compounds in most used concentrations. In addition to its reduction of tumor cell viability and induction of cell death, the hybrid AC254 displayed changes in cell cycle and reduction of cell migration. Taken together, these results demonstrate that clinically established compounds such as SAS and DHA can be potentiated in their anti-cancer effects by chemical hybridization. Thus, this concept provides the opportunity to devise new effective chemotherapeutic agents.
CRIS-Team Scopus Importer:2021-11-05

Chemotherapeutic xCT inhibitors sorafenib and erastin unraveled with the synaptic optogenetic function analysis tool - Dahlmanns, Marc; Yakubov, Eduard; Chen, Daishi; Sehm, Tina; Rauh, Manfred; Savaskan, Nicolai; Wrosch, Jana Katharina (Cell Death Discovery, 2017)
In the search for new potential chemotherapeutics, the compounds' toxicity to healthy cells is an important factor. The brain with its functional units, the neurons, is especially endangered during the radio- and chemotherapeutic treatment of brain tumors. The effect of the potential compounds not only on neuronal survival but also neuronal function needs to be taken into account. Therefore, in this study we aimed to comprehend the biological effects of chemotherapeutic xCT inhibition on healthy neuronal cells with our synaptic optogenetic function analysis tool (SOFA). We combined common approaches, such as investigation of morphological markers, neuronal function and cell metabolism. The glutamate-cystine exchanger xCT (SLC7A11, system Xc-) is the main glutamate exporter in malignant brain tumors and as such a relevant drug target for treating deadly glioblastomas (WHO grades III and IV). Recently, two small molecules termed sorafenib (Nexavar) and erastin have been found to efficiently block xCT function. We investigated neuronal morphology, metabolic secretome profiles, synaptic function and cell metabolism of primary hippocampal cultures (containing neurons and glial cells) treated with sorafenib and erastin in clinically relevant concentrations. We found that sorafenib severely damaged neurons already after 24 h of treatment. Noteworthy, also at a lower concentration, where no morphological damage or metabolic disturbance was monitored, sorafenib still interfered with synaptic and metabolic homeostasis. In contrast, erastin-treated neurons displayed mostly inconspicuous morphology and metabolic rates. Key parameters of proper neuronal function, such as synaptic vesicle pool sizes, were however disrupted following erastin application. In conclusion, our data revealed that while sorafenib and erastin effectively inhibited xCT function they also interfered with essential neuronal (synaptic) function. These findings highlight the particular importance of investigating the effects of potential neurooncological and general cancer chemotherapeutics also on healthy neuronal cells and their function as revealed by the SOFA tool.
EVALuna2:33743

Classification of neurovascular compression in glossopharyngeal neuralgia: Three-dimensional visualization of the glossopharyngeal nerve - Tanrikulu, Levent; Hastreiter, Peter; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Surgical Neurology International, 2015)
Background: We introduce a method of noninvasive topographical analysis of the neurovascular relationships of the glossopharyngeal nerve (CN IX) by three-dimensional (3D) visualization. Patients with glossopharyngeal neuralgia (GN) resulting from neurovascular compression (NVC) were studied. Methods: 15 patients with GN were prospectively examined with 3D visualization using high-resolution magnetic resonance imaging with constructive interference in steady state (MR-CISS). The datasets were segmented and visualized with the real, individual neurovascular relationships by direct volume rendering. Segmentation and 3D visualization of the CN IX and corresponding blood vessels were performed. The 3D visualizations were interactively compared with the intraoperative setup during microvascular decompression (MVD) in order to verify the results by the observed surgical-anatomical findings. Results: 15 patients (female/male: 5/10) were examined. All of them underwent MVD (100%). Microvascular details were documented. The posterior inferior cerebellar artery (PICA) was the most common causative vessel in 12 of 15 patients (80%), the vertebral artery (VA) alone in one case (6.7%), and the combination of compression by the VA and PICA in 3 patients (13.3%). We identified three distinct types of NVC within the root entry zone of CN IX. Conclusion: 3D visualization by direct volume rendering of MR-CISS data offers the opportunity of noninvasive exploration and anatomical categorization of the CN IX. It proves to be advantageous in supporting to establish the diagnosis and microneurosurgical interventions by representing original, individual patient data in a 3D fashion. It provides an excellent global individual view over the entire neurovascular relationships of the brainstem and corresponding nerves in each case.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Classification; glossopharyngeal nerve; glossopharyngeal neuralgia; image processing; neurovascular compression

Classification of primary cerebral lymphoma and glioblastoma featuring dynamic susceptibility contrast and apparent diffusion coefficient - Eisenhut, Felix; Schmidt, Manuel; Putz, Florian; Lettmaier, Sebastian; Fröhlich, Kilian; Arinrad, Soheil; Coras, Roland; Lücking, Hannes; Lang, Stefan; Fietkau, Rainer; Dörfler, Arnd (Brain Sciences, 2020)
This study aimed to differentiate primary central nervous system lymphoma (PCNSL) and glioblastoma (GBM) via multimodal MRI featuring radiomic analysis. MRI data sets of patients with histological proven PCNSL and GBM were analyzed retrospectively. Diffusion-weighted imaging (DWI) and dynamic susceptibility contrast (DSC) perfusion imaging were evaluated to differentiate contrast enhancing intracerebral lesions. Selective (contrast enhanced tumor area with the highest mean cerebral blood volume (CBV) value) and unselective (contouring whole contrast enhanced lesion) Apparent diffusion coefficient (ADC) measurement was performed. By multivariate logistic regression, a multiparametric model was compiled and tested for its diagnostic strength. A total of 74 patients were included in our study. Selective and unselective mean and maximum ADC values, mean and maximum CBV and ratioCBV as quotient of tumor CBV and CBV in contralateral healthy white matter were significantly larger in patients with GBM than PCNSL; minimum CBV was significantly lower in GBM than in PCNSL. The highest AUC for discrimination of PCNSL and GBM was obtained for selective mean and maximum ADC, mean and maximum CBV and ratioCBV. By integrating these five in a multiparametric model 100% of the patients were classified correctly. The combination of perfusion imaging (CBV) and tumor hot-spot selective ADC measurement yields reliable radiological discrimination of PCNSL from GBM with highest accuracy and is readily available in clinical routine.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ADC; DSC; Glioblastoma; MRI; Multimodal; Primary central nervous system lymphoma

Clinical and therapeutic implications of cavernous sinus invasion in pituitary adenomas - Lefevre, Etienne; Chasseloup, Fanny; Hage, Mirella; Chanson, Philippe; Buchfelder, Michael; Kamenický, Peter (Endocrine, 2024)
Invasion of the cavernous sinus by pituitary adenomas impedes complete surgical resection, compromises biochemical remission, and increases the risk of further tumor recurrence. Accurate preoperative MRI-based diagnosis or intraoperative direct inspection of cavernous sinus invasion are essential for optimal surgical planning and for tailoring postoperative therapeutic strategies, depending on whether a total resection has been achieved, or tumoral tissue has been left in surgically inaccessible locations. The molecular mechanisms underlying the invasive behavior of pituitary adenomas remain poorly understood, hindering the development of targeted therapies. Some studies have identified genes overexpressed in pituitary adenomas invading the cavernous sinus, offering insights into the acquisition of invasive behavior. Their main limitation however lies in comparing purely intrasellar specimens obtained from invasive and non-invasive adenomas. Further, precise anatomical knowledge of the medial wall of the cavernous sinus is crucial for grasping the mechanisms of invasion. Recently, alongside the standard intrasellar surgery, extended endoscopic intracavernous surgical procedures with systematic selective resection of the medial wall of the cavernous sinus have shown promising results for invasive secreting pituitary adenomas. The first- and second-generation somatostatin agonist ligands and cabergoline are used with variable efficacy to control secretory activity and/or growth of intracavernous remnants. Tumor regrowth usually requires surgical reintervention, sometimes combined with radiotherapy or radiosurgery which is applied despite their benign nature. Unraveling the molecular pathways driving invasive behavior of pituitary adenomas and their tropism to the cavernous sinuses is the key for developing efficient innovative treatment modalities that could reduce the need for repeated surgery or radiotherapy.
CRIS-Team Scopus Importer:2024-05-24

Clinical Comparison of FD-CT and MS-CT in Aneurysmal Subarachnoid Haemorrhage: A Single Center Experience - Eisenhut, Felix; Heidelbach, Cornelius; Heynold, Elisabeth; Manhart, Michael; Struffert, Tobias; Brandner, Sebastian; Dörfler, Arnd; Lang, Stefan (Diagnostics, 2022)
Single-center comparison of postinterventional multislice computed tomography (MS-CT) and flat-detector computed tomography (FD-CT) in patients with subarachnoid haemorrhage (SAH) and endovascularly treated cerebral aneurysms with a focus on detection of posttherapeutical complications. Patients with endovascularly treated aneurysmal SAH undergoing both MS-CT and FD-CT within 24 h after intervention were included. Datasets were compared regarding image quality (IQ) as well as qualitative (detection of SAH, intracerebral haemorrhage [ICH], intraventricular haemorrhage [IVH], external ventricular drain [EVD] position, acute obstructive hydrocephalus [AOH]) and quantitative (cella media distance [CMD], modified Graeb score [GS]) parameters. 410 patients with endovascularly treated aneurysmal SAH were included. IQ was equal between MS-CT and FD-CT. FD-CT allowed equal detection of SAH and ICH in comparison to MS-CT. FD-CT allowed excellent detection of IVH and delineation of EVD position with strong agreement to MS-CT findings. FD-CT allowed equal detection of AOH in comparison to MS-CT. There was no significant difference of CMD and GS between FD-CT and MS-CT. Postinterventional FD-CT yields equivalent diagnostic value in patients with endovascular treated SAH as MS-CT. Enabling reliable detection of SAH-associated complications within the angiosuite, FD-CT might be an efficient and safe imaging modality in these clinical emergencies.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cerebral aneurysm; endovascular treatment; flat-detector computed tomography; multislice computed tomography; subarachnoid haemorrhage

Clinical Course Score (CCS): a new clinical score to evaluate efficacy of neurotrauma treatment in traumatic brain injury and subarachnoid hemorrhage - Brandner, Sebastian; Kellermann, Isabel; Hore, Nirjhar; Bozhkov, Yavor; Buchfelder, Michael (Journal of Neurosurgical Anesthesiology, 2015)
Neurotrauma continues to represent a challenging public health issue requiring continual improvement in therapeutic approaches. As no such current system exists, we present in this study the Clinical Course Score (CCS) as a new clinical score to evaluate the efficacy of neurotrauma treatment.The CCS was calculated in neurotrauma patients to be the difference between the grade of the Glasgow Outcome Scale 6 months after discharge from our department and the grade of a 1 to 5 point reduced Glasgow Coma Scale on admission. We assessed the CCS in a total of 248 patients (196 traumatic brain injury [TBI] patients and 52 subarachnoid hemorrhage [SAH] patients) who were treated in our Department of Neurosurgery between January 2011 and December 2012.We found negative CCS grades both in mild TBI and in mild SAH patients. In patients with severe TBI or SAH, we found positive CCS grades. In SAH patients, we found higher CCS scores in younger patients compared with elderly subjects in both mild and severe cases.The CCS can be useful in evaluating different therapeutic approaches during neurotrauma therapy. This new score might improve assessment of beneficial effects of therapeutic procedures.
EVALuna2:22862

Clinical Evaluation of an Innovative Metal-Artifact-Reduction Algorithm in FD-CT Angiography in Cerebral Aneurysms Treated by Endovascular Coiling or Surgical Clipping - Eisenhut, Felix; Schmidt, Manuel; Kalik, Alexander; Struffert, Tobias; Feulner, Julian; Schlaffer, Sven-Martin; Manhart, Michael; Dörfler, Arnd; Lang, Stefan (Diagnostics, 2022)
Treated cerebral aneurysms (IA) require follow-up imaging to ensure occlusion. Metal artifacts complicate radiologic assessment. Our aim was to evaluate an innovative metal-artifact-reduction (iMAR) algorithm for flat-detector computed tomography angiography (FD-CTA) regarding image quality (IQ) and detection of aneurysm residua/reperfusion in comparison to 2D digital subtraction angiography (DSA). Patients with IAs treated by endovascular coiling or clipping underwent both FD-CTA and DSA. FD-CTA datasets were postprocessed with/without iMAR algorithm (MAR+/MAR−). Evaluation of all FD-CTA and DSA datasets regarding qualitative (IQ, MAR) and quantitative (coil package diameter/CPD) parameters was performed. Aneurysm occlusion was assessed for each dataset and compared to DSA findings. In total, 40 IAs were analyzed (ncoiling = 24; nclipping = 16). All iMAR+ datasets demonstrated significantly better IQ (pIQ coiling < 0.0001; pIQ clipping < 0.0001). iMAR significantly reduced the metal-artifact burden but did not affect the CPD. iMAR significantly improved the detection of aneurysm residua/reperfusion with excellent agreement with DSA (naneurysm detection MAR+/MAR−/DSA = 22/1/26). The iMAR algorithm significantly improves IQ by effective reduction of metal artifacts in FD-CTA datasets. The proposed algorithm enables reliable detection of aneurysm residua/reperfusion with good agreement to DSA. Thus, iMAR can help to reduce the need for invasive follow-up in treated IAs.
CRIS-Team Scopus Importer:2022-05-27
Keywords: cerebral aneurysm; endovascular coiling; flat-detector computed tomography angiography; metal-artifact-reduction algorithm; surgical clipping

Clinical relevance of source location in frontal lobe epilepsy and prediction of postoperative long-term outcome - Mu, Jie; Rampp, Stefan; Carrette, Evelien; Roessler, Karl; Sommer, Bjoern; Schmitt, Friedhelm Carl; De Tiege, Xavier; Hamer, Hajo; Boon, Paul; Pauli, Elisabeth; Blümcke, Ingmar; Zhou, Dong; et al. (Seizure-European Journal of Epilepsy, 2014)
To evaluate the value of magnetoencephalography (MEG) source localization in localization of epileptic activities and predicting surgical outcome in frontal lobe epilepsies (FLE).Forty-six patients with presurgical MEG evaluation and intractable FLE surgery (28 male patients) were analyzed retrospectively with a mean follow-up of 5 years. Dipole analysis was performed for MEG source imaging (MSI). The localization of dipole clusters in relation to the dominant hemisphere, lesions, resection cavity and functional cortex were analyzed. The predictive value of MSI in respect to clinical outcome with long-term postoperative follow up was evaluated.Interictal focal epileptic activities were found in 82.6% (38/46) patients with monofocal activity 81.6% (31/38) and multifocal activities 18.4% (7/38). Seizure free rate was 47.9% at the mean follow-up of 5.0 ± 4.0 years (median 11.5, range 2-57). Seizure recurrence mainly occurred in the first 1 year after surgery. In the monofocal epileptic activity group, 58.1% (18/31) of the patients were seizure free, predicitng postoperative seizure freedom better than multifocal localization 0% (0/7) (p=0.028). Dipole clusters were completely resected in 70.9% of monofocal activity patients, which had higher seizure free rates compared to partial resection (p=0.002). In patients with surgery in the dominant hemisphere, seizure control was less likely (p=0.006).MSI contributes to the clinical prediction of postoperative outcome in FLE patients. MSI may non-invasively disclose early epileptogenic lesions, pointing to a resectable lesion, and it then facilitates shortcut route of presurgical evaluation.
EVALuna2:7256

Clinical Results and Quality of Life After Transcortical Versus Transcallosal Resection of Adult Lateral and Third Ventricle Lesions: Long-Term Outcome - AlSharif, Mustafa; Stroop, Ralf; Scholz, Martin; Buchfelder, Michael; Wiendieck, Kurt; Shiban, Ehab; Sommer, Björn (World Neurosurgery, 2023)
Background: Resection of intraventricular tumors can be achieved using 2 main operative approaches: transcallosal or transcortical. This study aims to describe preoperative and postoperative factors as well as quality of life (QoL) based on long-term results in these patients. Methods: Patients underwent surgery of primary intraventricular lesions between 2007 and 2020 via a transcortical (group A) or transcallosal (group B) route. The main clinical parameters were completeness of resection, overall survival, surgical complications, postoperative neurologic deficits, and seizure rates. QoL was assessed using a modified questionnaire Short-Form 36 inventory. Results: Forty patients (19 women and 21 men) met the inclusion criteria. Group A consisted of 26 patients (12 women and 14 men; median age 45.5 years ± 16.7 standard deviation) and had lower preoperative tumor volume (confounder) compared with group B (7 women and 7 men; age 50.0 ± 17.4 years). Gross total resection was achieved in 65% in group A and 71% in group B. Follow-up was 7.8 ± 3.9 years. New seizures/permanent neurologic deficits occurred in 27%/15% (group A) and 29%/29% (group B) and surgical complications in 23% of patients. Group B had a higher degree of memory impairment (21%) compared with group A (10%). QoL impairment was present in both groups mainly regarding physical role function and mental health index. Conclusions: Keeping in mind the limitations, transcallosal surgery was associated with a higher probability of neurologic deficits and memory impairment in our series. However, it had fewer surgical complications with similar gross total resection and seizure rates.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Functional outcome; Morbidity; Quality of life; Surgical approach; Ventricle tumor

Clipping of unruptured cerebral aneurysms: Are older patients at higher risk? - Winter, Fabian; Markert, Celia; Krawagna, Maximilian; Buchfelder, Michael; Rössler, Karl (Wiener Klinische Wochenschrift, 2021)
Background: The incidence of aneurysms is steadily increasing in older patients due to the aging population. This study compared radiological parameters as well as clinical outcomes between patients younger than 65 years and those over 65 years of age, with special respect to individual treatment options. Methods: Retrospective data were obtained for patients with cerebral aneurysms at a single academic institution within a 7-year period. Data reviewed included admission protocols, patient charts, operating reports as well as outpatient clinic charts. Aneurysmal characteristics as well as surgical outcome were compared between older patients, defined as patients older than 65 years of age, and a control group of patients younger than 65 years of age. To evaluate and compare individual clinical characteristics various scores including the Hunt and Hess score, the Fisher score, and the Glasgow outcome scale were used. Results: A total of 347 patients were included in the final analysis. The control group included 290 patients, while 57 patients were in the older patient group. Neither the Hunt and Hess scores nor Fisher scores were significantly correlated to patient age. The Glasgow outcome scale was significantly lower in the older group after clipping of ruptured aneurysms (p < 0.000) but not significantly different after clipping of unruptured aneurysms (p = 0.793). Conclusion: Postoperative Glasgow outcome scale scores were not significantly different after clipping of unruptured cerebral aneurysms approximately 1 cm in diameter in older patients compared to the younger age group. Therefore, clipping of unruptured cerebral aneurysms may also be a valuable treatment option for older patients.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Coiling; Elderly; Neurosurgery; Outcome; Vascular

Clustering-Based Model Reduction for Glioma Graph Networks - Mlinarić, P.; Sokolikj, Z.; Talla, G.; Meyer-Baese, U.; Stadlbauer, Andreas; Malberg, H.; Na, C. H.; Juetten, K.; Wiestler, B.; Meyer-Baese, A. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
We analyze structural and functional connectivity graphs for both healthy and glioma subjects by clustering-based model reduction to obtain a detailed understanding of these complex graphs. The reduced-order network is obtained by dividing the connected brain regions or nodes into disjoint clusters. Further, each cluster is replaced by a single new node in a reduced-size graph network. Several partitions are analyzed and evaluated based on model reduction errors.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Glioma; graph clustering; network systems; reduced-order modeling; structure-preserving

Combined EEG/MEG can outperform single modality EEG or MEG source reconstruction in presurgical epilepsy diagnosis - Aydin, Uemit; Vorwerk, Johannes; Duempelmann, Matthias; Kuepper, Philipp; Kugel, Harald; Heers, Marcel; Wellmer, Joerg; Kellinghaus, Christoph; Haueisen, Jens; Rampp, Stefan; Stefan, Hermann; Wolters, Carsten H. (PLoS ONE, 2015)
We investigated two important means for improving source reconstruction in presurgical epilepsy diagnosis. The first investigation is about the optimal choice of the number of epileptic spikes in averaging to (1) sufficiently reduce the noise bias for an accurate determination of the center of gravity of the epileptic activity and (2) still get an estimation of the extent of the irritative zone. The second study focuses on the differences in single modality EEG (80-electrodes) or MEG (275-gradiometers) and especially on the benefits of combined EEG/MEG (EMEG) source analysis. Both investigations were validated with simultaneous stereo-EEG (sEEG) (167-contacts) and low-density EEG (ldEEG) (21-electrodes). To account for the different sensitivity profiles of EEG and MEG, we constructed a six-compartment finite element head model with anisotropic white matter conductivity, and calibrated the skull conductivity via somatosensory evoked responses. Our results show that, unlike single modality EEG or MEG, combined EMEG uses the complementary information of both modalities and thereby allows accurate source reconstructions also at early instants in time (epileptic spike onset), i.e., time points with low SNR, which are not yet subject to propagation and thus supposed to be closer to the origin of the epileptic activity. EMEG is furthermore able to reveal the propagation pathway at later time points in agreement with sEEG, while EEG or MEG alone reconstructed only parts of it. Subaveraging provides important and accurate information about both the center of gravity and the extent of the epileptogenic tissue that neither single nor grand-averaged spike localizations can supply.
EVALuna2:22410

Combined EEG/MEG source reconstruction of epileptic activity using a two-phase spike clustering approach - Dimakopoulos, Vasileios S.; Antonakakis, Marios; Moeddel, Gabriel; Wellmer, Jorg; Rampp, Stefan; Zervakis, Michalis; Wolters, Carsten H. (Proceedings - 2019 IEEE 19th International Conference on Bioinformatics and Bioengineering, BIBE 2019, 2019)
In recent years, several approaches have been introduced for estimating the spike onset zone within the irritative zone in epilepsy diagnosis for presurgical planning. One important direction utilizes source analysis from combined electroencephalography (EEG) and magnetoencephalography (MEG), EMEG, leveraging the benefits from the complementary properties of the two modalities. For EMEG source reconstruction, an average across the annotated epileptic spikes is often used to improve the signal-to-noise-ratio (SNR). In this contribution, we propose a two-phase clustering of interictal spikes with unsupervised learning methods, namely Self Organizing Maps (SOM) and K-means. In addition, we investigate the accuracy of combined EMEG source analysis on the sorted activity, using an individualized (with regard to both geometry and conductivity) six-compartment finite element head model with calibrated skull conductivity and white matter conductivity anisotropy. The results indicate that SOM eliminates the random variations of K-means and stabilizes the clustering efficiency. In terms of source reconstruction accuracy, this study demonstrates that the combined use of modalities reveals activity around two focal cortical dysplasias (FCDs), of one epilepsy patient, one in the right frontal area and one smaller in the left premotor cortex. It is worth mentioning that only EMEG could localize the left premotor FCD, which was then also found in surgery to be the responsible for triggering the epilepsy.
CRIS-Team Scopus Importer:2020-02-21
Keywords: EEG; Epilepsy; Finite Element Method; MEG; Multimodal Imaging; Spike Clustering

Combined Laser-Doppler Flowmetry and Spectrophotometry: Feasibility Study of a Novel Device for Monitoring Local Cortical Microcirculation during Aneurysm Surgery - Sommer, Bjoern; Kreuzer, Maximilian; Bischoff, Barbara; Wolf, Dennis; Schmitt, Hubert; Eyüpoglu, Ilker Yasin; Roessler, Karl; Buchfelder, Michael; Ganslandt, Oliver Thomas; Wiendieck, Kurt (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Monitoring of cortical cerebral perfusion is essential, especially in neurovascular surgery. Study Aims To test a novel noninvasive laser-Doppler flowmetry and spectrophotometry device for feasibility during elective cerebral aneurysm surgery. Material and Methods In this prospective single-institution nonrandomized trial, we studied local cerebral microcirculation using the noninvasive laser-Doppler spectrophotometer "Oxygen-to-see" (O2C) in 20 consecutive patients (15 female, 5 male; median age: 60.5 ± 11.7 years) who were operated on for incidental cerebral aneurysms. Capillary-venous oxygenation (oxygen saturation ["SO2"]), postcapillary venous filling pressures (relative hemoglobin content ["rHb"]), blood cell velocity ("velo"), and blood flow ("flow") were measured in 7-mm tissue depth using a subdural fiberoptic probe. Results Representative recordings were acquired immediately after dural opening over a median time span of 88 ± 21.8 seconds (range: 60-128 seconds) before surgical manipulation. Baseline values (median ± 2 standard deviations) of brain perfusion as measured with the O2C device were SO2, 39 ± 16.6%; rHb, 53 ± 18.6 arbitrary units (AU); velo, 60 ± 20.4 AU; and flow, 311 ± 72.8 AU. Placement of the self-retaining retractor led to a decrease in SO2 of 17% ± 29% (p < .05) and flow of 10% ± 11% (p < .01); rHb increased by 18% ± 20% (p < .01), and velo remained unchanged. Retractor removal caused the opposite with an increased flow of 10% ± 7% (p < 0.001) and velo (3% ± 6%, p = 0.11), but a decrease in SO2 of 24% ± 33% (p = 0.09) and rHb of 12% ± 20% (p =0.18). No neurologic or surgical complications occurred. Conclusion Using this novel noninvasive system, we were able to measure local cerebral microcirculation during aneurysm surgery. Our data indicate that this device is able to detect changes during routine neurosurgical maneuvers. Thus it may be useful for early detection of cerebral microcirculatory disturbance
EVALuna2:16739

Combining EEG and MEG for the reconstruction of epileptic activity using a calibrated realistic volume conductor model - Aydin, Uemit; Vorwerk, Johannes; Kuepper, Philipp; Heers, Marcel; Kugel, Harald; Galka, Andreas; Hamid, Laith; Wellmer, Joerg; Kellinghaus, Christoph; Rampp, Stefan; Wolters, Carsten Hermann (PLoS ONE, 2014)
To increase the reliability for the non-invasive determination of the irritative zone in presurgical epilepsy diagnosis, we introduce here a new experimental and methodological source analysis pipeline that combines the complementary information in EEG and MEG, and apply it to data from a patient, suffering from refractory focal epilepsy. Skull conductivity parameters in a six compartment finite element head model with brain anisotropy, constructed from individual MRI data, are estimated in a calibration procedure using somatosensory evoked potential (SEP) and field (SEF) data. These data are measured in a single run before acquisition of further runs of spontaneous epileptic activity. Our results show that even for single interictal spikes, volume conduction effects dominate over noise and need to be taken into account for accurate source analysis. While cerebrospinal fluid and brain anisotropy influence both modalities, only EEG is sensitive to skull conductivity and conductivity calibration significantly reduces the difference in especially depth localization of both modalities, emphasizing its importance for combining EEG and MEG source analysis. On the other hand, localization differences which are due to the distinct sensitivity profiles of EEG and MEG persist. In case of a moderate error in skull conductivity, combined source analysis results can still profit from the different sensitivity profiles of EEG and MEG to accurately determine location, orientation and strength of the underlying sources. On the other side, significant errors in skull modeling are reflected in EEG reconstruction errors and could reduce the goodness of fit to combined datasets. For combined EEG and MEG source analysis, we therefore recommend calibrating skull conductivity using additionally acquired SEP/SEF data.
EVALuna2:22291

Comment on Microsurgical therapy of pituitary adenomas - Buchfelder, Michael (Endocrine, 2018)
EVALuna2:214801

Comparative fMRI and MEG localization of cortical sensorimotor function: Bimodal mapping supports motor area reorganization in glioma patients - Zimmermann, Max; Roessler, Karl; Kaltenhaeuser, Martin; Grummich, Peter; Brandner, Nadja; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (PLoS ONE, 2019)
Introduction
CRIS-Team WoS Importer:2019-03-26

Comparing 1.5 T and 3.0 T MR data for 3D visualization of neurovascular relationships in the posterior fossa - Hastreiter, Peter; Maliachova, Olga; Fahlbusch, Rudolf; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Acta Neurochirurgica, 2023)
Background: Neurovascular relationships in the posterior fossa are more frequently investigated due to the increasing availability of 3.0 Tesla MRI. For an assessment with 3D visualization, no systematic analyzes are available so far and the question arises as to whether 3.0 Tesla MRI should be given preference over 1.5 Tesla MRI. Methods: In a prospective study, a series of 25 patients each underwent MRI investigations with 3D-CISS and 3D-TOF at 1.5 and 3.0 Tesla. For both field strengths separately, blood vessel information from the TOF data was fused into the CISS data after segmentation and registration. Four visualizations were created for each field strength, with and without optimization before and after fusion, which were evaluated with a rating system and verified with the intraoperative situation. Results: When only CISS data was used, nerves and vessels were better visualized at 1.5 Tesla. After fusion, flow and pulsation artifacts were reduced in both cases, missing vessel sections were supplemented at 3.0 Tesla and 3D visualization at 1.5 and 3.0 Tesla led to anatomically comparable results. By subsequent manual correction, the remaining artifacts were further eliminated, with the 3D visualization being significantly better at 3.0 Tesla, since the higher field strength led to sharper contours of small vessel and nerve structures. Conclusion: 3D visualizations at 1.5 Tesla are sufficiently detailed for planning microvascular decompression and can be used without restriction. Fusion further improves the quality of 3D visualization at 3.0 Tesla and enables an even more accurate delineation of cranial nerves and vessels.
CRIS-Team Scopus Importer:2023-12-29
Keywords: 1.5 and 3.0 Tesla; 3D Visualization; Compression syndromes; Data fusion; Neurovascular relationships; Posterior fossa

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (Journal of Alzheimer's Disease, 2016)
Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples.To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers.Three matrices were validated in this study: (A) human pooled CSF, (B) A? peptides spiked into human prediluted plasma, and (C) A? peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study.NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects.Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
EVALuna2:23767

Comparison of the Ramirez technique for the closure of large open myelomeningocele defects with alternative methods - Kneser, Ulrich; Bigdeli, Amir K.; Himmler, Joerg P.; Eyüpoglu, Ilker Yasin; Ganslandt, Oliver Thomas; Hirsch, Almut; Schmidt, Volker J.; Beier, Justus; Horch, Raymund E. (Journal of Plastic Reconstructive and Aesthetic Surgery, 2015)
To compare the Ramirez technique for the operative closure of large open myelomeningocele defects with conventional closure techniques in newborns. We hypothesized that the immediate surgical treatment with the Ramirez technique is superior to prior used operative techniques.From 2003 to 2010, 23 children (8 female, 15 male) underwent closure of large open myelomeningocele defects using the Ramirez technique (group A), while from 1993 to 2002, 23 children (6 female, 17 male) underwent conventional closure techniques (group B). All children were included in the retrospective analysis with a mean follow-up period of 3.4 years.Perioperative variables were similar in both groups (P = ns). There were no hospital deaths in both groups. The operation time was significantly higher in group A (228.7 ± 76.8 versus 157.8 ± 70.3 min, P = 0.003). Mean length of hospital stay was significantly lower in group A (30.7 ± 16.4 days versus 52.0 ± 38.5; P = 0.02). Postoperative complication rate was significantly lower in group A (P = 0.01). Beyond postoperative day 10, liquor fluid leakage was significantly lower in group A (P = 0.05). During follow-up, there were no complications in group A. In group B, 2 children developed liquor fistulas.The Ramirez technique allows efficient and safe closure of large open myelomeningocele defects and reduces incidence of postoperative liquor fistulae. The increased operation time and surgical efforts seem to be justified. Treatment of large myelomeningocele defects requires an interdisciplinary team including paediatrician-neonatologists, neurosurgeons and plastic surgeons.
EVALuna2:15600

Competency-based EEG education: a list of “must-know” EEG findings for adult and child neurology residents Competency-based EEG education: a list of "must-know" EEG findings for adult and child neurology residents - Nascimento, Fábio A.; Jing, Jin; Strowd, Roy; Sheikh, Irfan S.; Weber, Dan; Gavvala, Jay R.; Maheshwari, Atul; Tanner, Adriana; Ng, Marcus; Vinayan, K. P.; Sinha, Saurabh R.; Yacubian, Elza M.; et al. (Epileptic Disorders, 2022)
CRIS-Team Scopus Importer:2022-08-12

Complicated Clinical Course in Incipient Gigantism Due to Treatment-resistant Aryl Hydrocarbon Receptor–Interacting Protein–mutated Pediatric Somatotropinoma - van Santen, Selveta Sanne; Daly, Adrian F.; Buchfelder, Michael; Coras, Roland; Zhao, Yining; Beckers, Albert; van der Lely, Aart Jan; Hofland, Leo J.; Balvers, Rutger K.; van Koetsveld, P.; van den Heuvel-Eibrink, Marry Marrigje; Neggers, Sebastian Johannes Cornelis Martinus Maria (AACE Clinical Case Reports, 2022)
Background: Our objective was to describe the clinical course and treatment challenges in a very young patient with a pituitary adenoma due to a novel aryl hydrocarbon receptor–interacting protein (AIP) gene mutation, highlighting the limitations of somatostatin receptor immunohistochemistry to predict clinical responses to somatostatin analogs in acromegaly. Case Report: We report the case of a 7-year-old boy presenting with headache, visual field defects, and accelerated growth following failure to thrive. The laboratory results showed high insulin-like growth factor I (IGF-I) (standardised deviation scores (+3.49) and prolactin levels (0.5 nmol/L), and magnetic resonance imaging identified a pituitary macroadenoma. Tumoral/hormonal control could not be achieved despite 3 neurosurgical procedures, each time with apparent total resection or with lanreotide or pasireotide. IGF-I levels decreased with the GH receptor antagonist pegvisomant. The loss of somatostatin receptor 5 was observed between the second and third tumor resection. In vitro, no effect on tumoral GH release by pasireotide (with/without cabergoline) was observed. Genetic analysis revealed a novel germline AIP mutation: p.Tyr202∗ (pathogenic; class 4). Discussion: In vitro response of tumor tissue to somatostatin may better predict tumoral in vivo responses of somatostatin analogs than somatostatin receptor immunohistochemistry. Conclusion: We identified a novel pathologic AIP mutation that was associated with incipient acrogigantism in an extremely young patient who had a complicated course of disease. Growth acceleration can be masked due to failure to thrive. Tumoral growth hormone release in vivo may be predicted with in vitro exposure to somatostatin receptor analogs, as it cannot be assumed that all AIP-mutated somatotropinomas respond well to pasireotide.
CRIS-Team Scopus Importer:2022-02-11
Keywords: acromegaly; AIP mutation; gigantism; macroadenoma; pituitary adenoma; somatotropinoma

Comprehensive 7 T CEST: A clinical MRI protocol covering multiple exchange rate regimes - Fabian, Moritz; Rajput, Junaid Rasool; Schüre, Jan-Rüdiger; Weinmüller, Simon; Mennecke, Angelika; Möhle, Tim Alexius; Rampp, Stefan; Schmidt, Manuel; Dörfler, Arnd; Zaiß, Moritz (NMR in Biomedicine, 2024)
SECTIONSPDFPDFTOOLS SHARE Abstract Chemical exchange saturation transfer (CEST) is a magnetic resonance (MR) imaging method providing molecular image contrasts based on indirect detection of low concentrated solutes. Previous CEST studies focused predominantly on the imaging of single CEST exchange regimes (e.g., slow, intermediate or fast exchanging groups). In this work, we aim to establish a so-called comprehensive CEST protocol for 7 T, covering the different exchange regimes by three saturation B1 amplitude regimes: low, intermediate and high. We used the results of previous publications and our own simulations in pulseq-CEST to produce a 7 T CEST protocol that has sensitivity to these three B1 regimes. With postprocessing optimization (simultaneous mapping of water shift and B1, B0-fitting, multiple interleaved mode saturation B1 correction, neural network employment (deepCEST) and analytical input feature reduction), we are able to shorten our initially 40 min protocol to 15 min and generate six CEST contrast maps simultaneously. With this protocol, we measured four healthy subjects and one patient with a brain tumor. We established a comprehensive CEST protocol for clinical 7 T MRI, covering three different B1 amplitude regimes. We were able to reduce the acquisition time significantly by more than 50%, while still maintaining decent image quality and contrast in healthy subjects and one patient with a tumor. Our protocol paves the way to perform comprehensive CEST studies in clinical scan times for hypothesis generation regarding molecular properties of certain pathologies, for example, ischemic stroke or high-grade brain tumour

Comprehensive genetic profiling and molecularly guided treatment for patients with primary CNS tumors - Kuehn, Julia C.; Metzger, Patrick; Neidert, Nicolas; Matysiak, Uta; Gräßel, Linda; Philipp, Ulrike; Bleul, Sabine; Pauli, Thomas; Falkenstein, Julia; Bertemes, Henriette; Cysar, Stepan; Hess, Maria Elena; et al. (npj Precision Oncology, 2024)
Despite major advances in molecular profiling and classification of primary brain tumors, personalized treatment remains limited for most patients. Here, we explored the feasibility of individual molecular profiling and the efficacy of biomarker-guided therapy for adult patients with primary brain cancers in the real-world setting within the molecular tumor board Freiburg, Germany. We analyzed genetic profiles, personalized treatment recommendations, and clinical outcomes of 102 patients with 21 brain tumor types. Alterations in the cell cycle, BRAF, and mTOR pathways most frequently led to personalized treatment recommendations. Molecularly informed therapies were recommended in 71% and implemented in 32% of patients with completed molecular diagnostics. The disease control rate following targeted treatment was 50% and the overall response rate was 30%, with a progression-free survival 2/1 ratio of at least 1.3 in 31% of patients. This study highlights the efficacy of molecularly guided treatment and the need for biomarker-stratified trials in brain cancers.
CRIS-Team Scopus Importer:2024-09-06

Comprehensive Multimodal Deep Learning Survival Prediction Enabled by a Transformer Architecture: A Multicenter Study in Glioblastoma - Gomaa, Ahmed; Huang, Yixing; Hagag, Amr; Schmitter, Charlotte; Höfler, Daniel; Weissmann, Thomas; Breininger, Katharina; Schmidt, Manuel; Stritzelberger, Jenny; Delev, Daniel; Coras, Roland; Dörfler, Arnd; et al. (Neuro-Oncology Advances, 2024)
Keywords: Survival prediction; deep learning; glioblastoma; MR; prognosis; multimodal data

Consequences of EEG electrode position error on ultimate beamformer source reconstruction performance - Dalal, Sarang S.; Rampp, Stefan; Willomitzer, Florian; Ettl, Svenja (Frontiers in Neuroscience, 2014)
Inaccuracy of EEG electrode coordinates forms an error term in forward model generation and ultimate source reconstruction performance. This error arises from the combination of both intrinsic measurement noise of the digitization apparatus and manual coregistration error when selecting corresponding points on anatomical MRI volumes. A common assumption is that such an error would lead only to displacement of localized sources. Here, we measured electrode positions on a 3D-printed full-scale replica head, using three different techniques: a fringe projection 3D scanner, a novel "Flying Triangulation" 3D sensor, and a traditional electromagnetic digitizer. Using highly accurate fringe projection data as ground truth, the Flying Triangulation sensor had a mean error of 1.5 mm while the electromagnetic digitizer had a mean error of 6.8 mm. Then, again using the fringe projection as ground truth, individual EEG simulations were generated, with source locations across the brain space and a range of sensor noise levels. The simulated datasets were then processed using a beamformer in conjunction with the electrode coordinates registered with the Flying Triangulation and electromagnetic digitizer methods. The beamformer's output SNR was severely degraded with the digitizer-based positions but less severely with the Flying Triangulation coordinates. Therefore, the seemingly innocuous error in electrode registration may result in substantial degradation of beamformer performance, with output SNR penalties up to several decibels. In the case of low-SNR signals such as deeper brain structures or gamma band sources, this implies that sensor coregistration accuracy could make the difference between successful detection of such activity or complete failure to resolve the source.
EVALuna2:22315

Continued progress in DICOM neurophysiology standardization - Halford, Jonathan J.; Brinkmann, Benjamin H.; Clunie, David A.; Gotman, Jean; Beniczky, Sándor; Rampp, Stefan; Rémi, Jan; Husain, Aatif; Andrew Ehrenberg, J.; Winkler, Silvia (Clinical Neurophysiology, 2023)
CRIS-Team Scopus Importer:2023-01-20
Keywords: DICOM; Electroencephalogram; Electromyogram; Electrooculogram; Polysomnogram; Standards

Controllability and Robustness of Functional and Structural Connectomic Networks in Glioma Patients - Meyer-Baese, Anke; Jütten, Kerstin; Meyer-Baese, Uwe; Amani, Ali Moradi; Malberg, Hagen; Stadlbauer, Andreas; Kinfe, Thomas Mehari; Na, Chuh Hyoun (Cancers, 2023)
Previous studies suggest that the topological properties of structural and functional neural networks in glioma patients are altered beyond the tumor location. These alterations are due to the dynamic interactions with large-scale neural circuits. Understanding and describing these interactions may be an important step towards deciphering glioma disease evolution. In this study, we analyze structural and functional brain networks in terms of determining the correlation between network robustness and topological features regarding the default-mode network (DMN), comparing prognostically differing patient groups to healthy controls. We determine the driver nodes of these networks, which are receptive to outside signals, and the critical nodes as the most important elements for controllability since their removal will dramatically affect network controllability. Our results suggest that network controllability and robustness of the DMN is decreased in glioma patients. We found losses of driver and critical nodes in patients, especially in the prognostically less favorable IDH wildtype (IDHwt) patients, which might reflect lesion-induced network disintegration. On the other hand, topological shifts of driver and critical nodes, and even increases in the number of critical nodes, were observed mainly in IDH mutated (IDHmut) patients, which might relate to varying degrees of network plasticity accompanying the chronic disease course in some of the patients, depending on tumor growth dynamics. We hereby implement a novel approach for further exploring disease evolution in brain cancer under the aspects of neural network controllability and robustness in glioma patients.
CRIS-Team Scopus Importer:2023-06-09
Keywords: controllability; critical nodes; driver set; glioma; robustness; structural and functional connectomics

Controllability of Functional and Structural Brain Networks - Amani, Ali Moradi; Tahmassebi, Amirhessam; Stadlbauer, Andreas; Meyer-Baese, Uwe; Noblet, Vincent; Blanc, Frederic; Malberg, Hagen; Meyer-Baese, Anke (Complexity, 2024)
Normal and aberrant cognitive functions are the result of the dynamic interplay between large-scale neural circuits. Describing the nature of these interactions has been a challenging task yet important for neurodegenerative disease evolution. Fusing modern dynamic graph network theory techniques and control theory applied on complex brain networks creates a new framework for neurodegenerative disease research by determining disease evolution at the subject level, facilitating a predictive treatment response and revealing key mechanisms responsible for disease alterations. It has been shown that two types of controllability—the average and the modal controllability—are relevant for the mechanistic explanation of how the brain navigates between cognitive states. Te average controllability favors highly connected areas which move the brain to easily reachable states, while the modal controllability favors weakly connected areas representative for difcult-to-reach states. We propose two different techniques to achieve these two types of controllability: a centrality measure based on a sensitivity analysis of the Laplacian matrix is employed to determine the average controllability, while graph distances form the basis of the modal controllability. Te concepts of “choosing the best driver set” and “graph distances” are applied to measure the average controllability and the modal controllability, respectively. Based on these new techniques, we obtain important disease descriptors that visualize alterations in the disease trajectory by revealing densely connected hubs or sparser areas. Our results suggest that these two techniques can accurately describe the different node roles in controlling trajectories of brain networks.
CRIS-Team Scopus Importer:2024-10-25

Coping strategies have a strong impact on quality of life, depression, and embitterment in patients with Cushing's disease - Siegel, Sonja; Milian, Monika; Kleist, Bernadette; Psaras, Tsambika; Tsiogka, Maria; Fuehrer, Dagmar; Koltowska-Haggstrom, Maria; Honegger, Juergen; Mueller, Oliver; Sure, Ulrich; Menzel, Christa; Buchfelder, Michael; et al. (Pituitary, 2016)
PURPOSE: Quality of life (QoL) and psychosocial well-being are substantially impaired in patients with Cushing's disease (CD), not only at the acute illness stage but also after therapy; however, the reason for these impairments remains unclear. METHODS: In this cross-sectional, patient-reported outcome study, we conducted a postal survey on psychosocial impairment and coping strategies in patients after surgical treatment of CD in three large tertiary referral centers. In total, 176 patients with CD completed a compilation of self-assessment inventories pertaining to depression (Hospital Anxiety and Depression Scale, HADS), QoL (Short Form SF-36, Tuebingen CD; Tuebingen CD-25), coping style (Freiburg questionnaire on coping with illness, FKV-LIS), and embitterment (Bern Embitterment Inventory), on average 6.8 ± 6.66 years after surgery. Regression analyses were performed to identify predictors of psychosocial impairment. RESULTS: At the time of the study, 21.8 % of patients suffered from anxiety, 18.7 % experienced an above-average feeling of embitterment, and 13.1 % suffered from depression. Maladaptive coping styles (FKV-LIS subscales depressive coping and minimizing importance) emerged as robust and strong predictors of psychosocial impairment in all inventories; while age, sex, and hydrocortisone intake failed to explain the variance in these measures. CONCLUSION: Similar to several studies in non-pituitary patient cohorts (e.g., patients with multiple sclerosis or lower back pain), our results indicate that psychosocial impairment in CD is significantly influenced by how the patient deals with the illness. Therefore, psychological training of positive coping styles could be a helpful complementary therapy in the overall treatment strategy of CD.
EVALuna2:33852

Coregistrating magnetic source and magnetic resonance imaging for epilepsy surgery in focal cortical dysplasia - Kasper, Burkhard; Roessler, Karl; Hamer, Hajo; Dörfler, Arnd; Blümcke, Ingmar; Coras, Roland; Rösch, Julie; Mennecke, Angelika; Wellmer, Joerg; Sommer, Bjoern; Lorber, Bogdan; Lang, Johannes D.; et al. (NeuroImage: Clinical, 2018)
Background: Epilepsy surgery for focal cortical dysplasia type II (FCD II) offers good chances for seizure freedom, but remains a challenge with respect to lesion detection, defining the epileptogenic zone and the optimal resection strategy. Integrating results from magnetic source imaging from magnetoencephalography (MEG) with magnetic resonance imaging (MRI) including MRI postprocessing may be useful for optimizing these goals. Methods: We here present data from 21 adult FCD II patients, investigated during a 10 year period and evaluated including magnetic source imaging. 16 patients had epilepsy surgery, i.e. histopathologically verified FCD II, and a long follow up. We present our analysis of epileptogenic zones including MEG in relation to structural data according to MRI data and relate these results to surgical outcomes. Results: FCD II in our cohort was characterized by high MEG yield and localization accuracy and MEG showed impact on surgical success-rates. MEG source localizations were detected in 95.2% of patients and were as close as 12.3 ± 8,1 mm to the MRI-lesion. After a mean follow up of >3 years, we saw >80% Engel I outcomes, with more favourable outcomes when the MEG source was completely resected (Fishers exact test 0,033). Conclusion: We argue for a high value of conducting a combined MEG-MRI approach in the presurgical workup and the resection strategy in patients with FCD II related epilepsy.
EVALuna2:35523

Correction: Dissection of mitogenic and neurodegenerative actions of cystine and glutamate in malignant gliomas (Oncogene, (2011), 30, 1, (43-53), 10.1038/onc.2010.391) - Savaskan, N. E.; Seufert, S.; Hauke, J.; Tränkle, C.; Eyüpoglu, Ilker Yasin; Hahnen, E. (Oncogene, 2023)
Following the publication of the article the authors were informed by the scientific community that, regarding the MTT and LDH data presented in the manuscript, an inappropriate statistical test for outliers was used, which was not specified in the “Materials and methods” section. Our correction is aimed to extend the “Materials and methods” section in which the description of the statistical test for outliers was missing. Our re-analyses resulted in changes of some of the mean values, which differ from those presented in the manuscript. Our correction is aimed to address these changes. Cell proliferation and cytotoxicity assays were repeated at least eight times (MTT assay, n=8), or six times (LDH assay, n=6), respectively, using 96-well plates (500 cells per well; total volume 300 μl per well). For each 96-well plate experiment, at least four wells without cells and test compound(s) we used as blanks. Signals were quantified using a Tecan Safire2 microplate reader (Tecan, Zurich, Switzerland). Signals we tested for outliers using the two sided Iglewicz and Hoaglin’s robust test for multiple outliers using the recommended Z-score of 3.5 (available at contchart.com/outliers. sppx). Signals which were identified as outliers by Iglewicz and Hoaglin’s robust test for multiple outliers were removed from further analyses. Regarding the published data, several corrections have to be made. The following mean values deviate by at least five percentage points from the published mean values or the presented significance level changed.
CRIS-Team Scopus Importer:2023-03-03

Correction to: Criteria for the definition of Pituitary Tumor Centers of Excellence (PTCOE): A Pituitary Society Statement - Casanueva, Felipe F.; Barkan, Ariel L.; Buchfelder, Michael; Klibanski, Anne; Laws, Edward R.; Loeffler, Jay S.; Melmed, Shlomo; Mortini, Pietro; Wass, John; Giustina, Andrea (Pituitary, 2018)
The original version of this article unfortunately contained an affiliation error in 'Collaborators for The Pituitary Society, Expert Group on Pituitary Tumors' section. Dr. Misa Pfeifer is affiliated with Medical Faculty, University of Ljubljana, Slovenia and the correct email address to contact is misa.pfeifer@gmail.com.
EVALuna2:214799

Correction to: Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes (Acta Neuropathologica, (2023), 10.1007/s00401-023-02561-5) - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
In the original publication, incorrect version of Fig. 3 and wrong format of Table 1 were published. Specifically, the labels in Fig. 3 were missing and columns of Table 1 were not in the right format. The correct versions of Fig. 3 and Table 1 are shown below. The original article has been corrected.
CRIS-Team Scopus Importer:2023-05-05

Corticotroph tumor progression after bilateral adrenalectomy (Nelson's syndrome): systematic review and expert consensus recommendations - Reincke, Martin; Albani, Adriana; Assie, Guillaume; Bancos, Irina; Brue, Thierry; Buchfelder, Michael; Chabre, Olivier; Ceccato, Filippo; Daniele, Andrea; Detomas, Mario; Di Dalmazi, Guido; Elenkova, Atanaska; et al. (European Journal of Endocrinology, 2021)
Background: Corticotroph tumor progression (CTP) leading to Nelson's syndrome (NS) is a severe and difficult-to-treat complication subsequent to bilateral adrenalectomy (BADX) for Cushing's disease. Its characteristics are not well described, and consensus recommendations for diagnosis and treatment are missing. Methods: A systematic literature search was performed focusing on clinical studies and case series (≥5 patients). Definition, cumulative incidence, treatment and long-term outcomes of CTP/NS after BADX were analyzed using descriptive statistics. The results were presented and discussed at an interdisciplinary consensus workshop attended by international pituitary experts in Munich on October 28, 2018. Results: Data covered definition and cumulative incidence (34 studies, 1275 patients), surgical outcome (12 studies, 187 patients), outcome of radiation therapy (21 studies, 273 patients), and medical therapy (15 studies, 72 patients). Conclusions: We endorse the definition of CTP-BADX/NS as radiological progression or new detection of a pituitary tumor on thin-section MRI. We recommend surveillance by MRI after 3 months and every 12 months for the first 3 years after BADX. Subsequently, we suggest clinical evaluation every 12 months and MRI at increasing intervals every 2-4 years (depending on ACTH and clinical parameters). We recommend pituitary surgery as first-line therapy in patients with CTP-BADX/NS. Surgery should be performed before extrasellar expansion of the tumor to obtain complete and long-term remission. Conventional radiotherapy or stereotactic radiosurgery should be utilized as second-line treatment for remnant tumor tissue showing extrasellar extension.
CRIS-Team Scopus Importer:2021-03-19

Criteria for defining interictal epileptiform discharges in EEG: A clinical validation study - Kural, Mustafa Aykut; Duez, Lene; Sejer Hansen, Vibeke; Larsson, Pal G.; Rampp, Stefan; Schulz, Reinhard; Tankisi, Hatice; Wennberg, Richard; Bibby, Bo M.; Scherg, Michael; Beniczky, Sandor (Neurology, 2020)
ObjectiveTo define and validate criteria for accurate identification of EEG interictal epileptiform discharges (IEDs) using (1) the 6 sensor space criteria proposed by the International Federation of Clinical Neurophysiology (IFCN) and (2) a novel source space method. Criteria yielding high specificity are needed because EEG over-reading is a common cause of epilepsy misdiagnosis.MethodsSeven raters reviewed EEG sharp transients from 100 patients with and without epilepsy (diagnosed definitively by video-EEG recording of habitual events). Raters reviewed the transients, randomized, and classified them as epileptiform or nonepileptiform in 3 separate rounds: in 2, EEG was reviewed in sensor space (scoring the presence/absence of each IFCN criterion for each transient or classifying unrestricted by criteria [expert scoring]); in the other, review and classification were performed in source space.ResultsCutoff values of 4 and 5 criteria in sensor space and analysis in source space provided high accuracy (91%, 88%, and 90%, respectively), similar to expert scoring (92%). Two methods had specificity exceeding the desired threshold of 95%: using 5 IFCN criteria as cutoff and analysis in source space (both 95.65%); the sensitivity of these methods was 81.48% and 85.19%, respectively.ConclusionsThe presence of 5 IFCN criteria in sensor space and analysis in source space are optimal for clinical implementation. By extracting these objective features, diagnostic accuracy similar to expert scorings is achieved.Classification of evidenceThis study provides Class III evidence that IFCN criteria in sensor space and analysis in source space have high specificity (>95%) and sensitivity (81%-85%) for identification of IEDs.
CRIS-Team WoS Importer:2020-07-03

Criteria for the definition of Pituitary Tumor Centers of Excellence (PTCOE): A Pituitary Society Statement - Casanueva, Felipe F.; Barkan, Ariel L.; Buchfelder, Michael; Klibanski, Anne; Laws, Edward R.; Loeffler, Jay S.; Melmed, Shlomo; Mortini, Pietro; Wass, John; Giustina, Andrea (Pituitary, 2017)
INTRODUCTION: With the goal of generate uniform criteria among centers dealing with pituitary tumors and to enhance patient care, the Pituitary Society decided to generate criteria for developing Pituitary Tumors Centers of Excellence (PTCOE). METHODS: To develop that task, a group of ten experts served as a Task Force and through two years of iterative work an initial draft was elaborated. This draft was discussed, modified and finally approved by the Board of Directors of the Pituitary Society. Such document was presented and debated at a specific session of the Congress of the Pituitary Society, Orlando 2017, and suggestions were incorporated. Finally the document was distributed to a large group of global experts that introduced further modifications with final endorsement. RESULTS: After five years of iterative work a document with the ideal criteria for a PTCOE is presented. CONCLUSIONS: Acknowledging that very few centers in the world, if any, likely fulfill the requirements here presented, the document may be a tool to guide improvements of care delivery to patients with pituitary disorders. All these criteria must be accommodated to the regulations and organization of Health of a given country.
EVALuna2:102196

Current value of intraoperative electrocorticography (iopECoG) - Roessler, Karl; Heynold, Elisabeth; Buchfelder, Michael; Stefan, Hermann; Hamer, Hajo (Epilepsy & Behavior, 2019)
Objective: Intraoperative electrocorticography (iopECoG) can contribute to delineate the resection borders of the anticipated epileptogenic zone in epilepsy surgery. However, it has several caveats that should be considered to avoid incorrect interpretation during intraoperative monitoring.
CRIS-Team WoS Importer:2019-04-04

Cytotoxic profiling of artesunic and betulinic acids and their synthetic hybrid compound on neurons and gliomas - Ackermann, Annemarie; Capci Karagöz, Aysun; Ghoochani, Ali; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Tsogoeva, Svetlana; Savaskan, Nicolai (Oncotarget, 2017)
Gliomas are brain-born tumors with devastating impact on their brain microenvironment. Novel approaches employ multiple combinations of chemical compounds in synthetic hybrid molecules to target malignant tumors. Here, we report on the chemical hybridization approach exemplified by artesunic acid (ARTA) and naturally occurring triterpene betulinic acid (BETA). Artemisinin derived semisynthetic compound artesunic acid (ARTA) and naturally occurring triterpene BETA were used to synthetically couple to the hybrid compound termed 212A. We investigated the impact of 212A and its parent compounds on glioma cells, astrocytes and neurons. ARTA and BETA showed cytotoxic effects on glioma cells at micromolar concentrations. ARTA was more effective on rodent glioma cells compared to BETA, whereas BETA exhibited higher toxic effects on human glioma cells compared to ARTA. We investigated these compounds on non-transformed glial cells and neurons as well. Noteworthy, ARTA showed almost no toxic effects on astrocytes and neurons, whereas BETA as well as 212A displayed neurotoxicity at higher concentrations. Hence we compared the efficacy of the hybrid 212A with the combinational treatment of its parent compounds ARTA and BETA. The hybrid 212A was efficient in killing glioma cells compared to single compound treatment strategies. Moreover, ARTA and the hybrid 212A displayed a significant cytotoxic impact on glioma cell migration. Taken together, these results demonstrate that both plant derived compounds ARTA and BETA operate gliomatoxic with minor neurotoxic side effects. Altogether, our proof-of-principle study demonstrates that the chemical hybrid synthesis is a valid approach for generating efficacious anti-cancer drugs out of virtually any given structure. Thus, synthetic hybrid therapeutics emerge as an innovative field for new chemotherapeutic developments with low neurotoxic profile.
EVALuna2:102197

DAPK1 loss triggers tumor invasion in colorectal tumor cells - Steinmann, Sara; Kunze, Philipp; Hampel, Chuanpit; Eckstein, Markus; Bertram Bramsen, Jesper; Muenzner, Julienne K.; Carlé, Birgitta-Elisabeth; Ndreshkjana, Benardina; Kemenes, Stephan; Gasparini, Pierluigi; Friedrich, Oliver; Andersen, Claus; et al. (Cell Death & Disease, 2019)
Colorectal cancer (CRC) is one of the leading cancer-related causes of death worldwide. Despite the improvement of surgical and chemotherapeutic treatments, as of yet, the disease has not been overcome due to metastasis to distant organs. Hence, it is of great relevance to understand the mechanisms responsible for metastasis initiation and progression and to identify novel metastatic markers for a higher chance of preventing the metastatic disease. The Death-associated protein kinase 1 (DAPK1), recently, has been shown to be a potential candidate for regulating metastasis in CRC. Hence, the aim of the study was to investigate the impact of DAPK1 protein on CRC aggressiveness. Using CRISPR/Cas9 technology, we generated DAPK1-deficient HCT116 monoclonal cell lines and characterized their knockout phenotype in vitro and in vivo. We show that loss of DAPK1 implemented changes in growth pattern and enhanced tumor budding in vivo in the chorioallantoic membrane (CAM) model. Further, we observed more tumor cell dissemination into chicken embryo organs and increased invasion capacity using rat brain 3D in vitro model. The novel identified DAPK1-loss gene expression signature showed a stroma typical pattern and was associated with a gained ability for remodeling the extracellular matrix. Finally, we suggest the DAPK1-ERK1 signaling axis being involved in metastatic progression of CRC. Our results highlight DAPK1 as an anti-metastatic player in CRC and suggest DAPK1 as a potential predictive biomarker for this cancer type.
CRIS-Team Scopus Importer:2019-12-10

Data fusion and 3D visualization for optimized representation of neurovascular relationships in the posterior fossa - Hastreiter, Peter; Bischoff, Barbara; Fahlbusch, Rudolf; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Acta Neurochirurgica, 2022)
Background: Reliable 3D visualization of neurovascular relationships in the posterior fossa at the surface of the brainstem is still critical due to artifacts of imaging. To assess neurovascular compression syndromes more reliably, a new approach of 3D visualization based on registration and fusion of high-resolution MR data is presented. Methods: A total of 80 patients received MRI data with 3D-CISS and 3D-TOF at 3.0 Tesla. After registration and subsequent segmentation, the vascular information of the TOF data was fused into the CISS data. Two 3D visualizations were created for each patient, one before and one after fusion, which were verified with the intraoperative situation during microvascular decompression (MVD). The reproduction quality of vessels was evaluated with a rating system. Results: In all cases, the presented approach compensated for typical limitations in the 3D visualization of neurovascular compression such as the partial or complete suppression of larger vessels, suppression of smaller vessels at the CSF margin, and artifacts from heart pulsation. In more than 95% of the cases of hemifacial spasm and glossopharyngeal neuralgia, accurate assessment of the compression was only possible after registration and fusion. In more than 50% of the cases with trigeminal neuralgia, the presented approach was crucial to finding the actually offending vessel. Conclusions: 3D visualization of fused image data allows for a more complete representation of the vessel-nerve situation. The results from this approach are reproducible and the assessment of neurovascular compression is safer. It is a powerful tool for planning MVD.
CRIS-Team Scopus Importer:2022-01-21
Keywords: 3D visualization; Compression syndromes; Data fusion; Neurovascular relationships; Posterior fossa

Deep brain stimulation and stereotactic-assisted brain graft injection targeting fronto-striatal circuits for Huntington's disease: an update - Kinfe, Thomas Mehari; Del Vecchio, Alessandro; Nüssel, Martin; Zhao, Yining; Stadlbauer, Andreas; Buchfelder, Michael (Expert review of neurotherapeutics, 2022)
Introduction: Huntington's Disease as progressive neurological disorders associated with motor, behavioral, and cognitive impairment poses a therapeutic challenge in case of limited responsiveness to established therapeutics. Pallidal deep brain stimulation and neurorestorative strategies (brain grafts) scoping to modulate fronto-striatal circuits have gained increased recognition for the treatment of refractory Huntington's disease (HD).
CRIS-Team WoS Importer:2022-07-08
Keywords: Huntington´s disease; fronto-striatal circuits; chorea; parkinsonism; dystonia; globus pallidus externus/internus; deep-brain stimulation; striatum; brain grafts; unified Huntington´s disease rating scale (UHDRS); chorea; safety; efficacy; quality of life

Deep Brain Stimulation for Chronic Facial Pain: An Individual Participant Data (IPD) Meta-Analysis - Qassim, HebatAllah; Zhao, Yining; Ströbel, Armin; Regensburger, Martin; Buchfelder, Michael; Souza de Oliveira, Daniela; Del Vecchio, Alessandro; Kinfe, Thomas Mehari (Brain Sciences, 2023)
Despite available, advanced pharmacological and behavioral therapies, refractory chronic facial pain of different origins still poses a therapeutic challenge. In circumstances where there is insufficient responsiveness to pharmacological/behavioral therapies, deep brain stimulation should be considered as a potential effective treatment option. We performed an individual participant data (IPD) meta-analysis including searches on PubMed, Embase, and the Cochrane Library (2000–2022). The primary endpoint was the change in pain intensity (visual analogue scale; VAS) at a defined time-point of ≤3 months post-DBS. In addition, correlation and regression analyses were performed to identify predictive markers (age, duration of pain, frequency, amplitude, intensity, contact configuration, and the DBS target). A total of seven trials consisting of 54 screened patients met the inclusion criteria. DBS significantly reduced the pain levels after 3 months without being related to a specific DBS target, age, contact configuration, stimulation intensity, frequency, amplitude, or chronic pain duration. Adverse events were an infection or lead fracture (19%), stimulation-induced side effects (7%), and three deaths (unrelated to DBS—from cancer progression or a second stroke). Although comparable long-term data are lacking, the current published data indicate that DBS (thalamic and PVG/PAG) effectively suppresses facial pain in the short-term. However, the low-quality evidence, reporting bias, and placebo effects must be considered in future randomized-controlled DBS trials for facial pain.
CRIS-Team Scopus Importer:2023-04-07
Keywords: deep brain stimulation; efficacy; facial pain; placebo; predictive outcome measures; safety

Deep brain stimulation in patients on chronic antiplatelet or anticoagulation treatment - Runge, Joachim; Ascencao, Luisa Cassini; Blahak, Christian; Kinfe, Thomas Mehari; Schrader, Christoph; Wolf, Marc E.; Saryyeva, Assel; Krauss, Joachim K. (Acta Neurochirurgica, 2021)
Background: In the aging society, many patients with movement disorders, pain syndromes, or psychiatric disorders who are candidates for deep brain stimulation (DBS) surgery suffer also from cardiovascular co-morbidities that require chronic antiplatelet or anticoagulation treatment. Because of a presumed increased risk of intracranial hemorrhage during or after surgery and limited knowledge about perioperative management, chronic antiplatelet or anticoagulation treatment often has been considered a relative contraindication for DBS. Here, we evaluate whether or not there is an increased risk for intracranial hemorrhage or thromboembolic complications in patients on chronic treatment (paused for surgery or bridged with subcutaneous heparin) as compared to those without. Methods: Out of a series of 465 patients undergoing functional stereotactic neurosurgery, 34 patients were identified who were on chronic treatment before and after receiving DBS. In patients with antiplatelet treatment, medication was stopped in the perioperative period. In patients with vitamin K antagonists or novel oral anticoagulants (NOACs), heparin was used for bridging. All patients had postoperative stereotactic CT scans, and were followed up for 1 year after surgery. Results: In patients on chronic antiplatelet or anticoagulation treatment, intracranial hemorrhage occurred in 2/34 (5.9%) DBS surgeries, whereas the rate of intracranial hemorrhage was 15/431 (3.5%) in those without, which was statistically not significant. Implantable pulse generator pocket hematomas were seen in 2/34 (5.9%) surgeries in patients on chronic treatment and in 4/426 (0.9%) without. There were only 2 instances of thromboembolic complications which both occurred in patients without chronic treatment. There were no hemorrhagic complications during follow-up for 1 year. Conclusions: DBS surgery in patients on chronic antiplatelet or anticoagulation treatment is feasible. Also, there was no increased risk of hemorrhage in the first year of follow-up after DBS surgery. Appropriate patient selection and standardized perioperative management are necessary to reduce the risk of intracranial hemorrhage and thromboembolic complications.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Anticoagulation; Antiplatelet; Deep brain stimulation; Functional neurosurgery; NOAC; Vitamin K antagonist

Deep Brain Stimulation, Stereotactic Radiosurgery and High-Intensity Focused Ultrasound Targeting the Limbic Pain Matrix: A Comprehensive Review - Nüssel, Martin; Zhao, Yining; Knorr, Constantin; Regensburger, Martin; Stadlbauer, Andreas; Buchfelder, Michael; Del Vecchio, Alessandro; Kinfe, Thomas Mehari (Pain and Therapy, 2022)
Chronic pain (CP) represents a socio-economic burden for affected patients along with therapeutic challenges for currently available therapies. When conventional therapies fail, modulation of the affective pain matrix using reversible deep brain stimulation (DBS) or targeted irreversible thalamotomy by stereotactic radiosurgery (SRS) and magnetic resonance (MR)-guided focused ultrasound (MRgFUS) appear to be considerable treatment options. We performed a literature search for clinical trials targeting the affective pain circuits (thalamus, anterior cingulate cortex [ACC], ventral striatum [VS]/internal capsule [IC]). PubMed, Ovid, MEDLINE and Scopus were searched (1990-2021) using the terms "chronic pain", "deep brain stimulation", "stereotactic radiosurgery", "radioneuromodulation", "MR-guided focused ultrasound", "affective pain modulation", "pain attention". In patients with CP treated with DBS, SRS or MRgFUS the somatosensory thalamus and periventricular/periaquaeductal grey was the target of choice in most treated subjects, while affective pain transmission was targeted in a considerably lower number (DBS, SRS) consisting of the following nodi of the limbic pain matrix: the anterior cingulate cortex; centromedian-parafascicularis of the thalamus, pars posterior of the central lateral nucleus and internal capsule/ventral striatum. Although DBS, SRS and MRgFUS promoted a meaningful and sustained pain relief, an effective, evidence-based comparative analysis is biased by heterogeneity of the observation period varying between 3 months and 5 years with different stimulation patterns (monopolar/bipolar contact configuration; frequency 10-130 Hz; intensity 0.8-5 V; amplitude 90-330 mu s), source and occurrence of lesioning (radiation versus ultrasound) and chronic pain ethology (poststroke pain, plexus injury, facial pain, phantom limb pain, back pain). The advancement of neurotherapeutics (MRgFUS) and novel DBS targets (ACC, IC/VS), along with established and effective stereotactic therapies (DBS-SRS), increases therapeutic options to impact CP by modulating affective, pain-attentional neural transmission. Differences in trial concept, outcome measures, targets and applied technique promote conflicting findings and limited evidence. Hence, we advocate to raise awareness of the potential therapeutic usefulness of each approach covering their advantages and disadvantages, including such parameters as invasiveness, risk-benefit ratio, reversibility and responsiveness.
CRIS-Team WoS Importer:2022-05-13
Keywords: Limbic pain network; Deep brain stimulation; Magnetic resonance-guided focussed ultrasound; Stereotactic radiosurgery; Centromedian-parafascicular; Ventral striatum/anterior limb of the internal capsule; Anterior cingulate cortex; Central lateral nucleus of the thalamus; Chronic pain

Deep histopathology genotype–phenotype analysis of focal cortical dysplasia type II differentiates between the GATOR1-altered autophagocytic subtype IIa and MTOR-altered migration deficient subtype IIb - Honke, Jonas; Hoffmann, Lucas; Coras, Roland; Kobow, Katja; Leu, Costin; Pieper, Tom; Hartlieb, Till; Bien, Christian G.; Woermann, Friedrich; Cloppenborg, Thomas; Kalbhenn, Thilo; Gaballa, Ahmed; et al. (Acta Neuropathologica Communications, 2023)
Focal cortical dysplasia type II (FCDII) is the most common cause of drug-resistant focal epilepsy in children. Herein, we performed a deep histopathology-based genotype–phenotype analysis to further elucidate the clinico-pathological and genetic presentation of FCDIIa compared to FCDIIb. Seventeen individuals with histopathologically confirmed diagnosis of FCD ILAE Type II and a pathogenic variant detected in brain derived DNA whole-exome sequencing or mTOR gene panel sequencing were included in this study. Clinical data were directly available from each contributing centre. Histopathological analyses were performed from formalin-fixed, paraffin-embedded tissue samples using haematoxylin–eosin and immunohistochemistry for NF-SMI32, NeuN, pS6, p62, and vimentin. Ten individuals carried loss-of-function variants in the GATOR1 complex encoding genes DEPDC5 (n = 7) and NPRL3 (n = 3), or gain-of-function variants in MTOR (n = 7). Whereas individuals with GATOR1 variants only presented with FCDIIa, i.e., lack of balloon cells, individuals with MTOR variants presented with both histopathology subtypes, FCDIIa and FCDIIb. Interestingly, 50% of GATOR1-positive cases showed a unique and predominantly vacuolizing phenotype with p62 immunofluorescent aggregates in autophagosomes. All cases with GATOR1 alterations had neurosurgery in the frontal lobe and the majority was confined to the cortical ribbon not affecting the white matter. This pattern was reflected by subtle or negative MRI findings in seven individuals with GATOR1 variants. Nonetheless, all individuals were seizure-free after surgery except four individuals carrying a DEPDC5 variant. We describe a yet underrecognized genotype–phenotype correlation of GATOR1 variants with FCDIIa in the frontal lobe. These lesions were histopathologically characterized by abnormally vacuolizing cells suggestive of an autophagy-altered phenotype. In contrast, individuals with FCDIIb and brain somatic MTOR variants showed larger lesions on MRI including the white matter, suggesting compromised neural cell migration.
CRIS-Team Scopus Importer:2023-11-17

Deep Learning-Based Quantification of Pulmonary Hemosiderophages in Cytology Slides - Marzahl, Christian; Aubreville, Marc; Bertram, Christof A.; Stayt, Jason; Jasensky, Anne Katherine; Bartenschlager, Florian; Fragoso-Garcia, Marco; Barton, Ann K.; Elsemann, Svenja; Jabari, Samir; Krauth, Jens; Madhu, Prathmesh; et al. (Scientific Reports, 2020)
Exercise-induced pulmonary hemorrhage (EIPH) is a common condition in sport horses with negative impact on performance. Cytology of bronchoalveolar lavage fluid by use of a scoring system is considered the most sensitive diagnostic method. Macrophages are classified depending on the degree of cytoplasmic hemosiderin content. The current gold standard is manual grading, which is however monotonous and time-consuming. We evaluated state-of-the-art deep learning-based methods for single cell macrophage classification and compared them against the performance of nine cytology experts and evaluated inter- and intra-observer variability. Additionally, we evaluated object detection methods on a novel data set of 17 completely annotated cytology whole slide images (WSI) containing 78,047 hemosiderophages. Our deep learning-based approach reached a concordance of 0.85, partially exceeding human expert concordance (0.68 to 0.86, mean of 0.73, SD of 0.04). Intra-observer variability was high (0.68 to 0.88) and inter-observer concordance was moderate (Fleiss’ kappa = 0.67). Our object detection approach has a mean average precision of 0.66 over the five classes from the whole slide gigapixel image and a computation time of below two minutes. To mitigate the high inter- and intra-rater variability, we propose our automated object detection pipeline, enabling accurate, reproducible and quick EIPH scoring in WSI.
CRIS-Team Scopus Importer:2020-08-14

Defining benchmark outcomes for mesial temporal lobe epilepsy surgery: A global multicenter analysis of 1119 cases - Drexler, Richard; Ricklefs, Franz L.; Ben-Haim, Sharona; Rada, Anna; Wörmann, Friedrich; Cloppenborg, Thomas; Bien, Christian G.; Simon, Matthias; Kalbhenn, Thilo; Colon, Albert; Rijkers, Kim; Schijns, Olaf; et al. (Epilepsia, 2024)
Objective: Benchmarking has been proposed to reflect surgical quality and represents the highest standard reference values for desirable results. We sought to determine benchmark outcomes in patients after surgery for drug-resistant mesial temporal lobe epilepsy (MTLE). Methods: This retrospective multicenter study included patients who underwent MTLE surgery at 19 expert centers on five continents. Benchmarks were defined for 15 endpoints covering surgery and epilepsy outcome at discharge, 1 year after surgery, and the last available follow-up. Patients were risk-stratified by applying outcome-relevant comorbidities, and benchmarks were calculated for low-risk (“benchmark”) cases. Respective measures were derived from the median value at each center, and the 75th percentile was considered the benchmark cutoff. Results: A total of 1119 patients with a mean age (range) of 36.7 (1–74) years and a male-to-female ratio of 1:1.1 were included. Most patients (59.2%) underwent anterior temporal lobe resection with amygdalohippocampectomy. The overall rate of complications or neurological deficits was 14.4%, with no in-hospital death. After risk stratification, 377 (33.7%) benchmark cases of 1119 patients were identified, representing 13.6%–72.9% of cases per center and leaving 742 patients in the high-risk cohort. Benchmark cutoffs for any complication, clinically apparent stroke, and reoperation rate at discharge were ≤24.6%, ≤.5%, and ≤3.9%, respectively. A favorable seizure outcome (defined as International League Against Epilepsy class I and II) was reached in 83.6% at 1 year and 79.0% at the last follow-up in benchmark cases, leading to benchmark cutoffs of ≥75.2% (1-year follow-up) and ≥69.5% (mean follow-up of 39.0 months). Significance: This study presents internationally applicable benchmark outcomes for the efficacy and safety of MTLE surgery. It may allow for comparison between centers, patient registries, and novel surgical and interventional techniques.
CRIS-Team Scopus Importer:2024-03-15
Keywords: benchmarking; neurosurgery; outcome; quality; seizure

Definition of K(trans) and FA Thresholds for Better Assessment of Experimental Glioma Using High-field MRI: A Feasibility Study - Engelhorn, Tobias; Schwarz, Martin; Heß, Andreas; Budinsky, Lubos; Pitann, Patrick; Eyüpoglu, Ilker Yasin; Dörfler, Arnd (Clinical Neuroradiology, 2014)
To define K(trans) and fractional anisotropy (FA) thresholds in correlation to histology for improved magnetic resonance imaging (MRI) tumor assessment in an animal model of brain glioma.Twelve rats underwent 4.7 T MRI at day 10 after tumor implantation. Anatomical scans (T2, T1 at 8 min after double dose contrast application) as well as dynamic contrast-enhanced (DCE) imaging with calculation of K(trans) and diffusion tensor imaging (DTI) with calculation of FA were performed. T2- and T1-derived tumor volumes were calculated and thresholds for K(trans) and FA were defined for best MRI tumor assessment correlated to histology.Tumor volumes were 159 ± 14 mm(3) (histology), 126 ± 26 mm(3) (T1 with contrast, r = 0.76), and 153 ± 12 mm(3) (T2, r = 0.84), respectively. K(trans)- and FA-derived tumor volumes were 160 ± 16 mm(3) (for K(trans) ³ 0.04 min(-1), r = 0.94), and 159 ± 14 mm(3) (for FA £ 0.14, r = 0.96), respectively.DCE-MRI and DTI with calculation of K(trans) and FA maps allow very precise brain glioma assessment comparable to histology if established thresholds for the given tumor model are used.
EVALuna2:8504

Dentate gyrus astrocytes exhibit layer-specific molecular, morphological and physiological features - Karpf, Julian; Unichenko, Petr; Chalmers, Nicholas; Beyer, Felix; Wittmann, Marie-Theres; Schneider, Julia; Fidan, Elif; Reis, André; Beckervordersandforth, Jan; Brandner, Sebastian; Liebner, Stefan; Falk, Sven; et al. (Nature Neuroscience, 2022)
Neuronal heterogeneity has been established as a pillar of higher central nervous system function, but glial heterogeneity and its implications for neural circuit function are poorly understood. Here we show that the adult mouse dentate gyrus (DG) of the hippocampus is populated by molecularly distinct astrocyte subtypes that are associated with distinct DG layers. Astrocytes localized to different DG compartments also exhibit subtype-specific morphologies. Physiologically, astrocytes in upper DG layers form large syncytia, while those in lower DG compartments form smaller networks. Astrocyte subtypes differentially express glutamate transporters, which is associated with different amplitudes of glutamate transporter-mediated currents. Key molecular and morphological features of astrocyte diversity in the mice DG are conserved in humans. This adds another layer of complexity to our understanding of brain network composition and function, which will be crucial for further studies on astrocytes in health and disease.
CRIS-Team Scopus Importer:2022-12-09

Development and validation of a clinical risk model for postoperative outcome in newly diagnosed glioblastoma: A report of the RANO resect group - Karschnia, Philipp; Young, Jacob S.; Youssef, Gilbert C.; Dono, Antonio; Häni, Levin; Sciortino, Tommaso; Bruno, Francesco; Juenger, Stephanie T.; Teske, Nico; Dietrich, Jorg; Weller, Michael; Vogelbaum, Michael A.; et al. (Neuro-Oncology, 2025)
Background. Following surgery, patients with newly diagnosed glioblastoma frequently enter clinical trials. Nuanced risk assessment is warranted to reduce imbalances between study arms. Here, we aimed (I) to analyze the interactive effects of residual tumor with clinical and molecular factors on outcome and (II) to define a postoperative risk assessment tool. Methods. The response assessment in neuro-oncology (RANO) resect group retrospectively compiled an international, seven-center training cohort of patients with newly diagnosed glioblastoma.The combined associations of residual tumor with molecular or clinical factors and survival were analyzed, and recursive partitioning analysis was performed for risk modeling.The resulting model was prognostically verified in a separate external validation cohort. Results. Our training cohort compromised 1003 patients with newly diagnosed isocitrate dehydrogenase-wildtype glioblastoma. Residual tumor, O6-methylguanine DNA methyltransferase (MGMT) promotor methylation status, age, and postoperative Karnofsky Performance Score were prognostic for survival and incorporated into regression tree analysis. By individually weighting the prognostic factors, an additive score (range, 0–9 points) integrating these four variables distinguished patients with low (0–2 points), intermediate (3–5 points), and high risk (6–9 points) for inferior survival.The prognostic value of our risk model was retained in treatment-based subgroups and confirmed in an external validation cohort of 258 patients with glioblastoma. Compared to previously postulated models, goodness-of-fit measurements were superior for our model. Conclusions. The novel RANO risk model serves as an easy-to-use, yet highly prognostic tool for postoperative patient stratification prior to further therapy.The model may serve to guide patient management and reduce imbalances between study arms in prospective trials.
CRIS-Team Scopus Importer:2025-05-30
Keywords: extent of resection; glioblastoma; patient stratification; postoperative risk modeling; risk assessment

Development of a bleeding scale and hemostasis algorithm in cranial neurosurgery - Eyüpoglu, Ilker Yasin; Tuettenberg, Jochen; Schebesch, Karl Michael; Buhl, Ralf; Hampl, Jürgen A.; Kiriyanthan, George D.; Scheiwe, Christian (Heliyon, 2023)
Effective hemostasis is crucial in neurosurgery as anatomical and functional considerations reduce tolerance for any bleeding. The classification of bleeding severities is a necessary step to enable neurosurgeons to counteract bleeding during surgery. Even though bleeding scales are used for a variety of surgical specialties, they cannot be transferred to cranial neurosurgery without adaption, and no consensus on the nature of such a classification exists to date. Moreover, there is plethora of topical hemostasis products with diverse mechanisms of action and application available. Clinical studies investigating those products used in neurosurgery did not define standardized procedures. This article demonstrates the systematic establishment of both a bleeding scale and a hemostasis algorithm to close this gap in the assessment of intracranial bleeding. The expert panel consisting of 7 members from different neurosurgical centers developed a qualitative bleeding scale with the peculiarities of neurosurgical procedures, based on the experience of each member in daily practice. The hemostasis algorithm is a recommendation for neurosurgeons to aid in the decision-making process to control any sort of bleeding, taking into account the rational use of available hemostatics, depending on type and location of bleeding, as well as the mechanism of action of such agents. Effectiveness of hemostasis, surgery times and economic costs can be optimized by applying the algorithm in daily practice.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Bleeding scale; Bleeding score; Hemostasis; Hemostasis algorithm; Intracranial bleeding; Topical hemostats

Development of ACRODAT®, a new software medical device to assess disease activity in patients with acromegaly - Van Der Lely, Aart J.; Gomez, Roy; Pleil, Andreas; Badia, Xavier; Brue, Thierry; Buchfelder, Michael; Burman, Pia; Clemmons, David; Ghigo, Ezio; Jorgensen, Jens Otto Lunde; Luger, Anton; Van Der Lans-Bussemaker, Joli; et al. (Pituitary, 2017)
PURPOSE: Despite availability of multimodal treatment options for acromegaly, achievement of long-term disease control is suboptimal in a significant number of patients. Furthermore, disease control as defined by biochemical normalization may not always show concordance with disease-related symptoms or patient's perceived quality of life. We developed and validated a tool to measure disease activity in acromegaly to support decision-making in clinical practice. METHODS: An international expert panel (n = 10) convened to define the most critical indicators of disease activity. Patient scenarios were constructed based on these chosen parameters. Subsequently, a panel of 21 renowned endocrinologists at pituitary centers (Europe and Canada) categorized each scenario as stable, mild, or significant disease activity in an online validation study. RESULTS: From expert opinion, five parameters emerged as the best overall indicators to evaluate disease activity: insulin-like growth factor I (IGF-I) level, tumor status, presence of comorbidities (cardiovascular disease, diabetes, sleep apnea), symptoms, and health-related quality of life. In the validation study, IGF-I and tumor status became the predominant parameters selected for classification of patients with moderate or severe disease activity. If IGF-I level was ≤1.2x upper limit of normal and tumor size not significantly increased, the remaining three parameters contributed to the decision in a compensatory manner. CONCLUSION: The validation study underlined IGF-I and tumor status for routine clinical decision-making, whereas patient-oriented outcome measures received less medical attention. An Acromegaly Disease Activity Tool (ACRODAT) is in development that might assist clinicians towards a more holistic approach to patient management in acromegaly.
EVALuna2:102194

Development of a Non-invasive Assessment of Hypoxia and Neovascularization with Magnetic Resonance Imaging in Benign and Malignant Breast Tumors: Initial Results - Stadlbauer, Andreas; Zimmermann, Max; Bennani-Baiti, Barbara; Helbich, Thomas H.; Baltzer, Pascal; Clauser, Paola; Kapetas, Panagiotis; Bago-Horvath, Zsuzsanna; Pinker, Katja (Molecular Imaging and Biology, 2019)
Purpose: To develop a novel magnetic resonance imaging (MRI) approach for the noninvasive assessment of hypoxia and neovascularization in breast tumors. Procedures: In this IRB-approved prospective study, 20 patients with suspicious breast lesions (BI-RADS 4/5) underwent multiparametric breast MRI including quantitative BOLD (qBOLD) and vascular architecture mapping (VAM). Custom-made in-house MatLab software was used for qBOLD and VAM data postprocessing and calculation of quantitative MRI biomarker maps of oxygen extraction fraction (OEF), metabolic rate of oxygen (MRO2), and mitochondrial oxygen tension (mitoPO2) to measure tissue hypoxia and neovascularization including vascular architecture including microvessel radius (VSI), density (MVD), and type (MTI). Histopathology was used as standard of reference. Appropriate statistics were performed to assess and compare correlations between MRI biomarkers for hypoxia and neovascularization. Results: qBOLD and VAM data with good quality were obtained from all patients with 13 invasive ductal carcinoma (IDC) and 7 benign breast tumors with a lesion diameter of at least 10 mm in all spatial directions. MRI biomarker maps of oxygen metabolism and neovascularization demonstrated intratumoral spatial heterogeneity with a broad range of biomarker values. Bulk tumor neovasculature consisted of draining venous microvasculature with slow flowing blood. High OEF and low mitoPO2 were associated with low MVD and vice versa. The heterogeneous pattern of MRO2 values showed spatial congruence with VSI. IDCs showed significantly higher MRO2 (P = 0.007), lower mitoPO2 (P = 0.021), higher MVD (P = 0.005), and lower (i.e., more pathologic) MTI (P = 0.001) compared with benign breast tumors. These results indicate that IDCs consume more oxygen and are more hypoxic and neovascularized than benign tumors. Conclusions: We developed a novel MRI approach for the noninvasive assessment of hypoxia and neovascularization in benign and malignant breast tumors that can be easily integrated in a diagnostic MRI protocol and provides insight into intratumoral heterogeneity.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Breast cancer; Imaging biomarkers; MRI; Neovascularization; Oxygen metabolism; Tumor hypoxia

Development of pre-syrinx state and syringomyelia following a minor injury: a case report - Kleindienst, Andrea; Engelhorn, Tobias; Röckelein, Verena; Buchfelder, Michael (Journal of Medical Case Reports, 2020)
Background: A generally accepted rule is that posttraumatic syringomyelia (PTS) results from spinal cord injury (SCI). Case presentation: Here, we report the development of syringomyelia without SCI in a 54-year-old Caucasian man following a mild motor vehicle accident. The computed tomography on admission excluded an injury of the spine. Because of neck and back pain, magnetic resonance imaging was performed on day 3 post-injury and demonstrated minimal changes from a ligamentous strain at the cervicothoracic transition. Any traumatic affection of the bone, vertebral discs, intraspinal compartment, or spinal cord were excluded. Some limb weakness and neurogenic bladder dysfunction started manifesting within the following weeks. Repeated MRIs following the accident demonstrated arachnoid adhesions at the C1–2 level and spinal cord edema equivalent to a pre-syrinx state at 12 months and syrinx formation at 24 months. Because of further deterioration, decompression was performed at 36 months. Conclusions: We conclude that even after a minor trauma PTS can occur and that medullary edema (pre-syrinx state) may precede syrinx formation.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Pre-syrinx; Spinal cord injury; Syringomyelia; Trauma; Treatment

Dexamethasone alleviates tumor-associated brain damage and angiogenesis - Fan, Zheng; Sehm, Tina; Rauh, Manfred; Buchfelder, Michael; Eyupoglu, Ilker Y.; Savaskan, Nicolai E. (PLoS ONE, 2014)
Children and adults with the most aggressive form of brain cancer, malignant gliomas or glioblastoma, often develop cerebral edema as a life-threatening complication. This complication is routinely treated with dexamethasone (DEXA), a steroidal anti-inflammatory drug with pleiotropic action profile. Here we show that dexamethasone reduces murine and rodent glioma tumor growth in a concentration-dependent manner. Low concentrations of DEXA are already capable of inhibiting glioma cell proliferation and at higher levels induce cell death. Further, the expression of the glutamate antiporter xCT (system Xc-; SLC7a11) and VEGFA is up-regulated after DEXA treatment indicating early cellular stress responses. However, in human gliomas DEXA exerts differential cytotoxic effects, with some human glioma cells (U251, T98G) resistant to DEXA, a finding corroborated by clinical data of dexamethasone non-responders. Moreover, DEXA-resistant gliomas did not show any xCT alterations, indicating that these gene expressions are associated with DEXA-induced cellular stress. Hence, siRNA-mediated xCT knockdown in glioma cells increased the susceptibility to DEXA. Interestingly, cell viability of primary human astrocytes and primary rodent neurons is not affected by DEXA. We further tested the pharmacological effects of DEXA on brain tissue and showed that DEXA reduces tumor-induced disturbances of the microenvironment such as neuronal cell death and tumor-induced angiogenesis. In conclusion, we demonstrate that DEXA inhibits glioma cell growth in a concentration and species-dependent manner. Further, DEXA executes neuroprotective effects in brains and reduces tumor-induced angiogenesis. Thus, our investigations reveal that DEXA acts pleiotropically and impacts tumor growth, tumor vasculature and tumor-associated brain damage.
EVALuna2:18894

Diagnosis and management of acromegaly: the patient's perspective - Kreitschmann-Andermahr, Ilonka; Siegel, Sonja; Kleist, Bernadette; Kohlmann, Johannes; Starz, Daniel; Buslei, Rolf; Koltowska-Haggstrom, Maria; Strasburger, Christian J.; Buchfelder, Michael (Pituitary, 2016)
Early diagnosis is a success factor for the prevention of long-term comorbidity and premature death in patients with acromegaly, but large-scale data on the diagnostic process and disease management are scarce. Therefore, we aimed to evaluate the diagnostic process, implementation of treatment and changes in life situation in patients with acromegaly, focusing on sex-specific differences.Non-interventional patient-reported outcome study. 165 patients with clinically and biochemically proven acromegaly were questioned about the diagnostic process and utilization of health care by means of a self-developed standardized postal survey including questions on acromegaly symptoms experienced before diagnosis, number and specialty of consulted doctors, time to diagnosis and aftercare.The diagnostic process took 2.9 (SD 4.53) years, during which 3.4 (SD 2.99) physicians were consulted. Women waited longer [4.1 (SD 5.53) years] than men [1.6 (SD 2.69) years; p = 0.001] for the correct diagnosis, and consulted more doctors in the process [4.0 (SD 2.99) vs. 2.7 (SD 2.84) doctors, p < 0.001, respectively]. In 48.5 % of patients, acromegaly was diagnosed by an endocrinologist (men: 45.1 %; women: 52.4 %). Overall disease duration from symptom onset until last surgery was 5.5 (SD 6.85) years, with no sex differences. A change in employment status was the most commonly reported event after diagnosis and a quarter of the patients stated that the illness had changed their lives.Our findings confirm the urgent need to increase awareness of the clinical manifestation of acromegaly to facilitate an earlier diagnosis of the disease and to provide diagnostic equality across the sexes.
EVALuna2:7322

Diagnostic Accuracy of Neuroimaging to Delineate Diffuse Gliomas within the Brain: A Meta-Analysis - Verburg, Niels; Hoefnagels, F. W. A.; Barkhof, Frederik; Boellaard, Ronald; Goldman, Serge; Guo, Jun; Heimans, J. J.; Hoekstra, O. S.; Jain, Rajan; Kinoshita, Manabu; Pouwels, P. J. W.; Price, S. J.; et al. (American Journal of Neuroradiology, 2017)
BACKGROUND: Brain imaging in diffuse glioma is used for diagnosis, treatment planning, and follow-up. PURPOSE: In this meta-analysis, we address the diagnostic accuracy of imaging to delineate diffuse glioma. DATA SOURCES: We systematically searched studies of adults with diffuse gliomas and correlation of imaging with histopathology. STUDY SELECTION: Study inclusion was based on quality criteria. Individual patient data were used, if available. DATA ANALYSIS: A hierarchic summary receiver operating characteristic method was applied. Low- and high-grade gliomas were analyzed in subgroups. DATA SYNTHESIS: Sixty-one studies described 3532 samples in 1309 patients. The mean Standard for Reporting of Diagnostic Accuracy score (13/25) indicated suboptimal reporting quality. For diffuse gliomas as a whole, the diagnostic accuracy was best with T2-weighted imaging, measured as area under the curve, false-positive rate, true-positive rate, and diagnostic odds ratio of 95.6%, 3.3%, 82%, and 152. For low-grade gliomas, the diagnostic accuracy of T2-weighted imaging as a reference was 89.0%, 0.4%, 44.7%, and 205; and for high-grade gliomas, with T1-weighted gadolinium-enhanced MR imaging as a reference, it was 80.7%, 16.8%, 73.3%, and 14.8. In high-grade gliomas, MR spectroscopy (85.7%, 35.0%, 85.7%, and 12.4) and 11C methionine-PET (85.1%, 38.7%, 93.7%, and 26.6) performed better than the reference imaging. LIMITATIONS: True-negative samples were underrepresented in these data, so false-positive rates are probably less reliable than true-positive rates. Multimodality imaging data were unavailable. CONCLUSIONS: The diagnostic accuracy of commonly used imaging is better for delineation of low-grade gliomas than high-grade gliomas on the basis of limited evidence. Improvement is indicated from advanced techniques, such as MR spectroscopy and PET.
EVALuna2:214809

DICOM encoding of annotation and montage data for waveform recordings - Halford, J. J.; Brinkmann, B. A.; Rampp, Stefan; Rémi, J.; Poznikoff, S.; Nilsen, K. B.; Ehrenberg, J. A.; Winkler, S. (Clinical Neurophysiology, 2025)
CRIS-Team Scopus Importer:2025-05-02

Differences in Intrusive Memory Experiences in Post-traumatic Stress Disorder after Single, Re- and Prolonged Traumatization - Mueller, Helge H.; Möller, Sebastian; Jenderek, Konstanze; Stroebel, Armin; Wiendieck, Kurt; Sperling, Wolfgang (Frontiers in Psychology, 2016)
Intrusive memory experiences (IMEs) are a common symptom of post-traumatic stress disorder (PTSD). Sensory perceptions of IMEs in the PTSD context vary substantially. The present research examined 20 patients with a single trauma, 20 re-traumatized patients and 80 Holocaust-traumatized patients who suffered from PTSD. Our results revealed significant differences in IME frequency based on the types of trauma experience. The findings suggest that patients with prolonged (Holocaust) traumata suffered from visual (65%) and combined visual/acoustic intrusive memories (29%), whereas visual memory experiences were most frequent (90%) among single-trauma patients. The trauma experience and the intrusive memory trigger stimulus were interdependent. The type of trauma critically affects the traumatic experience. Future studies should focus on these findings to improve PTSD therapeutic options.
EVALuna2:23807

Differences in metabolism of fiber tract alterations in gliomas: A combined fiber density mapping and magnetic resonance spectroscopic imaging study - Stadlbauer, Andreas; Hammen, Thilo; Buchfelder, Michael; Bachmair, Johanna; Dörfler, Arnd; Nimsky, Christopher; Ganslandt, Oliver (Neurosurgery, 2012)
BACKGROUND: Gliomas propagate diffusely throughout and along white matter structures. Glioma-related changes in structural integrity and metabolism are not detectable by standard magnetic resonance (MR) imaging. OBJECTIVE: To investigate differences in the metabolism of fiber tract alterations between gliomas grade II to IV by correlation of fiber density values with metabolite concentrations measured by fiber density mapping and MR spectroscopic imaging. METHODS: Fiber density mapping and MR spectroscopic imaging were performed in 48 patients with gliomas WHO grade II to IV. Fiber density mapping data were used to define fiber tracts in tumoral and peritumoral areas. Structural integrity of fiber tracts was assessed as fiber density ipsilateral-to-contralateral ratio (FD ICR). Metabolite concentrations for choline-containing compounds and N-acetyl-aspartate were computed and correlated to FD ICR values after coregistration with anatomic MR imaging. RESULTS: In tumoral areas, choline-containing compound concentrations of altered fiber tracts were significantly different between low- and high-grade glioma and showed different courses for the correlations of FD ICR and choline-containing czeompounds. In high-grade glioma, increasing fiber destruction was associated with a massive progression in cell membrane proliferation. Peritumoral fiber structures showed significantly decreased N-acetyl-aspartate concentrations for all patients, but only patients with glioblastoma multiforme had significantly decreased fiber density compared with the contralateral side. Glioma grades II and III had significantly higher peritumoral FD ICR than glioblastoma multiforme. CONCLUSION: A multiparametric MR imaging strategy providing information about both structural integrity and metabolism of the tumor is required for detailed assessment of glioma-related fiber tract alterations, which in turn is essential for treatment planning. Copyright © 2012 by the Congress of Neurological Surgeons.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain tumor; Diffusion tensor; Fiber density; Magnetic resonance spectroscopy

Differential influence of hippocampal subfields to memory formation: insights from patients with temporal lobe epilepsy - Coras, Roland; Pauli, Elisabeth; Li, Jinmei; Schwarz, Michael; Roessler, Karl; Buchfelder, Michael; Hamer, Hajo; Stefan, Hermann; Blümcke, Ingmar (Brain, 2014)
To clarify the anatomical organization of human memory remains a major challenge in clinical neuroscience. Experimental data suggest dentate gyrus granule cells play a major role in memory acquisition, i.e. pattern separation and rapid pattern completion, whereas hippocampal CA1 neurons are implicated in place memory and autobiographical memory retrieval. Patients with temporal lobe epilepsy present with a broad spectrum of memory impairment, which can be assessed during clinical examination. Although long seizure histories may contribute to a pathophysiological reorganization of functional connectivity, surgical resection of the epileptic hippocampus offers a unique possibility to anatomically study the differential contribution of hippocampal subfields to compromised learning and memory in humans. Herein, we tested the hypothesis of hippocampal subfield specialization in a series of 100 consecutive patients with temporal lobe epilepsy submitted to epilepsy surgery. Memory profiles were obtained from intracarotid amobarbital testing and non-invasive verbal memory assessment before surgery, and correlated with histopathologically quantified cell loss pattern in hippocampal subfields obtained from the same patients using the new international consensus classification for hippocampal sclerosis proposed by the International League against Epilepsy (HS ILAE). Interestingly, patients with CA1 predominant cell loss (HS ILAE Type 2; n = 13) did not show declarative memory impairment and were indistinguishable from patients without any hippocampal cell loss (n = 19). In contrast, 63 patients with neuronal loss affecting all hippocampal subfields including CA1, CA4 and dentate gyrus (HS ILAE Type 1), or predominant cell loss in CA4 and partially affecting also CA3 and dentate gyrus (HS ILAE Type 3, n = 5) showed significantly reduced declarative memory capacities (intracarotid amobarbital testing: P < 0.001; verbal memory: P < 0.05). Our results suggested an alternative model of how memory processing can be organized amongst hippocampal subfields, and that CA1 pyramidal cells are less critically involved in declarative human memory acquisition compared to dentate gyrus granule cells or CA4/CA3 pyramidal cells.
EVALuna2:7242

Differential polarization and activation dynamics of systemic T helper cell subsets after aneurysmal subarachnoid hemorrhage (SAH) and during post-SAH complications - Chaudhry, Shafqat Rasul; Kahlert, Ulf Dietrich; Kinfe, Thomas Mehari; Endl, Elmar; Dolf, Andreas; Niemela, Mika; Haenggi, Daniel; Muhammad, Sajjad (Scientific Reports, 2021)
Aneurysmal subarachnoid hemorrhage (SAH) is associated with high morbidity and mortality. Devastating post-SAH complications, such as cerebral vasospasm (CVS), delayed cerebral ischemia or seizures to mention a few, are mainly responsible for the poor clinical outcome. Inflammation plays an indispensable role during early brain injury (EBI) and delayed brain injury (DBI) phases over which these complications arise. T helper cells are the major cytokine secreting cells of adaptive immunity that can polarize to multiple functionally unique sub-populations. Here, we investigate different CD4+T cell subsets during EBI and DBI phases after SAH, and their dynamics during post-SAH complications. Peripheral venous blood from 15 SAH patients during EBI and DBI phases, was analyzed by multicolour flowcytometry. Different subsets of CD3+CD4+T cells were characterized by differential cell surface expression of CXCR3 and CCR6 into Th1, Th2, Th17, whereas Tregs were defined by CD25(hi)CD127(lo). The analysis of activation states was done by the expression of stable activation markers CD38 and HLA-DR. Interestingly, compared to healthy controls, Tregs were significantly increased during both EBI and DBI phases. Different activation states of Tregs showed differential significant increase during EBI and DBI phases compared to controls. HLA-DR-CD38+Tregs were significantly increased during DBI phase compared to EBI phase in SAH patients developing CVS, seizures and infections. However, HLA-DR-CD38-Tregs were significantly reduced during EBI phase in patients with cerebral ischemia (CI) compared to those without CI. HLA-DR-CD38-Th2 cells were significantly increased during EBI phase compared to controls. A significant reduction in Th17/Tregs and HLA-DR-CD38+Th17/Tregs ratios was observed during both EBI and DBI phases compared to controls. While HLA-DR-CD38-Th17/Tregs and HLA-DR-CD38-Th1/Th2 ratios were impaired only during EBI phase compared to controls. In conclusion, CD4+T cell subsets display dynamic and unique activation patterns after SAH and during the course of the manifestation of post-SAH complications, which may be helpful for the development of precision neurovascular care. However, to claim this, confirmatory studies with larger patient cohorts, ideally from different ethnic backgrounds, are required. Moreover, our descriptive study may be the grounds for subsequent lab endeavors to explore the underlying mechanisms of our observations.
CRIS-Team WoS Importer:2021-07-30

Differentiation of Glioblastoma and Brain Metastases by MRI-Based Oxygen Metabolomic Radiomics and Deep Learning - Stadlbauer, Andreas; Heinz, Gertraud; Marhold, Franz; Meyer-Baese, Anke; Ganslandt, Oliver; Buchfelder, Michael; Oberndorfer, Stefan (Metabolites, 2022)
Glioblastoma (GB) and brain metastasis (BM) are the most frequent types of brain tumors in adults. Their therapeutic management is quite different and a quick and reliable initial characterization has a significant impact on clinical outcomes. However, the differentiation of GB and BM remains a major challenge in today's clinical neurooncology due to their very similar appearance in conventional magnetic resonance imaging (MRI). Novel metabolic neuroimaging has proven useful for improving diagnostic performance but requires artificial intelligence for implementation in clinical routines. Here; we investigated whether the combination of radiomic features from MR-based oxygen metabolism ("oxygen metabolic radiomics") and deep convolutional neural networks (CNNs) can support reliably pre-therapeutic differentiation of GB and BM in a clinical setting. A self-developed one-dimensional CNN combined with radiomic features from the cerebral metabolic rate of oxygen (CMRO2) was clearly superior to human reading in all parameters for classification performance. The radiomic features for tissue oxygen saturation (mitoPO(2); i.e., tissue hypoxia) also showed better diagnostic performance compared to the radiologists. Interestingly, both the mean and median values for quantitative CMRO2 and mitoPO(2) values did not differ significantly between GB and BM. This demonstrates that the combination of radiomic features and DL algorithms is more efficient for class differentiation than the comparison of mean or median values. Oxygen metabolic radiomics and deep neural networks provide insights into brain tumor phenotype that may have important diagnostic implications and helpful in clinical routine diagnosis.
CRIS-Team WoS Importer:2023-01-27

Diffuse Encephalopathy Associated with Isolated Cerebral Langerhans Cell Histiocytosis - Rompel, Oliver; Buslei, Rolf; Hammon, Matthias; Dörr, Helmuth-Günther; Chada, Martin; Nikkhah, Guido; Uder, Michael; Trollmann, Regina (Pediatric Neurology, 2016)
Langerhans cell histiocytosis is a rare disease of the monocyte-macrophage system. Abnormalities of the hypothalamic-pituitary region are common in individuals with central nervous system involvement.This six-year-old boy developed rapidly progressive aggressive behavior, central diabetes insipidus, and repeated complex partial seizures. Magnetic resonance imaging revealed a diffuse leukoencephalopathy-like pattern and numerous infratentorial and supratentorial granulomatous nodules in the brain parenchyma along with infundibular and hypothalamic mass lesions. Stereotactic serial biopsies enabled histopathologic and immunohistochemical diagnosis of Langerhans cell histiocytosis.Similar MRI findings have rarely been described in the literature. These findings represent part of the broad neuroradiological spectrum of Langerhans cell histiocytosis of the nervous system in children.
EVALuna2:7341

Direct current shifts, high frequency oscillations and the epileptogenic zone - Rampp, Stefan (Clinical Neurophysiology, 2015)
EVALuna2:22363

DNA methylation-based classification of malformations of cortical development in the human brain - Jabari, Samir; Kobow, Katja; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Polster, Tilman; Bien, Christian G.; Kalbhenn, Thilo; Simon, Matthias; Hamer, Hajo; Roessler, Karl; Feucht, Martha; et al. (Acta Neuropathologica, 2022)
Malformations of cortical development (MCD) comprise a broad spectrum of structural brain lesions frequently associated with epilepsy. Disease definition and diagnosis remain challenging and are often prone to arbitrary judgment. Molecular classification of histopathological entities may help rationalize the diagnostic process. We present a retrospective, multi-center analysis of genome-wide DNA methylation from human brain specimens obtained from epilepsy surgery using EPIC 850 K BeadChip arrays. A total of 308 samples were included in the study. In the reference cohort, 239 formalin-fixed and paraffin-embedded (FFPE) tissue samples were histopathologically classified as MCD, including 12 major subtype pathologies. They were compared to 15 FFPE samples from surgical non-MCD cortices and 11 FFPE samples from post-mortem non-epilepsy controls. We applied three different statistical approaches to decipher the DNA methylation pattern of histopathological MCD entities, i.e., pairwise comparison, machine learning, and deep learning algorithms. Our deep learning model, which represented a shallow neuronal network, achieved the highest level of accuracy. A test cohort of 43 independent surgical samples from different epilepsy centers was used to test the precision of our DNA methylation-based MCD classifier. All samples from the test cohort were accurately assigned to their disease classes by the algorithm. These data demonstrate DNA methylation-based MCD classification suitability across major histopathological entities amenable to epilepsy surgery and age groups and will help establish an integrated diagnostic classification scheme for epilepsy-associated MCD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Brain development; Cortical malformation; Deep learning; Epigenetic; Epilepsy

Does Temporary Externalization of Electrodes After Deep Brain Stimulation Surgery Result in a Higher Risk of Infection? - Runge, Joachim; Nagel, Johanna M.; Blahak, Christian; Kinfe, Thomas Mehari; Heissler, Hans E.; Schrader, Christoph; Wolf, Marc E.; Saryyeva, Assel; Krauss, Joachim K. (Neuromodulation, 2023)
Objectives: Deep brain stimulation (DBS) is a well-established surgical therapy for movement disorders that comprises implantation of stimulation electrodes and a pacemaker. These procedures can be performed separately, leaving the possibility of externalizing the electrodes for local field potential recording or testing multiple targets for therapeutic efficacy. It is still debated whether the temporary externalization of DBS electrodes leads to an increased risk of infection. We therefore aimed to assess the risk of infection during and after lead externalization in DBS surgery. Materials and Methods: In this retrospective study, we analyzed a consecutive series of 624 DBS surgeries, including 266 instances with temporary externalization of DBS electrodes for a mean of 6.1 days. Patients were available for follow-up of at least one year, except in 15 instances. In 14 patients with negative test stimulation, electrodes were removed. All kinds of infections related to implantation of the neurostimulation system were accounted for. Results: Overall, infections occurred in 22 of 624 surgeries (3.5%). Without externalization of electrodes, infections were noted after 7 of 358 surgeries (2.0%), whereas with externalization, 15 of 252 infections were found (6.0%). This difference was significant (p = 0.01), but it did not reach statistical significance when comparing groups within different diagnoses. The rate of infection with externalized electrodes was highest in psychiatric disorders (9.1%), followed by Parkinson's disease (7.3%), pain (5.7%), and dystonia (5.5%). The duration of the externalization of the DBS electrodes was comparable in patients who developed an infection (6.1 ± 3.1 days) with duration in those who did not (6.0 ± 3.5 days). Conclusions: Although infection rates were relatively low in our study, there was a slightly higher infection rate when DBS electrodes were externalized. On the basis of our results, the indication for electrode externalization should be carefully considered, and patients should be informed about the possibility of a higher infection risk when externalization of DBS electrodes is planned.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Deep brain stimulation; electrodes; externalization; functional neurosurgery; infection

Drug priming enhances radiosensitivity of adamantinomatous craniopharyngioma via downregulation of survivin - Stache, Christina; Bils, Christiane; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Stefanits, Harald; Czech, Thomas; Gaipl, Udo; Frey, Benjamin; Buslei, Rolf; Hoelsken, Annett (Neurosurgical Focus, 2016)
OBJECTIVE In this study, the authors investigated the underlying mechanisms responsible for high tumor recurrence rates of adamantinomatous craniopharyngioma (ACP) after radiotherapy and developed new targeted treatment protocols to minimize recurrence. ACPs are characterized by the activation of the receptor tyrosine kinase epidermal growth factor receptor (EGFR), known to mediate radioresistance in various tumor entities. The impact of tyrosine kinase inhibitors (TKIs) gefitinib or CUDC-101 on radiation-induced cell death and associated regulation of survivin gene expression was evaluated. METHODS The hypothesis that activated EGFR promotes radioresistance in ACP was investigated in vitro using human primary cell cultures of ACP (n = 10). The effects of radiation (12 Gy) and combined radiochemotherapy on radiosensitivity were assessed via cell death analysis using flow cytometry. Changes in target gene expression were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Survivin, identified in qRT-PCR to be involved in radioresistance of ACP, was manipulated by small interfering RNA (siRNA), followed by proliferation and vitality assays to further clarify its role in ACP biology. Immunohistochemically, survivin expression was assessed in patient tumors used for primary cell cultures. RESULTS In primary human ACP cultures, activation of EGFR resulted in significantly reduced cell death levels after radiotherapy. Treatment with TKIs alone and in combination with radiotherapy increased cell death response remarkably, assessed by flow cytometry. CUDC-101 was significantly more effective than gefitinib. The authors identified regulation of survivin expression after therapeutic intervention as the underlying molecular mechanism of radioresistance in ACP. EGFR activation promoting ACP cell survival and proliferation in vitro is consistent with enhanced survivin gene expression shown by qRT-PCR. TKI treatment, as well as the combination with radiotherapy, reduced survivin levels in vitro. Accordingly, ACP showed reduced cell viability and proliferation after survivin downregulation by siRNA. CONCLUSIONS These results indicate an impact of EGFR signaling on radioresistance in ACP. Inhibition of EGFR activity by means of TKI treatment acts as a radiosensitizer on ACP tumor cells, leading to increased cell death. Additionally, the results emphasize the antiapoptotic and pro-proliferative role of survivin in ACP biology and its regulation by EGFR signaling. The suppression of survivin by treatment with TKI and combined radiotherapy represents a new promising treatment strategy that will be further assessed in in vivo models of ACP.
EVALuna2:7353

Dynamical graph networks may aid in phenotyping prognostically different brain tumor types - Meyer-Baese, Anke; Juetten, Kerstin; Meyer-Baese, Uwe; Stadlbauer, Andreas; Kinfe, Thomas Mehari; Na, Chuh Hyoun (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
Diffuse infiltrative glioma are considered as a systemic brain disorder and produce alterations on cerebral functional and structural integrity beyond the tumor location. These alterations are the result of the dynamic interplay between large-scale neural circuits. Describing the nature of these interactions has been a challenging task yet important for glioma disease evolution. Modern dynamic graph network theory techniques and control theory applied to these structural and functional networks opens a new research avenue for understanding the dynamical properties and differences between healthy controls and glioma patients. It has been shown that controllability is relevant for providing the mechanistic explanation of how the brain navigates between cognitive states. We believe that it is also relevant for describing the connectomic alterations in glioma and the differences among subtypes and healthy controls. The nodes that are needed to control these networks and influence them to any state are called driver nodes. We determined the driver nodes of the Default-Mode Network (DMN) for resting-state functional connectivity (FC) and diffusion-MRI-based structural connectivity (SC) (comprising edge-weight (EW) and fractional anisotropy (FA)) networks in isodehydrogenase mutated (IDHmut) and wildtype (IDHwt) patients and healthy controls. Our results show that healthy controls have a better controllability for both FC and SC, and that structural connectomic dynamical aberrations are more pronounced in glioma patients than functional connectomic alterations.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Brain Networks; Default-Mode Network; Driver Nodes; Functional Connectivity; Glioma; Structural

Dynamical Graph Theory Networks Methods for the Analysis of Sparse Functional Connectivity Networks and for Determining Pinning Observability in Brain Networks - Meyer-Baese, Anke; Roberts, Rodney G.; Illan, Ignacio A.; Meyer-Base, Uwe; Lobbes, Marc; Stadlbauer, Andreas; Pinker-Domenig, Katja (Frontiers in Computational Neuroscience, 2017)
Neuroimaging in combination with graph theory has been successful in analyzing the functional connectome. However almost all analysis are performed based on static graph theory. The derived quantitative graph measures can only describe a snap shot of the disease over time. Neurodegenerative disease evolution is poorly understood and treatment strategies are consequently only of limited efficiency. Fusing modern dynamic graph network theory techniques and modeling strategies at different time scales with pinning observability of complex brain networks will lay the foundation for a transformational paradigm in neurodegnerative diseases research regarding disease evolution at the patient level, treatment response evaluation and revealing some central mechanism in a network that drives alterations in these diseases. We model and analyze brain networks as two-time scale sparse dynamic graph networks with hubs (clusters) representing the fast sub-system and the interconnections between hubs the slow sub-system. Alterations in brain function as seen in dementia can be dynamically modeled by determining the clusters in which disturbance inputs have entered and the impact they have on the large-scale dementia dynamic system. Observing a small fraction of specific nodes in dementia networks such that the others can be recovered is accomplished by the novel concept of pinning observability. In addition, how to control this complex network seems to be crucial in understanding the progressive abnormal neural circuits in many neurodegenerative diseases. Detecting the controlling regions in the networks, which serve as key nodes to control the aberrant dynamics of the networks to a desired state and thus influence the progressive abnormal behavior, will have a huge impact in understanding and developing therapeutic solutions and also will provide useful information about the trajectory of the disease. In this paper, we present the theoretical framework and derive the necessary conditions for (1) area aggregation and time-scale modeling in brain networks and for (2) pinning observability of nodes in dynamic graph networks. Simulation examples are given to illustrate the theoretical concepts.
EVALuna2:214808

Dysmorphic neurons as cellular source for phase-amplitude coupling in Focal Cortical Dysplasia Type II - Rampp, Stefan; Rössler, Karl; Hamer, Hajo; Illek, Margit; Buchfelder, Michael; Dörfler, Arnd; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Kölble, Konrad; Peixoto-Santos, Jose Eduardo; Blümcke, Ingmar; et al. (Clinical Neurophysiology, 2021)
Objective: Reliable localization of the epileptogenic zone is necessary for successful epilepsy surgery. Neurophysiological biomarkers include ictal onsets and interictal spikes. Furthermore, the epileptic network shows oscillations with potential localization value and pathomechanistic implications. The cellular origin of such markers in invasive EEG in vivo remains to be clarified. Methods: In the presented pilot study, surgical brain samples and invasive EEG recordings of seven patients with surgically treated Focal Cortical Dysplasia (FCD) type II were coregistered using a novel protocol. Dysmorphic neurons and balloon cells were immunohistochemically quantified. Evaluated markers included seizure onset, spikes, and oscillatory activity in delta, theta, gamma and ripple frequency bands, as well as sample entropy and phase-amplitude coupling between delta, theta, alpha and beta phase and gamma amplitude. Results: Correlations between histopathology and neurophysiology provided evidence for a contribution of dysmorphic neurons to interictal spikes, fast gamma activity and ripples. Furthermore, seizure onset and phase-amplitude coupling in areas with dysmorphic neurons suggests preserved connectivity is related to seizure initiation. Balloon cells showed no association. Conclusions: Phase-amplitude coupling, spikes, fast gamma and ripples are related to the density of dysmorphic neurons and localize the seizure onset zone. Significance: The results of our pilot study provide a new powerful tool to address the cellular source of abnormal neurophysiology signals to leverage current and novel biomarkers for the localization of epileptic activity in the human brain.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Electrophysiological markers; Epilepsy; Focal cortical dysplasia; Invasive EEG

EANS Epilepsy surgery Brain Dissection Course Vienna 2024 - Rössler, Karl; Van Roost, Dirk; Schijns, Olaf; Ackermans, Linda; Delev, Daniel; Batista, Pedro Duarte; Erőss, Lorand; Fountas, Kostas; Hart, Michael; Krüger, Marie; von Lehe, Marec; Campos, Alexandre Rainha; et al. (Brain and Spine, 2024)
CRIS-Team Scopus Importer:2024-11-01

Early CSF and Serum S100B Concentrations for Outcome Prediction in Traumatic Brain Injury and Subarachnoid Hemorrhage - Kellermann, Isabel; Kleindienst, Andrea; Hore, Nirjhar; Buchfelder, Michael; Brandner, Sebastian (Clinical Neurology and Neurosurgery, 2016)
OBJECTIVES: S100B has been proposed as a putative biochemical marker in determining the extent of brain injury and corresponding prognosis in neurotrauma. The aim of this study was to evaluate the prognostic value of S100B early concentrations in serum and cerebrospinal fluid (CSF) in traumatic brain injury (TBI) and subarachnoid hemorrhage (SAH), to determine prognostically relevant threshold values and to evaluate fluctuation following EVD placement. PATIENTS AND METHODS: In 102 patients (45 SAH and 57 TBI) under intensive care unit (ICU) treated between January 2011 and December 2012 with external ventricular drain (EVD) S100B measurements were performed simultaneously in serum and CSF during the first 5 days and before and after EVD exchange. Glasgow coma scale (GCS) was assessed on admission and Glasgow outcome scale (GOS) 6 months later. RESULTS: Peak S100B levels in CSF and serum were measured on the first day after admission and concentrations decreased during the ensuing days post injury gradually. CSF and serum S100B concentrations in TBI patients were significantly higher than in SAH (p<0.005). Both in TBI and SAH patients S100B concentrations in CSF and serum were significantly higher in patients with an unfavorable outcome (GOS 1-3) in comparison to patients with a good outcome (GOS 4-5). Correlation of S100B concentrations in serum and GOS score at 6 months was significant both in TBI and SAH (p<0.05). Serum S100B concentrations >0.7μg/l correlated with 100% mortality. Correlation between S100B in CSF and GOS was significant in SAH (p<0.05), whereas it was not significant in TBI. After EVD exchange (n=53) we found a significant increase of S100B concentration in CSF (p<0.005). CONCLUSION: Initial S100B levels have a limited prognostic value in neurotrauma with CSF concentrations being highly sensitive to smallest influences like EVD placement. However, high initial S100B levels of >0.7μg/dl in serum are associated with 100% mortality, which might help to guide therapy strategies in severe neurotrauma.
EVALuna2:33856

Early Intravenous Magnesium Sulfate and Its Impact on Cerebral Vasospasm as well as Delayed Cerebral Ischemia in Aneurysmal Subarachnoid Hemorrhage: A Retrospective Matched Case-Control Analysis - Feulner, Julian; Weidinger, Cornelia; Dörfler, Arnd; Birkholz, Torsten; Buchfelder, Michael; Sommer, Björn (World Neurosurgery, 2024)
Background: Magnesium sulfate (MgSO4) is a potential neuroprotective agent for patients with aneurysmal subarachnoid hemorrhage (SAH). We analyzed the effect of early application of intraoperative intravenous MgSO4 and compared cerebral vasospasm (CV), delayed cerebral ischemia (DCI), and neurological outcome in 2 patient cohorts. Methods: A retrospective matched-pair analysis from patients at a single center in Germany was performed without (group A) and with (group B) MgSO4 application <24 hours after diagnosis. Pairs were matched according to the known risk factors for DCI and CV (age, Fisher grade, smoking, severity of SAH). Incidence of CV and DCI and neurological outcome using the modified Rankin Scale score 3 and 12 months after SAH were recorded. Results: The inclusion criteria were met by 196 patients. After risk stratification, 48 patients were included in the final analysis (age 54.2 ± 8.1 years; 30 women and 18 men) and were assigned to group A (n = 24) or group B (n = 24). CV occurred less frequently in group B (33%) than in group A (46%). Likewise, DCI was present in 13% in group B compared with 42% in group A. After 12 months, 22 patients in group B had a favorable functional outcome (modified Rankin Scale score 0–3) compared with 15 patients in group A. Conclusions: In this study, the incidence of CV and DCI was lower in patients receiving intravenous MgSO4 within 24 hours after aneurysmal SAH onset. Favorable functional outcome was more likely in the MgSO4 group after 12 months of follow-up.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Aneurysmal subarachnoid hemorrhage; Cerebral vasospasm; Delayed cerebral ischemia; Functional outcome; Magnesium sulfate

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

Early postoperative tumor progression predicts clinical outcome in glioblastoma-implication for clinical trials - Merkel, Andreas; Soeldner, Dorothea; Wendl, Christina; Urkan, Dilek; Kuramatsu, Joji; Seliger, Corinna; Proescholdt, Martin; Eyupoglu, Ilker Y.; Hau, Peter; Uhl, Martin (Journal of Neuro-Oncology, 2017)
Molecular markers define the diagnosis of glioblastoma in the new WHO classification of 2016, challenging neuro-oncology centers to provide timely treatment initiation. The aim of this study was to determine whether a time delay to treatment initiation was accompanied by signs of early tumor progression in an MRI before the start of radiotherapy, and, if so, whether this influences the survival of glioblastoma patients. Images from 61 patients with early post-surgery MRI and a second MRI just before the start of radiotherapy were examined retrospectively for signs of early tumor progression. Survival information was analyzed using the Kaplan-Meier method, and a Cox multivariate analysis was performed to identify independent variables for survival prediction. 59 percent of patients showed signs of early tumor progression after a mean time of 24.1 days from the early post-surgery MRI to the start of radiotherapy. Compared to the group without signs of early tumor progression, which had a mean time of 23.3 days (p = 0.685, Student's t test), progression free survival was reduced from 320 to 185 days (HR 2.3; CI 95% 1.3-4.0; p = 0.0042, log-rank test) and overall survival from 778 to 329 days (HR 2.9; CI 95% 1.6-5.1; p = 0.0005). A multivariate Cox regression analysis revealed that the Karnofsky performance score, O-6-methylguanine-DNA-methyltransferase (MGMT) promoter methylation, and signs of early tumor progression are prognostic markers of overall survival. Early tumor progression at the start of radiotherapy is associated with a worse prognosis for glioblastoma patients. A standardized baseline MRI might allow for better patient stratification.
EVALuna2:22524

Early prediction of delayed cerebral ischemia in subarachnoid hemorrhage based on quantitative EEG: A prospective study in adults - Gollwitzer, S.; Groemer, Teja W.; Rampp, Stefan; Hagge, Mareike; Olmes, D.; Huttner, Hagen; Schwab, Sibylle; Madzar, D.; Hopfengaertner, R.; Hamer, Hajo (Clinical Neurophysiology, 2015)
Delayed cerebral infarction (DCI) has a significant impact on mortality and morbidity of patients with subarachnoid hemorrhage (SAH). The aim of this study was to define quantitative EEG (qEEG) parameters for the early and reliable prediction of DCI and compare the validity and time course of qEEG to standard procedures.12 consecutive unselected SAH patients (8 female, mean age 52 years, Hunt-and-Hess grade I-IV) were prospectively examined. Continuous six channel EEG monitoring was started within 48 h after admission (mean duration 5.2 days; range: 2-12 days). All raw and unselected EEG signal underwent automated artifact rejection, Short Time Fast Fourier Transformation and a detrending procedure in order to analyze regional spectral power changes in different frequency bands. According to clinical standards, transcranial Doppler sonography (TCD) was performed at least on alternate days and repeat cerebral computer tomography (CCT) as needed.6 patients (50%) developed vasospasm/DCI. Decrease of ?40% in power persisting over ?5h in the alpha band and ?6h in the theta band marked the optimal cut-off to detect DCI (sensitivity 89%, specificity 77% for alpha). EEG changes preceded detection of vasospasm/DCI in standard procedures by 2.3d ays. Changes in the beta and delta band as well as in the alpha/delta ratio demonstrated lower correlation with imminent DCI.Focal reduction in alpha power may represent a valid, observer independent, non-invasive and continuous marker for vasospasm/DCI in SAH patients.qEEG indicates imminent ischemia earlier than established diagnostic tools, such as TCD.
EVALuna2:22268

Editorial: Cerebral localization and neurostimulation for pain - Kinfe, Thomas Mehari; Chakravarthy, Krishnan; Deer, Timothy R. (Frontiers in Neurology, 2022)
CRIS-Team WoS Importer:2022-10-28

Editorial: Ferroptosis in malignant brain tumors - Yakubov, Eduard; Ghoochani, Ali; Savaskan, Nicolai (Frontiers in Oncology, 2023)
CRIS-Team Scopus Importer:2023-10-27
Keywords: brain edema; brain tumor; drug resistance; ferroptosis; glioblastoma; tumor microenvironment

Editorial: Magnetoencephalography (MEG) in Epilepsy and Neurosurgery - Poghosyan, Vahe; Rampp, Stefan; Wang, Zhong Irene (Frontiers in Human Neuroscience, 2022)
CRIS-Team Scopus Importer:2022-04-22
Keywords: drug-resistant epilepsy (DRE); epilepsy surgery; magnetic source imaging (MSI); magnetoencephalography (MEG); presurgical evaluation

EEG/MEG-Quellenrekonstruktion bei nichtläsioneller Epilepsie - Heide, Ev Christin; Rampp, Stefan; van de Velden, Daniel; Seeck, Margitta; Focke, Niels K. (Clinical Epileptology, 2023)
Background: The postsurgical outcome of non-lesional epilepsy is worse compared to that of lesional epilepsy. Electric and magnetic source imaging (ESI/MSI) are very important methods for the presurgical identification of the epileptogenic focus. Objective: The aim of this article is to provide an overview on the current state of knowledge on ESI and MSI in non-lesional epilepsy. Material and methods: The article presents a non-systematic literature review. Results and conclusion: Source imaging has proven its usefulness in the localization of the epileptogenic focus in non-lesional epilepsy patients. The concordance of the resection zone or intracranial EEG and the source imaging in patients with a good surgical outcome was high. It provides non-redundant information in a relevant proportion of patients by identifying unknown lesions; however, only 9 of 25 surveyed European epilepsy centers reported using ESI in their presurgical evaluation. Semi-automated source reconstruction and limitation of the number of spikes and electrodes needed could help to improve its practicability and increase its use in epilepsy centers.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Electroencephalography; Magnetoencephalography; Non-lesional epilepsy; Presurgical evaluation; Source reconstruction

Effective long-term local results and prognostic factors after fractionated stereotactic radiotherapy of 257 intracranial meningeoma - Lubgan, Dorota; Rutzner, Sandra; Semrau, S.; Lambrecht, U.; Roessler, K.; Buchfelder, Michael; Fietkau, Rainer (2016)
EVALuna2:18329

Effects of metabolites on the crosstalk between macrophages and brain tumor cells - Geiss, C.; Savaskan, Nicolai; Regnier-Vigouroux, A. (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Efficacy of Subperiosteal Drains in Chronic Subdural Hematoma: A Prospective Randomized Single-Center Study - Bozhkov, Yavor; Feulner, Julian; Buchfelder, Michael; Kleiß, Max-Augustus; Brandner, Sebastian; Kinfe, Thomas Mehari (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Chronic subdural hematomas (cSDHs) are most frequently treated by evacuation via a burr-hole craniostomy procedure. Subperiosteal drains have been introduced as alternatives to subdural ones, but only a few prospective studies have explored their efficacy. Thus, a prospective randomized trial was designed to assess their use. Methods The study enrolled patients with newly diagnosed surgically amenable cSDH. These patients were randomized into two groups. The first group underwent cSDH evacuation via a single burr hole craniostomy procedure, followed by placement of a subperiosteal drain; the second group underwent the identical procedure without drain placement. Patient demographics, drain volumes, duration of drainage, cSDH recurrence, and postoperative outcomes were recorded. Results Eighty-eight patients presenting with cSDH (12 with bilateral cSDHs) from a total of 100 surgical cases were enrolled. Nine patients (1 bilateral) were lost to followup. Of all remaining 90 procedures, 37 were carried out with drain placement and the remaining 53 without drain placement. There were five recurrent cases (13.5%) in the drain placement group and 17 (32.1%) in the group without drain placement. This resulted in a statistical significance (odds ratio [OR]: 0.33; p < 0.05) favoring the use of a drain. Conclusion Subperiosteal drain placement can be used safely and effectively to treat cSDH in conjunction with a burr-hole craniostomy procedure, significantly reducing the rate of recurrence without any additional disadvantages.
CRIS-Team Scopus Importer:2025-02-04
Keywords: chronic subdural hematoma; drain; efficacy; recurrence; subperiosteal

Efficacy of Temozolomide Therapy in Patients With Aggressive Pituitary Adenomas and Carcinomas -A German Survey - Elbelt, Ulf; Schlaffer, Sven-Martin; Buchfelder, Michael; Knappe, Ulrich J.; Vila, Greisa; Micko, Alexander; Deutschbein, Timo; Unger, Nicole; Lammert, Alexander; Topuzoglu-Müller, Tengü; Bojunga, Jörg; Droste, Michael; et al. (Journal of Clinical Endocrinology and Metabolism, 2020)
Context: Despite growing evidence that temozolomide (TMZ) therapy is effective for the treatment of aggressive pituitary tumors (APTs) or carcinomas (PCs), individual therapy decisions remain challenging. Objective: We therefore aimed to report on clinical characteristics leading to initiation of TMZ therapy and to add evidence on TMZ long-term effectiveness. Design and subjects: Retrospective survey on TMZ treatment in patients with APTs or PCs. TMZ therapy was initiated in 47 patients (22 females) with APTs (n = 34) or PCs (n = 13). Mean age at diagnosis was 45 ± 15 years. The immunohistochemical subtypes were corticotroph (n = 20), lactotroph (n = 18), and nonfunctioning (n = 9) tumors. TMZ therapy started 8 years after initial diagnosis using a standard regimen (median 6 cycles) for the majority of patients. Results: Long-term radiological response to TMZ after a median follow-up of 32 months with 4 patients still on TMZ therapy was tumor regression for 9 (20%), stable disease for 8 (17%), and tumor progression for 29 patients (63%) (outcome data available for 46 patients). Progression occurred 16 months after initiation of TMZ. Median estimated progression-free survival was 23 months. Disease stabilization and median progression-free survival did not differ between patients with APTs or PCs. Predictors of tumor response were not identified. Overall, TMZ was well tolerated. Conclusion: We performed a nationwide survey on TMZ therapy in patients with APTs and PCs. While early response rates to TMZ are promising, long-term outcome is less favorable. Prolonged TMZ administration should be considered. We were not able to confirm previously reported predictors of tumor response to TMZ.
CRIS-Team Scopus Importer:2020-03-27
Keywords: aggressive pituitary tumor; pituitary carcinoma; progression-free survival; response rate; temozolomide

Einführung und Evaluation eines Stationsapothekers in der Neurochirurgie: Projektarbeit im Rahmen der Weiterbildung Klinische Pharmazie - Pauly, Anne; Busse, Marika; Koch, Sonja; Dörje, Frank; Rammensee, Rudolf; Buchfelder, Michael (Krankenhauspharmazie, 2019)
2.5 full-time positions for clinical pharmacists were approved by the hospital board for a two-year project (01.01.2015 - 31.12.2016). The clinical pharmacists were deployed to different clinics with the objectives to support safety of medication therapy and achieve a pharmacoeconomic impact. A 0.45 part-time position was assigned to the neurosurgical department. During the two-year project, an evaluation period of one year was defined to assess drug related problems, pharmaceutical inquiries and pharmacoeconomic interventions. The results of the evaluation period were presented to the neurosurgical clinic management along with a final survey among the physicians and nursing staff. The neurosurgical directors decided to maintain a 0.25 clinical pharmacist position, hence a safe, efficacious and economic drug therapy can be ensured in the neurosurgical department.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Clinical pharmacist; Drug related problem; Medication management; Medication safety; Neurosurgery

e-learning comes of age: Web-based education provided by the International League Against Epilepsy - Beniczky, Sandor; Blümcke, Ingmar; Rampp, Stefan; Shisler, Priscilla; Biesel, Eva; Wiebe, Samuel (Epileptic Disorders, 2020)
Education tools and programs using interactive digital content, distributed on the internet, are increasingly becoming an integral part of postgraduate medical education. The coronavirus pandemic and global lockdown hoisted a major challenge for traditional teaching courses. A timely solution is to focus attention and reinforce web-based teaching programs. For more than 15 years, the ILAE has been developing and managing a wide range of e-learning programs. This paper provides an overview on the e-learning portfolio of the ILAE, including tutored e-courses, self-paced interactive e-courses and online multimedia resources, all linked to the ILAE curriculum and learning objectives addressing specific levels of professional experience. All e-learning programs will become available through the new ILAE Academy platform (www.ilae-academy.org), in July 2020. e-learning is an important tool for reaching the global educational mission of the ILAE.
CRIS-Team WoS Importer:2020-07-17

Elevated level of cerebrospinal fluid and systemic chemokine CCL5 is a predictive biomarker of clinical outcome after aneurysmal subarachnoid hemorrhage (aSAH) - Chaudhry, Shafqat Rasul; Kinfe, Thomas Mehari; Lamprecht, Alf; Niemelä, Mika; Dobreva, Gergana; Hänggi, Daniel; Muhammad, Sajjad (Cytokine, 2020)
Background: Pathophysiology of aneurysmal subarachnoid hemorrhage (aSAH) is highly complex. Bleeding from ruptured aneurysm causes increase in intracranial pressure that disrupts blood-brain barrier leading to infiltration of peripheral immune cells. Interactions between the infiltrated leukocytes and the resident brain cells in the injured tissue mainly determine the delayed tissue damage. Recruitment of leukocytes in the injured brain is mainly mediated by the chemokines. Chemokine C-C motif ligand 5 (CCL5) is a potent pro-inflammatory chemokine shown to be upregulated in preclinical SAH studies. However, detailed clinical investigations exploring the association of cerebrospinal fluid (CSF) and systemic CCL5 and post-aSAH complications and clinical outcome are still lacking. This study investigated CSF and systemic CCL5 after aSAH and its association with clinical outcome and post-aSAH complications. Methods: CSF and serum from control and aSAH patients were obtained after centrifugation of the CSF and peripheral blood, and were preserved at −80 °C until quantification by an enzyme-linked immunoassay. Patient pertinent data, post-aSAH complications and clinical outcome (modified Rankin scale [mRS] and Glasgow outcome scale [GOS]) were retrieved from patient records. Results: A significant increase in CSF and serum CCL5 levels was observed on post-aSAH day 1 and day 7 compared to control patients. Dichotomization of patients to poor (mRS 3–6 or GOS 1–3) and good (mRS 0–2 or GOS 4–5) clinical outcomes showed significantly higher serum CCL5 levels in patients with good clinical outcome at discharge, but lower CSF CCL5 levels. Interestingly, significantly lower serum CCL5 levels were observed on post-aSAH day 7 in patients who have additional intracerebral bleeding or the patients who developed chronic hydrocephalus or pneumonia. Whereas, CSF CCL5 levels significantly increased on post-aSAH day 1 in patients developing chronic hydrocephalus, delayed ischemic neurological deficits and intraventricular hemorrhage. CSF CCL5 levels on post-aSAH day 1 were correlated with poor clinical outcome, however, serum CCL5 levels on post-aSAH day 7 were correlated with good clinical outcome. Conclusion: Systemic and CSF CCL5 levels were elevated after aSAH and levels of serum CCL5 on day 7 were associated independently with clinical outcome (GOS and mRS) at discharge. Therapeutic approaches targeting CCL5 might be beneficial in aSAH.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Aneurysms; Chemokines; Clinical outcome; Post-SAH complications; RANTES; Stroke; Systemic inflammation

Elevated systemic Il-10 levels indicate immunodepression leading to nosocomial infections after aneurysmal subarachnoid hemorrhage (SAH) in patients - Chaudhry, Shafqat Rasul; Kahlert, Ulf Dietrich; Kinfe, Thomas Mehari; Lamprecht, Alf; Niemelä, Mika; Hänggi, Daniel; Muhammad, Sajjad (International Journal of Molecular Sciences, 2020)
Background: Aneurysmal subarachnoid hemorrhage (SAH) is a highly complex disease with very high mortality and morbidity. About one-third of SAH patients suffer from systemic infections, predominantly pneumonia, that can contribute to excess mortality after SAH. Immunodepression is probably the most important mechanism leading to infections. Interleukin-10 (IL-10) is a master regulator of immunodepression, but it is still not clear if systemic IL-10 levels contribute to immunodepression, occurrence of infections and clinical outcome after SAH. Methods: This explorative study included 76 patients with SAH admitted to our neurointensive care unit within 24 h after ictus. A group of 24 patients without any known intracranial pathology were included as controls. Peripheral venous blood was withdrawn on day 1 and day 7 after SAH. Serum was isolated by centrifugation and stored at −80 °C until analysis. Serum IL-10 levels were determined by enzyme-linked immunoassay (ELISA). Patient characteristics, post-SAH complications and clinical outcome at discharge were retrieved from patients’ record files. Results: Serum IL-10 levels were significantly higher on day 1 and day 7 in SAH patients compared to controls. Serum IL-10 levels were significantly higher on day 7 in patients who developed any kind of infection, cerebral vasospasm (CVS) or chronic hydrocephalus. Serum IL-10 levels were significantly higher in SAH patients discharged with poor clinical outcome (modified Rankin Scale (mRS) 3–6 or Glasgow Outcome Scale (GOS) 1–3). Conclusion: Serum IL-10 might be an additional useful parameter along with other biomarkers to predict post-SAH infections.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Aneurysm; Anti-inflammatory; Cerebral vasospasm; Clinical outcome; Complications; Cytokine; Early brain injury; Inflammation; Stroke; Subarachnoid hemorrhage

Emerging roles of leptin in Parkinson's disease: Chronic inflammation, neuroprotection and more? - Regensburger, Martin; Rasul Chaudhry, Shafqat; Yasin, Hammad; Zhao, Yining; Stadlbauer, Andreas; Buchfelder, Michael; Kinfe, Thomas Mehari (Brain Behavior and Immunity, 2023)
An increasing body of experimental evidence implicates a relationship between immunometabolic deterioration and the progression of Parkinson's disease (PD) with a dysregulation of central and peripheral neuroinflammatory networks mediated by circulating adipokines, in particular leptin. We screened the current literature on the role of adipokines in PD. Hence, we searched known databases (PubMed, MEDLINE/OVID) and reviewed original and review articles using the following terms: “leptin/ObR”, “Parkinson's disease”, “immune-metabolism”, “biomarkers” and “neuroinflammation”. Focusing on leptin, we summarize and discuss the existing in vivo and in vitro evidence on how adipokines may be protective against neurodegeneration, but at the same time contribute to the progression of PD. These components of the adipose brain axis represent a hitherto underestimated pathway to study systemic influences on dopaminergic degeneration. In addition, we give a comprehensive update on the potential of adjunctive therapeutics in PD targeting leptin, leptin-receptors, and associated pathways. Further experimental and clinical trials are needed to elucidate the mechanisms of action and the value of central and peripheral adipose-immune-metabolism molecular phenotyping in order to develop and validate the differential roles of different adipokines as potential therapeutic target for PD patients.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Immunometabolism; Leptin; Neurodegeneration; Neuroinflammation; ObR; Parkinson‘s disease

Endoscope-Assisted Microsurgical Removal of an Optic Foramen Meningioma through a Frontolateral Minicraniotomy - Kurucz, Peter; Opitz, Holger; Buchfelder, Michael; Ganslandt, Oliver (Journal of Neurological Surgery Part B: Skull Base, 2018)
A 72-year-old male patient with visual disturbance of the right eye was diagnosed with a small meningioma of the right optic foramen extending to the carotid cistern. The operation was performed through an individually tailored frontolateral minicraniotomy via a curvilinear skin incision behind the hairline. Endoscope-assisted microsurgical technique was used to resect the lesion. The roof of the optic canal was partly removed to get access to the intraforaminal tumor parts. The lesion could be completely removed and the patient showed a satisfactory visual recovery in the follow-up examinations. The link to the video can be found at: https://youtu.be/p8EZx7aryeQ .
EVALuna2:214806

Endoscope-Assisted Minimally Invasive Microsurgical Removal of a Medium-Sized Acoustic Neuroma (T3a) through a Retrosigmoid Mini-Craniotomy with Preservation of Hearing - Kurucz, Peter; Barany, Laszlo; Buchfelder, Michael; Ganslandt, Oliver (Journal of Neurological Surgery Part B: Skull Base, 2019)
A 45-year-old male patient with reduced hearing in the right ear was diagnosed with a medium-sized (T3a) acoustic neuroma. The operation was performed through an individually tailored retrosigmoid mini-craniotomy. Endoscope-assisted microsurgical technique was applied to early detect the location of the facial and cochlear nerves as well as to look around the hidden corners during the surgery. The entire operation was performed without using brain retractors. The moderate intrameatal extension of the tumor and the use of angled endoscopes allowed to avoid the drilling of the internal auditory meatus. The lesion could be completely removed and the patient showed a satisfactory hearing recovery in the follow-up examinations 3 months after the surgery. The link to the video can be found at: https://youtu.be/dAYLakih924.
CRIS-Team Scopus Importer:2019-06-18
Keywords: acoustic neuroma; endoscope-assisted microsurgery; keyhole approach; minimally invasive; retrosigmoid craniotomy

Endoscopic approach-routes in the posterior fossa cisterns through the retrosigmoid keyhole craniotomy: an anatomical study - Kurucz, Peter; Baksa, Gabor; Patonay, Lajos; Thaher, Firas; Buchfelder, Michael; Ganslandt, Oliver (Neurosurgical Review, 2017)
Endoscopy in cerebellopontine angle surgery is an increasingly used technique. Despite of its advantages, the shortcomings arising from the complex anatomy of the posterior fossa are still preventing its widespread use. To overcome these drawbacks, the goal of this study was to define the anatomy of different endoscopic approaches through the retrosigmoid craniotomy and their limitations by surgical windows. Anatomical dissections were performed on 25 fresh human cadavers to describe the main approach-routes. Surgical windows are spaces surrounded by neurovascular structures acting as a natural frame and providing access to deeper structures. The approach-routes are trajectories starting at the craniotomy and pointing to the lesion, passing through certain windows. Twelve different windows could be identified along four endoscopic approach-routes. The superior route provides access to the structures of the upper pons, lower mesencephalon, and the upper neurovascular complex through the suprameatal, superior cerebellar, and infratrigeminal windows. The supratentorial route leads to the basilar tip and some of the suprasellar structures via the ipsi- and contralateral oculomotor and dorsum sellae windows. The central endoscopic route provides access to the middle pons and the middle neurovascular complex through the inframeatal, AICA, and basilar windows. The inferior endoscopic route is the pathway to the medulla oblongata and the lower neurovascular complex through the accessory, hypoglossal, and foramen magnum windows. The anatomy and limitations of each surgical windows were described in detail. These informations are essential for safe application of endoscopy in posterior fossa surgery through the retrosigmoid approach.
EVALuna2:102200

EpCAM (CD326) is differentially expressed in craniopharyngioma subtypes and Rathke's cleft cysts - Thimsen, Vivian; Hoelsken, Annett; Buchfelder, Michael; Flitsch, Joerg; Fahlbusch, Rudolf; Stefanits, Harald; Losa, Marco; Jones, David T. W.; Buslei, Rolf (Scientific Reports, 2016)
The epithelial cell adhesion molecule (EpCAM) is a type I glycoprotein located on the surface of epithelial cells. It is strongly expressed in many neoplasms and already used in the diagnosis and distinction of various tumour subtypes. Comparative studies about EpCAM expression in cystic sellar lesions are lacking. Therefore, we analysed its distribution pattern in adamantinomatous (aCP) and papillary (pCP) craniopharyngiomas (CP) and Rathke's Cleft Cysts (RCC) using immunohistochemistry and gene expression profiling. Whereas the protein was not detectable in pCP (n = 10), all aCP (n = 64) showed distinct staining patterns. The vast majority of RCC (n = 10) also appeared positive, but these displayed notably lower labeling scores. Additionally, significantly higher mRNA levels were detectable in aCP (n = 19) when compared to pCP (n = 10) (p = 9.985(-8)). Furthermore, pediatric aCP cases, in general, exhibited stronger EpCAM staining levels compared to adult ones (p = 0.015). However, we were not able to verify this result on mRNA level. In summary, our findings demonstrate that EpCAM can be used as an additional distinction-marker for cystic lesions of the sellar region. Its unknown function in aCP and the presence of an approved monoclonal bispecific trifunctional antibody for cancer therapy are interesting starting points for further studies.
EVALuna2:7331

Epigenetics in Brain Tumors: HDACs Take Center Stage - Eyüpoglu, Ilker Yasin; Savaskan, Nicolai E. (Current Neuropharmacology, 2016)
Primary tumors of the brain account for 2 % of all cancers with malignant gliomas taking the lion's share with 70 %. Malignant gliomas (high grade gliomas WHO° III and °IV) belong to one of the most threatening tumor entities known with their disappointingly short median survival time of just 14 months despite maximum therapy according to current gold standards. Malignant gliomas secrete various factors, through which they adapt and manipulate the tumor microenvironment to their advantage. Epigenetic mechanisms operate on the tumor microenvironment by de- and methylation processes and imbalances between the histone deacetylases (HDAC) and histone acetylases (HAT). Many compounds have been discovered modulating epigenetically controlled signals. Recent studies indicate that xCT (system xc-, SLC7a11) and CD44 (H-CAM,ECM-III, HUTCH-1) functions as a bridge between these epigenetic regulatory mechanisms and the malignant glioma progression. The question that ensues is the extent to which therapeutic intervention on these signaling pathways would exert influence on the treatment of malignant gliomas as well as the extent to which manipulation of HDAC activity can sensitize tumor cells for chemotherapeutics through 'epigenetic priming'. Considering the current stagnation in the development of therapeutic options the need for new strategies in the treatment of gliomas has never been so urgent. Here, the possibility of pharmacological intervention on tumor-associated genes by epigenetic priming opens a novel path in combating primary brain tumors.
EVALuna2:22852

Erlangen Experience on radiosurgical Treatment for Trigeminal Neuralgia - Lettmaier, S.; Putz, Florian; Distel, Luitpold; Bischoff, B.; Bozhkov, Y.; Merkel, Andreas; Lambrecht, U.; Koca, S.; Fietkau, Rainer (2017)
EVALuna2:32886

Erratum: Histological criteria for atypical pituitary adenomas–data from the German pituitary adenoma registry suggests modifications - Miermeister, Christian; Petersenn, Stephan; Buchfelder, Michael; Fahlbusch, Rudolf; Luedecke, Dieter K.; Hoelsken, Annett; Bergmann, Markus; Knappe, Ulrich Johannes; Hans, Volkmar H.; Flitsch, Joerg; Saeger, Wolfgang; Buslei, Rolf (Acta Neuropathologica Communications, 2016)
The original version of this article unfortunately contained a mistake in the author list. The name of one co-author is written wrong in the final version of the article; Dr Hans Ulrich Knappe should be Ulrich Johannes Knappe. The updated author list is provided below: Christian P. Miermeister, Stephan Petersenn, Michael Buchfelder, Rudolf Fahlbusch, Dieter K.Lüdecke, Annett Hölsken, Markus Bergmann, Ulrich Johannes Knappe, Volkmar H. Hans, Jörg Flitsch, Wolfgang Saeger and Rolf Buslei.
EVALuna2:7381

Ese clinical practice guideline on functioning and nonfunctioning pituitary adenomas in pregnancy - Luger, A.; Broersen, L. H. A.; Biermasz, N. R.; Biller, B. M. K.; Buchfelder, Michael; Chanson, P.; Jorgensen, J. O. L.; Kelestimur, F.; Llahana, S.; Maiter, D.; Mintziori, G.; Petraglia, F.; et al. (European Journal of Endocrinology, 2021)
Pregnancies are rare in women with pituitary adenomas, which ma y relate to hormone excess from secretory subtypes such as prolactinomas or corticotroph adenomas. Decrea sed fertility may also result from pituitary hormone deficiencies due to compression of the gland by large tumours an d/or surgical or radiation treatment of the lesion. Counselling premenopausal women with pituitary adenomas about t heir chance of conceiving spontaneously or with assisted reproductive technology, and the optimal pre-conc eption treatment, should start at the time of initial diagnosis. The normal physiological changes during pregnancy ne ed to be considered when interpreting endocrine tests in women with pituitary adenomas. Dose adjustments in hor mone substitution therapies may be needed across the trimesters. When medical therapy is used for pituitary horm one excess, consideration should be given to the known efficacy and safety data specific to pregnant women for each therapeutic option. In healthy women, pituitary gland size increases during pregnancy. Since some pituitary ade nomas also enlarge during pregnancy, there is a risk of visual impairment, especially in women with macroadenomas or tumours near the optic chiasm. Pituitary apoplexy represents a rare acute complication of adenomas requiring surv eillance, with surgical intervention needed in some cases. This guideline describes the choice and timing of diagno stic tests and treatments from the pre-conception stage until after delivery, taking into account adenoma size, locatio n and endocrine activity. In most cases, pregnant women with pituitary adenomas should be managed by a multidisciplinar y team in a centre specialised in the treatment of such tumours.
CRIS-Team Scopus Importer:2021-09-17

Essentials in intraoperative indocyanine green videoangiography assessment for intracranial aneurysm surgery: conclusions from 295 consecutively clipped aneurysms and review of the literature - Roessler, Karl; Krawagna, Maximilian; Dörfler, Arnd; Buchfelder, Michael; Ganslandt, Oliver (Neurosurgical Focus, 2014)
Indocyanine green (ICG) videoangiography (VA) in cerebral aneurysm surgery allows confirmation of blood flow in parent, branching, and perforating vessels as well as assessment of remnant aneurysm parts after clip application. A retrospective analysis and review of the literature were conducted to determine the current essential advantages of ICG-VA in aneurysm surgery.The authors retrospectively evaluated all aneurysm cases treated with the aid of intraoperative ICG-VA at a single institution between 2007 and 2013. They also analyzed the literature published since the initial description of ICG-VA in 2003.Two hundred forty-six procedures were performed in 232 patients harboring 295 aneurysms. The patients, whose mean age was 54 years, consisted of 159 women and 73 men. One hundred twenty-four surgeries were performed after subarachnoid hemorrhage, and 122 were performed for incidental aneurysms. Single aneurysms were clipped in 185 patients, and multiple aneurysms were clipped in 47 (mean aneurysm diameter 6.9 mm, range 2-40 mm). No complications associated with ICG-VA occurred. Intraoperative microvascular Doppler ultrasonography was performed before ICG-VA in all patients, and postoperative digital subtraction angiography (DSA) studies were available in 121 patients (52.2%) for retrospective comparative analysis. In 22 (9%) of 246 procedures, the clip position was modified intraoperatively as a consequence of ICG-VA. Stenosis of the parent vessels (16 procedures) or occlusion of the perforators (6 procedures), not detected by micro-Doppler ultrasonography, were the most common problems demonstrated on ICG-VA. In another 11 procedures (4.5%), residual perfusion of the aneurysm was observed and one or more additional clips were applied. Vessel stenosis or a compromised perforating artery occurred independent of aneurysm location and was about equally common in middle cerebral artery and anterior communicating artery aneurysms. In 2 procedures (0.8%), aneurysm puncture revealed residual blood flow within the lesion, which had not been detected by the ICG-VA. In the postoperative DSA studies, unexpected small (< 2 mm) aneurysm neck remnants, which had not been detected on intraoperative ICG-VA, were found in 11 (9.1%) of 121 patients. However, these remnants remained without consequence except in 1 patient with a 6-mm residual aneurysm dome, which was subsequently embolized with coils.In a large cohort of consecutive patients, ICG-VA proved to be a helpful intraoperative tool and led to a significant intraoperative clip modification rate of 15%. However, small, < 2-mm-wide neck remnants and a 6-mm residual aneurysm were missed by intraoperative ICG-VA in up to 10% of patients. Results in this study confirm that DSA is indispensable for postoperative quality assessment in complex aneurysm surgery.
EVALuna2:22828

Etomidate activates epileptic high frequency oscillations - Rampp, Stefan; Heers, M.; Schoenherr, M.; Schmitt, F. C.; Hopfengaertner, R.; Stefan, Hermann; et al. (Clinical Neurophysiology, 2014)
The short acting anesthetic etomidate has been shown to provoke epileptic spikes and rarely seizures. Influence of etomidate on the occurrence of epileptic HFO (high frequency oscillations) however is unknown. An HFO inducing effect of etomidate would allow further validation of the substance as a provocation measure in presurgical evaluation as well as provide insights into the common mechanisms of HFO, spike and seizure generation.We retrospectively analyzed EEG data from four patients who underwent etomidate activation during invasive video-EEG monitoring with subdural strip electrodes. Spikes were manually selected in raw data, HFO in band pass filtered data (80-250Hz). Rate and spatial distribution of HFO and spikes in three segments were compared: immediately after etomidate administration, as well as during slow wave sleep and while awake.Rates of HFO and spikes increased significantly after etomidate administration: Overall average rates of spikes were 9.7/min during sleep, 10/min while awake and 61.4/min after etomidate. Average HFO rates were 9.5/min during sleep, 8.3/min while awake and 24.4/min after etomidate (p<0.001, non-parametric ANOVA). Spatial distributions of HFO and spikes after administration of etomidate were consistent with the seizure onset zone (SOZ) and area of resection when available (SOZ: two patients; resection: one patient; no information: one patient). Except for spurious events, no additional HFO and spike foci were seen with activation.Etomidate administration activates spikes and HFO. Spatial distributions do not extend beyond electrodes showing spikes and HFO without Etomidate and seem consistent with the epileptic network.Etomidate activation is a safe procedure to provoke not only epileptic spikes but also HFO, which were shown to have a high specificity for the SO
EVALuna2:16662

Evaluating a paradigm shift from anterior decompression and fusion to muscle-preserving selective laminectomy: a single-center study of degenerative cervical myelopathy - Kitamura, Kazuya; de Dios, Eddie; Bodon, Gergely; Barany, Laszlo; MacDowall, Anna (Journal of Neurosurgery-Spine, 2022)
OBJECTIVE Muscle-preserving selective laminectomy (SL) is an alternative to conventional decompression surgery in patients with degenerative cervical myelopathy (DCM). It is less invasive, preserves the extensor musculature, and maintains the range of motion of the cervical spine. Therefore, the preferred treatment for DCM at the authors’ institution has changed from anterior decompression and fusion (ADF), including anterior cervical discectomy and fusion (ACDF) and anterior cervical corpectomy and fusion (ACCF), toward SL. The aim of this study was to evaluate surgical outcomes before and after this paradigm shift with patient-reported outcome measures (PROMs), complications, reoperations, and cost-effectiveness. METHODS This study was a retrospective register-based cohort study. All patients with DCM who underwent ADF or SL at the authors’ institution from 2008 to 2019 were reviewed. Using ANCOVA, changes in PROMs from baseline to the 2-year follow-up were compared between the two groups, adjusting for clinicodemographic parameters, baseline PROMs, number of decompressed levels, and MRI measurements (C2–7 Cobb angle, C2–7 sagittal vertical axis [SVA], and modified K-line interval [mK-line INT]). The PROMs, including the European Myelopathy Score (EMS), the Neck Disability Index (NDI), and the EQ-5D, were collected from the national Swedish Spine Register. Complications, reoperations, and in-hospital treatment costs were also compared between the two groups. RESULTS Ninety patients (mean age 60.7 years, 51 men [57%]) were included in the ADF group and 63 patients (mean age 68.8 years, 41 men [65%]) in the SL group. The ADF and SL groups had similar PROMs at baseline. The preoperative MR images showed similar C2–7 Cobb angles (10.7° [ADF] vs 14.1° [SL], p = 0.12) and mK-line INTs (4.08 vs 4.88 mm, p = 0.07), but different C2–7 SVA values (16.2 vs 19.3 mm, p = 0.04). The comparison of ANCOVA-adjusted mean changes in PROMs from baseline to the 2-year follow-up presented no significant differences between the groups (EMS, p = 0.901; NDI, p = 0.639; EQ-5D, p = 0.378; and EQ-5D health, p = 0.418). The overall complication rate was twice as high in the ADF group (22.2% vs 9.5%, p = 0.049), while the reoperation rate was comparable (16.7% vs 7.9%, p = 0.146). The average in-hospital treatment cost per patient was 6617 (USD) for SL, 7046 for ACDF, and 12,000 for ACCF. CONCLUSIONS SL provides similar PROMs after 2 years, a significantly lower complication rate, and better cost-effectiveness compared with ADF.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anterior decompression and fusion; cost-effectiveness; degenerative cervical myelopathy; muscle-preserving selective laminectomy; patient-reported outcome measure

Evaluation of a novel noninvasive ICP monitoring device in patients undergoing invasive ICP monitoring: preliminary results - Ganslandt, Oliver; Mourtzoukos, Stylianos; Stadlbauer, Andreas; Sommer, Bjoern; Rammensee, Rudolf (Journal of Neurosurgery, 2018)
OBJECTIVE There is no established method of noninvasive intracranial pressure (NI-ICP) monitoring that can serve as an alternative to the gold standards of invasive monitoring with external ventricular drainage or intraparenchymal monitoring. In this study a new method of NI-ICP monitoring performed using algorithms to determine ICP based on acoustic properties of the brain was applied in patients undergoing invasive ICP (I-ICP) monitoring, and the results were analyzed. METHODS In patients with traumatic brain injury and subarachnoid hemorrhage who were undergoing treatment in a neurocritical intensive care unit, the authors recorded ICP using the gold standard method of invasive external ventricular drainage or intraparenchymal monitoring. In addition, the authors simultaneously measured the ICP noninvasively with a device (the HS-1000) that uses advanced signal analysis algorithms for acoustic signals propagating through the cranium. To assess the accuracy of the NI-ICP method, data obtained using both I-ICP and NI-ICP monitoring methods were analyzed with MATLAB to determine the statistical significance of the differences between the ICP measurements obtained using NI-ICP and I-ICP monitoring. RESULTS Data were collected in 14 patients, yielding 2543 data points of continuous parallel ICP values in recordings obtained from I-ICP and NI-ICP. Each of the 2 methods yielded the same number of data points. For measurements at the ≥ 17-mm Hg cutoff, which was arbitrarily chosen for this preliminary analysis, the sensitivity and specificity for the NI-ICP monitoring were found to be 0.7541 and 0.8887, respectively. Linear regression analysis indicated that there was a strong positive relationship between the measurements. Differential pressure between NI-ICP and I-ICP was within ± 3 mm Hg in 63% of data-paired readings and within ± 5 mm Hg in 85% of data-paired readings. The receiver operating characteristic-area under the curve analysis revealed that the area under the curve was 0.895, corresponding to the overall performance of NI-ICP monitoring in comparison with I-ICP monitoring. CONCLUSIONS This study provides the first clinical data on the accuracy of the HS-1000 NI-ICP monitor, which uses advanced signal analysis algorithms to evaluate properties of acoustic signals traveling through the brain in patients undergoing I-ICP monitoring. The findings of this study highlight the capability of this NI-ICP device to accurately measure ICP noninvasively. Further studies should focus on clinical validation for elevated ICP values.
EVALuna2:214803

Expert accuracy and inter-rater agreement of “must-know” EEG findings for adult and child neurology residents - Nascimento, Fábio A.; Katyal, Roohi; Olandoski, Marcia; Gao, Hong; Yap, Samantha; Matthews, Rebecca; Rampp, Stefan; Tatum, William; Strowd, Roy; Beniczky, Sándor (Epileptic Disorders, 2023)
Objective: We published a list of “must-know” routine EEG (rEEG) findings for trainees based on expert opinion. Here, we studied the accuracy and inter-rater agreement (IRA) of these “must-know” rEEG findings among international experts. Methods: A previously validated online rEEG examination was disseminated to EEG experts. It consisted of a survey and 30 multiple-choice questions predicated on the previously published “must-know” rEEG findings divided into four domains: normal, abnormal, normal variants, and artifacts. Questions contained de-identified 10–20-s epochs of EEG that were considered unequivocal examples by five EEG experts. Results: The examination was completed by 258 international EEG experts. Overall mean accuracy and IRA (AC1) were 81% and substantial (0.632), respectively. The domain-specific mean accuracies and IRA were: 76%, moderate (0.558) (normal); 78%, moderate (0.575) (abnormal); 85%, substantial (0.678) (normal variants); 85%, substantial (0.740) (artifacts). Academic experts had a higher accuracy than private practice experts (82% vs. 77%; p =.035). Country-specific overall mean accuracies and IRA were: 92%, almost perfect (0.836) (U.S.); 86%, substantial (0.762) (Brazil); 79%, substantial (0.646) (Italy); and 72%, moderate (0.496) (India). In conclusion, collective expert accuracy and IRA of “must-know” rEEG findings are suboptimal and heterogeneous. Significance: We recommend the development and implementation of pragmatic, accessible, country-specific ways to measure and improve the expert accuracy and IRA.
CRIS-Team Scopus Importer:2023-12-29
Keywords: education; EEG; EEG education; inter-rater agreement; inter-rater variability; noise

Expression of SRY-related HMG Box Transcription Factors (Sox) 2 and 9 in Craniopharyngioma Subtypes and Surrounding Brain Tissue - Thimsen, Vivian; John, Nora; Buchfelder, Michael; Flitsch, Joerg; Fahlbusch, Rudolf; Stefanits, Harald; Knosp, Engelbert; Losa, Marco; Buslei, Rolf; Hoelsken, Annett (Scientific Reports, 2017)
Stem cells have been discovered as key players in the genesis of different neoplasms including craniopharyngioma (CP), a rare tumour entity in the sellar region. Sox2 and Sox9 are well-known stem cell markers involved in pituitary development. In this study we analysed the expression of both transcription factors using immunohistochemistry in a large cohort of 64 adamantinomatous (aCP) and 9 papillary CP (pCP) and quantitative PCR in 26 aCP and 7 pCP. Whereas immunohistochemically Sox2+ cells were verifiable in only five aCP (7.8%) and in 39.1% of the respective surrounding cerebral tissue, pCP specimens appeared always negative. In contrast, Sox9 was detectable in all tumours with a significantly higher expression in aCP compared to pCP (protein, p < 0.0001; mRNA p = 0.0484) This was also true for the respective tumour adjacent CNS where 63 aCP (98.4%) and six pCP (66.7%) showed Sox9+ cells. We further confirmed absence of Sox9 expression in nuclear ?-catenin accumulating cells of aCP. Our results point to the conclusion that Sox2 and Sox9, seem to play essential roles not only in the specific formation of aCP, but also in processes involving the cerebral tumour environment, which needs to be illuminated in the future.
EVALuna2:7384

Expression pattern of neuronal intermediate filament ?-internexin in anterior pituitary gland and related tumors - Schult, David; Hoelsken, A.; Buchfelder, Michael; Schlaffer, Sven-Martin; Siegel, S.; Kreitschmann-Andermahr, I.; Fahlbusch, R.; Buslei, R. (Pituitary, 2015)
?-Internexin (INA) is a class IV neuronal intermediate filament protein that maintains the morphogenesis of neurons. It is expressed in developing neuroblasts and represents the major component of the cytoskeleton in cerebellar granule cells of adult central nervous system tissue. Data concerning INA expression in the human frontal pituitary lobe and related adenomas (PA) is missing.Using immunohistochemistry we examined the distribution pattern of INA in a large cohort of 152 PA, 11 atypical PA, 4 pituitary carcinomas and 20 normal pituitaries (overall n = 187). Quantity of INA protein expression was semi-quantitatively evaluated and grouped into five categories (0 = 0 %; 1 = >0-5 %; 2 = >5-35 %; 3 = >35-80 %; 4 = >80 % of cells).Cellular staining intensity of INA appeared significantly higher in gonadotropinomas (Go, n = 62), null cell adenomas (NC, n = 7) and thyrotropinomas (TSHomas, n = 7) compared to the other tumor subtypes (p <= 0.001). Furthermore, Go and NC showed a peculiar pseudorosette-like staining pattern surrounding blood vessels in 85.5 % (59/69) of cases. Interestingly, areas exhibiting homogenous INA staining were often associated with oncocytic cell changes and decreased immunohistochemically detectable hormone expression. Only 8.5 % (8/94) of other PA showed a comparable INA distribution (p <= 0.001).Go, NC as well as TSHomas exhibit high levels of intracellular INA protein indicating neuronal transdifferentiation. A possible impact on pathogenesis and endocrine activity needs further investigation.
EVALuna2:7234

Extended salvage surgery after high-dose chemoradiation therapy for tumors in the cervico-thoracic junction with invasion of the chest wall and the spine: a case series - Wiendieck, Kurt; Dörfler, Arnd; Sommer, Bjoern (Journal of Surgical Case Reports, 2022)
The treatment of malignant tumors localized in the upper thoracic cavity and involving the spine at the cervico-thoracic junction (CTJ) is challenging. We report on three patients with malignant tumors invading the thoracic inlet and the spine at the CTJ. All three patients underwent radical tumor resection and 360 degrees spine fusion following the posterior pedicle screw instrumentation and anterior vertebrectomy combined with implantation of an expandable titanium cage. Postoperatively, a mild paresis with hypesthesia of the ipsilateral arm occurred in one patient because of brachial plexus involvement. Two patients were still alive at last follow-up after 83 and 143 months, the third patient succumbed to tumor progression 13 months after extended salvage surgery. We display the possibilities of extended 'salvage' therapy in well-selected patients that were deemed hopeless regarding neurological function, biomechanical stability and tumor control after multiple courses of combined radio-chemotherapy.
CRIS-Team WoS Importer:2023-01-27

External noise removed from magnetoencephalographic signal using independent component analyses of reference channels - Hanna, Jeffrey; Kim, Cora; Müller-Voggel, Nadia (Journal of Neuroscience Methods, 2020)
Background: Many magnetoencephalographs (MEG) contain, in addition to data channels, a set of reference channels positioned relatively far from the head that provide information on magnetic fields not originating from the brain. This information is used to subtract sources of non-neural origin, with either geometrical or least mean squares (LMS) methods. LMS methods in particular tend to be biased toward more constant noise sources and are often unable to remove intermittent noise. New method: To better identify and eliminate external magnetic noise, we propose performing ICA directly on the MEG reference channels. This in most cases produces several components which are clear summaries of external noise sources with distinct spatio-temporal patterns. We present two algorithms for identifying and removing such noise components from the data which can in many cases significantly improve data quality. Results: We performed simulations using forward models that contained both brain sources and external noise sources. First, traditional LMS-based methods were applied. While this removed a large amount of noise, a significant portion still remained. In many cases, this portion could be removed using the proposed technique, with little to no false positives. Comparison with existing method(s): The proposed method removes significant amounts of noise to which existing LMS-based methods tend to be insensitive. Conclusions: The proposed method complements and extends traditional reference based noise correction with little extra computational cost and low chances of false positives. Any MEG system with reference channels could profit from its use, particularly in labs with intermittent noise sources.
CRIS-Team Scopus Importer:2020-02-14
Keywords: ICA; Magnetoencephalography; Simulation

Extracting structured information from unstructured histopathology reports using generative pre-trained transformer 4 (GPT-4) - Truhn, Daniel; Loeffler, Chiara M.L.; Müller-Franzes, Gustav; Nebelung, Sven; Hewitt, Katherine J.; Brandner, Sebastian; Bressem, Keno K.; Foersch, Sebastian; Kather, Jakob Nikolas (Journal of Pathology, 2023)
Deep learning applied to whole-slide histopathology images (WSIs) has the potential to enhance precision oncology and alleviate the workload of experts. However, developing these models necessitates large amounts of data with ground truth labels, which can be both time-consuming and expensive to obtain. Pathology reports are typically unstructured or poorly structured texts, and efforts to implement structured reporting templates have been unsuccessful, as these efforts lead to perceived extra workload. In this study, we hypothesised that large language models (LLMs), such as the generative pre-trained transformer 4 (GPT-4), can extract structured data from unstructured plain language reports using a zero-shot approach without requiring any re-training. We tested this hypothesis by utilising GPT-4 to extract information from histopathological reports, focusing on two extensive sets of pathology reports for colorectal cancer and glioblastoma. We found a high concordance between LLM-generated structured data and human-generated structured data. Consequently, LLMs could potentially be employed routinely to extract ground truth data for machine learning from unstructured pathology reports in the future. © 2023 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team Scopus Importer:2023-12-22
Keywords: artificial intelligence; large language models; named entity recognition; natural language processing; pathology report; text mining

Extra-pseudocapsular Transnasal Transsphenoidal Resection of Pituitary Macroadenoma: Technique Note and Evaluation of Endocrine Function - Xu, Yu; Wan, Xue-Yan; Li, Lin-Han; Chen, Juan; Wang, Jun-Wen; Shu, Kai; Buchfelder, Michael; Fahlbusch, Rudolf; Lei, Ting (Current Medical Science, 2022)
Objective: In this study, we investigated the surgical technique and endocrine assessment of pituitary function of patients with macroadenoma treated by extra-pseudocapsular transnasal transsphenoidal surgery (ETTS). Methods: Clinical data of 144 patients with pituitary macroadenomas in the same surgical group at the Department of Neurosurgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology were retrospectively analyzed from January 2019 to June 2021. Based on the results of the endocrinological evaluation and MRI examinations before and after surgery, the fluctuation of pituitary function and the extent of resection were analyzed. Multiple Logistic regression analysis was used to determine the predictors affecting postoperative tumor residual. Results: Among the 144 patients with pituitary macroadenomas, 72 (50.0%) were female and 72 (50.0%) were male, the median age was 50 years, 26 (18.1%) had invasiveness grade 0, 46 (31.9%) had grade I, 57 (39.6%) had grade II, and 15 (10.4%) had grade III according to Lu's classification method. Based on observation during surgery, 37 cases (25.7%) had no pseudocapsule, 54 cases (37.5%) had incomplete pseudocapsule, and 53 cases (36.8%) had intact pseudocapsule. In addition, 91 (63.2%) patients had total resection, 39 (27.1%) had subtotal resection, and 14 (9.7%) had partial resection. As for anterior pituitary function, 13 of 19 hypothyroid patients had recovery after surgery, with a remission rate of 68.4%. Eighteen of the 26 decreased cortisol patients got back to normal, with a remission rate of 69.2%. A total of 27 of 51 patients with hypogonadism improved, with a remission rate of 52.9%. Univariate and multivariate analyses indicated that gender, tumor size, and invasiveness were predictors of postoperative residual in patients (P < 0.05). Conclusion: The results showed that ETTS is an effective treatment modality for restoring the function of pituitary gland of the patients with macroadenomas. Tumor size and invasiveness are predictors of the extent of surgical resection and postoperative residual of macroadenomas.
CRIS-Team WoS Importer:2023-01-20

EZH2 is highly expressed in pituitary adenomas and associated with proliferation - Schult, David; Hoelsken, Annett; Siegel, Sonja; Buchfelder, Michael; Fahlbusch, Rudolf; Kreitschmann-Andermahr, Ilonka; Buslei, Rolf (Scientific Reports, 2015)
Enhancer of zeste homolog 2 (EZH2) is a core epigenetic regulator, playing a crucial role in cell cycle regulation. The protein is known to be associated with proliferation and worse outcome in several tumor entities. In this study, we immunohistochemically investigated the expression pattern of EZH2 in a large cohort of pituitary tumors. These results were correlated with clinical features and double immunofluorescence stainings (DIS) were conducted to evaluate co-expression of EZH2 and proliferation marker Ki-67. Furthermore, we analyzed the effect of EZH2 inhibition on cell proliferation in vitro using the pituitary cell line AtT-20. While in the normal anterior pituitary EZH2 was almost absent, the cohort of tumors showed enhanced expression levels (p <= 0.0005). This was positively associated with Ki-67 indices (r = 0.834, p <= 0.0005) and DIF confirmed a predominant co-expression of both markers. In vitro experiments revealed a significant (p <= 0.05) decrease of tumor cell proliferation using the EZH2 inhibitor GSK126. Our results further support that epigenetic events are involved in the pathogenesis and biology of pituitary adenomas (PA). Therefore, EZH2 may function as a new potential target for therapeutic interventions in PA.
EVALuna2:7303

Fatal Mycotic Aneurysm of the Basilar Artery Caused by Aspergillus fumigatus in a Patient with Pituitary Adenoma and Meningitis - Winterholler, Martin; Coras, Roland; Geißdörfer, Walter; Rammensee, Rudolf; Gölitz, Philipp; Bogdan, Christian; Lang, Roland (Frontiers in Medicine, 2017)
Fungal infections of the central nervous system (CNS) frequently occur in immunosuppressed patients. Here, we describe the case of an immunocompetent 64-year-old man who presented with diplopia, right-sided hemiparesis, and a mild headache after cleaning and replacing nesting boxes of wild birds during the preceding months. Lumbar puncture revealed pleocytosis, elevated protein, and lactate levels in the cerebrospinal fluid (CSF). Initial imaging showed ischemia in the left thalamus and an enlargement of the sellar region. Antibiotic treatment and corticosteroids led to an initial improvement but was followed by rapid deterioration. Antibiotic treatment was modified and antifungal therapy was added. Eighteen days after admission, the patient died from a subarachnoid hemorrhage resulting from the rupture of a fusiform aneurysm of the basilar artery. Microbiological culture of CSF was negative, but a positive galactomannan assay suggested fungal infection which was corroborated by detection of Aspergillus fumigatus DNA in pan-fungal PCR and sequencing. The presence of septated hyphae in the wall of the basilar artery confirmed the diagnosis of a mycotic aneurysm caused by hyphomycetal infection. In addition, brain autopsy revealed the presence of an invasive adrenocorticotrophic hormone-producing pituitary adenoma with arrosion of the sellar bone. This process and its invasiveness likely facilitated the spread of the fungal pathogen from the sphenoid sinus to the dura mater and finally led to cerebral angioinvasion. Our case demonstrates the challenge to timely diagnose and effectively treat aspergillosis as a cause of CNS infection also in apparently immunocompetent patients. The potential of assays detecting fungal antigens and of PCR to facilitate a timely diagnosis is discussed.
EVALuna2:7760

Ferroptosis and PPAR-gamma in the limelight of brain tumors and edema - Yakubov, Eduard; Schmid, Sebastian; Hammer, Alexander; Chen, Daishi; Dahlmanns, Jana; Mitrovic, Ivana; Zurabashvili, Luka; Savaskan, Nicolai; Steiner, Hans Herbert; Dahlmanns, Marc (Frontiers in Oncology, 2023)
Human malignant brain tumors such as gliomas are devastating due to the induction of cerebral edema and neurodegeneration. A major contributor to glioma-induced neurodegeneration has been identified as glutamate. Glutamate promotes cell growth and proliferation in variety of tumor types. Intriguently, glutamate is also an excitatory neurotransmitter and evokes neuronal cell death at high concentrations. Even though glutamate signaling at the receptor and its downstream effectors has been extensively investigated at the molecular level, there has been little insight into how glutamate enters the tumor microenvironment and impacts on metabolic equilibration until recently. Surprisingly, the 12 transmembrane spanning tranporter xCT (SLC7A11) appeared to be a major player in this process, mediating glutamate secretion and ferroptosis. Also, PPARγ is associated with ferroptosis in neurodegeneration, thereby destroying neurons and causing brain swelling. Although these data are intriguing, tumor-associated edema has so far been quoted as of vasogenic origin. Hence, glutamate and PPARγ biology in the process of glioma-induced brain swelling is conceptually challenging. By inhibiting xCT transporter or AMPA receptors in vivo, brain swelling and peritumoral alterations can be mitigated. This review sheds light on the role of glutamate in brain tumors presenting the conceptual challenge that xCT disruption causes ferroptosis activation in malignant brain tumors. Thus, interfering with glutamate takes center stage in forming the basis of a metabolic equilibration approach.
CRIS-Team Scopus Importer:2023-08-18
Keywords: ferroptosis; glioblastoma; glutamate; peritumoral edema; SLC7A11

First German experience using augmented reality for neuroanatomy education in undergraduate medical students: a feasibility and questionnaire-based study - Zhao, Yining; Bozhkov, Yavor; Chen, Xiaolei; Fuchs, Katharina; Buchfelder, Michael; Fester, Lars; Souza de Oliveira, Daniela; Del Vecchio, Alessandro; Kinfe, Thomas (Educational Technology Research and Development, 2025)
To date, neuroanatomy education courses are still based on two-dimensional (2D) illustrations combined with cadaver dissections. To gain a more comprehensive understanding of neuroanatomy, we offered mixed reality experience using a head-mounted device (HMD) for medical students during their neuroanatomy course. This pilot study´s purpose was to determine whether or not, from a pragmatic view, the utilization of 3D VR/AR via HMD is viable in neuroanatomy courses and aimed to evaluate the feasibility of using mixed reality in neuroanatomy education and experiences with the mixed reality brain environment. A virtual model including major neuroanatomical structures was generated from a MRI dataset using computer software. Major structures were displayed and annotated in different combinations and scenes using an HMD. Along with the 3D virtual model, the original MRI was presented in a virtual form inside the HMD. Conventional 2D anatomical atlases were also used during the seminar. Thirty medical students (11 male; 19 female; average: 23.2 years) in their second year were recruited from October 2022 to February 2023 for this study via open invitation during neuroanatomy lectures. Participants were asked to wear the HMDs and to take a 2 h neurosurgery-oriented mixed reality seminar given by a neurosurgical teacher in small groups (3 per group). A questionnaire comprising five levels of options was designed and used to evaluate the feasibility/effectiveness of this seminar. The mixed reality environment, comprising virtual 3D models of major brain structures, virtual MRI, and conventional 2D anatomical graphs, was uncomplicated and feasible for neuroanatomy education of the medical students. According to our survey, all participants (30/30) strongly agreed that the 3D visualization of the spatial relationships between anatomical structures was easy to use as a meaningful supplement. Twenty-one of the participants strongly agreed and nine quite agreed that they had more interest in neuroanatomy. Eighty-seven percent of the participants were strongly satisfied with the mixed reality seminar versus conventional neuroanatomy seminars, and the other 13% were quite satisfied with the mixed reality approach. Most of the participants (20/30) strongly agreed that mixed reality helped them memorize the anatomical structures, and 9/30 participants quite agreed. Seventy-four percent of the participants agreed that immersive mixed reality is better than 3D models presented in 2D devices. Over half of the participants could wear the HMD for over 60 min (65%) without any ophthalmic discomfort, and the HMD was reported to be well tolerable (57%). Nearly three-fourths of the participants found that handling the device was extremely simple, and the other part indicated that it was quite simple. No health issues or discomfort on the forehead occurred. As a consequence, the seminar has been officially classified as an elective neuroanatomy course for second-year medical students. The use of mixed reality with HMDs to illustrate 3D brain models relevant for the neuroanatomy cadaver dissection education and described in our study was positively perceived by the medical students and demonstrated the viability of 3D AR/VR via HMD in neuroanatomy education. Future research lines are warranted to determine the usefulness of mixed reality technologies to effectively support medical students education of the complex three-dimensional brain anatomy.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Educational technologies; Head-mounted device; Mixed augmented reality; Neuroanatomy

First German Guideline on Diagnostics and Therapy of Clinically Non-Functioning Pituitary Tumors - Deutschbein, Timo; Jaursch-Hancke, Cornelia; Knappe, Ulrich J.; Saeger, Wolfgang; Flitsch, Joerg; Bojunga, Joerg; Buchfelder, Michael; Ditzen, Beate; Gerlach, Ruediger; Gertzen, Elfriede; Honegger, Juergen; Horstmann, Gerhard A.; et al. (Experimental and Clinical Endocrinology and Diabetes, 2021)
Although non-functioning pituitary tumors are frequent, diagnostic and therapeutic concepts are not well standardized. We here present the first German multidisciplinary guideline on this topic. The single most important message is to manage the patients by a multidisciplinary team (consisting at least of an endocrinologist, a neurosurgeon, and a (neuro-) radiologist). The initial diagnostic work-up comprises a detailed characterization of both biochemical (focusing on hormonal excess or deficiency states) and morphological aspects (with magnetic resonance imaging of the sellar region). An ophthalmological examination is only needed in presence of symptoms or large tumors affecting the visual system. Asymptomatic, hormonally inactive tumors allow for a 'wait and scan' strategy. In contrast, surgical treatment by an experienced pituitary surgeon is standard of care in case of (impending) visual impairment. Therapeutic options for incompletely resected or recurrent tumors include re-operation, radiotherapy, and observation; the individual treatment plan should be developed multidisciplinary. Irrespective of the therapeutic approach applied, patients require long-term follow-up. Patient with larger pituitary tumors or former surgery/radiotherapy should be regularly counseled regarding potential symptoms of hormonal deficiency states.
CRIS-Team WoS Importer:2021-04-02

Flat panel detector angiographic CT for stent-assisted coil embolization of broad-based cerebral aneurysms - Richter, Gregor; Engelhorn, Tobias; Struffert, Tobias; Dölken, Marc; Ganslandt, Oliver; Hornegger, Joachim; Kalender, Willi Alfred; Dörfler, Arnd (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The purpose of this work was to evaluate angiographic CT (ACT) in the combined application of a self-expanding neurovascular stent and detachable platinum coils in the management of broad-based and fusiform intracranial aneurysms. MATERIALS AND METHODS: Eleven patients harboring wide-necked intracranial aneurysms were treated with a flexible self-expanding neurovascular stent and subsequent aneurysm embolization with platinum microcoils. ACT was performed after the interventional procedure to analyze stent position and the relationship of coils to the stent. Postprocessing included multiplanar reconstructions (MPRs) and maximum intensity projections (MIPs). ACT volume datasets were postprocessed for soft tissue visualization. RESULTS: Accurate stent placement with subsequent coil occlusion of the aneurysms was feasible in all of the patients. Similar to nonsubtracted digital subtraction angiography (DSA) images, radiopaque platinum stent markers showed excellent visibility in ACT as well. The stent struts themselves, hardly visible in nonsubtracted DSA, were visible in MPRs and MIPs of ACT in all of the patients. In aneurysms larger than 10 mm in diameter, accurate stent assessment at the level of the coils was limited due to beam hardening artifacts. Postprocedural ACT in all of the patients did not reveal any evidence of procedure-related intracranial hemorrhage. CONCLUSION: ACT provides cross-sectional, 3D visualization of endovascular stents otherwise hardly visible with plain fluoroscopy. ACT enables us to accurately determine stent position, which may be helpful in complex stent-assisted aneurysm coiling procedures. However, in aneurysms larger than 10 mm in diameter, beam hardening artifacts caused by the endoaneurysmal coil package impair visibility of the stent. Further data are necessary to evaluate the usefulness of ACT in stent-assisted aneurysm coiling.

Flat Panel Detector Computed Tomography-Guided Placement of External Ventricular Drains Using the BrainLAB Headband and Precalibrated Disposable Stylet Instrument: A Cadaveric Feasibility Study - Feulner, Julian; Lang, Stefan; Buder, Thomas; Struffert, Tobias; Buchfelder, Michael; Brandner, Sebastian (World Neurosurgery, 2018)
BACKGROUND: The standard freehand method for the insertion of external ventricular drains (EVDs) is associated with high rates of incorrect placement. Use of neuronavigation has been shown to reduce the rates of inaccurately positioned EVDs. We present a novel neuronavigation-based approach for EVD placement using flat panel detector computed tomography (FDCT) imaging. METHODS: Four cadaveric heads were used for neuronavigated placement of EVDs using the BrainLAB reference headband in combination with laser surface registration and the precalibrated disposable stylet. In 2 cases, conventional multislice CT imaging was performed to reference neuronavigation. In the other 2 cases, preprocedural imaging was performed with FDCT. After inserting the EVDs, all heads were examined again with the identical imaging method as used before the procedure, followed by evaluation of catheter position. RESULTS: Our data demonstrate that FDCT imaging provides adequate image quality for referencing neuronavigation and performing navigated neurosurgery. All EVDs showed an optimal position in the ipsilateral frontal horn. Use of a BrainLAB reference headband combined with laser surface registration and the precalibrated disposable stylet affords the advantage of not requiring rigid fixation in a clamp. CONCLUSIONS: Our presented method is fast, accurate, and easy to use. Furthermore, this study is the first to demonstrate that navigated neurosurgery can be performed on the basis of FDCT imaging.
EVALuna2:212791

Fleece-Bound Tissue Sealing in Microvascular Decompression - Tanrikulu, Levent; Buchfelder, Michael; Naraghi, Ramin (Turkish Neurosurgery, 2017)
AIM: Cerebrospinal fluid (CSF) leakage is a feared complication after microvascular decompression (MVD). In this study, we present our experience of fleece-bound tissue sealing in MVD with an aim to minimize the rate of postoperative CSF leakage. MATERIAL AND METHODS: We treated 50 patients (female/male: 26/24) with neurovascular compression (NVC) syndromes (trigeminal neuralgia, hemifacial spasm and glossopharyngeal neuralgia) by MVD from 2003 to 2006. All patients underwent retromastoid craniectomy and duraplasty by fleece-bound tissue sealing using the so-called "sandwich technique" by a three-layer reconstruction and cranioplasty. RESULTS: In 49 (98%) of 50 patients, we did not observe postoperative CSF leakage. One patient (2%) suffered postoperative CSF leakage and required surgical revision. CONCLUSION: Fleece-bound tissue sealing by a three-layer reconstruction is effective and safe in the prevention of cerebrospinal fluid leakage in microvascular decompression.
EVALuna2:102198

Flow-diverting stents allow efficient treatment of unruptured, intradural dissecting aneurysms of the vertebral artery: An explanatory approach using in vivo flow analysis - Gölitz, Philipp; Struffert, Tobias; Eyüpoglu, Ilker Yasin; Knossalla, Frauke; Dörfler, Arnd; Hölter, Philip (Interventional Neuroradiology, 2016)
Our study aimed to evaluate the efficiency of flow-diverting stents (FDS) in treating unruptured, intradural dissecting aneurysms of the vertebral artery (VADAs). Additionally, the effect of FDS on the aneurysmal flow pattern was investigated by performing in vivo flow analysis using parametric color coding (PCC).We evaluated 11 patients with unruptured, intradural VADAs, treated with FDS. Pre- and postinterventional DSA-series were postprocessed by PCC, and time-density curves were calculated. The parameters aneurysmal inflow-velocity, outflow-velocity and relative time-to-peak (rTTP) were calculated. Pre- and postinterventional values were compared and correlated with the occlusion rate after six months.Follow-up DSA detected 10 aneurysms occluded, meaning an occlusion rate of 91%. No procedure-related morbidity and mortality was found. Flow analyses revealed a significant reduction of aneurysmal inflow- velocity and prolongation of rTTP after FDS deployment. Concerning aneurysm occlusion, the postinterventional outflow-velocity turned out to be a marginally statistically significant predictor. A definite threshold value (-0.7 density change/s) could be determined for the outflow-velocity that allows prediction of complete aneurysm occlusion with high sensitivity and specificity (100%).Using FDS can be considered an efficient and safe therapy option in treating unruptured, intradural VADA. From in vivo flow analyses the postinterventional aneurysmal outflow-velocity turned out to be a potential predictor for later complete aneurysm occlusion. Here, it might be possible to determine a threshold value that allows prediction of aneurysm occlusion with high specificity and sensitivity. As fast, applicable and easy-to-handle tool, PCC could be used for procedural monitoring and might contribute to further treatment optimization.
EVALuna2:22441

FOCAL CORTICAL DYSPLASIA TYPE II IS MEG, MULTIMODAL NEURONAVIGATION AND INTRAOPERATIVE MR IMAGING HELPFUL FOR SURGERY? - Roessler, K.; Kasper, Burkhard; Heynold, Elisabeth; Coras, R.; Rampp, Stefan; Sommer, B.; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (2017)
EVALuna2:7380

Focal epilepsies: Update on diagnosis and classification - Nascimento, Fábio A.; Friedman, Daniel; Peters, Jurriaan M.; Bensalem-Owen, Meriem K; Cendes, Fernando; Rampp, Stefan; Wirrell, Elaine; Blümcke, Ingmar; Tatum, William; Beniczky, Sándor (Epileptic Disorders, 2023)
Correctly diagnosing and classifying seizures and epilepsies is paramount to ensure the delivery of optimal care to patients with epilepsy. Focal seizures, defined as those that originate within networks limited to one hemisphere, are primarily subdivided into focal aware, focal impaired awareness, and focal to bilateral tonic–clonic seizures. Focal epilepsies account for most epilepsy cases both in children and adults. In children, focal epilepsies are typically subdivided in three groups: self-limited focal epilepsy syndromes (e.g., self-limited epilepsy with centrotemporal spikes), focal epilepsy of unknown cause but which do not meet criteria for a self-limited focal epilepsy syndrome, and focal epilepsy of known cause (e.g., structural lesions—developmental or acquired). In adults, focal epilepsies are often acquired and may be caused by a structural lesion such as stroke, infection and traumatic brain injury, or brain tumors, vascular malformations, metabolic disorders, autoimmune, and/or genetic causes. In addition to seizure semiology, neuroimaging, neurophysiology, and neuropathology constitute the cornerstones of a diagnostic evaluation. Patients with focal epilepsy who become drug-resistant should promptly undergo assessment in an epilepsy center. After excluding pseudo-resistance, these patients should be considered for presurgical evaluation as a means to identify the location and extent of the epileptogenic zone and assess their candidacy for a surgical procedure. The goal of this seminar in epileptology is to summarize clinically relevant information concerning focal epilepsies. This contributes to the ILAE's mission to ensure that worldwide healthcare professionals, patients, and caregivers continue to have access to high-quality educational resources concerning epilepsy.
CRIS-Team Scopus Importer:2023-05-12
Keywords: education; electroencephalography; epilepsy; focal epilepsy; MRI; neuroimaging; neuropathology

Follow-up and long-term outcome of nonfunctioning pituitary adenoma operated by transsphenoidal surgery with intraoperative high-field magnetic resonance imaging - Berkmann, Sven; Schlaffer, Sven-Martin; Nimsky, Christopher; Fahlbusch, Rudolf; Buchfelder, Michael (Acta Neurochirurgica, 2014)
Intraoperative MRI (iMRI) increases gross total resection (GTR) rates in transsphenoidal surgery; however, long-term follow-up data is lacking. The objective is to assess the outcome of patients with nonfunctioning pituitary adenomas (NFA) at a mean follow-up of > 5 years.Patients with NFA operated in a single institution with resection control by a 1.5 T intraoperative magnetic resonance imaging (iMRI) scanner and no previous pituitary surgery were included. Microscopical transsphenoidal approaches with optional endoscopy were used. The iMRI was chosen for spacious suprasellar or retrosellar and/or invasive tumours. IMRI-scans were made if GTR or if nonresectable remnants were presumed. The patients had a full neuroradiological, endocrinological and ophthalmological follow-up at the institution.Eighty-five patients (67 % male;55 ± 14 years) with a follow-up of 5.6 ± 1.9 years were included. The initial GTR rate on iMRI was 44 %. In 83 %, further resections were possible, resulting in a final GTR rate of 66 %. In invasive tumours, the GTR rate was increased by 29 %. The detection of remnants by iMRI had high sensitivity and specificity (100 %), as opposed to endoscopy (21 %;78 %). During follow-up, four (7 %) tumours recurred and 14 (64 %) remnants grew. The recurrence and regrowth rate were 0.013 and 0.114 patients/years, respectively. Seventy-nine percent of the growing remnants were seen < 5 years postoperatively.The use of iMRI for transsphenoidal resection leads to low recurrence rates. Even in case of invasive tumours, distinctly more patients show long tumour-free follow-ups. Tumour remnants detected by iMRI are at high risk to grow within 5 years after surgery.
EVALuna2:22837

Foreword II - Buchfelder, Michael (Adult Craniopharyngiomas: Differences and Lessons from Paediatrics, 2020)
CRIS-Team Scopus Importer:2020-07-24

Frameless stereotactic functional neuronavigation combined with intraoperative magnetic resonance imaging as a strategy in highly eloquent located tumors causing epilepsy - Sommer, Bjoern; Grummich, Peter; Hamer, Hajo; Blümcke, Ingmar; Coras, Roland; Buchfelder, Michael; Roessler, Karl (Stereotactic and Functional Neurosurgery, 2014)
Background: Intractable epilepsy due to tumors located in highly eloquent brain regions is often considered surgically inaccessible because of a high risk of postoperative neurological deterioration. Intraoperative MRI and functional navigation contribute to overcome this problem. Objectives: To retrospectively investigate the long-term results and impact of functional neuronavigation and 1.5-tesla intraoperative MRI on patients who underwent surgery of tumors associated with epilepsy located close to or within eloquent brain areas. Methods: Nineteen patients (9 female, 10 male, mean age 41.4 ± 13.4 years, 11 low-grade and 8 high-grade glial tumors) were evaluated preoperatively using BOLD imaging, diffusion-tensor imaging tractography and magnetoencephalography. Functional data were implemented into neuronavigation in this multimodal approach. Results: In 14 of 19 patients (74%), complete resection was achieved, and in 5 patients significant tumor volume reduction was accomplished. Eight of 14 (57%) complete resections were achieved only by performing an intraoperative image update. Neurological deterioration was found permanently in 2 patients. After a mean follow-up of 43.8 ± 23.8 months, 15 patients (79%) became seizure free (Engel class Ia). Conclusions: Despite the highly eloquent location of tumors causing intractable epilepsy, our multimodal approach led to complete resection in more than two-thirds of patients with an acceptable neurological morbidity and excellent long-term seizure control. © 2013 S. Karger AG, Basel.
EVALuna2:7222

Frameless Stereotaxy in Stereoelectroencephalography Using Intraoperative Computed Tomography - Grote, Alexander; Gjorgjevski, Marko; Carl, Barbara; Delev, Daniel; Knake, Susanne; Menzler, Katja; Nimsky, Christopher; Bopp, Miriam H.A. (Brain Sciences, 2025)
Background: Pharmacoresistant epilepsy affects approximately one-third of all epilepsy patients, and resective surgery may offer favorable outcomes for carefully selected patients with focal epilepsy. The accurate identification of the epileptogenic zone (EZ) is essential for successful surgery, particularly in cases where non-invasive diagnostics are inconclusive. Invasive diagnostics with stereoelectroencephalography (SEEG) offer a reliable approach to localizing the EZ, especially in MRI-negative cases. Methods: This retrospective study analyzed the data of 22 patients with pharmacoresistant epilepsy who underwent frameless stereotactic SEEG electrode implantation with automated CT-based registration between September 2016 and November 2024. For measuring accuracy, Euclidean distance, radial deviation, angular deviation, and depth deviation were calculated for each electrode. Results: A total of 153 depth electrodes were implanted, targeting various cortical regions. The median Euclidean distance at the entry point was 1.54 mm (IQR 1.31), with a radial deviation of 1.33 mm (IQR 1.32). At the target level, the median Euclidean distance was 2.61 mm (IQR 1.53), with a radial deviation of 1.67 mm (IQR 1.54) and depth deviation of 0.95 mm (IQR 2.43). Accuracy was not significantly affected by electrode order, anatomical location, skull thickness, or intracranial length. Conclusions: These findings demonstrate that frameless stereotactic SEEG electrode implantation is safe and feasible for identifying the EZ. The integration of automatic intraoperative CT-based registration ensures precision. While maintaining workflow efficiency, it achieves accuracy comparable to frame-based methods. Further studies with larger cohorts are warranted to validate these results and assess their impact on surgical outcomes.
CRIS-Team Scopus Importer:2025-03-07
Keywords: accuracy; epilepsy surgery; invasive diagnostic; navigation; SEEG

FRED Flow Diverter: A Study on Safety and Efficacy in a Consecutive Group of 50 Patients - Lücking, Hannes; Engelhorn, Tobias; Lang, Stefan; Gölitz, Philipp; Kloska, Stephan; Roessler, Karl; Dörfler, Arnd (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Endovascular flow diverters are increasingly used for the treatment of cerebral aneurysms. We assessed the safety and efficacy of the Flow-Redirection Endoluminal Device (FRED) in a consecutive series of 50 patients. MATERIALS AND METHODS: Inclusion criteria were wide-neck, blister-like, or fusiform/dissecting aneurysms independent of size, treated with the FRED between February 2014 and May 2015. Assessment criteria were aneurysm occlusion, manifest ischemic stroke, bleeding, or death. The occlusion rate was assessed at 3 months with flat panel CT and at 6 months with DSA by using the Raymond classification and the O'Kelly-Marotta grading scale. RESULTS: Fifty patients with 52 aneurysms were treated with 54 FREDs; 20 patients were treated with the FRED and coils. Aneurysm size ranged from 2.0 to 18.5 mm. Deployment of the FRED was successful in all cases. There were no device-associated complications. One patient developed mild stroke symptoms that fully receded within days. There have been no late-term complications so far and no treatment-related mortality. Initial follow-up at 3 months showed complete occlusion in 72.3% of the overall study group, Six-month follow-up showed total and remnant-neck occlusion in 87.2% of patients, distributed over 81.5% of the FRED-only cases and 95.0% of the cases with combined treatment. CONCLUSIONS: The FRED flow diverter is a safe device for the treatment of cerebral aneurysms of various types. Our data reveal high occlusion rates at 3 and 6 months, comparable with those in other flow diverters. Long-term occlusion rates are expected.
EVALuna2:33142

Frequent occurrence of therapeutically reversible CMV-associated encephalopathy during radiotherapy of the brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Ruehle, Paul F.; Putz, Florian; Semrau, Sabine; et al. (Neuro-Oncology, 2016)
Neurological decline during radio(chemo)therapy of the brain is often attributed to disease progression or side effects of radiotherapy. Diagnosis of opportunistic neurotropic infections such as cytomegalovirus (CMV) infections is uncommon, even though high-grade gliomas and some brain metastases are known to contain CMV particles. We prospectively examined the frequency of CMV encephalopathy during radiotherapy of the brain.Fifty patients requiring whole-brain radiotherapy for brain metastases (n = 27) or local radio(chemo)therapy of the brain for high-grade gliomas (n = 23) were observed in the prospective observational GLIO-CMV-01 study. MRIs and blood samples were obtained before, halfway through, and at the end of radiotherapy. MRIs were screened for disease progression or increased intracranial pressure. Blood was tested for anti-CMV immunoglobulin (Ig)M, anti-CMV IgG, and CMV DNA.Thirty-two of 50 (64%) patients were positive for anti-CMV IgG before radio(chemo)therapy. Fifteen of those 32 (48%) developed viremia during or up to 28 days after treatment. Thirteen of those 15 (87%) required treatment for CMV-associated encephalopathy. MRIs were negative for disease progression, edema, or bleeding. None of the patients negative for anti-CMV IgG developed viremia, suggesting a reactivation rather than a primary infection.In the group at risk consisting of anti-CMV IgG+ patients, age >65 (P = .004) and the amount of dexamethasone taken during radio(chemo)therapy (P = .004) were associated with an increased risk for CMV-associated encephalopathy. One hundred and fifty days after the start of radio(chemo)therapy, survival was 74% (14/19) (no encephalopathy) versus 54% (7/13) (encephalopathy) (odds ratio, 0.42; 95% CI, 0.03-1.86; P = .25).CMV reactivation frequently causes encephalopathy during radio(chemo)therapy of the brain. The unexpected high incidence of this infection makes it highly clinically relevant for every treating physician.
EVALuna2:8306

From first symptoms to final diagnosis of Cushing's disease: experiences of 176 patients - Kreitschmann-Andermahr, Ilonka; Psaras, Tsambika; Tsiogka, Maria; Starz, Daniel; Kleist, Bernadette; Siegel, Sonja; Milian, Monika; Kohlmann, Johannes; Menzel, Christa; Fuehrer-Sakel, Dagmar; Honegger, Juergen; Sure, Ulrich; et al. (European Journal of Endocrinology, 2015)
To obtain structured information on the diagnostic delay in patients with Cushing's disease (CD) from the patients perspective to provide leverage points for earlier diagnosis.The study includes 176 patients with ACTH-dependent CD who had received pituitary surgery completed a self-developed questionnaire on their symptomatology before the illness was diagnosed, the course and length of the diagnostic process, and the role of the involved health care professionals.Data were analyzed statistically. Answers in free text options were categorized and counted.The overall diagnostic process took 3.8±4.8 years (median 2 years), during which 4.6±3.8 (1-30) physicians were consulted, most frequently the family physician (FP; 83.0%). The presented symptoms were various and often vague, e.g. 'poor general condition' (at FPs), or very common in the field of the visited specialist (i.e. 'skin changes' at dermatologists). Women recognized the first CD symptoms themselves significantly more frequently than men, whereas physicians recognized CD symptoms significantly more frequently in males.A clear difficulty of diagnosing CD seems that patients describe isolated symptoms to the FP or the respective specialists according to their fields of specialization. As FPs are contacted most frequently, they should be trained to recognize the broad spectrum of CD symptoms, especially in female patients with weight gain, and initiate endocrinological referral.
EVALuna2:22869

Functional and quantitative magnetic resonance myelography of symptomatic stenoses of the lumbar spine - Eberhardt, Knut; Ganslandt, Oliver Thomas; Stadlbauer, Andreas (Neuroradiology, 2014)
The objective of this study was to demonstrate that functional, quantitative magnetic resonance myelography (MRM) allows standardized diagnosis of symptomatic lumbar spinal stenoses which show at least equal detectability compared to functional myelography and postmyelographic CT (pmCT) based on intra- and postoperative findings.We investigated 43 volunteers and 47 patients with symptomatic lumbar spinal stenoses using MRM in normal position as well as in flexion and extension in a standard whole-body MR scanner. Twenty volunteers were additionally examined under axial loading. All patients were investigated by functional myelography and pmCT and 10 patients had a functional lumbar MRM postoperatively. Range of motion and cerebrospinal fluid (CSF) volumes in normal position, flexion, extension, and under axial loading (volunteers) were assessed for each segment. Detectability was determined by using intraoperative findings, and postoperative freedom of symptoms was correlated with CSF volume changes in MRM.The ranges of motion in a standard whole-body MR scanner provide adequate scope for investigations into function (flexion and extension) in both volunteers and patients. Axial loading was associated with a mechanism of extension, albeit to a far smaller extent. Detectability of lumbar stenoses was 100% for MRM, 58% for conventional myelography, and 68% for pmCT. Postoperative changes in CSF volume of levels with stenoses in MRM strongly correlated with freedom of symptoms (R = 0.772).This MRM method allows for exact diagnosis and reproducible quantification of stenoses, motion-related changes, and spondylolistheses of the lumbar spine. It may be useful for early detection of alterations in order to avoid neuronal compression.
EVALuna2:22847

Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
Exome-wide sequencing studies recently described PTPN11 as a novel brain somatic epilepsy gene. In contrast, germline mutations of PTPN11 are known to cause Noonan syndrome, a multisystem disorder characterized by abnormal facial features, developmental delay, and sporadically, also brain tumors. Herein, we performed a deep phenotype-genotype analysis of a comprehensive series of ganglioglioma (GG) with brain somatic alterations of the PTPN11/KRAS/NF1 genes compared to GG with common MAP-Kinase signaling pathway alterations, i.e., BRAFV600E. Seventy-two GG were submitted to whole exome sequencing and genotyping and 84 low grade epilepsy associated tumors (LEAT) to DNA-methylation analysis. In 28 tumours, both analyses were available from the same sample. Clinical data were retrieved from hospital files including disease onset, age at surgery, brain localization, and seizure outcome. A comprehensive histopathology staining panel was available in all cases. We identified eight GG with PTPN11 alterations, copy number variant (CNV) gains of chromosome 12, and the commonality of additional CNV gains in NF1, KRAS, FGFR4 and RHEB, as well as BRAFV600E alterations. Histopathology revealed an atypical glio-neuronal phenotype with subarachnoidal tumor spread and large, pleomorphic, and multinuclear cellular features. Only three out of eight patients with GG and PTPN11/KRAS/NF1 alterations were free of disabling-seizures 2 years after surgery (38% had Engel I). This was remarkably different from our series of GG with only BRAFV600E mutations (85% had Engel I). Unsupervised cluster analysis of DNA methylation arrays separated these tumours from well-established LEAT categories. Our data point to a subgroup of GG with cellular atypia in glial and neuronal cell components, adverse postsurgical outcome, and genetically characterized by complex alterations in PTPN11 and other RAS-/MAP-Kinase and/or mTOR signaling pathways. These findings need prospective validation in clinical practice as they argue for an adaptation of the WHO grading system in developmental, glio-neuronal tumors associated with early onset focal epilepsy.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Brain; DNA methylation; Epilepsy; Seizure; Summary plots

Gender disparity in German neurosurgery - Forster, Marie Therese; Behrens, Marion; McLean, Anna Cecilia Lawson; Nistor-Gallo, Dorothea; Weiss, Miriam; Maurer, Stefanie (Journal of Neurosurgery, 2022)
OBJECTIVE Despite the rising number of women in higher education and leadership positions, the proportional rise of female neurosurgeons still lags behind these fields. This study evaluates the gender distribution in German neurosurgical departments across all career levels, and is aimed at heightening the awareness of gender disparity and the need for improving gender equality and its related opportunities. METHODS Data on gender distribution across all professional levels in German neurosurgical departments were obtained from departmental websites as well as by email and telephone request. Results were additionally analyzed in reference to hospital ownership type of the neurosurgical departments. RESULTS A total of 140 German neurosurgical departments employing 2324 neurosurgeons were evaluated. The analysis revealed a clear preponderance of men in leadership positions. Only 9 (6.3%) of 143 department heads were women, and there were only 1 (2.4%), 17 (14.5%), and 4 (12.5%) women among 42 vice-directors, 117 chief senior physicians, and 32 managing senior physicians, respectively. Senior physicians not holding a leadership position were female in 23.1%, whereas board-certified neurosurgeons not holding a senior physician position and residents were female in 33.6% and 35.0%, respectively. Of note, the highest proportion of female department heads (15.6%) was found in private hospitals. CONCLUSIONS The number of women in leadership positions in German neurosurgical departments is dramatically low, and with increasing leadership status gender disparity increases. Mentorship, recruitment, the perception of benefits offered by diversity and programs facilitating gender equality, job sharing, parental leave policies, and onsite childcare programs are needed to turn German neurosurgical departments into modern medical departments reflecting the gender profile of the general patient population.
CRIS-Team Scopus Importer:2022-05-06
Keywords: gender; Germany; neurosurgery; women

Genome-wide DNA methylation profiles distinguish silent from non-silent ACTH adenomas - Ricklefs, Franz L.; Fita, Krystian D.; Rotermund, Roman; Piffko, Andras; Schmid, Simone; Capper, David; Buslei, Rolf; Buchfelder, Michael; Burkhardt, Till; Matschke, Jakob; Lamszus, Katrin; Westphal, Manfred; et al. (Acta Neuropathologica, 2020)
CRIS-Team Scopus Importer:2020-03-27

Genomic DNA methylation distinguishes subtypes of human focal cortical dysplasia - Kobow, Katja; Ziemann, Mark; Kaipananickal, Harikrishnan; Khurana, Ishant; Mühlebner, Angelika; Feucht, Martha; Hainfellner, Johannes A.; Czech, Thomas; Aronica, Eleonora; Pieper, Tom; Holthausen, Hans; Kudernatsch, Manfred; et al. (Epilepsia, 2019)
Objectives: Focal cortical dysplasia (FCD) is a major cause of drug-resistant focal epilepsy in children, and the clinicopathological classification remains a challenging issue in daily practice. With the recent progress in DNA methylation–based classification of human brain tumors we examined whether genomic DNA methylation and gene expression analysis can be used to also distinguish human FCD subtypes. Methods: DNA methylomes and transcriptomes were generated from massive parallel sequencing in 15 surgical FCD specimens, matched with 5 epilepsy and 6 nonepilepsy controls. Results: Differential hierarchical cluster analysis of DNA methylation distinguished major FCD subtypes (ie, Ia, IIa, and IIb) from patients with temporal lobe epilepsy patients and nonepileptic controls. Targeted panel sequencing identified a novel likely pathogenic variant in DEPDC5 in a patient with FCD type IIa. However, no enrichment of differential DNA methylation or gene expression was observed in mechanistic target of rapamycin (mTOR) pathway–related genes. Significance: Our studies extend the evidence for disease-specific methylation signatures toward focal epilepsies in favor of an integrated clinicopathologic and molecular classification system of FCD subtypes incorporating genomic methylation.
CRIS-Team Scopus Importer:2019-06-18
Keywords: diagnostic biomarker; epigenetic; focal cortical dysplasia; focal epilepsy; mTOR pathway

Glial Glutamate Transporter-Mediated Plasticity: System xc -/xCT/SLC7A11 and EAAT1/2 in Brain Diseases - Dahlmanns, Marc; Dahlmanns, Jana; Savaskan, Nicolai; Steiner, Hans Herbert; Yakubov, Eduard (Frontiers in Bioscience - Landmark, 2023)
Glial cells play an essential role in the complex function of the nervous system. In particular, astrocytes provide nutritive support for neuronal cells and are involved in regulating synaptic transmission. Oligodendrocytes ensheath axons and support information transfer over long distances. Microglial cells constitute part of the innate immune system in the brain. Glial cells are equipped with the glutamatecystine- exchanger xCT (SLC7A11), the catalytic subunit of system xc -, and the excitatory amino acid transporter 1 (EAAT1, GLAST) and EAAT2 (GLT-1). Thereby, glial cells maintain balanced extracellular glutamate levels that enable synaptic transmission and prevent excitotoxic states. Expression levels of these transporters, however, are not fixed. Instead, expression of glial glutamate transporters are highly regulated in reaction to the external situations. Interestingly, such regulation and homeostasis is lost in diseases such as glioma, (tumor-associated) epilepsy, Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis or multiple sclerosis. Upregulation of system xc - (xCT or SLC7A11) increases glutamate export from the cell, while a downregulation of EAATs decreases intracellular glutamate import. Occurring simultaneously, these reactions entail excitotoxicity and thus harm neuronal function. The release of glutamate via the antiporter system xc - is accompanied by the import of cystine-an amino acid essential in the antioxidant glutathione. This homeostasis between excitotoxicity and intracellular antioxidant response is plastic and off-balance in central nervous system (CNS) diseases. System xc - is highly expressed on glioma cells and sensitizes them to ferroptotic cell death. Hence, system xc - is a potential target for chemotherapeutic add-on therapy. Recent research reveals a pivotal role of system xc - and EAAT1/2 in tumor-associated and other types of epilepsy. Numerous studies show that in Alzheimer's disease, amyotrophic lateral sclerosis and Parkinson's disease, these glutamate transporters are dysregulated-and disease mechanisms could be interposed by targeting system xc - and EAAT1/2. Interestingly, in neuroinflammatory diseases such as multiple sclerosis, there is growing evidence for glutamate transporter involvement. Here, we propose that the current knowledge strongly suggest a benefit from rebalancing glial transporters during treatment.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Alzheimer's disease; amyotrophic lateral sclerosis; GLAST; glioma; GLT-1; neuroinflammation; Parkinson's disease; SLC7A11

Glioblastoma cells induce differential glutamatergic gene expressions in human tumor-associated microglia/macrophages and monocyte-derived macrophages - Choi, Judy; Stradmann-Bellinghausen, Beate; Yakubov, Eduard; Savaskan, Nicolai E.; Regnier-Vigouroux, Anne (Cancer Biology & Therapy, 2015)
Glioblastoma cells produce and release high amounts of glutamate into the extracellular milieu and subsequently can trigger seizure in patients. Tumor-associated microglia/macrophages (TAMs), consisting of both parenchymal microglia and monocytes-derived macrophages (MDMs) recruited from the blood, are known to populate up to 1/3 of the glioblastoma tumor environment and exhibit an alternative, tumor-promoting and supporting phenotype. However, it is unknown how TAMs respond to the excess extracellular glutamate in the glioblastoma microenvironment. We investigated the expressions of genes related to glutamate transport and metabolism in human TAMs freshly isolated from glioblastoma resections. Quantitative real-time PCR analysis showed (i) significant increases in the expressions of GRIA2 (GluA2 or AMPA receptor 2), SLC1A2 (EAAT2), SLC1A3 (EAAT1), (ii) a near-significant decrease in the expression of SLC7A11 (cystine-glutamate antiporter xCT) and (iii) a remarkable increase in GLUL expression (glutamine synthetase) in these cells compared to adult primary human microglia. TAMs co-cultured with glioblastoma cells also exhibited a similar glutamatergic profile as freshly isolated TAMs except for a slight increase in SLC7A11 expression. We next analyzed these genes expressions in cultured human MDMs derived from peripheral blood monocytes for comparison. In contrast, MDMs co-cultured with glioblastoma cells compared to MDMs co-cultured with normal astrocytes exhibited decreased expressions in the tested genes except for GLUL. This is the first study to demonstrate transcriptional changes in glutamatergic signaling of TAMs in a glioblastoma microenvironment, and the findings here suggest that TAMs and MDMs might potentially elicit different cellular responses in the presence of excess extracellular glutamate.
EVALuna2:22851

Glioblastoma-instructed microglia transition to heterogeneous phenotypic states with phagocytic and dendritic cell-like features in patient tumors and patient-derived orthotopic xenografts - Yabo, Yahaya A.; Moreno-Sanchez, Pilar M.; Pires-Afonso, Yolanda; Kaoma, Tony; Nosirov, Bakhtiyor; Scafidi, Andrea; Ermini, Luca; Lipsa, Anuja; Oudin, Anaïs; Kyriakis, Dimitrios; Grzyb, Kamil; Poovathingal, Suresh K.; et al. (Genome Medicine, 2024)
Background: A major contributing factor to glioblastoma (GBM) development and progression is its ability to evade the immune system by creating an immune-suppressive environment, where GBM-associated myeloid cells, including resident microglia and peripheral monocyte-derived macrophages, play critical pro-tumoral roles. However, it is unclear whether recruited myeloid cells are phenotypically and functionally identical in GBM patients and whether this heterogeneity is recapitulated in patient-derived orthotopic xenografts (PDOXs). A thorough understanding of the GBM ecosystem and its recapitulation in preclinical models is currently missing, leading to inaccurate results and failures of clinical trials. Methods: Here, we report systematic characterization of the tumor microenvironment (TME) in GBM PDOXs and patient tumors at the single-cell and spatial levels. We applied single-cell RNA sequencing, spatial transcriptomics, multicolor flow cytometry, immunohistochemistry, and functional studies to examine the heterogeneous TME instructed by GBM cells. GBM PDOXs representing different tumor phenotypes were compared to glioma mouse GL261 syngeneic model and patient tumors. Results: We show that GBM tumor cells reciprocally interact with host cells to create a GBM patient-specific TME in PDOXs. We detected the most prominent transcriptomic adaptations in myeloid cells, with brain-resident microglia representing the main population in the cellular tumor, while peripheral-derived myeloid cells infiltrated the brain at sites of blood–brain barrier disruption. More specifically, we show that GBM-educated microglia undergo transition to diverse phenotypic states across distinct GBM landscapes and tumor niches. GBM-educated microglia subsets display phagocytic and dendritic cell-like gene expression programs. Additionally, we found novel microglial states expressing cell cycle programs, astrocytic or endothelial markers. Lastly, we show that temozolomide treatment leads to transcriptomic plasticity and altered crosstalk between GBM tumor cells and adjacent TME components. Conclusions: Our data provide novel insights into the phenotypic adaptation of the heterogeneous TME instructed by GBM tumors. We show the key role of microglial phenotypic states in supporting GBM tumor growth and response to treatment. Our data place PDOXs as relevant models to assess the functionality of the TME and changes in the GBM ecosystem upon treatment. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-04-12
Keywords: Glioblastoma; Microglia; Myeloid cells; Patient-derived orthotopic xenografts; Single-cell RNA sequencing; Tumor microenvironment

Glucocorticoid modulation of synaptic plasticity in the human temporal cortex of epilepsy patients: Does chronic stress contribute to memory impairment? - Brandner, Sebastian; Schröter, Sarah; Çalışkan, Gürsel; Salar, Seda; Kobow, Katja; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Schwarz, Michael; Buchfelder, Michael; Maslarova, Anna (Epilepsia, 2021)
Objective: Memory impairment is common in patients with temporal lobe epilepsy and seriously affects life quality. Chronic stress is a recognized cofactor in epilepsy and can also impair memory function. Furthermore, increased cortisol levels have been reported in epilepsy patients. Animal models have suggested that aggravating effects of stress on memory and synaptic plasticity were mediated via glucocorticoids. The aim of this study was, therefore, to investigate the effect of glucocorticoid receptor (GR) modulation on synaptic plasticity in the human cortex of epilepsy patients. Methods: We performed field potential recordings in acute slices from the temporal neocortex of patients who underwent surgery for drug-resistant temporal lobe epilepsy. Synaptic plasticity was investigated by a theta-burst stimulation (TBS) protocol for induction of long-term potentiation (LTP) in the presence of GR modulators. Results: LTP was impaired in temporal cortex from epilepsy patients. Pretreatment of the slices with the GR antagonist mifepristone (RU486) improved LTP induction, suggesting that LTP impairment was due to baseline GR activation in the human cortex. The highly potent GR agonist dexamethasone additionally weakened synaptic strength in an activity-dependent manner when applied after TBS. Significance: Our results show a direct negative glucocorticoid effect on synaptic potentiation in the human cortex and imply chronic activation of GRs. Chronic stress may therefore contribute to memory impairment in patients with temporal lobe epilepsy. Furthermore, the activity-dependent acute inhibitory effect of dexamethasone suggests a mechanism of synaptic downscaling by which postictally increased cortisol levels may prevent pathologic plasticity upon seizures.
CRIS-Team Scopus Importer:2021-10-29
Keywords: dexamethasone; epilepsy; human cortex; long-term potentiation; stress

Hedgehog signaling activation induces stem cell proliferation and hormone release in the adult pituitary gland - Pyczek, Joanna; Buslei, Rolf; Schult, David; Hoelsken, Annett; Buchfelder, Michael; Hess, Ina; Hahn, Heidi; Uhmann, Anja (Scientific Reports, 2016)
Hedgehog (HH) signaling is known to be essential during the embryonal development of the pituitary gland but the knowledge about its role in the adult pituitary and in associated tumors is sparse. In this report we investigated the effect of excess Hh signaling activation in murine pituitary explants and analyzed the HH signaling status of human adenopituitary lobes and a large cohort of pituitary adenomas. Our data show that excess Hh signaling led to increased proliferation of Sox2(+) and Sox9(+) adult pituitary stem cells and to elevated expression levels of adrenocorticotropic hormone (Acth), growth hormone (Gh) and prolactin (Prl) in the adult gland. Inhibition of the pathway by cyclopamine reversed these effects indicating that active Hh signaling positively regulates proliferative processes of adult pituitary stem cells and hormone production in the anterior pituitary. Since hormone producing cells of the adenohypophysis as well as ACTH-, GH- and PRL-immunopositive adenomas express SHH and its target GLI1, we furthermore propose that excess HH signaling is involved in the development/maintenance of hormone-producing pituitary adenomas. These findings advance the understanding of physiological hormone regulation and may open new treatment options for pituitary tumors.
EVALuna2:7325

Higher Peripheral Inflammation Is Associated With Lower Orbitofrontal Gamma Power in Chronic Tinnitus - Becker, Linda; Keck, Antonia; Rohleder, Nicolas; Müller-Voggel, Nadia (Frontiers in Behavioral Neuroscience, 2022)
Chronic tinnitus, the continuous perception of a phantom sound, is a highly prevalent audiological symptom, for which the underlying pathology has not yet been fully understood. It is associated with neurophysiological alterations in the central nervous system and chronic stress, which can be related with a disinhibition of the inflammatory system. We here investigated the association between resting-state oscillatory activity assessed with Magnetoencephalography (MEG), and peripheral inflammation assessed by C-reactive protein (CRP) in a group of patients with chronic tinnitus (N = 21, nine males, mean age: 40.6 ± 14.6 years). Additionally, CRP was assessed in an age- and sex-matched healthy control group (N = 21, nine males, mean age: 40.9 ± 15.2 years). No MEG data was available for the control group. We found a significant negative correlation between CRP and gamma power in the orbitofrontal cortex in tinnitus patients (p < 0.001), pointing to a deactivation of the orbitofrontal cortex when CRP was high. No significant clusters were found for other frequency bands. Moreover, CRP levels were significantly higher in the tinnitus group than in the healthy controls (p = 0.045). Our results can be interpreted based on findings from previous studies having disclosed the orbitofrontal cortex as part of the tinnitus distress network. We suggest that higher CRP levels and the associated deactivation of the orbitofrontal cortex in chronic tinnitus patients is maintaining the tinnitus percept through disinhibition of the auditory cortex and attentional or emotional top-down processes. Although the direction of the association (i.e., causation) between CRP levels and orbitofrontal gamma power in chronic tinnitus is not yet known, inflammation reducing interventions are promising candidates when developing treatments for tinnitus patients. Overall, our study highlights the importance of considering immune-brain communication in tinnitus researc
Keywords: tinnitus; inflammation; MEG; C-reactive protein; stress; oscillatory activity

High-Resolution 3D-constructive interference in steady-state MR imaging and 3D time-of-flight MR angiography in neurovascular compression: A comparison between 3T and 1.5T - Dörfler, Arnd; Garcia, M.; Naraghi, Ramin; Zumbrunn, T.; Roesch, J.; Hastreiter, Peter (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: High-resolution MR imaging is useful for diagnosis and preoperative planning in patients with NVC. Because high-field MR imaging promises higher SNR and resolution, the aim of this study was to determine the value of high-resolution 3D-CISS and 3D-TOF MRA at 3T compared with 1.5T in patients with NVC. MATERIALS AND METHODS: Forty-seven patients with NVC, trigeminal neuralgia, hemifacial spasm, and glossopharyngeal neuralgia were examined at 1.5T and 3T, including high-resolution 3D-CISS and 3D-TOF MRA sequences. Delineation of anatomic structures, overall image quality, severity of artifacts, visibility of NVC, and assessment of the SNR and CNR were compared between field strengths. RESULTS: SNR and CNR were significantly higher at 3T (P < .001). Significantly better anatomic conspicuity, including delineation of CNs, nerve branches, and assessment of small vessels, was obtained at 3T (P < .02). Severity of artifacts was significantly lower at 3T (P < .001). Consequently, overall image quality was significantly higher at 3T. NVC was significantly better delineated at 3T (P < .001). Six patients in whom NVC was not with certainty identifiable at 1.5T were correctly diagnosed at 3T. CONCLUSIONS: Patients with NVC may benefit from the higher resolution and greater sensitivity of 3T for preoperative assessment of NVC, and 3T may be of particular value when 1.5T is equivocal.
CRIS-Team Scopus Importer:2022-08-05

Histone deacetylases inhibition by SAHA/Vorinostat normalizes the glioma microenvironment via xCT equilibration - Wolf, Ines; Fan, Zheng; Rauh, Manfred; Seufert, Sebastian; Hore, Nirjhar; Buchfelder, Michael; Savaskan, Nic E.; Eyupoglu, Ilker Y. (Scientific Reports, 2014)
Malignant gliomas are characterized by neurodegenerative actions leading to the destruction of surrounding brain parenchyma. The disturbance in glutamate homeostasis caused by increased expression of the glutamate transporter xCT plays a key role in glioma progression. We demonstrate that the HDAC-inhibitor SAHA specifically inhibits the xCT-transporter expression. Thereby, tumor cell stress is engendered, marked by increase in ROS. Moreover, SAHA dependent xCT-reduction correlates with the inhibition of ATF4-expression, a factor known to foster xCT expression. Since xCT/system Xc- is pivotal for the brain tumor microenvironment, normalization of this system is a key in the management of malignant gliomas. To date, the problem lay in the inability to specifically target xCT due to the ubiquitous expression of the xCT-transporter–i.e. in non-cancerously transformed cells too–as well as its essential role in physiological CNS processes. Here, we show xCT-transporter equilibration through SAHA is specific for malignant brain tumors whereas SAHA does not affect the physiological xCT levels in healthy brain parenchyma. Our data indicate that SAHA operates on gliomas specifically via normalizing xCT expression which in consequence leads to reduced extracellular glutamate levels. This in turn causes a marked reduction in neuronal cell death and normalized tumor microenvironment.
EVALuna2:18895

Histopathological Features of Focal Cortical Dysplasia Type IIIc adjacent to Epilepsy-associated Vascular Malformations - Miyata, Hajime; Kuwashige, Haruka; Coras, Roland; Blümcke, Ingmar; Rossler, Karl; Kubota, Yuichi; Hori, Tomokatsu (JOURNAL OF NEUROPATHOLOGY AND EXPERIMENTAL NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Histopathological Findings in Brain Tissue Obtained during Epilepsy Surgery - Blümcke, Ingmar; Spreafico, R.; Haaker, G.; Coras, R.; Kobow, K.; Bien, C. G.; Pfaefflin, M.; Elger, C.; Widman, G.; Schramm, J.; Becker, Albert; Braun, K. P.; et al. (New England Journal of Medicine, 2017)
Detailed neuropathological information on the structural brain lesions underlying seizures is valuable for understanding drug-resistant focal epilepsy.We report the diagnoses made on the basis of resected brain specimens from 9523 patients who underwent epilepsy surgery for drug-resistant seizures in 36 centers from 12 European countries over 25 years. Histopathological diagnoses were determined through examination of the specimens in local hospitals (41%) or at the German Neuropathology Reference Center for Epilepsy Surgery (59%).The onset of seizures occurred before 18 years of age in 75.9% of patients overall, and 72.5% of the patients underwent surgery as adults. The mean duration of epilepsy before surgical resection was 20.1 years among adults and 5.3 years among children. The temporal lobe was involved in 71.9% of operations. There were 36 histopathological diagnoses in seven major disease categories. The most common categories were hippocampal sclerosis, found in 36.4% of the patients (88.7% of cases were in adults), tumors (mainly ganglioglioma) in 23.6%, and malformations of cortical development in 19.8% (focal cortical dysplasia was the most common type, 52.7% of cases of which were in children). No histopathological diagnosis could be established for 7.7% of the patients.In patients with drug-resistant focal epilepsy requiring surgery, hippocampal sclerosis was the most common histopathological diagnosis among adults, and focal cortical dysplasia was the most common diagnosis among children. Tumors were the second most common lesion in both groups. (Funded by the European Union and others.).
EVALuna2:7385

Histopathological proof of the pathogenicity of a rare GFAP mutation in a patient with flaccid paraparesis - Brackmann, Florian; Coras, Roland; Rössler, Karl; Kraus, Cornelia; Rompel, Oliver; Trollmann, Regina (Brain & Development, 2017)
Infantile Alexander disease is a rare progressive leukodystrophy caused by autosomal dominant mutations in the (GFAP) gene typically presenting with psychomotor retardation, progressive macrocephaly and refractory epilepsy. Neuroradiological hallmarks are extensive white matter lesions with frontal preponderance as well as signal intensity changes of basal ganglia and medulla oblongata with variable contrast enhancement. Here, we report an atypical manifestation in a 21-month-old boy presenting with flaccid paraparesis and areflexia. Cognitive, visual as well as fine motor skills and muscular strength of the upper extremities were appropriate for age. Weight and height as well as head circumference were within normal range. Clinical or electroencephalographic signs of seizures were absent. Cranial MRI demonstrated bifrontal cystic tumorous lesions with partial contrast rims, as well as space-occupying focal lesions of the caudate nuclei. Spinal MRI revealed swelling of the lumbar and cervical spinal cord. CSF and blood chemistry showed normal results. Histopathology of a subcortical lesion showed large amounts of Rosenthal fibers and protein droplets characteristic of Alexander disease. Sequencing detected a heterozygous mutation of the GFAP gene (c.205G > A; p.(Glu69Lys)) that has been reported before as probably pathogenetic in another case of lower spinal involvement. This well documented case draws attention to atypical spinal manifestations of Alexander disease and gives histopathological proof of the pathogenetic role of a rare GFAP mutation with marked spinal involvement.
EVALuna2:9396

How early can one diagnose Cushing's disease? An early diagnosis in a case of prepubertal Cushing's disease - Hoppmann, Julia; Wagner, Isabel V.; Junghans, Gudrun; Wudy, Stefan A.; Buchfelder, Michael; Hirsch, Franz W.; Ritter, Lutz; Kiess, Wieland; Pfaeffle, Roland (Journal of Pediatric Endocrinology & Metabolism, 2014)
Cushing's disease is very rare in children, and the diagnosis is frequently delayed by several years.We report a case of prepubertal Cushing's disease with a medical history of only 9 months. This case illustrates the difficulties involved in diagnosing children at the early stage of the disease.An 8-year-old prepubertal boy presented with rapid weight gain accompanied by a decreasing growth velocity and hirsutism. Thyroid function tests and growth factor levels were normal, thus excluding hypothyroidism and growth hormone deficiency. Cushing's syndrome was confirmed by elevated 24-h urinary free cortisol levels, increased diurnal cortisol levels, and a lack of cortisol suppression in the low-dose dexamethasone suppression test. Further tests to investigate the source of the hypercortisolism showed the following results: Basal morning adrenocorticotropic hormone (ACTH) was normal. The high-dose dexamethasone suppression test led to a 51% decrease in cortisol level. In the corticotropin-releasing hormone (CRH) test, ACTH and cortisol increased only by 28%. Repeated magnetic resonance imaging (MRI) finally revealed a microadenoma in the anterior pituitary, thus establishng the diagnosis of Cushing's disease. Upon diagnosis, the patient underwent transsphenoidal surgery. Histological analysis confirmed an ACTH-secreting pituitary adenoma.This case illustrates the difficulties associated with the clinical, biochemical, and radiological diagnoses of Cushing's disease in children. Early diagnosis remains a challenge because test results often do not match standard diagnostic criteria.
EVALuna2:22846

How S100B crosses brain barriers and why it is considered a peripheral marker of brain injury - Gayger-Dias, Vitor; Vizuete, Adriana F.K.; Rodrigues, Letícia; Wartchow, Krista Minéia; Bobermin, Larissa; Leite, Marina Concli; Quincozes-Santos, André; Kleindienst, Andrea; Gonçalves, Carlos Alberto (Experimental Biology and Medicine, 2023)
S100B is a 21-kDa protein that is produced and secreted by astrocytes and widely used as a marker of brain injury in clinical and experimental studies. The majority of these studies are based on measurements in blood serum, assuming an associated increase in cerebrospinal fluid and a rupture of the blood–brain barrier (BBB). Moreover, extracerebral sources of S100B are often underestimated. Herein, we will review these interpretations and discuss the routes by which S100B, produced by astrocytes, reaches the circulatory system. We discuss the concept of S100B as an alarmin and its dual activity as an inflammatory and neurotrophic molecule. Furthermore, we emphasize the lack of data supporting the idea that S100B acts as a marker of BBB rupture, and the need to include the glymphatic system in the interpretations of serum changes of S100B. The review is also dedicated to valorizing extracerebral sources of S100B, particularly adipocytes. Furthermore, S100B per se may have direct and indirect modulating roles in brain barriers: on the tight junctions that regulate paracellular transport; on the expression of its receptor, RAGE, which is involved in transcellular protein transport; and on aquaporin-4, a key protein in the glymphatic system that is responsible for the clearance of extracellular proteins from the central nervous system. We hope that the data on S100B, discussed here, will be useful and that it will translate into further health benefits in medical practice.
CRIS-Team Scopus Importer:2023-12-22
Keywords: AQP-4; Astrocyte; BBB; glymphatic system; RAGE; S100B; tight junctions

Hyponatremia in Neurotrauma: The Role of Vasopressin - Kleindienst, Andrea; Hannon, Mark J.; Buchfelder, Michael; Verbalis, Joseph G. (Journal of Neurotrauma, 2016)
Hyponatremia is frequent in patients suffering from traumatic brain injury, subarachnoid hemorrhage, or following intracranial procedures, with approximately 20% having a decreased serum sodium concentration to <125 mmol/L. The pathophysiology of hyponatremia in neurotrauma is not completely understood, but in large part is explained by the syndrome of inappropriate secretion of antidiuretic hormone (SIADH). The abnormal water and/or sodium handling creates an osmotic gradient promoting the shift of water into brain cells, thereby worsening cerebral edema and precipitating neurological deterioration. Unless hyponatremia is corrected promptly and effectively, morbidity and mortality increases through seizures, elevations in intracranial pressure, and/or herniation. The excess mortality in patients with severe hyponatremia (<125 mmol/L) extends beyond the time frame of hospital admission, with a reported mortality of 20% in hospital and 45% within 6 months of follow-up. Current options for the management of hyponatremia include fluid restriction, hypertonic saline, mineralocorticoids, and osmotic diuretics. However, the recent development of vasopressin receptor antagonists provides a more physiological tool for the management of excess water retention and consequent hyponatremia, such as occurs in SIADH. This review summarizes the existing literature on the pathophysiology, clinical features, and management of hyponatremia in the setting of neurotrauma.
EVALuna2:33858

Hypothermia Reduces the Cerebral Blood Flow Threshold Critical to Reestablish Neuronal Membrane Potential - Kleindienst, Andrea; Buchfelder, Michael; Churn, Severn B. (Critical Care Medicine, 2015)
EVALuna2:22863

Hypoxia and microvascular alterations are early predictors of IDH-mutated anaplastic glioma recurrence - Stadlbauer, Andreas; Oberndorfer, Stefan; Heinz, Gertraud; Zimmermann, Max; Kinfe, Thomas Mehari; Dörfler, Arnd; Buchfelder, Michael; Kremenevski, Natalia; Marhold, Franz (Cancers, 2021)
Anaplastic gliomas (AG) represents aggressive brain tumors that often affect young adults. Although isocitrate-dehydrogenase (IDH) gene mutation has been identified as a more favorable prognostic factor, most IDH-mutated AG patients are confronted with tumor recurrence. Hence, increased knowledge about pathophysiological precursors of AG recurrence is urgently needed in order to develop precise diagnostic monitoring and tailored therapeutic approaches. In this study, 142 physiological magnetic resonance imaging (phyMRI) follow-up examinations in 60 AG patients after standard therapy were evaluated and magnetic resonance imaging (MRI) biomarker maps for microvascular architecture and perfusion, neovascularization activity, oxygen metabolism, and hypoxia calculated. From these 60 patients, 34 patients developed recurrence of the AG, and 26 patients showed no signs for AG recurrence during the study period. The time courses of MRI biomarker changes were analyzed regarding early pathophysiological alterations over a one-year period before radiological AG recurrence or a one-year period of stable disease for patients without recurrence, respectively. We detected intensifying local tissue hypoxia 250 days prior to radiological recurrence which initiated upregulation of neovascularization activity 50 to 70 days later. These changes were associated with a switch from an avascular infiltrative to a vascularized proliferative phenotype of the tumor cells another 30 days later. The dynamic changes of blood perfusion, microvessel density, neovascularization activity, and oxygen metabolism showed a close physiological interplay in the one-year period prior to radiological recurrence of IDH-mutated AG. These findings may path the wave for implementing both new MR-based imaging modalities for routine follow-up monitoring of AG patients after standard therapy and furthermore may support the development of novel, tailored therapy options in recurrent AG.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Anaplastic glioma; Hypoxia; IDH gene mutation; Isocitrate-dehydrogenase; Neovascularization; Physiological MRI; Recurrence; Treatment failure; Vascular cooption

Hypoxia and the hypoxia inducible factor 1α activate protein kinase A by repressing RII beta subunit transcription - Lucia, Kristin; Wu, Yonghe; Garcia, Jose Monteserin; Barlier, Anne; Buchfelder, Michael; Saeger, Wolfgang; Renner, Ulrich; Stalla, Günter K.; Theodoropoulou, Marily (Oncogene, 2020)
Overactivation of the cAMP signal transduction pathway plays a central role in the pathogenesis of endocrine tumors. Genetic aberrations leading to increased intracellular cAMP or directly affecting PKA subunit expression have been identified in inherited and sporadic endocrine tumors, but are rare indicating the presence of nongenomic pathological PKA activation. In the present study, we examined the impact of hypoxia on PKA activation using human growth hormone (GH)-secreting pituitary tumors as a model of an endocrine disease displaying PKA-CREB overactivation. We show that hypoxia activates PKA and enhances CREB transcriptional activity and subsequently GH oversecretion. This is due to a previously uncharacterized ability of HIF-1α to suppress the transcription of the PKA regulatory subunit 2B (PRKAR2B) by sequestering Sp1 from the PRKAR2B promoter. The present study reveals a novel mechanism through which the transcription factor HIF-1α transduces environmental signals directly onto PKA activity, without affecting intracellular cAMP concentrations. By identifying a point of interaction between the cellular microenvironment and intracellular enzyme activation, neoplastic, and nonneoplastic diseases involving overactivated PKA pathway may be more efficiently targeted.
CRIS-Team Scopus Importer:2020-03-10

IgG4-related hypophysitis is highly prevalent among cases of histologically confirmed hypophysitis - Bernreuther, Christian; Illies, Christopher; Flitsch, Joerg; Buchfelder, Michael; Buslei, Rolf; Glatzel, Markus; Saeger, Wolfgang (Brain Pathology, 2017)
IgG4-related disease is an immune-mediated disease with manifestations in most organ systems among them the pituitary gland. To date, few cases of histologically confirmed cases of IgG-related hypophysitis have been reported. The aim of this study was to retrospectively determine the prevalence of IgG4-related hypophysitis among cases previously diagnosed as primary hypophysitis (lymphocytic hypophysitis, granulomatous hypophysitis and hypophysitis not otherwise specified). Histological and immunohistochemical analysis revealed that 12 of 29 cases (41.4%) previously diagnosed as primary hypophysitis fulfilled the criteria for IgG4-related disease and, thus, IgG4-related hypophysitis should always be considered in the differential diagnosis of primary hypophysitis. All cases of IgG4-related hypophysitis showed a dense lymphoplasmacytic infiltrate with more than 10 IgG4-positive cells per high power field and a ratio of IgG4/IgG-positive cells of more than 40%, whereas storiform fibrosis was an inconsistent histological feature and was also seen in few cases of non-IgG-related hypophysitis, thus lacking sensitivity and specificity. Obliterative phlebitis was not seen in any case. Thus, histological criteria defined for IgG4-related disease in other organs should be modified for IgG4-related hypophysitis, accordingly.
EVALuna2:7393

ILAE Neuroimaging Task Force Highlight: harnessing optimized imaging protocols for drug- resistant childhood epilepsy - Lariviere, Sara; Federico, Paolo; Chinvarun, Yotin; Jackson, Graeme; Morgan, Victoria; Rampp, Stefan; Vaudano, Anna Elisabetta; Wang, Irene; Cendes, Fernando; Boelman, Cyrus G.; Bernasconi, Andrea; Bernasconi, Neda; et al. (Epileptic Disorders, 2021)
The ILAE Neuroimaging Task Force aims to publish educational case reports highlighting basic aspects related to neuroimaging in epilepsy consistent with the educational mission of the ILAE. Previous quantitative MRI studies have established important imaging markers of epilepsy-related pathology, including features sensitive to hippocampal cell loss and reactive astrogliosis. Here, we review the case of a female with pediatric drug-resistant epilepsy. Throughout her course of treatment, she had seven MRI investigations at several centers; the first three did not follow optimized epilepsy imaging protocols whereas the remaining four adhered to HARNESS-MRI protocols (harmonized neuroimaging of epilepsy structural sequences). Visual inspection of a set of HARNESS-MR images revealed conspicuous left hippocampal hyperintensity which may have been initially overlooked on non-optimized MR images. Quantitative analysis of these multimodal imaging data along hippocampal subfields provided clear evidence of hippocampal sclerosis, with increased atrophy, increased mean diffusivity, increased T2-FLAIR signal, and lower qT1 values observed in the anterior portions of the left, compared to the right hippocampus. The patient underwent a left anterior temporal lobectomy with amygdalohippocampectomy at age 16 years. Histopathology of the resected specimen also confirmed hippocampal sclerosis with widespread gliosis and focal neuronal loss in the hippocampal subfields overlapping with regions of multimodal quantitative alterations. The patient remains seizure-free one year after surgery. Collectively, this case highlights the need for optimized data acquisition protocols early in the treatment of epilepsy and supports quantitative analysis of MRI contrasts to enhance personalized diagnosis and prognosis of drug-resistant patients with epilepsy.
CRIS-Team WoS Importer:2021-11-05

ILAE neuroimaging task force highlight: MRI detection of early life epilepsy caused by focal cortical dysplasia - Cohen, Nathan T.; Vezina, L. Gilbert; Oluigbo, Chima; Anwar, Tayyba; Archer, John; Bernhardt, Boris C.; Caciagli, Lorenzo; Cendes, Fernando; Chinvarun, Yotin; Concha, Luis; Federico, Paolo; Kobayashi, Eliane; et al. (Epileptic Disorders, 2025)
The ILAE Neuroimaging Task Force aims to publish educational case reports that highlight basic aspects of neuroimaging in epilepsy consistent with the ILAE's educational mission. Here, we describe a case series of three neonates with focal cortical dysplasia (FCD)-related drug-resistant epilepsy who underwent surgical intervention. The purpose of this series is to demonstrate the difficulties of identifying FCD in this age group and to highlight the potential added value of arterial spin labeling MRI for delineation of the epileptogenic zone. This series also supports the importance of the 2019 ILAE recommendations for structural imaging in epilepsy, the 2009 ILAE recommendations on imaging infants and children with recent-onset epilepsy, and the 2022 ILAE consensus classification of FCD.
CRIS-Team Scopus Importer:2025-05-16
Keywords: arterial spin labeling; ASL; drug-resistant epilepsy; focal cortical dysplasia

ILAE Neuroimaging Task Force highlight: Review MRI scans with semiology in mind - Federico, Paolo; Ng, Denise W.; Bernasconi, Andrea; Bernhardt, Boris; Blumenfeld, Hal; Cendes, Fernando; Chinvarun, Yotin; Jackson, Graeme D.; Morgan, Victoria; Rampp, Stefan; Vaudano, Anna Elisabetta; Wang, Irene (Epileptic Disorders, 2020)
The ILAE Neuroimaging Task Force aims to publish educational case reports highlighting basic aspects related to neuroimaging in epilepsy consistent with the educational mission of the ILAE. It is important to obtain MRI scans early in the clinical course of epilepsy, using an optimized protocol. Furthermore, it is critical that MRI scans are reviewed by experts who have been provided with all the clinical information and results from other investigations. We report a patient with a 21-year history of drug-resistant seizures who was admitted from another centre for presurgical evaluation. She had four previous MRI scans from this centre which were reported as unremarkable. However, a review of the MRI scan obtained on the day of admission, with the patient's ictal semiology in mind, resulted in identification of an epileptogenic lesion which was later confirmed by video-EEG monitoring and interictal PET. This lesion was present on all previous MRI scans and showed no change. The patient underwent lesionectomy, and histopathology of the resected specimen was consistent with a dysembryoplastic neuroepithelial tumour. The patient remains seizure-free, 2.5 years after surgery. This case highlights the importance of obtaining detailed descriptions of seizure semiology and considering them when reviewing MR images.
CRIS-Team WoS Importer:2020-11-27

ILAE neuroimaging task force highlight: Subcortical laminar heterotopia - Kasper, Burkhard S.; Archer, John; Bernhardt, Boris C.; Caciagli, Lorenzo; Cendes, Fernando; Chinvarun, Yotin; Concha, Luis; Federico, Paolo; Gaillard, William; Kobayashi, Eliane; Ogbole, Godwin; Vaudano, Anna Elisabetta; et al. (Epileptic Disorders, 2024)
The ILAE Neuroimaging Task Force publishes educational case reports that highlight basic aspects of neuroimaging in epilepsy consistent with the ILAE's educational mission. Subcortical laminar heterotopia, also known as subcortical band heterotopia (SBH) or “double cortex,” is an intriguing and rare congenital malformation of cortical development. SBH lesions are part of a continuum best designated as agyria-pachygyria-band-spectrum. The malformation is associated with epilepsy that is often refractory, as well as variable degrees of developmental delay. Moreover, in an increasing proportion of cases, a distinct molecular-genetic background can be found. Diagnosing SBH can be a major challenge for many reasons, including more subtle lesions, and “non-classic” or unusual MRI-appearances. By presenting an illustrative case, we address the challenges and needs of diagnosing and treating SBH patients in epilepsy, especially the value of high-resolution imaging and specialized MRI-protocols.<br
Keywords: double cortex; epilepsy; neuroimaging; subcortical band heterotopia; subcortical laminar heterotopia

ILAE neuroimaging task force highlight: The utility of multimodal neuroimaging in diagnostic and presurgical workup of drug-resistant focal epilepsy - Biagioli, Niccolò; Parfyonov, Maksim; Meletti, Stefano; Pavesi, Giacomo; Archer, John; Bernhardt, Boris C.; Caciagli, Lorenzo; Cendes, Fernando; Chinvarun, Yotin; Concha, Luis; Federico, Paolo; Gaillard, William D.; et al. (Epileptic Disorders, 2025)
The ILAE Neuroimaging Task Force publishes educational case reports that highlight basic aspects of neuroimaging in epilepsy, consistent with ILAE's educational mission. In patients with drug-resistant focal epilepsy who are candidates for surgical intervention, the identification of structural abnormalities is a strong predictor of favorable postoperative seizure outcomes. When conventional imaging is insufficient, the integration of multimodal neuroimaging data with structural, metabolic, and functional imaging modalities is often helpful. The following two illustrative cases from two different centers highlight the challenges and needs to integrate the information from multiple imaging modalities for a more accurate diagnosis and resection planning of drug-resistant focal epilepsies. This approach can increase the number of patients eligible for surgery while minimizing the risk of postoperative deficits.
CRIS-Team Scopus Importer:2025-03-28
Keywords: MRI post-processing; MRI-negative; multimodal; nonlesional; presurgical evaluation

Image stitching of sphenoid sinuses from monocular endoscopic views - Bergen, Tobias; Hastreiter, Peter; Münzenmayer, Christian; Buchfelder, Michael; Wittenberg, Thomas (Tagungsband 12. Jahrestagung der Deutschen Gesellschaft für Computer- und Roboter Assistierte Chirurgie (CURAC), 2013)
For operations of the pituitary glands, the most subtle method is an intervention through the paranasal and especially through the sphenoid sinus. To avoid dangerous interference with adjacent organs and nerves, the surgeon has to orient himself in the very small sphenoid cavity and navigate across the hollow space to break through the sellar floor to the pituitary gland above. Especially in reoperations or anatomical variants such as so-called kissing carotids, transsphenoidal surgery is a challenge even in experienced hands. To support such a surgery, various imaging modalities can be applied such as CT, MRI or endoscopy. While pre-operative MRI or CT-data can be used for intervention planning and navigation support, endoscopy can be applied intra-operatively for the examination of surfaces inside the sphenoid sinus. In this work, we present initial experiments and results from real-time panorama-endoscopy of the sphenoid sinus for navigation and orientation support, based on monocular endoscopic sequences of a skull phantom, yielding partial reconstructions of the walls of the sphenoid sinus.
UnivIS-Import:2017-12-18:Pub.2013.tech.IMMD.IMMD9.images
Keywords: Mosaicking; Panorama-endoscopy; Pituitary surgery; Real-time; Sinus surgery; Stitching

Imaging characteristics of temporopolar blurring in the context of hippocampal sclerosis - Clavijo Prado, Carlos Andrés; Federico, Paolo; Bernasconi, Andrea; Bernhardt, Boris; Caciagli, Lorenzo; Concha, Luis; Chinvarun, Yotin; Jackson, Graeme; Morgan, Victoria; Rampp, Stefan; Vaudano, Anna Elisabetta; Wang, Irene; et al. (Epileptic Disorders, 2022)
We present an illustrative case to address anterior temporal lobe atrophy with poor delineation of the temporopolar gray-white matter interface based on T2-weighted and fluid-attenuated inversion recovery (FLAIR) images in patients with temporal lobe epilepsy associated with hippocampal sclerosis (TLE-HS). A 52-year-old woman with pharmacoresistant seizures since the age of six months underwent a previous MRI scan using a suboptimal protocol which was reported as unremarkable. MRI performed according to an epilepsy protocol showed classic signs of left HS and ipsilateral temporal polar atrophy with blurring of the gray-white matter boundary on FLAIR images. She underwent a left amygdalohippocampectomy and anterior temporal resection and remains seizure-free after 24 months. Histopathological analyses showed HS and no signs of focal cortical dysplasia (FCD). Blurring and atrophy of the ipsilateral temporal pole are common in TLE-HS and often misinterpreted as FCD. This relates to delayed myelination in patients with seizures before the age of two, is more pronounced on FLAIR sequences, and gives a false impression of cortical thickening. However, the T1-weighted images show a relatively well-demarcated cortical-subcortical transition and normal cortical thickness. By contrast, the cortical thickening in FCD is observed on both T1-weighted and FLAIR images. Since FCD also occurs in temporal lobe regions, it is important to differentiate the extra-hippocampal MRI abnormalities in TLE-HS from those likely to be FCD. This case highlights the importance of evaluation based on detailed imaging, which should always be conducted considering the EEG, seizure semiology, and other clinical information.
CRIS-Team Scopus Importer:2022-02-25
Keywords: hippocampal sclerosis; MRI; temporal lobe epilepsy; temporal pole blurring

Immunometabolic Profiling of Chronic Subdural Hematoma through Untargeted Mass Spectrometry Analysis: Preliminary Findings of a Novel Approach - Kipele, Maria William; Buchfelder, Michael; Taudte, R. Verena; Stadlbauer, Andreas; Kinfe, Thomas Mehari; Bozhkov, Yavor (Diagnostics, 2023)
Objective: Metabolomics has growing importance in the research of inflammatory processes. Chronic subdural hematoma (cSDH) is considered to be, at least in part, of inflammatory nature, but no metabolic analyses yet exist. Therefore, a mass spectrometry untargeted metabolic analysis was performed on hematoma samples from patients with cSDH. Methods: A prospective analytical cross-sectional study on the efficacy of subperiosteal drains in cSDH was performed. Newly diagnosed patients had the option of granting permission for the collection of a hematoma sample upon its removal. The samples were analyzed using liquid chromatography–mass spectrometry to obtain different types of metabolites from diverse biochemical classes. The statistical analysis included data cleaning, imputation, and log transformation, followed by PCA, PLS-DA, HCA, and ANOVA. The postoperative course of the disease was followed for 3 months. The metabolite concentrations in the hematoma fluid were compared based on whether a recurrence of the disease was recorded within this time frame. Results: Fifty-nine samples from patients who were operated on because of a cSDH were gathered. Among those, 8 samples were eliminated because of missing metabolites, and only 51 samples were analyzed further. Additionally, 39 samples were from patients who showed no recurrence over the course of a 3-month follow-up, and 12 samples were from a group with later recurrence. We recorded a noticeable drop (35%) in the concentration of acylcarnitines in the ”recurrence group“, where 10 of the 22 tested metabolites showed a significant reduction (p < 0.05). Furthermore, a noticeable reduction in different Acyl-CoA-dehydrogenases was detected (VLCAD-deficiency p < 0.05, MCAD-deficiency p = 0.07). No further changes were detected between both populations. Conclusions: The current study presents a new approach to the research of cSDH. The measurements presented us with new data, which, to date, are without any reference values. Therefore, it is difficult to interpret the information, and our conclusions should be considered to be only speculative. The results do, however, point in the direction of impaired fatty acid oxidation for cases with later recurrence. As fatty acid oxidation plays an important role in inflammatory energy metabolism, the results suggest that inflammatory processes could be aggravated in cases with recurrence. Because our findings are neither proven through further analyses nor offer an obvious therapy option, their implications would not change everyday practice in the management of cSDH. They do, however, present a further possibility of research that might, in the future, be relevant to the therapy.
CRIS-Team Scopus Importer:2023-11-24
Keywords: chronic subdural hematoma; inflammation; metabolic profile; metabolomics

Immunoprofiling of glial tumours of the neurohypophysis suggests a common pituicytic origin of neoplastic cells - Hagel, Christian; Buslei, Rolf; Buchfelder, Michael; Fahlbusch, Rudolf; Bergmann, Markus; Giese, Armin; Flitsch, Joerg; Luedecke, Dieter K.; Glatzel, Markus; Saeger, Wolfgang (Pituitary, 2017)
To analyse the antigen expression profiles of 27 cases of pituicytoma, spindle cell oncocytoma, and granular cell tumour of the sellar region concerning a common pituicytic origin of neoplastic cells.Material from 12 female and 15 male patients (13 granular cell tumours of the sellar region, 10 pituicytomas, four spindle cell oncocytomas) collected in the German Registry of Pituitary Tumours between 1993 and 2015 was re-evaluated according to the current WHO classification of tumours of the central nervous system and supplementary immunohistochemistry including S100-protein, CD56, CD68, thyroid transcription factor-1 (TTF-1), and Ki-67 was performed.S100-protein was detected in all 27 tumours and TTF-1 in all 16 tumours that were assessed. Vimentin was expressed in all 13 cases investigated whereas broad spectrum cytokeratin was not detected in any of 14 evaluated cases. GFAP was observed in nine out of 21 cases. 15 out of 17 investigated lesions showed some CD68 expression and five out of 14 cases were labelled with CD56 antibodies. Proliferative activity did not differ significantly between the three tumour subgroups although one primary and one recurrent pituicytoma showed exceptionally high Ki-67-proliferation indices of 15.3 and 12.7 %, respectively (means: granular cell tumour of the sellar region 2.0 %, pituicytoma 2.8 %, spindle cell oncocytoma 2.7 %).The study confirms and expands earlier data and is in line with the notion that the three tumour types are variants of pituicytoma.
EVALuna2:7362

Immunostaining and laser-assisted cell picking for mRNA analysis. - Kinfe, Thomas Mehari; et al. (Laboratory Investigation, 2000)

Impact of USP8 Gene Mutations on Protein Deregulation in Cushing Disease - Weigand, Isabel; Knobloch, Lisanne; Flitsch, Jörg; Saeger, Wolfgang; Monoranu, Camelia M.; Höfner, Kerstin; Herterich, Sabine; Rotermund, Roman; Ronchi, Cristina L.; Buchfelder, Michael; Glatzel, Markus; Hagel, Christian; et al. (Journal of Clinical Endocrinology and Metabolism, 2019)
CONTEXT: Cushing disease (CD) is a rare disorder with severe sequels and incompletely understood pathogenesis. The underlying corticotroph adenomas harbor frequently somatic mutations in the ubiquitin-specific peptidase 8 (USP8) gene. These mutations render USP8 hyperactive and prevent client proteins from degradation. OBJECTIVE: To investigate the impact of USP8 mutations on proteins deregulated in CD. DESIGN: One hundred eight pituitary adenomas (75 corticotroph [58 USP8 wild type (WT) and 17 USP8 mutated], 14 somatotroph, and 19 nonfunctioning) were investigated by immunohistochemistry. All evaluated proteins [USP8, arginine vasopressin receptor 1b and 2, corticotropin-releasing hormone receptor, cAMP response element-binding protein (CREB), p27/kip1, cyclin E, heat shock protein 90 (HSP90), orphan nuclear receptor 4, epidermal growth factor receptor, histone deacetylase 2, glucocorticoid receptor, cyclin-dependent kinase 5 and Abelson murine leukemia viral oncogene homolog 1 enzyme substrate 1] were known to be deregulated in CD. Furthermore, AtT20 cells were transfected with USP8 to investigate the expression of possible downstream proteins by immunoblot. RESULTS: Whereas most of the investigated proteins were not differentially expressed, the cell-cycle inhibitor p27 was significantly reduced in USP8 mutated corticotroph adenoma (H-score 2.0 ± 1.0 vs 1.1 ± 1.1 in WT adenomas; P = 0.004). In contrast, the chaperone HSP90 was expressed higher (0.5 ± 0.4 vs 0.2 ± 0.4; P = 0.29), and the phosphorylation of the transcription factor CREB was increased in USP8 mutated adenomas (1.30.5 ± 0.40.9 vs 0.70.5 ± 0.40.7; P = 0.014). Accordingly, AtT20 cells transfected with the USP8 P720R mutant had higher phosphorylated CREB (pCREB) levels than WT transfected cells (1.3 ± 0.14 vs 1 ± 0.23; P = 0.13). CONCLUSIONS: We could demonstrate that USP8 mutations are associated with deregulation of p27/kip1, HSP90, and pCREB. These findings suggest that these proteins are direct or indirect clients of USP8 and could therefore be potential targets for therapeutic approaches in patients with CD.
CRIS-Team Scopus Importer:2019-06-18

Improved Detection of Cavernous Sinus Invasion of Pituitary Macroadenomas with Ultra-High-Field 7 T MRI - Eisenhut, Felix; Schmidt, Manuel; Buchfelder, Michael; Dörfler, Arnd; Schlaffer, Sven-Martin (Life, 2023)
To compare 7 T magnetic resonance imaging (MRI) of pituitary macroadenomas (PMA) with standard MRI and intraoperative findings regarding tumor detection, localization, size, and extension. Patients with suspected pituitary adenoma underwent pre-operative 1.5 T or 3 T and 7 T MRI; 14 patients with a PMA were included. A qualitative (lesion detection, location, cavernous sinus infiltration) and quantitative (lesion size, depth of cavernous sinus infiltration) analysis of 1.5 T, 3 T and 7 T MRI was performed and compared with intraoperative findings. Both 1.5/3 T and 7 T MRI enabled the detection of all PMAs; lesion size determination was equal. 7 T MRI enables more precise assessments of cavernous sinus infiltration of PMA (ncorrect 7T = 78.6%, ncorrect 1.5/3T = 64.3%). Ultra-high-field MRI is a reliable imaging modality for evaluation of PMAs providing exact information on lesion location and size. 7 T MRI yielded more accurate information on cavernous sinus infiltration with better agreement with intraoperative findings than standard MRI.
CRIS-Team Scopus Importer:2023-01-27
Keywords: cavernous sinus infiltration; intraoperative findings; pituitary macroadenoma; ultra-high-field MRI

Improved magnetic resonance myelography of the lumbar spine using image fusion and volumetry - Eberhardt, Knut; Ganslandt, Oliver Thomas; Stadlbauer, Andreas (Journal of Neurosurgery-Spine, 2014)
The goal of this study was to investigate the usefulness and diagnostic potential of an improved MR myelography approach using a dedicated, heavily T2-weighted, 3D MRI sequence in combination with image fusion. A further aim was to compare dural areas and volumes of normal and pathological altered lumbar spine levels, and accuracy in the assessment of the stenoses, with those obtained by postmyelographic CT.Fifty patients underwent myelography, postmyelographic CT, and the improved MR myelography approach using a dedicated, heavily T2-weighted, 3D MRI sequence and image fusion. Dural cross-sectional areas and volumes for normal lumbar levels and levels with stenosis were calculated for postmyelographic CT and MR myelography data. The significant differences and Pearson correlations between dural cross-sectional areas and volumes from L1-2 to L5-S1 of postmyelographic CT and MR myelography were analyzed. The 99% CIs for normal and stenotic levels in patients with claudication distances less than 100 meters were calculated.For both dural areas and volumes in normal lumbar levels, the authors found no significant differences and strong correlations between postmyelographic CT and MR myelography. For the lower lumbar levels (L4-5 and L5-S1) they found significantly larger dural areas on MR myelography compared with postmyelographic CT, but not for the upper levels (L2-3 and L3-4). Dural volume analysis revealed significantly larger volumes for MR myelography at all 4 lumbar levels with stenoses in the cohort (L2-3 to L5-S1). Complete separation with no overlap was found between the 99% CIs for normal levels and stenotic levels.Differences in dural areas and volumes in this study may have been caused by the fact that in the case of a severely compressed thecal sac, the viscosity of the intrathecally applied contrast agent is too high in the framework of myelography. The gravitationally dependent component is thus too low to achieve sufficient fluid contrast. An optimized MR myelography approach-a dedicated 3D MR myelography sequence with high spatial resolution in combination with image fusion-is required to achieve a more reliable diagnosis of lumbar spine stenoses, especially with severe compression, compared with postmyelographic CT. This MR myelography approach may be helpful in preventing overestimation of lumbar spine stenoses. The upper limits of 99% CIs for stenotic levels can be interpreted as an indication for surgical treatment. However, further studies that include postoperative outcomes are required.
EVALuna2:22867

Improved pasireotide response in USP8 mutant corticotroph tumours in vitro - Albani, Adriana; Perez-Rivas, Luis Gustavo; Tang, Sicheng; Simon, Julia; Lucia, Kristin Elisabeth; Colón-Bolea, Paula; Schopohl, Jochen; Roeber, Sigrun; Buchfelder, Michael; Rotermund, Roman; Flitsch, Jörg; Thorsteinsdottir, Jun; et al. (Endocrine-Related Cancer, 2022)
Cushing's disease is a rare but devastating and difficult to manage condition. The somatostatin analogue pasireotide is the only pituitary-targeting pharmaceutical approved for the treatment of Cushing's disease but is accompanied by varying efficacy and potentially severe side effects. Finding means to predict which patients are more likely to benefit from this treatment may improve their management. More than half of corticotroph tumours harbour mutations in the USP8 gene, and there is evidence of higher somatostatin receptor 5 (SSTR5) expression in the USP8-mutant tumours. Pasireotide has a high affinity for SSTR5, indicating that these tumours may be more sensitive to treatment. To test this hypothesis, we examined the inhibitory action of pasireotide on adrenocorticotrophic hormone synthesis in primary cultures of human corticotroph tumour with assessed USP8 mutational status and in immortalized murine corticotroph tumour cells overexpressing human USP8 mutants frequent in Cushing's disease. Our in vitro results demonstrate that pasireotide exerts a higher antisecretory response in USP8-mutant corticotroph tumours. Overexpressing USP8 mutants in a murine corticotroph tumour cell model increased endogenous somatostatin receptor 5 (Sstr5) transcription. The murine Sstr5 promoter has two binding sites for the activating protein 1 (AP-1) and USP8 mutants possibly to mediate their action by stimulating AP-1 transcriptional activity. Our data corroborate the USP8 mutational status as a potential marker of pasireotide response and describe a potential mechanism through which USP8 mutants may regulate SSTR5 gene expression.
CRIS-Team Scopus Importer:2022-08-12
Keywords: corticotroph tumours; Cushing’s disease; pasireotide; somatostatin receptor; USP8

Improved Postoperative Facial Nerve and Hearing Function in Retrosigmoid Vestibular Schwannoma Surgery Significantly Associated with Semisitting Position - Roessler, Karl; Krawagna, Maximilian; Bischoff, Barbara; Rampp, Stefan; Ganslandt, Oliver Thomas; Iro, Heinrich; Schmitt, Hubert; Buchfelder, Michael (World Neurosurgery, 2016)
The pros and cons of semisitting positioning (SSP) versus lateral, horizontal positioning (LP) during retrosigmoid vestibular schwannoma (VS) surgery, especially concerning postoperative cranial nerve and brain stem preservation, are under continuous discussion.In a single-center retrospective cohort study, 30 VSs operated on in SSP compared with 30 operated on in LP with comparable demography were analyzed. During SSP surgery, transesophageal echocardiographic monitoring for venous air embolism was used continuously. Electrophysiologic cranial nerve monitoring was used in both groups.Length of surgery was significantly different between both groups: 183 minutes mean in SSP surgery versus 365 minutes mean in LP surgery (P = 0.0001). Postoperative rates of facial palsy and hearing loss were also significantly different. Six months postoperatively, 63% had normal facial nerve function after SSP surgery, whereas in LP surgery, 40% had no facial palsy (P = 0.02). Hearing preservation rate was also significantly different: 44% in SSP surgery compared with 14% in LP surgery who had preserved hearing (P = 0.006). Because of cerebrospinal fluid leaks, there were 3 operative revisions in the LP group (10%) and 1 (3.3%) in the SSP group. A clinically insignificant venous air embolism rate was found in 3.3% of patients (1/30) during SSP surgery. The neurologic outcome after 6 months was 1.2 on the Rankin Scale in the LP group and 1.0 in the SSP group, with zero mortality.SSP compared with LP surgery was associated with significantly shorter operation time and better facial and cochlear nerve function in VS surgery postoperatively, without differences in complication rate
EVALuna2:16715

Improved resection in lesional temporal lobe epilepsy surgery using neuronavigation and intraoperative MR imaging: Favourable long term surgical and seizure outcome in 88 consecutive cases - Roessler, Karl; Sommer, Bjoern; Grummich, Peter; Coras, Roland; Kasper, Burkhard; Hamer, Hajo; Blümcke, Ingmar; Stefan, Hermann; Buchfelder, Michael (Seizure-European Journal of Epilepsy, 2014)
To investigate the value of intraoperative MR imaging (iopMRI) combined with neuronavigation to avoid intraoperative underestimation of the resection amount during surgery of lesional temporal lobe epilepsy (LTLE) patients.We retrospectively investigated 88 patients (40 female, 48 male, mean age 37.2yrs, from 12 to 69yrs, 41 left sided lesions) with LTLE operated at our department, including 40.9% gangliogliomas (GG), 26.1% cavernomas (CM), 10.2% dysembryoplastic neuroepithelial tumours (DNT) and 11.4% focal cortical dysplasias (FCD), excluding hippocampal sclerosis.Complete resection was achieved in 85 of 88 patients (96.6%), as proven by postoperative MRI 6 months after surgery. In contrast, the routine first iopMR imaging before closure revealed radical resection in only 66 of these 88 patients (75%). After re-intervention, the second iopMR imaging demonstrated complete resection in 19 more patients. Thus, as a direct effect of iopMRI and neuronavigation, overall resection rate was increased by 21.6%. An excellent seizure outcome Engel Class I was found in 76.1% of patients during a mean follow-up of 26.4 months, irrespective of histological entity (74% in CM, 75% in GG, 78% in DNT and 60% in FCD). No severe postoperative complications occurred; permanent superior visual field defects were detected in 10.2% and permanent dysphasia/dyscalculia in 1.1%.Refined surgery using neuronavigation combined with iopMR imaging in LTLE surgery led to radical resection in 96.6% of the patients, due to immediate correction of underestimated resection in 21.6% of patients. This protocol resulted in a favourable seizure outcome and a low complication rate.
EVALuna2:7229

Improved survival for elderly married glioblastoma patients : Better treatment delivery, less toxicity, and fewer disease complications - Putz, Florian; Putz, Tobias; Goerig, Nicole; Knippen, Stefan; Gryc, Thomas; Eyüpoglu, Ilker Yasin; Roessler, Karl; Semrau, Sabine; Lettmaier, Sebastian; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
OBJECTIVES: Marital status is a well-described prognostic factor in patients with gliomas but the observed survival difference is unexplained in the available population-based studies. METHODS: A series of 57 elderly glioblastoma patients (≥70 years) were analyzed retrospectively. Patients received radiotherapy or chemoradiation with temozolomide. The prognostic significance of marital status was assessed. Disease complications, toxicity, and treatment delivery were evaluated in detail. RESULTS: Overall survival was significantly higher in married than in unmarried patients (median, 7.9 vs. 4.0 months; p = 0.006). The prognostic significance of marital status was preserved in the multivariate analysis (HR, 0.41; p = 0.011). Married patients could receive significantly higher daily temozolomide doses (mean, 53.7 mg/m² vs. 33.1 mg/m²; p = 0.020), were more likely to receive maintenance temozolomide (45.7 % vs. 11.8 %; p = 0.016), and had to be hospitalized less frequently during radiotherapy (55.0 % vs. 88.2 %; p = 0.016). Of the patients receiving temozolomide, married patients showed significantly lower rates of hematologic and liver toxicity. Most complications were infectious or neurologic in nature. Complications of any grade were more frequent in unmarried patients (58.8 % vs. 30.0 %; p = 0.041) with the incidence of grade 3-5 complications being particularly elevated (47.1 % vs. 15.0 %; p = 0.004). CONCLUSION: We found poorer treatment delivery as well as an unexpected severe increase in toxicity and disease complications in elderly unmarried glioblastoma patients. Marital status may be an important predictive factor for clinical decision-making and should be addressed in further studies.
EVALuna2:32918

Incisionless MR-guided focused ultrasound: technical considerations and current therapeutic approaches in psychiatric disorders - Kinfe, Thomas Mehari; Stadlbauer, Andreas; Winder, Klemens; Hurlemann, Rene; Buchfelder, Michael (Expert review of neurotherapeutics, 2020)
Introduction: MR-guided focused ultrasound operating at higher intensities have been reported to effectively and precisely ablate deeper brain structures like the basal ganglia or the thalamic nuclei for the treatment of refractory movement disorders, neuropathic pain and most recently neuropsychiatric disorders, while low-intensity focused ultrasound represents an approach promoting mechanical blood-brain-barrier opening and neuromodulation. This narrative review summarizes the technical development and the therapeutic potential of incisionless MRgFUS in order to treat neuropsychiatric disorders. Areas covered: A narrative review of clinical trials assessing the safety and efficacy of MRgFUS. A literature review was performed using the following search terms: MR-guided focused ultrasound, psychiatric disorders, noninvasive and invasive brain modulation/stimulation techniques. Expert opinion: MRgFUS ablation is under clinical investigation (unblinded study design) for obsessive-compulsive disorders (OCDs) [capsulotomy; ALIC] and depression/anxiety disorders [capsulotomy] and has demonstrated an improvement in OCD and depression, although of preliminary character. Low-intensity ultrasound applications have been explored in Alzheimer´s disease (phase 1 study) and healthy subjects. Currently, limited evidence hinders comparison and selection between MRgFUS and noninvasive/invasive brain modulation therapies. However, comparative, sham-controlled trials are needed to reexamine the preliminary findings for the treatment of psychiatric disorders.
CRIS-Team Scopus Importer:2020-07-10
Keywords: capsulotomy; cingulotomy; deep brain stimulation; depression; Noninvasive MR-guided focused ultrasound; obsessive-compulsive disorder; outcome measures; radiosurgery

Individualized targeting and optimization of multi-channel transcranial direct current stimulation in drug-resistant epilepsy - Antonakakis, Marios; Rampp, Stefan; Kellinghaus, Christoph; Wolters, Carsten H.; Moeddel, Gabriel (Proceedings - 2019 IEEE 19th International Conference on Bioinformatics and Bioengineering, BIBE 2019, 2019)
The principle of epilepsy surgery in patients with drug-resistant focal epilepsy is to localize and then to resect the epileptogenic zone. However, epilepsy surgery might not be feasible if a cortical malformation or focal cortical dysplasia (FCD), is located very close to eloquent areas of the brain. Non-invasive brain stimulation is a promising technique for modulating brain activity and may become a neurotherapeutic approach for suppressing long term epileptic seizures. In the present study, we optimize a multi-channel transcranial direct current stimulation (tDCS) montage based on Electro-(EEG) and Magneto-Encephalography (MEG) source analysis for the therapeutic stimulation of a patient with drug-resistant epilepsy due to an FCD located very close to Broca's area. We first construct a realistic volume conductor Finite Element Method (FEM) model of the patient's head, including skull defects, calibrated skull conductivities and white matter conductivity anisotropy. Single modality (EEG or MEG) and combined EEG/MEG (EMEG) source analysis is performed for localizing the irritative zone that caused interictal epileptic discharges (IEDs). We then adopt a novel optimization algorithm, Alternating Direction Method of Multipliers (ADMM), in order to optimize the multichannel tDCS montage for distributing the injected currents in the target brain region. The patient's source analysis indicates localizations very close to the FCD and orientations to a different cortical side depending on the used measurement modality. The resulting tDCS optimized montage is based on the source reconstruction which is closer to the FCD and the occurred stimulation montage is focal over the detected FCD. The combination of individual source analysis for targeting and optimization algorithms for the estimation of a tDCS montage is a promising neurotherapeutic approach of suppressing long term epileptic seizures.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Brain stimulation; EEG; Finite element method; Focal epilepsy; MEG

Induction of anti-tumor responses via antigen targeting of dendritic cells in vivo - Amon, Lukas; Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Heger, Lukas; Lühr, Jennifer; Hofmann, Andrea; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Inferring histology-associated gene expression gradients in spatial transcriptomic studies - Kueckelhaus, Jan; Frerich, Simon; Kada-Benotmane, Jasim; Koupourtidou, Christina; Ninkovic, Jovica; Dichgans, Martin; Beck, Juergen; Schnell, Oliver; Heiland, Dieter Henrik (Nature Communications, 2024)
Spatially resolved transcriptomics has revolutionized RNA studies by aligning RNA abundance with tissue structure, enabling direct comparisons between histology and gene expression. Traditional approaches to identifying signature genes often involve preliminary data grouping, which can overlook subtle expression patterns in complex tissues. We present Spatial Gradient Screening, an algorithm which facilitates the supervised detection of histology-associated gene expression patterns without prior data grouping. Utilizing spatial transcriptomic data along with single-cell deconvolution from injured mouse cortex, and TCR-seq data from brain tumors, we compare our methodology to standard differential gene expression analysis. Our findings illustrate both the advantages and limitations of cluster-free detection of gene expression, offering more profound insights into the spatial architecture of transcriptomes. The algorithm is embedded in SPATA2, an open-source framework written in R, which provides a comprehensive set of tools for investigating gene expression within tissue.
CRIS-Team Scopus Importer:2024-09-06

Inhibition of Heat Shock Factor 1 Enhances Repressive Molecular Mechanisms on the POMC Promoter - Ciato, Denis; Li, Ran; Garcia, Jose Luis Monteserin; Papst, Lilia; D'Annunzio, Sarah; Hristov, Michael; Tichomirowa, Maria A.; Belaya, Zhanna; Rozhinskaya, Liudmila; Buchfelder, Michael; Theodoropoulou, Marily; Paez-Pereda, Marcelo; et al. (Neuroendocrinology, 2019)
Background: Cushing's disease (CD) is caused by adrenocorticotropic hormone (ACTH)-secreting pituitary tumours. They express high levels of heat shock protein 90 and heat shock factor 1 (HSF1) in comparison to the normal tissue counterpart, indicating activated cellular stress. Aims: Our objectives were: (1) to correlate HSF1 expression with clinical features and hormonal/radiological findings of CD, and (2) to investigate the effects of HSF1 inhibition as a target for CD treatment. Patients/Methods: We examined the expression of total and pSer326HSF1 (marker for its transcriptional activation) by Western blot on eight human CD tumours and compared to the HSF1 status of normal pituitary. We screened a cohort of 45 patients with CD for HSF1 by immunohistochemistry and correlated the HSF1 immunoreactivity score with the available clinical data. We evaluated the effects of HSF1 silencing with RNA interference and the HSF1 inhibitor KRIBB11 in AtT-20 cells and four primary cultures of human corticotroph tumours. Results: We show that HSF1 protein is highly expressed and transcriptionally active in CD tumours in comparison to normal pituitary. The immunoreactivity score for HSF1 did not correlate with the typical clinical features of the disease. HSF1 inhibition reduced proopiomelanocortin (Pomc) transcription in AtT-20 cells. The HSF1 inhibitor KRIBB11 suppressed ACTH synthesis from 75% of human CD tumours in primary cell culture. This inhibitory action on Pomc transcription was mediated by increased glucocorticoid receptor and suppressed Nurr77/Nurr1 and AP-1 transcriptional activities. Conclusions: These data show that HSF1 regulates POMC transcription. Pharmacological targeting of HSF1 may be a promising treatment option for the control of excess ACTH secretion in CD.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Cushing's disease; Heat shock factor 1; KRIBB11; POMC

Initiating anticoagulant therapy after ICH is associated with patient characteristics and treatment recommendations - Sembill, Jochen; Wieser, Claudia; Sprügel, Maximilian; Gerner, Stefan; Giede-Jeppe, Antje; Reindl, Caroline; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Journal of Neurology, 2018)
The proportion of patients with intracerebral hemorrhage (ICH) and concomitant indication for oral anticoagulant (OAC) therapy is increasing. Although recent studies documented a favorable risk-benefit profile of OAC initiation, deciding whether, when, and which OAC should be started remains controversial. We investigated (1) OAC recommendations, its implementation, and adherence and (2) factors associated with OAC initiation after ICH. This prospective observational study analyzed consecutive ICH patients (n = 246) treated at the neurological and neurosurgical department of the University-Hospital Erlangen, Germany over a 21-month inclusion period (05/2013-01/2015). We analyzed the influence of patient characteristics, in-hospital measures, and functional status on treatment recommendations and on OAC initiation during 12-month follow-up. In-hospital mortality of 24.8% (n = 61/246) left 185 patients discharged alive of which 34.1% (n = 63/185) had OAC indication. In these patients, OAC initiation was clearly recommended in only 49.2% (n = 31/63) and associated with favorable [modified Rankin Scale (mRS) = 0-3] functional discharge status [OR 7.18, CI (1.05-49.13), p = 0.04], less frequent heart failure [OR 0.19, CI (0.05-0.71), p = 0.01], and younger age [OR 0.95, CI (0.90-1.00), p = 0.05]. OAC was more often started if clearly recommended [n = 19/31 (61.3%) versus (no recommendation) n = 4/26 (15.4%), p < 0.001; (clearly not recommended, n = 6)] and associated with younger age [67 (58-74) versus 79 (73-83), p < 0.001], favorable functional outcome [n = 10/23 (43.5%) versus n = 5/40 (12.5%), p = 0.01], decreased mortality [n = 6/23 (26.1%) versus n = 19/40 (47.5%), p = 0.06], and functional improvement [n = 13/17 (76.5%) versus n = 7/21 (33.3%), p = 0.01]. We observed no differences in rates of intracranial complications [thromboembolism, n = 3/23 (13.0%) versus n = 4/40 (10.0%), p = 1.00; hemorrhage, n = 1/23 (4.3%) versus n = 3/40 (7.5%), p = 1.00]. Clear treatment recommendations by attending stroke physicians significantly influence OAC initiation after ICH. OAC were more frequently recommended and started in younger patients with better functional recovery independent from intracranial complications. This might represent an important determinant of observed beneficial associations, hinting towards an indication bias which might affect observational analyses.
EVALuna2:34916

Insights into the infiltrative behavior of adamantinomatous craniopharyngioma in a new xenotransplant mouse model - Stache, Christina; Hoelsken, Annett; Schlaffer, Sven-Martin; Heß, Andreas; Metzler, Markus; Frey, Benjamin; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Buslei, Rolf (Brain Pathology, 2015)
Adamantinomatous craniopharyngiomas (adaCP) cause hypothalamic pituitary dysfunction. Elucidation of pathomechanisms underlying tumor progression is essential for the development of targeted chemotherapeutic treatment options. In order to study the mechanisms of tumor outgrowth, we implanted human primary adaCP tissue from three different surgical specimens stereotactically into the brain of immunodeficient mice (n = 20). Three months after tumor inoculation, magnetic resonance imaging and histology confirmed tumor engraftment in all 20 mice (100%) that obtained tissue transplants. The lesions invaded adjoining brain tissue with micro finger-shaped protrusions. Immunohistochemical comparison of the primary tumor and xenotransplants revealed a similar amount of proliferation (Mib-1) and cytokeratin expression pattern (KL-1). Whole tumor reconstruction using serial sections confirmed whirl-like cell clusters with nuclear ?-catenin accumulations at the tumor brain border. These whirls were surrounded by a belt of Claudin-1 expressing cells, showed an activated epidermal growth factor receptor (EGFR) and distinct CD133 as well as p21(WAF1/Cip1) positivity, indicating a tumor stem cell phenotype. Consistent with our previous in vitro studies, intracranial xenotransplants of adaCP confirmed cells with nuclear ?-catenin and activated EGFR being the driving force of tumor outgrowth. This model provides the possibility to study in vivo tumor cell migration and to test novel treatment regimens targeting this tumor stem cell niche.
EVALuna2:7210

Integration of functional neuronavigation and intraoperative MRI in surgery for drug-resistant extratemporal epilepsy close to eloquent brain areas - Sommer, Bjoern; Grummich, Peter; Coras, Roland; Kasper, Burkhard S.; Blümcke, Ingmar; Hamer, Hajo; Stefan, Hermann; Buchfelder, Michael; Roessler, Karl (Neurosurgical Focus, 2013)
Object. The authors performed a retrospective study to assess the impact of functional neuronavigation and intraoperative MRI (iMRI) on surgery of extratemporal epileptogenic lesions on postsurgical morbidity and seizure control. Methods. Twenty-five patients (14 females and 11 males) underwent extratemporal resections for drug-resistant epilepsy close to speech/motor brain areas or adjacent to white matter tracts. The mean age at surgery was 34 years (range 12-67 years). The preoperative mean disease duration was 13.2 years. To avoid awake craniotomy, cortical motor-sensory representation was mapped during preoperative evaluation in 14 patients and speech representation was mapped in 15 patients using functional MRI. In addition, visualization of the pyramidal tract was performed in 11 patients, of the arcuate fascicle in 7 patients, and of the visual tract in 6 patients using diffusion tensor imaging. The mean minimum distance of tailored resection between the eloquent brain areas was 5.6mm. During surgery, blood oxygen level-dependent imaging and diffusion tensor imaging data were integrated into neuronavigation and displayed through the operating microscope. The postoperative mean follow-up was 44.2 months. Results. In 20% of these patients, further intraoperative resection was performed because of intraoperatively documented residual lesions according to iMRI findings. At the end of resection, the final iMRI scans confirmed achievement of total resection of the putative epileptogenic lesion in all patients. Postoperatively, transient complications and permanent complications were observed in 20% and 12% of patients, respectively. Favorable postoperative seizure control (Engel Classes I and II) was achieved in 84% and seizure freedom in 72% of these consecutive surgical patients. Conclusions. By using functional neuronavigation and iMRI for treatment of epileptogenic brain lesions, the authors achieved a maximum extent of resection despite the lesions' proximity to eloquent brain cortex and fiber tracts in all cases. The authors' results underline possible benefits of this technique leading to a favorable seizure outcome with acceptable neurological deficit rates in difficult-to-treat extratemporal epilepsy. © AANS, 2013.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Eloquent brain area; Extratemporal epilepsy; Functional neuronavigation; Intraoperative MRI; Seizure outcome; Surgery

INTEGRATION OF MULTIMODAL IMAGING AND INTRAOPERATIVE MR IN RESECTIVE SURGERY FOR MEDICALLY REFRACTORY EPILEPSY: THE ERLANGEN EXPERIENCE OF 415 PATIENTS - Sommer, B.; Roessler, K.; Hofmann, Andrea; Coras, R.; Kasper, Burkhard; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (2016)
EVALuna2:33851

Interfacing Motor Units in Nonhuman Primates Identifies a Principal Neural Component for Force Control Constrained by the Size Principle - Del Vecchio, Alessandro; Jones, Rachael H.A.; Schofield, Ian S.; Kinfe, Thomas Mehari; Ibáñez, Jaime; Farina, Dario; Baker, Stuart N. (The Journal of Neuroscience, 2022)
Motor units convert the last neural code of movement into muscle forces. The classic view of motor unit control is that the CNS sends common synaptic inputs to motoneuron pools and that motoneurons respond in an orderly fashion dictated by the size principle. This view, however, is in contrast with the large number of dimensions observed in motor cortex, which may allow individual and flexible control of motor units. Evidence for flexible control of motor units may be obtained by tracking motor units longitudinally during tasks with some level of behavioral variability. Here we identified and tracked populations of motor units in the brachioradialis muscle of two macaque monkeys during 10 sessions spanning.1 month with a broad range of rate of force development (1.8-38.6 N · m · s21). We found a very stable recruitment order and discharge characteristics of the motor units over sessions and contraction trials. The small deviations from orderly recruitment were fully predicted by the motor unit recruitment intervals, so that small shifts in recruitment thresholds happened only during contractions at a high rate of force development. Moreover, we also found that one component explained more than;50% of the motor unit discharge rate variance, and that the remaining components represented a time-shifted version of the first. In conclusion, our results show that the recruitment of motoneurons is determined by the interplay of the size principle and common input and that this recruitment scheme is not violated over time or by the speed of the contractions.
CRIS-Team Scopus Importer:2022-10-21
Keywords: common synaptic input; EMG; motor units; peripheral stimulation; size principle

Interictal and Ictal MEG in presurgical evaluation for epilepsy surgery - Stefan, Hermann; Rampp, Stefan (Acta Epileptologica, 2020)
Although presurgical evaluation of patients with pharamacoresistent focal epilepsies provides essential information for successful epilepsy surgery, there is still a need for further improvement. Developments of noninvasive electrophysiological recording and analysis techniques offer additional information based on interictal and ictal epileptic activities. In this review, we provide an overview on the application of ictal magnetoencephalography (MEG). The results of a literature research for published interictal/ictal MEG findings and experiences with own cases are demonstrated and discussed. Ictal MEG may provide added value in comparison to interictal recordings. The results may be more focal and closer to the invasively determined seizure onset zone. In some patients without clear interictal findings, ictal MEG could provide correct localization. Novel recording and analysis techniques facilitate ictal recordings. However, extended recording durations, movement and artifacts still represent practical limitations. Ictal MEG may provide added value regarding the localization of the seizure onset zone but depends on the selection of patients and the application of optimal analysis techniques.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Ictal MEG; Interictal MEG; Localization of epileptic activity; Presurgical evaluation

Interictal Electrical Source Imaging. - Rampp, Stefan; Müller-Voggel, Nadia; Hamer, Hajo; Dörfler, Arnd; Brandner, Sebastian; Buchfelder, Michael (Journal of Clinical Neurophysiology, 2024)
Interictal electrical source imaging (ESI) determines the neuronal generators of epileptic activity in EEG occurring outside of seizures. It uses computational models to take anatomic and neuronal characteristics of the individual patient into account. The presented article provides an overview of application and clinical value of interictal ESI in patients with pharmacoresistant focal epilepsies undergoing evaluation for surgery. Neurophysiological constraints of interictal data are discussed and technical considerations are summarized. Typical indications are covered as well as issues of integration into clinical routine. Finally, an outlook on novel markers of epilepsy for interictal source analysis is presented. Interictal ESI provides diagnostic performance on par with other established methods, such as MRI, PET, or SPECT. Although its accuracy benefits from high-density recordings, it provides valuable information already when applied to EEG with only a limited number of electrodes with complete coverage. Novel oscillatory markers and the integration of frequency coupling and connectivity may further improve accuracy and efficiency.
EVALuna2:547206

Interictal epileptiform discharges affect memory in an Alzheimer's disease mouse model - Soula, Marisol; Maslarova, Anna; Harvey, Ryan E.; Valero, Manuel; Brandner, Sebastian; Hamer, Hajo; Fernández-Ruiz, Antonio; Buzsáki, György (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Interictal epileptiform discharges (IEDs) are transient abnormal electrophysiological events commonly observed in epilepsy patients but are also present in other neurological diseases, such as Alzheimer's disease (AD). Understanding the role IEDs have on the hippocampal circuit is important for our understanding of the cognitive deficits seen in epilepsy and AD. We characterize and compare the IEDs of human epilepsy patients from microwire hippocampal recording with those of AD transgenic mice with implanted multilayer hippocampal silicon probes. Both the local field potential features and firing patterns of pyramidal cells and interneurons were similar in the mouse and human. We found that as IEDs emerged from the CA3-1 circuits, they recruited pyramidal cells and silenced interneurons, followed by post-IED suppression. IEDs suppressed the incidence and altered the properties of physiological sharp-wave ripples, altered their physiological properties, and interfered with the replay of place field sequences in a maze. In addition, IEDs in AD mice inversely correlated with daily memory performance. Together, our work implies that IEDs may present a common and epilepsy-independent phenomenon in neurodegenerative diseases that perturbs hippocampal-cortical communication and interferes with memory.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Alzheimer model; interictal epileptiform discharges; memory; replay; sharp wave ripples

Interictal magnetoencephalography used in magnetic resonance imaging-negative patients with epilepsy - Wu, Xueqing; Rampp, Stefan; Buchfelder, Michael; Kuwert, Torsten; Blümcke, Ingmar; Zhou, D.; Stefan, Herrmann; Dörfler, Arnd (Acta Neurologica Scandinavica, 2013)
Purpose: This study aims to investigate the contributions of magnetoencephalography (MEG) in magnetic resonance imaging (MRI)-negative patients. Methods: A total of 18 MRI-negative patients diagnosed with refractory epilepsy, subjected to MEG investigation, and subsequently underwent surgery were selected for retrospective analysis. A 1.5-tesla Magnetom Sonata with an eight-channel head array coil was used. MEG data were obtained using a 74/248-channel system. Results: A total of 16 patients (16/18) had positive MEG results, comprising 12 patients with monofocal localizations, five with multifocal localizations, and one with unremarkable results in MEG. In addition, 12 patients had indicative single photon-emission computed tomography (SPECT), five had indicative fluorodeoxyglucose positron emission tomography (FDG-PET), and all the patients had intracranial electroencephalography (EEG) (14 with subdural electrodes and four with electrocorticography). The intracranial EEG recordings of nine patients were guided by MEG informative results. Among these 18 patients, 10 exhibited good postoperative outcomes (Engel I and II), four of which were completely seizure-free. All these ten patients had clear monofocal localization in MEG, including nine with accordant indicative metabolic changes in either SPECT or FDG-PET, or both. None of the five patients with multifocal localizations achieved good postoperative outcomes. Conclusion: For cases with negative MRI findings, epilepsy surgery may be an alternative option for pharmaco-resistant patients if epileptogenic focus localizations by MEG are present in multimodal evaluation. © 2012 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Magnetic resonance imaging; Magnetoencephalography; Non-lesional epilepsy; Outcome

Interlaboratory proficiency processing scheme in CSF aliquoting: implementation and assessment based on biomarkers of Alzheimer's disease - Lewczuk, Piotr; Gaignaux, Amelie; Kofanova, Olga; Ermann, Natalia; Betsou, Fay; Brandner, Sebastian; Mroczko, Barbara; Blennow, Kaj; Strapagiel, Dominik; Paciotti, Silvia; Vogelgsang, Jonathan; Roehrl, Michael H.; et al. (Alzheimer's Research and Therapy, 2018)
BACKGROUND: In this study, we tested to which extent possible between-center differences in standardized operating procedures (SOPs) for biobanking of cerebrospinal fluid (CSF) samples influence the homogeneity of the resulting aliquots and, consequently, the concentrations of the centrally analyzed selected Alzheimer's disease biomarkers. METHODS: Proficiency processing samples (PPSs), prepared by pooling of four individual CSF samples, were sent to 10 participating centers, which were asked to perform aliquoting of the PPSs into two secondary aliquots (SAs) under their local SOPs. The resulting SAs were shipped to the central laboratory, where the concentrations of amyloid beta (Aβ) 1-42, pTau181, and albumin were measured in one run with validated routine analytical methods. Total variability of the concentrations, and its within-center and between-center components, were analyzed with hierarchical regression models. RESULTS: We observed neglectable variability in the concentrations of pTau181 and albumin across the centers and the aliquots. In contrast, the variability of the Aβ1-42 concentrations was much larger (overall coefficient of variation 31%), with 28% of the between-laboratory component and 10% of the within-laboratory (i.e., between-aliquot) component. We identified duration of the preparation of the aliquots and the centrifugation force as two potential confounders influencing within-center variability and biomarker concentrations, respectively. CONCLUSIONS: Proficiency processing schemes provide objective evidence for the most critical preanalytical variables. Standardization of these variables may significantly enhance the quality of the collected biospecimens. Studies utilizing retrospective samples collected under different local SOPs need to consider such differences in the statistical evaluations of the data.
EVALuna2:211623

International recommendation for a comprehensive neuropathologic workup of epilepsy surgery brain tissue: A consensus Task Force report from the ILAE Commission on Diagnostic Methods - Blümcke, Ingmar; Aronica, Eleonora; Miyata, Hajime; Sarnat, Harvey B.; Thom, Maria; Roessler, Karl; Rydenhag, Bertil; Jehi, Lara; Krsek, Pavel; Wiebe, Samuel; Spreafico, Roberto (Epilepsia, 2016)
Epilepsy surgery is an effective treatment in many patients with drug-resistant focal epilepsies. An early decision for surgical therapy is facilitated by a magnetic resonance imaging (MRI)-visible brain lesion congruent with the electrophysiologically abnormal brain region. Recent advances in the pathologic diagnosis and classification of epileptogenic brain lesions are helpful for clinical correlation, outcome stratification, and patient management. However, application of international consensus classification systems to common epileptic pathologies (e.g., focal cortical dysplasia [FCD] and hippocampal sclerosis [HS]) necessitates standardized protocols for neuropathologic workup of epilepsy surgery specimens. To this end, the Task Force of Neuropathology from the International League Against Epilepsy (ILAE) Commission on Diagnostic Methods developed a consensus standard operational procedure for tissue inspection, distribution, and processing. The aims are to provide a systematic framework for histopathologic workup, meeting minimal standards and maximizing current and future opportunities for morphofunctional correlations and molecular studies for both clinical care and research. Whenever feasible, anatomically intact surgical specimens are desirable to enable systematic analysis in selective hippocampectomies, temporal lobe resections, and lesional or nonlesional neocortical samples. Correct orientation of sample and the sample's relation to neurophysiologically aberrant sites requires good communication between pathology and neurosurgical teams. Systematic tissue sampling of 5-mm slabs along a defined anatomic axis and application of a limited immunohistochemical panel will ensure a reliable differential diagnosis of main pathologies encountered in epilepsy surgery.
EVALuna2:7311

Inter-Subject Variability of Skull Conductivity and Thickness in Calibrated Realistic Head Models - Antonakakis, Marios; Schrader, Sophie; Aydin, Ümit; Khan, Asad; Gross, Joachim; Zervakis, Michalis; Rampp, Stefan; Wolters, Carsten H. (NeuroImage, 2020)
Skull conductivity has a substantial influence on EEG and combined EEG and MEG source analysis as well as on optimized transcranial electric stimulation. To overcome the use of standard literature values, we propose a non-invasive two-level calibration procedure to estimate skull conductivity individually in a group study with twenty healthy adults. Our procedure requires only an additional run of combined somatosensory evoked potential and field data, which can be easily integrated in EEG/MEG experiments. The calibration procedure uses the P20/N20 topographies and subject-specific realistic head models from MRI. We investigate the inter-subject variability of skull conductivity and relate it to skull thickness, age and gender of the subjects, to the individual scalp P20/N20 surface distance between the P20 potential peak and the N20 potential trough as well as to the individual source depth of the P20/N20 source. We found a considerable inter-subject variability for (calibrated) skull conductivity (8.44 ± 4.84 mS/m) and skull thickness (5.97 ± 1.19 mm) with a statistically significant correlation between them (rho = 0.52). Age showed a statistically significant negative correlation with skull conductivity (rho = -0.5). Furthermore, P20/N20 surface distance and source depth showed large inter-subject variability of 12.08 ± 3.21 cm and 15.45 ± 4.54 mm, respectively, but there was no significant correlation between them. We also found no significant differences among gender subgroups for the investigated measures. It is thus important to take the inter-subject variability of skull conductivity and thickness into account by means of using subject-specific calibrated realistic head modeling.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Calibrated Realistic Head Model; EEG/MEG Source Analysis; Skull Conductivity; Skull Thickness; Somatosensory evoked responses; Transcranial Electric Stimulation

Intracranial Germinomas: Diagnosis, Pathogenesis, Clinical Presentation, and Management - Kremenevski, Natalia; Buchfelder, Michael; Hore, Nirjhar (Current Oncology Reports, 2023)
Purpose of ReviewIntracranial germinomas constitute a rare brain tumor entity of unknown etiology, characterized by unique histopathology and molecular biology. In this manuscript, we review the literature focusing on the epidemiology, histopathology with molecular biology, clinical presentation with emphasis on tumor location, diagnostic workup, and current treatment strategies with related clinical outcomes of intracranial germinomas.Recent FindingsAlthough the optimal treatment strategy remains a matter of debate, intracranial germinomas respond well to radiotherapy, chemotherapy, or a combination of both and are characterized by very high cure and survival rates. It is well-known that early discrimination of germinomas from other intracranial neoplasms facilitates the timely initiation of appropriate treatment, thereby contributing to the reduction of morbidity as well as mortality.Ongoing research will need to be directed towards discovering and refining reliable parameters for early diagnosis and evaluation of prognosis in patients with intracranial germinomas.
CRIS-Team WoS Importer:2023-05-05

Intraoperative continuous cerebral microcirculation measurement in patients with aneurysmal subarachnoid hemorrhage: preliminary data on the early administration of magnesium sulfate - Sommer, Bjoern; Weidinger, Cornelia; Wolf, Dennis; Buchfelder, Michael; Schmitt, Hubert (BMC Anesthesiology, 2017)
BACKGROUND: In patients with subarachnoid hemorrhage (SAH), vasospasm remains one of the major complications. The application of intravenous magnesium sulfate (MgSO4) has been under discussion to prevent cerebral ischemia. Our aim was to examine the impact of early MgSO4 administration on local cerebral microcirculation during microsurgical clipping of SAH-related aneurysms. METHODS: The non-invasive laser-Doppler spectrophotometry system "Oxygen-to-See (O2C)" was used in 14 consecutive patients (11 female, 3 male, median age 56.5±9.7 yrs) with aneurysmatic SAH. A subdural probe measured capillary venous oxygenation (SO2), relative hemoglobin content (rHb), blood cell velocity (velo) and blood flow (flow) in 7 mm tissue depth. Data samples were recorded as baseline immediately before intraoperative application of MgSO4 10% 50 mg/kg body weight and 10 min thereafter. The continuous MgSO4 infusion rate depended on blood pressure (mean arterial pressure > 60-65 mmHg) and lasted a maximum of 60 min. RESULTS: MgSO4 was administered 2.8 (min. 1.6, max. 15.5) hours after onset of symptoms. Median flow increased significantly by 20.8% (5-68%, p = 0.001). Velo increased 4.9% (1-17%), rHb decreased 1.5% (3-34%) and SO2 decreased 9.4% (8-38%) by trend compared to the baseline values. FiO2 correlated positively with velo (rs = 0.712, p = 0.004), whereas arterial HCO3 correlated negatively with SO2 (rs = -0.599, p = 0.024). Of 14 patients, 2 had symptomatic vasospasm. CONCLUSIONS: Our data suggest an increased cerebral blood flow after early intraoperative administration of MgSO4 in patients with SAH. Using a non-invasive laser-Doppler spectrophotometry system, this technique is feasible for continuous real-time monitoring of cerebral microcirculation. TRIAL REGISTRATION: DRKS (German Clinical Trial Registry), DRKS00013047 , retrospectively registered on September 21st, 2017.
EVALuna2:35115

Intraoperative high-field MRI for transsphenoidal reoperations of nonfunctioning pituitary adenoma - Berkmann, Sven; Schlaffer, Sven-Martin; Nimsky, Christopher; Fahlbusch, Rudolf; Buchfelder, Michael (Journal of Neurosurgery, 2014)
The loss of anatomical landmarks, frequently invasive tumor growth, and tissue changes make transsphenoidal reoperation of nonfunctioning pituitary adenomas (NFAs) challenging. The use of intraoperative MRI (iMRI) may lead to improved results. The goal of this retrospective study was to evaluate the impact of iMRI on transsphenoidal reoperations for NFA.Between September 2002 and July 2012, 109 patients underwent reoperations in which 111 transsphenoidal procedures were performed and are represented in this study. A 1.5-T Magnetom Sonata Maestro Class scanner (Siemens) was used for iMRI. Follow-up iMRI scans were acquired if gross-total resection (GTR) was suspected or if no further removal seemed possible.Surgery was performed for tumor persistence and regrowth in 26 (23%) and 85 (77%) patients, respectively. On the initial iMRI scans, GTR was confirmed in 19 (17%) patients. Remnants were located as follows: 65 in the cavernous sinus (71%), 35 in the suprasellar space (38%), 9 in the retrosellar space (10%). Additional resection was possible in 62 (67%) patients, resulting in a significant volume reduction and increased GTR rate (49%). The GTR rates of invasive tumors on initial iMRI and postoperative MRI (poMRI) were 7% and 25%, respectively. Additional remnant resection was possible in 64% of the patients. Noninvasive tumors were shown to be totally resected on the initial iMRI in 31% of cases. After additional resection for 69% of the procedures, the GTR rate on poMRI was 75%. Transcranial surgery to resect tumor remnants was indicated in 5 (5%), and radiotherapy was performed in 29 (27%) patients. After GTR, no recurrence was detected during a mean follow-up of 2.2 ± 2.1 years.The use of iMRI in transsphenoidal reoperations for NFA leads to significantly higher GTR rates. It thus prevents additional operations and reduces the number of tumor remnants. The complication rates do not exceed the incidences reported in the literature for primary transsphenoidal surgery. If complete tumor resection is not possible, iMRI guidance can facilitate tumor volume reduction.
EVALuna2:22840

Intraoperative Intermittent Pneumatic Compression Reduces Incidence of Venous Thromboembolism in Patients Undergoing Craniotomy: Study Protocol of a Randomized Multicenter, Single-Blind Trial - Scheer, Maximilian; Schenk, Grit; Taute, Bettina; Richter, Michael; Hlavac, Michael; Gempt, Jens; Krammer, Matthias; Shiban, Ehab; Sabel, Michael; Stein, Marco; Wienke, Andreas; Höllig, Anke; et al. (Neurosurgery practice, 2024)
BACKGROUND AND OBJECTIVE: Venous thromboembolism (VTE), which includes deep vein thrombosis (DVT) and pulmonary embolism (PE), is a common complication in craniotomy patients. The duration of surgery has been identified as a risk factor for the development of VTE. In a pilot study, the use of intermittent pneumatic venous compression (IPC) dramatically reduced the incidence of VTE. Despite randomization, a significant difference in the duration of surgery between the groups limited the validity of this result. The study was underpowered to compensate for this problem. We now present the protocol of a multicenter trial. METHODS: All patients receive medical compression stockings and low-molecular-weight heparin from the first postoperative day. The therapy group receives IPC stockings intraoperatively. Postoperatively, all patients receive lower-extremity duplex sonography to detect/exclude DVT within the first 7 postoperative days. Contrast-enhanced chest CT is the gold standard for the detection of PE and is performed in cases of clinical suspicion of PE. EXPECTED OUTCOMES: The incidence of VTE is the primary end point. The distinction between symptomatic and asymptomatic, etiologies, influence of lesion type, duration of surgery, and mortality will be evaluated as secondary end points. The pilot study showed a VTE incidence of 26% in the control group vs 7% in the treatment group. To avoid overly optimistic treatment effect assumptions, we assume VTE rates of 9% and 24% in the treatment and control groups, respectively, and thus calculated a number of 127 patients per treatment group. DISCUSSION: If this trial shows that intraoperative IPC reduces the risk of VTE to the extent observed in our pilot study (number needed to treat: 5.24), the potential benefit to neurosurgical patients would be significant. The results would potentially influence treatment guidelines by providing the high-quality evidence needed to make robust recommendations.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Deep vein thrombosis; Neuro-oncology; Pulmonary embolism

Intraoperative magnetic resonance imaging in epilepsy surgery: systematic review of the literature and meta-analysis - Tomschik, Matthias; Shawarba, Julia; Mercea, Petra A.; Dorfer, Christian; Rössler, Karl (Journal of Neurosurgical Sciences, 2022)
INTRODUCTION: Intraoperative magnetic resonance imaging (iopMRI) is increasingly incorporated into neurosurgery to improve outcomes. However, its usefulness in epilepsy surgery remains debated. To elucidate its current role, we conducted a systematic review of the data published to date. EVIDENCE ACQUISITION: We performed a systematic review of the available literature using the PubMed, Scopus, and Embase database. Only articles detailing the usefulness of iopMRI in quantifiable measures were included. Different aspects of iopMRI in epilepsy surgery were analyzed and two meta-analyses summarizing its impact on extent of resection and seizure outcomes performed. EVIDENCE SYNTHESIS: A total of 33 articles met the inclusion criteria, comprising a total of 1313 patients, both children and adults operated under iopMRI guidance. The mean rate of return to surgery was 29.2% in 30 articles reporting this number. Eleven publications were eligible for meta-analysis of seizure outcome in patients with refractory epilepsy, who had undergone surgery with iopMRI (N.=294) compared to controls (N.=298). Eight articles described the impact of iopMRI on the radiological extent of resection. In both regards, usage of iopMRI improved outcomes in our meta-analysis with an OR of 3.8 and 4.75, respectively. CONCLUSIONS: This work presents the first meta-analysis of the value of iopMRI in epilepsy surgery. Its use resulted in an improvement of the desired extent of resection and led to a better seizure outcome compared to conventional surgery. Understanding its benefits might help improve surgical strategies in traditional, open epilepsy surgery.
CRIS-Team Scopus Importer:2022-12-02

Intraoperative Magnetic Resonance Imaging of Cerebral Oxygen Metabolism During Resection of Brain Lesions - Stadlbauer, Andreas; Merkel, Andreas; Zimmermann, Max; Sommer, Björn; Buchfelder, Michael; Meyer-Bäse, Anke; Rössler, Karl (World Neurosurgery, 2017)
OBJECTIVE: Tissue oxygen tension is an important parameter for brain tissue viability and its noninvasive intraoperative monitoring in the whole brain is of highly clinical relevance. The purpose of this study was the introduction of a multiparametric quantitative blood oxygenation dependent magnetic resonance imaging (MRI) approach for intraoperative examination of oxygen metabolism during the resection of brain lesions. METHODS: Sixteen patients suffering from brain lesions were examined intraoperatively twice (before craniotomy and after gross-total resection) via the quantitative blood oxygenation dependent technique and a 1.5-Tesla MRI scanner, which is installed in an operating room. The MRI protocol included T2*- and T2 mapping and dynamic susceptibility weighted perfusion. Data analysis was performed with a custom-made, in-house MatLab software for calculation of maps of oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO2) as well as of cerebral blood volume and cerebral blood flow. RESULTS: Perilesional edema showed a significant increase in both perfusion (cerebral blood volume +21%, cerebral blood flow +13%) and oxygen metabolism (OEF +32%, CMRO2 +16%) after resection of the lesions. In perilesional nonedematous tissue only, however, oxygen metabolism (OEF +19%, CMRO2 +11%) was significantly increased, but not perfusion. No changes were found in normal brain. Fortunately, no neurovascular adverse events were observed. CONCLUSIONS: This approach for intraoperative examination of oxygen metabolism in the whole brain is a new application of intraoperative MRI additionally to resection control (residual tumor detection) and updating of neuronavigation (brain shift detection). It may help to detect neurovascular adverse events early during surgery.
EVALuna2:102201

Intraoperative Magnetic-Resonance Tomography and Neuronavigation During Resection of Focal Cortical Dysplasia Type II in Adult Epilepsy Surgery Offers Better Seizure Outcomes - Roessler, Karl; Kasper, Burkhard; Heynold, Elisabeth; Coras, Roland; Sommer, Bjoern; Rampp, Stefan; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (World Neurosurgery, 2018)
Focal cortical dysplasia (FCD) is one important cause of drug-resistant epilepsy potentially curable by epilepsy surgery. We investigated the options of using neuronavigation and intraoperative magnetic-resonance tomographical imaging (MRI) to avoid residual epileptogenic tissue during resection of patients with FCD II to improve seizure outcome.Altogether, 24 patients with FCD II diagnosed by MRI (16 female, 8 male; mean age 34 ± 10 years) suffered from drug-resistant electroclinical and focal epilepsy for a mean of 20.7 ± 5 years. Surgery was performed with preoperative stereoelectroencephalography (in 15 patients), neuronavigation, and intraoperative 1.5T-iopMRI in all 24 investigated patients.In 75% of patients (18/24), a complete resection was performed. In 89% (16/18) of completely resected patients, we documented an Engel I seizure outcome after a mean follow-up of 42 months. All incompletely resected patients had a worse outcome (Engel II-III, P < 0.0002). Patients with FCD IIB had also significant better seizure outcome compared with patients diagnosed as having FCD IIA (82% vs. 28%, P < 0.02). In 46% (11/24) of patients, intraoperative second-look surgeries due to residual lesions detected during the intraoperative MRI were performed. In these 11 patients, there were significant more completely seizure free patients (73% vs. 38% Engel IA), compared with 13 patients who finished surgery after the first intraoperative MRI (P < 0.05).Excellent seizure outcome after surgery of patients with FCD II positively correlated with the amount of resection, histologic subtype, and the use of intraoperative MRI, especially when intraoperative second-look surgeries were performed.
EVALuna2:7382

Intraoperative use of high-field MRI in hypothalamic hamartomas associated with epilepsy: clinico-pathological presentation of five adult patients - Sommer, Bjoern; Schlaffer, Sven-Martin; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Stefan, Hermann; Buchfelder, Michael (Acta Neurochirurgica, 2014)
Hypothalamic harmartomas (HHs) are either occasionally associated with medically intractable epileptic syndromes or precocious puberty. Due to the extraordinary location and the expansive intra-axial growth, surgical resection is difficult and challenging without causing severe neurological, hypothalamic or endocrinological deficits, which account for higher mortality and morbidity.We present a series of five adult patients with drug-resistant epilepsy who had been operated on for HH using neuronavigation and intraoperative 1.5-T magnetic resonance imaging (MRI). In this retrospective investigation, we compared our surgical strategy and postoperative results to existing series.During surgery, we identified remnant HH in the first intraoperative MRI control scan in three out of five patients. After re-segmentation of the residual lesion using neuronavigation, complete resection was achieved in two of the three patients as confirmed by final intraoperative and late follow-up MRI, raising the rate of total resections to four out of five patients. Two patients died during the observation period. One patient suffered from a permanent third nerve palsy and one from a transient monoparesis of the left arm. New endocrinological disturbances included diabetes insipidus centralis in two and secondary hypothyroidism and hypogonadism in one patient. Four out of five patients had favourable seizure control (Engel I or II) after 64.8 (34-83) months of mean follow-up.Neuronavigation and intraoperative MRI are valuable tools to encounter difficulties while performing surgery in patients with HHs. Intraoperative resection control increases the amount of maximum resection.
EVALuna2:7252

Intraoperative vascular DIVA surgery reveals angiogenic hotspots in tumor zones of malignant gliomas - Eyüpoglu, Ilker Yasin; Hore, Nirjhar; Fan, Zheng; Buslei, Rolf; Merkel, Andreas; Buchfelder, Michael; Savaskan, Nicolai E. (Scientific Reports, 2015)
Malignant gliomas belong to the most threatening tumor entities and are hallmarked by rapid proliferation, hypervascularization and an invasive growth pattern. The primary obstacle in surgical treatment lies in differentiation between healthy and pathological tissue at the tumor margins, where current visualization methods reach their limits. Here, we report on a novel technique (vascular dual intraoperative visualization approach - vDIVA) enabling visualization of different tumor zones (TZ I-III) on the basis of angiogenic hotspots. We investigated glioblastoma patients who underwent 5-ALA fluorescence-guided surgery with simultaneous intraoperative ICG fluorescence angiography. This vDIVA technique revealed hypervascularized areas which were further histologically investigated. Neuropathological assessments revealed tissue areas at the resection margins corresponding to TZ II, and postoperative CD34- and Map2 immunostaining confirmed these angiogenic hotspots to be occupied by glioma cells. Hence, the vascular architecture in this transitional zone could be well differentiated from both primary tumor bulk and healthy brain parenchyma. These data demonstrate that ICG fluorescence angiography improves state-of-the-art glioma surgery techniques and facilitates the future characterization of polyclonal attributes of malignant gliomas.
EVALuna2:7262

Intraoperative Vascular Neuromonitoring in Patients with Subarachnoid Hemorrhage: A Pilot Study Using Combined Laser-Doppler Spectrophotometry - Schmitz, Emilija; Bischoff, Barbara; Wolf, Dennis; Schmitt, Hubert; Eyupoglu, Ilker Y.; Roessler, Karl; Buchfelder, Michael; Sommer, Bjoern (World Neurosurgery, 2017)
BACKGROUND: Intraoperative monitoring of cerebral microcirculation in patients with subarachnoid hemorrhage (SAH) may predict the postoperative neurologic outcome. In this pilot study, we examined the value of a novel noninvasive real-time measurement technique for detecting changes in local microcirculation. METHODS: We used the O2C (Oxygen to see) laser-Doppler spectrophotometry system in 14 patients with Hunt & Hess grade 2-5 SAH who underwent microsurgical cerebral aneurysm clipping. A subdural probe recorded capillary venous oxygenation (SO2), relative hemoglobin concentration, blood cell velocity, and blood flow at a tissue depth of 7 mm. Data were recorded immediately before dural closure. We also recorded somatosensory evoked potentials (SEPs) with median and tibial nerve stimulation. Results were compared with neurologic performance, as measured on the modified Rankin Scale, at the day of discharge from the hospital and 12 months thereafter. RESULTS: Patient functional outcomes after discharge and 12 months were correlated with pathological decreased flow and increased SO2 values. In 6 of 8 patients, microcirculatory monitoring parameters indicated ischemia during surgery, as shown by electrophysiological SEP changes and infarction detected on the postoperative computed tomography (CT) scan. Pathological SEP results correlated closely with infarct demarcation as seen on CT. CONCLUSIONS: Our results indicate the potential benefit of intraoperative combined laser-Doppler flowmetry and spectrophotometry for predicting postoperative clinical outcomes in this small patient sample. Larger-cohort testing is needed to verify our findings and show the possible merits of this novel method.
EVALuna2:35113

Intratumoral heterogeneity of oxygen metabolism and neovascularization uncovers 2 survival-relevant subgroups of IDH1 wild-type glioblastoma - Stadlbauer, Andreas; Zimmermann, Max; Dörfler, Arnd; Oberndorfer, Stefan; Buchfelder, Michael; Coras, Roland; Kitzwoegerer, Melitta; Roessler, Karl (Neuro-Oncology, 2018)
Background: The intratumoral heterogeneity of oxygen metabolism in combination with variable patterns of neovascularization (NV) as well as reprogramming of energy metabolism affects the landscape of tumor microenvironments (TMEs) in glioblastoma. Knowledge of the hypoxic and perivascular niches within the TME is essential for understanding treatment failure. Methods: Fifty-two patients with untreated glioblastoma (isocitrate dehydrogenase 1 wild type [IDH1wt]) were examined with a physiological MRI protocol including a multiparametric quantitative blood oxygen level dependent (qBOLD) approach and vascular architecture mapping (VAM). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of 6 different TMEs: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation (OxPhos), and glycolysis with/without neovascularization. Association of the different TME volume fractions with progression-free survival (PFS) was assessed using Kaplan-Meier analysis and Cox proportional hazards models. Results: A common spatial structure of TMEs was detected: central necrosis surrounded by tumor hypoxia (with defective and functional neovasculature) and different TMEs with a predominance of OxPhos and glycolysis for energy production, respectively. The percentage of the different TMEs on the total tumor volume uncovered 2 clearly different subtypes of glioblastoma IDH1wt: a glycolytic dominated phenotype with predominantly functional neovasculature and a necrotic/hypoxic dominated phenotype with approximately 50% of defective neovasculature. Patients with a necrotic/hypoxic dominated phenotype showed significantly shorter PFS (P = 0.035). Conclusions: Our non-invasive mapping approach allows for classification of the TME and detection of tumor-supportive niches in glioblastoma which may be helpful for both clinical patient management and research.
EVALuna2:36560

Intraventricular fibrinolysis has no effects on shunt dependency and functional outcome in endovascular-treated aneurysmal SAH - Gerner, Stefan; Kuramatsu, Joji; Abel, Henning; Kloska, Stephan; Lücking, Hannes; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Neurocritical Care, 2014)
Intraventricular fibrinolysis (IVF) in subarachnoid hemorrhage (SAH) is an emerging strategy aiming to hasten clot lysis, treat hydrocephalus, and reduce permanent shunt rates. Because of clinical heterogeneity of investigated patient effects of IVF on permanent shunt incidence and functional outcome are widely debated. The present study is the first to investigate solely endovascular-treated SAH patients.Overall, 88 consecutive patients with aneurysmal SAH requiring external ventricular drain placement and endovascular aneurysm closure were included. Functional outcome and shunt dependency were assessed 90 days after event. A matched controlled sub-analysis was carried out to investigate the effects of IVF treatment (n = 14; matching criteria: age, neuro-status and imaging). Multivariate modeling was performed to identify independent predictors for permanent shunt dependency.In IVF-patients neurological status was significantly poorer [Hunt&Hess: IVF = 4(3-5) vs. non-IVF = 3(1-5); p = 0.035] and the extent of ventricular hemorrhage was increased [Graeb Score: IVF = 7(6-8) vs. non-IVF = 3(1-4); p <= 0.001]. Consecutive matched controlled sub-analysis revealed no significant therapeutic effect of IVF with respect to shunt dependency rate and functional outcome. Multivariate analysis revealed Graeb score [OR = 1.34(1.02-1.76); p = 0.035] and sepsis [OR = 11.23(2.28-55.27); p = 0.003] as independent predictors for shunt dependency, whereas IVF did not exert significant effects (p = 0.820).In endovascular-treated SAH patients IVF neither reduced permanent shunt dependency nor influenced functional outcome. Despite established effects on intraventricular clot resolution IVF appears less powerful in SAH as compared to ICH. Given the reported positive effects of lumbar drainage (LD) in SAH, a prospective analysis of a combined treatment approach of IVF and subsequent lumbar drain sOeems warranted aiming to reduce permanent shunting and improve functional outcome.
EVALuna2:22283

Intraventricular SEEG and laser ablation for the treatment of infantile spasm: Technical note - Xu, Xinghua; Wang, Qun; Zhao, Yining; Xu, Xin; Gan, Zhichao; Zhang, Shiyu; Chen, Xiaolei (Brain and Behavior, 2023)
Objectives: Infantile spasm (IS) is an epileptic encephalopathy with ongoing neurological damage due to seizures and epileptiform abnormalities. Epilepsy surgery is considered for children refractory to drug therapy, especially when there is a focal brain lesion. In this study, we investigated the feasibility and efficacy of intraventricular stereotactic electroencephalography (SEEG) and laser ablation for the treatment of IS children with focal brain lesions. Methods: We performed the first reported study using ventriculoscopic laser ablation to treat IS. Seven IS children with drug-resistant epilepsy and definite encephalomalacia on brain magnetic resonance imaging scan were included in this study. Ablation was performed after confirmation of epileptiform discharges by SEEG under the surveillance of ventriculoscope. Results: The median follow-up time for the cohort was 3.1 years and 86% (6/7) of the children had an Engel class ≤III epilepsy at the final follow-up. Five (71%) children had a reduction in seizure medication usage, and the other two were on the same amount as preablation. None of the children experienced serious new neurological deficits. Laser ablation might result in seizure freedom by destroying the local brain network and blocking the spread of abnormal discharges. Conclusions: Intraventricular SEEG and laser ablation was feasible and effective for the treatment of IS. Further studies are warranted.
CRIS-Team Scopus Importer:2023-08-04
Keywords: epilepsy; infantile spasm; laser ablation; ventriculoscope

Introducing the Concept of Error Vectors to Improve Source Localization Results of Epileptic Discharges - Unnwongse, Kanjana; Wolters, Carsten H.; Wehner, Tim; Krger, Lia Theophilo; Rampp, Stefan; Wellmer, Jörg (Journal of Clinical Neurophysiology, 2025)
Purpose:To improve EEG source localization results of interictal epileptic discharges (IED) by applying postprocessing step to electrical source imaging (ESI).Methods:Localization error of ESI was evaluated in comparison to known sources of stimulation potentials (ESP) by recording simultaneous stereo-EEG/scalp EEG. Error vectors were defined as the offset of the ESI-dipole of ESP to the stereo-EEG contacts used for stimulation. The inverted error vector was applied to the ESI-dipole of IED (IED-dipole).Results:Seven IED clusters were evaluated. Corrected IED-dipoles were located closer to IED-onset contacts on stereo-EEG than uncorrected IED-dipoles (median [IQR]: 7.8 [2.5] versus 18.7 [10.7] mm, P = 0.02). Anatomically, for high skull conductivities, all corrected IED-dipoles were located in cortical structures or adjacent to epileptogenic lesion, whereas uncorrected IED-dipoles were located in white matter or CSF (P = 0.02). Physiologically, cortical extent of IED generators estimated from corrected IED-dipoles was 16.5 cm2 (IQR = 10.4 cm2) and 7.4 cm2 (range 5.8-9.2 cm2) in the group of anterior temporal IED and prefrontal IED, respectively; the former was concordant with the extent estimated by subdural electrodes. In addition, the relationship of stereo-EEG IED amplitude (a) drop with increasing distance (d) from corrected IED-dipole could be modeled as a negative power equation a(d)∝1/db (R2 = 0.87, P < 0.01), with b ranging from 0.79 to 2.3, median: 1.57, consistent with a simulation model of the sensitivity of intracerebral electrode.Conclusions:Application of inverted error vector reduces localization error and shifts IED-dipole to an anatomically and physiologically plausible location.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Electrical source imaging; Epileptic discharge; Generator; Localization error; Presurgical evaluation; stereo EEG contact

Introduction: clinical neuropathology in the diagnostics of epilepsy Einleitung: Klinische Neuropathologie in der Epilepsiediagnostik - Haaker, Gerrit; Roessler, Karl; Blümcke, Ingmar (Zeitschrift für Epileptologie, 2017)
Epilepsy surgery has become accepted as a successful therapeutic option in patients with drug-resistant focal epilepsy and was comprehensively reviewed in the August 2016 issue of this journal [16]. As a general conclusion, patients with a structural brain lesion as the likely trigger for the patient’s drug-refractory epilepsy are candidates for a successful surgical therapy. Neuropathology is mandatory to identify and classify any structural brain lesion in surgically resected tissue samples in order to assign a scientifically validated diagnosis; however, the spectrum of epilepsy-associated brain lesions is broad, covering neoplasms, neuronal cell death and degeneration (hippocampal sclerosis), malformations of cortical development, glial scars, vascular malformations and inflammation. The neuropathology reference center for epilepsy surgery in Erlangen identified 36 histopathological entities in a series of 5622 patients, whereby the 10 most common disease entities accounted for 84.3% of the entire cohort. More than half of all the patients had either hippocampal sclerosis, ganglioglioma or type II focal cortical dysplasia (total of 54.3%). These figures and numbers also highlight typical patterns for localization of the lesion and seizure onset. Together with previously published series of post-surgical long-term seizure control, the neuropathological investigations and evaluation of large patient collectives provide a reliable basis for prediction of the most suitable candidates for epilepsy surgery.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain; Dysplasia; Neurosurgery; Pathology; Seizure

Investigation of subdural electrode displacement in invasive epilepsy surgery workup using neuronavigation and intraoperative MRI - Sommer, Bjoern; Rampp, Stefan; Dörfler, Arnd; Stefan, Hermann; Hamer, Hajo; Buchfelder, Michael; Roessler, Karl (Neurological Research, 2018)
OBJECTIVES: One of the main obstacles of electrode implantation in epilepsy surgery is the electrode shift between implantation and the day of explantation. We evaluated this possible electrode displacement using intraoperative MRI (iopMRI) data and CT/MRI reconstruction. METHODS: Thirteen patients (nine female, four male, median age 26 ± 9.4 years) suffering from drug-resistant epilepsy were examined. After implantation, the position of subdural electrodes was evaluated by 3.0 T-MRI and thin-slice CCT for 3D reconstruction. Localization of electrodes was performed with the volume-rendering technique. Post-implantation and pre-explantation 1.5 T-iopMRI scans were coregistered with the 3D reconstructions to determine the extent of electrode dislocation. RESULTS: Intraoperative MRI at the time of explantation revealed a relevant electrode shift in one patient (8%) of 10 mm. Median electrode displacement was 1.7 ± 2.6 mm with a coregistration error of 1.9 ± 0.7 mm. The median accuracy of the neuronavigation system was 2.2 ± 0.9 mm. Six of twelve patients undergoing resective surgery were seizure free (Engel class 1A, median follow-up 37.5 ± 11.8 months). CONCLUSION: Comparison of pre-explantation and post-implantation iopMRI scans with CT/MRI data using the volume-rendering technique resulted in an accurate placement of electrodes. In one patient with a considerable electrode dislocation, the surgical approach and extent was changed due to the detected electrode shift. ABBREVIATIONS: ECoG: electrocorticography; EZ: epileptogenic zone; iEEG: invasive EEG; iopMRI: intraoperative MRI; MEG: magnetoencephalography; PET: positron emission tomography; SPECT: single photon emission computed tomography; 3D: three-dimensional.
EVALuna2:201939

In vitro performance of combinations of anti-siphon devices with differential pressure valves in relation to the spatial position - Fiss, I.; Vanderheyden, M.; von der Brelie, C.; Bettag, C.; Hore, N.; Freimann, F.; Thomale, U. W.; Rohde, V.; Brandner, Sebastian (Acta Neurochirurgica, 2020)
Background: Programmable differential pressure (DP) valves combined with an anti-siphon device (ASD) represent the current standard of care in preemtping overdrainage associated with ventriculoperitoneal shunting for hydrocephalus. Objective: We aimed to provide comparative data of four combinations of two ASDs of different working principles in combination with two DP valves in an in vitro model in order to achieve a better understanding of the flow characteristics and potential clinical application. Methods: We analyzed the flow performance of four possible combinations of two DP valves (CHPV [HM]; proGAV 2.0[PG]) in combination with either a gravity-regulated (Shuntassistant [SA]) or a flow-regulated (SiphonGuard [SG]) ASD in an in vitro setup. A DP between 4 and 60 cmH2O was generated, and the specific flow characteristics were measured. In addition, the two combinations with gravity-regulated ASDs were measured in defined spatial positions. Results: Flow characteristics of the SA combinations corresponded to the DP in linear fashion and to the spatial position. Flow characteristics of the SG combinations were dependent upon the DP in a non-linear fashion and independent of the spatial position. Highest mean flow rate of the PG-SG- (HM-SG-) combination was 1.41 ± 0.24 ml/min (1.16 ± 0.06 ml/min). The mean flow rates sharply decreased with increasing inflow pressure and subsequently increased slowly up to 0.82 ± 0.26 ml/min (0.77 ± 0.08 ml/min). Conclusion: All tested device combinations were able to control hydrostatic effect and prevent consecutive excessive flow, to varying degrees. However, significant differences in flow characteristics can be seen, which might be relevant for their clinical application.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Anti-siphon device; Hydrocephalus; Overdrainage; Shunt valve

In vitro performance of six combinations of adjustable differential pressure valves and fixed anti-siphon devices with and without vertical motion - Fiss, I.; Röhrig, P.; Hore, N.; von der Brelie, C.; Bettag, C.; Freimann, F. B.; Thomale, U. W.; Rohde, V.; Brandner, Sebastian (Acta Neurochirurgica, 2020)
Objective: Adjustable differential pressure (DP) valves in combination with fixed anti-siphon devices are currently a popular combination in counteracting the effects of cerebrospinal fluid overdrainage following implantation of a ventriculoperitoneal shunt system. The study examined the flow performance of three DP valves in successive combination with an anti-siphon device in an in vitro shunt laboratory with and without vertical motion. Methods: We analyzed three DP valves (Codman Hakim Medos programmable valve [HM], Codman CertasPlus [CP], and Miethke proGAV [PG], in combination with either Codman SiphonGuard [SG] or Miethke ShuntAssistant [SA]), resulting in the evaluation of six different valve combinations. Defined DP conditions between 4 and 40 cm H2O within a simulated shunt system were generated and the specific flow characteristics were measured. In addition, combinations with SA, which is a gravity-dependent valve, were measured in defined spatial positions (90°, 60°). All device combinations were tested during vertical motion with movement frequencies of 2, 3, and 4 Hz. Results: All valve combinations effectively counteracted the siphon effect in relation to the chosen DP. Angulation-related flow changes were similar in the three combinations of DP valve and SA in the 60° and 90° position. In CP-SA and PG-SA, repeated vertical movement at 2, 3, and 4 Hz led to significant increase in flow, whereas in HM-SA, constant increase was seen at 4 Hz only (flow change at 4Hz, DP 40 cm H2O: PG (opening pressure 4 cm H2O) 90°: 0.95 ml/min, 60°: 0.71 ml/min; HM (opening pressure 4 cm H2O) 90°: 0.66 ml/min, 60°: 0.41 ml/min; CP (PL 2) 90°: 0.94 ml/min, 60°: 0.79 ml/min; p < 0.01); however, HM-SA showed relevant motion-induced flow already at low DPs (0.85 ml/min, DP 4 cm H2O). In combinations of DP valve with SG, increase of flow was far less pronounced and even led to significant reduction of flow in certain constellations. Maximum overall flow increase was 0.46 ± 0.04 ml/min with a HM (opening pressure 12 cm H2O) at 2 Hz and a DP of 10 cm H2O, whereas maximum flow decrease was 1.12 ± 0.08 with a PG (opening pressure 4 cm H2O) at 3 Hz and a DP of 10 cmH2O. Conclusion: In an experimental setup, all valve combinations effectively counteracted the siphon effect in the vertical position according to their added resistance. Motion-induced increased flow was consistently demonstrated in combinations of DP valve and SA. The combination of HM and SA especially showed relevant motion-induced flow already at low DPs. In combinations of DP and SG, the pattern of the motion induced flow was more inconsistent and motion even led to significant flow reduction, predominantly at DPs of 10 and 20 cmH2O.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Anti-siphon device; Hydrocephalus; Overdrainage; Shunt valve

Is Hypothermia Helpful in Severe Subarachnoid Hemorrhage? An Exploratory Study on Macro Vascular Spasm, Delayed Cerebral Infarction and Functional Outcome after Prolonged Hypothermia - Kuramatsu, Joji; Kollmar, Rainer; Gerner, Stefan; Madzar, Dominik; Pisarcikova, Andrea; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (Cerebrovascular Diseases, 2015)
Therapeutic hypothermia (TH) is an established treatment after cardiac arrest and growing evidence supports its use as neuroprotective treatment in stroke. Only few and heterogeneous studies exist on the effect of hypothermia in subarachnoid hemorrhage (SAH). A novel approach of early and prolonged TH and its influence on key complications in poor-grade SAH, vasospasm and delayed cerebral ischemia (DCI) was evaluated.This observational matched controlled study included 36 poor-grade (Hunt and Hess Scale >3 and World Federation of Neurosurgical Societies Scale >3) SAH patients. Twelve patients received early TH (<48 h after ictus), mild (35°C), prolonged (7 ± 1 days) and were matched to 24 patients from the prospective SAH database. Vasospasm was diagnosed by angiography, macrovascular spasm serially evaluated by Doppler sonography and DCI was defined as new infarction on follow-up CT. Functional outcome was assessed at 6 months by modified Rankin Scale (mRS) and categorized as favorable (mRS score 0-2) versus unfavorable (mRS score 3-6) outcome.Angiographic vasospasm was present in 71.0% of patients. TH neither influenced occurrence nor duration, but the degree of macrovascular spasm as well as peak spastic velocities were significantly reduced (p < 0.05). Frequency of DCI was 87.5% in non-TH vs. 50% in TH-treated patients, translating into a relative risk reduction of 43% and preventive risk ratio of 0.33 (95% CI 0.14-0.77, p = 0.036). Favorable functional outcome was twice as frequent in TH-treated patients 66.7 vs. 33.3% of non-TH (p = 0.06).Early and prolonged TH was associated with a reduced degree of macrovascular spasm and significantly decreased occurrence of DCI, possibly ameliorating functional outcome. TH may represent a promising neuroprotective therapy possibly targeting multiple pathways of DCI development, notably macrovascular spasm, which strongly warrants further evaluation of its clinical impact.
EVALuna2:22357

It is time to harmonize clinical MEG practice internationally - Bagić, Anto I.; Rampp, Stefan (Clinical Neurophysiology, 2020)
CRIS-Team Scopus Importer:2020-06-09

Kinetics of oxytocin effects on amygdala and striatal reactivity vary between women and men - Lieberz, Jana; Scheele, Dirk; Spengler, Franny B.; Matheisen, Tatjana; Schneider, Lìa; Stoffel-Wagner, Birgit; Kinfe, Thomas Mehari; Hurlemann, René (Neuropsychopharmacology, 2019)
Accumulating evidence suggests that intranasal oxytocin (OXT; 24 IU) reduces amygdala responses to fear-related stimuli in men, while exerting inverse effects in women. However, OXT enhances activity of the brain reward system in both sexes. Importantly, a crucial and still open question is whether there are sex-specific dose-response relationships for the amygdala and striatal regions. To address this question, a total of 90 healthy women participated in a double-blind, placebo-controlled crossover functional magnetic resonance imaging (fMRI) study and the results were compared with our previous findings from men. Participants were randomly assigned to three doses of OXT (6 IU, 12 IU, and 24 IU) and completed an emotional face recognition task including fearful and happy faces of varying emotional intensities. Across doses, OXT enhanced amygdala reactivity to low fearful faces compared to placebo and increased responses to happy faces in the dorsal striatum in women. While treatment effects on amygdala reactivity were evident at each given dose, the OXT effect on striatal responses to social stimuli was more pronounced with higher doses, but this dose-dependent effect did not survive correction for multiple comparisons. Importantly, OXT effects on amygdala and striatal activation significantly differed between sexes and striatal baseline sexual-dimorphic response patterns were diminished after administration of OXT. Our findings suggest that OXT increases the salience of social signals by strengthening the sensitivity for these signals in the amygdala and in the striatum in women, while OXT may primarily induce anxiolysis by reducing amygdala responses in men.
CRIS-Team Scopus Importer:2019-12-17

Landscape of somatic mutations in sporadic GH-secreting pituitary adenomas - Ronchi, Cristina L.; Peverelli, Erika; Herterich, Sabine; Weigand, Isabel; Mantovani, Giovanna; Schwarzmayr, Thomas; Sbiera, Silviu; Allolio, Bruno; Honegger, Juergen; Appenzeller, Silke; Lania, Andrea G.; Reincke, Martin; et al. (European Journal of Endocrinology, 2016)
Alterations in the cAMP signaling pathway are common in hormonally active endocrine tumors. Somatic mutations at GNAS are causative in 30-40% of GH-secreting adenomas. Recently, mutations affecting the USP8 and PRKACA gene have been reported in ACTH-secreting pituitary adenomas and cortisol-secreting adrenocortical adenomas respectively. However, the pathogenesis of many GH-secreting adenomas remains unclear.Comprehensive genetic characterization of sporadic GH-secreting adenomas and identification of new driver mutations.Screening for somatic mutations was performed in 67 GH-secreting adenomas by targeted sequencing for GNAS, PRKACA, and USP8 mutations (n=31) and next-generation exome sequencing (n=36).By targeted sequencing, known activating mutations in GNAS were detected in five cases (16.1%), while no somatic mutations were observed in both PRKACA and USP8. Whole-exome sequencing identified 132 protein-altering somatic mutations in 31/36 tumors with a median of three mutations per sample (range: 1-13). The only recurrent mutations have been observed in GNAS (31.4% of cases). However, seven genes involved in cAMP signaling pathway were affected in 14 of 36 samples and eight samples harbored variants in genes involved in the calcium signaling or metabolism. At the enrichment analysis, several altered genes resulted to be associated with developmental processes. No significant correlation between genetic alterations and the clinical data was observed.This study provides a comprehensive analysis of somatic mutations in a large series of GH-secreting adenomas. No novel recurrent genetic alterations have been observed, but the data suggest that beside cAMP pathway, calcium signaling might be involved in the pathogenesis of these tumors.
EVALuna2:22842

Large-Scale Graph Networks and AI Applied to Medical Image Data Processing - Meyer-Baese, Anke; Foo, Simon; Tahmassebi, Amirhessam; Meyer-Baese, Uwe; Amani, Ali Moradi; Götz, Theresa; Leithner, Doris; Stadlbauer, Andreas; Pinker-Domenig, Katja (COMPUTATIONAL IMAGING V, 2020)
CRIS-Team WoS Importer:2021-07-30

Lateralization of delta band power in magnetoencephalography (MEG) in patients with unilateral focal epilepsy and its relation to verbal fluency - Annika Melissa, S.; Hug, Marion; Conradi, Nadine; Kienitz, Ricardo; Rosenow, Felix; Rampp, Stefan; Merkel, Nina (Brain and Behavior, 2023)
Introduction: Delta power is a clinically established biomarker for abnormal brain processes. However, in patients with unilateral focal epilepsy (FE) it is still not well understood, how it relates to the epileptogenic zone and to neurocognitive functioning. The aim of the present study was thus to assess how delta power relates to the affected hemisphere, whether lateralization strength differs between the patients, and how changes in delta power correlate with cognitive functioning. Method: We retrospectively studied patients with left (LFE) and right FE (RFE) who had undergone a resting-state magnetoencephalography measurement. We computed global and hemispheric delta power and lateralization indices and examined whether delta power correlates with semantic and letter verbal fluency (former being a marker for language and verbal memory, latter for executive functions) in 26 FE patients (15 LFE, 11 RFE) and 10 healthy controls. Results: Delta power was increased in FE patients compared to healthy controls. However, the increase across hemispheres was related to the site of the epileptic focus: On group level, LFE patients showed higher delta power in both hemispheres, whereas RFE patients primarily exhibited higher delta power in the ipsilateral right hemisphere. Both groups showed co-fluctuations of delta power between the hemispheres. Besides, delta power correlated negatively only with letter verbal fluency. Conclusion: The findings confirm and provide further evidence that delta power is a marker of pathological activity and abnormal brain processes in FE. Delta power dynamics differ between patient groups, indicating that delta power could offer additional diagnostic value. The negative association of delta power and letter verbal fluency suggests that executive dysfunctions are related to low frequency abnormalities.
CRIS-Team Scopus Importer:2023-10-06
Keywords: delta band power; focal epilepsy; MEG; verbal fluency

Lateralization of interictal delta slowing in the magnetoencephalography (MEG) in patients with focal epilepsy and its relation to cognitive functions - Schuster, Annika Melissa; Behrens, Marion; Conradi, Nadine; Strzelczyk, Adam; Rosenow, Felix; Rampp, Stefan; Merkel, Nina (EPILEPSIA, 2021)
CRIS-Team WoS Importer:2021-11-26

Learning a Hand Model from Dynamic Movements Using High-Density EMG and Convolutional Neural Networks - Simpetru, Raul; Arkudas, Andreas; Braun, Dominik; Oßwald, Marius; Souza de Oliveira, Daniela; Eskofier, Björn; Kinfe, Thomas Mehari; Del Vecchio, Alessandro (IEEE Transactions on Biomedical Engineering, 2024)
Objective: Surface electromyography (sEMG) can sense the motor commands transmitted to the muscles. This work presents a deep learning method that can decode the electrophysiological activity of the forearm muscles into the movements of the human hand. Methods: We have recorded the kinematics and kinetics of the hand during a wide range of grasps and individual digit movements that cover 22 degrees of freedom of the hand at slow (0.5 Hz) and comfortable (1.5 Hz) movement speeds in 13 healthy participants. The input of the model consists of 320 non-invasive EMG sensors placed on the extrinsic hand muscles. Results: Our network achieves accurate continuous estimation of both kinematics and kinetics, surpassing the performance of comparable networks reported in the literature. By examining the latent space of the network, we find evidence that it mapped EMG activity into the anatomy of the hand at the individual digit level. In contrast to what is observed from the low-pass filtered EMG and linear decoding approaches, we found that the full-bandwidth EMG (monopolar unfiltered) signals during synergistic and individual digit movements contain distinct neural embeddings that encode each movement of the human hand. These manifolds consistently represent the anatomy of the hand and are generalized across participants. Moreover, we found a task-specific distribution of the embeddings without any presence of correlated activations during multi- and individual-digit tasks. Conclusion/Significance: The proposed method could advance the control of assistive hand devices by providing a robust and intuitive interface between muscle signals and hand movement
Keywords: Thumb; Task analysis; Deep learning; EMG; Force; Deep Learning; Electromyography; Muscles; Recording; Kinematics; Kinematics

Leptin and Associated Mediators of Immunometabolic Signaling: Novel Molecular Outcome Measures for Neurostimulation to Treat Chronic Pain - Kinfe, Thomas Mehari; Buchfelder, Michael; Chaudhry, Shafqat R.; Chakravarthy, Krishnan V.; Deer, Timothy R.; Russo, Marc; Georgius, Peter; Hurlemann, Rene; Rasheed, Muhammad; Muhammad, Sajjad; Yearwood, Thomas L. (International Journal of Molecular Sciences, 2019)
Chronic pain is a devastating condition affecting the physical, psychological, and socioeconomic status of the patient. Inflammation and immunometabolism play roles in the pathophysiology of chronic pain disorders. Electrical neuromodulation approaches have shown a meaningful success in otherwise drug-resistant chronic pain conditions, including failed back surgery, neuropathic pain, and migraine. A literature review (PubMed, MEDLINE/OVID, SCOPUS, and manual searches of the bibliographies of known primary and review articles) was performed using the following search terms: chronic pain disorders, systemic inflammation, immunometabolism, prediction, biomarkers, metabolic disorders, and neuromodulation for chronic pain. Experimental studies indicate a relationship between the development and maintenance of chronic pain conditions and a deteriorated immunometabolic state mediated by circulating cytokines, chemokines, and cellular components. A few uncontrolled in-human studies found increased levels of pro-inflammatory cytokines known to drive metabolic disorders in chronic pain patients undergoing neurostimulation therapies. In this narrative review, we summarize the current knowledge and possible relationships of available neurostimulation therapies for chronic pain with mediators of central and peripheral neuroinflammation and immunometabolism on a molecular level. However, to address the needs for predictive factors and biomarkers, large-scale databank driven clinical trials are needed to determine the clinical value of molecular profiling.
CRIS-Team Scopus Importer:2019-10-04
Keywords: biomarkers development; chronic pain; immunometabolism; neuromodulation; quantitative outcome measures; systemic inflammation

Lesion guided stereotactic radiofrequency thermocoagulation for palliative, in selected cases curative epilepsy surgery - Wellmer, Joerg; Parpaley, Yaroslav; Rampp, Stefan; Popkirov, Stoyan; Kugel, Harald; Aydin, Uemit; Wolters, Carsten H.; Von Lehe, Marec; Voges, Juergen (Epilepsy Research, 2016)
Resective epilepsy surgery is an established treatment option in patients with pharmacoresistant, lesion related epilepsy. Yet, if the presurgical work-up proves multi-focal organization of the epileptogenic zone, or the area of intended resection is close to eloquent brain areas, patients may decide against resections because of an unfavorable risk-benefit-ratio. We assess if lesion guided cortical stereotactic radiofrequency thermocoagulation (L-RFTC) is a potential surgical alternative in these patients.We performed seven procedures of L-RFTC. Three patients had monofocal epilepsy arising close to eloquent structures; in four, invasive pre-surgical workup documented monofocal seizure onset but strong interictal epileptic activity also independent and distant from the seizure onset zone. L-RFTC was restricted to the lesional area (=seizure onset site).12 to 37 months after RFTC worthwhile seizure improvement was achieved in 6 patients. One patient became seizure free following complete coagulation of a focal cortical dysplasia, two had had 1-2 auras under tapered but not under continued medication. In one patient only subclinical seizures persisted. In one patient hypermotor seizures were transformed into milder short tonic seizures and another one had a seizure reduction by 50%. Only one patient did not profit at all. One patient developed a persisting neurological deficit.In patients with complex epileptogenic zones L-RFTC can lead to worthwhile seizure reduction. This qualifies this procedure as a palliative surgical technique with potential good risk-benefit ratio. In patients with small focal cortical dysplasias L-RFTC may even allow minimal-invasive surgery with curative intention.
EVALuna2:22454

Letter to the Editor: Announcement of a Call for Proposals for biomedical waveform coding - Halford, J. J.; Campobello, G.; Brinkmann, B. H.; Stead, M.; Rampp, Stefan; Rémi, J.; Nilsen, K. B.; Dauwels, J.; Galanti, M.; Dean, B. C.; Winkler, S.; Ehrenberg, J. A.; et al. (Clinical Neurophysiology, 2024)
CRIS-Team Scopus Importer:2024-07-19

Levoketoconazole treatment in endogenous Cushing's syndrome: extended evaluation of clinical, biochemical, and radiologic outcomes - Fleseriu, Maria; Auchus, Richard J.; Greenman, Yona; Zacharieva, Sabina; Geer, Eliza B.; Salvatori, Roberto; Pivonello, Rosario; Feldt-Rasmussen, Ulla; Kennedy, Laurence; Buchfelder, Michael; Biller, Beverly Mk; Cohen, Fredric; et al. (European Journal of Endocrinology, 2022)
Objective: This extended evaluation (EE) of the SONICS study assessed the effects of levoketoconazole for an additional 6 months following open-label, 6-month maintenance treatment in endogenous Cushing's syndrome. Design/Methods: SONICS included dose-titration (150-600 mg BID), 6-month maintenance, and 6-month EE phases. Exploratory efficacy assessments were performed at months 9 and 12 (relative to the start of maintenance). For pituitary MRI in patients with Cushing's disease, a threshold of ≥2 mm denoted change from baseline in the largest tumor diameter. Results: Sixty patients entered EE at month 6; 61% (33/54 with data) exhibited normal mean urinary free cortisol (mUFC). At months 9 and 12, respectively, 55% (27/49) and 41% (18/44) of patients with data had normal mUFC. Mean fasting glucose, total and LDL-cholesterol, body weight, BMI, abdominal girth, hirsutism, CushingQoL, and Beck Depression Inventory-II scores improved from the study baseline at months 9 and 12. Forty-six patients completed month 12; four (6.7%) discontinued during EE due to adverse events. The most common adverse events in EE were arthralgia, headache, hypokalemia, and QT prolongation (6.7% each). No patient experienced alanine aminotransferase or aspartate aminotransferase >3× upper limit of normal, Fridericia-corrected QT interval >460 ms, or adrenal insufficiency during EE. Of 31 patients with tumor measurements at baseline and month 12 or follow-up, the largest tumor diameter was stable in 27 (87%) patients, decreased in one, and increased in three (largest increase 4 mm). Conclusion: In the first long-term levoketoconazole study, continued treatment through a 12-month maintenance period sustained the early clinical and biochemical benefits in most patients completing EE, without new adverse effects.
CRIS-Team Scopus Importer:2022-12-16

Listen to yourself: The medial prefrontal cortex modulates auditory alpha power during speech preparation - Müller-Voggel, Nadia; Leske, Sabine; Hartmann, Thomas; Szebenyi, Szabolcs; Weisz, Nathan (Cerebral Cortex, 2015)
How do we process stimuli that stem from the external world and stimuli that are self-generated? In the case of voice perception it has been shown that evoked activity elicited by self-generated sounds is suppressed compared with the same sounds played-back externally. We here wanted to reveal whether neural excitability of the auditory cortex-putatively reflected in local alpha band power-is modulated already prior to speech onset, and which brain regions may mediate such a top-down preparatory response. In the left auditory cortex we show that the typical alpha suppression found when participants prepare to listen disappears when participants expect a selfspoken sound. This suggests an inhibitory adjustment of auditory cortical activity already before sound onset. As a second main finding we demonstrate that the medial prefrontal cortex, a region known for selfreferential processes, mediates these condition-specific alpha power modulations. This provides crucial insights into how higher-order regions prepare the auditory cortex for the processing of self-generated sounds. Furthermore, the mechanism outlined could provide further explanations to self-referential phenomena, such as "tickling yourself". Finally, it has implications for the so-far unsolved question of how auditory alpha power is mediated by higher-order regions in a more general sense.
Created from Fastlane, Scopus look-up
Keywords: Effective connectivity; Efference copy; MEG; Oscillation; Top-down

Localization of beta power decrease as measure for lateralization in pre-surgical language mapping with magnetoencephalography, compared with functional magnetic resonance imaging and validated by Wada test - Herfurth, Kirsten; Harpaz, Yuval; Rösch, Julie; Müller, Nadia; Walther, Katrin; Kaltenhaeuser, Martin; Pauli, Elisabeth; Goldstein, Abraham; Hamer, Hajo; Buchfelder, Michael; Dörfler, Arnd; Prell, Julian; et al. (Frontiers in Human Neuroscience, 2022)
Objective: Atypical patterns of language lateralization due to early reorganizational processes constitute a challenge in the pre-surgical evaluation of patients with pharmaco-resistant epilepsy. There is no consensus on an optimal analysis method used for the identification of language dominance in MEG. This study examines the concordance between MEG source localization of beta power desynchronization and fMRI with regard to lateralization and localization of expressive and receptive language areas using a visual verb generation task. Methods: Twenty-five patients with pharmaco-resistant epilepsy, including six patients with atypical language lateralization, and ten right-handed controls obtained MEG and fMRI language assessment. Fourteen patients additionally underwent the Wada test. We analyzed MEG beta power desynchronization in sensor (controls) and source space (patients and controls). Beta power decrease between 13 and 35 Hz was localized applying Dynamic Imaging of Coherent Sources Beamformer technique. Statistical inferences were grounded on cluster-based permutation testing for single subjects. Results: Event-related desynchronization of beta power in MEG was seen within the language-dominant frontal and temporal lobe and within the premotor cortex. Our analysis pipeline consistently yielded left language dominance with high laterality indices in controls. Language lateralization in MEG and Wada test agreed in all 14 patients for inferior frontal, temporal and parietal language areas (Cohen’s Kappa = 1, p < 0.001). fMRI agreed with Wada test in 12 out of 14 cases (85.7%) for Broca’s area (Cohen’s Kappa = 0.71, p = 0.024), while the agreement for temporal and temporo-parietal language areas were non-significant. Concordance between MEG and fMRI laterality indices was highest within the inferior frontal gyrus, with an agreement in 19/24 cases (79.2%), and non-significant for Wernicke’s area. Spatial agreement between fMRI and MEG varied considerably between subjects and brain regions with the lowest Euclidean distances within the inferior frontal region of interest. Conclusion: Localizing the desynchronization of MEG beta power using a verb generation task is a promising tool for the identification of language dominance in the pre-surgical evaluation of epilepsy patients. The overall agreement between MEG and fMRI was lower than expected and might be attributed to differences within the baseline condition. A larger sample size and an adjustment of the experimental designs are needed to draw further conclusions.
CRIS-Team Scopus Importer:2022-11-25
Keywords: beta power decrease; epilepsy; epilepsy surgery; functional magnetic resonance imaging (fMRI); intracarotid sodium amobarbital procedure (IAT); language lateralization; magnetoencephalography (MEG); Wada test

Long-Term Clinical and Radiologic Outcome Following Surgical Treatment of Lumbar Spondylodiscitis: A Retrospective Bicenter Study - Sommer, Björn; Babbe-Pekol, Timo; Feulner, Julian; Richter, Richard Heinrich; Buchfelder, Michael; Shiban, Ehab; Sesselmann, Stefan; Forst, Raimund; Wiendieck, Kurt (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background and Study Aims Spinal instrumentation for spondylodiskitis (SD) remains highly controversial. To date, surgical data are limited to relatively small case series with short-term follow-up data. In this study, we wanted to elucidate the biomechanical, surgical, and neurologic long-term outcomes in these patients. Material and Methods A retrospective analysis from two German primary care hospitals over a 9-year period (2005-2014) was performed. The inclusion criteria were (1) pyogenic lumbar SD, (2) minimum follow-up of 1 year, and (3) surgical instrumentation. The clinical and radiologic outcome was assessed before surgery, at discharge, and at a minimum of 12 months of follow-up. Follow-up included physical examination, laboratory results, CT and MRI scans, as well as assessment of quality of life (QoL) using short-form health survey (SF-36) inventory, Oswestry Disability Questionnaire, and visual analog scale (VAS) spine score. Results Complete data were available in 70 patients (49 males and 21 females, with an age range of 67±12.3 years) with a median follow-up of 6.6 ± 4.2 years. Follow-up data were available in 70 patients after 1 year, in 58 patients after 2 years, and in 44 patients after 6 years. Thirty-five patients underwent posterior stabilization and decompression alone and 35 patients were operated on in a two-stage 360-degree interbody fusion with decompression. Pre- and postoperative angles of the affected motion segment were 17.6 ± 10.2 and 16.1 ± 10.7 degrees in patients with posterior instrumentation only and 21.0 ± 10.2 and 18.3 ± 10.5 degrees in patients with combined anterior/posterior fusion. Vertebral body subsidence was seen in 12 and 6 cases following posterior instrumentation and 360-degree instrumentation, respectively. Nonfusion was encountered in 22 and 11 cases following posterior instrumentation and 360-degree instrumentation, respectively. The length of hospital stay was 35.0 ± 24.5 days. Surgery-associated complication rate was 18% (12/70). New neurologic symptoms occurred in 7% (5/70). Revision surgery was performed in 3% (2/70) due to screw misplacement/hardware failure and in 3% (2/70) due to intraspinal hematoma. Although patients reported a highly impaired pain deception and vitality, physical mobility was unaffected and pain disability during daily activities was moderate. Conclusion Surgical treatment of SD with a staged surgical approach (if needed) is safe and provides very good long-term clinical and radiologic outcome.
CRIS-Team Scopus Importer:2022-07-22
Keywords: biomechanics; diagnostics; functional outcome; quality of life; risk factor; spinal infection; surgical approach; vertebral pyogenic osteomyelitis

Long-Term Complications and Influence on Outcome in Patients Surviving Spontaneous Subarachnoid Hemorrhage - Gerner, Stefan; Reichl, Jonathan; Custal, Christina; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Hölter, Philip; Kallmünzer, Bernd; Huttner, Hagen (Cerebrovascular Diseases, 2020)
BACKGROUND: While the short-term clinical outcome of patients with subarachnoid hemorrhage (SAH) is well described, there are limited data on long-term complications and their impact on social reintegration. This study aimed to assess the frequency of complications post-SAH and to investigate whether these complications attribute to functional and self-reported outcomes as well as the ability to return to work in these patients. METHODS: This retrospective single-center study included patients with atraumatic SAH over a 5-year period at a tertiary care center. Patients received a clinical follow-up for 12 months. In addition to demographics, imaging data, and parameters of acute treatment, the rate and extent of long-term complications after SAH were recorded. The functional outcome was assessed using the modified Rankin Scale (mRS; favorable outcome defined as mRS = 0-2). Further outcomes comprised self-reported subjective health measured by the EQ-5D and return to work for SAH patients with appropriate age. Multivariable analyses including in-hospital parameters and long-term complications were conducted to identify parameters independently associated with outcomes in SAH survivors. RESULTS: This study cohort consisted of 505 SAH patients of whom 405 survived the follow-up period of 12 months (i.e., mortality rate of 19.8%). Outcome data were available in 359/405 (88.6%) patients surviving SAH. At 12 months, a favorable functional outcome was achieved in 287/359 (79.9%) and 145/251 (57.8%) SAH patients returned to work. The rates of post-acute complications were headache (32.3%), chronic hydrocephalus requiring permanent ventriculoperitoneal shunting (VP shunt 25.4%) and epileptic seizures (9.5%). Despite patient's and clinical characteristics, both presence of epilepsy and need for VP shunt were independently and negatively associated with a favorable functional outcome (epilepsy: adjusted odds ratio [aOR] (95% confidence interval [95% CI]): 0.125 [0.050-0.315]; VP shunt: 0.279 [0.132-0.588]; both p < 0.001) as well as with return to work (aOR [95% CI]: epilepsy 0.195 [0.065-0.584], p = 0.003; VP shunt 0.412 [0.188-0.903], p = 0.027). Multivariable analyses revealed presence of headache, VP shunt, or epilepsy to be significantly related to subjective health impairment (aOR [95% CI]: headache 0.248 [0.143-0.430]; epilepsy 0.223 [0.085-0.585]; VP shunt 0.434 [0.231-0.816]; all p < 0.01). CONCLUSIONS: Long-term complications occur frequently after SAH and are associated with an impairment of functional and social outcomes. Further studies are warranted to investigate if treatment strategies specifically targeting these complications, including preventive aspects, may improve the outcomes after SAH.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Long-term complications; Post-stroke outcomes; Social participation; Subarachnoid hemorrhage

Long-term efficacy and safety of pegvisomant in combination with long-acting somatostatin analogs in acromegaly - Neggers, S. J. C. M. M.; Franck, S. E.; De Rooij, F. W. M.; Dallenga, A. H. G.; Poublon, R. M. L.; Feelders, R. A.; Janssen, J. A. M. J. L.; Buchfelder, Michael; Hofland, L. J.; Jorgensen, J. O. L.; Van Der Lely, A. J. (Journal of Clinical Endocrinology and Metabolism, 2014)
Treatment for acromegaly patients with long-acting somatotropin release-inhibiting factor (LA-SRIF) often does not result in complete normalization of IGF-1. Addition of pegvisomant (PEGV), a GH receptor antagonist, could improve this; however, the literature has not described long-term follow-up.To assess long-term efficacy and safety of this combined treatment in the largest current single-center cohort of patients, from 2004-2013.Acromegaly patients were treated for at least 6 months with a high-dose LA-SRIF. To patients with persistently elevated IGF-1 levels (>1.2 × upper limit of normal) or poor quality of life, PEGV was added as one weekly injection.The patients (n = 141) were treated with PEGV and LA-SRIFs for a median period of 4.9 years (range, 0.5-9.2). Efficacy, defined as the lowest measured IGF-1 level during treatment, was 97.0%. The median PEGV dose to achieve this efficacy was 80 mg weekly (interquartile range, 60-120 mg). Combination treatment-related adverse events were recorded in 26 subjects (18.4%). Pituitary tumor size increase was observed in one patient. Injection-site reactions were observed in four subjects. In 19 patients (13.5%), transiently elevated liver transaminases of more than three times the upper limit of normal were observed, of which 83% occurred within the first year of combination treatment. Eight patients died, at a mean age of 71 years; none of them were considered treatment-related.The combination treatment with LA-SRIFs and PEGV was effective in 97% of the patients, it appears to be a safe medical treatment and it reduces the required dose of PEGV.
EVALuna2:22834

Longterm Increased S100B Enhances Hippocampal Progenitor Cell Proliferation in a Transgenic Mouse Model - Rodrigues, Leticia; Wartchow, Krista Mineia; Buchfelder, Michael; Souza, Diogo Onofre; Goncalves, Carlos-Alberto; Kleindienst, Andrea (International Journal of Molecular Sciences, 2022)
(1) The neurotrophic protein S100B is a marker of brain injury and has been associated with neuroregeneration. In S100Btg mice rendering 12 copies of the murine S100B gene we evaluated whether S100B may serve as a treatment option. (2) In juvenile, adult, and one-year-old S100Btg mice (female and male; n = 8 per group), progenitor cell proliferation was quantified in the subgranular zone (SGZ) and the granular cell layer (GCL) of the dentate gyrus with the proliferative marker Ki67 and BrdU (50 mg/kg). Concomitant signaling was quantified utilizing glial fibrillary acidic protein (GFAP), apolipoprotein E (ApoE), brain-derived neurotrophic factor (BDNF), and the receptor for advanced glycation end products (RAGE) immunohistochemistry. (3) Progenitor cell proliferation in the SGZ and migration to the GCL was enhanced. Hippocampal GFAP was reduced in one-year-old S100Btg mice. ApoE in the hippocampus and frontal cortex of male and BDNF in the frontal cortex of female S100Btg mice was reduced. RAGE was not affected. (4) Enhanced hippocampal neurogenesis in S100Btg mice was not accompanied by reactive astrogliosis. Sex- and brain region-specific variations of ApoE and BDNF require further elucidations. Our data reinforce the importance of this S100Btg model in evaluating the role of S100B in neuroregenerative medicine.
CRIS-Team WoS Importer:2022-09-16

Long-term outcome after epilepsy surgery in older adults - Lang, Johannes D.; Grell, Laura; Hagge, Mareike; Onugoren, Muejgan Dogan; Gollwitzer, Stephanie; Graf, Wolfgang; Schwarz, Michael; Coras, Roland; Blümcke, Ingmar; Sommer, Bjoern; Roessler, Karl; Buchfelder, Michael; et al. (Seizure-European Journal of Epilepsy, 2018)
PURPOSE: The incidence of epilepsy in older adults is growing, as does the incidence of comorbidities. Therefore, when it comes to epilepsy surgery in medically intractable epilepsy, age is often seen as a limiting factor. To investigate the outcome after epilepsy surgery in a population of older adults, we compared the benefit for patients aged 50-59 years with those aged 60 years and older in respect of efficacy and safety. METHOD: Patients aged ≥50 years with medically intractable epilepsy who underwent epilepsy surgery from 1990 to 2013 were selected from the database of a German epilepsy center. All of them received a standardised and detailed presurgical diagnostic evaluation. Follow-up included at least four scheduled visits with EEG, MRI and neuropsychological testing. Outcome was assessed using the Engel outcome scale. RESULTS: 79 patients aged between 50 and 67 years were followed-up for a median of 4.7 years (2-16 years). 68% of patients were free of disabling seizures (Engel class I, ≥60 years: 75%) and 58% were seizure-free (Engel class IA, ≥60 years: 70%). 90% of our patients suffered from temporal lobe epilepsy (TLE), 9% from frontal lobe epilepsy (FLE) and one occipital lobe epilepsy (OLE). After surgery, 9% discontinued or tapered their medication. Permanent surgical complications occurred in 10% of cases and transient neurological deficits were seen in 11%. Older patients had a higher risk for postoperative hygroma (≥60 years 15%; <60 years 8%) and were more prone to postoperative memory deficits (≥60 years 45%), especially after resection of the dominant temporal lobe. Verbal and figural memory testing did not differ significantly between the groups. CONCLUSIONS: The results support the view that in selected older patients, epilepsy surgery shows equal or even higher success rates as compared to younger patients. However, patients of older age may be at greater risk for postoperative hygroma and memory deficits, especially after dominant temporal lobe resections.
EVALuna2:34593

Long-term remission and recurrence rates after first and second transsphenoidal surgery for Cushing's disease: care reality in the Munich Metropolitan Region - Dimopoulou, C.; Schopohl, J.; Rachinger, W.; Buchfelder, Michael; Honegger, J.; Reincke, M.; Stalla, G. K. (European Journal of Endocrinology, 2014)
Transsphenoidal surgery (TSS) presents the treatment of choice for Cushing's disease (CD). Remission and recurrence rates vary dependent on tumor size, extension, adenoma visibility on magnetic resonance imaging, and neurosurgical expertise. Other than published from single-surgeon neurosurgical series so far, we have aimed to describe long-term remission and recurrence rates of CD in a series incorporating different neurosurgeons, trying to reflect care reality in the Munich Metropolitan Region, which is accommodated by three tertiary university and multiple, smaller neurosurgical centers.We conducted a retrospective analysis of 120 patients who underwent first and 36 patients who underwent second TSS as treatment for CD between 1990 and 2012.Patients were divided into three groups according to remission status. Potential risk factors for recurrence, pituitary function, and strategy in persistent disease were assessed.THREE OUTCOME GROUPS WERE IDENTIFIED ACCORDING TO REMISSION STATUS AFTER FIRST TSS (MEAN FOLLOW-UP 79 MONTHS): remission, 71% (85/120), disease persistence, 29% (35/120), and disease recurrence, 34% (29/85) (mean time to recurrence 54 months). After second TSS (n=36, mean follow-up 62 months), we documented remission in 42% (15/36), disease persistence in 58% (21/36), and disease recurrence in 40% (6/15) (mean time to recurrence 42 months). Postoperative hypocortisolism after first, though not after second, TSS was associated with a lower risk of suffering disease recurrence (risk=0.72; 95% CI 0.60-0.88; exact significance (two-sided) P=0.035).Our study shows higher recurrence rates of CD after first TSS than previously reported. Second TSS leads an additional 8% of the patients to long-term CD remission.
EVALuna2:22835

Long-term treatment with pegvisomant: observations from 2090 acromegaly patients in ACROSTUDY - Buchfelder, Michael; Van Der Lely, Aart-Jan; Biller, Beverly M. K.; Webb, Susan M.; Brue, Thierry; Strasburger, Christian J.; Ghigo, Ezio; Camacho-Hubners, Cecilia; Pang, Kaijie; Lavenbergt, Joanne; Jonsson, Peter; Hey-Hadavi, Juliana H. (European Journal of Endocrinology, 2018)
Objectives ACROSTUDY is an international, non-interventional study of acromegaly patients treated with pegvisomant (PEGV), a growth hormone receptor antagonist and has been conducted since 2004 in 15 countries to study the long-term safety and efficacy of PEGV. This report comprises the second interim analysis of 2090 patients as of May 12, 2016. Methods Descriptive analyses of safety, pituitary imaging and outcomes on PEGV treatment up to 12 years were performed. Results Prior to starting PEGV, 96% of patients had reported surgery, radiation, medical therapy or any combinations of those. At start of PEGV, 89% of patients had IGFI levels above the upper limit of normal (ULN). The percentage of patients with normal IGFI levels increased from 53% at year 1 to 73% at year 10, and the average daily dose of PEGV increased from 12.8 mg (year 1) to 18.9 mg (year 10). A total of 4832 adverse events (AEs) were reported in 1137 patients (54.4%), of which 570 were considered treatment related in 337 patients (16.1%). Serious AEs were reported in 22% of patients, of which 2.3% were considered treatment related. Locally reported MRIs showed most patients (72.2%) had no change in tumor size relative to the prior scan; 16.8% had a decrease, 6.8% an increase and 4.3% both. In patients with normal liver tests at PEGV start, an ALT or AST elevation of >3× ULN at any time point during their follow-up was reported in 3%. Conclusions This second interim analysis confirms that long-term use of PEGV is an effective and safe treatment in patients with acromegaly.
EVALuna2:214798

Low proliferation and differentiation capacities of adult hippocampal stem cells correlate with memory dysfunction in humans - Coras, Roland; Siebzehnrübl, Florian; Pauli, Elisabeth; Huttner, Hagen; Njunting, Marleisje; Kobow, Katja; Villmann, Carmen; Hahnen, Eric; Neuhuber, Winfried; Weigel, Daniel; Buchfelder, Michael; Stefan, Herrmann; et al. (Brain, 2010)
The hippocampal dentate gyrus maintains its capacity to generate new neurons throughout life. In animal models, hippocampal neurogenesis is increased by cognitive tasks, and experimental ablation of neurogenesis disrupts specific modalities of learning and memory. In humans, the impact of neurogenesis on cognition remains unclear. Here, we assessed the neurogenic potential in the human hippocampal dentate gyrus by isolating adult human neural stem cells from 23 surgical en bloc hippocampus resections. After proliferation of the progenitor cell pool in vitro we identified two distinct patterns. Adult human neural stem cells with a high proliferation capacity were obtained in 11 patients. Most of the cells in the high proliferation capacity cultures were capable of neuronal differentiation (53 +/- 13% of in vitro cell population). A low proliferation capacity was observed in 12 specimens, and only few cells differentiated into neurons (4 +/- 2%). This was reflected by reduced numbers of proliferating cells in vivo as well as granule cells immunoreactive for doublecortin, brain-derived neurotrophic factor and cyclin-dependent kinase 5 in the low proliferation capacity group. High and low proliferation capacity groups differed dramatically in declarative memory tasks. Patients with high proliferation capacity stem cells had a normal memory performance prior to epilepsy surgery, while patients with low proliferation capacity stem cells showed severe learning and memory impairment. Histopathological examination revealed a highly significant correlation between granule cell loss in the dentate gyrus and the same patient's regenerative capacity in vitro (r = 0.813; P < 0.001; linear regression: R-adjusted(2) = 0.635), as well as the same patient's ability to store and recall new memories (r = 0.966; P = 0.001; linear regression: R-adjusted(2) = 0.9). Our results suggest that encoding new memories is related to the regenerative capacity of the hippocampus in the human brain.
Keywords: stem cells; neurogenesis; hippocampus; memory; learning; epilepsy; doublecortin

Lung cancer presenting with central nervous system metastasis: Clinicopathological and molecular analysis of 171 cases - Demleitner, Madeleine; Erlenbach-Wünsch, Katharina; Coras, Roland; Erber, Ramona; Polifka, Iris; Eyüpoglu, Ilker Yasin; Fuchs, Florian; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2023)
A subset of lung carcinoma presents initially with brain metastasis. Precise subtyping is mandatory for optimized treatment of these advanced aggressive carcinomas. We herein analyzed surgical biopsies from 171 Patients (99 males and 72 females aged 48–96; mean, 72), who presented with brain metastasis of lung cancer. In addition to conventional subtyping, we applied an extended immunohistochemistry (IHC) panel and performed several molecular tests looking for potential therapeutic targets other than EGFR mutations. Non-small cell carcinoma (NSCLC) comprised 157 (91.8 %) of cases: 109 (63.7 %) adenocarcinomas, 27 (15.8 %) squamous cell (SCC), 18 (10.5 %) large cell undifferentiated, 1 (0.6 %) adenosquamous and 2 (1.2 %) unclassified carcinomas. Of the adenocarcinomas, 81.7 % were TTF1+. Notably, 45 % of those TTF1-negative cases expressed HepPar1. SMARCA4 and SMARCA2 loss was observed in 13/171 (7.6 %) and 32/163 (19.6 %) cases, respectively; mainly TTF1- (40.0 %) and HepPar1+ (38.1 %) adenocarcinomas were affected by SMARCA2/4 loss. Loss of at least one mismatch repair (MMR) protein was observed in 3/156 (1.9 %) cases (2 adenocarcinomas and 1 large cell neuroendocrine carcinoma/LCNEC). Limited available data on mutation testing showed a frequency of EGFR mutations of 4.3% and of KRAS mutations of 57%. HER2 expression (2+/3+) was found in 45/166 (27.1 %) of cases with amplification verified by CISH in 18/38 (47.4 % of immunopositive cases and 10.5 % of the whole cohort); all but one were adenocarcinomas. Other genetic abnormalities detected included EML4::ALK rearrangements in 3 (1.8 %; 2 TTF1+ adenocarcinomas and 1 LCNEC) and RET rearrangements in one SCNEC. Variable subsets of tumors revealed amplifications of several potentially therapeutically targetable genes including MYC (30.0 %), MET (10.1 %), HER2 (10 %), FGFR1 (9.6 %), FGFR3 (4.6 %), and FGFR2 (3.4 %). This study highlights a highly heterogeneous molecular background in lung cancer presenting with CNS metastases. These findings highlight the need for individualized tumor testing strategies looking for potential therapeutic targets for this aggressive disease.
CRIS-Team Scopus Importer:2023-01-27
Keywords: ALK; Central nervous system metastasis; Immune therapy; Microsatellite instability; NSCLC; SMARCA4

Machine Learning-Based Prediction of Glioma IDH Gene Mutation Status Using Physio-Metabolic MRI of Oxygen Metabolism and Neovascularization (A Bicenter Study) - Stadlbauer, Andreas; Nikolic, Katarina; Oberndorfer, Stefan; Marhold, Franz; Kinfe, Thomas Mehari; Meyer-Bäse, Anke; Bistrian, Diana Alina; Schnell, Oliver; Dörfler, Arnd (Cancers, 2024)
The mutational status of the isocitrate dehydrogenase (IDH) gene plays a key role in the treatment of glioma patients because it is known to affect energy metabolism pathways relevant to glioma. Physio-metabolic magnetic resonance imaging (MRI) enables the non-invasive analysis of oxygen metabolism and tissue hypoxia as well as associated neovascularization and microvascular architecture. However, evaluating such complex neuroimaging data requires computational support. Traditional machine learning algorithms and simple deep learning models were trained with radiomic features from clinical MRI (cMRI) or physio-metabolic MRI data. A total of 215 patients (first center: 166 participants + 16 participants for independent internal testing of the algorithms versus second site: 33 participants for independent external testing) were enrolled using two different physio-metabolic MRI protocols. The algorithms trained with physio-metabolic data demonstrated the best classification performance in independent internal testing: precision, 91.7%; accuracy, 87.5%; area under the receiver operating curve (AUROC), 0.979. In external testing, traditional machine learning models trained with cMRI data exhibited the best IDH classification results: precision, 84.9%; accuracy, 81.8%; and AUROC, 0.879. The poor performance for the physio-metabolic MRI approach appears to be explainable by site-dependent differences in data acquisition methodologies. The physio-metabolic MRI approach potentially supports reliable classification of IDH gene status in the presurgical stage of glioma patients. However, non-standardized protocols limit the level of evidence and underlie the need for a reproducible framework of data acquisition techniques.
CRIS-Team Scopus Importer:2024-04-05
Keywords: artificial intelligence; deep learning; glioma; IDH gene mutation; isocitrate dehydrogenase gene; machine learning; neurooncology; physio-metabolic MRI; preoperative classification

Magnetic resonance imaging biomarkers for clinical routine assessment of microvascular architecture in glioma - Stadlbauer, Andreas; Zimmermann, Max; Heinz, Gertraud; Oberndorfer, Stefan; Dörfler, Arnd; Buchfelder, Michael; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2017)
Knowledge about the topological and structural heterogeneity of the microvasculature is important for diagnosis and monitoring of glioma. A vessel caliber and type-dependent temporal shift in the magnetic resonance imaging signal forms the basis for vascular architecture mapping. This study introduced a clinically feasible approach for assessment of vascular pathologies in gliomas using vascular architecture mapping. Sixty consecutive patients with known or suspected gliomas were examined using vascular architecture mapping as part of the routine magnetic resonance imaging protocol. Maps of microvessel radius and density, which adapted to the vasculature-dependent temporal shift phenomenon, were calculated using a costume-made software tool. Microvessel radius and density were moderately to severely elevated in a heterogeneous, inversely correlated pattern within high-grade gliomas. Additionally, three new imaging biomarkers were introduced: Microvessel type indicator allowing differentiation between supplying arterial and draining venous microvasculature in high-grade gliomas. Vascular-induced bolus peak time shift may presumably be sensitive for early neovascularization in the infiltration zone. Surprisingly, curvature showed significant changes in peritumoral vasogenic edema which correlated with neovascularization in the tumor core of high-grade gliomas. These new magnetic resonance imaging biomarkers give insights into complexity and heterogeneity of vascular changes in glioma; however, histological validations in more well-defined patient populations are required.
EVALuna2:33149

Magnetoencephalography for epileptic focus localization in a series of 1000 cases. - Rampp, Stefan; Stefan, Hermann; Wu, Xintong; Kaltenhäuser, Martin; Maess, Burkhard; Schmitt, Friedhelm C.; Wolters, Carsten H.; Hamer, Hajo; Kasper, Burkhard S.; Schwab, Stefan; Blümcke, Ingmar; Rössler, Karl; et al. (Brain, 2019)
The aim of epilepsy surgery in patients with focal, pharmacoresistant epilepsies is to remove the complete epileptogenic zone to achieve long-term seizure freedom. In addition to a spectrum of diagnostic methods, magnetoencephalography focus localization is used for planning of epilepsy surgery. We present results from a retrospective observational cohort study of 1000 patients, evaluated using magnetoencephalography at the University Hospital Erlangen over the time span of 28 years. One thousand consecutive cases were included in the study, evaluated at the University Hospital Erlangen between 1990 and 2018. All patients underwent magnetoencephalography as part of clinical workup for epilepsy surgery. Of these, 405 underwent epilepsy surgery after magnetoencephalography, with postsurgical follow-ups of up to 20 years. Sensitivity for interictal epileptic activity was evaluated, in addition to concordance of localization with the consensus of presurgical workup on a lobar level. We evaluate magnetoencephalography characteristics of patients who underwent epilepsy surgery versus patients who did not proceed to surgery. In operated patients, resection of magnetoencephalography localizations were related to postsurgical seizure outcomes, including long-term results after several years. In comparison, association of lesionectomy with seizure outcomes was analysed. Measures of diagnostic accuracy were calculated for magnetoencephalography resection and lesionectomy. Sensitivity for interictal epileptic activity was 72% with significant differences between temporal and extra-temporal lobe epilepsy. Magnetoencephalography was concordant with the presurgical consensus in 51% and showed additional or more focal involvement in an additional 32%. Patients who proceeded to surgery showed a significantly higher percentage of monofocal magnetoencephalography results. Complete magnetoencephalography resection was associated with significantly higher chances to achieve seizure freedom in the short and long-term. Diagnostic accuracy was significant in temporal and extra-temporal lobe cases, but was significantly higher in extra-temporal lobe epilepsy (diagnostic odds ratios of 4.4 and 41.6). Odds ratios were also higher in non-lesional versus lesional cases (42.0 versus 6.2). The results show that magnetoencephalography provides non-redundant information, which significantly contributes to patient selection, focus localization and ultimately long-term seizure freedom after epilepsy surgery. Specifically in extra-temporal lobe epilepsy and non-lesional cases, magnetoencephalography provides excellent accuracy.
EVALuna2:204465

Magnetoencephalography for epileptic focus localization in a series of 1000 cases - Rampp, Stefan; Stefan, Hermann; Wu, Xueqing; Kaltenhäuser, Martin; Maess, Burkhard; Schmitt, Friedhelm C.; Wolters, Carsten H.; Hamer, Hajo; Kasper, Burkhard; Schwab, Stefan; Dörfler, Arnd; Blümcke, Ingmar; et al. (Brain, 2019)
The aim of epilepsy surgery in patients with focal, pharmacoresistant epilepsies is to remove the complete epileptogenic zone to achieve long-term seizure freedom. In addition to a spectrum of diagnostic methods, magnetoencephalography focus localization is used for planning of epilepsy surgery. We present results from a retrospective observational cohort study of 1000 patients, evaluated using magnetoencephalography at the University Hospital Erlangen over the time span of 28 years. One thousand consecutive cases were included in the study, evaluated at the University Hospital Erlangen between 1990 and 2018. All patients underwent magnetoencephalography as part of clinical workup for epilepsy surgery. Of these, 405 underwent epilepsy surgery after magnetoencephalography, with postsurgical follow-ups of up to 20 years. Sensitivity for interictal epileptic activity was evaluated, in addition to concordance of localization with the consensus of presurgical workup on a lobar level. We evaluate magnetoencephalography characteristics of patients who underwent epilepsy surgery versus patients who did not proceed to surgery. In operated patients, resection of magnetoencephalography localizations were related to postsurgical seizure outcomes, including long-term results after several years. In comparison, association of lesionectomy with seizure outcomes was analysed. Measures of diagnostic accuracy were calculated for magnetoencephalography resection and lesionectomy. Sensitivity for interictal epileptic activity was 72% with significant differences between temporal and extra-temporal lobe epilepsy. Magnetoencephalography was concordant with the presurgical consensus in 51% and showed additional or more focal involvement in an additional 32%. Patients who proceeded to surgery showed a significantly higher percentage of monofocal magnetoencephalography results. Complete magnetoencephalography resection was associated with significantly higher chances to achieve seizure freedom in the short and long-term. Diagnostic accuracy was significant in temporal and extra-temporal lobe cases, but was significantly higher in extra-temporal lobe epilepsy (diagnostic odds ratios of 4.4 and 41.6). Odds ratios were also higher in non-lesional versus lesional cases (42.0 versus 6.2). The results show that magnetoencephalography provides non-redundant information, which significantly contributes to patient selection, focus localization and ultimately long-term seizure freedom after epilepsy surgery. Specifically in extra-temporal lobe epilepsy and non-lesional cases, magnetoencephalography provides excellent accuracy.
CRIS-Team Scopus Importer:2019-10-08
Keywords: epilepsy; epilepsy surgery; long-term outcome; magnetic source imaging; magnetoencephalography

Magnetoencephalography-guided surgery in frontal lobe epilepsy using neuronavigation and intraoperative MR imaging - Sommer, Bjoern; Roessler, Karl; Rampp, Stefan; Hamer, Hajo; Blümcke, Ingmar; Stefan, Hermann; Buchfelder, Michael (Epilepsy Research, 2016)
Especially in hidden lesions causing drug-resistant frontal lobe epilepsy (FLE), the localization of the epileptic zone EZ can be a challenge. Magnetoencephalography (MEG) can raise the chances for localization of the (EZ) in combination with electroencephalography (EEG). We investigated the impact of MEG-guided epilepsy surgery with the aid of neuronavigation and intraoperative MR imaging (iopMRI) on seizure outcome of FLE patients.Twenty-eight patients (15 females, 13 males; mean age 31.0±11.1 years) underwent surgery in our department. All patients underwent presurgical MEG monitoring (two-sensor Magnes II or whole head WH3600 MEG system; 4-D Neuroimaging, San Diego, CA, USA). Of those, six patients (group 1) with MRI-negative FLE were operated on before 2002 with intraoperative electrocorticography (ECoG) and invasive EEG mapping only. Eleven patients with MRI-negative FLE (group 2) and eleven with lesional FLE (group 3) underwent surgery using 1.5T-iopMRI and neuronavigation, including intraoperative visualization of the MEG localizations in 22 and functional MR imaging (for motor and speech areas) as well as DTI fiber tracking (for language and pyramidal tracts) in 13 patients.In the first group, complete resection of the defined EZ including the MEG localization according to the latest postoperative MRI was achieved in four out of six patients. Groups two and three had complete removal of the MEG localizations in 20/22 (91%, 10 of 11 each). Intraoperative MRI revealed incomplete resection of the MEG localizations of four patients (12%; two in both groups), leading to successful re-resection. Transient and permanent neurological deficits alike occurred in 7.1%, surgery-associated complications in 11% of all patients. In the first group, excellent seizure outcome (Engel Class IA) was achieved in three (50%), in the second in 7 patients (61%) and third group in 8 patients (64%, two iopMRI-based re-resections). Mean follow-up was 70.3 months (from 12 to 284 months).In our series, MEG-guided resection using neuronavigation and iopMR imaging led to promising seizure control rates. Even in non-lesional FLE, seizure control rates and the probability of complete resection of the MEG localizations was similar to lesional FLE using multimodal navigation.
EVALuna2:7339

Mapping myeloid cell function: Spatial diversity in tumor and neuronal microenvironment - Villa, Giulia; Delev, Daniel; Heiland, Dieter Henrik (Cancer Cell, 2024)
In this issue of Cancer Cell, Zhong et al. explore the dual role of TREM2 in glioblastoma-associated myeloid cells, demonstrating its function in promoting inflammation at the tumor-neural interface and suppression within the tumor core, influenced by the local microenvironment. These findings open up promising prospects for advancements in neuro-oncological immunotherapy.
CRIS-Team Scopus Importer:2024-06-14

MCT4 Promotes Tumor Malignancy in F98 Glioma Cells - Reuß, Anna Maria; Groos, Dominik; Ghoochani, Ali; Buchfelder, Michael; Savaskan, Nicolai (Journal of Oncology, 2021)
Monocarboxylate transporter 4 (MCT4, SLC16A3) is elevated under hypoxic conditions in many malignant tumors including gliomas. Moreover, MCT4 expression is associated with shorter overall survival. However, the functional consequences of MCT4 expression on the distinct hallmarks of cancer have not yet been explored at the cellular level. Here, we investigated the impact of MCT4 overexpression on proliferation, survival, cell death, migration, invasion, and angiogenesis in F98 glioma cells. Stable F98 glioma cell lines with MCT4 overexpression, normal expression, and knockdown were generated. Distinct hallmarks of cancer were examined using in silico analysis, various in vitro cell culture assays, and ex vivo organotypic rat brain slice culture model. Consistent with its function as lactate and proton exporter, MCT4 expression levels correlated inversely with extracellular pH and proportionally with extracellular lactate concentrations. Our results further indicate that MCT4 promotes proliferation and survival by altered cell cycle regulation and cell death mechanisms. Moreover, MCT4 overexpression enhances cell migration and invasiveness via reorganization of the actin cytoskeleton. Finally, MCT4 inhibition mitigates the induction of angiogenesis, suggesting that MCT4 also plays a crucial role in tumor-related angiogenesis. In summary, our data highlight MCT4/SLC16A3 as a key gene for distinct hallmarks of tumor malignancy in glioma cells.
CRIS-Team Scopus Importer:2021-05-14

Mechanical stability of a novel screw design after repeated insertion: can the double-thread screw serve as a back up? - Wiendieck, Kurt; Mueller, Helge; Buchfelder, Michael; Sommer, Bjoern (Journal of Neurosurgical Sciences, 2018)
BACKGROUND: We investigated mechanical pull-out behavior and tightening torque of a novel dual-core pedicle "6T screw" (6T). The aim of this study was to test if these changes in screw geometry are increasing the strength of the pedicle screw fixation after repeated insertion. METHODS: Three different types of pedicle screws were inserted in rigid foam blocks. Tightening torque and pull-out strength were measured during two repetitive insertions of a standard 6.5×45-mm conical screw. The third insertion into the pilot hole was performed using either standard 6.5×45-mm or 7.2×45-mm conical screws or the novel 6.5×45-mm (6T) screw. Additionally, we performed a surface analysis to investigate the bone/screw interface. RESULTS: The maximal tightening torque at the third insertion of the novel 6T screw was 194% higher compared to the standard 6.5×45-mm conical screw and 135% higher compared to the standard 7.2×45-mm conical screw. The pull-out strength of the 6T screw showed no significant changes, and surface analysis revealed a compression of the screw-foam interface due to the different internal diameters. CONCLUSIONS: The modified geometrical design of the 6T screw seems to have no statistically significant effect on the pull-out strength, although it achieved a higher tightening torque. This might be due to the different pitch angle cutting a new thread into the material and also to the enlarged inner diameter.
EVALuna2:214802

Mechanism of necrotic Cell Clearance by non-professional Phagocytes - Hofmann, Andrea; Seeberg, J.; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36484

MEG in frontal epilepsy - Rampp, Stefan; Kasper, Burkhard; Brandner, Sebastian; Hamer, Hajo; Buchfelder, Michael (Zeitschrift für Epileptologie, 2022)
Magnetoencephalography (MEG) offers considerable advantages for presurgical localization diagnostics of frontal and generalized extratemporal epilepsy. A number of retrospective and prospective studies show a significant impact on the planning of invasive recordings and epilepsy surgical procedures with marked improvement of postoperative seizure control. This article provides a concise overview of the current state of the evidence.
CRIS-Team WoS Importer:2022-02-04

MEG in MRI-Negative Patients with Focal Epilepsy - Kreidenhuber, Rudolf; Poppert, Kai-Nicolas; Mauritz, Matthias; Hamer, Hajo; Delev, Daniel; Schnell, Oliver; Rampp, Stefan (Journal of Clinical Medicine, 2024)
Objectives: To review the evidence on the clinical value of magnetic source imaging (MSI) in patients with refractory focal epilepsy without evidence for an epileptogenic lesion on magnetic resonance imaging (“MRI-negative” or “non-lesional MRI”). Methods: We conducted a systematic literature search on PUBMED, which was extended by researchrabbit.ai using predefined criteria to identify studies that applied MSI in MRI-negative patients with epilepsy. We extracted data on patient characteristics, MSI methods, localization results, surgical outcomes, and correlation with other modalities. Results: We included 23 studies with a total of 512 non-lesional epilepsy patients who underwent MSI. Most studies used equivalent current dipole (ECD) models to estimate the sources of interictal epileptic discharges (IEDs). MEG detected IEDs in 32–100% of patients. MSI results were concordant with other modalities, such as EEG, PET, and SPECT, in 3892% of cases. If MSI concordant surgery was performed, 52–89% of patients achieved seizure freedom. MSI contributed to the decision-making process in 28–75% of cases and altered the surgical plan in 5–33% of cases. Conclusions: MSI is a valuable diagnostic tool for MRI-negative patients with epilepsy, as it can detect and localize IEDs with high accuracy and sensitivity, and provides useful information for surgical planning and predicts outcomes. MSI can also complement and refine the results of other modalities, such as EEG and PET, and optimize the use of invasive recordings. MSI should be considered as part of the presurgical evaluation, especially in patients with non-lesional refractory epileps
CRIS-Team Scopus Importer:2024-10-25
Keywords: magnetic source imaging; non-lesional; epilepsy; magnetoencephalography; negative MRI; normal MRI; refractory epilepsy; presurgical

MEG Node Degree Differences in Patients with Focal Epilepsy vs. Controls-Influence of Experimental Conditions - Vogel, Stephan; Kaltenhaeuser, Martin; Kim, Cora; Müller-Voggel, Nadia; Rössler, Karl; Dörfler, Arnd; Schwab, Stefan; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan (Brain Sciences, 2021)
Drug-resistant epilepsy can be most limiting for patients, and surgery represents a viable therapy option. With the growing research on the human connectome and the evidence of epilepsy being a network disorder, connectivity analysis may be able to contribute to our understanding of epilepsy and may be potentially developed into clinical applications. In this magnetoencephalographic study, we determined the whole-brain node degree of connectivity levels in patients and controls. Resting-state activity was measured at five frequency bands in 15 healthy controls and 15 patients with focal epilepsy of different etiologies. The whole-brain all-to-all imaginary part of coherence in source space was then calculated. Node degree was determined and parcellated and was used for further statistical evaluation. In comparison to controls, we found a significantly higher overall node degree in patients with lesional and non-lesional epilepsy. Furthermore, we examined the conditions of high/reduced vigilance and open/closed eyes in controls, to analyze whether patient node degree levels can be achieved. We evaluated intraclass-correlation statistics (ICC) to evaluate the reproducibility. Connectivity and specifically node degree analysis could present new tools for one of the most common neurological diseases, with potential applications in epilepsy diagnostics.
CRIS-Team WoS Importer:2022-01-07

MEG Node Degree for Focus Localization: Comparison with Invasive EEG - Rampp, Stefan; Kaltenhaeuser, Martin; Müller-Voggel, Nadia; Dörfler, Arnd; Kasper, Burkhard S.; Hamer, Hajo; Brandner, Sebastian; Buchfelder, Michael (Biomedicines, 2023)
Epilepsy surgery is a viable therapy option for patients with pharmacoresistant focal epilepsies. A prerequisite for postoperative seizure freedom is the localization of the epileptogenic zone, e.g., using electro- and magnetoencephalography (EEG/MEG). Evidence shows that resting state MEG contains subtle alterations, which may add information to the workup of epilepsy surgery. Here, we investigate node degree (ND), a graph-theoretical parameter of functional connectivity, in relation to the seizure onset zone (SOZ) determined by invasive EEG (iEEG) in a consecutive series of 50 adult patients. Resting state data were subjected to whole brain, all-to-all connectivity analysis using the imaginary part of coherence. Graphs were described using parcellated ND. SOZ localization was investigated on a lobar and sublobar level. On a lobar level, all frequency bands except alpha showed significantly higher maximal ND (mND) values inside the SOZ compared to outside (ratios 1.11-1.20, alpha 1.02). Area-under-the-curve (AUC) was 0.67-0.78 for all expected alpha (0.44, ns). On a sublobar level, mND inside the SOZ was higher for all frequency bands (1.13-1.38, AUC 0.58-0.78) except gamma (1.02). MEG ND is significantly related to SOZ in delta, theta and beta bands. ND may provide new localization tools for presurgical evaluation of epilepsy surgery.
CRIS-Team WoS Importer:2023-03-24
Keywords: MEG; epilepsy; epilepsy surgery; connectivity; graph theory; focus localization

Melatonin moderates the triangle of chronic pain, sleep architecture and immunometabolic traffic - Chaudhry, Shafqat R.; Stadlbauer, Andreas; Buchfelder, Michael; Kinfe, Thomas Mehari (Biomedicines, 2021)
Preclinical as well as human studies indicate that melatonin is essential for a physiological sleep state, promotes analgesia and is involved in immunometabolic signaling by regulating neuroin-flammatory pathways. Experimental and clinical neuromodulation studies for chronic pain treatment suggest that neurostimulation therapies such as spinal cord stimulation, vagus nerve stimulation and dorsal root ganglion stimulation have an impact on circulating inflammatory mediators in blood, cerebrospinal fluid and saliva. Herein, we provide an overview of current literature relevant for the shared pathways of sleep, pain and immunometabolism and elaborate the impact of melatonin on the crossroad of sleep, chronic pain and immunometabolism. Furthermore, we discuss the potential of melatonin as an adjunct to neurostimulation therapies. In this narrative review, we addressed these questions using the following search terms: melatonin, sleep, immunometabolism, obesity, chronic pain, neuromodulation, neurostimulation, neuroinflammation, molecular inflammatory phenotyping. So far, the majority of the published literature is derived from experimental studies and studies specifically assessing these relationships in context to neurostimulation are sparse. Thus, the adjunct potential of melatonin in clinical neurostimulation has not been evaluated under the umbrella of randomized-controlled trials and deserves increased attention as melatonin interacts and shares pathways relevant for noninvasive and invasive neurostimulation therapies.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Augmentation of neurostimulation therapies; Central and peripheral neuroinflammation pathways; Chronic pain; Immune-metabolism; Melatonin; Sleep

Meningioma growth dynamics assessed by radiocarbon retrospective birth dating - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; El Cheikh, Raouf; Nakamura, Makoto; Tortora, Angelo; Heinke, Paula; Coras, Roland; Englund, Elisabet; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Röder, Sebastian; et al. (EBioMedicine, 2018)
It is not known how long it takes from the initial neoplastic transformation of a cell to the detection of a tumor, which would be valuable for understanding tumor growth dynamics. Meningiomas show a broad histological, genetic and clinical spectrum, are usually benign and considered slowly growing. There is an intense debate regarding their age and growth pattern and when meningiomas should be resected. We have assessed the age and growth dynamics of 14 patients with meningiomas (WHO grade I: n=6 with meningothelial and n=6 with fibrous subtype, as well as n=2 atypical WHO grade II meningiomas) by combining retrospective birth-dating of cells by analyzing incorporation of nuclear-bomb-test-derived 14C, analysis of cell proliferation, cell density, MRI imaging and mathematical modeling. We provide an integrated model of the growth dynamics of benign meningiomas. The mean age of WHO grade I meningiomas was 22.1±6.5years, whereas atypical WHO grade II meningiomas originated 1.5±0.1years prior to surgery (p<0.01). We conclude that WHO grade I meningiomas are very slowly growing brain tumors, which are resected in average two decades after time of origination.
EVALuna2:34031

Metabolic tumor microenvironment characterization of contrast enhancing brain tumors using physiologic mri - Stadlbauer, Andreas; Marhold, Franz; Oberndorfer, Stefan; Heinz, Gertraud; Zimmermann, Max; Buchfelder, Michael; Heynold, Elisabeth; Kinfe, Thomas Mehari (Metabolites, 2021)
The tumor microenvironment is a critical regulator of cancer development and progression as well as treatment response and resistance in brain neoplasms. The available techniques for investigation, however, are not well suited for noninvasive in vivo characterization in humans. A total of 120 patients (59 females; 61 males) with newly diagnosed contrast-enhancing brain tumors (64 glioblastoma, 20 brain metastases, 15 primary central nervous system (CNS) lymphomas (PCNSLs), and 21 meningiomas) were examined with a previously established physiological MRI protocol including quantitative blood-oxygen-level-dependent imaging and vascular architecture mapping. Six MRI biomarker maps for oxygen metabolism and neovascularization were fused for classification of five different tumor microenvironments: glycolysis, oxidative phosphorylation (OxPhos), hypoxia with/without neovascularization, and necrosis. Glioblastoma showed the highest metabolic heterogeneity followed by brain metastasis with a glycolysis-to-OxPhos ratio of approximately 2:1 in both tumor entities. In addition, glioblastoma revealed a significant higher percentage of hypoxia (24%) compared to all three other brain tumor entities: brain metastasis (7%; p < 0.001), PCNSL (8%; p = 0.001), and meningioma (8%; p = 0.003). A more aggressive biological brain tumor behavior was associated with a higher percentage of hypoxia and necrosis and a lower percentage of remaining vital tumor tissue and aerobic glycolysis. The proportion of oxidative phosphorylation, however, was rather similar (17–26%) for all four brain tumor entities. Tumor micro-environment (TME) mapping provides insights into neurobiological differences of contrast-enhancing brain tumors and deserves further clinical cancer research attention. Although there is a long roadmap ahead, TME mapping may become useful in order to develop new diagnostic and therapeutic approaches.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Brain tumors; Energy metabolism; Hypoxia; Metabolic imaging; Neovascularization; Physiological MRI; Tumor microenviron-ment

Microscopic transsphenoidal surgery - Buchfelder, Michael; Zhao, Yining; Schlaffer, Sven-Martin (Elsevier, 2021)
The classical transsphenoidal microsurgical approach has been continuously improved since its initial description, not least due to new technical possibilities, although the basic principle of the approach has not changed since the descriptions of Schloffer and Hirsch.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Direct endonasal approach; Microscopic transsphenoidal surgery; Midline orientation; Perinasal-paraseptal approach; Perioperative management; Reconstruction of sellar floor; Sublabial-paraseptal approach; Tumor resection

Microsurgical anatomy and pathoanatomy of the outer arachnoid membranes in the cerebellopontine angle: cadaveric and intraoperative observations - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo (Acta Neurochirurgica, 2023)
Purpose: The cerebellopontine angle (CPA) is a frequent region of skull base pathologies and therefore a target for neurosurgical operations. The outer arachnoid is the key structure to approach the here located lesions. The goal of our study was to describe the microsurgical anatomy of the outer arachnoid of the CPA and its pathoanatomy in case of space-occupying lesions. Methods: Our examinations were performed on 35 fresh human cadaveric specimens. Macroscopic dissections and microsurgical and endoscopic examinations were performed. Retrospective analysis of the video documentations of 35 CPA operations was performed to describe the pathoanatomical behavior of the outer arachnoid. Results: The outer arachnoid cover is loosely attached to the inner surface of the dura of the CPA. At the petrosal surface of the cerebellum the pia mater is strongly adhered to the outer arachnoid. At the level of the dural penetration of the cranial nerves, the outer arachnoid forms sheath-like structures around the nerves. In the midline, the outer arachnoid became detached from the pial surface and forms the base of the posterior fossa cisterns. In pathological cases, the outer arachnoid became displaced. The way of displacement depends on the origin of the lesion. The most characteristic patterns of changes of the outer arachnoid were described in case of meningiomas, vestibular schwannomas, and epidermoid cysts of the CPA. Conclusion: The knowledge of the anatomy of the outer arachnoid of the cerebellopontine region is essential to safely perform microsurgical approaches as well as of dissections during resection of pathological lesions.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Arachnoid; Cerebellopontine angle; Epidermoid cyst; Meningioma; Surgical anatomy; Vestibular schwannoma

Microsurgical treatment of cranial and spinal dural arteriovenous fistulas for acute occlusion: a single institution's experience - Winter, F.; Böhm, Lea; Shawarba, Julia; Callegari, K.; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2022)
Objectives: To determine the success rate of primary microsurgical treatment of both cranial and spinal dural arteriovenous fistulas (cdAVFs and sdAVFs).
CRIS-Team WoS Importer:2022-08-26

MIF-CD74 signaling impedes microglial M1 polarization and facilitates brain tumorigenesis - Ghoochani, Ali; Schwarz, Martin; Yakubov, Eduard; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; Bucala, R.; Savaskan, N. E.; Eyupoglu, I. Y. (Oncogene, 2016)
Microglial cells in the brain tumor microenvironment are associated with enhanced glioma malignancy. They persist in an immunosuppressive M2 state at the peritumoral site and promote the growth of gliomas. Here, we investigated the underlying factors contributing to the abolished immune surveillance. We show that brain tumors escape pro-inflammatory M1 conversion of microglia via CD74 activation through the secretion of the cytokine macrophage migration inhibitory factor (MIF), which results in a M2 shift of microglial cells. Interruption of this glioma-microglial interaction through an antibody-neutralizing approach or small interfering RNA (siRNA)-mediated inhibition prolongs survival time in glioma-implanted mice by reinstating the microglial pro-inflammatory M1 function. We show that MIF-CD74 signaling inhibits interferon (IFN)-γ secretion in microglia through phosphorylation of microglial ERK1/2 (extracellular signal-regulated protein kinases 1 and 2). The inhibition of MIF signaling or its receptor CD74 promotes IFN-γ release and amplifies tumor death either through pharmacological inhibition or through siRNA-mediated knockdown. The reinstated IFN-γ secretion leads both to direct inhibition of glioma growth as well as inducing a M2 to M1 shift in glioma-associated microglia. Our data reveal that interference with the MIF signaling pathway represents a viable therapeutic option for the restoration of IFN-γ-driven immune surveillance.
EVALuna2:33151

Migration measurement of the cemented Lubinus SP II hip stem - a 10-year follow-up using radiostereometric analysis - Sesselmann, Stefan; Hong, Yutong; Schlemmer, Frank; Wiendieck, Kurt; Söder, Stephan; Hussnaetter, Isabell; Müller, Lutz Arne; Forst, Raimund; Wierer, Thomas (Biomedizinische Technik, 2016)
In a previous radiostereometric analysis (RSA) of the Lubinus SP II (Link, Hamburg, Germany), which is one of the most often used cemented hip stems worldwide, our research group detected a very small but statistically significant distal migration of -0.03±0.17 mm 2 years after surgery compared to the postoperative radiograph. Maximum subsidence occurred between 6 and 12 months. The implant appeared to have stabilized after 2 years. The mean value of maximum total point motion (MTPM) was 0.99±0.69 mm, which was detected 2 years after surgery. The purpose of this study was to analyze the migration pattern and to verify the predictive value of short-term RSA of the Lubinus SP II stem after 10 years. After a follow-up of 5 and 10 years, 38 and 27 out of 100 patients remained available for further assessment, respectively. No statistically significant implant translation or rotation was found along or about the axes of the global coordinate system 5 and 10 years after surgery with respect to the postoperative radiograph. Furthermore, the MTPM was stable in both follow-up periods. The results suggest that the Lubinus SP II hip stem is still stable 10 years after surgery, supporting that determining prognosis by short-term RSA follow-up of 2 years could be an appropriate tool for appraisal of implant behavior 10 years after surgery.
EVALuna2:6812

Mild Malformation of Cortical Development with Oligodendroglial Hyperplasia in Frontal Lobe Epilepsy: A New Clinico-Pathological Entity - Schurr, Johannes; Coras, Roland; Roessler, Karl; Pieper, Tom; Kudernatsch, Manfred; Holthausen, Hans; Winkler, Peter; Woermann, Friedrich; Bien, Christian G.; Polster, Tilman; Schulz, Reinhard; Kalbhenn, Thilo; et al. (Brain Pathology, 2017)
The histopathological spectrum of human epileptogenic brain lesions is widespread including common and rare variants of cortical malformations. However, 2-26% of epilepsy surgery specimens are histopathologically classified as nonlesional. We hypothesized that these specimens include also new diagnostic entities, in particular when presurgical magnetic resonance imaging (MRI) can identify abnormal signal intensities within the anatomical region of seizure onset. In our series of 1381 en bloc resected epilepsy surgery brain specimens, 52 cases could not be histopathologically classified and were considered nonlesional (3.7%). An increase of Olig2-, and PDGFR-alpha-immunoreactive oligodendroglia was observed in white matter and deep cortical layers in 22 of these patients (42%). Increased proliferation activity as well as heterotopic neurons in white matter were additional histopathological hallmarks. All patients suffered from frontal lobe epilepsy (FLE) with a median age of epilepsy onset at 4 years and 16 years at epilepsy surgery. Presurgical MRI suggested focal cortical dysplasia (FCD) in all patients. We suggest to classify this characteristic histopathology pattern as "mild malformation of cortical development with oligodendroglial hyperplasia (MOGHE)." Further insights into pathomechanisms of MOGHE may help to bridge the diagnostic gap in children and young adults with difficult-to-treat FLE.
EVALuna2:7369

Minimally invasive surgeries for spontaneous hypertensive intracerebral hemorrhage (MISICH): a multicenter randomized controlled trial - Xu, Xinghua; Zhang, Huaping; Zhang, Jiashu; Luo, Ming; Wang, Qun; Zhao, Yining; Gan, Zhichao; Xu, Bainan; Chen, Xiaolei (BMC Medicine, 2024)
Background: Intracerebral hemorrhage (ICH) is a common stroke type with high morbidity and mortality. There are mainly three surgical methods for treating ICH. Unfortunately, thus far, no specific surgical method has been proven to be the most effective. We carried out this study to investigate whether minimally invasive surgeries with endoscopic surgery or stereotactic aspiration (frameless navigated aspiration) will improve functional outcomes in patients with supratentorial ICH compared with small-bone flap craniotomy. Methods: In this parallel-group multicenter randomized controlled trial conducted at 16 centers, patients with supratentorial hypertensive ICH were randomized to receive endoscopic surgery, stereotactic aspiration, or craniotomy at a 1:1:1 ratio from July 2016 to June 2022. The follow-up duration was 6 months. Patients were randomized to receive endoscopic evacuation, stereotactic aspiration, or small-bone flap craniotomy. The primary outcome was favorable functional outcome, defined as the proportion of patients who achieved a modified Rankin scale (mRS) score of 0–2 at the 6-month follow-up. Results: A total of 733 patients were randomly allocated to three groups: 243 to the endoscopy group, 247 to the aspiration group, and 243 to the craniotomy group. Finally, 721 patients (239 in the endoscopy group, 246 in the aspiration group, and 236 in the craniotomy group) received treatment and were included in the intention-to-treat analysis. Primary efficacy analysis revealed that 73 of 219 (33.3%) in the endoscopy group, 72 of 220 (32.7%) in the aspiration group, and 47 of 212 (22.2%) in the craniotomy group achieved favorable functional outcome at the 6-month follow-up (P =.017). We got similar results in subgroup analysis of deep hemorrhages, while in lobar hemorrhages the prognostic outcome was similar among three groups. Old age, deep hematoma location, large hematoma volume, low preoperative GCS score, craniotomy, and intracranial infection were associated with greater odds of unfavorable outcomes. The mean hospitalization expenses were ¥92,420 in the endoscopy group, ¥77,351 in the aspiration group, and ¥100,947 in the craniotomy group (P =.000). Conclusions: Compared with small bone flap craniotomy, endoscopic surgery and stereotactic aspiration improved the long-term outcome of hypertensive ICH, especially deep hemorrhages. Trial Registration: ClinicalTrials.gov Identifier: NCT02811614.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Endoscopic surgery; Intracerebral hemorrhage; Minimally invasive surgery; Randomized controlled trial; Small-bone flap craniotomy; Stereotactic aspiration

Mobile internet-based mixed-reality interactive telecollaboration system for neurosurgical procedures: technical feasibility and clinical implementation - Zhang, Shiyu; Li, Fangye; Zhao, Yining; Xiong, Ruochu; Wang, Jingyue; Gan, Zhichao; Xu, Xinghua; Wang, Qun; Zhang, Huaping; Zhang, Jiashu; Chen, Xiaolei (Neurosurgical Focus, 2022)
OBJECTIVE To increase access to health interventions and healthcare services for patients in resource-constrained settings, strategies such as telemedicine must be implemented for the allocation of medical resources across geographic boundaries. Telecollaboration is the dominant form of surgical telemedicine. In this study, the authors report and evaluate a novel mobile internet-based mixed- reality interactive telecollaboration (MIMIT) system as a new paradigm for telemedicine and validate its clinical feasibility.
CRIS-Team WoS Importer:2022-06-24

MODIFIED SUBPIAL - Roessler, K.; Kasper, Burkhard; Coras, R.; Sommer, B.; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael (2017)
EVALuna2:7378

Morphometry and microsurgical anatomy of Bochdalek's flower basket and the related structures of the cerebellopontine angle - Barany, Laszlo; Baksa, Gabor; Patonay, Lajos; Ganslandt, Oliver; Buchfelder, Michael; Kurucz, Peter (Acta Neurochirurgica, 2017)
BACKGROUND: Bochdalek's flower basket (Bfb) is the distal part of the horizontal segment of the fourth ventricle's choroid plexus protruding through the lateral aperture (foramen of Luschka). The microsurgical anatomy of the cerebellopontine angle, fourth ventricle and its inner choroid plexus is well described in the literature, but only one radiological study has investigated the Bfb so far. The goal of the present study was to give an extensive morphometric analysis of the Bfb for the first time and discuss the surgically relevant anatomical aspects. METHOD: Forty-two formalin-fixed human brains (84 cerebellopontine angles) were involved in this study. Photomicrographs with scale bars were taken in every step of dissection to perform further measurements with Fiji software. The lengths and widths of the Bfb, rhomboid lip and lateral aperture of the fourth ventricle as well as the related neurovascular and arachnoid structures were measured. The areas of two sides were compared with paired t-tests using R software. Significance level was set at p < 0.05. RESULTS: Protruding choroid plexus was present in 77 cases (91.66%). In 6 cases (7.14%), the Bfb was totally covered by the rhomboid lip, and in one case (1.19%), it was absent. The mean width of the Bfb was 6.618 mm (2-14 mm), the mean height 5.658 mm (1.5-14 mm) and mean area 25.80 mm2 (3.07-109.83 mm2). There was no statistically significant difference between the two sides (p = 0.1744). The Bfb was in contact with 20 AICAs (23.80%), 6 PICAs (7.14%) and 39 vestibulocochlear nerves (46.42%). Arachnoid trabecules, connecting the lower cranial nerves to the Bfb or rhomboid lip, were found in 57 cases (67.85%). CONCLUSIONS: The Bfb is an important landmark during various surgical procedures. Detailed morphology, dimensions and relations to the surrounding neurovascular structures are described in this study. These data are essential for surgeons operating in this region.
EVALuna2:102199

Mosaic trisomy of chromosome 1q in human brain tissue associates with unilateral polymicrogyria, very early-onset focal epilepsy, and severe developmental delay - Kobow, Katja; Jabari, Samir; Pieper, Tom; Kudernatsch, Manfred; Polster, Tilman; Woermann, Friedrich G.; Kalbhenn, Thilo; Hamer, Hajo; Roessler, Karl; Muhlebner, Angelika; Spliet, Wim G. M.; Feucht, Martha; et al. (Acta Neuropathologica, 2020)
Polymicrogyria (PMG) is a developmental cortical malformation characterized by an excess of small and frustrane gyration and abnormal cortical lamination. PMG frequently associates with seizures. The molecular pathomechanisms underlying PMG development are not yet understood. About 40 genes have been associated with PMG, and small copy number variations have also been described in selected patients. We recently provided evidence that epilepsy-associated structural brain lesions can be classified based on genomic DNA methylation patterns. Here, we analyzed 26 PMG patients employing array-based DNA methylation profiling on formalin-fixed paraffin-embedded material. A series of 62 well-characterized non-PMG cortical malformations (focal cortical dysplasia type 2a/b and hemimegalencephaly), temporal lobe epilepsy, and non-epilepsy autopsy controls was used as reference cohort. Unsupervised dimensionality reduction and hierarchical cluster analysis of DNA methylation profiles showed that PMG formed a distinct DNA methylation class. Copy number profiling from DNA methylation data identified a uniform duplication spanning the entire long arm of chromosome 1 in 7 out of 26 PMG patients, which was verified by additional fluorescence in situ hybridization analysis. In respective cases, about 50% of nuclei in the center of the PMG lesion were 1q triploid. No chromosomal imbalance was seen in adjacent, architecturally normal-appearing tissue indicating mosaicism. Clinically, PMG 1q patients presented with a unilateral frontal or hemispheric PMG without hemimegalencephaly, a severe form of intractable epilepsy with seizure onset in the first months of life, and severe developmental delay. Our results show that PMG can be classified among other structural brain lesions according to their DNA methylation profile. One subset of PMG with distinct clinical features exhibits a duplication of chromosomal arm 1q.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Brain development; Chromosome 1; Copy number variation; Cortical malformation; ID; Seizures

MR-guided high-intensity focused ultrasound for chronic pain: where do we stand? - Kinfe, Thomas Mehari (Expert review of neurotherapeutics, 2023)
CRIS-Team Scopus Importer:2023-08-25
Keywords: chronic pain disorders; Incisionless magnetic resonance-guided focused ultrasound; limbic pain matrix; objective outcome measures; sensory thalamic nuclei

MRI essentials in epileptology: a review from the ILAE Imaging Taskforce - Wang, Irene; Bernasconi, Andrea; Bernhardt, Boris; Blumenfeld, Hal; Cendes, Fernando; Chinvarun, Yotin; Jackson, Graeme; Morgan, Victoria; Rampp, Stefan; Vaudano, Anna Elisabetta; Federico, Paolo (Epileptic Disorders, 2020)
Magnetic resonance imaging (MRI) plays a central role in the management and evaluation of patients with epilepsy. It is important that structural MRI scans are optimally acquired and carefully reviewed by trained experts within the context of all available clinical data. The aim of this review is to discuss the essentials of MRI that will be useful to health care providers specialized in epilepsy, as outlined by the competencies and learning objectives of the recently developed ILAE curriculum. This review contains information on basic MRI principles, sequences, field strengths and safety, when to perform and repeat an MRI, epilepsy MRI protocol (HARNESS-MRI) and the basic reading guidelines, and common epileptic pathologies. More advanced topics such as MRI-negative epilepsy, functional MRI and diffusion-weighted imaging are also briefly discussed. Although the available resources can differ markedly across different centers, it is the hope that this review can provide general guidance in the everyday practice of using MRI for patients with epilepsy.
CRIS-Team Scopus Importer:2020-09-18
Keywords: adults; epilepsy; pediatrics; structural magnetic resonance imaging

MR Imaging-derived Oxygen Metabolism and Neovascularization Characterization for Grading and IDH Gene Mutation Detection of Gliomas - Stadlbauer, Andreas; Zimmermann, Max; Kitzwoegerer, Melitta; Oberndorfer, Stefan; Roessler, Karl; Dörfler, Arnd; Buchfelder, Michael; Heinz, Gertraud (Radiology, 2017)
Purpose To explore the diagnostic performance of physiological magnetic resonance (MR) imaging of oxygen metabolism and neovascularization activity for grading and characterization of isocitrate dehydrogenase (IDH) gene mutation status of gliomas. Materials and Methods This retrospective study had institutional review board approval; written informed consent was obtained from all patients. Eighty-three patients with histopathologically proven glioma (World Health Organization [WHO] grade II-IV) were examined with quantitative blood oxygen level-dependent imaging and vascular architecture mapping. Biomarker maps of neovascularization activity (microvessel radius, microvessel density, and microvessel type indicator [MTI]) and oxygen metabolism (oxygen extraction fraction [OEF] and cerebral metabolic rate of oxygen [CMRO2]) were calculated. Receiver operating characteristic analysis was used to determine diagnostic performance for grading and detection of IDH gene mutation status. Results Low-grade (WHO grade II) glioma showed areas with increased OEF (+18%, P < .001, n = 20), whereas anaplastic glioma (WHO grade III) and glioblastoma (WHO grade IV) showed decreased OEF when compared with normal brain tissue (-54% [P < .001, n = 21] and -49% [P < .001, n = 41], respectively). This allowed clear differentiation between low- and high-grade glioma (area under the receiver operating characteristic curve [AUC], 1) for the patient cohort. MTI had the highest diagnostic performance (AUC, 0.782) for differentiation between gliomas of grades III and IV among all biomarkers. CMRO2was decreased (P = .037) in low-grade glioma with a mutated IDH gene, and MTI was significantly increased in glioma grade III with IDH mutation (P = .013) when compared with the IDH wild-type counterparts. CMRO2showed the highest diagnostic performance for IDH gene mutation detection in low-grade glioma (AUC, 0.818) and MTI in high-grade glioma (AUC, 0.854) and for all WHO grades (AUC, 0.899) among all biomarkers. Conclusion MR imaging-derived oxygen metabolism and neovascularization characterization may be useful for grading and IDH mutation detection of gliomas and requires only 7 minutes of extra imaging time.©RSNA, 2016 Online supplemental material is available for this article.
EVALuna2:33140

Multidisciplinary management of acromegaly: A consensus - Giustina, Andrea; Barkhoudarian, Garni; Beckers, Albert; Ben-Shlomo, Anat; Biermasz, Nienke; Biller, Beverly; Boguszewski, Cesar; Bolanowski, Marek; Bollerslev, Jens; Bonert, Vivien; Bronstein, Marcello D.; Buchfelder, Michael; et al. (Reviews in Endocrine & Metabolic Disorders, 2020)
The 13th Acromegaly Consensus Conference was held in November 2019 in Fort Lauderdale, Florida, and comprised acromegaly experts including endocrinologists and neurosurgeons who considered optimal approaches for multidisciplinary acromegaly management. Focused discussions reviewed techniques, results, and side effects of surgery, radiotherapy, and medical therapy, and how advances in technology and novel techniques have changed the way these modalities are used alone or in combination. Effects of treatment on patient outcomes were considered, along with strategies for optimizing and personalizing therapeutic approaches. Expert consensus recommendations emphasize how best to implement available treatment options as part of a multidisciplinary approach at Pituitary Tumor Centers of Excellence.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Acromegaly; Consensus; Medical therapy; Multidisciplinary management; Pituitary tumor centers of excellence; Radiotherapy; Surgery

Multidisciplinary management strategies for recurrent brain metastasis after prior radiotherapy: An overview - Kotecha, Rupesh; La Rosa, Alonso; Brown, Paul D.; Vogelbaum, Michael A.; Navarria, Pierina; Bodensohn, Raphael; Niyazi, Maximilian; Karschnia, Philipp; Minniti, Giuseppe (Neuro-Oncology, 2025)
As cancer patients with intracranial metastatic disease experience increasingly prolonged survival, the diagnosis and management of recurrent brain metastasis pose significant challenges in clinical practice. Prior to deciding upon a management strategy, it is necessary to ascertain whether patients have recurrent/progressive disease vs adverse radiation effect, classify the recurrence as local or distant in the brain, evaluate the extent of intracranial disease (size, number and location of lesions, and brain metastasis velocity), the status of extracranial disease, and enumerate the interval from the last intracranially directed intervention to disease recurrence. A spectrum of salvage local treatment options includes surgery (resection and laser interstitial thermal therapy [LITT]) with or without adjuvant radiotherapy in the forms of external beam radiotherapy, intraoperative radiotherapy, or brachytherapy. Nonoperative salvage local treatments also range from single fraction and fractionated stereotactic radiosurgery (SRS/FSRS) to whole brain radiation therapy (WBRT). Optimal integration of systemic therapies, preferably with central nervous system (CNS) activity, may also require reinterrogation of brain metastasis tissue to identify actionable molecular alterations specific to intracranial progressive disease. Ultimately, the selection of the appropriate management approach necessitates a sophisticated understanding of patient, tumor, and prior treatment-related factors and is often multimodal; hence, interdisciplinary evaluation for such patients is indispensable.
CRIS-Team Scopus Importer:2025-04-04
Keywords: brain metastases; progression; radiosurgery; radiotherapy; recurrence

Multiple tumorous lesions of the pituitary gland - Von Schoening, Jannik; Flitsch, Joerg; Luedecke, Dieter K.; Fahlbusch, Rudolf; Buchfelder, Michael; Buslei, Rolf; Knappe, Ulrich J.; Bergmann, Markus; Schulz-Schaeffer, Walter J.; Herms, Jochen; Glatzel, Markus; Saeger, Wolfgang (Hormones-International Journal of Endocrinology and Metabolism, 2022)
Purpose/Objective: Multiple tumorous lesions in one pituitary gland are rare and mostly described in case reports. Their incidences and combinations are defined in larger collectives. Therefore, we analyzed our large collection for double tumors and combinations of tumors, cysts, and inflammation. Methods: The German Registry of Pituitary Tumors, including cases from 1990 to 2018, served as the database. Our collection comprises a total of 16,283 cases up until the end of 2018. Of these cases, 12,673 originated from surgical and 3,610 from autopsy material. All specimens were fixed in formalin and embedded in paraffin. The sections were stained with hematoxylin–eosin and PAS. Monoclonal (prolactin, TSH, FSH, LH, and α subunit) or polyclonal (GH and ACTH) antibodies were used to detect pituitary hormones in the lesions. Since 2017, antibodies against the transcription factors Pit-1, T-Pit, and SF-1 have been used in difficult cases. The criteria of the 2017 WHO classification have been basic principles for classification since 2018 (Osamura et al. 2017). For differentiation of other sellar tumors, such as meningiomas, chordomas, or metastases, the use of additional antibodies was necessary. For these cases, it was possible to use a broad antibody spectrum. Autopsy pituitaries were generally studied by H&E and PAS sections. If any lesions were demonstrated in these specimens, additional immunostaining was performed. Results: Multiple tumorous lesions with more than one pituitary neuroendocrine tumor (PitNET) respectively adenoma make up 1.4% (232 cases) in our collection. Within the selected cases, synchronous multiple pituitary neuroendocrine tumors (PitNETs) account for 17.3%, PANCH cases (pituitary adenoma with neuronal choristoma) for 14.7%, PitNETs and posterior lobe tumors for 2.2%, PitNETs and metastases for 5.2%, PitNETs and mesenchymal tumors for 2.6%, PitNETs and cysts for 52.2%, and PitNETs and primary inflammation for 6.0%. The mean patient age was 53.8 years, with a standard deviation of 18.5 years. A total of 55.3% of the patients were female and 44.7% were male. From 1990 to 2018, there was a continuous increase in the number of multiple tumorous lesions. Conclusion: From our studies, we conclude that considering possible tumorous double lesions during surgeries and in preoperative X-ray analyses is recommended.
CRIS-Team Scopus Importer:2022-08-26
Keywords: Adenoma; Double adenomas; Gangliocytoma; Granular cell tumor; Metastasis; Multiple tumorous lesions; PANCH; PitNETs; Pituicytoma; Pituitary; Pituitary cysts; Rathke’s cleft cyst; Spindle cell oncocytoma

Mutations in the deubiquitinase gene USP8 cause Cushing's disease - Reincke, Martin; Sbiera, Silviu; Hayakawa, Akira; Theodoropoulou, Marily; Osswald, Andrea; Beuschlein, Felix; Meitinger, Thomas; Mizuno-Yamasaki, Emi; Kawaguchi, Kohei; Saeki, Yasushi; Tanaka, Keiji; Wieland, Thomas; et al. (Nature Genetics, 2015)
Cushing's disease is caused by corticotroph adenomas of the pituitary. To explore the molecular mechanisms of endocrine autonomy in these tumors, we performed exome sequencing of 10 corticotroph adenomas. We found somatic mutations in the USP8 deubiquitinase gene in 4 of 10 adenomas. The mutations clustered in the 14-3-3 protein binding motif and enhanced the proteolytic cleavage and catalytic activity of USP8. Cleavage of USP8 led to increased deubiqutination of the EGF receptor, impairing its downregulation and sustaining EGF signaling. USP8 mutants enhanced promoter activity of the gene encoding proopiomelanocortin. In summary, our data show that dominant mutations in USP8 cause Cushing's disease via activation of EGF receptor signaling.
EVALuna2:22866

Nanoparticles size-dependently initiate self-limiting NETosis-driven inflammation - Munoz, Luis E.; Bilyy, Rostyslav; Biermann, Mona H. C.; Kienhoefer, Deborah; Maueröder, Christian; Hahn, Jonas; Brauner, Jan M.; Weidner, Daniela; Chen, Juan; Scharin-Mehlmann, Marina; Janko, Christina; Friedrich, Ralf P.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The critical size for strong interaction of hydrophobic particles with phospholipid bilayers has been predicted to be 10 nm. Because of the wide spreading of nonpolar nanoparticles (NPs) in the environment, we aimed to reveal the ability of living organisms to entrap NPs via formation of neutrophil extracellular traps (NETs). Upon interaction with various cell types and tissues, 10- to 40-nm-sized NPs induce fast (<20 min) damage of plasma membranes and instability of the lysosomal compartment, leading to the immediate formation of NETs. In contrast, particles sized 100-1,000 nm behaved rather inertly. Resulting NET formation (NETosis) was accompanied by an inflammatory reaction intrinsically endowed with its own resolution, demonstrated in lungs and air pouches of mice. Persistence of small NPs in joints caused unremitting arthritis and bone remodeling. Small NPs coinjected with antigen exerted adjuvant-like activity. This report demonstrates a cellular mechanism that explains how small NPs activate the NETosis pathway and drive their entrapping and resolution of the initial inflammatory response.
EVALuna2:13106

Nature has no principle-inflammation following brain injury is neither good nor evil* - Kleindienst, Andrea; Buchfelder, Michael; Brandner, Sebastian (Critical Care Medicine, 2014)
EVALuna2:22850

Neighborhood-level inequalities and influencing factors of COVID-19 incidence in berlin based on Bayesian spatial modelling - Zhuang, Sida; Wolf, Kathrin; Schmitz, Tillman; Roth, Alexandra; Sun, Yukai; Savaskan, Nicolai; Lakes, Tobia (Sustainable Cities and Society, 2024)
Numerous studies have explored influencing factors in COVID-19, yet empirical evidence on spatiotemporal dynamics of COVID-19 inequalities concerning both socioeconomic and environmental factors at an intra-urban scale is lacking. This study, therefore, focuses on neighborhood-level spatial inequalities of the COVID-19 incidences in relation to socioeconomic and environmental factors for Berlin-Neukölln, Germany, covering six pandemic periods (March 2020 to December 2021). Spatial Bayesian negative binomial mixed-effect models were employed to identify influencing factors and risk patterns for different periods. We identified that (1) influencing factors and relative risks varied across time and space, with sociodemographic factors exerting a stronger influence over environmental features; (2) as the most identified predictors, the population with migrant backgrounds was positively associated, and the population over 65 was negatively associated with COVID-19 incidence; (3) certain neighborhoods consistently faced elevated risks of COVID-19 incidence. This study highlights potential structural health inequalities within migrant communities, associated with lower socioeconomic status and a higher risk of COVID-19 incidence across diverse pandemic periods. Our findings indicate that locally tailored interventions for diverse citizens are essential to address health inequalities and foster a more sustainable urban environment.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Bayesian spatial modelling; COVID-19 health inequality; Environmental justice; Intra-urban; Social inequality; Social vulnerability; Spatial inequality

Network topology in brain tumor patients with and without structural epilepsy: a prospective MEG study - Ladisich, Barbara; Rampp, Stefan; Trinka, Eugen; Weisz, Nathan; Schwartz, Christoph; Kraus, Theo; Sherif, Camillo; Marhold, Franz; Demarchi, Gianpaolo (Therapeutic Advances in Neurological Disorders, 2023)
Background: It was proposed that network topology is altered in brain tumor patients. However, there is no consensus on the pattern of these changes and evidence on potential drivers is lacking. Objectives: We aimed to characterize neurooncological patients’ network topology by analyzing glial brain tumors (GBTs) and brain metastases (BMs) with respect to the presence of structural epilepsy. Methods: Network topology derived from resting state magnetoencephalography was compared between (1) patients and controls, (2) GBTs and BMs, and (3) patients with (PSEs) and without structural epilepsy (PNSEs). Eligible patients were investigated from February 2019 to March 2021. We calculated whole brain (WB) connectivity in six frequency bands, network topological parameters (node degree, average shortest path length, local clustering coefficient) and performed a stratification, where differences in power were identified. For data analysis, we used Fieldtrip, Brain Connectivity MATLAB toolboxes, and in-house built scripts. Results: We included 41 patients (21 men), with a mean age of 60.1 years (range 23–82), of those were: GBTs (n = 23), BMs (n = 14), and other histologies (n = 4). Statistical analysis revealed a significantly decreased WB node degree in patients versus controls in every frequency range at the corrected level (p1–30Hz = 0.002, pγ = 0.002, pβ = 0.002, pα = 0.002, pθ = 0.024, and pδ = 0.002). At the descriptive level, we found a significant augmentation for WB local clustering coefficient (p1–30Hz = 0.031, pδ = 0.013) in patients compared to controls, which did not persist the false discovery rate correction. No differences regarding networks of GBTs compared to BMs were identified. However, we found a significant increase in WB local clustering coefficient (pθ = 0.048) and decrease in WB node degree (pα = 0.039) in PSEs versus PNSEs at the uncorrected level. Conclusion: Our data suggest that network topology is altered in brain tumor patients. Histology per se might not, however, tumor-related epilepsy seems to influence the brain’s functional network. Longitudinal studies and analysis of possible confounders are required to substantiate these findings.
CRIS-Team Scopus Importer:2023-09-29
Keywords: brain metastasis; brain tumor; epilepsy; magnetoencephalography; network topology; resting-state

Neural and vascular architecture of the septum pellucidum: an anatomical study and considerations for safe endoscopic septum pellucidotomy - Barany, Laszlo; Meszaros, Cintia; Ganslandt, Oliver; Buchfelder, Michael; Kurucz, Peter (Journal of Neurosurgery, 2020)
OBJECTIVE The septum pellucidum is a bilateral thin membranous structure representing the border between the frontal horns of the lateral ventricles. Its most examined components are the septal veins due to their surgical importance during endoscopic septum pellucidotomy (ESP), which is a well-accepted method for surgical treatment of unilateral hydrocephalus. It is widely accepted that the septum pellucidum contains nerve fibers as well, but interestingly, no anatomical study has been addressed to its neural components before. The aim of the present study was to identify these elements as well as their relations to the septal veins and to define major landmarks within the ventricular system for neurosurgical use. METHODS Nine formalin-fixed human cadaveric brains (18 septa pellucida) were involved in this study. A central block containing both septa pellucida was removed and frozen at -30°C for 2 weeks in 7 cases. The fibers of the septum pellucidum and the adjacent areas including the venous elements were dissected under magnification by using homemade wooden spatulas and microsurgical instruments. In 2 cases a histological technique was used to validate the findings of the dissections. The blocks were sliced, embedded in paraffin, cut in 7-µm-thick slices, and then stained as follows: 1) with H & E, 2) with Luxol fast blue combined with cresyl violet, and 3) with Luxol fast blue combined with Sirius red. RESULTS The septum pellucidum and the subjacent septum verum form the medial wall of the frontal horn of the lateral ventricle. Both structures contain nerve fibers that were organized in 3 groups: 1) the precommissural fibers of the fornix; 2) the inferior fascicle; and 3) the superior fascicle of the septum pellucidum. The area directly rostral to the postcommissural column of the fornix consisted of macroscopically identifiable gray matter corresponding to the septal nuclei. The histological examinations validated the findings of the authors’ fiber dissections. CONCLUSIONS The nerve elements of the septum pellucidum as well as the subjacent septum verum were identified with fiber dissection and verified with histology for the first time. The septal nuclei located just anterior to the fornix and the precommissural fibers of the fornix should be preserved during ESP. Considering the venous anatomy as well as the neural architecture of the septum pellucidum, the fenestration should ideally be placed above the superior edge of the fornix and preferably dorsal to the interventricular foramen.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Endoscopic septum pellucidotomy; Fiber dissection; Hydrocephalus; Klingler method; Septum pellucidum; Surgical anatomy; White matter tracts

Neural decoding from surface high-density EMG signals: influence of anatomy and synchronization on the number of identified motor units - Souza de Oliveira, Daniela; Casolo, Andrea; Balshaw, Thomas G.; Maeo, Sumiaki; Lanza, Marcel Bahia; Martin, Neil R. W.; Maffulli, Nicola; Kinfe, Thomas Mehari; Eskofier, Björn; Folland, Jonathan P.; Farina, Dario; Del Vecchio, Alessandro (Journal of Neural Engineering, 2022)
Objective.High-density surface electromyography (HD-sEMG) allows the reliable identification of individual motor unit (MU) action potentials. Despite the accuracy in decomposition, there is a large variability in the number of identified MUs across individuals and exerted forces. Here we present a systematic investigation of the anatomical and neural factors that determine this variability.Approach. We investigated factors of influence on HD-sEMG decomposition, such as synchronization of MU discharges, distribution of MU territories, muscle-electrode distance (MED-subcutaneous adipose tissue thickness), maximum anatomical cross-sectional area (ACSAmax), and fiber cross-sectional area. For this purpose, we recorded HD-sEMG signals, ultrasound and magnetic resonance images, and took a muscle biopsy from the biceps brachii muscle from 30 male participants drawn from two groups to ensure variability within the factors-untrained-controls (UT = 14) and strength-trained individuals (ST = 16). Participants performed isometric ramp contractions with elbow flexors (at 15%, 35%, 50% and 70% maximum voluntary torque-MVT). We assessed the correlation between the number of accurately detected MUs by HD-sEMG decomposition and each measured parameter, for each target force level. Multiple regression analysis was then applied.Main results.ST subjects showed lower MED (UT = 5.1 ± 1.4 mm; ST = 3.8 ± 0.8 mm) and a greater number of identified MUs (UT: 21.3 ± 10.2 vs ST: 29.2 ± 11.8 MUs/subject across all force levels). The entire cohort showed a negative correlation between MED and the number of identified MUs at low forces (r= -0.6,p= 0.002 at 15% MVT). Moreover, the number of identified MUs was positively correlated to the distribution of MU territories (r= 0.56,p= 0.01) and ACSAmax(r= 0.48,p= 0.03) at 15% MVT. By accounting for all anatomical parameters, we were able to partly predict the number of decomposed MUs at low but not at high forces.Significance.Our results confirmed the influence of subcutaneous tissue on the quality of HD-sEMG signals and demonstrated that MU spatial distribution and ACSAmaxare also relevant parameters of influence for current decomposition algorithms.
CRIS-Team Scopus Importer:2022-08-19
Keywords: decomposition; high-density surface electromyography; motor unit identification

Neurochirurgische Operationsmöglichkeiten bei posteriorer Epilepsie - Rössler, Karl; Kasper, Burkhard; Tomschik, Matthias; Dörfler, Arnd; Buchfelder, Michael; Dorfer, Christian (Zeitschrift für Epileptologie, 2021)
Background: The surgical treatment of posterior epilepsy within the spectrum of epilepsy surgery represents a particular challenge. Objective: To present the different surgical options for epilepsy surgery of posterior epilepsies. Material and methods: The different surgical procedures are illustrated in the light of the historical development and recent technical developments. Results: Invasive monitoring (implantation of electrodes), resective and disconnective procedures in combination with new technical developments led to an improvement in seizure outcome in the surgical treatment of posterior epilepsies.
CRIS-Team Scopus Importer:2021-01-15
Keywords: ECoG; Epilepsy surgery; Lesionectomy; Posterior disconnection; Tailored lesionectomy

Neurocysticercosis and epilepsy: Imaging and clinical characteristics - Rodríguez-Leyva, Ildefonso; Cantú-Flores, Karla; Domínguez-Frausto, Arturo; Vaudano, Anna Elisabetta; Archer, John; Bernhardt, Boris; Caciagli, Lorenzo; Cendes, Fernando; Chinvarun, Yotin; Federico, Paolo; Gaillard, William D.; Kobayashi, Eliane; et al. (Epileptic Disorders, 2023)
The ILAE Neuroimaging Task Force aimed to publish educational case reports highlighting basic aspects related to neuroimaging in epilepsy consistent with the educational mission of the ILAE. Neurocysticercosis (NCC) is highly endemic in resource-limited countries and increasingly more often seen in non-endemic regions due to migration. Cysts with larva of the tapeworm Taenia solium lodge in the brain and cause several neurological conditions, of which seizures are the most common. There is great heterogeneity in the clinical presentation of neurocysticercosis because cysts vary in number, larval stage, and location among patients. We here present two illustrative cases with different clinical features to highlight the varying severity of symptoms secondary to this parasitic infestation. We also present several examples of imaging characteristics of the disease at various stages, which emphasize the central role of neuroimaging in the diagnosis of neurocysticercosis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: CT; epilepsy; MRI; neurocysticercosis; neuroimaging

Neurodegeneration and the Brain Tumor Microenvironment. [corrected] - Savaskan, Nicolai E.; Fan, Zheng; Broggini, Thomas; Buchfelder, Michael; Eyüpoglu, Ilker Yasin (Current Neuropharmacology, 2015)
Malignant brain tumors are characterized by destructive growth and neuronal cell death making them one of the most devastating diseases. Neurodegenerative actions of malignant gliomas resemble mechanisms also found in many neurodegenerative diseases such as Alzheimer's and Parkinson's diseases and amyotrophic lateral sclerosis. Recent data demonstrate that gliomas seize neuronal glutamate signaling for their own growth advantage. Excessive glutamate release via the glutamate/cystine antiporter xCT (system xc-, SLC7a11) renders cancer cells resistant to chemotherapeutics and create the tumor microenvironment toxic for neurons. In particular the glutamate/cystine antiporter xCT takes center stage in neurodegenerative processes and sets this transporter a potential prime target for cancer therapy. Noteworthy is the finding, that reactive oxygen species (ROS) activate transient receptor potential (TRP) channels and thereby TRP channels can potentiate glutamate release. Yet another important biological feature of the xCT/glutamate system is its modulatory effect on the tumor microenvironment with impact on host cells and the cancer stem cell niche. The EMA and FDA-approved drug sulfasalazine (SAS) presents a lead compound for xCT inhibition, although so far clinical trials on glioblastomas with SAS were ambiguous. Here, we critically analyze the mechanisms of action of xCT antiporter on malignant gliomas and in the tumor microenvironment. Deciphering the impact of xCT and glutamate and its relation to TRP channels in brain tumors pave the way for developing important cancer microenvironmental modulators and drugable lead targets.
EVALuna2:22860

Neuroendocrine Disturbances One to Five or More Years after Traumatic Brain Injury and Aneurysmal Subarachnoid Hemorrhage: Data from the German Database on Hypopituitarism - Krewer, Carmen; Schneider, Manfred; Schneider, Harald Joern; Kreitschmann-Andermahr, Ilonka; Buchfelder, Michael; Faust, Michael; Berg, Christian; Wallaschofski, Henri; Renner, Caroline; Uhl, Eberhard; Koenig, Eberhard; Jordan, Martina; et al. (Journal of Neurotrauma, 2016)
Neuroendocrine disturbances are common after traumatic brain injury (TBI) and aneurysmal subarachnoid hemorrhage (SAH), but only a few data exist on long-term anterior pituitary deficiencies after brain injury. We present data from the Structured Data Assessment of Hypopituitarism after TBI and SAH, a multi-center study including 1242 patients. We studied a subgroup of 351 patients, who had sustained a TBI (245) or SAH (106) at least 1 year before endocrine assessment (range 1-55 years) in a separate analysis. The highest prevalence of neuroendocrine disorders was observed 1-2 years post-injury, and it decreased over time only to show another maximum in the long-term phase in patients with brain injury occurring ≥5 years prior to assessment. Gonadotropic and somatotropic insufficiencies were most common. In the subgroup from 1 to 2 years after brain injury (n = 126), gonadotropic insufficiency was the most common hormonal disturbance (19%, 12/63 men) followed by somatotropic insufficiency (11.5%, 7/61), corticotropic insufficiency (9.2%, 11/119), and thyrotropic insufficiency (3.3%, 4/122). In patients observed ≥ 5 years after brain injury, the prevalence of somatotropic insufficiency increased over time to 24.1%, whereas corticotropic and thyrotrophic insufficiency became less frequent (2.5% and 0%, respectively). The prevalence differed regarding the diagnostic criteria (laboratory values vs. physician`s diagnosis vs. stimulation tests). Our data showed that neuroendocrine disturbances are frequent even years after TBI or SAH, in a cohort of patients who are still on medical treatment.
EVALuna2:33855

Neurological outcome and frequency of overdrainage in normal pressure hydrocephalus directly correlates with implanted ventriculo-peritoneal shunt valve type - Bozhkov, Yavor; Roessler, Karl; Hore, Nirjhar; Buchfelder, Michael; Brandner, Sebastian (Neurological Research, 2017)
BACKGROUND: The correlation between neurological outcome and frequency of overdrainage in the management of idiopathic normal pressure hydrocephalus (iNPH) using different ventriculoperitoneal shunt valve types is under investigation. Thus, we retrospectively compared one group of iNPH patients implanted with a programmable differential pressure valve (DPV) with another group treated by implantation of a DPV in combination with a flow-regulated anti-siphon device valve (ASD). METHODS: A retrospective evaluation of clinical outcome and frequency of overdrainage of 40 consecutive iNPH patients following surgical management between 08/2010 and 08/2014 was performed. Within the first 2 years of the study, a programmable DPV was implanted in 21 patients (DPV-group, 14 males, 7 females, mean age 74.0 ± 6.0 years). In the following two years, a programmable DPV with a flow-regulated ASD was implanted in 19 patients (ASD- group, 12 males, 7 females, mean age 73.3 ± 4.2 years). Neurological outcome was assessed by employing the NPH recovery rate (comparison of pre- and postoperative Kiefer-score). Mean follow-up period was 12.4 ± 9.8 months. RESULTS: In the DPV-group, three patients (14.3%) experienced severe overdrainage needing surgical intervention despite initial higher valve opening pressures (175 ± 11 mmH2O), compared to one non surgical overdrainage in the ASD-group despite significant lower valve opening pressure (144 ± 22 mmH2O). Excellent/good clinical outcome was found in 78.9% of the patients implanted with ASD compared to 44.4% of patients in the DPV group (p < 0.05). CONCLUSION: Our results clearly demonstrate reduction in surgical over-drainage frequency and resulting complications in iNPH patients, with significantly better clinical outcome following insertion of a flow regulated ASD VP shunt compared to a DPV VP shunt, despite both systems comprised a programmable opening pressure mechanism.
EVALuna2:102203

Neuropathologic measurements in focal cortical dysplasias: validation of the ILAE 2011 classification system and diagnostic implications for MRI - Mühlebner, Angelika; Coras, Roland; Kobow, Katja; Feucht, Martha; Czech, Thomas; Stefan, Hermann; Buchfelder, Michael; Holthausen, Hans; Kudernatsch, Manfred; Blümcke, Ingmar; et al. (Acta Neuropathologica, 2012)
Focal cortical dysplasias (FCD) which represent a composite group of cortical malformations are increasingly recognized as morphological substrate for severe therapy-refractory epilepsy in children and young adults. However, presurgical evaluation remains challenging as not all FCD variants can be reliably detected by high-resolution magnetic resonance imaging (MRI). Here, we studied a cohort of 52 epilepsy patients with neuropathological evidence for FCD using the 2011 classification of the International League against Epilepsy (ILAE) and systematically analysed those histopathologic features applicable also for MRI diagnostics. Histopathologic parameters included quantitative measurements of cellular profiles, cortical thickness, heterotopic neurons in white matter, and myelination that were compared between FCD subtypes and age-/localization-matched controls (n = 36) using multivariate analysis. Dysmorphic neurons in both FCD Type II variants showed significantly increased diameter of their cell bodies and nuclei. Cortical thickness was also increased with a distinct loss of myelin content specifying FCD Type IIb from IIa. The data further suggested that myelination deficits in FCD Type IIb result from compromised oligodendroglial lineage differentiation and we concluded that the "transmantle sign" is a unique finding in FCD Type IIb. In contrast, FCD Type Ia was characterized by a smaller cortical ribbon and higher neuronal densities, but these parameters failed to reach statistical significance (considering age-and location-dependent variability in controls). All FCD variants showed abnormal grey-white matter boundaries with increased numbers of heterotopic neurons. Similar results were obtained also at deep white matter location. Thus, many FCD variants may indeed escape visual MRI inspection, but suspicious areas with increased or decreased cortical thickness as well as grey-white matter blurring may be uncovered using post-processing protocols of neuroimaging data. The systematic analysis of well-specified histopathological features could be helpful to improve sensitivity and specificity in MRI detection during pre-surgical work-up of patients with drug-resistant focal epilepsies.
Keywords: Malformations; Neocortex; MRI; Seizures; Epilepsy; Neuropathology

Neurophysiology Signal Codecs for the DICOM® Standard: Preliminary Results - Battaglia, Filippo; Galanti, Mattia; Gugliandolo, Giovanni; Rampp, Stefan; Remi, Jan; Parashos, Alexandra; Sharma, Sonali; Bhatia, Sonal; Dean, Brian C.; Kutluay, Ekrem; Campbell, Zeke; Schmitt, Sarah; et al. (2024 IEEE International Symposium on Medical Measurements and Applications, MeMeA 2024 - Proceedings, 2024)
In this paper we report experimental results on compression of neurophysiology signals obtained as part of the standardization activities conducted by the Working Group 32 (WG-32) of the Digital Imaging and Communications in Medicine (DICOM). WG-32 focuses on extending the DICOM® standard for clinical neurophysiology data exchange. With this aim, several compression techniques specifically devised for neurophysiology signals, as well as audio codecs, have been investigated and compared using real-world datasets. Moreover, a web-based application, named EEGnet and developed specifically for viewing and annotating electroencephalography (EEG) data, has been exploited for determining the maximum distortion that can be tolerated on neurophysiology signals. Through the EEGnet framework, eight neurologists, affiliated to different universities and medical centers, identified signals where they observed a clinically-significant difference. As one of the main results of our study, we found that, in the case of EEG signals, a percentage root mean square difference (PRD) of 5% can be accepted by clinicians and experts. On the other hand, all experts agreed that distortion is unacceptable when the PRD is greater than 15%. Finally, surprisingly enough, experimental results showed that audio codecs provide performance levels that, in some cases, are comparable to those of state-of-the-art algorithms specifically devised for compression of EEG signals.
CRIS-Team Scopus Importer:2024-08-23
Keywords: biomedical signal processing; compression techniques; Neurophysiology signals

Neurosurgical Treatment of Acromegaly - Buchfelder, Michael; Feulner, Julian (Progress in Nucleic Acid Research and Molecular Biology, 2016)
Surgical removal of as much tumor mass as possible is usually considered the first step of treatment in acromegaly, unless the patients are unfit for surgery or refuse an operation. To date, in almost all cases, minimally invasive, transsphenoidal microscopic or endoscopic approaches are used. Whether a curative approach is feasible or a debulking procedure is planned, can be anticipated on the basis of preoperative magnetic resonance imaging. It mostly depends on localization, size, and the invasive character of the lesion. The surgical results depend on tumor-related factors such as size, extension, the presence or absence of invasion, and the magnitude of IGF-1 and growth hormone oversecretion, respectively. However, even surgeon-related factors such as experience and case load of the centers have been shown to strongly affect surgical results and complication rates. A reoperation can be considered at various stages in the treatment algorithm. There are several new technical gadgets which might aid in the surgical procedure: navigation, the Doppler probe, and variants of intraoperative imaging.
EVALuna2:33862

Neurovascular compression in arterial hypertension: Correlation of clinical data to 3d-visualizations of mri-findings - Manava, Panagiota; Hastreiter, Peter; Schmieder, Roland; Jung, Susanne; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael; Buchfelder, Michael; Naraghi, Ramin (Open Neuroimaging Journal, 2021)
Aims: In this study, we attempted to identify clinical parameters predicting the absence or presence of Neurovascular Compression (NVC) at the Ventrolateral Medulla (VLM) in arterial hypertension (HTN) in MRI findings. Background: Cardiovascular and pulmonary afferences are transmitted through the left vagus and glossopharyngeal nerve to the brain stem and vasoactive centers. Evidence supports the association between HTN and NVC at the left VLM. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left VLM. Image processing of MRI provides comprehensible detection of NVC. HTN affects hemodynamic parameters and organs. Objective: This study analyzes and correlates clinical data and MRI findings in patients with and without NVC at the VLM in treatment resistant HTN to obtain possible selection criteria for neurogenic hypertension. Methods: In 44 patients with treatment resistant HTN, we compared MRI findings of neurovascular imaging to demographic, clinical and lifestyle data, office and 24-hour ambulatory Blood Pressure (BP), and cardiovascular imaging and parameters. Results: Twenty-nine (66%) patients had evidence of NVC at the VLM in MRI. Sixteen patients (36%) had unilateral NVC on the left side, 7 (16%) unilateral right and 6 (14%) bilateral NVC. Fifteen (34%) had no evidence of NVC at the VLM. Patients with left sided NVC were significantly younger, than those without NVC (p=0.034). They showed a statistically significant variance in daytime (p=0.020) and nighttime diastolic BP (p<0.001) as the mean arterial pressure (p=0.020). Other measured parameters did not show significant differences between the two groups. Conclusion: We suggest to examine young adults with treatment resistant HTN for the presence of NVC at VLM, before signs of permanent organ damage appear. Clinical and hemodynamic parameters did not emerge as selection criteria to predict NVC. MVD as a surgical treatment of NVC in HTN is not routine yet as a surgical treatment of NVC in HTN is not routine yet. Detection of NVC by imaging and image processing remains the only criteria to suggest MVD, which should be indicated on an individual decision.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypertension; Image fusion; MRI; Neuroimaging; Neurovascular compression; Ventrolateral medulla

Neurovascular compression of medulla oblongata - Association for gestation-induced hypertension - Tanrikulu, Levent; Naraghi, Ramin; Ernst, Veronika; Voigt, Franziska; Hastreiter, Peter; Dörfler, Arnd; Buchfelder, Michael; Beckmann, Matthias; Goecke, Tamme W. (Medical Hypotheses, 2015)
Patients with essential hypertension may show neurovascular compression (NVC) at the rostral ventrolateral medulla oblongata (RVLM). Ectatic loops of the vertebral artery (VA) or the inferior posterior cerebellar artery (PICA) cause NVC. This study aims to show the existence and morphology of NVC in patients with gestation-induced hypertension. 17 females were prospectively examined between 19. +. 0 and 35. +. 6. weeks of gestation. 3 patients with chronic hypertension (group A), 10 patients with preeclampsia (group B), 3 patients with superimposed preeclampsia (chronic hypertension with preeclampsia; group C) and one normotensive patient were included. Groups B and C represented patients with gestation-induced hypertension. All 17 patients underwent imaging by high resolution magnetic resonance imaging (MR-CISS, constructive interference in the steady state). Image processing was done with segmentation and three-dimensional (3D)-visualization was implemented with direct volume rendering of the individual neurovascular details of each patient. 9 of 17 patients (53%) showed NVC of the RVLM. Right-sided NVC was seen in 7 patients (41%). Left-sided NVC was seen in 6 patients (35%). Bilateral NVC was seen in 4 patients (24%). NVC was missing in 8 of the examined 17 patients (47%). The existence of NVC with high-resolution MRI was analyzed in gestation-induced hypertensive pregnant females for the first time. Neurovascular conflicts were seen in hypertensive pregnants. It is possible that NVC is potentially associated in patients with gestation-induced hypertension.
CRIS-Team Scopus Importer:2022-08-05

Neutrophil-to-lymphocyte ratio as an independent predictor for unfavorable functional outcome in aneurysmal subarachnoid hemorrhage - Giede-Jeppe, Antje; Reichl, Jonathan; Sprügel, Maximilian; Lücking, Hannes; Hölter, Philip; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Huttner, Hagen; Gerner, Stefan (Journal of Neurosurgery, 2019)
OBJECTIVEStroke-associated immunosuppression and inflammation are increasingly recognized as factors triggering infections and thus potentially influencing outcome after stroke. Several studies have demonstrated that elevated neutrophil-to-lymphocyte ratio (NLR) is a significant predictor of adverse outcomes for patients with ischemic stroke or intracerebral hemorrhage. Thus far, in patients with subarachnoid hemorrhage the association between NLR and outcome is insufficiently established. The authors sought to investigate the association between NLR on admission and functional outcome in aneurysmal subarachnoid hemorrhage (aSAH).METHODSThis observational study included all consecutive aSAH patients admitted to a German tertiary center over a 5-year period (2008-2012). Data regarding patient demographics and clinical, laboratory, and in-hospital measures, as well as neuroradiological data, were retrieved from institutional databases. Functional outcome was assessed at 3 and 12 months using the modified Rankin Scale (mRS) score and categorized into favorable (mRS score 0-2) and unfavorable (mRS score 3-6). Patients' radiological and laboratory characteristics were compared between aSAH patients with favorable and those with unfavorable outcome at 3 months. In addition, multivariate analysis was conducted to investigate parameters independently associated with favorable outcome. Receiver operating characteristic (ROC) curve analysis was undertaken to identify the best cutoff for NLR to discriminate between favorable and unfavorable outcome in these patients. To account for imbalances in baseline characteristics, propensity score matching was carried out to assess the influence of NLR on outcome measures.RESULTSOverall, 319 patients with aSAH were included. Patients with unfavorable outcome at 3 months were older, had worse clinical status on admission (Glasgow Coma Scale score and Hunt and Hess grade), greater amount of subarachnoidal and intraventricular hemorrhage (modified Fisher Scale grade and Graeb score), and higher rates of infectious complications (pneumonia and sepsis). A significantly higher NLR on admission was observed in patients with unfavorable outcome according to mRS score (median [IQR] NLR 5.8 [3.0-10.0] for mRS score 0-2 vs NLR 8.3 [4.5-12.6] for mRS score 3-6; p < 0.001). After adjustments, NLR on admission remained a significant predictor for unfavorable outcome in SAH patients (OR [95% CI] 1.014 [1.001-1.027]; p = 0.028). In ROC analysis, an NLR of 7.05 was identified as the best cutoff value to discriminate between favorable and unfavorable outcome (area under the curve = 0.614, p < 0.001, Youden's index = 0.211; mRS score 3-6: 94/153 [61.4%] for NLR ≥ 7.05 vs 67/166 [40.4%] for NLR < 7.05; p < 0.001). Subanalysis of patients with NLR levels ≥ 7.05 vs < 7.05, performed using 2 propensity score-matched cohorts (n = 133 patients in each group), revealed an increased proportion of patients with unfavorable functional outcome at 3 months in patients with NLR ≥ 7.05 (mRS score 3-6 at 3 months: NLR ≥ 7.05 82/133 [61.7%] vs NLR < 7.05 62/133 [46.6%]; p = 0.014), yet without differences in mortality at 3 months (NLR ≥ 7.05 37/133 [27.8%] vs NLR < 7.05 27/133 [20.3%]; p = 0.131).CONCLUSIONSAmong aSAH patients, NLR represents an independent parameter associated with unfavorable functional outcome. Whether the impact of NLR on functional outcome is related to preexisting comorbidities or represents independent causal relationships in the context of stroke-associated immunosuppression should be investigated in future studies.
EVALuna2:204508

New Clinical and Morphologic Aspects in Trigeminal Neuralgia - Tanrikulu, Levent; Hastreiter, Peter; Bassemir, Teresa; Bischoff, Barbara; Buchfelder, Michael; Dörfler, Arnd; Naraghi, Ramin (World Neurosurgery, 2016)
OBJECTIVE: High-resolution magnetic resonance imaging can be used to delineate the morphology of neurovascular compression (NVC) in detail. This study focuses on essential morphologic parameters in relation to the clinical appearance of patients with trigeminal neuralgia (TN). METHODS: A total of 180 patients with TN underwent magnetic resonance-constructive interference in steady state/time of flight. Parameters of the affected nerves (length) and causative vessels were examined: (1) the relationship between the NVC site (caudal/cranial/laterocaudal/mediocranial) and affected area (V1, V2, V3); (2) nerve deformity; (3) vascular loop; (4) existence of a "cerebrospinal fluid (CSF) sign" by a separation of trigeminal fascicles by a vessel; and (5) localization of the causative vessel. RESULTS: A total of 10 patients with V1 affection showed 6 caudal, 0 cranial and laterocaudal, and 4 mediocranial NVC; 26 patients with V2 affection showed 17 caudal, 0 cranial, 1 laterocaudal, and 8 mediocranial NVC; 29 patients with V3 affection showed 23 caudal, 1 cranial, 3 laterocaudal, and 2 mediocranial NVC; 25 patients with V1 and V2 affection showed 17 caudal, 1 cranial, 0 laterocaudal, and 7 mediocranial NVC; 36 patients with V2 and V3 affection showed 30 caudal, 3 cranial, 1 laterocaudal, and 2 mediocranial NVC; and 6 patients with V1, V2, and V3 affection showed 4 caudal, 1 cranial, 0 laterocaudal, and 1 mediocranial NVC. A total of 63 patients (35%) showed nerval deformity by distorsion of the trigeminal fascicles from compressing vessel; 37 of 39 patients (95%) with right-sided deformity showed right-sided TN; and 21 of 22 patients (95%) with left-sided TN showed left-sided nerve deformation. Two patients with bilateral nerve deformity showed bilateral TN. Rostral superior cerebellar artery (SCA) loop compression was seen in 24 patients (17%), caudal SCA loop compression was seen in 10 patients (7%), and double SCA loop compression was seen in 33 patients (23%). Sandwich compression was seen in 18 (12%), and a CSF sign was seen in 24 patients. All 24 patients (100%) with a CSF sign had V1 affection. CONCLUSIONS: The CSF sign is pathognomonic for V1 affection. Vascular loops from cranial on the nerve were the most frequent types of compression in all areas of pain, followed by mediocranial loops. This evaluation is reproducible and contributes to the role of magnetic resonance imaging and a classification of findings in the preoperative evaluation of NVC.
EVALuna2:33152

New Perspectives for Spinal Cord Stimulation in Parkinson’s Disease-Associated Gait Impairment: A Systematic Review - Seufert, Christian; Borutta, Matthias; Regensburger, Martin; Zhao, Yining; Kinfe, Thomas Mehari (Biomedicines, 2024)
Parkinson’s Disease is a neurodegenerative disorder manifesting itself as a hypokinetic movement impairment with postural instability and gait disturbance. In case of failure and/or limited response, deep brain stimulation has been established as an alternative and effective treatment modality. However, a subset of PD patients with gait impairment represents a therapeutic challenge. A systematic review (2000–2023) was performed using PubMed, Embase, Web of Science, Scopus, and Cochrane Library databases to determine the efficacy, stimulation waveform/parameters, spine level, and outcome measures of spinal cord stimulation using different waveforms in PD patients with and without chronic pain. Spinal cord stimulation responsiveness was assessed within the pre-defined follow-up period in three groups (short-term follow-up = 0–3 months; intermediate follow-up = 3–12 months; and long-term follow-up = more than 12 months). In addition, we briefly outline alternative neurostimulation therapies and the most recent developments in closed-loop spinal cord stimulation relevant to PD. In summary, 18 publications and 70 patients from uncontrolled observational trials were included, with low-quality evidence and conflicting findings. First and foremost, the currently available data do not support the use of spinal cord stimulation to treat PD-related gait disorders but have confirmed its usefulness for PD-associated chronic pain.
CRIS-Team Scopus Importer:2024-09-06
Keywords: deep brain stimulation; freezing of gait; gait dysfunction; motor symptoms; movement disorders; neurodegenerative disorders; neuromodulation; neurostimulation; Parkinson’s Disease; spinal cord stimulation

No evidence for human papillomavirus infection in focal cortical dysplasia IIb - Coras, Roland; Korn, Klaus; Bien, Christian G.; Kalbhenn, Thilo; Roessler, Karl; Kobow, Katja; Giedl, Josef; Fleckenstein, Bernhard; Blümcke, Ingmar (Annals of Neurology, 2015)
The etiology of focal cortical dysplasia type IIb (FCDIIb) remains enigmatic in patients suffering from drug-resistant epilepsy, and an aberrant activation of the mammalian target of rapamycin complex 1 signaling pathway (mTORC1) was detected in this developmental brain malformation. Recently, the human papillomavirus (HPV) oncoprotein E6 has been identified as a potent activator of mTORC1, and HPV16 E6 has been described to persist in balloon cells obtained from surgical FCDIIb specimens. Although this observation was replicated by an independent second report, it contradicts current knowledge of HPV biology. HPV infects the squamous or mucocutaneous epithelium; hematogenic spread into other tissues has not been observed. In addition, brain carcinogenesis has never been reported in FCDIIb patients. Herein, we have tried to confirm 2 previous reports of HPV16 E6 infection using an independent series of 14 surgical specimens with histopathologically confirmed FCDIIb.Snap-frozen FCDIIb specimens were tested for HPV DNA using the primer set for amplification of the complete E6 reading frame of HPV16 and 3 other sets of primers (2 consensus primer sets detecting multiple HPV genotypes, and another primer set specifically used for HPV16). Furthermore, formalin-fixed and paraffin-embedded histopathological preparations were immunohistochemically analyzed using previously described antibodies directed against the HPV E6 oncoprotein.All 14 FCDIIb specimens were negative for HPV DNA with all 4 primer sets. Antibodies directed against the HPV E6 epitope showed weak labeling of cytoplasm in balloon cells, as previously described in FCDIIb, but also in other cell populations.Our data did not confirm previously reported evidence for HPV16 detection in FCDIIb. Ann Neurol 2015;77:312-319.
EVALuna2:6690

Non-functioning pituitary adenomas: indications for pituitary surgery and post-surgical management - Esposito, Daniela; Olsson, Daniel S.; Ragnarsson, Oskar; Buchfelder, Michael; Skoglund, Thomas; Johannsson, Gudmundur (Pituitary, 2019)
Purpose: Non-functioning pituitary adenomas (NFPAs) are associated with impaired well-being, increased comorbidities, and reduced long-term survival. Data on optimal management of NFPAs around surgical treatment are scarce, and postoperative treatment and follow-up strategies have not been evaluated in prospective trials. Here, we review the preoperative, perioperative, and early postoperative management of patients with NFPAs. Methods: We searched Medline and the Cochrane Library for articles published in English with the following items “Pituitary neoplasms AND Surgery” and “Surgery AND Hypopituitarism”. Studies containing detailed analyses of the management of NFPAs in adult patients, including pituitary surgery, endocrine care, imaging, ophthalmologic assessment and long-term outcome were reviewed. Results: Treatment options for NFPAs include active surveillance, surgical resection, and radiotherapy. Pituitary surgery is currently recommended as first-line treatment in patients with visual impairment due to adenomas compressing the optic nerves or chiasma. Radiotherapy is reserved for large tumor remnants or tumor recurrence following one or more surgical attempts. There is no consensus of optimal pre-, peri-, and postoperative management such as timing, frequency, and duration of endocrine, radiologic, and ophthalmologic assessments as well as management of smaller tumor remnants or tumor recurrence. Conclusions: In clinical practice, there is a great variation in the treatment and follow-up of patients with NFPAs. We have, based on available data, suggested an optimal management strategy for patients with NFPAs in relation to pituitary surgery. Prospective trials oriented at drawing up strategies for the management of NFPAs are needed.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Endocrine care; Hypopituitarism; Pituitary adenomas; Pituitary surgery; Surgical outcome

Non-invasive assessment of hypoxia and neovascularization with MRI for identification of aggressive breast cancer - Bennani-Baiti, Barbara; Pinker, Katja; Zimmermann, Max; Helbich, Thomas H.; Baltzer, Pascal A.; Clauser, Paola; Kapetas, Panagiotis; Bago-Horvath, Zsuzsanna; Stadlbauer, Andreas (Cancers, 2020)
The aim of this study was to investigate the potential of magnetic resonance imaging (MRI) for a non-invasive synergistic assessment of tumor microenvironment (TME) hypoxia and induced neovascularization for the identification of aggressive breast cancer. Fifty-three female patients with breast cancer underwent multiparametric breast MRI including quantitative blood-oxygen-level-dependent (qBOLD) imaging for hypoxia and vascular architecture mapping for neovascularization. Quantitative MRI biomarker maps of oxygen extraction fraction (OEF), metabolic rate of oxygen (MRO2), mitochondrial oxygen tension (mitoPO2), microvessel radius (VSI), microvessel density (MVD), and microvessel type indicator (MTI) were calculated. Histopathology was the standard of reference. Histopathological markers (vascular endothelial growth factor receptor 1 (FLT1), podoplanin, hypoxia-inducible factor 1-alpha (HIF-1alpha), carbonic anhydrase 9 (CA IX), vascular endothelial growth factor C (VEGF-C)) were used to confirm imaging biomarker findings. Univariate and multivariate regression analyses were performed to differentiate less aggressive luminal from aggressive non-luminal (HER2-positive, triple negative) malignancies and assess the interplay between hypoxia and neoangiogenesis markers. Aggressive non-luminal cancers (n = 40) presented with significantly higher MRO2 (i.e., oxygen consumption), lower mitoPO2 values (i.e., hypoxia), lower MTI, and higher MVD than less aggressive cancers (n = 13). Data suggest that a model derived from OEF, mitoPO2, and MVD can predict tumor proliferation rate. This novel MRI approach, which can be easily implemented in routine breast MRI exams, aids in the non-invasive identification of aggressive breast cancer.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Breast cancer; Hypoxia; Magnetic resonance imaging; Neovascularization; Tumor aggressiveness

Non-invasive estimation of muscle fibre size from high-density electromyography - Casolo, Andrea; Maeo, Sumiaki; Balshaw, Thomas G.; Lanza, Marcel B.; Martin, Neil R. W.; Nuccio, Stefano; Moro, Tatiana; Paoli, Antonio; Felici, Francesco; Maffulli, Nicola; Eskofier, Björn; Kinfe, Thomas Mehari; et al. (The Journal of Physiology, 2023)
Abstract: Because of the biophysical relation between muscle fibre diameter and the propagation velocity of action potentials along the muscle fibres, motor unit conduction velocity could be a non-invasive index of muscle fibre size in humans. However, the relation between motor unit conduction velocity and fibre size has been only assessed indirectly in animal models and in human patients with invasive intramuscular EMG recordings, or it has been mathematically derived from computer simulations. By combining advanced non-invasive techniques to record motor unit activity in vivo, i.e. high-density surface EMG, with the gold standard technique for muscle tissue sampling, i.e. muscle biopsy, here we investigated the relation between the conduction velocity of populations of motor units identified from the biceps brachii muscle, and muscle fibre diameter. We demonstrate the possibility of predicting muscle fibre diameter (R2 = 0.66) and cross-sectional area (R2 = 0.65) from conduction velocity estimates with low systematic bias (∼2% and ∼4% respectively) and a relatively low margin of individual error (∼8% and ∼16%, respectively). The proposed neuromuscular interface opens new perspectives in the use of high-density EMG as a non-invasive tool to estimate muscle fibre size without the need of surgical biopsy sampling. The non-invasive nature of high-density surface EMG for the assessment of muscle fibre size may be useful in studies monitoring child development, ageing, space and exercise physiology, although the applicability and validity of the proposed methodology need to be more directly assessed in these specific populations by future studies. (Figure presented.). Key points: Because of the biophysical relation between muscle fibre size and the propagation velocity of action potentials along the sarcolemma, motor unit conduction velocity could represent a potential non-invasive candidate for estimating muscle fibre size in vivo. This relation has been previously assessed in animal models and humans with invasive techniques, or it has been mathematically derived from simulations. By combining high-density surface EMG with muscle biopsy, here we explored the relation between the conduction velocity of populations of motor units and muscle fibre size in healthy individuals. Our results confirmed that motor unit conduction velocity can be considered as a novel biomarker of fibre size, which can be adopted to predict muscle fibre diameter and cross-sectional area with low systematic bias and margin of individual error. The proposed neuromuscular interface opens new perspectives in the use of high-density EMG as a non-invasive tool to estimate muscle fibre size without the need of surgical biopsy sampling.
CRIS-Team Scopus Importer:2023-04-21
Keywords: conduction velocity; high-density surface electromyography; motor unit; muscle fibre size

Non-Phosphorylated Tau as a Potential Biomarker of Alzheimer's Disease: Analytical and Diagnostic Characterization - Lewczuk, Piotr; Lelental, Natalia; Lachmann, Ingolf; Holzer, Max; Flach, Katharina; Brandner, Sebastian; Engelborghs, Sebastiaan; Teunissen, Charlotte E.; Zetterberg, Henrik; Luis Molinuevo, Jose; Mroczko, Barbara; Blennow, Kaj; et al. (Journal of Alzheimer's Disease, 2017)
BACKGROUND: Virtually nothing is known about a potential diagnostic role of non-phospho-epitopes of Tau (Non-P-Tau) in cerebrospinal fluid (CSF). OBJECTIVE: To establish and analytically and clinically characterize the first assay capable to measure concentrations of Non-P-Tau in human CSF. METHODS: An antibody (1G2) was developed that selectively binds to the Tau molecule non-phosphorylated at the positions T175 and T181, and was used in establishing a sandwich ELISA capable to measure Non-P-Tau in human CSF, following analytical and clinical validation of the method. RESULTS: The 1G2 antibody shows decreasing reactivity to tau peptides containing phosphorylation mainly at positions T175 and T181. Detection limit of the assay is 25 pg/ml; the coefficients of variation (CVs) of the optical densities of the repeated standard curves were between 3.6-15.9%. Median intra-assay imprecision of double measurements was 4.8%; inter-assay imprecision was in the range of 11.2% - 15.3%. Non-P-Tau concentrations are stable in the CSF samples sent to distinct laboratories under ambient temperature; inter-laboratory variation was approximately 30%. The Non-P-Tau CSF concentrations were highly significantly increased in patients with Alzheimer's disease in stage of mild cognitive impairment or dementia (AD/MCI, n = 58, 109.2±32.0 pg/mL) compared to the non-demented Controls (n = 42, 62.1±9.3 pg/mL, p < 0.001). At the cut-off of 78.3 pg/mL, the sensitivity and the specificity were 94.8% and 97.6%, respectively. CONCLUSION: For the first time, an assay is reported to reliably measure concentrations of non-phosphorylated Tau in human CSF.
EVALuna2:33506

Non-professional Phagocytes can phagocytize Necrotic Cells at any Stage of the Cell Cycle - Hofmann, Andrea; Seeberg, Jacob; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Normal Variants in Magnetoencephalography - Rampp, Stefan; Kakisaka, Yosuke; Shibata, Sumiya; Wu, Xueqing; Rössler, Karl; Buchfelder, Michael; Burgess, Richard C. (Journal of Clinical Neurophysiology, 2020)
Normal variants, although not occurring frequently, may appear similar to epileptic activity. Misinterpretation may lead to false diagnoses. In the context of presurgical evaluation, normal variants may lead to mislocalizations with severe impact on the viability and success of surgical therapy. While the different variants are well known in EEG, little has been published in regard to their appearance in magnetoencephalography. Furthermore, there are some magnetoencephalography normal variants that have no counterparts in EEG. This article reviews benign epileptiform variants and provides examples in EEG and magnetoencephalography. In addition, the potential of oscillatory configurations in different frequency bands to appear as epileptic activity is discussed.
CRIS-Team Scopus Importer:2020-11-20

Not Simply a Structural Problem: Psychological Determinants of Headache in Patients with Tumors of the Sellar Region - Siegel, Sonja; Schenk, Thomas; Brabant, Georg; Scholl, Renata Carneiro; Buchfelder, Michael; Kreitschmann-Andermahr, Ilonka (Experimental and Clinical Endocrinology and Diabetes, 2022)
Objective Headache in patients with tumors of the sellar region (TSR) has previously been attributed entirely to biomechanical causes. This study aimed to investigate the influence of psychological determinants for the occurrence of and disability due to headaches in patients with TSR. Methods This was a cross-sectional single-center study with a logistic regression approach. Eighty-four patients (75%) with pituitary adenomas and 28 with other TSR prior to first-time neurosurgery were investigated. One-hundred and twelve patients received standardized questionnaires on personality, headache characteristics, and disability due to headache. Fifty-nine patients additionally filled in questionnaires about coping with stress and pain catastrophizing. Separate logistic regression models were used to predict the risk of headache occurrence and disability due to headache by personality, stress coping, and pain catastrophizing. Results Conscientiousness, neuroticism, and pain catastrophizing were significant predictors of headache occurrence. The amount of explained variance for both models predicting headache occurrence was comparable to that in primary headache. Neuroticism, pain catastrophizing, and humor as a coping strategy predicted disability due to headache with a high variance explanation of 20-40%. Conclusion For the first time, we report data supporting a strong psychological influence on headache and headache-related disability in patients with TSR, which argue against purely mechanistic explanatory models. Physicians treating patients with TSR and headaches should adopt an integrative diagnostic and treatment approach, taking the biopsychosocial model of pain into account.
CRIS-Team WoS Importer:2022-09-02

Novel Techniques in the Surgical Treatment of Acromegaly: Applications and Efficacy - Buchfelder, Michael; Schlaffer, Sven-Martin (Neuroendocrinology, 2016)
Since the establishment of transsphenoidal microsurgery as the operative treatment of choice in most patients with acromegaly 40 years ago, a few novel technical developments have evolved. Their application, utility and efficacy will be briefly discussed in this review article, based on an analysis of published results and the authors' personal experience. The endoscope was additionally used to search for residual tumours in locations which could not be visualised with the operating microscope. In many centres it has by now fully replaced the operating microscope. Extended endoscopic operations hardly have limits in respect to accessible pathology. Overall, the results and complications reported from microsurgical and endoscopic series are comparable. Intraoperative magnetic resonance imaging allows depicting the completeness of a tumour resection. While in many patients additional tumour resections are performed on the basis of intraoperative imaging, the improvements in hormonal remission rates reported are less impressive. Neuronavigation uses imaging data to improve the surgeon's orientation, and it is certainly a major asset to the inexperienced. In high-caseload centres it is mainly appreciated in anatomical variants and reoperations. While the Doppler probe is a valuable and easily affordable gadget to avoid vascular arterial injury, intraoperative ultrasound imaging of tumour extension has a much poorer resolution than magnetic resonance imaging and is thus not widely implemented. The clinical value of intraoperative growth hormone measurements is controversially discussed. In summary, the application of modern technology has only led to a minor improvement of results, but it has widened the spectrum of accessible pathologies and increased the safety of the procedures for the patient. It is expected that outcomes will continue to improve as novel techniques and concepts are being developed.
EVALuna2:22871

Nrf2-Keap1 pathway promotes cell proliferation and diminishes ferroptosis - Fan, Zheng; Wirth, A-K; Chen, Daishi; Wruck, C. J.; Rauh, Manfred; Buchfelder, Michael; Savaskan, Nicolai (Oncogenesis, 2017)
Cancer cells are hallmarked by high proliferation and imbalanced redox consumption and signaling. Various oncogenic pathways such as proliferation and evading cell death converge on redox-dependent signaling processes. Nrf2 is a key regulator in these redox-dependent events and operates in cytoprotection, drug metabolism and malignant progression in cancer cells. Here, we show that patients with primary malignant brain tumors (glioblastomas, WHO °IV gliomas, GBM) have a devastating outcome and overall reduced survival when Nrf2 levels are upregulated. Nrf2 overexpression or Keap1 knockdown in glioma cells accelerate proliferation and oncogenic transformation. Further, activation of the Nrf2-Keap1 signaling upregulates xCT (aka SLC7A11 or system Xc-) and amplifies glutamate secretion thereby impacting on the tumor microenvironment. Moreover, both fostered Nrf2 expression and conversely Keap1 inhibition promote resistance to ferroptosis. Altogether, the Nrf2-Keap1 pathway operates as a switch for malignancy in gliomas promoting cell proliferation and resistance to cell death processes such as ferroptosis. Our data demonstrate that the Nrf2-Keap1 pathway is critical for cancer cell growth and operates on xCT. Nrf2 presents the Achilles' heel of cancer cells and thus provides a valid therapeutic target for sensitizing cancer for chemotherapeutics.
EVALuna2:34244

One EEG, one read – A manifesto towards reducing interrater variability among experts - Nascimento, Fábio A.; Jing, Jin; Beniczky, Sándor; Benbadis, Selim R.; Gavvala, Jay R.; Yacubian, Elza M.T.; Wiebe, Samuel; Rampp, Stefan; van Putten, Michel J.A.M.; Tripathi, Manjari; Cook, Mark J.; Kaplan, Peter W.; et al. (Clinical Neurophysiology, 2022)
CRIS-Team Scopus Importer:2021-11-26

One hundred years of EEG for brain and behaviour research - Mushtaq, Faisal; Welke, Dominik; Gallagher, Anne; Pavlov, Yuri G.; Kouara, Layla; Bosch-Bayard, Jorge; van den Bosch, Jasper J.F.; Arvaneh, Mahnaz; Bland, Amy R.; Chaumon, Maximilien; Borck, Cornelius; He, Xun; et al. (Nature Human Behaviour, 2024)
On the centenary of the first human EEG recording, more than 500 experts reflect on the impact that this discovery has had on our understanding of the brain and behaviour. We document their priorities and call for collective action focusing on validity, democratization and responsibility to realize the potential of EEG in science and society over the next 100 years.
CRIS-Team Scopus Importer:2024-09-06

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

Optimal choice of antiseizure medication: Agreement among experts and validation of a web-based decision support application - Beniczky, Sándor; Rampp, Stefan; Asadi-Pooya, Ali A.; Rubboli, Guido; Perucca, Emilio; Sperling, Michael R. (Epilepsia, 2020)
Objective: Optimal choice of antiseizure medication (ASM) depends on seizure type, syndrome, age, gender, comorbidities and co-medications. There are no fixed rules on how to weigh these factors; choices are subjective and experience-driven. We investigated agreement among experts in selecting ASM as monotherapy and used their prevailing choices to validate a web-based decision-support application. Methods: Twenty-four international experts, blinded to the app, selected the optimal ASM for 25 individual patient-cases covering a wide variation of seizure types and other factors influencing ASM selection. The app ranked ASMs in order of likely appropriateness for each case. In a second step, experts rated anonymously the choices of the app. Results: Of the 25 patient-cases (age 13-74 years), 13 were female, 18 (72%) had comorbidities, six (24%) were on contraceptives, and 13 (52%) had other co-medications. The median number of experts who selected the same ASM for a given case was 15 (62.5%) and interquartile range (IQR) 13-18 (54%-75%). Gwet's agreement coefficient among experts was 0.38 (95% confidence interval [CI] 0.32-0.44), corresponding to a "fair" agreement. Agreement between the app and the prevailing expert choice for each case was 0.48 (95% CI 0.29-0.67), corresponding to a “moderate” beyond chance agreement. The percent agreement between the highest ranked selections of the app and the expert selections was 73% (95% CI 64%-82%). Ninety-five percent of the experts considered that no incorrect or potentially harmful ASMs were ranked highest by the app, and most experts strongly agreed with the app's selections. Significance: This app, now validated by experts, provides an objective, reproducible method for selecting ASM that accounts for relevant clinical features. It is freely available at: https://epipick.org.
CRIS-Team Scopus Importer:2020-12-11
Keywords: algorithm; antiepileptic drugs; antiseizure medication; decision support system; standardization

Optimized angiographic computed tomography with intravenous contrast injection: An alternative to conventional angiography in the follow-up of clipped aneurysms? Clinical article - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver; Saake, Marc; Lücking, Hannes; Rösch, Julie; Knossalla, Frauke; Dörfler, Arnd (Journal of Neurosurgery, 2012)
Object. The purpose of this study was to evaluate the diagnostic accuracy of an optimized angiographic CT (ACT) program with intravenous contrast agent injection (ivACT) in the assessment of potential aneurysm remnants after neurosurgical clipping compared with conventional digital subtraction angiography (DSA). Methods. The authors report on 14 patients with 19 surgically clipped cerebral aneurysms who were scheduled to undergo angiographic follow-up. For each patient, the authors performed ivACT with dual rotational acquisition and conventional angiography including a 3D rotational run. The ivACT and 3D DSA data were reconstructed with different imaging modes, including a newly implemented subtraction mode with motion correction. Thereafter, the data sets were merged by the dual-volume technique, and freely rotatable 3D images were obtained for further analysis. Observed aneurysm remnants were electronically measured and classified for each modality by 2 experienced neuroradiologists. Results. Digital subtraction angiography and ivACT both provided high-quality images without motion artifacts. Artifact disturbances from the aneurysm clips led to a compromised, but still sufficient, image quality in 1 case. The ivACT assessed all aneurysm remnants as true-positive up to a minimal size of 2.6 x 2.4 mm in accordance with the DSA findings. There was a tendency for ivACT to overestimate the size of the aneurysm remnants. All cases without aneurysm remnants on DSA were scored correctly as true-negative by ivACT. Conclusions. By using an optimized image acquisition protocol as well as enhanced postprocessing algorithms, the noninvasive ivACT seems to achieve results comparable to those of conventional angiography in the follow-up of clipped cerebral aneurysms. The authors have shown that ivACT can provide reliable diagnostic information about potential aneurysm remnants after neurosurgical clipping with high sensitivity and specificity, sufficient for clinical decision making, at least for aneurysms in the anterior circulation located distal to the internal carotid artery. These preliminary results may be a promising step to replace conventional angiography by a noninvasive imaging technique in selected cases after aneurysm clipping.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Aneurysm clipping; Angiographic computed tomography; Follow-up imaging; Noninvasive imaging; Vascular disorders

Optimized angiographic CT using intravenous contrast injection: a noninvasive imaging option for the follow-up of coiled aneurysms? - Gölitz, Philipp; Struffert, Tobias; Kaschka, Iris; Roessler, Karl; Knossalla, F.; Dörfler, Arnd (American Journal of Neuroradiology, 2014)
Because recanalization of coiled cerebral aneurysms is reported to occur, follow-up imaging is mandatory, ideally noninvasively. Our study aimed to evaluate the accuracy of an optimized angiographic CT by using intravenous contrast material injection in the assessment of coiled cerebral aneurysms, compared with MR angiography and digital subtraction angiography, the criterion standard.We included 69 patients with 76 coiled cerebral aneurysms. In each patient, we performed an angiographic CT with intravenous contrast material injection with a dual rotational acquisition, a time-of-flight MR angiography, and a DSA. The angiographic CT with intravenous contrast material injection data was postprocessed by using newly implemented reconstructions modes and a dual-volume technique. An aneurysm occlusion rate was assessed in angiographic CT with intravenous contrast material injection and MRA; remnants were measured and correlated with DSA, respectively.Twenty-eight remnants were revealed by DSA with a mean size of 3.1 × 3.1 mm. Angiographic CT with intravenous contrast material injection demonstrated a sensitivity of 93% and a specificity of 96% in remnant detection. MRA showed almost identical accuracy (sensitivity of 93%, specificity of 100%). Assessment of remnant size by angiographic CT with intravenous contrast material injection and by MRA revealed a high significant correlation with DSA, respectively (P < .001).Optimized angiographic CT with intravenous contrast material injection and MRA demonstrated accuracy comparable with that of DSA in the follow-up of coiled aneurysms, respectively. The assessment of remnant size showed a high correlation with DSA for both techniques. Due to the lack of radiation exposure, MRA seems to be the preferred technique. However, angiographic CT with intravenous contrast material injection can be considered a reliable, noninvasive alternative in patients with MR imaging contraindications or in cases of compromising artifacts due to metal implants (ie, clips).
EVALuna2:22327

Optimized set of criteria for defining interictal epileptiform EEG discharges - Kural, Mustafa Aykut; Tankisi, Hatice; Duez, Lene; Sejer Hansen, Vibeke; Udupi, Aparna; Wennberg, Richard; Rampp, Stefan; Larsson, Pål G.; Schulz, Reinhard; Beniczky, Sándor (Clinical Neurophysiology, 2020)
Objective: To find and validate the optimal combination of criteria that define interictal epileptiform EEG discharges (IEDs). Our target was a specificity over 95%, to avoid over-reading in clinical EEG. Methods: We constructed 63 combinations of the six criteria from the operational definition of IEDs, recently issued in the EEG-glossary of the International Federation of Clinical Neurophysiology (IFCN). The diagnostic gold standard was derived from video-EEG recordings. In a testing EEG dataset from 100 patients, we selected the best performing combinations of criteria and then we validated them in an independent dataset from 70 patients. We compared their performance with subjective, expert-scorings and we determined inter-rater agreement (IRA). Results: Without using criteria, the specificity of expert-scorings was lower than the pre-defined threshold (86%). The best performing combination of criteria was the following: waves with spiky morphology, followed by a slow-afterwave and voltage map suggesting a source in the brain. In the validation dataset this achieved a specificity of 97% and a sensitivity of 89%. IRA was substantial. Conclusions: The optimized set of criteria for defining IEDs has high accuracy and IRA. Significance: Using these criteria will contribute to decreasing over-reading of EEG and avoid misdiagnosis of epilepsy.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Criteria; Definition; Diagnostic accuracy EEG; Interictal epileptiform discharges

Optimizing contrast-enhanced magnetic resonance imaging characterization of brain metastases: Relevance to stereotactic radiosurgery - Anzalone, Nicoletta; Essig, Marco; Lee, Seung-Koo; Dörfler, Arnd; Ganslandt, Oliver; Combs, Stephanie E.; Picozzi, Piero (Neurosurgery, 2013)
Intracranial metastases are the most common form of intra-axial brain tumor. Management approaches to brain metastases include surgical resection, whole-brain radiotherapy, and stereotactic radiosurgery (SRS). The management approach that is selected is based typically on algorithms that incorporate the number, size, and location of lesions. SRS is the treatment of choice when metastases detected on imaging are few (maximum, 3-5) and/or of small size (≤30 mm) and offers the advantages of noninvasiveness and the ability to treat inaccessible lesions compared with surgical resection. Contrast-enhanced magnetic resonance imaging (MRI) is the standard imaging technique for determining the number, size, and location of metastatic lesions. In SRS, the capability of MRI to delineate lesion borders precisely in 3 dimensions helps reduce recurrence rates and minimize radiation necrosis in surrounding tissue. Optimization of the MRI protocol, including selection of the appropriate gadolinium-based contrast agent (GBCA), is paramount for accurate lesion imaging. GBCAs differ in their safety, tolerability, and efficacy because of their diverse physicochemical properties. Gadobutrol and gadobenate dimeglumine are high-relaxivity GBCAs that demonstrate superior efficacy for imaging metastatic lesions compared with other GBCAs, whereas gadobutrol additionally provides macrocyclic stability. This article reviews recent comparative trials of GBCAs and discusses their relevance for optimizing MRI protocols in the management of brain metastases, with particular relevance to SRS. ABBREVIATIONS:: CNR, contrast-to-noise ratioCNS, central nervous systemGBCA, gadolinium-based contrast agentNSF, nephrogenic systemic fibrosisSRS, stereotactic radiosurgeryWBRT, whole-brain radiotherapy. © 2013 by the Congress of Neurological Surgeons.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain metastases; Gadobutrol; Gadolinium-based contrast media; MRI; Stereotactic radiosurgery

"Original Research" instead research Neural networks for estimation of facial palsy after vestibular schwannoma surgery - Rampp, Stefan; Holze, Magdalena; Scheller, Christian; Strauss, Christian; Prell, Julian (Journal of Clinical Monitoring and Computing, 2022)
Purpose Facial nerve damage in vestibular schwannoma surgery is associated with A-train patterns in free-running EMG, correlating with the degree of postoperative facial palsy. However, anatomy, preoperative functional status, tumor size and occurrence of A-trains clusters, i.e., sudden A-trains in most channels may further contribute. In the presented study, we examine neural networks to estimate postoperative facial function based on such features. Methods Data from 200 consecutive patients were used to train neural feed-forward networks (NN). Estimated and clinical postoperative House and Brackmann (HB) grades were compared. Different input sets were evaluated. Results Networks based on traintime, preoperative HB grade and tumor size achieved good estimation of postoperative HB grades (chi(2) = 54.8), compared to using tumor size or mean traintime alone (chi(2) = 30.6 and 31.9). Separate intermediate nerve or detection of A-train clusters did not improve performance. Removal of A-train cluster traintime improved results (chi(2) = 54.8 vs. 51.3) in patients without separate intermediate nerve. Conclusion NN based on preoperative HB, traintime and tumor size provide good estimations of postoperative HB. The method is amenable to real-time implementation and supports integration of information from different sources. NN could enable multimodal facial nerve monitoring and improve postoperative outcomes.
CRIS-Team WoS Importer:2022-11-18

Oro-dental pathologies in acromegaly - Kreitschmann-Andermahr, Ilonka; Kohlmann, Johannes; Kleist, Bernadette; Hirschfelder, Ursula; Buslei, Rolf; Buchfelder, Michael; Siegel, Sonja (Endocrine, 2018)
PURPOSE: Oro-dental pathologies (ODP) such as enlargement of the tongue, mandibular prognathism, and spaced teeth are characteristic features of acromegaly. Their frequency of occurrence during the course of the disease is largely unresolved. Purpose of this study was to assess ODP and oro-dental treatments in patients with acromegaly with regard to the length of the diagnostic process, tumor histology, and quality of life (QoL). METHODS: Single-center retrospective survey study using questionnaires on dental symptoms, diagnostic process, and treatment in patients with acromegaly operated on a growth hormone-secreting pituitary adenoma. The association between ODP and QoL was assessed using the Short-Form 36 (SF-36) Health Survey. RESULTS: 145/314 patients completed the questionnaires. 80.7% were affected by any ODP, most frequently enlargement of the tongue (57.9%), spaced teeth (42.8%), mandibular growth (24.1%), and mandibular prognathism (22.1%). ODP were significantly more frequent in patients with sparsely vs. densely granulated adenomas (p = 0.045). Early diagnosis within 2 years was associated with significantly fewer ODP than later diagnosis (68.5 vs. 87.2%, p = 0.009). Treatments included dental crowns (16.6%), dental bridges (12.4%), dental implants (9.7%), dental prostheses (3.4%), orthodontal (i.e., braces, 6.9%), and surgical correction of the teeth (2.1%). Physical QoL was significantly lower in patients with ODP than in those without (p = 0.014). CONCLUSION: In our large series of patients, four of five patients were affected by ODP at any time during the course of the disease. The results highlight the importance of early identification and treatment of oro-dental problems in patients with acromegaly as hallmarks of the disease.
EVALuna2:36585

Pallidal Deep Brain Stimulation in Patients with Prior Bilateral Pallidotomy and Selective Peripheral Denervation for Treatment of Dystonia - Saryyeva, Assel; Capelle, Hans-Holger; Kinfe, Thomas Mehari; Schrader, Christoph; Krauss, Joachim K. (Stereotactic and Functional Neurosurgery, 2020)
Introduction: Deep brain stimulation (DBS) of the globus pallidus internus has become an accepted treatment for severe isolated idiopathic and inherited dystonia. Patients who had other forms of surgery earlier, such as radiofrequency lesioning or selective peripheral denervation, however, usually are not considered candidates for DBS. Objective: The aim of this study was to evaluate the long-term outcome of pallidal DBS in a rare subgroup of patients who had undergone both pallidotomy and selective peripheral denervation previously with a waning effect over the years. Methods: Pallidal DBS was performed according to a prospective study protocol in 2 patients with isolated idiopathic dystonia, and patients were followed for a period of at least 6 years. Results: Both patients benefitted from long-lasting amelioration of dystonia after pallidal DBS, which was comparable to that of patients who did not have previous surgeries. In a 62-year-old female with cervical dystonia both the Burke-Fahn-Marsden (BFM) and the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) motor scores were improved at follow-up 8 years after surgery (50 and 39%). In a 32-year-old male with generalized dystonia, the BFM motor and disability scores showed marked improvement at 6.5 years of follow-up (82 and 66%). Conclusions: Pallidal DBS can yield marked and long-lasting improvement in patients who underwent both pallidotomy and selective peripheral denervation earlier. Therefore, such patients, in general, should not be excluded from DBS.<br
Keywords: Deep brain stimulation; Dystonia; Globus pallidus; Long-term outcome; Pallidotomy; Peripheral denervation

Papillary tumor of the pineal region with anaplastic small cell component - Heim, Stephanie; Coras, Roland; Ganslandt, Oliver; Kufeld, Markus; Blümcke, Ingmar; Paulus, Werner; Hasselblatt, Martin (Journal of Neuro-Oncology, 2013)
CRIS-Team Scopus Importer:2022-08-05

Papilledema and Echographically Detectable Retro-orbital Dilatation of the Sub-arachnoidal Space with open Fontanelle - Six Case Reports - Gusek-Schneider, G. C.; Mardin, Christian Y.; Trollmann, Regina; Eyüpoglu, Ilker Yasin; Ganslandt, Oliver Thomas (Klinische Monatsblätter für Augenheilkunde, 2011)
This paper analyses the case reports for three children in which a papilledema occurred before the age of one year. Furthermore, an analysis is also given of three further case reports for children aged less than one year in which, in spite of open fontanelle, no papilledema was found, however, a dilatation of the sub-arachnoidal space was demonstrated echographically. Even in children less than one year of age in which an open fontanelle still exists and in whom a neuro-paediatric clarification of internal hydrocepalus is made, in spite of opththalmoscopically inconspicuous findings for the papilla an echography is indispensable for the evaluation of the sub-arachnoidal space. Here, the early recognition of a dilatation of the retro-bulbar sub-arachnoidal space can possibly prevent the occurrence of a consecutive optic atrophy. At the present time, the data available do not allow the recommendation of an upper age limit for an echographic examination.
EVALuna2:21040

Parametric color coding of digital subtraction angiography in the evaluation of carotid cavernous fistulas - Gölitz, Philipp; Struffert, Tobias; Lücking, Hannes; Roesch, J.; Knossalla, F.; Ganslandt, Oliver; Deuerling-Zheng, Y.; Dörfler, Arnd (Clinical Neuroradiology, 2013)
Purpose: Angiographic assessment of carotid cavernous fistulas (CCFs) can be complex. Our purpose was to examine whether the use of parametric color coding in the postprocessing of DSA series is advantageous in the evaluation of CCFs. Methods: We enrolled 16 patients with angiographically proven CCFs. Endovascular treatment was performed in 14 cases. For postprocessing of digital subtraction angiography (DSA) series, a newly implemented algorithm of parametric color coding was used, turning sequential images of two-dimensional (2D)-DSA series into a single color-coded image. Angiographic data of initial, interventional, and postinterventional 2D-DSA series were compared with color-coded images. Whether parametric color coding could facilitate evaluation of fistula architecture and provide a more precise estimation of fistula venous drainage patterns as well as whether flow analysis could reveal objective changes during and after treatment were investigated. Results: In 56 % of the cases, parametric color coding was observed to facilitate visualization of fistula angioarchitecture. Estimation of fistula drainage flow patterns was considered to be improved in 31 % of the cases. For assessment of hemodynamic changes during and after treatment, parametric color coding was assumed to be helpful in 21 % of the cases, especially because revealing flow changes that were not visible on 2D-DSA series were now visible. Conclusions: Parametric color coding is a fast application tool that might provide additional support in the angiographic evaluation of CCFs. Visualization of complex fistula architecture could be facilitated, and flow analysis might improve assessment of venous drainage patterns, thereby increasing overall diagnostic confidence. During and after treatment, hemodynamic changes that were not visible on 2D-DSA series could now be depicted. © 2012 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cerebrovascular disease; Digital subtraction angiography; Endovascular treatment; Image postprocessing

Parasellar Meningiomas - Graillon, Thomas; Regis, Jean; Barlier, Anne; Brue, Thierry; Dufour, Henry; Buchfelder, Michael (Neuroendocrinology, 2020)
Parasellar spaces remain particularly singular, comprising the most important neurovascular structures such as the internal carotid artery and optic, oculomotor, and trigeminal nerves. Meningiomas are one of the most frequent tumors arising from parasellar spaces. In this location, meningiomas remain mostly benign tumors with WHO grade I and a meningothelial subtype. Progestin intake should be investigated and leads mostly to conservative strategies. In the case of benign nonsymptomatic tumors, observation should be proposed. Tumor growth will lead to the proposition of surgery or radiosurgery. In the case of an uncertain diagnosis and an aggressive pattern, a precise diagnosis is required. For cavernous sinus and Meckel's cave lesions, complete removal is rarely considered, leading to the proposition of an endoscopic endonasal or transcranial biopsy. Optic nerve decompression could also be proposed via these approaches. A case-by-case discussion about the best approach is recommended. A transcranial approach remains necessary for tumor removal in most cases. Vascular injury could lead to severe complications. Cerebrospinal fluid leakage, meningitis, venous sacrifice, visual impairment, and cranial nerve palsies are more frequent complications. Pituitary dysfunctions are rare in preoperative assessment and in postoperative follow-up but should be assessed in the case of meningiomas located close to the pituitary axis. Long-term follow-up is required given the frequent incomplete tumor removal and the risk of delayed recurrence. Radiosurgery is relevant for small and well-limited meningiomas or intra-cavernous sinus postoperative residue, whereas radiation therapy and proton beam therapy are indicated for large, extended, nonoperable meningiomas. The place of the peptide receptor radionuclide therapyneeds to be defined. Targeted therapy should be considered in rare, recurrent, and aggressive parasellar meningiomas.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Diagnosis; Meningioma; Parasellar spaces; Surgery; Therapy

Parenchymatous hematoma in patients with atraumatic subarachnoid hemorrhage: Characteristics, treatment, and clinical outcomes - Gerner, Stefan; Hülsbrink, Robert; Reichl, Jonathan; Mrochen, Anne; Eyüpoglu, Ilker Yasin; Brandner, Sebastian; Dörfler, Arnd; Engelhorn, Tobias; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2020)
Background: Data regarding the influence of concomitant parenchymatous hematoma (PH) on long-term outcomes in patients with atraumatic subarachnoid hemorrhage (SAH) are scarce. Further, it is not established if these patients benefit from surgical intervention. Aim: The aim of this study was to determine the influence of concomitant PH in SAH patients on functional long-term outcome, and whether these patients may benefit from surgical hematoma evacuation. Methods: Over a 5-year period, all consecutive patients with SAH treated at the Departments of Neurology, Neuroradiology, and Neurosurgery, at the University Hospital Erlangen (Germany) were recorded. In addition to the clinical and imaging characteristics of SAH, we documented the presence, location, and volume of PH as well as treatment parameters. Outcome assessment at 12 months included functional outcome (modified Rankin scale (mRS), favorable = 0–2), health-related quality of life, and long-term complications. For outcome analysis, a propensity score matching (ratio 1:1, caliper 0.1) was performed to compare SAH patients with and without PH. Sub-analyses were performed regarding PH treatment (surgical evacuation vs. conservative). Results: A total of 494 patients with atraumatic SAH were available. Eighty-five (17.2%) had PH on initial imaging. SAH patients with PH had a worse clinical condition on admission and had a greater extent of subarachnoid/intraventricular hemorrhage. Median PH volume was 11.0 ml (5.4–31.8) with largest volumes observed in patients with ruptured middle cerebral artery (MCA)-aneurysm (31.7 ml (16.3–43.2)). After propensity-score matching (PSM), patients with PH had worse functional outcomes at 12 months (modified Rankin scale (mRS) 0–2: PH 31.8% vs. ØPH57.7% p < 0.001), and a lower rate of self-reported health compared to patients without PH (EQ-5D VAS: PH 50(30–70) vs. ØPH 80(65–95); p < 0.001). In PH patients, surgical evacuation was associated with a higher rate of favorable outcome at 12 months compared to those treated conservatively (surgery 14/28 (50.0%) vs. conservative 14/57 (24.6%); adjusted odds-ratio (OR; 95%CI): 1.34 (1.08–1.66); p = 0.001), irrespective of aneurysm location. Subgroup-analysis revealed positive associations of surgical hematoma evacuation with outcome in subgroups with larger PH volumes (>10 ml; OR (95%CI): 1.39 (1.09–1.79)), frontal PH location (OR 1.59 (1.14–2.23)), and early surgery (within 600 min after onset; OR 1.42 (1.03–1.94)). Conclusions: Concomitant PH occurs frequently in patients with SAH and is associated with functional impairment after 1 year. Surgical evacuation of PH may improve outcomes in these patients, irrespective of aneurysm-location.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Cerebral hemorrhage; complications; intracerebral hemorrahage; subarachnoid hemorrhage; surgery; treatment

Parenchymatous hemorrhage is associated with unfavorable longterm outcome in patients with atraumatic subarachnoid hemorrhage - Gerner, Stefan; Kuramatsu, J.; Reichl, J.; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Dörfler, Arnd; Struffert, Tobias; Schwab, Sibylle; Huttner, Hagen (2017)
EVALuna2:34024

Path to success: female leaders in German neurosurgery - Weiss, Miriam; Dogan, Rabia; Eisenberg, Ulrike; Velalakan, Aruni; Krüger, Jutta; Moritz, Ina; Nistor-Gallo, Dorothea; Flueh, Charlotte; Janz, Claudia; Ahmadi, Rezvan; Hakvoort, Karlijn; Forster, Marie Thérèse (Neurosurgical Review, 2023)
Despite advances in gender equality, only 6% of German neurosurgical departments are currently led by women. With regard to their pioneering work and the importance of their role model effect, we aimed at reporting on the career pathways of the present and former female chairs of neurosurgical departments in Germany. We approached current and former female chairs in German neurosurgery and gathered descriptive information on their ways into leadership positions through structured interviews. Data were obtained from 16/22 (72.7%) female neurosurgical chairs, aged between 44 and 82 years. They completed their training within 6.5 ± 0.6 years, and it took them further 14.5 ± 5.9 years between training completion and chair acquisition. Having obtained their chair positions between 1993 and 2020, six (37.5%) of them have retired or changed career tracks. Of ten (62.5%) chairs still practicing, two are directors of university departments. Twelve (75.0%) hold professorships. Nine chairs (56.3%) are married, eight (50.0%) having children. Five chairs reported having experienced gender-based discrimination. Twelve had a male mentor or role model, two had a female role model, while only one had a female mentor. This study characterizes the to date small number of female neurosurgical chairs in Germany and their paths to neurosurgical leadership positions. In future, these should become historical in order to perceive the presence of women in leadership positions as self-evident normality, reflecting our society. However, further analyses comparing paths of both female and male neurosurgical chairs are necessary to explore gender-based differences in achieving neurosurgical leadership positions.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Diversity; Gender; Leadership; Neurosurgery; Women

Pedicle screw instrumentation of the cervicothoracic junction in the sitting position using ct-guided navigation: Application and technical aspects - Hore, Nirjhar; Lücking, Hannes; Schmitt, Hubert; Buchfelder, Michael; Brandner, Sebastian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background We evaluate the feasibility and potential advantages of spinal CT navigation in the placement of pedicle screws at the cervicothoracic junction in the sitting position to counteract the anatomy-related limitations of 2D fluoroscopy. Methods We retrospectively analyze the data from 15 patients who underwent CT-based navigation-guided placement of a total of 36 pedicle screws at the cervicothoracic junction in the sitting position. Results CT-based spinal navigation is a useful method in increasing accuracy of pedicle screw instrumentation in the sitting position, successfully counteracting the anatomy-related limitations of 2D fluoroscopy at the cervicothoracic junction. Conclusion CT-based navigation-guided placement of pedicle screws at the cervicothoracic junction in the sitting position proved to be an accurate, safe, and user-friendly method.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Cervical spine; Sitting position; Spinal navigation

Phase-amplitude coupling measures for determination of the epileptic network: A methodological comparison - Ali, Ryshum; Gollwitzer, Stephanie; Reindl, Caroline; Hamer, Hajo; Coras, Roland; Blümcke, Ingmar; Buchfelder, Michael; Hastreiter, Peter; Rampp, Stefan (Journal of Neuroscience Methods, 2022)
CRIS-Team WoS Importer:2022-05-13
Keywords: EEG; Epilepsy; Phase-Amplitude Coupling

Physiological effects of cigarette smoking in the limbic system revealed by 3 tesla magnetic resonance spectroscopy - Mennecke, Angelika; Gossler, Andrea; Hammen, Thilo; Dörfler, Arnd; Stadlbauer, Andreas; Roesch, Julie; Kornhuber, Johannes; Bleich, Stefan; Dölken, Marc; Thürauf, Norbert (Journal of Neural Transmission, 2014)
Several studies and recent models of effects of nicotine, the main addictive and psychoactive component in tobacco, point to action of the drug on the limbic system during maintenance of addiction, either direct or indirect via projections from the ventral tegmental area. The objective of this study was to demonstrate physiological effects of cigarette smoking on the hippocampus and the grey matter of the dorsal anterior cingulate cortex in the human brain with regard to addiction and withdrawal. This aim was achieved by group comparisons of results of magnetic resonance spectroscopy between non-smokers, smokers and smokers during withdrawal. 12 smokers and 12 non-smokers were measured with single voxel proton magnetic resonance spectroscopy for total N-acetyl aspartate, glutamate and glutamine, choline-containing compounds, myo-inositol and total creatine in the right and the left hippocampus and in the right and the left dorsal anterior cingulate cortex. Smokers were examined twice, first during regular cigarette smoking and second on the third day of nicotine withdrawal. The ratios to total creatine were used for better reliability. In our study, Glx/tCr was significantly increased and tCho/tCr was significantly decreased in the left cingulate cortex in smokers compared to non-smokers (p = 0.01, both). Six out of seven smokers showed normalization of the Glx/tCr in the left cingulate cortex during withdrawal. Although these results are preliminary due to the small sample size, our results confirm the assumption that cigarette smoking interferes directly or indirectly with the glutamate circuit in the dorsal anterior cingulate cortex.
EVALuna2:22826

Physiological MRI Biomarkers in the Differentiation Between Glioblastomas and Solitary Brain Metastases - Heynold, Elisabeth; Zimmermann, Max; Hore, Nirjhar; Buchfelder, Michael; Dörfler, Arnd; Stadlbauer, Andreas; Kremenevski, Natalia (Molecular Imaging and Biology, 2021)
Purpose: Glioblastomas (GB) and solitary brain metastases (BM) are the most common brain tumors in adults. GB and BM may appear similar in conventional magnetic resonance imaging (cMRI). Their management strategies, however, are quite different with significant consequences on clinical outcome. The aim of this study was to evaluate the usefulness of a previously presented physiological MRI approach scoping to obtain quantitative information about microvascular architecture and perfusion, neovascularization activity, and oxygen metabolism to differentiate GB from BM. Procedures: Thirty-three consecutive patients with newly diagnosed, untreated, and histopathologically confirmed GB or BM were preoperatively examined with our physiological MRI approach as part of the cMRI protocol. Results: Physiological MRI biomarker maps revealed several significant differences in the pathophysiology of GB and BM: Central necrosis was more hypoxic in GB than in BM (30 %; P = 0.036), which was associated with higher neovascularization activity (65 %; P = 0.043) and metabolic rate of oxygen (48 %; P = 0.004) in the adjacent contrast-enhancing viable tumor parts of GB. In peritumoral edema, GB infiltration caused neovascularization activity (93 %; P = 0.018) and higher microvascular perfusion (30 %; P = 0.022) associated with higher tissue oxygen tension (33 %; P = 0.020) and lower oxygen extraction from vasculature (32 %; P = 0.040). Conclusion: Our physiological MRI approach, which requires only 7 min of extra data acquisition time, might be helpful to noninvasively distinguish GB and BM based on pathophysiological differences. However, further studies including more patients are required.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Angiogenesis; Brain metastasis; Glioblastoma; Hypoxia; Physiological MRI

Physiological MRI of microvascular architecture, neovascularization activity, and oxygen metabolism facilitate early recurrence detection in patients with IDH-mutant WHO grade 3 glioma - Stadlbauer, Andreas; Heinz, Gertraud; Oberndorfer, Stefan; Zimmermann, Max; Kinfe, Thomas Mehari; Buchfelder, Michael; Dörfler, Arnd; Kremenevski, Natalia; Marhold, Franz (Neuroradiology, 2021)
Purpose: This study aimed to determine the diagnostic performance of physiological MRI biomarkers including microvascular perfusion and architecture, neovascularization activity, tissue oxygen metabolism, and tension for recurrence detection of IDH-mutant WHO grade 3 glioma. Methods: Sixty patients with IDH-mutant WHO grade 3 glioma who received overall 288 follow-up MRI examinations at 3 Tesla after standard treatment were retrospectively evaluated. A conventional MRI protocol was extended with a physiological MRI approach including vascular architecture mapping and quantitative blood-oxygen-level-dependent imaging which required 7 min extra data acquisition time. Custom-made MATLAB software was used for the calculation of MRI biomarker maps of microvascular perfusion and architecture, neovascularization activity, tissue oxygen metabolism, and tension. Statistical procedures included receiver operating characteristic analysis. Results: Overall, 34 patients showed recurrence of the WHO grade 3 glioma; of these, in 15 patients, recurrence was detected one follow-up examination (averaged 160 days) earlier by physiological MRI data than by conventional MRI. During this time period, the tumor volume increased significantly (P = 0.001) on average 7.4-fold from 1.5 to 11.1 cm3. Quantitative analysis of MRI biomarkers demonstrated microvascular but no macrovascular hyperperfusion in early recurrence. Neovascularization activity (AUC = 0.833), microvascular perfusion (0.682), and oxygen metabolism (0.661) showed higher diagnostic performance for early recurrence detection of WHO grade 3 glioma compared to conventional MRI including cerebral blood volume (0.649). Conclusion: This study demonstrated that the targeted assessment of microvascular features and tissue oxygen tension as an early sign of neovascularization activity provided valuable information for recurrence diagnostic of WHO grade 3 glioma.
CRIS-Team Scopus Importer:2021-06-23
Keywords: Glioma; Humans; Magnetic resonance imaging; Neoplasm recurrence; Neovascularization; Oxygen metabolism; Treatment failure

Physiologic MR imaging of the tumor microenvironment revealed switching of metabolic phenotype upon recurrence of glioblastoma in humans - Stadlbauer, Andreas; Oberndorfer, Stefan; Zimmermann, Max; Renner, Bertold; Buchfelder, Michael; Heinz, Gertraud; Dörfler, Arnd; Kleindienst, Andrea; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2019)
Treating recurrent glioblastoma (GB) is one of the challenges in modern neurooncology. Hypoxia, neovascularization, and energy metabolism are of crucial importance for therapy failure and recurrence. Twenty-one patients with initially untreated GB who developed recurrence were examined with a novel MRI approach for noninvasive visualization of the tumor microenvironment (TME). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and glycolysis. Volume percentages of these TME compartments were compared between untreated and recurrent GB. At initial diagnosis, all 21 GB showed either the features of a glycolytic dominant phenotype with a high percentage of functional neovasculature (N = 12) or those of a necrotic/hypoxic dominant phenotype with a high percentage of defective tumor neovasculature (N = 9). At recurrence, all 21 GB revealed switching of the initial metabolic phenotype: either from the glycolytic to the necrotic/hypoxic dominant phenotype or vice-versa. A necrotic/hypoxic phenotype at recurrence was associated with a higher rate of multifocality of the recurrent lesions. Our MRI approach may be helpful for a better understanding of treatment-induced metabolic phenotype switching and for future studies developing targeted therapeutic strategies for recurrent GB.
CRIS-Team Scopus Importer:2020-02-21
Keywords: angiogenesis; Glioblastoma; hypoxia; recurrence; treatment failure; tumor microenvironment

Physiologic MR imaging of the tumor microenvironment revealed switching of metabolic phenotype upon recurrence of glioblastoma in humans - Stadlbauer, Andreas; Oberndorfer, Stefan; Zimmermann, Max; Renner, Bertold; Buchfelder, Michael; Heinz, Gertraud; Dörfler, Arnd; Kleindienst, Andrea; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2020)
Treating recurrent glioblastoma (GB) is one of the challenges in modern neurooncology. Hypoxia, neovascularization, and energy metabolism are of crucial importance for therapy failure and recurrence. Twenty-one patients with initially untreated GB who developed recurrence were examined with a novel MRI approach for noninvasive visualization of the tumor microenvironment (TME). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and glycolysis. Volume percentages of these TME compartments were compared between untreated and recurrent GB. At initial diagnosis, all 21 GB showed either the features of a glycolytic dominant phenotype with a high percentage of functional neovasculature (N = 12) or those of a necrotic/hypoxic dominant phenotype with a high percentage of defective tumor neovasculature (N = 9). At recurrence, all 21 GB revealed switching of the initial metabolic phenotype: either from the glycolytic to the necrotic/hypoxic dominant phenotype or vice-versa. A necrotic/hypoxic phenotype at recurrence was associated with a higher rate of multifocality of the recurrent lesions. Our MRI approach may be helpful for a better understanding of treatment-induced metabolic phenotype switching and for future studies developing targeted therapeutic strategies for recurrent GB.
EVALuna2:212798

Pinning observability of competitive neural networks with different time–constants - Meyer-Base, A.; Amani, A. Moradi; Meyer-Base, U.; Foo, S.; Stadlbauer, A.; Yu, W. (Neurocomputing, 2019)
The new concept called pinning observability is proposed for competitive neural networks with different time-scales and a distributed observer structure, which is determined to estimate the states of this large scale network. This network observer has local distinct sub-observers that process local information at the node level but exchange their state estimates with the neighboring observers and thus reflect the interconnection structure of the neural network. The goal is to employ only a minimum number of measurements at certain nodes within the whole neural network, however to be able to estimate the entire state of the network. This can be interpreted as the dual problem to the longer studied pinning control problem. In this paper, we formulate the proposed approach for the two most common competitive neural networks with different time-scales and derive some decoupled and simple conditions for pinning observability. The sub-observers are driven by only local neuron level information but communicate the estimated local states with the neighboring observers. This exchange of local information is the basis of cortical neural processing. The monitoring of few signals from the network holds important practical application for brain signal processing. Simulation examples are given to illustrate the theoretical concepts.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Multi-time-scale competitive neural network; Pinning observability; Synchronization

Pituicytoma-An outlook on possible targeted therapies - Mende, Klaus Christian; Matschke, Jakob; Burkhardt, Till; Saeger, Wolfgang; Buslei, Rolf; Buchfelder, Michael; Fahlbusch, Rudolf; Westphal, Manfred; Flitsch, Joerg (Cns Neuroscience & Therapeutics, 2017)
Pituicytoma is a rare neoplasm of the sella region. Tumor resection is the primary treatment option, but remains subtotal due to excessive bleeding in many cases. The search for alternative or additional treatment regimens is necessary.We aimed to determine the receptor expression of pituicytoma to find alternatives or supplements to surgical therapy in the use of targeted therapies.Pituicytoma samples were collected from three institutions between 2006 and 2015 and were stained for vascular endothelial growth factors (VEGF), thyroid transcription factor (TTF1), and somatostatin receptors (SSTR 2/3/5). The stains were classified from 0=no staining to +++=strong staining. A complementary retrospective analysis of the patient charts regarding sex, age, and primary symptoms, pituitary function, and perioperative complications was performed.Ten samples were analyzed; mean patient age was 57.8 years SD 16.3 years. Seven samples were acquired from male patients (one relapse) and three from female. All tumors stained strongly positive (+++) for VEGF-R. Six samples stained positive for TTF1. As for somatostatin receptors, three samples were slightly positive for SSTR 2; seven were negative. SSTR 3 was + in one, three were ++, three were +++, and three were 0. SSTR 5 stained +++ in 1, ++ in 5, + in 1, and 0 in three patients.Pituicytomas were generally positive for VEGFR and showed regular expression of SSTR 3 and 5 indicating a possible treatment option through targeted therapies in cases where resection remains insufficient. Further research is necessary as to whether tumor growth can be inhibited using these pathways.
EVALuna2:7364

Pituitary Neoplasm Nomenclature Workshop: Does Adenoma Stand the Test of Time? - Ho, Ken; Fleseriu, Maria; Kaiser, Ursula; Salvatori, Roberto; Brue, Thierry; Lopes, M. Beatriz; Kunz, Pamela; Molitch, Mark; Camper, Sally A.; Gadelha, Monica; Syro, Luis; Laws, Edward; et al. (Journal of the Endocrine Society, 2021)
The WHO Classification of Endocrine Tumours designates pituitary neoplasms as adenomas. A proposed nomenclature change to pituitary neuroendocrine tumors (PitNETs) has been met with concern by some stakeholder groups. The Pituitary Society coordinated the Pituitary Neoplasm Nomenclature (PANOMEN) workshop to address the topic. Experts in pituitary developmental biology, pathology, neurosurgery, endocrinology, and oncology, including representatives nominated by the Endocrine Society, European Society of Endocrinology, European Neuroendocrine Association, Growth Hormone Research Society, and International Society of Pituitary Surgeons. Clinical epidemiology, disease phenotype, management, and prognosis of pituitary adenomas differ from that of most NETs. The vast majority of pituitary adenomas are benign and do not adversely impact life expectancy. A nomenclature change to PitNET does not address the main challenge of prognostic prediction, assigns an uncertain malignancy designation to benign pituitary adenomas, and may adversely affect patients. Due to pandemic restrictions, the workshop was conducted virtually, with audiovisual lectures and written precis on each topic provided to all participants. Feedback was collated and summarized by Content Chairs and discussed during a virtual writing meeting moderated by Session Chairs, which yielded an evidence-based draft document sent to all participants for review and approval. There is not yet a case for adopting the PitNET nomenclature. The PANOMEN Workshop recommends that the term adenoma be retained and that the topic be revisited as new evidence on pituitary neoplasm biology emerges.
CRIS-Team WoS Importer:2021-05-28

Pituitary society expert Delphi consensus: operative workflow in endoscopic transsphenoidal pituitary adenoma resection - Marcus, Hani J.; Khan, Danyal Z.; Borg, Anouk; Buchfelder, Michael; Cetas, Justin S.; Collins, Justin W.; Dorward, Neil L.; Fleseriu, Maria; Gurnell, Mark; Javadpour, Mohsen; Jones, Pamela S.; Koh, Chan Hee; et al. (Pituitary, 2021)
Purpose: Surgical workflow analysis seeks to systematically break down operations into hierarchal components. It facilitates education, training, and understanding of surgical variations. There are known educational demands and variations in surgical practice in endoscopic transsphenoidal approaches to pituitary adenomas. Through an iterative consensus process, we generated a surgical workflow reflective of contemporary surgical practice. Methods: A mixed-methods consensus process composed of a literature review and iterative Delphi surveys was carried out within the Pituitary Society. Each round of the survey was repeated until data saturation and > 90% consensus was reached. Results: There was a 100% response rate and no attrition across both Delphi rounds. Eighteen international expert panel members participated. An extensive workflow of 4 phases (nasal, sphenoid, sellar and closure) and 40 steps, with associated technical errors and adverse events, were agreed upon by 100% of panel members across rounds. Both core and case-specific or surgeon-specific variations in operative steps were captured. Conclusions: Through an international expert panel consensus, a workflow for the performance of endoscopic transsphenoidal pituitary adenoma resection has been generated. This workflow captures a wide range of contemporary operative practice. The agreed “core” steps will serve as a foundation for education, training, assessment and technological development (e.g. models and simulators). The “optional” steps highlight areas of heterogeneity of practice that will benefit from further research (e.g. methods of skull base repair). Further adjustments could be made to increase applicability around the world.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Consensus; Delphi; Endoscopic endonasal; Endoscopic transsphenoidal surgery; Pituitary; Pituitary adenoma; Skull base surgery

Pituitary society guidance: pituitary disease management and patient care recommendations during the COVID-19 pandemic—an international perspective - Fleseriu, Maria; Buchfelder, Michael; Cetas, Justin S.; Fazeli, Pouneh K.; Mallea-Gil, Susana M.; Gurnell, Mark; McCormack, Ann; Pineyro, Maria M.; Syro, Luis V.; Tritos, Nicholas A.; Marcus, Hani J. (Pituitary, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the viral strain that has caused the coronavirus disease 2019 (COVID-19) pandemic, has presented healthcare systems around the world with an unprecedented challenge. In locations with significant rates of viral transmission, social distancing measures and enforced ‘lockdowns’ are the new ‘norm’ as governments try to prevent healthcare services from being overwhelmed. However, with these measures have come important challenges for the delivery of existing services for other diseases and conditions. The clinical care of patients with pituitary disorders typically involves a multidisciplinary team, working in concert to deliver timely, often complex, disease investigation and management, including pituitary surgery. COVID-19 has brought about major disruption to such services, limiting access to care and opportunities for testing (both laboratory and radiological), and dramatically reducing the ability to safely undertake transsphenoidal surgery. In the absence of clinical trials to guide management of patients with pituitary disease during the COVID-19 pandemic, herein the Professional Education Committee of the Pituitary Society proposes guidance for continued safe management and care of this population.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Acromegaly; COVID-19; Cushing’s disease; Pituitary disease and surgery; Prolactinomas; SARS-CoV-2

Plasma concentrations of the amyloid-? peptides in young volunteers: the influence of the APOE genotype - Zimmermann, Rüdiger; Huber, Ellen; Schamber, Christine; Lelental, Natalia; Mroczko, Barbara; Brandner, Sebastian; Maler, Juan Manuel; Oberstein, Timo; Szmitkowski, Maciej; Rauh, Manfred; Kornhuber, Johannes; Lewczuk, Piotr (Journal of Alzheimer's Disease, 2014)
Changes in the concentrations of amyloid-? (A?) in the body fluids are the earliest alterations observed in Alzheimer's disease (AD), however, there is a lack of data about how early these alterations occur, before the onset of the clinical symptoms. APOE genotype is the most recognized genetic risk/protective factor of AD, meaning that a group of non-demented persons carrying ?4 allele is enriched in the subjects who will develop AD, compared to the group of non-carriers. Therefore, we studied the plasma concentrations of A? peptides (A?1-42, A?1-40, A?x-42, and A?x-40), and the APOE genotype in 173 young volunteers (average age, 28 ± 7.6 years) without memory deficits, in order to see whether the non-demented group of subjects at risk already characterize with A? changes three-to-four decades before the age at which dementia usually occurs. We did not find statistically significant differences among the groups of ?4 carriers, ?3 homozygotes, and ?2 carriers. We conclude that the APOE genotype does not influence the metabolism of the A? peptides in young persons without memory deficits.
EVALuna2:18883

Plasticity Related Gene 3 (PRG3) overcomes myelin-associated growth inhibition and promotes functional recovery after spinal cord injury - Broggini, Thomas; Schnell, Lisa; Ghoochani, Ali; Mateos, Jose Maria; Buchfelder, Michael; Wiendieck, Kurt; Schaefer, Michael K.; Eyupoglu, Ilker Y.; Savaskan, Nicolai E. (Aging-Us, 2016)
The Plasticity Related Gene family covers five, brain-specific, transmembrane proteins (PRG1-5, also termed LPPR1-5) that operate in neuronal plasticity during development, aging and brain trauma. Here we investigated the role of the PRG family on axonal and filopodia outgrowth. Comparative analysis revealed the strongest outgrowth induced by PRG3 (LPPR1). During development, PRG3 is ubiquitously located at the tip of neuronal processes and at the plasma membrane and declines with age. In utero electroporation of PRG3 induced dendritic protrusions and accelerated spine formations in cortical pyramidal neurons. The neurite growth promoting activity of PRG3 requires RasGRF1 (RasGEF1/Cdc25) mediated downstream signaling. Moreover, in axon collapse assays, PRG3-induced neurites resisted growth inhibitors such as myelin, Nogo-A (Reticulon/RTN-4), thrombin and LPA and impeded the RhoA-Rock-PIP5K induced neurite repulsion. Transgenic adult mice with constitutive PRG3 expression displayed strong axonal sprouting distal to a spinal cord lesion. Moreover, fostered PRG3 expression promoted complex motor-behavioral recovery compared to wild type controls as revealed in the Schnell swim test (SST). Thus, PRG3 emerges as a developmental RasGRF1-dependent conductor of filopodia formation and axonal growth enhancer. PRG3-induced neurites resist brain injury-associated outgrowth inhibitors and contribute to functional recovery after spinal cord lesions. Here, we provide evidence that PRG3 operates as an essential neuronal growth promoter in the nervous system. Maintaining PRG3 expression in aging brain may turn back the developmental clock for neuronal regeneration and plasticity.
EVALuna2:33854

PPARδ-mediated mitochondrial rewiring of osteoblasts determines bone mass - Müller, Dorothea; Stoll, Cornelia; Palumbo-Zerr, Katrin; Böhm, Christina; Krishnacoumar, Brenda; Ipseiz, Natacha; Taubmann, Jule; Zimmermann, Max; Böttcher, Martin; Mougiakakos, Dimitrios; Tuckermann, Jan; Djouad, Farida; et al. (Scientific Reports, 2020)
Bone turnover, which is determined by osteoclast-mediated bone resorption and osteoblast-mediated bone formation, represents a highly energy consuming process. The metabolic requirements of osteoblast differentiation and mineralization, both essential for regular bone formation, however, remain incompletely understood. Here we identify the nuclear receptor peroxisome proliferator-activated receptor (PPAR) δ as key regulator of osteoblast metabolism. Induction of PPARδ was essential for the metabolic adaption and increased rate in mitochondrial respiration necessary for the differentiation and mineralization of osteoblasts. Osteoblast-specific deletion of PPARδ in mice, in turn, resulted in an altered energy homeostasis of osteoblasts, impaired mineralization and reduced bone mass. These data show that PPARδ acts as key regulator of osteoblast metabolism and highlight the relevance of cellular metabolic rewiring during osteoblast-mediated bone formation and bone-turnover.
CRIS-Team Scopus Importer:2020-06-02

Pre- and postoperative headache in patients with meningioma - Günther, Franziska; Swozil, Ferdinand; Heber, Stefan; Buchfelder, Michael; Meßlinger, Karl; Fischer, Michael (Cephalalgia, 2018)
Background Meningiomas are generally slowly growing intracranial tumors. They are often incidentally diagnosed, given that symptoms may be absent even in cases of an enormous tumor size. Headache is a frequent but not consistent symptom. Therefore, we examined the association between structural, biochemical and histochemical tumor parameters with preoperative as well as postoperative occurrence of headache. Methods In our study, we prospectively investigated 69 consecutive patients enrolled for meningioma neurosurgery. Anatomical, histological and biochemical parameters were acquired, and headache parameters were registered from the clinical report and from a questionnaire filled by the patients before neurosurgery. The headache was re-evaluated one year after neurosurgery. The study was designed to exploratively investigate whether there is an association of acquired clinical and biological parameters with the occurrence of preoperative and postoperative headache. Results Edema diameter and the proliferation marker MIB-1 were negatively associated with the incidence and intensity of preoperative headache, while the content of prostaglandin E2 in the tumor tissue was positively associated with preoperative headache intensity. Headache was more prevalent when the meningioma was located in the area supplied by the ophthalmic trigeminal branch. Compared to preoperative headache levels, an overall reduction was observed one year postoperative, and patients with a larger tumor had a higher headache remission. In parietal and occipital meningiomas and in those with a larger edema, the percentage of the headache remission rate was higher compared to other locations or smaller edema. Multivariable analyses showed an involvement of substance P and prostaglandin E2 in preoperative headache. Conclusions The study demonstrates new associations between meningiomas and headache. The postoperative headache outcome in the presented patient sample is encouraging for the performed neurosurgical intervention. These results should be tested in a prospective study that incorporates all patients with meningiomas.
EVALuna2:35834

Predicting Glioblastoma Response to Bevacizumab Through MRI Biomarkers of the Tumor Microenvironment - Stadlbauer, Andreas; Roessler, Karl; Zimmermann, Max; Buchfelder, Michael; Kleindienst, Andrea; Dörfler, Arnd; Heinz, Gertraud; Oberndorfer, Stefan (Molecular Imaging and Biology, 2019)
Purpose: Glioblastoma (GB) is one of the most vascularized of all solid tumors and, therefore, represents an attractive target for antiangiogenic therapies. Many lesions, however, quickly develop escape mechanisms associated with changes in the tumor microenvironment (TME) resulting in rapid treatment failure. To prevent patients from adverse effects of ineffective therapy, there is a strong need to better predict and monitor antiangiogenic treatment response. Procedures: We utilized a novel physiological magnetic resonance imaging (MRI) method combining the visualization of oxygen metabolism and neovascularization for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and aerobic glycolysis. This approach, termed TME mapping, was used to monitor changes in tumor biology and pathophysiology within the TME in response to bevacizumab treatment in 18 patients with recurrent GB. Results: We detected dramatic changes in the TME by rearrangement of its compartments after the onset of bevacizumab treatment. All patients showed a decrease in active tumor volume and neovascularization as well as an increase in hypoxia and necrosis in the first follow-up after 3 months. We found that recurrent GB with a high percentage of neovascularization and active tumor before bevacizumab onset showed a poor or no treatment response. Conclusions: TME mapping might be useful to develop strategies for patient stratification and response prediction before bevacizumab onset.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Angiogenesis; Antiangiogenic therapy; Bevacizumab; Glioblastoma; Hypoxia; Recurrence; Treatment failure; Treatment monitoring; Tumor microenvironment

Prediction of Hearing Preservation in Vestibular Schwannoma Surgery According to Tumor Size and Anatomic Extension - Bozhkov, Yavor; Shawarba, Julia; Feulner, Julian; Winter, Fabian; Rampp, Stefan; Hoppe, Ulrich; Dörfler, Arnd; Iro, Heinrich; Buchfelder, Michael; Rössler, Karl (Otolaryngology-Head and Neck Surgery, 2021)
Objective: Vestibular schwannoma (VS) surgery is feasible for various tumor sizes that are inappropriate for wait and scan or radiosurgery. The predictive value of 2 grading systems was investigated for postoperative hearing preservation (HP) in a large series. Study Design: Retrospective analysis. Setting: Neurosurgical patient database of the University of Erlangen was queried between 2014 and 2017. Methods: Retrospective single-center analysis on 138 VSs operated on via a retrosigmoidal approach. The mean tumor size was 20.4 mm (SD, 7.6 mm) with fundal infiltration in 67.4%. The overall resection rate was 93.5%. Tumors were classified preoperatively by the 3-tier Erlangen grading system depending on size or the anatomically based 4-tier Koos grading system. Results: Preoperative hearing preservation was found in 70.3% of patients and was significantly correlated to tumor size (P =.001). For Erlangen grading, a mean postoperative serviceable hearing preservation rate of 32% was achieved: 83.3% for tumors <12 mm, 30.3% for tumors between 12 and 25 mm, and 5.3% for tumors >25 mm. In contrast, according to Koos grading, postoperative serviceable hearing preservation was 100% for grade 1 tumors (meatal), 35.6% for grade 2 (cisternal), 23.1% for grade 3 (brainstem contact), and 21.7% for grade 4 (brainstem compression). Of the total cohort, 86% had normal or nearly normal postoperative facial function (House-Brackmann grades 1 and 2). Conclusion: Surgery on small VSs can achieve excellent hearing preservation. Different grading has a significant influence on and correlates with postoperative hearing preservation. Tumor size seems more important than anatomic relationship.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Erlangen vestibula schwannoma grading; grading systems; hearing preservation; Koos vestibular schwannoma grading; vestibular schwannoma surgery

Prediction of therapy response in acromegalic patients under pegvisomant therapy within the German ACROSTUDY cohort - Sievers, Caroline; Baur, Dorothee M.; Schwanke, Anja; Buchfelder, Michael; Droste, Michael; Mann, Klaus; Stalla, Guenter K. (Pituitary, 2015)
This study aimed at investigating predicting factors for therapy response under growth hormone receptor antagonist therapy with a focus on subjective and patient-oriented measures.Observational, multicenter nested-cohort study including 271 selected patients with the diagnosis of acromegaly and a minimum of one-year follow-up period within the German ACROSTUDY cohort (total cohort: n = 514). Outcome measures were the change of the biomarker IGF-1 (IGF-1 change and IGF-1 normalisation) between baseline and after 1 year of pegvisomant therapy (12 ± 6 months). Main predictors were patient-assessed subjective measures according to the Patient-Assessed Acromegaly Symptom Questionnaire (PASQ) in conjugation with age, gender, BMI, max. dosage of pegvisomant at follow-up and IGF-1 before the start of pegvisomant therapy.The mean age of the study population was 51.2 (13.9) years and the mean BMI was 29.5 (5.1) kg/m(2). In adjusted analyses, none of the individual perceived health (PASQ) scores, but age, BMI and IGF-1 at baseline were predictive for an IGF-1 decrease after 1 year of pegvisomant therapy and BMI and IGF-1, but equally none of the PASQ items, were predicting IGF-1 normalisation.Age, BMI and baseline IGF-1 but not subjective perceived health measures predict therapy response under second line medical therapy with pegvisomant.
EVALuna2:22865

Prediction of the Topography of the Corticospinal Tract on T1-Weighted MR Images Using Deep-Learning-Based Segmentation - Barany, Laszlo; Hore, Nirjhar; Stadlbauer, Andreas; Buchfelder, Michael; Brandner, Sebastian (Diagnostics, 2023)
Introduction: Tractography is an invaluable tool in the planning of tumor surgery in the vicinity of functionally eloquent areas of the brain as well as in the research of normal development or of various diseases. The aim of our study was to compare the performance of a deep-learning-based image segmentation for the prediction of the topography of white matter tracts on T1-weighted MR images to the performance of a manual segmentation. Methods: T1-weighted MR images of 190 healthy subjects from 6 different datasets were utilized in this study. Using deterministic diffusion tensor imaging, we first reconstructed the corticospinal tract on both sides. After training a segmentation model on 90 subjects of the PIOP2 dataset using the nnU-Net in a cloud-based environment with graphical processing unit (Google Colab), we evaluated its performance using 100 subjects from 6 different datasets. Results: Our algorithm created a segmentation model that predicted the topography of the corticospinal pathway on T1-weighted images in healthy subjects. The average dice score was 0.5479 (0.3513–0.7184) on the validation dataset. Conclusions: Deep-learning-based segmentation could be applicable in the future to predict the location of white matter pathways in T1-weighted scans.
CRIS-Team Scopus Importer:2023-03-24
Keywords: corticospinal tract; deep learning; magnetic resonance imaging; tractography

Predictive chromosomal clusters of synchronous and metachronous brain metastases in clear cell renal cell carcinoma - Gutenberg, Angelika; Nischwitz, Martin D.; Gunawan, Bastian; Enders, Christina; Jung, Klaus; Bergmann, Markus; Feiden, Wolfgang; Egensperger, Rupert; Keyvani, Kathy; Stolke, Dietmar; Sure, Ulrich; Schroeder, Henry W. S.; et al. (Cancer genetics, 2014)
Synchronous (early) and metachronous (late) brain metastasis (BM) events of sporadic clear cell renal cell carcinoma (ccRCC) (n = 148) were retrospectively analyzed using comparative genomic hybridization (CGH). Using oncogenetic tree models and cluster analyses, chromosomal imbalances related to recurrence-free survival until BM (RFS-BM) were analyzed. Losses at 9p and 9q appeared to be hallmarks of metachronous BM events, whereas an absence of detectable chromosomal changes at 3p was often associated with synchronous BM events. Correspondingly, k-means clustering showed that cluster 1 cases generally exhibited low copy number chromosomal changes that did not involve 3p. Cluster 2 cases had a high occurrence of -9p/-9q (94-98%) deletions, whereas cluster 3 cases had a higher frequency of copy number changes, including loss at chromosome 14 (80%). The higher number of synchronous cases in cluster 1 was also associated with a significantly shorter RFS-BM compared with clusters 2 and 3 (P = 0.02). Conversely, a significantly longer RFS-BM was observed for cluster 2 versus clusters 1 and 3 (P = 0.02). Taken together, these data suggest that metachronous BM events of ccRCC are characterized by loss of chromosome 9, whereas synchronous BM events may form independently of detectable genetic changes at chromosomes 9 and 3p.
EVALuna2:7238

Predictive Value Of Preoperative Magnetoencephalography (MEG) For Seizure Outcome In Surgery Of Long Term Epilepsy Associated Tumors - Roessler, K.; Heynold, Elisabeth; Kasper, Burkhard; Coras, R.; Blumcke, I.; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

Predictors for occlusion of cerebral AVMs following radiation therapy : Radiation dose and prior embolization, but not Spetzler-Martin grade - Knippen, Stefan; Putz, Florian; Semrau, Sabine; Lambrecht, Ulrike; Knippen, Arzu; Buchfelder, Michael; Schlaffer, Sven-Martin; Struffert, Tobias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Intracranial arteriovenous malformations (AVMs) may show a harmful development. AVMs are treated by surgery, embolization, or radiation therapy. OBJECTIVE: This study investigated obliteration rates and side effects in patients with AVMs treated by radiation therapy. METHODS: A total of 40 cases treated between 2005 and 2013 were analyzed. Single-dose stereotactic radiosurgery (SRS) was received by 13 patients and 27 received hypofractionated stereotactic radiation therapy (HSRT). In 20 patients, endovascular embolization had been performed prior to irradiation and 24 patients (60 %) had a history of previous intracranial hemorrhage. RESULTS: Treatment resulted in complete obliteration (CO) in 23/40 cases and partial obliteration in 8/40. CO was achieved in 85 % of patients receiving SRS compared to 44 % of those receiving HSRT. In the HSRT group, a first indication of an influence of AVM volume on obliteration rate was found. Equivalent 2 Gy fraction doses (EQD2) >70 Gy showed an obliteration rate of 50 %. Prior embolization was significantly associated with a higher portion of CO (p = 0.032). Median latency period (24.2 vs. 26 months) until CO was similar in both groups (SRS vs. HSRT). The rate of intracranial hemorrhage in patients with no prior bleeding events was 0 %. CONCLUSION: Excellent obliteration rates were achieved by SRS. Consistent with the literature, this data analysis suggests that the results of HSRT are volume-dependent. Furthermore, regimens with EQD2 doses >70 Gy appear more likely to achieve obliteration than schemes with lower doses. The findings indicate that radiation therapy does not increase the risk of bleeding. Prior embolization may have a good prognostic impact.
EVALuna2:32909

PREDICTORS OF QUALITY OF LIFE IN 165 PATIENTS WITH ACROMEGALY: RESULTS FROM A SINGLE-CENTER STUDY - Kreitschmann-Andermahr, Ilonka; Buchfelder, Michael; Kleist, Bernadette; Kohlmann, Johannes; Menzel, Christa; Buslei, Rolf; Koltowska-Hggstroem, Maria; Strasburger, Christian; Siegel, Sonja (Endocrine Practice, 2017)
Even if treated, acromegaly has a considerable impact on patient quality of life (QoL); despite this, the exact clinical determinants of QoL in acromegaly are unknown. This study retrospectively examines a cohort of treated patients with acromegaly, with the aim of identifying these determinants.Retrospective survey analysis, with 165 patients included in the study. All patients completed a survey, which included demographic data and the clinical details of their disease, the Short Form-36 Health Survey (SF-36), the revised Beck Depression Inventory (BDI-II), and the Bern Embitterment Inventory (BEI). Stepwise regression was used to identify predictors of QoL.The strongest predictors of the physical component score of the SF-36 were (in order of declining strength of association): Delay between first presentation of the disease and diagnosis, body mass index (BMI), number of doctors visited before the diagnosis of acromegaly, and age at diagnosis. For the mental component score, the strongest predictors were: number of doctors visited, previous radiotherapy, and age at study entry; and, for the BDI-II score: number of doctors visited, previous radiotherapy, age at study entry, and employment status at the time of diagnosis. The following were predictors of the BEI score: number of doctors visited, and age at study entry.Diagnostic delay and lack of diagnostic acumen in medical care provision are strong predictors of poor QoL in patients with acromegaly. Other identified parameters are radiotherapy, age, BMI, and employment status. An efficient acromegaly service should address these aspects when devising disease management plans.BDI-II = Beck Depression Inventory II BEI = Bern Embitterment Inventory BMI = body mass index IGF-1 = insulin-like growth factor 1 MCS = mental component summary (score) PCS = physical component summary (score) QoL = quality of life SDS = standard deviation score SF-36 = Short Form-36 Health Survey.
EVALuna2:7356

Presence of headache and headache types in patients with tumors of the sellar region-can surgery solve the problem? Results of a prospective single center study - Siegel, Sonja; Carneiro, Renata Weber; Buchfelder, Michael; Kleist, Bernadette; Grzywotz, Agnieszka; Buslei, Rolf; Bingel, Ulrike; Brabant, Georg; Schenk, Thomas; Kreitschmann-Andermahr, Ilonka (Endocrine, 2017)
Headache is a common presenting feature of patients with pituitary adenomas and other tumors of the sellar region. However, at present, it still is unclear whether the headache is actually caused by the tumor. To explore whether there is a relation, we examined in detail the headache types, their relationship to the underlying pathology, and if the headache responded to neurosurgery in a prospective study design.One hundred twelve patients with tumors of the sellar region scheduled for neurosurgery in a single center were analyzed for presence and quality of headache before surgery and at least 3 months after surgery. Patients received headache and depression self-rating inventories, presented on a handheld computer (PainDetect(®)). Clinical variables thought to impact on headache were analyzed in conjunction with the inventories.Fifty-nine (53%) patients reported headache in the 3 months prior to neurosurgery, 49 (44%) had headache at the time of filling in the questionnaires. The four patients with pituitary apoplexy described thunderclap headache. In the other patients diverse headache types were encountered, most frequently migraine. Untreated gonadotroph deficiency was significantly associated with absence of headache, while none of the other clinical and morphological variables related to headache. Presence of headache and disability due to headache were not significantly reduced after surgery.Apart from pituitary apoplexy we detected no specific headache type in our patient group and no significant improvement of headache after neurosurgery. Headache alone constitutes neither a valid diagnostic marker for the presence of tumors of the sellar region nor a sufficient indication for tumor removal.
EVALuna2:7358

Prestimulus feedback connectivity biases the content of visual experiences - Rassi, Elie; Wutz, Andreas; Müller-Voggel, Nadia; Weisz, Nathan (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Ongoing fluctuations in neural excitability and in networkwide activity patterns before stimulus onset have been proposed to underlie variability in near-threshold stimulus detection paradigms—that is, whether or not an object is perceived. Here, we investigated the impact of prestimulus neural fluctuations on the content of perception—that is, whether one or another object is perceived. We recorded neural activity with magnetoencephalography (MEG) before and while participants briefly viewed an ambiguous image, the Rubin face/vase illusion, and required them to report their perceived interpretation in each trial. Using multivariate pattern analysis, we showed robust decoding of the perceptual report during the poststimulus period. Applying source localization to the classifier weights suggested early recruitment of primary visual cortex (V1) and ∼160-ms recruitment of the category-sensitive fusiform face area (FFA). These poststimulus effects were accompanied by stronger oscillatory power in the gamma frequency band for face vs. vase reports. In prestimulus intervals, we found no differences in oscillatory power between face vs. vase reports in V1 or in FFA, indicating similar levels of neural excitability. Despite this, we found stronger connectivity between V1 and FFA before face reports for low-frequency oscillations. Specifically, the strength of prestimulus feedback connectivity (i.e., Granger causality) from FFA to V1 predicted not only the category of the upcoming percept but also the strength of poststimulus neural activity associated with the percept. Our work shows that prestimulus network states can help shape future processing in category-sensitive brain regions and in this way bias the content of visual experiences.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Connectivity; MEG; Oscillations; Prestimulus; Visual object perception

Prestimulus network integration of auditory cortex predisposes near-threshold perception independently of local excitability - Leske, Sabine; Ruhnau, Philipp; Frey, Julia; Lithari, Chrysa; Müller-Voggel, Nadia; Hartmann, Thomas; Weisz, Nathan (Cerebral Cortex, 2015)
Created from Fastlane, Scopus look-up
Keywords: Auditory consciousness; Functional connectivity; Graph theory; MEG; Ongoing oscillations

Presurgical functional cortical mapping using electromagnetic source imaging - Kreidenhuber, Rudolf; De Tiege, Xavier; Rampp, Stefan (Frontiers in Neurology, 2019)
Preoperative localization of functionally eloquent cortex (functional cortical mapping) is common clinical practice in order to avoid or reduce postoperative morbidity. This review aims at providing a general overview of magnetoencephalography (MEG) and high-density electroencephalography (hdEEG) based methods and their clinical role as compared to common alternatives for functional cortical mapping of (1) verbal language function, (2) sensorimotor cortex, (3) memory, (4) visual, and (5) auditory cortex. We highlight strengths, weaknesses and limitations of these functional cortical mapping modalities based on findings in the recent literature. We also compare their performance relative to other non-invasive functional cortical mapping methods, such as functional Magnetic Resonance Imaging (fMRI), Transcranial Magnetic Stimulation (TMS), and to invasive methods like the intracarotid Amobarbital Test (WADA-Test) or intracranial investigations.
CRIS-Team Scopus Importer:2019-06-28
Keywords: EEG; FMRI; Functional cortical mapping; Magnetoencephalography; Presurgical

Prevalence and clinical correlations of SF3B1 variants in lactotroph tumours - Simon, Julia; Perez-Rivas, Luis Gustavo; Zhao, Yining; Chasseloup, Fanny; Lasolle, Helene; Cortet, Christine; Descotes, Francoise; Villa, Chiara; Baussart, Bertrand; Burman, Pia; Maiter, Dominique; von Selzam, Vivian; et al. (European Journal of Endocrinology, 2023)
OBJECTIVE: A somatic mutational hotspot in the SF3B1 gene was reported in lactotroph tumours. The aim of our study was to examine the prevalence of driver SF3B1 variants in a multicentre independent cohort of patients with lactotroph tumours and correlate with clinical data. DESIGN AND METHODS: This was a retrospective, multicentre study involving 282 patients with lactotroph tumours (including 6 metastatic lactotroph tumours) from 8 European centres. We screened SF3B1 exon 14 hotspot for somatic variants using Sanger sequencing and correlated with clinicopathological data. RESULTS: We detected SF3B1 variants in seven patients with lactotroph tumours: c.1874G > A (p.Arg625His) (n = 4, 3 of which metastatic) and a previously undescribed in pituitary tumours variant c.1873C > T (p.Arg625Cys) (n = 3 aggressive pituitary tumours). In two metastatic lactotroph tumours with tissue available, the variant was detected in both primary tumour and metastasis. The overall prevalence of likely pathogenic SF3B1 variants in lactotroph tumours was 2.5%, but when we considered only metastatic cases, it reached the 50%. SF3B1 variants correlated with significantly larger tumour size; higher Ki67 proliferation index; multiple treatments, including radiotherapy and chemotherapy; increased disease-specific death; and shorter postoperative survival. CONCLUSIONS: SF3B1 variants are uncommon in lactotroph tumours but may be frequent in metastatic lactotroph tumours. When present, they associate with aggressive tumour behaviour and worse clinical outcome.
CRIS-Team Scopus Importer:2023-09-29
Keywords: aggressive; carcinoma; lactotroph tumour; prolactinoma; SF3B1

PRG3 induces Ras-dependent oncogenic cooperation in gliomas - Fan, Zheng; Bittermann-Rummel, Philipp; Yakubov, Eduard; Chen, Daishi; Broggini, Thomas; Sehm, Tina; Hatipoglu Majernik, Gökce; Hock, Stefan; Schwarz, Marc; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; et al. (Oncotarget, 2016)
Malignant gliomas are one of the most devastating cancers in humans. One characteristic hallmark of malignant gliomas is their cellular heterogeneity with frequent genetic lesions and disturbed gene expression levels conferring selective growth advantage. Here, we report on the neuronal-associated growth promoting gene PRG3 executing oncogenic cooperation in gliomas. We have identified perturbed PRG3 levels in human malignant brain tumors displaying either elevated or down-regulated PRG3 levels compared to non-transformed specimens. Further, imbalanced PRG3 levels in gliomas foster Ras-driven oncogenic amplification with increased proliferation and cell migration although angiogenesis was unaffected. Hence, PRG3 interacts with RasGEF1 (RasGRF1/CDC25), undergoes Ras-induced challenges, whereas deletion of the C-terminal domain of PRG3 (PRG3ΔCT) inhibits Ras. Moreover PRG3 silencing makes gliomas resistant to Ras inhibition. In vivo disequilibrated PRG3 gliomas show aggravated proliferation, invasion, and deteriorate clinical outcome. Thus, our data show that the interference with PRG3 homeostasis amplifies oncogenic properties and foster the malignancy potential in gliomas.
EVALuna2:23011

Primary Obstruction of the Foramen of Luschka: Anatomy, Histology, and Clinical Significance - Barany, Laszlo; Baksa, Gabor; Patonay, Lajos; Racz, Gergely; Ganslandt, Oliver; Buchfelder, Michael; Kurucz, Peter (World Neurosurgery, 2018)
BACKGROUND: The foramen of Luschka is a natural aperture between the fourth ventricle and the subarachnoid space at the cerebellopontine angle. Membranous closure of this foramen is referred to as primary obstruction. Available information about this variant and its role in the development of the cysts of the posterior fossa is contradictory. METHODS: The macroscopic and histologic features of the obstructed foramina were examined in 61 formalin-fixed human brains (122 foramina). Three rhomboid lips of various sizes with lateral recess were used for comparison. Five postoperative cases of diverticulum of the foramen of Luschka were included in this study, with 1 case presented in detail to illustrate anatomic and histologic findings. RESULTS: Primary obstruction was present in 11 of 122 cases. In 1 case, an enlarged rigid pouch with a thick wall was found. The wall of the membrane in primary obstruction and the rhomboid lip were composed of an inner ependymal, a middle glial, and an outer leptomeningeal layer. CONCLUSIONS: The rhomboid lip is a remnant of the roof of the fourth ventricle. Imperforation of the foramen of Luschka results in a pouch in the cerebellopontine angle that contains choroid plexus (Bochdalek's flower basket) and communicates with the fourth ventricle. This pouch has the potential to grow to a diverticulum and cause clinical symptoms. Based on our clinical observations, detailed radiologic and surgical-anatomic criteria were proposed to support the differential diagnosis of a diverticulum of the foramen of Luschka. Treatment strategies were also suggested.
EVALuna2:214804

Proliferating non-professional Phagocytes are able to generate Cell-in-Cell Structures - Hofmann, Andrea; Seeberg, J.; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36485

Proliferating non-professional Phagocytes to generate Cell-in-Cell Structures - Hofmann, Andrea; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

PROPHYLACTIC AND PROLONGED HYPOTHERMIA IN POOR-GRADESAH REDUCES DEGREE OF VASOSPASM AND RATE OF DELAYED CEREBRAL INFARCTIONS - Kuramatsu, J. B.; Kollmar, Rainer; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22484

Prophylactic nimodipine treatment and improvement in hearing outcome after vestibular schwannoma surgery: a combined analysis of a randomized, multicenter, Phase III trial and its pilot study - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2017)
OBJECTIVE In clinical routines, neuroprotective strategies in neurosurgical interventions are still missing. A pilot study (n = 30) and an analogously performed Phase III trial (n = 112) pointed to a beneficial effect of prophylactic nimodipine and hydroxyethyl starch (HES) in vestibular schwannoma (VS) surgery. Considering the small sample size, the data from both studies were pooled. METHODS The patients in both investigator-initiated studies were assigned to 2 groups. The treatment group (n = 70) received parenteral nimodipine (1-2 mg/hour) and HES (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 72) was not treated prophylactically. Facial and cochlear nerve functions were documented preoperatively, during the inpatient care, and 1 year after surgery. RESULTS Pooled raw data were analyzed retrospectively. Intent-to-treat analysis revealed a significantly lower risk for hearing loss (Class D) 12 months after surgery in the treatment group compared with the control group (OR 0.46, 95% CI 0.22-0.97; p = 0.04). After exclusion of patients with preoperative Class D hearing, this effect was more pronounced (OR 0.38, 95% CI 0.17-0.83; p = 0.016). Logistic regression analysis adjusted for tumor size showed a 4 times lower risk for hearing loss in the treatment group compared with the control group (OR 0.25, 95% CI 0.09-0.63; p = 0.003). Facial nerve function was not significantly improved with treatment. Apart from dose-dependent hypotension (p < 0.001), the study medication was well tolerated. CONCLUSIONS Prophylactic nimodipine is safe and may be recommended in VS surgery to preserve hearing. Prophylactic neuroprotective treatment in surgeries in which nerves are at risk seems to be a novel and promising concept. Clinical trial registration no.: DRKS 00000328 ( https://drks-neu.uniklinik-freiburg.de/drks_web/ ).
EVALuna2:33133

Prophylactic nimodipine treatment for cochlear and facial nerve preservation after vestibular schwannoma surgery: a randomized multicenter Phase III trial - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2016)
OBJECT A pilot study of prophylactic nimodipine and hydroxyethyl starch treatment showed a beneficial effect on facial and cochlear nerve preservation following vestibular schwannoma (VS) surgery. A prospective Phase III trial was undertaken to confirm these results. METHODS An open-label, 2-arm, randomized parallel group and multicenter Phase III trial with blinded expert review was performed and included 112 patients who underwent VS surgery between January 2010 and February 2013 at 7 departments of neurosurgery to investigate the efficacy and safety of the prophylaxis. The surgery was performed after the patients were randomly assigned to one of 2 groups using online randomization. The treatment group (n = 56) received parenteral nimodipine (1-2 mg/hr) and hydroxyethyl starch (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 56) was not treated prophylactically. RESULTS Intent-to-treat analysis showed no statistically significant effects of the treatment on either preservation of facial nerve function (35 [67.3%] of 52 [treatment group] compared with 34 [72.3%] of 47 [control group]) (p = 0.745) or hearing preservation (11 [23.4%] of 47 [treatment group] compared with 15 [31.2%] of 48 [control group]) (p = 0.530) 12 months after surgery. Since tumor sizes were significantly larger in the treatment group than in the control group, logistic regression analysis was required. The risk for deterioration of facial nerve function was adjusted nearly the same in both groups (OR 1.07 [95% CI 0.34-3.43], p = 0.91). In contrast, the risk for postoperative hearing loss was adjusted 2 times lower in the treatment group compared with the control group (OR 0.49 [95% CI 0.18-1.30], p = 0.15). Apart from dose-dependent hypotension (p < 0.001), no clinically relevant adverse reactions were observed. CONCLUSIONS There were no statistically significant effects of the treatment. Despite the width of the confidence intervals, the odds ratios may suggest but do not prove a clinically relevant effect of the safe study medication on the preservation of cochlear nerve function after VS surgery. Further study is needed before prophylactic nimodipine can be recommended in VS surgery.
EVALuna2:22832

Proposal of a clinical response score and predictors of clinical response to 2 years of GH replacement therapy in adult GH deficiency - Schneider, Harald J.; Buchfelder, Michael; Wallaschofski, Henri; Luger, Anton; Johannsson, Gudmundur; Kann, Peter H.; Mattsson, Anders (European Journal of Endocrinology, 2015)
There is no single clinical marker to reliably assess the clinical response to growth hormone replacement therapy (GHRT) in adults with growth hormone deficiency (GHD). The objective of this study was to propose a clinical response score to GHRT in adult GHD and to establish clinical factors that predict clinical response.This was a prospective observational cohort study from the international KIMS database (Pfizer International Metabolic Database).We included 3612 adult patients with GHD for proposing the response score and 844 patients for assessing predictors of response. We propose a clinical response score based on changes in total cholesterol, waist circumference and QoL-AGHDA quality of life measurements after 2 years of GHRT. A score point was added for each quintile of change in each variable, resulting in a sum score ranging from 3 to 15. For clinical response at 2 years, we analysed predictors at baseline and after 6 months using logistic regression analyses.In a baseline prediction model, IGF1, QoL-AGHDA, total cholesterol and waist circumference predicted response, with worse baseline parameters being associated with a favourable response (AUC 0.736). In a combined baseline and 6-month prediction model, baseline QoL-AGHDA, total cholesterol and waist circumference, and 6-month change in waist circumference were significant predictors of response (AUC 0.815).A simple clinical response score might be helpful in evaluating the success of GHRT. The baseline prediction model may aid in the decision to initiate GHRT and the combined prediction model may be helpful in the decision to continue GHRT.
EVALuna2:22859

Psychopathologic Symptoms in Survivors of Critical Illness and Their Relatives-What to Expect From a Screening Tool - Dodoo-Schittko, Frank; Kleindienst, Andrea (Critical Care Medicine, 2019)
CRIS-Team WoS Importer:2019-07-02

Psychosocial outcome in epilepsy after extratemporal surgery - Walther, Katrin; Onugoren, Muejgan Dogan; Buchfelder, Michael; Gollwitzer, Stephanie; Graf, Wolfgang; Kasper, Burkhard; Kriwy, Peter; Kurzbuch, Katrin; Lang, Johannes; Roessler, Karl; Schwab, Stefan; Schwarz, Michael; et al. (Epilepsy and Behavior, 2018)
OBJECTIVE: Only limited data exist on psychosocial long-term outcome after epilepsy surgery in patients with extratemporal epilepsy. The aim of this study was to investigate psychosocial outcome after extratemporal epilepsy surgery and to assess factors predicting favorable outcome. METHOD: Sixty-five out of 104 eligible patients who had undergone extratemporal epilepsy surgery at our epilepsy center between 1990 and 2015 (mean age: 42.2. years; 75% of the resections in the frontal lobe) completed a questionnaire asking about seizure status, employment status, marital and living situation, driving status, depressive symptoms, and quality of life (QOL). Follow-up was on average 9.2years after surgery (range: 1-26years). RESULTS: Thirty-eight (58%) patients were free of disabling seizures (Engel class I), and 28 (43%) have not experienced any seizures after surgery (Engel class IA). Employment rate in the primary labor market remained at 45%, but more patients lost employment (14%) than gained employment (8%). Postoperative employment was predicted by preoperative employment (p=.007), seizure freedom (p=.025), older age at seizure onset (p=.018), younger age at follow-up (p=.035), and female gender (p=.048). Seizure-free patients were more likely to be driving; have a partner, particularly in males; and have lower depressive scores. Quality of life at follow-up was best predicted by employment (p=.012), partnership (p=.025), and seizure freedom (p=.025). In contrast, recurrence of seizures and early seizure onset were associated with poor psychosocial outcome, particularly in men. CONCLUSION: The study provides support that extratemporal surgery can lead to improved QOL and favorable psychosocial outcome. Seizure freedom is important but not the only determinant of good psychosocial outcome.
EVALuna2:35520

Quantification of serial changes in cerebral blood volume and metabolism in patients with recurrent glioblastoma undergoing antiangiogenic therapy - Stadlbauer, Andreas; Pichler, Petra; Karl, Marianne; Brandner, Sebastian; Lerch, Claudia; Renner, Bertold; Heinz, Gertraud (European Journal of Radiology, 2015)
To evaluate the usefulness of quantitative advanced magnetic resonance imaging (MRI) methods for assessment of antiangiogenic therapy (AAT) response in recurrent glioblastoma multiforme (GBM).Eighteen patients with recurrent GBM received bevacizumab and 18 patients served as control group. Baseline MRI and two follow-up examinations were acquired every 3-5 months using dynamic susceptibility-weighted contrast (DSC) perfusion MRI and (1)H-MR spectroscopic imaging ((1)H-MRSI). Maps of absolute cerebral blood volume (aCBV) were coregistered with choline (Cho) and N-acetyl-aspartate (NAA) concentrations and compared to usually used relative parameters as well as controls.Perfusion significantly decreased in responding and pseudoresponding GBMs but also in normal appearing brain after AAT onset. Cho and NAA concentrations were superior to Cr-ratios in lesion differentiation and showed a clear gap between responding and pseudoresponding lesions. Responders to AAT exceptionally frequently (6 out of 8 patients) showed remote GBM progression.Quantification of CBV reveals changes in normal brain perfusion due to AAT, which were not described so far. DSC perfusion MRI seems not to be suitable for differentiation between response and pseudoresponse to AAT. However, absolute quantification of brain metabolites may allow for distinction due to a clear gap at 6-9 months after therapy onset.
EVALuna2:8524

Quantitative EEG may predict weaning failure in ventilated patients on the neurological intensive care unit - Welte, Tamara; Gabriel, Maria; Hopfengaertner, Ruediger; Rampp, Stefan; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Reindl, Caroline; Madzar, Dominik; Sprügel, Maximilian; Huttner, Hagen; Kuramatsu, Joji; et al. (Scientific Reports, 2022)
Neurocritical patients suffer from a substantial risk of extubation failure. The aim of this prospective study was to analyze if quantitative EEG (qEEG) monitoring is able to predict successful extubation in these patients. We analyzed EEG-monitoring for at least six hours before extubation in patients receiving mechanical ventilation (MV) on our neurological intensive care unit (NICU) between November 2017 and May 2019. Patients were divided in 2 groups: patients with successful extubation (SE) versus patients with complications after MV withdrawal (failed extubation; FE), including reintubation, need for non-invasive ventilation (NIV) or death. Bipolar six channel EEG was applied. Unselected raw EEG signal underwent automated artefact rejection and Short Time Fast Fourier Transformation. The following relative proportions of global EEG spectrum were analyzed: relative beta (RB), alpha (RA), theta (RT), delta (RD) as well as the alpha delta ratio (ADR). Coefficient of variation (CV) was calculated as a measure of fluctuations in the different power bands. Mann–Whitney U test and logistic regression were applied to analyze group differences. 52 patients were included (26 male, mean age 65 ± 17 years, diagnosis: 40% seizures/status epilepticus, 37% ischemia, 13% intracranial hemorrhage, 10% others). Successful extubation was possible in 40 patients (77%), reintubation was necessary in 6 patients (12%), 5 patients (10%) required NIV, one patient died. In contrast to FE patients, SE patients showed more stable EEG power values (lower CV) considering all EEG channels (RB: p < 0.0005; RA: p = 0.045; RT: p = 0.045) with RB as an independent predictor of weaning success in logistic regression (p = 0.004). The proportion of the EEG frequency bands (RB, RA RT, RD) of the entire EEG power spectrum was not significantly different between SE and FE patients. Higher fluctuations in qEEG frequency bands, reflecting greater fluctuation in alertness, during the hours before cessation of MV were associated with a higher rate of complications after extubation in this cohort. The stability of qEEG power values may represent a non-invasive, examiner-independent parameter to facilitate weaning assessment in neurocritical patients.
CRIS-Team Scopus Importer:2022-05-20

QUANTITATIVE MAGNETIC RESONANCE IMAGING CORRELATES WITH EARLY S100B PROFILE AND FUNCTIONAL OUTCOME AFTER ACUTE BRAIN INJURY - Roeckelein, Verena; Kloska, Stephan; Uder, Michael; Buchfelder, Michael; Kleindienst, Andrea (2016)
EVALuna2:14588

Quantitative sensory phenotyping in chronic neuropathic pain patients treated with unilateral L4-dorsal root ganglion stimulation - Kinfe, Thomas Mehari; von Willebrand, Nico; Stadlbauer, Andreas; Buchfelder, Michael; Yearwood, Thomas L.; Muhammad, Sajjad; Chaudhry, Shafqat R.; Gravius, Sascha; Randau, Thomas; Winder, Klemens; Maihöfner, Christian; Gravius, Nadine; et al. (Journal of Translational Medicine, 2020)
Background: In a previous study, we reported that selective dorsal root ganglion stimulation (DRGSTIM) at DRG level L4 promoted a favorable outcome for complex regional pain syndrome (CRPS) patients along with DRGSTIM-related changes of inflammatory biomarkers in blood and saliva. The impact on somatosensation is largely unknown. Herein, we assessed the quantitative sensory profile to quantify L4-DRGSTIM effects in CRPS patients. Methods: Twelve refractory CRPS patients (4 female; 8 male; mean age 69 ± 9 years) received standardized quantitative sensory testing (QST) protocol at baseline and after 3 months of unilateral L4-DRGSTIM assessing nociceptive and non-nociceptive thermal and mechanical sensitivity of the knee affected by CRPS and the contralateral non-painful knee area. Results: At baseline, CRPS subjects showed significantly increased thresholds for warmth, tactile and vibration detection (WDT, MDT and VDT) and exaggerated pain summation (WUR). After 3 months of unilateral L4-DRGSTIM all pain parameters exhibited trends towards normalization of sensitivity accumulating to a significant overall normalization for pain sensitivity (effect size: 0.91, p < 0.01), while with the one exception of WDT all non-nociceptive QST parameters remained unchanged. Overall change of non-nociceptive detection was negligible (effect size: 0.25, p > 0.40). Notably, reduction of pain summation (WUR) correlated significantly with pain reduction after 3 months of L4-DRGSTIM. Conclusions: Selective L4-DRGSTIM lowered ongoing pain in CRPS patients and evoked significant normalization in the pain domain of the somatosensory profile. Thermoreception and mechanoreception remained unchanged. However, larger randomized, sham-controlled trials are highly warranted to shed more light on effects and mechanisms of dorsal root ganglion stimulation on quantitative sensory characteristics. The study protocol was registered at the 15.11.2016 on German Register for Clinical Trials (DRKS ID 00011267). https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00011267.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Complex regional pain syndrome; Dorsal root ganglion stimulation; Objective measures for neurostimulation; Sensory quantitative testing

Radiophysiomics: Brain Tumors Classification by Machine Learning and Physiological MRI Data - Stadlbauer, Andreas; Marhold, Franz; Oberndorfer, Stefan; Heinz, Gertraud; Buchfelder, Michael; Kinfe, Thomas Mehari; Meyer-Bäse, Anke (Cancers, 2022)
The precise initial characterization of contrast-enhancing brain tumors has significant con-sequences for clinical outcomes. Various novel neuroimaging methods have been developed to in-crease the specificity of conventional magnetic resonance imaging (cMRI) but also the increased complexity of data analysis. Artificial intelligence offers new options to manage this challenge in clinical settings. Here, we investigated whether multiclass machine learning (ML) algorithms applied to a high-dimensional panel of radiomic features from advanced MRI (advMRI) and physiological MRI (phyMRI; thus, radiophysiomics) could reliably classify contrast-enhancing brain tu-mors. The recently developed phyMRI technique enables the quantitative assessment of microvas-cular architecture, neovascularization, oxygen metabolism, and tissue hypoxia. A training cohort of 167 patients suffering from one of the five most common brain tumor entities (glioblastoma, ana-plastic glioma, meningioma, primary CNS lymphoma, or brain metastasis), combined with nine common ML algorithms, was used to develop overall 135 classifiers. Multiclass classification performance was investigated using tenfold cross-validation and an independent test cohort. Adaptive boosting and random forest in combination with advMRI and phyMRI data were superior to human reading in accuracy (0.875 vs. 0.850), precision (0.862 vs. 0.798), F-score (0.774 vs. 0.740), AUROC (0.886 vs. 0.813), and classification error (5 vs. 6). The radiologists, however, showed a higher sensitivity (0.767 vs. 0.750) and specificity (0.925 vs. 0.902). We demonstrated that ML-based radiophys-iomics could be helpful in the clinical routine diagnosis of contrast-enhancing brain tumors; how-ever, a high expenditure of time and work for data preprocessing requires the inclusion of deep neural networks.
CRIS-Team Scopus Importer:2022-06-03
Keywords: artificial intelligence; brain tumors; machine learning; multiclass classification; neuro-oncology; physiological MRI; pretreatment classification

Rathke's Cleft Cyst as Origin of a Pediatric Papillary Craniopharyngioma - Schlatter, Sven-Martin; Buchfelder, Michael; Stoehr, Robert; Buslei, Rolf; Hoelsken, Annett (Frontiers in Genetics, 2018)
A 6-year old patient presented with an intra and suprasellar cystic lesion accompanied with impairment of the hypothalamic-pituitary axis and partial hypopituitarism. The most likely cause of sellar lesions in this age group are adamantinomatous craniopharyngioma (adaCP) or Rathke´s cleft cysts (RCCs). AdaCP are characterized byCTNNB1mutations accompanied with aberrant nuclear beta-catenin expression. RCC show neither nuclear beta-catenin expression norBRAFmutation. The latter is a hallmark of papillary craniopharyngiomas (papCP) that exhibit remarkable histological similarity with metaplasia of RCC. Diagnosis of the patient was elucidated byCTNNB1andBRAFmutation screening, utilizing different approaches, as well as histological examination of markers, e.g., beta-catenin, claudin-1, EpCAM and the mutated BRAFV600E protein, which are known to be differentially expressed in sellar lesions. The case presented reveals extraordinary aspects for two reasons. Firstly, the lesion appeared clinically, on MRI, intraoperatively and histologically as RCC with prominent squamous metaplasia, but showing an expression pattern of markers also found in papCP, whilst exhibiting a hitherto undescribedBRAF V 600Emutation. This important result documents a supposable transition of RCC metaplasia into a papillary craniopharyngioma (papCP). Secondly, this intriguing case shows unexpectedly that although papCP usually occurs almost exclusively in adults, it can also arise in childhood.
EVALuna2:33790

Reactivation of HCMV during RT of the brain results in critical illness and early mortality - Frey, Benjamin; Goerig, Nicole; Becker, Ina; Donaubauer, Anna-Jasmina; Korn, Klaus; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Putz, Florian; Semrau, Sabine; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Real-time imaging of glutamate transients in the extracellular space of acute human brain slices using a single-wavelength glutamate fluorescence nanosensor - Brandner, Sebastian; Aicher, Simon; Schröter, Sarah; Swierzy, Izabela; Kinfe, Thomas Mehari; Buchfelder, Michael; Maslarova, Anna; Stadlbauer, Andreas (Scientific Reports, 2022)
Glutamate is the most important excitatory neurotransmitter in the brain. The ability to assess glutamate release and re-uptake with high spatial and temporal resolution is crucial to understand the involvement of this primary excitatory neurotransmitter in both normal brain function and different neurological disorders. Real-time imaging of glutamate transients by fluorescent nanosensors has been accomplished in rat brain slices. We performed for the first time single-wavelength glutamate nanosensor imaging in human cortical brain slices obtained from patients who underwent epilepsy surgery. The glutamate fluorescence nanosensor signals of the electrically stimulated human cortical brain slices showed steep intensity increase followed by an exponential decrease. The spatial distribution and the time course of the signal were in good agreement with the position of the stimulation electrode and the dynamics of the electrical stimulation, respectively. Pharmacological manipulation of glutamate release and reuptake was associated with corresponding changes in the glutamate fluorescence nanosensor signals. We demonstrated that the recently developed fluorescent nanosensors for glutamate allow to detect neuronal activity in acute human cortical brain slices with high spatiotemporal precision. Future application to tissue samples from different pathologies may provide new insights into pathophysiology without the limitations of an animal model.
CRIS-Team Scopus Importer:2022-03-25

Real-Time, In Vivo Monitoring, and Quantitative Assessment of Intra-Arterial Vasospasm Therapy - Gölitz, Philipp; Kaschka, Iris; Lang, Stefan; Roessler, Karl; Knossalla, Frauke; Dörfler, Arnd (Neurocritical Care, 2016)
Our study aimed to evaluate whether the effect of an intra-arterial vasospasm therapy can be assessed quantitatively by in vivo blood flow analysis using the postprocessing algorithm parametric color coding (PCC).We evaluated 17 patients presenting with acute clinical deterioration due to vasospasm following subarachnoidal hemorrhage treated with intra-arterial nimodipine application. Pre- and post-interventional DSA series were post-processed by PCC. The relative time to maximum opacification (rTmax) was calculated in 14 arterially and venously located points of interest. From that data, the pre- and post-interventional cerebral circulation time (CirT) was calculated. Additionally, the arterial vessel diameters were measured. Pre- and post-interventional values were compared and tested for significance, respectively.Flow analysis revealed in all arterial vessel segments a non-statistically significant prolongation of rTmax after treatment. The mean CirT was 5.62 s (±1.19 s) pre-interventionally and 5.16 s (±0.81 s) post-interventionally, and the difference turned out as statistically significant (p = 0.039). A significantly increased diameter was measurable in all arterial segments post-interventionally.PCC is a fast applicable imaging technique that allows via real-time and in vivo blood flow analysis a quantitative assessment of the effect of intra-arterial vasospasm therapy. Our results seem to validate in vivo that an intra-arterial nimodipine application induces not only vasodilatation of the larger vessels, but also improves the microcirculatory flow, leading to a shortened cerebral CirT that reaches normal range post-interventionally. Procedural monitoring via PCC offers the option to compare quantitatively different therapy regimes, which allows optimization of existing approaches and implementation of individualized treatment strategies.
EVALuna2:22520

Reconstruction of composite defects of the scalp and neurocranium-a treatment algorithm from local flaps to combined AV loop free flap reconstruction - Steiner, Dominik; Horch, Raymund E.; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Arkudas, Andreas; Schmitz, Marweh; Ludolph, Ingo; Beier, Justus; Boos, Anja (World Journal of Surgical Oncology, 2018)
BACKGROUND: Reconstruction of cranial composite defects, including all layers of the scalp and the neurocranium, poses an interdisciplinary challenge. Especially after multiple previous operations and/or radiation therapy, sufficient reconstruction is often only possible using microsurgical free flap transplantation. The aim of this study was to analyze the therapy of interdisciplinary cases with composite defects including the scalp and neurocranium. METHODS: From 2009 to 2017, 23 patients with 18 free flaps and 10 pedicled/local flaps were analyzed. First choices for free flaps were muscle flaps followed by fasciocutaneous flaps. RESULTS: Except for four patients, a stable coverage could be reached in the first operation. Three of these patients received a local scalp rotation flap in the first operation and needed an additional free flap because the local flap was no longer sufficient for coverage after wound healing deficiency or tumor relapse. The superficial temporal artery or external carotid artery served as recipient vessels. In special cases, venous grafts or an arteriovenous loop (AV loop) were used as extensions for the recipient vessels. CONCLUSIONS: In summary, an interdisciplinary approach with radical debridement of infected or necrotic tissue and the reconstruction of the dura mater are essential to reach a stable, long-lasting reconstructive result. Based on our experience, free flaps seem to be the first choice for patients after multiple previous operations and/or radiation therapy.
EVALuna2:211467

Recurrence of glioblastoma is associated with elevated microvascular transit time heterogeneity and increased hypoxia - Stadlbauer, Andreas; Mouridsen, Kim; Dörfler, Arnd; Hansen, Mikkel Bo; Oberndorfer, Stefan; Zimmermann, Max; Buchfelder, Michael; Heinz, Gertraud; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2018)
Dynamic susceptibility contrast (DSC) perfusion MRI provide information about differences in macro- and microvasculature when executed with gradient-echo (GE; sensitive to macrovasculature) and spin-echo (SE; sensitive to microvasculature) contrast. This study investigated whether there are differences between macro- and microvascular transit time heterogeneity (MVTH and µVTH) and tissue oxygen tension (PO2mit) in newly-diagnosed and recurrent glioblastoma. Fifty-seven patients with glioblastoma (25 newly-diagnosed/32 recurrent) were examined with GE- and SE-DSC perfusion sequences, and a quantitative blood-oxygen-level-dependent (qBOLD) approach. Maps of MVTH, µVTH and coefficient of variation (MCOV and µCOV) were calculated from GE- and SE-DSC data, respectively, using an extended flow-diffusion equation. PO2mit maps were calculated from qBOLD data. Newly-diagnosed and recurrent glioblastoma showed significantly lower ( P ≤ 0.001) µCOV values compared to both normal brain and macrovasculature (MCOV) of the lesions. Recurrent glioblastoma had significantly higher µVTH ( P = 0.014) and µCOV ( P = 0.039) as well as significantly lower PO2mit values ( P = 0.008) compared to newly-diagnosed glioblastoma. The macrovasculature, however, showed no significant differences. Our findings provide evidence of microvascular adaption in the disorganized tumor vasculature for retaining the metabolic demands in stress response of therapeutically-uncontrolled glioblastomas. Thus, µVTH and PO2mit mapping gives insight into the tumor microenvironment (vascular and hypoxic niches) responsible for therapy resistance.
EVALuna2:212789

Recurrences of Pituitary Adenomas or Second De Novo Tumors: Comparisons with First Tumors - Saeger, Wolfgang; Mueller, Maximilian; Buslei, Rolf; Flitsch, Joerg; Fahlbusch, Rudolf; Buchfelder, Michael; Knappe, Ulrich J.; Crock, Patricia A.; Luedecke, Dieter K. (World Neurosurgery, 2018)
BACKGROUND: Recurrences of pituitary adenomas are not so rare. METHODS: In the German Registry of Pituitary Tumors, more than 12,000 surgical specimens were collected between 1967 and 2012, of which 312 patients with altogether 334 recurrences (n = 646 specimens) were included in our study. RESULTS: The histopathology of 162 recurrent adenomas could be compared with the original tumor and 37 second recurrences could be compared with the first recurrence. Comparing the proliferation index (Ki-67) of the original and the first recurrent tumor (n = 162), we found an unchanged index in 43 cases (26%), whereas in 69 cases (43%) the index increased and in 50 cases (31%) it decreased. Comparing the first with the second recurrence (n = 37), we found an unchanged index in 8 cases (22%), an increased index in 15 cases (40%), and a decreased index in 14 cases (38%). The third recurrence showed an unchanged index in 1 case (20%), an increased index in 2 cases (40%), and a decreased index in 2 cases (40%). p53 was unchanged in recurrences in 44% of cases, increased in 33%, and decreased in 22%. In 4 cases, adenomas developed into adenomas with strongly increased proliferation (formerly atypical adenomas, now aggressive adenomas) for the first recurrence, and 9 recurrences became aggressive adenomas. A change of tumor type without change of the common transcription factor occurred in 82 cases. CONCLUSIONS: A second independent de novo adenoma was present in 10 cases, probably due to changes of transcription factors.
EVALuna2:36561

Recurrent glioblastoma: who receives tumor specific treatment and how often? - Steffens, Rieke; Semrau, Sabine; Lahmer, Godehard; Putz, Florian; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Fietkau, Rainer (Journal of Neuro-Oncology, 2016)
The recurrence of glioblastoma (rGBM) is inevitable and often short-term. Therefore, information on the prognosis and effectiveness of tumor-specific versus purely palliative approaches should be more in-depth than a mere list of available treatment options for patients in this situation. However, follow-up data on the course of the disease in unselected patient populations after completion of primary treatment are scarce. This single-center analysis investigated the rate and number of glioblastoma recurrences after initial radiotherapy in 189 consecutive GM patients, focusing on the incidence of early death and the frequency of tumor-specific treatment (TST) versus best-supportive care (BSC) as well as the outcomes for the different approaches. In 61 % of initial population first recurrence (rGBM) could be determined by histology or imaging. 47 % received TST. 58 % of the patients with rGBM and TST were diagnosed with a second recurrence. Up to five recurrences were treated. 35-45 % of patients died before undergoing imaging studies to confirm the next recurrence. Multivariate analysis identified male sex and KPS score as independent factors (p < 0.01) for the choice of TST over BSC. Median overall survival from the diagnosis of first recurrence was 267 days in the TST group versus 65 days in patients receiving BSC (p < 0.0001). Nearly half of all rGBM patients received second-line TST, but a remarkably high proportion died early. Gender and KPS played a role in the choice of TST over BSC for recurrence treatment.
EVALuna2:18351

Reducing Tinnitus via Inhibitory Influence of the Sensorimotor System on Auditory Cortical Activity - Sabados, Anne; Kim, Cora; Rampp, Stefan; Bergherr, Elisabeth; Buchfelder, Michael; Schnell, Oliver; Müller-Voggel, Nadia (The Journal of Neuroscience, 2025)
Tinnitus is the subjective perception of a sound without corresponding external acoustic stimuli. Research highlights the influence of the sensorimotor system on tinnitus perception. Associated neuronal processes, however, are insufficiently understood, and it remains unclear how and at which hierarchical level the sensorimotor system interacts with the tinnitus-processing auditory system. We therefore asked 23 patients suffering from chronic tinnitus (11 males) to perform specific exercises, aimed at relaxing or tensing the jaw area, which temporarily modulated tinnitus perception. Associated neuronal processes were assessed using magnetencephalography. Results show that chronic tinnitus patients experienced their tinnitus as weaker and less annoying after completion of relaxing compared with tensing exercises. Furthermore, (1) sensorimotor alpha power and alpha-band connectivity directed from the somatosensory to the auditory cortex increased and (2) gamma power in the auditory cortex reduced, which (3) related to reduced tinnitus annoyance perception on a trial-by-trial basis in the relaxed state. No effects were revealed for 23 control participants without tinnitus (six males) performing the same experiment. We conclude that the increase in directed alpha-band connectivity from the somatosensory to the auditory cortex most likely reflects the transmission of inhibition from the somatosensory to the auditory cortex during relaxation, where concurrently tinnitus-related gamma power reduces. We suggest that revealed neuronal processes are transferable to other tinnitus-modulating systems beyond the sensorimotor one that is involved in attentional or emotional tinnitus modulation and provides deeper mechanistic insights into how and through which channels phantom sound perception might be modulated on a neuronal level.
CRIS-Team Scopus Importer:2025-05-02
Keywords: alpha; chronic tinnitus; connectivity; gamma; somatosensory; top-down

Refined Functional Magnetic Resonance Imaging and Magnetoencephalography Mapping Reveals Reorganization in Language-Relevant Areas of Lesioned Brains - Zimmermann, Max; Rössler, Karl; Kaltenhäuser, Martin; Grummich, Peter; Yang, Bing; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (World Neurosurgery, 2019)
BACKGROUND: Neurosurgical decisions regarding interventions close to brain areas with language-related functions remain highly challenging because of the risk of postoperative dysfunction. To minimize these risks, improvements in the preoperative mapping of language-related regions are required, especially as space-occupying lesions often lead to altered cortical topography and language area reorganization. METHODS: The degree of deviation and language area reorganization were investigated in 26 functional magnetic resonance imaging- and magnetoencephalography-dissociable cortical sub-areas displaying language-related activations in each of 18 patients with brain lesions and 3 healthy volunteers (during visual language tasks). RESULTS: Both modalities showed good congruency of the language areas. The mean spatial distance of the centroids and maxima was 9.06 mm and 10.58 mm, respectively, allowing us to define more specific anatomical positions. Postoperatively, language abilities increased in 11% (2 of 18) of the patients, remained unchanged in 83% (15 of 18) of the patients, and decreased in 6% (1 of 18) of the patients, respectively. Signs of language function reorganization detected on both functional magnetic resonance imaging and magnetoencephalography were present in 29% (5 of 17) of the patients. Attenuation of neurovascular coupling was found postoperatively in 17% (3 of 18) of the patients. Monohemispheric language processing cannot be assumed always in patients with brain lesions. CONCLUSIONS: The more detailed subdivision of language-relevant brain areas shown in this study can help to achieve more radical tumor resection without postoperative language deficits.
EVALuna2:212793

Refined Functional Magnetic Resonance Imaging and Magnetoencephalography Mapping Reveals Reorganization in Language-Relevant Areas of Lesioned Brains - Zimmermann, Max; Rössler, Karl; Kaltenhäuser, Martin; Grummich, Peter; Yang, Bing; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (World Neurosurgery, 2020)
Background: Neurosurgical decisions regarding interventions close to brain areas with language-related functions remain highly challenging because of the risk of postoperative dysfunction. To minimize these risks, improvements in the preoperative mapping of language-related regions are required, especially as space-occupying lesions often lead to altered cortical topography and language area reorganization. Methods: The degree of deviation and language area reorganization were investigated in 26 functional magnetic resonance imaging- and magnetoencephalography-dissociable cortical sub-areas displaying language-related activations in each of 18 patients with brain lesions and 3 healthy volunteers (during visual language tasks). Results: Both modalities showed good congruency of the language areas. The mean spatial distance of the centroids and maxima was 9.06 mm and 10.58 mm, respectively, allowing us to define more specific anatomical positions. Postoperatively, language abilities increased in 11% (2 of 18) of the patients, remained unchanged in 83% (15 of 18) of the patients, and decreased in 6% (1 of 18) of the patients, respectively. Signs of language function reorganization detected on both functional magnetic resonance imaging and magnetoencephalography were present in 29% (5 of 17) of the patients. Attenuation of neurovascular coupling was found postoperatively in 17% (3 of 18) of the patients. Monohemispheric language processing cannot be assumed always in patients with brain lesions. Conclusions: The more detailed subdivision of language-relevant brain areas shown in this study can help to achieve more radical tumor resection without postoperative language deficits.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Brain tumor; Broca; fMRI; Language; MEG; Reorganization; Wernicke

Reoperation In Failed Epilepsy Surgery Using MEG, Neuronavigation And Intraoperative Mr Imaging - Roessler, K.; Heynold, Elisabeth; Kasper, Burkhard; Rampp, Stefan; Coras, R.; Blumcke, I.; Buchfelder, Michael (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

Reorganization and Plasticity of the Language Network in Patients with Cerebral Gliomas - Nieberlein, Laura; Rampp, Stefan; Gussew, Alexander; Prell, Julian; Hartwigsen, Gesa (NeuroImage: Clinical, 2023)
Language is organized in large-scale networks in the human brain that show a strong potential for flexible interactions and adaptation. Neuroplasticity is the central mechanism that allows such dynamic modulation to changing conditions across the life span and is particularly important for network reorganization after brain lesions. Most studies on language reorganization focused on language recovery after stroke. Yet, a strong degree of adaptive neuroplasticity can also be observed in patients with brain tumors in language-eloquent brain areas. This review discusses key mechanisms for neural reorganization in patients with brain tumors. Our main aim is to elucidate the underlying mechanisms for intra- and interhemispheric plasticity in the language network in these patients. The following reorganization patterns are discussed: 1) Persisting function within the tumor; 2) Reorganization in perilesional regions; 3) Reorganization in a distributed network of the affected hemisphere; 4) Reorganization to the contralesional hemisphere. In this context, we shed light on language-related reorganization patterns in frontal and temporo-parietal areas and discuss their functional relevance. We also address tumor-related changes in structural and functional connectivity between eloquent brain regions. Thereby, we aim to expand the general understanding of the plastic potential of the neural language network and facilitate clinical decision-making processes for effective, function-preserving tumor treatment.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Brain lesion; Brain surgery; Direct electrical brain stimulation; EEG; fMRI; MEG; Resection; Speech; Transcranial magnetic stimulation; Tumor

Resection of cerebral gangliogliomas causing drug-resistant epilepsy: short- and long-term outcomes using intraoperative MRI and neuronavigation - Sommer, Bjoern; Wimmer, Cornelia; Coras, Roland; Blümcke, Ingmar; Lorber, Bogdan; Hamer, Hajo; Stefan, Hermann; Buchfelder, Michael; Roessler, Karl (Neurosurgical Focus, 2015)
OBJECT Cerebral gangliogliomas (GGs) are highly associated with intractable epilepsy. Incomplete resection due to proximity to eloquent brain regions or misinterpretation of the resection amount is a strong negative predictor for local tumor recurrence and persisting seizures. A potential method for dealing with this obstacle could be the application of intraoperative high-field MRI (iopMRI) combined with neuronavigation. METHODS Sixty-nine patients (31 female, 38 male; median age 28.5 ± 15.4 years) suffering from cerebral GGs were included in this retrospective study. Five patients received surgery twice in the observation period. In 48 of the 69 patients, 1.5-T iopMRI combined with neuronavigational guidance was used. Lesions close to eloquent brain areas were resected with the implementation of preoperative diffusion tensor imaging tractography and blood oxygenation level-dependent functional MRI (15 patients). RESULTS Overall, complete resection was accomplished in 60 of 69 surgical procedures (87%). Two patients underwent biopsy only, and in 7 patients, subtotal resection was accomplished because of proximity to critical brain areas. Excluding the 2 biopsies, complete resection using neuronavigation/iopMRI was documented in 33 of 46 cases (72%) by intraoperative imaging. Remnant tumor mass was identified intraoperatively in 13 of 46 patients (28%). After intraoperative second-look surgery, the authors improved the total resection rate by 9 patients (up to 91% [42 of 46]). Of 21 patients undergoing conventional surgery, 14 (67%) had complete resection without the use of iopMRI. Regarding epilepsy outcome, 42 of 60 patients with seizures (70%) became completely seizure free (Engel Class IA) after a median follow-up time of 55.5 ± 36.2 months. Neurological deficits were found temporarily in 1 (1.4%) patient and permanently in 4 (5.8%) patients. CONCLUSIONS Using iopMRI combined with neuronavigation in cerebral GG surgery, the authors raised the rate of complete resection in this series by 19%. Given the fact that total resection is a strong predictor of long-term seizure control, this technique may contribute to improved seizure outcome and reduced neurological morbidity.
EVALuna2:7260

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Resective surgery for medically refractory epilepsy using intraoperative MRI and functional neuronavigation: the Erlangen experience of 415 patients - Roessler, Karl; Hofmann, Andrea; Sommer, Bjoern; Grummich, Peter; Coras, Roland; Kasper, Burkhard; Hamer, Hajo; Blümcke, Ingmar; Stefan, Hermann; Nimsky, Christopher; Buchfelder, Michael (Neurosurgical Focus, 2016)
Intraoperative overestimation of resection volume in epilepsy surgery is a well-known problem that can lead to an unfavorable seizure outcome. Intraoperative MRI (iMRI) combined with neuronavigation may help surgeons avoid this pitfall and facilitate visualization and targeting of sometimes ill-defined heterogeneous lesions or epileptogenic zones and may increase the number of complete resections and improve seizure outcome.To investigate this hypothesis, the authors conducted a retrospective clinical study of consecutive surgical procedures performed during a 10-year period for epilepsy in which they used neuronavigation combined with iMRI and functional imaging (functional MRI for speech and motor areas; diffusion tensor imaging for pyramidal, speech, and visual tracts; and magnetoencephalography and electrocorticography for spike detection). Altogether, there were 415 patients (192 female and 223 male, mean age 37.2 years; 41% left-sided lesions and 84.9% temporal epileptogenic zones). The mean preoperative duration of epilepsy was 17.5 years. The most common epilepsy-associated pathologies included hippocampal sclerosis (n = 146 [35.2%]), long-term epilepsy-associated tumor (LEAT) (n = 67 [16.1%]), cavernoma (n = 45 [10.8%]), focal cortical dysplasia (n = 31 [7.5%]), and epilepsy caused by scar tissue (n = 23 [5.5%]).In 11.8% (n = 49) of the surgeries, an intraoperative second-look surgery (SLS) after incomplete resection verified by iMRI had to be performed. Of those incomplete resections, LEATs were involved most often (40.8% of intraoperative SLSs, 29.9% of patients with LEAT). In addition, 37.5% (6 of 16) of patients in the diffuse glioma group and 12.9% of the patients with focal cortical dysplasia underwent an SLS. Moreover, iMRI provided additional advantages during implantation of grid, strip, and depth electrodes and enabled intraoperative correction of electrode position in 13.0% (3 of 23) of the cases. Altogether, an excellent seizure outcome (Engel Class I) was found in 72.7% of the patients during a mean follow-up of 36 months (range 3 months to 10.8 years). The greatest likelihood of an Engel Class I outcome was found in patients with cavernoma (83.7%), hippocampal sclerosis (78.8%), and LEAT (75.8%). Operative revisions that resulted from infection occurred in 0.3% of the patients, from hematomas in 1.6%, and from hydrocephalus in 0.8%. Severe visual field defects were found in 5.2% of the patients, aphasia in 5.7%, and hemiparesis in 2.7%, and the total mortality rate was 0%.Neuronavigation combined with iMRI was beneficial during surgical procedures for epilepsy and led to favorable seizure outcome with few specific complications. A significantly higher resection volume associated with a higher chance of favorable seizure outcome was found, especially in lesional epilepsy involving LEAT or diffuse glioma.
EVALuna2:7327

Risk Factors for Poor Postoperative Outcome and Epileptic Symptoms in Patients Diagnosed with Cerebral Cavernous Malformations - Winter, Fabian; Blair, Lisa; Buchfelder, Michael; Rössler, Karl (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Objective Roughly 12 to 47% of individuals with cerebral cavernous malformations (CCM) are asymptomatic, while other people may present with symptoms such as epileptic seizures, neurologic deficits, and intracerebral hemorrhages (IH). The aim of this study was to report our experience of postoperative outcomes of patients diagnosed with CCMs. Patients and Methods We present a series of consecutive patients who underwent surgical treatment for a diagnosed CCM between January 2003 and March 2014. Data were retrospectively analyzed with respect to preoperative visits, operating reports, patient admission charts, and postoperative follow-up visits. The Engel scale was used to evaluate the outcome of patients with epileptic seizures. Results A total of 91 patients were included with a mean age of 38.8 ± 15 years (range: 2-72 years). Prior to surgery, 57 of these patients had epileptic seizures, while 25 patients recorded at least one episode of IH with a latency time of 6.7 ± 8.5 years (range: 3-240 months) in between hemorrhages. A CCM located within the brainstem was significantly associated with IH prior to surgery (p = 0.000). If the CCM was adjacent to an eloquent brain area, the postoperative outcome in terms of seizure control was significantly worse (p = 0.033). In addition, a trend for worsened outcomes according to the Engel scale was observed in patients with more than one seizure prior to surgery (p = 0.055). Conclusion Proximity of CCMs to eloquent brain areas is a risk factor for poor postoperative outcome with respect to a lower rate of medication reduction as well as a lower rate of epileptic seizure omission. This underlines the importance of patient-specific therapeutic approaches.
CRIS-Team Scopus Importer:2020-12-25
Keywords: cavernoma; cerebral cavernous malformation; epileptic symptoms; outcome

Risk reduction in dominant temporal lobe epilepsy surgery combining fMRI/DTI maps, neuronavigation and intraoperative 1.5-Tesla MRI - Roessler, Karl; Sommer, Bjoern; Grummich, Peter; Hamer, Hajo; Pauli, Elisabeth; Coras, Roland; Blümcke, Ingmar; Buchfelder, Michael (Stereotactic and Functional Neurosurgery, 2015)
In dominant temporal lobe epilepsy surgery, speech, memory and visual systems are at risk.Functional magnetic resonance imaging (fMRI) and diffusion tensor imaging combined with intraoperative neuronavigation and MRI were investigated retrospectively regarding risk reductions for favorable neurological and seizure outcome.Functional imaging risk maps were generated for 14 patients suffering from dominant temporal lobe epilepsy [7 with hippocampal sclerosis (HS), 7 with various lesions] and used for neuronavigation-guided tailored resection. Postoperative neurological and seizure outcome and complications were evaluated.None of the patients had postoperative speech dysfunction despite 2.3/3.6-cm mean hippocampal/neocortical resection. Verbal memory decline was found in 2 of the 14 (14.3%) patients, correlating with surgical lesions in fMRI memory-activated functional areas in the dominant posterior parahippocampal gyrus. Verbal memory scores did not statistically differ between the HS and the lesional group, neither pre- nor postoperatively. A contralateral visual field defect occurred in 1 patient (7.1%). An Engel class I seizure outcome was found in 12 patients (85.7%), and 11 were completely seizure free (78.6%) at a mean follow-up of 19.5 months.This retrospectively investigated protocol led to an excellent neurological and seizure outcome and a low complication rate in dominant temporal lobe epilepsy surgery.
EVALuna2:7287

Role of the adipocyte immune brain axis in Parkinson's disease: friend or foe? - Regensburger, Martin; Kinfe, Thomas Mehari (Neural Regeneration Research, 2023)
CRIS-Team Scopus Importer:2023-06-30

Safety and Efficacy of Vaptans in the Treatment of Hyponatremia from Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH): A Systematic Review and Meta-Analysis - Krisanapan, Pajaree; Tangpanithandee, Supawit; Thongprayoon, Charat; Pattharanitima, Pattharawin; Kleindienst, Andrea; Miao, Jing; Craici, Iasmina M.; Mao, Michael A.; Cheungpasitporn, Wisit (Journal of Clinical Medicine, 2023)
The utilization of vasopressin receptor antagonists, known as vaptans, in the management of hyponatremia among patients afflicted with the syndrome of inappropriate antidiuretic hormone (SIADH) remains a contentious subject. This meta-analysis aimed to evaluate the safety and efficacy of vaptans for treating chronic hyponatremia in adult SIADH patients. Clinical trials and observational studies were identified by a systematic search using MEDLINE, EMBASE, and Cochrane Database from inception through September 2022. The inclusion criteria were the studies that reported vaptans’ safety or efficacy outcomes compared to placebo or standard therapies. The study protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO; CRD 42022357307). Five studies were identified, comprising three RCTs and two cohort studies, enrolling a total of 1840 participants. Regarding short-term efficacy on days 4–5, vaptans exhibited a significant increase in serum sodium concentration from the baseline in comparison to the control group, with a weighted mean difference of 4.77 mmol/L (95% CI, 3.57, 5.96; I2 = 34%). In terms of safety outcomes, the pooled incidence rates of overcorrection were 13.1% (95% CI 4.3, 33.6; I2 = 92%) in the vaptans group and 3.3% (95% CI 1.6, 6.6; I2 = 27%) in the control group. Despite the higher correction rate linked to vaptans, with an OR of 5.72 (95% CI 3.38, 9.70; I2 = 0%), no cases of osmotic demyelination syndrome were observed. Our meta-analysis comprehensively summarizes the efficacy and effect size of vaptans in managing SIADH. While vaptans effectively raise the serum sodium concentration compared to placebo/fluid restriction, clinicians should exercise caution regarding the potential for overcorrection.
CRIS-Team Scopus Importer:2023-09-15
Keywords: hyponatremia; satavaptan; SIAD; SIADH; syndrome of inappropriate antidiuresis; syndrome of inappropriate antidiuretic hormone secretion; tolvaptan; V2R antagonists; vaptans; vasopressin receptor antagonist

Screening for Acromegaly in Patients with Carpal Tunnel Syndrome: A Prospective Study (ACROCARP) - Zoicas, Flavius; Kleindienst, Andrea; Mayr, Bernhard; Buchfelder, Michael; Megele, R.; Schöfl, Christof (Hormone and Metabolic Research, 2016)
Early diagnosis of acromegaly prevents irreversible comorbidities and facilitates surgical cure. Carpal tunnel syndrome (CTS) is common in acromegaly and patients have often undergone surgery for CTS prior to the diagnosis of acromegaly. We hypothesized that screening CTS-patients for acromegaly could facilitate active case-finding. We prospectively enrolled 196 patients [135 women, 56.9 (range 23-103) years] who presented with CTS for surgery. Patients were asked about 6 symptoms suggestive of acromegaly using a questionnaire calculating a symptom score (0-6 points), and insulin-like-growth factor 1 (IGF-1) was measured. If IGF-1 was increased, IGF-1 measurement was repeated, and random growth hormone (GH) and/or an oral glucose tolerance test (OGTT) with assessment of GH-suppression were performed. The mean symptom score was 1.7±1.3 points. Three patients reported the maximal symptom score of 6 points, but none of them had an increased IGF-1. There was no correlation between the symptom score and IGF-1-SDS (standard deviation score) (r=0.026; p=0.71). Four patients had an IGF-1>2 SDS. In 2 patients acromegaly was ruled out using random GH and OGTT. One patient had normal IGF-1 and random GH at follow-up. One patient refused further diagnostics. In this prospective cohort of patients with CTS, the observed frequency of acromegaly was at most 0.51% (95% CI 0.03 to 2.83%). In this prospective study, none of the 196 patients with CTS had proven acromegaly. Thus, we see no evidence to justify general screening of patients with CTS for acromegaly.
EVALuna2:2072

Selenium action in neuro-oncology - Yakubov, Eduard; Buchfelder, Michael; Eyupoglu, Ilker Y.; Savaskan, Nic E. (Biological trace element research, 2014)
The trace element selenium and selenocysteine-carrying selenoproteins play a pivotal role in the brain. Beside the essential function during development and maintenance of brain action, selenium has also been associated with several neurological and neuro-oncological conditions. Reliable supply of selenium is important since selenium compounds can affect tumor microenvironment and neoangiogenesis in malignant gliomas (WHO grade III and IV [glioblastoma, GBM]) via induction of apoptosis and alteration of matrix metalloproteinases expression. Here, we summarize recent findings focusing on the anti-toxicity and cancer-preventive properties of selenium and their implication in current multimodal therapies including temozolomide (Temodal), cyclophosphamide (Endoxan), and cisplatin (DDP, Platiblastin, and Platinol). We shed light on unintended side effects in chemotherapy and the developments of novel combinatorial chemotherapeutics with selenium compounds. We found that selenium and selenium compounds have dual action profiles with direct anti-cancer and chemotherapy-intensifier effects as well as neuroprotective and cytoprotective agents. Current selenium trials and selenium supplementation with focus on neuro-oncology will be discussed with regard to low-adequate-to-high/toxic selenium status.
EVALuna2:22848

SHH pathway inhibition is protumourigenic in adamantinomatous craniopharyngioma - Carreno, G.; Boult, J. K. R.; Apps, J.; Gonzalez-Meljem, J. M.; Haston, S.; Guiho, R.; Stache, C.; Danielson, L. S.; Koers, A.; Smith, L. M.; Virasami, A.; Panousopoulos, L.; et al. (Endocrine-Related Cancer, 2019)
Pharmacological inhibition of the sonic hedgehog (SHH) pathway can be beneficial against certain cancers but detrimental in others. Adamantinomatous craniopharyngioma (ACP) is a relevant pituitary tumour, affecting children and adults, that is associated with high morbidity and increased mortality in long-term follow up. We have previously demonstrated overactivation of the SHH pathway in both human and mouse ACP. Here, we show that this activation is ligand dependent and induced by the expression of SHH protein in a small proportion of tumour cells. We investigate the functional relevance of SHH signalling in ACP through magnetic resonance imaging (MRI)-guided preclinical studies using an ACP mouse model. Treatment with vismodegib, a clinically approved SHH pathway inhibitor, results in a significant reduction in median survival due to premature development of highly proliferative and vascularised undifferentiated tumours. Reinforcing the mouse data, SHH pathway inhibition in human ACP leads to a significant increase in tumour cell proliferation both ex vivo, in explant cultures, and in vivo, in a patient-derived xenograft model. Together, our results demonstrate a protumourigenic effect of vismodegib-mediated SHH pathway inhibition in ACP.
CRIS-Team WoS Importer:2019-03-15

Significant improvement in neuropsychological functions after awake craniotomy in a patient with Oligodendroglioma: A case report - Thomas, Mareike; Scheer, Maximilian; Spindler, Kai; Nieberlein, Laura; Hartwigsen, Gesa; Gussew, Alexander; Schob, Stefan; Prell, Julian; Strauss, Christian; Rampp, Stefan (Interdisciplinary Neurosurgery, 2023)
Objective: The goal of awake craniotomy in glioma patients is sparing of cognitive function. Previous investigations suggest that patients in the postoperative state may reach their preoperative level regarding domain-based criteria. Data on significant postoperative improvement beyond the preoperative level is sparse. This article examines the prospective neuropsychological assessment of a glioma patient who underwent awake craniotomy and has shown functional improvement exceeding preoperative levels. Methods: A 34-year-old patient with high premorbid cognitive function level who underwent awake craniotomy for left frontal oligodendroglioma was neuropsychologically assessed and took part in a fMRI-examination at 3 different time points. Results: Preoperative examination revealed severe isolated impairment of working memory, long-term narrative memory in free recall and recognition, and alertness with intact language production and comprehension. After transient global aphasia in the postoperative state, the follow-up examination showed significant improvement in memory and attention exceeding the preoperative level. Conclusions: Tumor location is an important factor in terms of surgical procedures. Cognitive impairment is, however, not always associated with a specific location. Mechanical pressure of the tumor might have led to the isolated consolidation deficit which fully recovered after tumor removal. Psychological disorders should be taken into account regarding prodromal symptoms of neurooncological diseases.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Awake craniotomy; Glioma; Improvement of cognitive functions; Neuropsychological assessment

Skull Base Chordomas and Chondrosarcomas - Kremenevski, Natalia; Schlaffer, Sven-Martin; Coras, Roland; Kinfe, Thomas Mehari; Graillon, Thomas; Buchfelder, Michael (Neuroendocrinology, 2020)
Skull base chordomas account for less than 0.2% and chondrosarcomas for less than 0.15% of all intracranial tumors. Although their clinical and imaging presentations are similar, they derive from different origins. Chordomas arise from embryonic remnants of the primitive notochord and chondrosarcomas from primitive mesenchymal cells or from the embryonic rest of the cranial cartilaginous matrix. Both entities are characterized by infiltration and destruction of the surrounding bone and soft tissue and a high locoregional recurrence rate. Chondrosarcomas, when treated with similar complex strategies, display a much better prognosis than chordomas. The overall survival is approximately 65% for chordomas and 80% for chondrosarcomas at 5 years and 30 and 50%, respectively, at 10 years. Chordomas are divided into the following 3 histological types: classical (conventional), chondroid, and dedifferentiated. Chondrosarcomas have conventional, mesenchymal, clear cell, and dedifferentiated subgroups. Both tumor entities often present with nonspecific symptoms, and headaches are the most reported initial symptom. Computed tomography and magnetic resonance imaging are required to determine the tumor localization and the extent of tumor growth. The treatment philosophy is to maximize tumor resection, minimize morbidity, and preserve function. Neurosurgical approaches commonly used for the resection of intracranial chordomas and chondrosarcomas are transsphenoidal, transbasal, cranio-orbitozygomatic, transzygomatic extended middle fossa, transcondylar, and transmaxillary approaches. Chordomas and chondrosarcomas are not sensitive to chemotherapy and there are no approved drugs for their treatment. The present treatment concept is a combination of surgical resection with a maximal excision and preserving patients' quality of life by adjuvant radiotherapy for both chordomas and chondrosarcomas.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Chondrosarcoma; Chordoma; Diagnosis; Skull base; Therapy

Slow-theta power decreases during item-place encoding predict spatial accuracy of subsequent context recall - Crespo-Garcia, Maite; Zeiller, Monika; Leupold, Claudia; Kreiselmeyer, Gernot; Rampp, Stefan; Hamer, Hajo; Dalal, Sarang S. (NeuroImage, 2016)
Human hippocampal theta oscillations play a key role in accurate spatial coding. Associative encoding involves similar hippocampal networks but, paradoxically, is also characterized by theta power decreases. Here, we investigated how theta activity relates to associative encoding of place contexts resulting in accurate navigation. Using MEG, we found that slow-theta (2-5Hz) power negatively correlated with subsequent spatial accuracy for virtual contextual locations in posterior hippocampus and other cortical structures involved in spatial cognition. A rare opportunity to simultaneously record MEG and intracranial EEG in an epilepsy patient provided crucial insights: during power decreases, slow-theta in right anterior hippocampus and left inferior frontal gyrus phase-led the left temporal cortex and predicted spatial accuracy. Our findings indicate that decreased slow-theta activity reflects local and long-range neural mechanisms that encode accurate spatial contexts, and strengthens the view that local suppression of low-frequency activity is essential for more efficient processing of detailed information.
EVALuna2:22490

Smartphone navigated endoscopic port surgery of hypertensive basal ganglia hemorrhage - Li, Fangye; Gan, Zhichao; Xu, Xinghua; Zhao, Yining; Wang, Qun; Chen, Chuanbiao; Liu, Hongyu; Xiong, Ruochu; Qi, Ziyu; Sun, Guochen; Zhang, Jiashu; Xu, Bainan; et al. (Journal of Clinical Neuroscience, 2022)
OBJECTIVE: Endoscopic port surgery is a promising alternative for the surgical treatment of intracerebral hypertensive basal ganglia hemorrhage (HBGH). The precise location of hematoma is a crucial step for surgery. The authors developed a simple, low-cost navigation method using an Android smartphone for the localization of HBGH. METHODS: All patients' CT DICOM data were processed with an open-source software (3D Slicer). The volume of hematoma, angle, and length of trajectory were calculated automatically. A smartphone running the Android system and the Compass APP was used to help insert the inner introducer. An endoscopic port system was applied to create a working channel for neuro-endoscopic hematoma evacuation. RESULTS: There were 27 patients enrolled in this study (mean age 56). All patients underwent successful surgical evacuation of HBGH with neuroendoscopic evacuation. The mean time taken for the surgical plan was 4 min. The total operation time from skin incision to final suture was 82.6 min. Compared with standard neuronavigation, mean error of trajectory was 5.1 mm. The mean preoperative hematoma volume was 44.8 ml. The optimal trajectory angle averaged 39.5°and the length was 71 mm. Intraoperative blood loss was about 45 ml. Post-operative hematoma volume was 2.9 ml, and the average evacuation rate was 93.6%. One week after surgery, the mean GCS score was improved from 8.2 to 13.8 (p < 0.01). CONCLUSIONS: This simple, low-cost navigation method using 3D Slicer, an Android smartphone with the Compass APP, helps precisely insert the endoscopic working channel to the desired point, which is crucial for satisfactory evacuation of HBGH.
CRIS-Team Scopus Importer:2022-07-01
Keywords: 3D Slicer; Endoscope; Hypertensive basal ganglia hemorrhage; Navigation; Smartphone

Somatic mutations are frequent events in corticotroph tumor progression causing Nelson's tumor - Perez-Rivas, Luis G.; Theodoropoulou, Marily; Puar, Troy H.; Fazel, Julia; Stieg, Mareike R.; Ferrau, Francesco; Assie, Guillaume; Gadelha, Monica R.; Deutschbein, Timo; Fragoso, Maria C.; Kusters, Benno; Saeger, Wolfgang; et al. (European Journal of Endocrinology, 2018)
Somatic mutations in the ubiquitin-specific protease 8 () gene are frequent in corticotroph tumors causing Cushing's disease (CD). Corticotroph tumor progression, the so-called Nelson's syndrome (NS), is a potentially life-threatening complication of bilateral adrenalectomy in patients with refractory CD that is caused by the development of an ACTH-secreting tumor of the pituitary gland. Whether alterations are also present in progressive Nelson's tumors has not been studied in detail so far.Retrospective, multicenter study involving tumors from 33 patients with progressive corticotroph tumors (29 females) and screening for somatic mutations on the mutational hotspot of the gene in the exon 14 with Sanger sequencing.Fifteen out of 33 tumors (45%) presented with a mutation in the exon 14 of , with c.2159C>A (p.Pro720Gln) being the most frequent (9/33), followed by c.2155_2157delTCC (p.Ser718del, 4/33) and c.2152T>C (p.Ser718Pro, 2/33). This prevalence is similar to that previously reported for CD. Mutations were found exclusively in females. Other variables, such as age at diagnosis with NS, body mass index, hyperpigmentation, visual field defects, adenoma size or mortality, did not significantly differ between patients with wild-type and mutant tumors. Patients with mutant tumors exhibited higher levels of plasma ACTH after surgery (median: 640 vs 112 pg/mL, = 0.03). No differences were observed in ACTH normalization (<50 pg/mL) and tumor control after surgery for Nelson's tumor.Somatic mutations in are common in Nelson's tumors, indicating that they do not drive the corticotroph tumor progression that leads to NS, and may be associated with a less favorable biochemical outcome after surgery for Nelson's tumor.
EVALuna2:51491

Spatially resolved transcriptomics and graph-based deep learning improve accuracy of routine CNS tumor diagnostics - Ritter, Michael; Blume, Christina; Tang, Yiheng; Patel, Areeba; Patel, Bhuvic; Berghaus, Natalie; Kada Benotmane, Jasim; Kückelhaus, Jan; Yabo, Yahaya; Zhang, Jiajia; Grabis, Elena; Villa, Giulia; et al. (Nature Cancer, 2025)
The diagnostic landscape of brain tumors integrates comprehensive molecular markers alongside traditional histopathological evaluation. DNA methylation and next-generation sequencing (NGS) have become a cornerstone in central nervous system (CNS) tumor classification. A limiting requirement for NGS and methylation profiling is sufficient DNA quality and quantity, which restrict its feasibility. Here we demonstrate NePSTA (neuropathology spatial transcriptomic analysis) for comprehensive morphological and molecular neuropathological diagnostics from single 5-µm tissue sections. NePSTA uses spatial transcriptomics with graph neural networks for automated histological and molecular evaluations. Trained and evaluated across 130 participants with CNS malignancies and healthy donors across four medical centers, NePSTA predicts tissue histology and methylation-based subclasses with high accuracy. We demonstrate the ability to reconstruct immunohistochemistry and genotype profiling on tissue with minimal requirements, inadequate for conventional molecular diagnostics, demonstrating the potential to enhance tumor subtype identification with implications for fast and precise diagnostic workup.
CRIS-Team Scopus Importer:2025-02-14

Spatiotemporal Pattern of Human Cortical and Subcortical Activity during Early-Stage Odor Processing - Stadlbauer, Andreas; Kaltenhauser, Martin; Buchfelder, Michael; Brandner, Sebastian; Neuhuber, Winfried; Renner, Bertold (Chemical Senses, 2016)
The dynamics of early-stage cortical and subcortical responses in the human brain to odor stimulation are currently unknown. The objective of the present study was to analyze spatiotemporal patterns of human brain activity during odor perception using magnetoencephalography (MEG). In 12 normosmic healthy subjects, we investigated the onset of brain activity in relation to ipsilateral and contralateral stimulation with 2 odorants. Olfactory stimuli (200ms duration) were applied using an olfactometer, and brain activity was recorded with a 248-magnetometer whole-head MEG system. Olfactory responses were identified shortly (within 150ms) after stimulus onset in both hemispheres. Stimulation on the ipsilateral side yielded signals earlier (starting at 90ms) compared with contralateral stimulation in the primary olfactory cortex, hippocampus, parahippocampal gyrus, amygdala, and orbitofrontal cortex (P < 0.001). The duration and peak amplitude of olfactory evoked magnetic fields were found to increase with increasing poststimulus time in the majority of the investigated cortical structures (P ≤ 0.019 and P ≤ 0.021). The study showed the locations of early olfactory brain activity in humans within 150ms after the onset of stimuli. Olfactory activation is processed on the ipsilateral side of stimulation in early stages. After a short delay of 34ms a corresponding pattern of activation was also seen in the contralateral hemisphere, indicating the functional connectivity between the 2 hemispheres in the anterior commissure.
EVALuna2:32855

Spectral fingerprints or spectral tilt? Evidence for distinct oscillatory signatures of memory formation - Fellner, Marie-Christin; Gollwitzer, Stephanie; Rampp, Stefan; Kreiselmeyr, Gernot; Bush, Daniel; Diehl, Beate; Axmacher, Nikolai; Hamer, Hajo; Hanslmayr, Simon (Plos Biology, 2019)
Decreases in low-frequency power (2-30 Hz) alongside high-frequency power increases (>40 Hz) have been demonstrated to predict successful memory formation. Parsimoniously, this change in the frequency spectrum can be explained by one factor, a change in the tilt of the power spectrum (from steep to flat) indicating engaged brain regions. A competing view is that the change in the power spectrum contains several distinct brain oscillatory fingerprints, each serving different computations. Here, we contrast these two theories in a parallel magnetoencephalography (MEG)-intracranial electroencephalography (iEEG) study in which healthy participants and epilepsy patients, respectively, studied either familiar verbal material or unfamiliar faces. We investigated whether modulations in specific frequency bands can be dissociated in time and space and by experimental manipulation. Both MEG and iEEG data show that decreases in alpha/beta power specifically predicted the encoding of words but not faces, whereas increases in gamma power and decreases in theta power predicted memory formation irrespective of material. Critically, these different oscillatory signatures of memory encoding were evident in different brain regions. Moreover, high-frequency gamma power increases occurred significantly earlier compared to low-frequency theta power decreases. These results show that simple spectral tilt cannot explain common oscillatory changes and demonstrate that brain oscillations in different frequency bands serve different functions for memory encoding.
CRIS-Team WoS Importer:2019-08-23

Spectral properties of bursts in therapeutic burst suppression predict successful treatment of refractory status epilepticus - Gollwitzer, Stephanie; Hopfengärtner, Rüdiger; Rampp, Stefan; Welte, Tamara; Madžar, Dominik; Lang, Johannes; Reindl, Caroline; Stritzelberger, Jenny; Köhn, Julia; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen B.; et al. (Epilepsy and Behavior, 2024)
Burst suppression (BS) on EEG induced by intravenous anesthesia (IVAT) is standard therapy for refractory status epilepticus (RSE). If BS has any independent therapeutic effect on RSE is disputed. We aimed to define EEG characteristics of BS predicting termination or recurrence of status after weaning. All RSE patients treated with IVAT while undergoing continuous EEG monitoring on the neurological intensive care unit between 2014 and 2019 were screened for inclusion. A one hour-period of visually preselected BS-EEG was analyzed. Bursts were segmented by a special thresholding technique and underwent power spectral analysis. Out of 48 enrolled patients, 25 (52.1 %) did not develop seizure recurrence (group Non SE) after weaning from IVAT; in 23 patients (47.9 %), SE reestablished (group SE). In group Non SE, bursts contained higher amounts of EEG delta power (91.59 % vs 80.53 %, p < 0.0001), while faster frequencies were more pronounced in bursts in group SE (theta: 11.38 % vs 5.41 %, p = 0.0008; alpha: 4.89 % vs 1.82 %, p < 0.0001; beta: 3.23 % vs 1.21 %, p = 0.0002). Spectral profiles of individual bursts closely resembled preceding seizure patterns in group SE but not in group Non SE. Accordingly, persistence of spectral composition of initial ictal patterns in bursts, suggests ongoing SE, merely interrupted but not altered by BS. Fast oscillations in bursts indicate a high risk of status recurrence after weaning from IVAT. EEG guided individualized sedation regimes might therefore be superior to standardized anesthesia protocols.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Intravenous anesthesia; Multimodal monitoring; Quantitative EEG

Status epilepticus in patients with glioblastoma: Clinical characteristics, risk factors, and epileptological outcome - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Balk, Stefanie; Reindl, Caroline; Madzar, Dominik; Uhl, Martin; Welte, Tamara; Brandner, Sebastian; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; et al. (Seizure-European Journal of Epilepsy, 2023)
Purpose: Epilepsy is a common comorbidity in patients with glioblastoma, however, clinical data on status epilepticus (SE) in these patients is sparse. We aimed to investigate the risk factors associated with the occurrence and adverse outcomes of SE in glioblastoma patients. Methods: We retrospectively analysed electronic medical records of patients with de-novo glioblastoma treated at our institution between 01/2006 and 01/2020 and collected data on patient, tumour, and SE characteristics. Results: In the final cohort, 292/520 (56.2 %) patients developed seizures, with 48 (9.4 % of the entire cohort and 16.4 % of patients with epilepsy, PWE) experiencing SE at some point during the course of their disease. SE was the first symptom of the tumour in 6 cases (1.2 %) and the first manifestation of epilepsy in 18 PWE (6.2 %). Most SE episodes occurred postoperatively (n = 37, 77.1 %). SE occurrence in PWE was associated with postoperative seizures and drug-resistant epilepsy. Adverse outcome (in-house mortality or admission to palliative care, 10/48 patients, 20.8 %), was independently associated with higher status epilepticus severity score (STESS) and Charlson Comorbidity Index (CCI), but not tumour progression. 32/48 SE patients (66.7 %) were successfully treated with first- and second-line agents, while escalation to third-line agents was successful in 6 (12.5 %) cases. Conclusion: Our data suggests a link between the occurrence of SE, postoperative seizures, and drug-resistant epilepsy. Despite the dismal oncological prognosis, SE was successfully treated in 79.2 % of the cases. Higher STESS and CCI were associated with adverse SE outcomes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Glioblastoma; Status epilepticus; Status epilepticus severity score (STESS)

Stent-Assisted Coiling Using Leo+ Baby Stent: Immediate and Mid-Term Results - Lücking, Hannes; Struffert, Tobias; Gölitz, Philipp; Engelhorn, Tobias; Brandner, Sebastian; Kuramatsu, Joji; Lang, Stefan; Schmidt, Manuel; Dörfler, Arnd (Clinical Neuroradiology, 2020)
Background: Stent-assisted coiling is well-established for treatment of cerebral aneurysms. The technique enables treatment of wide-neck, bifurcation and recurrent aneurysms with high packing rates. While described in extenso for laser cut stents, the results of patients treated with the Leo+ Baby (Balt, Montmorency, France) braided microstent are presented. Material and Methods: Patients were included if treated with a Leo+ Baby and with digital subtraction angiography (DSA) follow-up available of at least 6 months. Data were evaluated for successful deployment, aneurysm occlusion according to the modified Raymond-Roy classification (MRRC), stent patency and procedure-related morbidity and mortality. Results: A total of 81 patients were included and Leo+ Baby deployment was successful in all cases. Coils were used in 80 cases. In 1 case 2 stents were used stent-in-stent without additional coiling. Initial aneurysm occlusion rates were MRRCi1 51.9%, MRRCi2 11.1%, MRRCi3a 24.7% and MRRCi3b 12.3%. Occlusion rates after 6 months were MRRC6m1 78.9%, MRRC6m2 3.9%, MRRC6m3a 6.6% and MRRC6m3b 10.5%. Procedure-related morbidity was 1 case of acute stent thrombosis successfully treated with tirofiban and 1 case with transient hemiparesis due to stent thrombosis after 4 months. There was 1 case of coil-associated subarachnoid hemorrhage (SAH) which caused prolonged hospitalization. No procedure-related mortality was observed. Conclusion: The results confirm that stent-assisted coiling with the Leo+ Baby stent is safe and efficient for treatment of wide neck or recurrent cerebral aneurysms. Spontaneous progressive aneurysm occlusion over 6 months supports the theory of considerable flow-modulating effects of Leo+ Baby.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Bifurcation aneurysm; Braided stent; Cerebral aneurysm; Coiling; Low profile stent

Stereotactic radiotherapy as primary definitive or postoperative treatment of intracranial meningioma of WHO grade II and III leads to better disease control than stereotactic radiotherapy of recurrent meningioma - Lubgan, Dorota; Rutzner, Sandra; Lambrecht, Ulrike; Roessler, Karl; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Fietkau, Rainer; Semrau, Sabine (Journal of Neuro-Oncology, 2017)
The aim of this study was to evaluate long-term clinical outcome, prognostic factors and quality of life after adjuvant or definitive fractionated stereotactic radiotherapy (SRT) of meningioma WHO grade II and III or at recurrence. 131 patients with 138 meningioma (64 WHO grade II, 16 WHO grade III, 58 without histology) of the skull base, falx and convexity were treated between 01/2002 and 01/2015 at the Erlangen University Hospital by fractionated stereotactic radiotherapy (SRT) as primary treatment (adjuvant or definitive) and at recurrence. 53% (n = 53) lesions of patients with primary tumour received postoperative SRT and 47% (n = 47) as definitive treatment (without surgery). All 38 lesions (100%) of recurrent meningioma underwent surgery followed by SRT. SRT was mostly given in 28, 30 or 25 fractions to a median dose of 54.0 Gy in the reference point. Progression-free-survival at 8 years for patients with meningioma at primary treatment were significantly better with 100% for patients with definitive SRT (p = 0.008) or 85% for patients with adjuvant SRT (p = 0.009) compared to 42% after treatment (surgery + SRT) of recurrence. Progression-free-survival at 8 years for patients with SRT as adjuvant treatment after gross total resection of WHO grade II meningioma were significantly better at 83% (p = 0.016) compared to 46% after adjuvant SRT of recurrence. In 31% of patients after primary treatment and in 38.5% after recurrence treatment an improvement of pain symptoms was achieved. The favourable prognostic factor for better PFS at recurrence treatment was tumor location (skull base or convexity better compared to the falx). Postoperative SRT of WHO grade II meningioma after gross total resection (GTR) can effectively reduce recurrence risk.
EVALuna2:32870

Stereotactic radiotherapy of vestibular schwannoma : Hearing preservation, vestibular function, and local control following primary and salvage radiotherapy - Putz, Florian; Müller, Jan; Wimmer, Cornelia; Goerig, Nicole; Knippen, Stefan; Iro, Heinrich; Grundtner, Philipp; Eyüpoglu, Ilker Yasin; Roessler, Karl; Semrau, Sabine; Fietkau, Rainer; Lettmaier, Sebastian (Strahlentherapie und Onkologie, 2017)
OBJECTIVE: The aim of this publication is to present long-term data on functional outcomes and tumor control in a cohort of 107 patients treated with stereotactic radiotherapy (RT) for vestibular schwannoma. PATIENTS AND METHODS: Included were 107 patients with vestibular schwannoma (primary or recurrent following resection) treated with stereotactic RT (either fractioned or single-dose radiosurgery) between October 2002 and December 2013. Local control and functional outcomes were determined. Analysis of hearing preservation was limited to a subgroup of patients with complete audiometric data collected before treatment and during follow-up. Vestibular function test (FVT) results could be analyzed in a subset of patients and were compared to patient-reported dizziness. RESULTS: After a mean follow-up of 46.3 months, actuarial local control for the whole cohort was 100% after 2, 97.6% after 5, and 94.1% after 10 years. In patients with primary RT, serviceable hearing was preserved in 72%. Predictors for preservation of serviceable hearing in multivariate analysis were time of follow-up (odds ratio, OR = 0.93 per month; p = 0.021) and pre-RT tumor size (Koos stage I-IIa vs. IIb-IV; OR = 0.15; p = 0.031). Worsening of FVT results was recorded in 17.6% (N = 3). Profound discrepancy of patient-reported dizziness and FVT results was observed after RT. In patients with primary RT, worsening of facial nerve function occurred in 1.7% (N = 1). CONCLUSION: Stereotactic RT of vestibular schwannoma provides good functional outcomes and high control rates. Dependence of hearing preservation on time of follow-up and initial tumor stage has to be considered.
EVALuna2:32910

Study on the Impact of CMV-Encephalopathy on the Survival of Brain Cancer Patients Undergoing Radio(Chemo) therapy of the Brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, M. A.; Engelhorn, Tobias; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, F.; et al. (2017)
EVALuna2:32868

Subacute Degeneration of Fibers After Vertical Parasagittal Hemispherotomy - Hittinger, Markus; Hartlieb, Till; Heiland, Dieter Henrik; Heiland, Pamela; Pieper, Tom; Staudt, Martin; Berlis, Ansgar; Kudernatsch, Manfred; Mader, Irina (Clinical Neuroradiology, 2024)
Purpose: After vertical parasagittal hemispherotomy a restricted diffusion is often seen ipsilaterally and even distant from the adjacent resection margin. This retrospective cohort study analyses the anatomic site and the time course of the diffusion restriction after vertical parasagittal hemispherotomy. Methods: Fifty-nine patients were included into this study, all of them having had one pre-operative and at least one post-operative MRI, including diffusion imaging at b‑values of 0 and 1000 s/mm2 with a calculated ADC. Results: Diffusion restriction occurred exclusively on the operated site in all patients. In the basal ganglia, diffusion restriction was present in 37 of 38 patients at the first postoperative day with a duration of 38 days. In the midbrain, the posterior limb of the internal capsule and the thalamus, a restricted diffusion became postoperatively prominent at day 9 in all three localizations, with a duration of 36, 34 and 36 days, respectively. The incidence of thalamic lesions was lower if a preoperative damage had occurred. Conclusion: The restricted diffusion in the basal ganglia resembles direct effects of the operation at its edges, whereas the later appearing diffusion restriction in the midbrain and the posterior limb of the internal capsule rather belong to a degeneration of the descending fibers being transected by the hemispherotomy in the sense of a Wallerian degeneration. The presence of preoperative hemispheric lesions influences the development of diffusion restriction at subacute fiber degeneration.
CRIS-Team Scopus Importer:2024-07-05
Keywords: Diffusion restriction; Preoperative hemispheric lesions; Vertical parasagittal hemispherotomy; Wallerian degeneration

Successful Surgery of Exophytic Brainstem Glioma Mimicking Cerebellar-Pontine Angle Tumor: Case Report and Review of Literature - Roessler, Karl; Heynold, Elisabeth; Coras, Roland; Lücking, Hannes; Buchfelder, Michael (World Neurosurgery, 2019)
Background: Nontectal plate exophytic brainstem gliomas with pilocytic histology are rare and occur mainly in children. Because of their eloquent location, therapy usually consists of bioptic histologic verification and radiotherapy in case of progression. Case Description: We report on a 43-year-old patient who presented with intermittent tinnitus and reduced hearing in his left ear, as well as a slight left-sided ataxia. Magnetic resonance imaging revealed a left-sided solid cystic cerebellar-pontine angle (CPA) tumor completely obliterating the CPA. Radiologically, a solid cystic vestibular schwannoma was diagnosed. Intraoperatively, a glossy-grayish, intensively bleeding tumor without any capsule or delineation to the brainstem or cranial nerves was resected using electrophysiologic monitoring. Postoperative histology revealed a pilocytic astrocytoma. Three months postoperatively, hearing was preserved (pure tone average—35 dB) and ataxia was equal to what it was preoperatively, gradually becoming better. Postoperative magnetic resonance scans demonstrated a complete resection of the tumor with completely restored brainstem contours. Conclusions: Exophytic brainstem gliomas may occur in the CPA and mimic vestibular schwannoma. Complete resection even with preserved hearing without neurologic deterioration may be feasible.
EVALuna2:204027
Keywords: Cerebellar-pontine angle; Complete resection; Pilocytic astrocytoma; Vestibular schwannoma hearing preservation

Successful surgery of the hypothalamic region: Yes, we can! - Buchfelder, Michael (Endocrine, 2018)
EVALuna2:214800

Sulfasalazine impacts on ferroptotic cell death and alleviates the tumor microenvironment and glioma-induced brain edema. - Sehm, Tina; Fan, Zheng; Ghoochani, Ali; Rauh, Manfred; Engelhorn, Tobias; Minakaki, Georgia; Dörfler, Arnd; Klucken, Jochen; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai (Oncotarget, 2016)
The glutamate transporter xCT (SCL7a11, system Xc-, SXC) is an emerging key player in glutamate/cysteine/glutathione homeostasis in the brain and in cancer. xCT expression correlates with the grade of malignancy. Here, we report on the use of the U.S. Food and Drug Administration and EMA-approved xCT inhibitor, sulfasalazine (SAS) in gliomas. SAS does not affect cell viability in gliomas at concentrations below 200 µM. At higher concentrations SAS becomes gliomatoxic. Mechanistically SAS inhibits xCT and induces ferroptotic cell death in glioma cells. There is no evidence for impact on autophagic flux following SAS application. However, SAS can potentiate the efficacy of the standard chemotherapeutic and autophagy-inducing agent temozolomide (Temcat, Temodal or Temodar®). We also investigated SAS in non-transformed cellular constituents of the brain. Neurons and brain tissue are almost non-responding to SAS whereas isolated astrocytes are less sensitive towards SAS toxicity compared to gliomas. In vivo SAS treatment does not affect experimental tumor growth and treated animals revealed comparable tumor volume as untreated controls. However, SAS treatment resulted in reduced glioma-derived edema and, hence, total tumor volume burden as revealed by T2-weighted magnetic resonance imaging. Altogether, we show that SAS can be utilized for targeting the glutamate antiporter xCT activity as a tumor microenvironment-normalizing drug, while crucial cytotoxic effects in brain tumors are minor.

Sunitinib impedes brain tumor progression and reduces tumor-induced neurodegeneration in the microenvironment - Hatipoglu, Gökce; Hock, Stefan; Weiss, Ruth; Fan, Zheng; Sehm, Tina; Ghoochani, Ali; Buchfelder, Michael; Savaskan, Nicolai E.; Eyüpoglu, Ilker Yasin (Cancer Science, 2015)
Malignant gliomas can be counted to the most devastating tumors in humans. Novel therapies do not achieve significant prolonged survival rates. The cancer cells have an impact on the surrounding vital tissue and form tumor zones, which make up the tumor microenvironment. We investigated the effects of sunitinib, a small molecule multitargeted receptor tyrosine kinase inhibitor, on constituents of the tumor microenvironment such as gliomas, astrocytes, endothelial cells, and neurons. Sunitinib has a known anti-angiogenic effect. We found that sunitinib normalizes the aberrant tumor-derived vasculature and reduces tumor vessel pathologies (i.e. auto-loops). Sunitinib has only minor effects on the normal, physiological, non-proliferating vasculature. We found that neurons and astrocytes are protected by sunitinib against glutamate-induced cell death, whereas sunitinib acts as a toxin towards proliferating endothelial cells and tumor vessels. Moreover, sunitinib is effective in inducing glioma cell death. We determined the underlying pathways by which sunitinib operates as a toxin on gliomas and found vascular endothelial growth factor receptor 2 (VEGFR2, KDR/Flk1) as the main target to execute gliomatoxicity. The apoptosis-inducing effect of sunitinib can be mimicked by inhibition of VEGFR2. Knockdown of VEGFR2 can, in part, foster the resistance of glioma cells to receptor tyrosine kinase inhibitors. Furthermore, sunitinib alleviates tumor-induced neurodegeneration. Hence, we tested whether temozolomide treatment could be potentiated by sunitinib application. Here we show that sunitinib can amplify the effects of temozolomide in glioma cells. Thus, our data indicate that combined treatment with temozolomide does not abrogate the effects of sunitinib. In conclusion, we found that sunitinib acts as a gliomatoxic agent and at the same time carries out neuroprotective effects, reducing tumor-induced neurodegeneration. Thus, this report uncovered sunitinib's actions on the brain tumor microenvironment, revealing novel aspects for adjuvant approaches and new clinical assessment criteria when applied to brain tumor patients.
EVALuna2:22836

Support Needs of Patients with Cushing's Disease and Cushing's Syndrome: Results of a Survey Conducted in Germany and the USA - Kreitschmann-Andermahr, Ilonka; Siegel, Sonja; Gammel, Christa; Campbell, Karen; Edwin, Leslie; Grzywotz, Agnieszka; Kuhna, Victoria; Koltowska-Haggstrom, Maria; Mueller, Oliver; Buchfelder, Michael; Kleist, Bernadette (International Journal of Endocrinology, 2018)
Background: Cushing's disease (CD) and Cushing's syndrome (CS) are chronic illnesses, characterized by symptoms of prolonged hypercortisolism, which often changes to hypocortisolism after successful treatment. In view of the high disease burden of CD/CS patients and long-term impaired quality of life, the present survey was conducted to gain information about subjective illness distress and patients' specific needs in terms of supportive measures beyond medical interventions. Patients and Methods: Cross-sectional questionnaire study including patients with CD treated in 2 German neurosurgical tertiary referral centers and CD/CS patient members of a US-based patient support group completed a survey inquiring about disease burden, coping strategies, and support needs. Additionally, the degree of interest in different offers, e.g., internet-based programs and seminars, was assessed. Results: 84 US and 71 German patients answered the questionnaire. Patients in both countries indicated to suffer from Cushing-related symptoms, reduced performance, and psychological problems. 48.8% US patients and 44.4% German patients stated that good medical care and competent doctors helped them the most in coping with the illness. US patients were more interested in support groups (p = 0.035) and in courses on illness coping (p = 0.008) than the German patients, who stated to prefer brochures (p = 0.001). 89.3% of US patients would attend internet-based programs compared to 75.4% of German patients (p = 0.040). There were no differences between groups for the preferred duration of and the willingness to pay for such a program, but US patients would travel longer distances to attend a support meeting (p = 0.027). Conclusion: Patients in both countries need skilled physicians and long-term medical care in dealing with the effects of CD/CS, whereas other support needs differ between patients of both countries. The latter implies that not only disease-specific but also culture-specific training programs would need to be considered to satisfy the needs of patients in different countries.
EVALuna2:214807

Supra-complete surgery via dual intraoperative visualization approach (DiVA) prolongs patient survival in glioblastoma - Eyüpoglu, Ilker Yasin; Hore, Nirjhar; Merkel, Andreas; Buslei, Rolf; Buchfelder, Michael; Savaskan, Nicolai (Oncotarget, 2016)
Safe and complete resection represents the first step in the treatment of glioblastomas and is mandatory in increasing the effectiveness of adjuvant therapy to prolong overall survival. With gross total resection currently limited in extent to MRI contrast enhancing areas, the extent to which supra-complete resection beyond obvious contrast enhancement could have impact on overall survival remains unclear. DiVA (dual intraoperative visualization approach) redefines gross total resection as currently accepted by enabling for the first time supra-complete surgery without compromising patient safety. This approach exploits the advantages of two already accepted surgical techniques combining intraoperative MRI with integrated functional neuronavigation and 5-ALA by integrating them into a single surgical approach. We investigated whether this technique has impact on overall outcome in GBM patients. 105 patients with GBM were included. We achieved complete resection with intraoperative MRI alone according to current best-practice in glioma surgery in 75 patients. 30 patients received surgery with supra-complete resection. The control arm showed a median life expectancy of 14 months, reflecting current standards-of-care and outcome. In contrast, patients receiving supra-complete surgery displayed significant increase in median survival time to 18.5 months with overall survival time correlating directly with extent of supra-complete resection. This extension of overall survival did not come at the cost of neurological deterioration. We show for the first time that supra-complete glioma surgery leads to significant prolongation of overall survival time in GBM patients.
EVALuna2:7326

Surgery for Prolactinomas to Date - Buchfelder, Michael; Zhao, Yining; Schlaffer, Sven-Martin (Neuroendocrinology, 2019)
While in the past surgery for prolactinomas was a competitive option to medical treatment with dopamine agonists, to date the indications for operations are restricted to only a few specific situations. However, if a patient is intolerant to medical treatment or if the drugs are not sufficiently effective in terms of lowering prolactin levels or tumor shrinkage, surgery should always be considered. In microprolactinomas, operations can achieve excellent prolactin normalization rates. In tumors difficult to treat, the combination of surgical tumor resection and long-term medical treatment supports better control of the disease. The individual indications, results, techniques, and complications of operations for prolactinomas are briefly reviewed in this paper.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Medical treatment; Prolactinoma; Surgery; Technical advances

Surgical debulking of pituitary adenomas improves responsiveness to octreotide lar in the treatment of acromegaly - Fahlbusch, Rudolf; Kleinberg, David; Biller, Beverly; Bonert, Vivien; Buchfelder, Michael; Cappabianca, Paolo; Carmichael, John; Chandler, William; Colao, Annamaria; George, Ajax; Klibanski, Anne; Knopp, Edmond; et al. (Pituitary, 2017)
BACKGROUND: Studies comparing primary medical treatment of acromegaly with surgery are often non-randomized, and not stratified by illness severity. We prospectively compared primary medical therapy with pituitary surgery in patients with acromegaly. All patients had macroadenomas, at least one random human growth hormone (GH) level ≥12.5 ng/mL, elevated IGF-I levels and failure to suppress GH to <1 ng/mL during an oral glucose tolerance test (oGTT). METHODS: Forty-one patients from seven centers were randomized to primary treatment with octreotide LAR, 30 mg every 4 weeks × 3 months (ARM A, N = 15), or pituitary surgery (ARM B, N = 26) using a 1:2 randomization design. Patients cured by surgery (defined as nadir GH during oGTT <1 ng/mL and normal IGF-I) received no subsequent treatment. Those not cured surgically were then treated with octreotide LAR (SubArm B1) for 3 months. RESULTS: Only one of the 15 patients in ARM A (6.7%) had normalization of both GH and IGF-I. In contrast, 13/26 patients had normalization of both GH and IGF-I after surgery alone (50%). Of the remaining 13 patients who did not normalize with surgery alone, treatment with octreotide LAR resulted in a normal nadir GH and normal serum IGF-I in 7 (53.9%). In total, 20/26 in ARM B (76.9%) experienced normalization of defined biochemical acromegaly parameters. CONCLUSIONS: Pituitary surgery alone was more effective than primary medical treatment (p = 0.006), and the combination of surgery followed by medical therapy was even more effective (p < 0.0001). Subjects treated with medical therapy after surgical debulking had a significant improvement in response rate compared to matched subjects treated with primary medical therapy.
EVALuna2:102193

Surgical hematoma evacuation of cortical intracerebral hemorrhage ≥10 ml reduces risk of subsequent epilepsy by more than 70%: A retrospective monocenter study - Welte, Tamara; Steidl, Josephine; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Rampp, Stefan; Maslarova, Anna; Brandner, Sebastian; Hock, Stefan; Mühlen, Iris; Dörfler, Arnd; et al. (European Journal of Neurology, 2022)
Aim: The aim of this study was to re-evaluate risk factors for post-ICH epilepsy (PICHE) and examine the impact of surgical hematoma evacuation on epilepsy development after ICH. Background and purpose: Epilepsy is a common complication after intracerebral hemorrhage (ICH). Information on risk factors is still scarce and the role of ICH evacuation remains uncertain. Methods: We retrospectively included patients with spontaneous ICH treated in our hospital in 2006–2019. Patients' medical records were analyzed. In addition, mailed questionnaires and telephone interviews were used to complete the dataset. Uni- and multivariable hazard ratios (HRs) were applied to investigate risk factors for PICHE and the impact of surgical ICH evacuation. Results: Among 587 ICH patients available for analyses, 139 (23.7%) developed PICHE (mean follow-up 1795 ± 1378 days). The median time of epilepsy onset was 7 months after ICH (range 1–132 months). Risk factors associated with PICHE were cortical hemorrhage (multivariable HR 1.65 [95% CI 1.14–2.37]; p = 0.008), ICH volume > 10 ml (multivariable HR 1.91 [95% CI 1.33–2.73]; p < 0.001) and acute symptomatic seizures (multivariable HR 1.81 [95% CI 1.20–2.75]; p = 0.005). Patients with cortical ICH > 10 ml who underwent surgical hematoma evacuation were less likely to develop epilepsy than those with conservative treatment alone (multivariable HR 0.26 [95% CI 0.08–0.84]; p = 0.025). Conclusions: Post-ICH epilepsy is frequent and predicted by large cortical ICH and acute symptomatic seizures. Hematoma evacuation reduced the risk of PICHE by more than 70% in patients with large cortical ICH. This finding could be considered in the clinical decision making on the acute treatment of ICH.
CRIS-Team Scopus Importer:2022-10-21
Keywords: CAVE score; hematoma evacuation; intracerebral hemorrhage; post-stroke epilepsy

Surgical management of epilepsy due to cerebral cavernomas using neuronavigation and intraoperative MR imaging - Sommer, Bjoern; Kasper, Burkhard S.; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Roessler, Karl (Neurological Research, 2013)
Objectives: Cure from seizures due to cavernomas might be surgically achieved dependent on both, the complete removal of the cavernoma as well as its surrounding hemosiderin rim. High field intraoperative MRI imaging (iopMRI) and neuronavigation might play a crucial role to achieve both goals. We retrospectively investigated the long-term results and impact of intraoperative 1.5T MRI (iopMRI) and neuronavigation on the completeness of surgical removal of a cavernous malformation (CM) and its perilesional hemosiderin rim as well as reduction of surgical morbidity. Methods: 26 patients (14 female, 12 male, mean age 39.1 years, range: 17-63 years) with CM related epilepsy were identified. Eighteen patients suffered from drug resistant epilepsy (69.2%). Mean duration of epilepsy was 11.9 years in subjects with drug resistant epilepsy (n = 18) and 0.3 years in subjects presenting with first-time seizures (n = 8). We performed 24 lesionectomies and two lesionectomies combined with extended temporal resections. Seven lesions were located extratemporally. Results: Complete CM removal was documented by postsurgical MRI in all patients. As direct consequence of iopMRI, refined surgery was necessary in 11.5% of patients to achieve complete cavernoma removal and in another 11.5% for complete resection of additional adjacent epileptogenic cortex. Removal of the hemosiderin rim was confirmed by iopMRI in 92% of patients. Two patients suffered from mild (7.7%) and one from moderate (3.8%) visual field deficits. Complete seizure control (Engel class 1A) was achieved in 80.8% of patients with a mean follow-up period of 47.7 months. Discussion: We report excellent long-term seizure control with minimal surgical morbidity after complete resection of CM using our multimodal approach. © W. S. Maney & Son Ltd 2013.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cavernous hemangioma; Epilepsy outcome; Intraoperative high field MRI; Surgical morbidity

Surgical planning, histopathology findings and postoperative outcome in MR-negative extra-temporal epilepsy using intracranial EEG, functional imaging, magnetoencephalography, neuronavigation and intraoperative MRI. - Maslarova, Anna; Zhao, Yining; Rösch, Julie; Dörfler, Arnd; Coras, Roland; Blümcke, Ingmar; Lang, Johannes; Schmidt, Manuel; Hamer, Hajo; Reindl, Caroline; Welte, Tamara; Rampp, Stefan; et al. (Clinical Neurology and Neurosurgery, 2023)
OBJECTIVE: MRI-negative drug-resistant epilepsy presents a challenge when it comes to surgical planning, and surgical outcome is worse than in cases with an identified lesion. Although increasing implementation of more powerful MRI scanners and artificial intelligence has led to the detection of previously unrecognizable lesions, in some cases even postoperative pathological evaluation of electrographically epileptogenic zones shows no structural alterations. While in temporal lobe epilepsy a standardized resection approach can usually be performed, the surgical management of extra-temporal lesions is always individual. Here we present a strategy for treating patients with extra-temporal MRI-negative epilepsy focus and report our histological findings and patient outcome. METHODS: Patients undergoing epilepsy surgery in the Department of Neurosurgery at the University Hospital Erlangen between 2012 and 2020 were included in the study. Inclusion criteria were: (1) failure to identify a structural lesion on preoperative high-resolution 3 Tesla MRI with a standardized epilepsy protocol and (2) preoperative intracranial EEG (iEEG) diagnostics. RESULTS: We identified 8 patients corresponding to the inclusion criteria. Second look MRI analysis by an experienced neuroradiologist including the most recent analysis algorithm utilized in our clinic revealed a possible lesion in two patients. One of the patients with a clear focal cortical dysplasia (FCD) finding on a second look was excluded from further analysis. Of the other 7 patients, in one patient iEEG was performed with subdural electrodes, whereas the other 6 were evaluated with depth electrodes. MEG was performed preoperatively in all but one patient. An MEG focus was implemented in resection planning in 3 patients. FDG PET was performed in all, but only implemented in one patient. Histopathological evaluation revealed one non-lesional case, 4 cases of FCD and 2 cases with mild developmental malformation. All patients were free from permanent neurological deficits and presented with Engel 1A or 1B outcome on the last follow-up. CONCLUSION: We demonstrate that extra-temporal MRI-negative epilepsy can be treated successfully provided an extensive preoperative planning is performed. The most important diagnostic was stereo-EEG, whereas additional data from MEG was helpful and FDG PET was rarely useful in our cohort.
EVALuna2:522951

Surgical Technique and Efficacy Analysis of Extra-pseudocapsular Transnasal Transsphenoidal Surgery for Pituitary Microprolactinoma - Wan, Xue-Yan; Li, Lin-Han; Chen, Juan; Wang, Jun-Wen; Liu, Yan-Chao; Huang, Yi-Min; Shu, Kai; Buchfelder, Michael; Fahlbusch, Rudolf; Lei, Ting (Current Medical Science, 2022)
Objective: To elucidate the role of transsphenoidal surgery in the treatment of pituitary microprolactinoma. Methods: The clinical data of 107 prolactinoma cases treated by extra-pseudocapsular transnasal transsphenoidal surgery (ETTS) for different indications in our department since 2011 was retrospectively analyzed. Results: The most common indication was the ineffectiveness of oral medication (41.1%), followed by the personal willingness of the patient (35.5%), and 20.6% of the patients were young women with clear tumor boundaries. The pseudocapsule was not observed in 63 cases (58.9%), incomplete pseudocapsule was observed in 26 cases (24.3%), and complete pseudocapsule in 18 cases (16.8%). A total of 97 patients (90.7%) obtained 1-year post-operation remission. According to the relative location of the adenoma and pituitary gland on the MRI scan, 46 patients were classified into a central type, 59 a lateral type, and 2 a supra-pituitary type. Two patients developed hypogonadism, one patient developed hypocortisolism, and one patient developed post-operative hypothyroidism. Two patients were administrated with hormone replacement treatment, and the treatment was stopped within one week. There was no permanent hypopituitarism. Further investigation demonstrated that the adenoma types could affect the remission rates of hyperprolactinemia and gross total resection rate in microprolactinoma. Conclusion: ETTS was an effective treatment for pituitary microprolactinomas. This could be the first choice for patients who presented enclosed adenoma on the MRI and were potentially curable in a preoperative evaluation. Maximal safe removal of the adenoma by ETTS with the aim to increase the sensitivity of the drugs was also recommended for patients with invasive dopamine agonist resistant prolactinomas and patients with difficulty in childbirth.
CRIS-Team WoS Importer:2023-01-13

Surgical treatment of aggressive pituitary adenomas and pituitary carcinomas - Buchfelder, Michael; Schlaffer, Sven-Martin (Reviews in Endocrine & Metabolic Disorders, 2020)
Surgery of aggressive pituitary adenomas and pituitary carcinomas is part of the interdisciplinary management of these difficult to treat tumors. Invasion, giant size and unusual, asymmetric extent of these tumors frequently require modifications or extensions of the standard approaches for transsphenoidal and transcranial surgery. Frequently, only debulking procedures can be performed. In aggressive and hormone secreting adenomas, the remission rates achieved by surgery alone are relatively poor and adjuvant medical treatments or irradiation are needed. Safe resection of as much tumor as possible and symptomatic control is aimed at, rather than remission. Many procedures are required for rapid progression of lesions or recurrences, in order to extend the survival of the patients. Metastases of pituitary carcinomas within the cranial cavity or spine can be attacked. Since they can occur anywhere in the brain or spinal canal they require the entire battery of neurosurgical approaches. Unfortunately, in this group of pituitary tumors, the complication rates are higher than in primary operations of enclosed adenomas. The respective techniques with their facilities and limitations are reviewed in this article.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Aggressive growth; Cavernous sinus; Interdisciplinary management; Invasive adenoma; Pituitary carcinomas; Transcranial surgery; Transsphenoidal surgery

Surgical treatment outcome on a national cohort of 176 patients with cervical manifestation of rheumatoid arthritis - Macdowall, Anna; Barany, Laszlo; Bodon, Gergely (Journal of Craniovertebral Junction and Spine, 2021)
Purpose: Rheumatoid arthritis (RA) affecting the cervical spine results in instability and deformity that can be divided into the subtypes C1-C2 horizontal (atlantoaxial instability), C0-C2 vertical (basilar invagination), subaxial, and combined instabilities. The aim of this study was to compare the surgical treatments and outcomes of RA-related deformity and instability in a population-based setting.
CRIS-Team WoS Importer:2022-02-25

Surveillance Imaging Strategies for Pituitary Adenomas: When, How Frequent, and When to Stop - Yuen, Kevin C.J.; Ghalib, Luma; Buchfelder, Michael; Hughes, Jeremy; Langlois, Fabienne; Molitch, Mark E. (Endocrine Practice, 2024)
Objective: To describe a practical approach of when and how often to perform imaging, and when to stop imaging pituitary adenomas (PAs). Methods: A literature review was carried out and recommendations provided are derived largely from personal experience. Results: Magnetic resonance imaging is the mainstay imaging modality of choice in the assessment, treatment planning, and follow-up of PAs. These adenomas are discovered incidentally during imaging for a variety of unrelated conditions, because of clinical symptoms related to mass effects on the adjacent structures, or during workup for functional alterations of the adenoma. Imaging is also used in the preoperative and postoperative phases of assessment of PAs, for surgical and radiotherapy planning, for postoperative surveillance to assess for adenoma stability and detection of adenoma recurrence, and for surveillance to monitor for adenoma growth in unoperated PAs. Currently, because there are no evidence-based consensus recommendations, the optimal strategy for surveillance imaging of PAs is not clearly established. Younger age, initial adenoma size, extrasellar extension, mass effect, cavernous sinus invasion, functional status, histopathologic characteristics, cost considerations, imaging accessibility, patient preference, and patient contraindications (eg, implanted metallic devices and patient claustrophobia) are all important factors that influence the strategy for surveillance imaging. Conclusions: This review provides a practical approach of performing surveillance imaging strategies for PAs that should be individualized based on clinical presentation, history, adenoma morphology on imaging, and histopathologic characteristics.
CRIS-Team Scopus Importer:2024-02-16
Keywords: acromegaly; Cushing disease; functioning pituitary adenoma; magnetic resonance imaging; nonfunctioning pituitary adenoma; pituitary adenoma; prolactinoma

Survey on Training Satisfaction among German Neurosurgical Trainees - Lawson McLean, Anna Cecilia; Maurer, Stefanie; Nistor-Gallo, Dorothea; Moritz, Ina; Tourbier, Meriem (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background There has been a fivefold increase of neurosurgeons over the last three decades in Germany, despite a lesser increase in operations. Currently, there are approximately 1,000 neurosurgical residents employed at training hospitals. Little is known about the overall training experience and career opportunities for these trainees. Methods In our role as resident representatives, we implemented a mailing list for interested German neurosurgical trainees. Thereafter, we created a survey including 25 items to assess the trainees' satisfaction with their training and their perceived career prospects, which we then distributed through the mailing list. The survey was open from April 1 until May 31 2021. Results Ninety trainees were enrolled in the mailing list and we received 81 completed responses to our survey. Overall, 47% of the trainees were very dissatisfied or dissatisfied with their training. Sixty-two percent of the trainees reported a lack of surgical training. Fifty-eight percent of trainees found it difficult to attend courses or classes and only 16% had consistent mentoring. There was an expressed desire for a more structured training program and mentoring projects. In addition, 88% of trainees were willing to relocate for fellowships outside their current hospitals. Conclusions Half of the responders were dissatisfied with their neurosurgical training. There are various aspects that require improvement, such as the training curriculum, structured mentoring, and reduction of the amount of administrative work. We propose the implementation of a modernized structured curriculum, which addresses the mentioned aspects, in order to improve neurosurgical training and, consecutively, patient care.
CRIS-Team Scopus Importer:2024-12-16
Keywords: curriculum; Germany; neurosurgical training; residency training

Symmetric tract-based spatial statistics of patients with left versus right mesial temporal lobe epilepsy with hippocampal sclerosis - Mennecke, Angelika; Rösch, Julie; Kasper, Burkhard; Schmidt, Manuel; Roessler, Karl; Coras, Roland; Hamer, Hajo; Dörfler, Arnd; Laun, Frederik Bernd (NeuroReport, 2018)
This study aims to investigate the diffusion metrics of left versus right temporal lobe epilepsy in a well-defined subgroup of patients with mesial temporal lobe epilepsy (mTLE) because of unilateral hippocampal sclerosis while taking into account interhemispheric differences. Eighteen patients with TLE [nine left temporal lobe epilepsy (LTLE) and nine right temporal lobe epilepsy (RTLE)] and a norm group of 36 nonepileptic individuals were scanned with a multiband accelerated diffusion tensor imaging protocol at 3T. The scalar diffusion tensor parameters fractional anisotropy (FA), mean diffusivity (MD), and radial diffusivity (RD) and, after projection on a symmetric skeleton, their hemispheric difference (dFA, dMD, and dRD) were analyzed using tract-based spatial statistics. In the cluster with significantly (P<0.008) different dFA, dMD, and dRD between right TLE and left TLE, the hemispheric difference in the mean scalar indices (dmFA, dmMD, and dmRD) was assessed and tested for differences using a one-way analysis of variance and for correlation with patient age, seizure onset, or duration of epilepsy using Pearson's correlation. Patients with LTLE showed lower dFA, higher dMD, and higher dRD (P<0.008) compared with patients with RTLE in a cluster including parts of the uncinated and inferior longitudinal fasciculus and the inferior fronto-occipital fasciculus. dmFA, dmMD, and dmRD differed significantly between groups (P<10, corrected) and showed no correlation with patient age, seizure onset, or duration of epilepsy. The exclusion of bilateral interindividual variance through the calculation of the hemispheric difference of the diffusion metrics by the symmetric variant of tract-based spatial statistics allows for a sensitive differentiation of LTLE and RTLE with unilateral hippocampal sclerosis.
EVALuna2:34910

Targeted and optimized multi-channel transcranial direct current stimulation for focal epilepsy: An N-of-1 trial - Antonakakis, Marios; Kaiser, Fabian; Rampp, Stefan; Kovac, Stjepana; Wiendl, Heinz; Stummer, Walter; Gross, Joachim; Kellinghaus, Christoph; Khaleghi-Ghadiri, Maryam; Möddel, Gabriel; Wolters, Carsten H. (Brain Stimulation, 2024)
CRIS-Team Scopus Importer:2024-03-15

Technical Modification of Amygdalo-Hippocampectomy in Temporal Lobe Epilepsy Surgery to Further Reduce Severe Neurological Complications: A Clinical-Anatomical Study - Roessler, Karl; Kasper, Burkhard; Coras, Roland; Arinrad, Soheil; Scholz, Michael; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (World Neurosurgery, 2018)
BACKGROUND: Temporal lobe resection (TLR) including amygdalohippocampectomy (AHE) is the most frequent performed procedure in epilepsy surgery. Owing to the close anatomic relationship of the mesial temporal structures and the midbrain and choroidal fissure, the incidence of severe complications, such as postoperative stroke, is as high as 2.5%. METHODS: We developed a modification of the classical technique for AHE that involves entering the choroidal fissure early via the anterior part of the frontomesial temporal horn cleft to identify the crus cerebri, posterior cerebri artery, and oculomotor nerve. In a second step, after visualization of the cleavage plane between the midbrain and middle cerebral artery, the uncus and amygdala are removed. RESULTS: A total of 81 patients (47 females and 34 males; mean age at surgery, 40 years) underwent TLR including AHE with our surgical modification to treat heterogeneous pathologies. The cohort included 45 patients with hippocampal sclerosis, 11 with ganglioglioma, 2 with dysembryoplastic neuroepithelioma, 2 with diffuse glioma, and 21 with other pathologies, including cavernoma, scar tissue, and mild cortical dysplasia, among others. In all patients, anterior temporal resection was performed via AHE using our modified technique. Seizure outcome was favorable after a mean follow-up of 27 months (range, 3-56 months); 64% of the patients were completely seizure-free (Engel class 1A), and 75% had an Engel class 1 outcome. There was no mortality or permanent severe neurologic complications, and the rate of surgical complications was 3.7%. CONCLUSIONS: Our modified AHE technique is associated with a low rate of complications in TLR for medically refractory temporal lobe epilepsy, and helps avoid permanent severe neurologic complications.
EVALuna2:34587

Temozolomide toxicity operates in a xCT/SLC7a11 dependent manner and is fostered by ferroptosis - Sehm, Tina; Rauh, Manfred; Wiendieck, Kurt; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai E. (Oncotarget, 2016)
The glutamate exchanger xCT (SLC7a11) is causally linked with the malignancy grade of brain tumors and represents a key player in glutamate, cystine and glutathione metabolism. Although blocking xCT is not cytotoxic for brain tumors, xCT inhibition disrupts the neurodegenerative and microenvironment-toxifying activity of gliomas. Here, we report on the use of various xCT inhibitors as single modal drugs and in combination with the autophagy-inducing standard chemotherapeutic agent temozolomide (Temodal/Temcad®, TMZ). xCT overexpressing cells (xCTOE) are more resistant to the FDA and EMA approved drug sulfasalazine (Azulfidine/Salazopyrin/Sulazine®, SAS) and RNAi-mediated xCT knock down (xCTKD) in gliomas increases the susceptibility towards SAS in rodent gliomas. In human gliomas, challenged xCT expression had no impact on SAS-induced cytotoxicity. Noteworthy, other xCT inhibitors such as erastin and sorafenib showed enhanced efficacy on xCTKD gliomas. In contrast, cytotoxic action of TMZ operates independently from xCT expression levels on rodent gliomas. Human glioma cells with silenced xCT expression display higher vulnerability towards TMZ alone as well as towards combined TMZ and SAS. Hence, we tested the partial xCT blockers and ferroptosis inducing agents erastin and sorafenib (Nexavar®, FDA and EMA-approved drug for lung cancer). Noteworthy, xCTOE gliomas withstand erastin and sorafenib-induced cell death in a concentration-dependent manner, whereas siRNA-mediated xCT knock down increased susceptibility towards erastin and sorafenib. TMZ efficacy can be potentiated when combined with erastin, however not by sorafenib. Moreover, gliomas with high xCT expression are more vulnerable towards combinatorial treatment with erastin-temozolomide. These results disclose that ferroptosis inducers are valid compounds for potentiating the frontline therapeutic agent temozolomide in a multitoxic approach.
EVALuna2:33853

Temporal lobe surgery in Germany from 1988 to 2008: diverse trends in etiological subgroups - Helmstaedter, C.; May, T. W.; Von Lehe, Marec; Pfaefflin, M.; Ebner, A.; Pannek, H. W.; Elger, C. E.; Stefan, H.; Schramm, Johannes (European Journal of Neurology, 2014)
In the epilepsy community, there is talk that the number of classical patients with early onset temporal lobe epilepsy (TLE) and Ammon's horn sclerosis (AHS) is decreasing. This is counterintuitive, considering the success story of epilepsy surgery, improved diagnostic methods and the current recommendation of early admission to surgery. In order to recognize trends, the development of temporal lobe surgery over 20 years in three major German epilepsy centers was reviewed.Age at surgery and duration of epilepsy, which was differentiated according to histopathology (AHS, developmental, tumor, vascular), year of surgery and center, were evaluated in a cohort of 2812 patients from three German epilepsy centers who underwent temporal lobe surgery between 1988 and 2008. The analysis was carried out for the pooled cohort as well as for each center separately.Of all patients, 52% showed AHS. Compared with other pathologies, the AHS group had the earliest epilepsy onset and the longest duration of epilepsy. Across five time epochs, the diagnosis of AHS increased in the first epoch, remaining constant thereafter. Contrary to the trends in other pathologies, in the AHS group the mean age of patients at surgery increased by 7 years and the duration of epilepsy until surgery increased by 5 years. This trend could be replicated in all three centers. As initially hypothesized for all groups, age and duration of epilepsy in other pathology groups remained constant or indicated earlier submission to surgery.During the first few years studied, most probably due to progress in brain imaging, the proportion of patients with AHS increased. However, despite stable numbers over time, and contrary to the trends in other pathology groups, age and duration of epilepsy in mesial TLE with AHS (mTLE + AHS) increased over time. This supports the hypothesis of a decreasing incidence of AHS. This trend is discussed with respect to disease-modifying factors which have changed the incidence of classical mTLE + AHS or, alternatively, to recent developments in antiepileptic drug treatment, the appraisal of surgery and economic incentives for treatment options other than surgery.
EVALuna2:22259

The acidic brain—glycolytic switch in the microenvironment of malignant glioma - Reuß, Anna Maria; Groos, Dominik; Buchfelder, Michael; Savaskan, Nicolai (International Journal of Molecular Sciences, 2021)
Malignant glioma represents a fatal disease with a poor prognosis and development of resistance mechanisms against conventional therapeutic approaches. The distinct tumor zones of this heterogeneous neoplasm develop their own microenvironment, in which subpopulations of cancer cells communicate. Adaptation to hypoxia in the center of the expanding tumor mass leads to the glycolytic and angiogenic switch, accompanied by upregulation of different glycolytic enzymes, transporters, and other metabolites. These processes render the tumor microenvironment more acidic, remodel the extracellular matrix, and create energy gradients for the metabolic communication between different cancer cells in distinct tumor zones. Escape mechanisms from hypoxia-induced cell death and energy deprivation are the result. The functional consequences are more aggressive and malignant behavior with enhanced proliferation and survival, migration and invasiveness, and the induction of angiogenesis. In this review, we go from the biochemical principles of aerobic and anaerobic glycolysis over the glycolytic switch, regulated by the key transcription factor hypoxia-inducible factor (HIF)-1α, to other important metabolic players like the monocarboxylate transporters (MCTs)1 and 4. We discuss the metabolic symbiosis model via lactate shuttling in the acidic tumor microenvironment and highlight the functional consequences of the glycolytic switch on glioma malignancy. Furthermore, we illustrate regulation by micro ribonucleic acids (miRNAs) and the connection between isocitrate dehydrogenase (IDH) mutation status and glycolytic metabolism. Finally, we give an outlook about the diagnostic and therapeutic implications of the glycolytic switch and the relation to tumor immunity in malignant glioma.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Acidic; Angiogenesis; Carbonic anhydrase (CA)IX; Glioma; Glycolytic; HIF; Lactate; MCT1; MCT4; Tumor microenvironment

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

The Challenging Management of Craniopharyngiomas in Adults: Time for a Reappraisal? - Cuny, Thomas; Buchfelder, Michael; Dufour, Henry; Grossman, Ashley; Gatta-Cherifi, Blandine; Jouanneau, Emmanuel; Raverot, Gerald; Vasiljevic, Alexandre; Castinetti, Frederic (Cancers, 2022)
Simple Summary Craniopharyngiomas (CPs) currently represent one of the most challenging diseases to deal with in the group of skull base tumors. Due to their location near, within, or surrounding the pituitary gland and stalk, CPs can be revealed by pituitary tumor syndrome and/or symptoms of hormonal deficiencies. Furthermore, surgery, which represents the first-line therapy, almost always results in hypopituitarism, diabetes insipidus and, in the case of hypothalamic involvement by the tumor, the occurrence of hypothalamic syndrome. The latter is characterized by intractable weight gain associated with severe morbid obesity, memory impairment, attention deficit, reduced impulse control and, eventually, increased risk of cardiovascular and metabolic disorders. Recent progress made in the understanding of the molecular pathways involved in CPs tumorigenesis paves the way for promising alternative therapeutic approaches and diagnostic procedures. Taken together, they lay the groundwork for new paradigms in the management of CPs in adults. Craniopharyngiomas (CPs) are rare tumors of the skull base, developing near the pituitary gland and hypothalamus and responsible for severe hormonal deficiencies and an overall increase in mortality rate. While surgery and radiotherapy represent the recommended first-line therapies for CPs, a new paradigm for treatment is currently emerging, as a consequence of accumulated knowledge concerning the molecular mechanisms involved in tumor growth, paving the way for anticipated use of targeted therapies. Significant clinical and basic research conducted in the field of CPs will undoubtedly constitute a real step forward for a better understanding of the behavior of these tumors and prevent associated complications. In this review, our aim is to summarize the multiple steps in the management of CPs in adults and emphasize the most recent studies that will contribute to advancing the diagnostic and therapeutic algorithms.
CRIS-Team WoS Importer:2022-08-26

The Clival Line as an Important Arachnoid Landmark During Endoscopic Third Ventriculostomy: An Anatomic Study - Kurucz, Peter; Barany, Laszlo; Buchfelder, Michael; Ganslandt, Oliver (World Neurosurgery, 2018)
OBJECTIVE: Endoscopic third ventriculostomy (ETV) is a well-accepted treatment option instead of ventriculoperitoneal shunt placement in cases of obstructive hydrocephalus. A sufficient flow from the ventricles to the basal cisterns requires perforation of the arachnoid membranes in the retroclival region. This point is critical to achieve an optimal outcome. The complex arachnoid relations were investigated in the retroclival region from the viewpoint of ETV, and anatomic landmarks were defined for subarachnoid dissections. METHODS: Sixty fresh human cadaveric specimens were dissected under macroscopic, microscopic, and endoscopic control. The recordings of 100 operated cases of ETVs were analyzed to ascertain the clinical-anatomic relevance. RESULTS: The Liliequist membrane complex and the anterior pontine membranes are located just above and parallel to both sides of the basilar artery. The basal attachment of these membranes forms an inverted U-shaped, white-grey thickening on the outer arachnoid. We refer to this structure as the clival line. During ETV, if arachnoid dissections were performed ventrally to the clival line, the outer arachnoid was opened; this resulted in a limited flow to the subarachnoid spaces (ventriculo-subdural). If the perforation on the arachnoid membranes was dorsal to the clival line, the prepontine cistern could be directly reached through the Liliequist membrane complex. CONCLUSIONS: Sufficient arachnoid dissection is essential for a successful ETV. The clival line is an important landmark that helps to perform the subarachnoid dissections correctly and achieve an undisrupted cerebral spinal fluid flow between the ventricles and the basal cisterns.
EVALuna2:214797

The course of tumor-related epilepsy in glioblastoma patients: A retrospective analysis - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Uhl, Martin; Brandner, Sebastian; Welte, Tamara; Schembs, Leah; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsy and Behavior, 2024)
Purpose: Many patients with glioblastoma suffer from tumor-related seizures. However, there is limited data on the characteristics of tumor-related epilepsy achieving seizure freedom. The aim of this study was to characterize the course of epilepsy in patients with glioblastoma and the factors that influence it. Methods: We retrospectively analyzed the medical records of glioblastoma patients treated at the University Hospital Erlangen between 01/2006 and 01/2020. Results: In the final cohort of patients with glioblastoma (n = 520), 292 patients (56.2 %) suffered from tumor-related epilepsy (persons with epilepsy, PWE). Levetiracetam was the most commonly used first-line antiseizure medication (n = 245, 83.9 % of PWE). The onset of epilepsy was preoperative in 154/292 patients (52.7 %). 136 PWE (46.6 %) experienced only one single seizure while 27/292 PWE (9.2 %) developed drug-resistant epilepsy. Status epilepticus occurred in 48/292 patients (16.4 %). Early postoperative onset (within 30 days of surgery) of epilepsy and total gross resection (compared with debulking) were independently associated with a lower risk of further seizures. We did not detect dose-dependent pro- or antiseizure effects of radiochemotherapy. Conclusion: Tumor-related epilepsy occurred in more than 50% of our cohort, but drug-resistant epilepsy developed in less than 10% of cases. Epilepsy usually started before tumor surgery.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Glioblastoma; Radiochemotherapy; Surgery; Tumor-related epilepsy

The delta between postoperative seizure freedom and persistence: Automatically detected focal slow waves after epilepsy surgery - Schoenherr, Margit; Stefan, Hermann; Hamer, Hajo; Roessler, Karl; Buchfelder, Michael; Rampp, Stefan (NeuroImage: Clinical, 2017)
In this study, we use a novel automated method for localization and quantitative comparison of magnetoencephalographic (MEG) delta activity in patients with and without recurrent seizures after epilepsy surgery as well as healthy controls.We identified the generators of delta activity by source location in frequency domain between 1 and 4 Hz in spontaneous MEG data. Comparison with healthy control subjects by z-transform emphasized relative changes of activation in patients. The individual results were compared to spike localizations and statistical group analysis was performed. Additionally, MEG results were compared to 1-4 Hz activity in invasive EEG (iEEG) in two patients, in whom this data was available.Patients with recurrent seizures exhibited significantly increased focal MEG delta activity both in comparison to healthy controls and seizure free patients. This slow activity showed a correlation to interictal epileptic activity and was not explained by consequences of the resection alone. In two patients with iEEG, iEEG analysis was concordant with the MEG findings.The quantity of delta activity could be used as a diagnostic marker for recurrent seizures. The close relation to epileptic spike localizations and the resection volume of patients with successful second surgery imply involvement in seizure recurrence. This initial evidence suggests a potential application in the planning of second epilepsy surgery.
EVALuna2:22488

The Diagnostic and Therapeutic Role of Leptin and Its Receptor ObR in Glioblastoma Multiforme - Kinfe, Thomas Mehari; Stadlbauer, Andreas; Bozhkov, Yavor; Kremenevski, Natalia; Brandner, Sebastian; Buchfelder, Michael; Chaudhry, Shafqat R. (Cancers, 2020)
Simple Summary
CRIS-Team WoS Importer:2021-01-08

The effect of head model simplification on beamformer source localization - Neugebauer, Frank; Moeddel, Gabriel; Rampp, Stefan; Burger, Martin; Wolters, Carsten H. (Frontiers in Neuroscience, 2017)
WWU::133621

The effect of stimulation type, head modeling, and combined EEG and MEG on the source reconstruction of the somatosensory P20/N20 component - Antonakakis, Marios; Schrader, Sophie; Wollbrink, Andreas; Oostenveld, Robert; Rampp, Stefan; Haueisen, Jens; Wolters, Carsten H. (Human Brain Mapping, 2019)
Modeling and experimental parameters influence the Electro- (EEG) and Magnetoencephalography (MEG) source analysis of the somatosensory P20/N20 component. In a sensitivity group study, we compare P20/N20 source analysis due to different stimulation type (Electric-Wrist [EW], Braille-Tactile [BT], or Pneumato-Tactile [PT]), measurement modality (combined EEG/MEG – EMEG, EEG, or MEG) and head model (standard or individually skull-conductivity calibrated including brain anisotropic conductivity). Considerable differences between pairs of stimulation types occurred (EW-BT: 8.7 ± 3.3 mm/27.1° ± 16.4°, BT-PT: 9 ± 5 mm/29.9° ± 17.3°, and EW-PT: 9.8 ± 7.4 mm/15.9° ± 16.5° and 75% strength reduction of BT or PT when compared to EW) regardless of the head model used. EMEG has nearly no localization differences to MEG, but large ones to EEG (16.1 ± 4.9 mm), while source orientation differences are non-negligible to both EEG (14° ± 3.7°) and MEG (12.5° ± 10.9°). Our calibration results show a considerable inter-subject variability (3.1–14 mS/m) for skull conductivity. The comparison due to different head model show localization differences smaller for EMEG (EW: 3.4 ± 2.4 mm, BT: 3.7 ± 3.4 mm, and PT: 5.9 ± 6.8 mm) than for EEG (EW: 8.6 ± 8.3 mm, BT: 11.8 ± 6.2 mm, and PT: 10.5 ± 5.3 mm), while source orientation differences for EMEG (EW: 15.4° ± 6.3°, BT: 25.7° ± 15.2° and PT: 14° ± 11.5°) and EEG (EW: 14.6° ± 9.5°, BT: 16.3° ± 11.1° and PT: 12.9° ± 8.9°) are in the same range. Our results show that stimulation type, modality and head modeling all have a non-negligible influence on the source reconstruction of the P20/N20 component. The complementary information of both modalities in EMEG can be exploited on the basis of detailed and individualized head models.
CRIS-Team Scopus Importer:2019-08-16
Keywords: EEG; finite element method; MEG; multimodal imaging; somatosensory cortex; somatosensory evoked fields; somatosensory evoked potentials

The EpiPick algorithm to select appropriate antiseizure medications in patients with epilepsy: Validation studies and updates - Asadi-Pooya, Ali A.; Beniczky, Sándor; Rubboli, Guido; Sperling, Michael R.; Rampp, Stefan; Perucca, Emilio (Epilepsia, 2021)
CRIS-Team Scopus Importer:2021-11-26

The Forces Generated by Agonist Muscles during Isometric Contractions Arise from Motor Unit Synergies - Del Vecchio, Alessandro; Marconi Germer, Carina; Kinfe, Thomas Mehari; Nuccio, Stefano; Hug, François; Eskofier, Björn; Farina, Dario; Enoka, Roger M. (The Journal of Neuroscience, 2023)
The purpose of our study was to identify the low-dimensional latent components, defined hereafter as motor unit modes, underlying the discharge rates of the motor units in two knee extensors (vastus medialis and lateralis, eight men) and two hand muscles (first dorsal interossei and thenars, seven men and one woman) during submaximal isometric contractions. Factor analysis identified two independent motor unit modes that captured most of the covariance of the motor unit discharge rates. We found divergent distributions of the motor unit modes for the hand and vastii muscles. On average, 75% of the motor units for the thenar muscles and first dorsal interosseus were strongly correlated with the module for the muscle in which they resided. In contrast, we found a continuous distribution of motor unit modes spanning the two vastii muscle modules. The proportion of the muscle-specific motor unit modes was 60% for vastus medialis and 45% for vastus lateralis. The other motor units were either correlated with both muscle modules (shared inputs) or belonged to the module for the other muscle (15% for vastus lateralis). Moreover, coherence of the discharge rates between motor unit pools was explained by the presence of shared synaptic inputs. In simulations with 480 integrate-and-fire neurons, we demonstrate that factor analysis identifies the motor unit modes with high levels of accuracy. Our results indicate that correlated discharge rates of motor units that comprise motor unit modes arise from at least two independent sources of common input among the motor neurons innervating synergistic muscles.SIGNIFICANCE STATEMENT It has been suggested that the nervous system controls synergistic muscles by projecting common synaptic inputs to the engaged motor neurons. In our study, we reduced the dimensionality of the output produced by pools of synergistic motor neurons innervating the hand and thigh muscles during isometric contractions. We found two neural modules, each representing a different common input, that were each specific for one of the muscles. In the vastii muscles, we found a continuous distribution of motor unit modes spanning the two synergistic muscles. Some of the motor units from the homonymous vastii muscle were controlled by the dominant neural module of the other synergistic muscle. In contrast, we found two distinct neural modules for the hand muscles.
CRIS-Team Scopus Importer:2023-04-28
Keywords: common synaptic input; motor neurons; motor unit; muscle synergies

The Gene of the Ubiquitin-Specific Protease 8 Is Frequently Mutated in Adenomas Causing Cushing's Disease - Perez-Rivas, Luis G.; Theodoropoulou, Marily; Ferrau, Francesco; Nusser, Clara; Kawaguchi, Kohei; Stratakis, Constantine A.; Faucz, Fabio Rueda; Wildemberg, Luiz E.; Assie, Guillaume; Beschorner, Rudi; Dimopoulou, Christina; Buchfelder, Michael; et al. (Journal of Clinical Endocrinology and Metabolism, 2015)
We have recently reported somatic mutations in the ubiquitin-specific protease USP8 gene in a small series of adenomas of patients with Cushing's disease.To determine the prevalence of USP8 mutations and the genotype-phenotype correlation in a large series of patients diagnosed with Cushing's disease.We performed a retrospective, multicentric, genetic analysis of 134 functioning and 11 silent corticotroph adenomas using Sanger sequencing. Biochemical and clinical features were collected and examined within the context of the mutational status of USP8, and new mutations were characterized by functional studies.A total of 145 patients who underwent surgery for an ACTH-producing pituitary adenoma.Mutational status of USP8. Biochemical and clinical features included sex, age at diagnosis, tumor size, preoperative and postoperative hormonal levels, and comorbidities.We found somatic mutations in USP8 in 48 (36%) pituitary adenomas from patients with Cushing's disease but in none of 11 silent corticotropinomas. The prevalence was higher in adults than in pediatric cases (41 vs 17%) and in females than in males (43 vs 17%). Adults having USP8-mutated adenomas were diagnosed at an earlier age than those with wild-type lesions (36 vs 44 y). Mutations were primarily found in adenomas of 10 ± 7 mm and were inversely associated with the development of postoperative adrenal insufficiency. All the mutations affected the residues Ser718 or Pro720, including five new identified alterations. Mutations reduced the interaction between USP8 and 14-3-3 and enhanced USP8 activity. USP8 mutants diminished epidermal growth factor receptor ubiquitination and induced Pomc promoter activity in immortalized AtT-20 corticotropinoma cells.USP8 is frequently mutated in adenomas causing Cushing's disease, especially in those from female adult patients diagnosed at a younger age.
EVALuna2:22855

The genomic landscape across 474 surgically accessible epileptogenic human brain lesions - A López-Rivera, Javier; Leu, Costin; Macnee, Marie; Khoury, Jean; Hoffmann, Lucas; Coras, Roland; Kobow, Katja; Bhattarai, Nisha; Pérez-Palma, Eduardo; Hamer, Hajo; Brandner, Sebastian; Rössler, Karl; et al. (Brain, 2022)
Understanding the exact molecular mechanisms involved in the etiology of epileptogenic pathologies with or without tumor activity is essential for improving treatment of drug-resistant focal epilepsy. Here, we characterize the landscape of somatic genetic variants in resected brain specimens from 474 individuals with drug-resistant focal epilepsy using deep whole-exome sequencing (>350×) and whole-genome genotyping. Across the exome, we observe a greater number of somatic single-nucleotide variants (SNV) in low-grade epilepsy-associated tumors (LEAT; 7.92 ± 5.65 SNV) than in brain tissue from malformations of cortical development (MCD; 6.11 ± 4 SNV) or hippocampal sclerosis (HS; 5.1 ± 3.04 SNV). Tumor tissues also had the largest number of likely pathogenic variant carrying cells. LEAT had the highest proportion of samples with one or more somatic copy number variants (CNV; 24.7%), followed by MCD (5.4%) and HS (4.1%). Recurring somatic whole chromosome duplications affecting Chromosome 7 (16.8%), chromosome 5 (10.9%), and chromosome 20 (9.9%) were observed among LEAT. For germline variant-associated MCD genes such as TSC2, DEPDC5, and PTEN, germline SNV were frequently identified within large loss of heterozygosity regions, supporting the recently proposed ‘second hit’ disease mechanism in these genes. We detect somatic variants in twelve established lesional epilepsy genes and demonstrate exome-wide statistical support for three of these in the etiology of LEAT (e.g., BRAF) and MCD (e.g., SLC35A2 and MTOR). We also identify novel significant associations for PTPN11 with LEAT and NRAS Q61 mutated protein with a complex MCD characterized by polymicrogyria and nodular heterotopia. The variants identified in NRAS are known from cancer studies to lead to hyperactivation of NRAS, which can be targeted pharmacologically. We identify large recurrent 1q21-q44 duplication including AKT3 in association with focal cortical dysplasia type 2a with hyaline astrocytic inclusions, another rare and possibly under-recognized brain lesion. The clinical genetic analyses showed that the numbers of somatic SNV across the exome and the fraction of affected cells were positively correlated with the age at seizure onset and surgery in individuals with LEAT. In summary, our comprehensive genetic screen sheds light on the genome-scale landscape of genetic variants in epileptic brain lesions, informs the design of gene panels for clinical diagnostic screening, and guides future directions for clinical implementation of epilepsy surgery genetics.<br
Keywords: epilepsy; malformation of cortical development; low-grade epilepsy-associated tumor; hippocampal sclerosis; genetics

The Impact of Burst Motor Cortex Stimulation on Cardiovascular Autonomic Modulation in Chronic Pain: A Feasibility Study for a New Approach to Objectively Monitor Therapeutic Effects - Borutta, Matthias; Köhn, Julia; Souza de Oliveira, Daniela; Del Vecchio, Alessandro; Engelhorn, Tobias; Schwab, Stefan; Buchfelder, Michael; Kinfe, Thomas Mehari (Pain and Therapy, 2023)
Introduction: Chronic refractory pain of various origin occurs in 30–45% of pain patients, and a considerable proportion remains resistant to pharmacological and behavioral therapies, requiring adjunctive neurostimulation therapies. Chronic pain is known to stimulate sympathetic outflow, yet the impact of burst motor cortex stimulation (burstMCS) on objectifiable autonomic cardiovascular parameters in chronic pain remains largely unknown. Methods: In three patients with chronic pain (2 facial pain/1 post-stroke pain), we compared pain intensity using a visual analog scale (VAS 1–10) and parameters of autonomic cardiovascular modulation at supine rest, during parasympathetic challenge with six cycles per minute of metronomic deep breathing, and during sympathetic challenge (active standing) at baseline and after 4 months of burstMCS compared to age-/gender-matched healthy controls. Results: While two out of three patients were responsive after 4 months of adjunctive burstMCS (defined as pain reduction of > 30%), no differences were found in any of the three patients regarding the R-R intervals of adjacent QRS complexes (RRI, 642 vs. 676 ms) and blood pressure (BP, 139/88 vs. 141/90 mmHg). Under resting conditions, parameters of parasympathetic tone [normalized units of high-frequency oscillations of RRI (RRI-HFnu power) 0.24 vs. 0.38, root-mean-square differences of successive RRI (RRI-RMSSD) 7.7 vs. 14.7 ms], total autonomic cardiac modulation [RRI total power 129.3 vs. 406.2 ms2, standard deviation of RRI (RRI-SD) 11.6 vs. 18.5 ms, coefficient of variation of RRI (RRI-CV) 1.9 vs. 3.7%], and baroreceptor reflex sensitivity (BRS, 1.9 vs. 2.3 ms/mmHg) increased, and parameters of sympathetic tone [normalized units of low-frequency oscillations of RRI (RRI-LFnu power) 0.76 vs. 0.62] and sympatho-vagal balance [ratio of RR-LF to RRI-HF power (RRI-LF/HF ratio) 3.4 vs. 1.9] decreased after 4 months of burstMCS. Low-frequency oscillations of systolic blood pressure (SBP-LF power), a parameter of sympathetic cardiovascular modulation, increased slightly (17.6 vs. 20.4 mmHg2). During parasympathetic stimulation, the expiratory–inspiratory ratio (E/I ratio) increased slightly, while upon sympathetic stimulation, the ratio between the shortest RRI around the 15th heartbeat and the longest RRI around the 30th heartbeat after standing up (RRI 30/15 ratio) remained unchanged. Conclusion: Four months of adjunctive burstMCS was associated with an increase in parameters reflecting both total and parasympathetic autonomic modulation and baroreceptor reflex sensitivity. In contrast, sympathetic tone declined in our three patients, suggesting stimulation-associated improvement not only in subjectively perceived VAS pain scores, but also in objectifiable parameters of autonomic cardiovascular modulation.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Autonomic cardiovascular modulation; Burst motor cortex stimulation; Chronic post stroke pain; Objective outcome measures

The impact of dietary isoflavonoids on malignant brain tumors - Sehm, Tina; Fan, Zheng; Weiss, Ruth; Schwarz, Marc; Engelhorn, Tobias; Hore, Nirjhar; Dörfler, Arnd; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nic E. (Cancer Medicine, 2014)
Poor prognosis and limited therapeutic options render malignant brain tumors one of the most devastating diseases in clinical medicine. Current treatment strategies attempt to expand the therapeutic repertoire through the use of multimodal treatment regimens. It is here that dietary fibers have been recently recognized as a supportive natural therapy in augmenting the body's response to tumor growth. Here, we investigated the impact of isoflavonoids on primary brain tumor cells. First, we treated glioma cell lines and primary astrocytes with various isoflavonoids and phytoestrogens. Cell viability in a dose-dependent manner was measured for biochanin A (BCA), genistein (GST), and secoisolariciresinol diglucoside (SDG). Dose-response action for the different isoflavonoids showed that BCA is highly effective on glioma cells and nontoxic for normal differentiated brain tissues. We further investigated BCA in ex vivo and in vivo experimentations. Organotypic brain slice cultures were performed and treated with BCA. For in vivo experiments, BCA was intraperitoneal injected in tumor-implanted Fisher rats. Tumor size and edema were measured and quantified by magnetic resonance imaging (MRI) scans. In vascular organotypic glioma brain slice cultures (VOGIM) we found that BCA operates antiangiogenic and neuroprotective. In vivo MRI scans demonstrated that administered BCA as a monotherapy was effective in reducing significantly tumor-induced brain edema and showed a trend for prolonged survival. Our results revealed that dietary isoflavonoids, in particular BCA, execute toxicity toward glioma cells, antiangiogenic, and coevally neuroprotective properties, and therefore augment the range of state-of-the-art multimodal treatment approach.
EVALuna2:22829

The Infiltrative Margins in Glioblastoma: Important Is What Has Been Left behind - Karschnia, Philipp; Tonn, Joerg Christian; Cahill, Daniel P. (Clinical Cancer Research, 2024)
Supramaximal resection beyond the contrast-enhancing tumor borders represents an emerging surgical strategy for patients with newly diagnosed glioblastoma. A recent study provides evidence detailing the interactive effects of more aggressive surgery on other clinical predictors of outcome, supporting guidance for surgical decision-making and informing clinical trialists about the need to stratify for extent of resection.
CRIS-Team Scopus Importer:2024-11-15

The oncological role of resection in newly diagnosed diffuse adult-type glioma defined by the WHO 2021 classification: a Review by the RANO resect group - Karschnia, Philipp; Gerritsen, Jasper K.W.; Teske, Nico; Cahill, Daniel P.; Jakola, Asgeir S.; van den Bent, Martin; Weller, Michael; Schnell, Oliver; Vik-Mo, Einar O.; Thon, Niklas; Vincent, Arnaud J.P.E.; Kim, Michelle M.; et al. (Lancet Oncology, 2024)
Glioma resection is associated with prolonged survival, but neuro-oncological trials have frequently refrained from quantifying the extent of resection. The Response Assessment in Neuro-Oncology (RANO) resect group is an international, multidisciplinary group that aims to standardise research practice by delineating the oncological role of surgery in diffuse adult-type gliomas as defined per WHO 2021 classification. Favourable survival effects of more extensive resection unfold over months to decades depending on the molecular tumour profile. In tumours with a more aggressive natural history, supramaximal resection might correlate with additional survival benefit. Weighing the expected survival benefits of resection as dictated by molecular tumour profiles against clinical factors, including the introduction of neurological deficits, we propose an algorithm to estimate the oncological effects of surgery for newly diagnosed gliomas. The algorithm serves to select patients who might benefit most from extensive resection and to emphasise the relevance of quantifying the extent of resection in clinical trials.
CRIS-Team Scopus Importer:2024-09-06

The optimal surgical techniques for pituitary tumors - Buchfelder, Michael; Schlaffer, Sven-Martin; Zhao, Yining (Best Practice & Research Clinical Endocrinology & Metabolism, 2019)
In this paper, the currently used and well evaluated techniques for the surgery of pituitary tumors will be reviewed. Since the first surgical approaches to pituitary tumors more than 100 years have elapsed. Various surgical techniques have been developed, refined and standardized. Most of these tumors are to date treated via transsphenoidal approaches. Many pituitary adenomas, particularly, smaller, enclosed ones, can be completely excised and a selective adenomectomy is usually attempted. It leads to remission of hormonal oversecretion and also to recovery of pituitary function in many patients. The resection of pseudocapsule around the adenoma seems to improve the operative results further. Transcranial approaches, employing craniotomies, are still needed in some patients with pituitary adenomas and in many of those harbouring craniopharyngiomas. The operative techniques will be described and briefly commented. Moreover, the application and usefulness of several technical developments will be reviewed, such as the use of the endoscope, magnetic resonance imaging, fluorenscent dyes and neuronavigation. The use of the intraoperative Doppler probe, ultrasound and the value of intraoperative hormonal measurements will be briefly discussed. There is sufficient evidence that the best and optimal outcome in terms of tumor resection and correction of hormonal oversecretion as well as the lowest rate of complications are obtained in centers of excellence with sufficiently experienced, specialized surgeons and a high patient load.
CRIS-Team Scopus Importer:2019-08-23
Keywords: microsurgery; pituitary surgery; pituitary tumor; selective adenomectomy; transsphenoidal approach

The oxido-metabolic driver ATF4 enhances temozolamide chemo-resistance in human gliomas - Chen, Daishi; Rauh, Manfred; Buchfelder, Michael; Eyupoglu, Ilker Y.; Savaskan, Nicolai (Oncotarget, 2017)
Malignant gliomas are devastating neoplasia with limited curative treatment options. Temozolomide (TMZ, Temcat®, Temodal® or Temodar®) is a first-line treatment for malignant gliomas but the development of drug resistance remains a major concern. Activating transcription factor 4 (ATF4) is a critical oxido-metabolic regulator in gliomas, and its role in the pathogenesis of TMZ-resistance remains elusive. We investigated the effect of TMZ on human glioma cells under conditions of enhanced ATF4 expression (ATF4OE) and ATF4 knock down (ATF4KD). We monitored cell survival, ATF4 mRNA expression of ATF4 and xCT (SLC7a11) regulation within human gliomas. TMZ treatment induces a transcriptional response with elevated expression of ATF4, xCT and Nrf2, as a sign of ER stress and toxic cell damage response. ATF4 overexpression (ATF4OE) fosters TMZ resistance in human gliomas and inhibits TMZ-induced autophagy. Conversely, ATF4 suppression by small interfering RNAs (ATF4KD) leads to increased TMZ susceptibility and autophagy in comparison to wild type gliomas. ATF4OE gliomas show reduced cell cycle shift and apoptotic cell death, whereas ATF4KD gliomas reveal higher susceptibility towards cell cycle rearrangements. Hence, the migration capacity of ATF4OE glioma cells is almost not affected by TMZ treatment. In contrast, ATF4KD gliomas show a migratory stop following TMZ application. Mechanistically, xCT elevation is a consequence of ATF4 activation and increased levels of xCT amplifies ATF4-induced TMZ resistance. Our data show that ATF4 operates as a chemo-resistance gene in gliomas, and the tumor promoting function of ATF4 is mainly determined by its transcriptional target xCT. Therefore, therapeutic inactivation of ATF4 can be a promising strategy to overcome chemo-resistance and promote drug efficacy in human gliomas.
EVALuna2:34245

Therapeutic Potential of Selenium in Glioblastoma - Yakubov, Eduard; Eibl, Thomas; Hammer, Alexander; Holtmannspotter, Markus; Savaskan, Nicolai; Steiner, Hans-Herbert (Frontiers in Neuroscience, 2021)
Little progress has been made in the long-term management of malignant brain tumors, leaving patients with glioblastoma, unfortunately, with a fatal prognosis. Glioblastoma remains the most aggressive primary brain cancer in adults. Similar to other cancers, glioblastoma undergoes a cellular metabolic reprogramming to form an oxidative tumor microenvironment, thereby fostering proliferation, angiogenesis and tumor cell survival. Latest investigations revealed that micronutrients, such as selenium, may have positive effects in glioblastoma treatment, providing promising chances regarding the current limitations in surgical treatment and radiochemotherapy outcomes. Selenium is an essential micronutrient with anti-oxidative and anti-cancer properties. There is additional evidence of Se deficiency in patients suffering from brain malignancies, which increases its importance as a therapeutic option for glioblastoma therapy. It is well known that selenium, through selenoproteins, modulates metabolic pathways and regulates redox homeostasis. Therefore, selenium impacts on the interaction in the tumor microenvironment between tumor cells, tumor-associated cells and immune cells. In this review we take a closer look at the current knowledge about the potential of selenium on glioblastoma, by focusing on brain edema, glioma-related angiogenesis, and cells in tumor microenvironment such as glioma-associated microglia/macrophages.
CRIS-Team Scopus Importer:2021-06-25
Keywords: glioblastoma; glutamate; microglia; selenium; SLC7A11

Therapy of acromegalic patients exacerbated by concomitant type 2 diabetes requires higher pegvisomant doses to normalise IGF1 levels - Droste, Michael; Domberg, Julia; Buchfelder, Michael; Mann, Klaus; Schwanke, Anja; Stalla, Guenter; Strasburger, Christian J. (European Journal of Endocrinology, 2014)
Acromegaly is associated with an increased prevalence of glucose metabolism disorders. Clinically confirmed diabetes mellitus is observed in approximately one quarter of all patients with acromegaly and is known to have a worse prognosis in these patients.Of 514 acromegalic patients treated with pegvisomant and recorded in the German Cohort of ACROSTUDY, 147 had concomitant diabetes mellitus. We analysed these patients in an observational study and compared patients with and without concomitant diabetes.Under treatment with pegvisomant, patients with diabetes mellitus rarely achieved normalisation (64% in the diabetic cohort vs 75% in the non-diabetic cohort, P=0.04) for IGF1. Diabetic patients normalised for IGF1 required higher pegvisomant doses (18.9 vs 15.5 mg pegvisomant/day, P<0.01). Furthermore, those diabetic patients requiring insulin therapy showed a tendency towards requiring even higher pegvisomant doses to normalise IGF1 values than diabetic patients receiving only oral treatment (22.8 vs 17.2 mg pegvisomant/day, P=0.11).Hence, notable interdependences between the acromegaly, the glucose metabolism of predisposed patients and their treatment with pegvisomant were observed. Our data support recent findings suggesting that intra-portal insulin levels determine the GH receptor expression in the liver underlined by the fact that patients with concomitant diabetes mellitus, in particular those receiving insulin therapy, require higher pegvisomant doses to normalise IGF1. It is therefore important to analyse various therapy modalities to find out whether they influence the associated diabetes mellitus and/or whether the presence of diabetes mellitus influences the treatment results of an acromegaly therapy.
EVALuna2:22861

The Shape grading system: a classification for growth patterns of pituitary adenomas - Berkmann, Sven; Lattmann, Jaqueline; Schuetz, Philipp; Diepers, Michael; Remonda, Luca; Fandino, Javier; Buchfelder, Michael; Mueller, Beat (Acta Neurochirurgica, 2021)
Background: Long-term tumor control of pituitary adenomas may be achieved by gross total resection (GTR). Factors, which influence the extent of resection, are invasiveness, tumor size, and possibly tumor shape. Nevertheless, the latter factor has not been assessed so far and there is no classification for the different shapes. The aim of this study was to evaluate the impact of different tumor shapes on GTR rates and outcome according to our proposed “Shape grading system.” Methods: In this retrospective single center study, the radiological outcome of nonfunctioning pituitary adenomas was assessed with respect to the following previously defined growth patterns: spherical (Shape I), oval (Shape II), dumbbell (Shape III), mushroom (Shape IV), and polylobulated (Shape V). Results: A total of 191 patients were included (Shape I, n = 28 (15%); Shape II, n = 91 (48%); Shape III, n = 37 (19%); Shape IV, n = 12 (6%); Shape V, n = 23 (12%)). GTR was achieved in 101 patients (53%) with decreasing likelihood of GTR in higher shape grades (Shape I, n = 23 (82%); Shape II, n = 67 (74%); Shape III, n = 9 (24%); Shape IV, n = 2 (17%); Shape V, n = 0 (0%)). This correlated with larger tumor remnants, a higher risk of tumor recurrence/regrowth and therefore necessity of re-surgery and/or radiotherapy/radiosurgery. Conclusion: The “Shape grading system” may be used as a predictor of the outcome in nonfunctioning pituitary adenomas. The higher the “Shape grade,” the higher the likelihood for lower GTR rates, larger tumor remnants, and need for further therapies.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Grading; Outcome; Pituitary; Shape; Transsphenoidal; Tumor

The SIP-NVC-Wizard User Guidance on Segmentation for Surgical Intervention Planning of Neurovascular Compression - Franz, Daniela; Syré, Liane; Paulus, Dietrich; Bischoff, Barbara; Wittenberg, Thomas; Hastreiter, Peter (Deutschland, 2015)
Neurovascular compression syndromes (NVC) result from a compression of the entry/exit zone of cranial nerves by a vessel at the surface of the brainstem. Surgical intervention planning (SIP) for NVC enables a comprehensive spatial understanding of the patient specific anatomy. Specifically, brainstem, vessels and nerves are segmented in NVC SIP. To support segmentation for NVC SIP, we propose a wizard-based user guidance. The SIP-NVC-Wizard guides the user through the patient's individual anatomy and segmentations, and translates the parameter tuning into adequate medical terminology. We were able to show pathological nerve-vessel-contact in ten NVC cases producing results comparable to conventional NVC SIP, and performed a pilot-study to evaluate usability and functionality of the proposed wizard. With the SIP-NVC-Wizard our subjects were able to perform a NVC SIP without any knowledge in image processing. Anatomical beginners showed a steep learning curve. Time was reduced to 34 minutes compared to 1-2 hours for conventional NVC SIP.

The surgical treatment of acromegaly - Buchfelder, Michael; Schlaffer, Sven-Martin (Pituitary, 2017)
PURPOSE: Surgical extraction of as much tumour mass as possible is considered the first step of treatment in acromegaly in many centers. In this article the potential benefits, disadvantages and limitations of operative acromegaly treatment are reviewed. METHODS: Pertinent literature was selected to provide a review covering current indications, techniques and results of operations for acromegaly. RESULTS: The rapid reduction of tumour volume is an asset of surgery. To date, in almost all patients, minimally invasive, transsphenoidal microscopic or endoscopic approaches are employed. Whether a curative approach is feasible or a debulking procedure is planned, can be anticipated on the basis of preoperative magnetic resonance imaging. The radicality of adenoma resection essentially depends on localization, size and invasive character of the tumour. The normalization rates of growth hormone and IGF-1 secretion, respectively, depend on tumour-related factors such as size, extension, the presence or absence of invasion and the magnitude of IGF-1 and growth hormone oversecretion. However, also surgeon-related factors such as experience and patient load of the centers have been shown to strongly affect surgical results and the rate of complications. As compared to most medical treatments, surgery is relatively cheap since the costs occur only once and not repeatedly. There are several new technical gadgets which aid in the surgical procedure: navigation and variants of intraoperative imaging. CONCLUSIONS: For the mentioned reasons, current algorithms of acromegaly management suggest an initial operation, unless the patients are unfit for surgery, refuse an operation or only an unsatisfactory resection is anticipated. A few suggestions are made when a re-operation could be considered.
EVALuna2:102202

The USP8 mutational status may predict long-term remission in patients with Cushing's disease - Albani, Adriana; Perez-Rivas, Luis G.; Dimopoulou, Christina; Zopp, Stephanie; Colon-Bolea, Paula; Roeber, Sigrun; Honegger, Juergen; Flitsch, Joerg; Rachinger, Walter; Buchfelder, Michael; Stalla, Guenter K.; Herms, Jochen; et al. (Clinical Endocrinology, 2018)
OBJECTIVE: Almost half of the cases of Cushing's disease (CD) tumours carry recurrent activating somatic mutations in the ubiquitin-specific protease eight gene (USP8). The USP8 mutational status could predict remission in patients with CD, so our objective was to correlate the presence of somatic USP8 mutations with the rate of recurrence after transsphenoidal surgery (TSS) retrospectively. DESIGN: Biochemical, radiological and clinical data were retrospectively assessed in 48 patients. USP8 mutational status was determined from corticotroph tumour samples. Association between USP8 mutational status, remission and recurrence was investigated. PATIENTS: Patients with Cushing's disease from a single-centre cohort who underwent TSS between 1991 and 2012. MEASUREMENTS: Long-term remission and recurrence rate after TSS with at least 6 months follow-up. Biochemical, radiological and clinical data, including sex, age at diagnosis, tumour size and pre-operative hormonal levels. USP8 mutational status. RESULTS: Patients with USP8 mutant corticotroph tumours (18 of 48; 37%) were diagnosed significantly earlier (mean ± SD 46 ± 10 years vs 53 ± 11 years; P = 0.028) and presented with higher pre-operative 24-hour urinary-free cortisol levels (median IQR μg/24 hours 1174.0, 1184.5 vs 480.0, 405.3; P = 0.045). The incidence of recurrence in a 10-year follow-up was significantly higher in patients with USP8 mutant tumours after the initial remission (58% vs 18% P = 0.026). Recurrence appeared significantly earlier in these patients (months 70, 44-97 95% CI vs 102, 86-119 95% CI; P = 0.019). CONCLUSION: Recurrence appears to be more frequent and earlier after TSS in patients with USP8 mutant corticotroph tumours.
EVALuna2:51490

The “Valva Cerebri”: Morphometry, Topographic Anatomy and Histology of the Rhomboid Membrane at the Craniocervical Junction - Kurucz, Peter; Meszaros, Cintia; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo (Clinical Anatomy, 2020)
The arachnoid membranes' anatomy is a controversial topic in the literature, and the rhomboid membrane at the craniovertebral junction is an element of this system that has been described poorly. Hence, the objective of our study was to examine this membrane's anatomy and histology. A total of 45 fresh formalin-fixed human cadaveric heads were examined, and anatomic dissections and histologic examinations using standard staining methods were performed. The membrane was found to be a constant structure. It has a rhomboid shape and is located on the medulla oblongata and upper cervical spine's ventral surface within the subarachnoid space. Its average craniocaudal length is 49 mm and the short axis is 26 mm. The cranial apex is attached to the vertebral arteries' junction, and the caudal apex reaches the level of C4. The lateral apices are attached to the dura mater at the level of the denticulate ligament's second insertion. The C1 spinal nerves perforate the membrane, while the C2 roots are located dorsal to it. The membrane is attached strongly to the underlying pia mater. Histologically, it has a typical arachnoid structure, in which its adhesions to the vertebral arteries as well as to the pia mater could be verified histologically. This is the first detailed examination of the rhomboid membrane. Our results suggest that the membrane serves a valve-like function between the spinal and cranial subarachnoid spaces. Based on our findings, further hydrodynamic studies should clarify the membrane's physiological role. Clin. Anat., 2019. © 2019 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2019-09-17

Three-dimensional structure of the basal lamella of the middle turbinate - Eördögh, Márton; Baksa, Gábor; Grimm, András; Barany, Laszlo; Petneházy, Örs; Reisch, Robert; Schroeder, Henry W.S.; Briner, Hans Rudolf; Hosemann, Werner (Scientific Reports, 2021)
The middle turbinate’s basal lamella (3BL) is a variable landmark which needs to be understood in endoscopic transnasal skull base surgery. It comprises an anterior frontal and a posterior horizontal part and appears in its simplest depiction to be “L”-shaped, when viewed laterally. In this study we analyzed its 3D morphology and variations focusing on a precise and systematic description of the anatomy. CBCTs of 25 adults, 19 cadavers and 6 skulls (total: 100 sides) were investigated with the 3DSlicer software, creating 3D models of the 3BL. We introduced a novel geometrical classification of the 3BL’s shape, based on segments. We analyzed their parameters and relationship to neighboring structures. When viewed laterally, there was no consistent “L”-shaped appearance of the 3BL, as it is frequently quoted. A classification of 9 segment types was used to describe the 3BL. The 3BLs had in average of 2.95 ± 0.70 segments (median: 3), the most frequent was the horizontal plate (23.05% of all segments), next a concave/convex plate (22.71%), then a sigma plate (22.37%). Further types were rare. We identified a horizontal plate in 68% of all lateral views whilst 32% of the 3BLs were vertical. A sigma–concave/convex–horizontal trisegmental 3BL was the most common phenotype (27%). Globally, the sigma–concave/convex pattern was present in 42%. The 3BL adhered the ethmoidal bulla in 87%. The segmenting method is eligible to describe the 3BL’s sophisticated morphology.
CRIS-Team Scopus Importer:2021-09-17

Tight junction protein claudin-1 is differentially expressed in craniopharyngioma subtypes and indicates invasive tumor growth - Stache, Christina; Hölsken, Annett; Fahlbusch, Rudolf; Flitsch, Jörg; Schlaffer, Sven-Martin; Buchfelder, Michael; Buslei, Rolf (Neuro-Oncology, 2014)
Background Claudins are tight junction proteins expressed in epithelial tissues that play important roles in cell polarity and adhesion. Altered distribution of claudin-1(CLDN1) affects cell mobility and tumor invasiveness. Craniopharyngiomas (CPs) represent epithelial tumors of the sellar region, consisting of adamantinomatous (adaCP) and papillary (papCP) variants. Their tendency to infiltrate surrounding brain structures complicates successful surgery. Reliable markers are required to predict tumor behavior and to establish individualized treatment protocols. Methods We describe the distribution pattern of CLDN1 in a large cohort of 66 adaCPs, 21 papCPs, and 24 Rathke`s cleft cyst (RCC) cases using immunohistochemistry. CLDN1 mRNA levels were analyzed with qRT-PCR in 33 CP samples. The impact on the migration potential was studied in primary adaCP cell cultures (n = 11) treated with small interfering RNA (siRNA) for CLDN1. Furthermore, CLDN1 distribution patterns and expression levels were compared between invasive (n = 16) and noninvasive (n = 17) tumor groups. Results PapCPs and RCCs exhibited a distinct homogenous and membranous expression pattern, whereas CLDN1 immunoreactivity appeared weaker and more heterogeneous in adaCPs. In the latter cases, whirl-like cell clusters showed complete absence of CLDN1. mRNA analysis confirmed reduced CLDN1 levels in adaCPs versus papCPs. Interestingly, invasive tumors exhibited significantly lower CLDN1 expression compared with noninvasive counterparts regardless of CP subtype. Accordingly, siRNA treatment for CLDN1 altered tumor cell migration in vitro. Conclusion CLDN1 represents a novel marker in the differential diagnosis of CP variants and RCCs. Low CLDN1 expression levels correlate with an invasive CP growth pattern and may serve as a prognostic marker.
EVALuna2:7206

Time course of pain response and toxicity after whole-nerve-encompassing LINAC-based stereotactic radiosurgery for trigeminal neuralgia—a prospective observational study - Koca, Selim; Distel, Luitpold; Lubgan, Dorota; Weissmann, Thomas; Lambrecht, Ulrike; Lang-Welzenbach, Marga; Eyüpoglu, Ilker Yasin; Bischoff, Barbara; Buchfelder, Michael; Semrau, Sabine; Fietkau, Rainer; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2019)
Purpose: To prospectively evaluate the time course of pain response and toxicity after linear accelerator-based whole-nerve-encompassing radiosurgery (LINAC-SRS) using a uniform treatment schedule for dosing and target volume definition in patients with refractory trigeminal neuralgia. Methods: From December 2012 to December 2016, 21 patients were treated using a standardized protocol. Patients received LINAC-SRS with 70 Gy to the cisternal portion while aiming for the 90% isodose to fully envelope the nerve in one cross-sectional plane. Data on pain, analgesics, and toxicity were gathered prospectively. Four time intervals (1–6, 6–12, 12–18, and 18–24 months) were defined and compared to baseline and each other. Results: The median follow-up from radiotherapy was 16 months. Freedom from pain was achieved at least once in 90.5, 81.0, and 85.7% of patients for everyday pain, rest pain, and pain peaks, respectively. At 1–6 months, pain was significantly reduced in everyday routine (mean VAS, 2.0/10 vs. 5.8/10; P = 0.004), at rest (1.5/10 vs. 4.0/10; P = 0.002), and for pain peaks (2.9/10 vs. 10/10; P < 0.001), as was the number of analgesics (mean 1.5 vs. 2.9; P < 0.001). No significant increase in pain or analgesics was observed for subsequent time intervals. At last follow-up, reduction in pain compared to baseline for everyday routine (2.1/10 vs. 5.8/10; P = 0.010) and for pain peaks (3.3/10 vs. 10/10; P < 0.001) was significant, whereas it was not for rest pain (1.8/10 vs. 3.9/10; P = 0.073). Most toxicities were related to trigeminal nerve impairment, with 42.9% reporting new-onset hypoesthesia at last follow-up. Conclusion: This study provides prospective data after whole nerve encompassing LINAC-SRS for trigeminal neuralgia. No significant pain relapse was observed.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Facial pain; Radiosurgery; SRS; Toxicity; Trigeminal neuralgia

Time-dependent risk factors for epileptic seizures in glioblastoma patients: A retrospective analysis of 520 cases - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Brandner, Sebastian; Welte, Tamara; Balk, Stefanie; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsia, 2023)
Objective: Epilepsy is a common comorbidity of glioblastoma. Seizures may occur in various phases of the disease. We aimed to assess potential risk factors for seizures in accordance with the point in time at which they occurred. Methods: We retrospectively analyzed medical files of adult patients with de novo glioblastoma treated at our institution between January 2006 and January 2020. We categorized seizures as preoperative seizures (POS), early postoperative seizures (EPS; before initiation of radio[chemo]therapy [RCT]), seizures during radiotherapy (SDR; during or <30 days after RCT), and posttherapeutic seizures (PTS; ≥30 days after completion of RCT). We addressed associations between patients' characteristics and their seizures. Results: In the final cohort (N = 520), 292 patients experienced seizures. POS, EPS, SDR, and/or PTS occurred in 29.6% (154/520), 6.0% (31/520), 13.8% (70/509), and 36.1% (152/421) of patients, respectively. POS occurred more frequently in patients with higher Karnofsky Performance Scale scores (odds ratio [OR] = 3.27, p =.001) and tumor location in the temporal lobe (OR = 1.51, p =.034). None of the parameters we analyzed was related to the occurrence of EPS. SDR were independently associated with tumor location (parietal lobe, OR = 1.86, p =.027) and POS, but not EPS, and were independent of RCT. PTS were independently associated with tumor progression (OR = 2.32, p <.001) and with occurrence of SDR (OR = 3.36, p <.001), and negatively correlated with temporal lobe location (OR =.58, p <.014). In patients with tumors exclusively located in the temporal lobe, complete tumor resection was associated with a decreased risk of postoperative seizures. Significance: Seizures in glioblastoma patients have various, time-dependent risk factors. Temporal lobe localization was a risk factor for preoperative seizures; surgery may have had a protective effect in these patients. RCT did not have dose-dependent pro- or anticonvulsive effects. PTS were associated with tumor progression.
CRIS-Team Scopus Importer:2023-07-07
Keywords: glioblastoma; radiochemotherapy; seizures; surgery

Time trends in incidence of pathological and etiological stroke subtypes during 16 years: the Erlangen Stroke Project - Kolominsky-Rabas, Peter; Wiedmann, Silke; Weingärtner, Michael; Liman, Thomas G.; Endres, Matthias; Schwab, Stefan; Buchfelder, Michael; Heuschmann, Peter U. (Neuroepidemiology, 2015)
Population-based data, which continuously monitors time trends in stroke epidemiology are limited. We investigated the incidence of pathological and etiological stroke subtypes over a 16 year time period.Data were collected within the Erlangen Stroke Project (ESPro), a prospective, population-based stroke register in Germany covering a total study population of 105,164 inhabitants (2010). Etiology of ischemic stroke was classified according to the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria.Between January 1995 and December 2010, 3,243 patients with first-ever stroke were documented. The median age was 75 and 55% were females. The total stroke incidence decreased over the 16 year study period in men (Incidence Rate Ratio 1995-1996 vs. 2009-2010 (IRR) 0.78; 95% CI 0.58-0.90) but not in women. Among stroke subtypes, a decrease in ischemic stroke incidence (IRR 0.73; 95% CI 0.57-0.93) and of large artery atherosclerotic stroke (IRR 0.27; 95% CI 0.12-0.59) was found in men and an increase of stroke due to small artery occlusion in women (IRR 2.33; 95% CI 1.39-3.90).Variations in time trends of pathological and etiological stroke subtypes were found between men and women that might be linked to gender differences in the development of major vascular risk factors in the study population.
EVALuna2:22434

Tissue hypoxia and alterations in microvascular architecture predict glioblastoma recurrence in humans - Stadlbauer, Andreas; Kinfe, Thomas Mehari; Eyüpoglu, Ilker Yasin; Zimmermann, Max; Kitzwoegerer, Melitta; Podar, Klaus; Buchfelder, Michael; Heinz, Gertraud; Oberndorfer, Stefan; Marhold, Franz (Clinical Cancer Research, 2021)
Purpose: Insufficient control of infiltrative glioblastoma (GBM) cells is a major cause of treatment failure and tumor recurrence. Hence, detailed insights into pathophysiologic changes that precede GBM recurrence are needed to develop more precise neuroimaging modalities for tailored diagnostic monitoring and therapeutic approaches. Experimental Design: Overall, 168 physiologic MRI follow-up examinations of 56 patients with GBM who developed recurrence after standard therapy were retrospectively evaluated, that is, two post-standard-therapeutic follow-ups before and one at radiological recurrence. MRI biomarkers for microvascular architecture and perfusion, neovascularization activity, oxygen metabolism, and hypoxia were determined for brain areas that developed in the further course into recurrence and for the recurrent GBM itself. The temporal pattern of biomarker changes was fitted with locally estimated scatterplot smoothing functions and analyzed for pathophysiologic changes preceding radiological GBM recurrence. Results: Our MRI approach demonstrated early pathophysiologic changes prior to radiological GBM recurrence in all patients. Analysis of the time courses revealed a model for the pathophysiology of GBM recurrence: 190 days prior to radiological recurrence, vascular cooption by GBM cells induced vessel regression, detected as decreasing vessel density/perfusion and increasing hypoxia. Seventy days later, neovascularization activity was upregulated, which reincreased vessel density and perfusion. Hypoxia, however, continued to intensify for 30 days and peaked 90 days before radiological recurrence. Conclusions: Hypoxia may represent an early sign for GBM recurrence. This might become useful in the development of new combined diagnostic-therapeutic approaches for tailored clinical management of recurrent GBM. Further preclinical and in-human studies are required for validation and evaluation.
CRIS-Team Scopus Importer:2021-04-09

Tolvaptan Versus Fluid Restriction in the Treatment of Hyponatremia Resulting from SIADH Following Pituitary Surgery - Kleindienst, Andrea; Georgiev, Simeon; Schlaffer, Sven-Martin; Buchfelder, Michael (Journal of the Endocrine Society, 2020)
Context. The relevance of hyponatremia has been acknowledged by guidelines from the United States (2013) and Europe (2014). However, treatment recommendations differ due to limited evidence.
CRIS-Team WoS Importer:2020-08-21

Topographical anatomy of the septum verum and its white matter connections - Barany, Laszlo; Meszaros, Cintia; Alpar, Alan; Ganslandt, Oliver; Hore, Nirjhar; Delev, Daniel; Schnell, Oliver; Kurucz, Peter (Scientific Reports, 2024)
The human septum verum represents a small but clinically important region of the brain. Based on the results of animal experiments, the stimulation of its medial part was recently proposed with various indications like epilepsy or cognitive impairment after traumatic brain injury. The aim of our study was to present the anatomical relationships of the human septum verum using fiber dissection and histological analysis to support its research and provide essential information for future deep brain stimulation therapies. 16 human cadaveric brains were dissected according to Klingler’s method. To validate our macroscopical findings, 12 samples obtained from the dissected brains and 2 additional specimens from unfrozen brains were prepared for histological examinations. We identified the following white matter connections of the septum verum: (1) the precommissural fibers of the fornix; (2) the inferior fascicle of the septum pellucidum; (3) the cingulum; (4) the medial olfactory stria; (5) the ventral amygdalofugal pathway; (6) the stria medullaris of the thalamus and (7) the stria terminalis. Moreover, we could distinguish a less-known fiber bundle connecting the postcommissural column of the fornix to the stria medullaris of the thalamus and the anterior thalamic nuclei. In this study we present valuable anatomical information about this region to promote safe and effective deep brain stimulation therapies in the future.
CRIS-Team Scopus Importer:2024-08-16

Topographical anatomy of the subthalamic region with special interest in the human medial forebrain bundle - Meszaros, Cintia; Kurucz, Peter; Baksa, Gabor; Alpar, Alan; Ganslandt, Oliver; Brandner, Sebastian; Barany, Laszlo (Journal of Neurosurgery, 2024)
OBJECTIVE The medial forebrain bundle (MFB) is a novel promising deep brain stimulation (DBS) target in severe affective disorders that courses through the subthalamic region according to tractography studies. Its potential therapeutic role arose in connection with the development of hypomania during stimulation of the subthalamic nucleus (STN) in Parkinson's disease, offering an alternative explanation for the occurrence of this side effect. However, until now its course exclusively described by tractography had not yet been confirmed by any anatomical method. The aim of this study was to fill this gap as well as to provide a detailed description of the fiber tracts surrounding the STN to facilitate a better understanding of the background of side effects occurring during STN DBS. METHODS Ten human cadaveric brains (20 hemispheres) and 100 healthy subjects (200 hemispheres) from the S500 Release of the Human Connectome Project were involved in this study. Nineteen hemispheres were dissected according to Klingler's method. One additional hemisphere was prepared for histological examinations to validate the macroscopical results and stained with neurofibril silver impregnation according to Krutsay. The authors also aimed to reconstruct the MFB using tractography and correlated the results with their dissections and histological findings. RESULTS The white matter connections coursing through the subthalamic region were successfully dissected. The ansa lenticularis, lenticular fasciculus, thalamic fasciculus, ipsi- and contralateral cerebellar fibers, and medial lemniscus were revealed as closely related fiber tracts to the STN. However, the existence of a distinct fiber bundle corresponding to the MFB described by tractography could not be identified. Using tractography, the authors showed that the depiction of the streamlines representing the MFB was also strongly dependent on the threshold parameters. CONCLUSIONS According to this study's findings, the streamlines of the MFB described by tractography arise from the limitations of the diffusion-weighted MRI fiber tracking method and actually correspond to subthalamic fiber bundles, especially the ansa lenticularis and lenticular fasciculus, which erroneously continue in the anterior limb of the internal capsule, toward the prefrontal cortex.
CRIS-Team Scopus Importer:2024-08-16
Keywords: anatomy; deep brain stimulation; fiber dissection; functional neurosurgery; medial forebrain bundle; subthalamus; tractography

TP53 mutations in functional corticotroph tumors are linked to invasion and worse clinical outcome - Perez-Rivas, Luis Gustavo; Simon, Julia; Albani, Adriana; Tang, Sicheng; Roeber, Sigrun; Assie, Guillaume; Deutschbein, Timo; Fassnacht, Martin; Gadelha, Monica R.; Hermus, Ad R.; Stalla, Guenter K.; Tichomirowa, Maria A.; et al. (Acta Neuropathologica Communications, 2022)
Corticotroph macroadenomas are rare but difficult to manage intracranial neoplasms. Mutations in the two Cushing’s disease mutational hotspots USP8 and USP48 are less frequent in corticotroph macroadenomas and invasive tumors. There is evidence that TP53 mutations are not as rare as previously thought in these tumors. The aim of this study was to determine the prevalence of TP53 mutations in corticotroph tumors, with emphasis on macroadenomas, and their possible association with clinical and tumor characteristics. To this end, the entire TP53 coding region was sequenced in 86 functional corticotroph tumors (61 USP8 wild type; 66 macroadenomas) and the clinical characteristics of patients with TP53 mutant tumors were compared with TP53/USP8 wild type and USP8 mutant tumors. We found pathogenic TP53 variants in 9 corticotroph tumors (all macroadenomas and USP8 wild type). TP53 mutant tumors represented 14% of all functional corticotroph macroadenomas and 24% of all invasive tumors, were significantly larger and invasive, and had higher Ki67 indices and Knosp grades compared to wild type tumors. Patients with TP53 mutant tumors had undergone more therapeutic interventions, including radiation and bilateral adrenalectomy. In conclusion, pathogenic TP53 variants are more frequent than expected, representing a relevant amount of functional corticotroph macroadenomas and invasive tumors. TP53 mutations associated with more aggressive tumor features and difficult to manage disease.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Corticotroph; Cushing’s disease; Macroadenomas; TP53; USP8

Tracking cell turnover in human brain using 15N-thymidine imaging mass spectrometry - Röder, Sebastian; Bonnin, Elisa A.; Wu, Ting Di; Guerquin-Kern, Jean Luc; Jabari, Samir; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Gollwitzer, Stephanie; Hamer, Hajo; Gerner, Stefan; Döppner, Thorsten R.; Rummel, Christoph; et al. (Frontiers in Neuroscience, 2023)
Microcephaly is often caused by an impairment of the generation of neurons in the brain, a process referred to as neurogenesis. While most neurogenesis in mammals occurs during brain development, it thought to continue to take place through adulthood in selected regions of the mammalian brain, notably the hippocampus. However, the generality of neurogenesis in the adult brain has been controversial. While studies in mice and rats have provided compelling evidence for neurogenesis occurring in the adult rodent hippocampus, the lack of applicability in humans of key methods to demonstrate neurogenesis has led to an intense debate about the existence and, in particular, the magnitude of neurogenesis in the adult human brain. Here, we demonstrate the applicability of a powerful method to address this debate, that is, the in vivo labeling of adult human patients with 15N-thymidine, a non-hazardous form of thymidine, an approach without any clinical harm or ethical concerns. 15N-thymidine incorporation into newly synthesized DNA of specific cells was quantified at the single-cell level with subcellular resolution by Multiple-isotype imaging mass spectrometry (MIMS) of brain tissue resected for medical reasons. Two adult human patients, a glioblastoma patient and a patient with drug-refractory right temporal lobe epilepsy, were infused for 24 h with 15N-thymidine. Detection of 15N-positive leukocyte nuclei in blood samples from these patients confirmed previous findings by others and demonstrated the appropriateness of this approach to search for the generation of new cells in the adult human brain. 15N-positive neural cells were easily identified in the glioblastoma tissue sample, and the range of the 15N signal suggested that cells that underwent S-phase fully or partially during the 24 h in vivo labeling period, as well as cells generated therefrom, were detected. In contrast, within the hippocampus tissue resected from the epilepsy patient, none of the 2,000 dentate gyrus neurons analyzed was positive for 15N-thymidine uptake, consistent with the notion that the rate of neurogenesis in the adult human hippocampus is rather low. Of note, the likelihood of detecting neurogenesis was reduced because of (i) the low number of cells analyzed, (ii) the fact that hippocampal tissue was explored that may have had reduced neurogenesis due to epilepsy, and (iii) the labeling period of 24 h which may have been too short to capture quiescent neural stem cells. Yet, overall, our approach to enrich NeuN-labeled neuronal nuclei by FACS prior to MIMS analysis provides a promising strategy to quantify even low rates of neurogenesis in the adult human hippocampus after in vivo15N-thymidine infusion. From a general point of view and regarding future perspectives, the in vivo labeling of humans with 15N-thymidine followed by MIMS analysis of brain tissue constitutes a novel approach to study mitotically active cells and their progeny in the brain, and thus allows a broad spectrum of studies of brain physiology and pathology, including microcephaly.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adult; cell turnover; DNA-labeling; glioblastoma; hippocampus; Nano-SIMS; neurogenesis

Transient Enlargement in Meningiomas Treated with Stereotactic Radiotherapy - Maksoud, Ziad; Schmidt, Manuel; Huang, Yixing; Rutzner, Sandra; Mansoorian, Sina; Weissmann, Thomas; Bert, Christoph; Distel, Luitpold; Semrau, Sabine; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Fietkau, Rainer; et al. (Cancers, 2022)
To investigate the occurrence of pseudoprogression/transient enlargement in meningiomas after stereotactic radiotherapy (RT) and to evaluate recently proposed volumetric RANO meningioma criteria for response assessment in the context of RT. Sixty-nine meningiomas (benign: 90%, atypical: 10%) received stereotactic RT from January 2005–May 2018. A total of 468 MRI studies were segmented longitudinally during a median follow-up of 42.3 months. Best response and local control were evaluated according to recently proposed volumetric RANO criteria. Transient enlargement was defined as volumetric increase ≥20% followed by a subsequent regression ≥20%. The mean best volumetric response was −23% change from baseline (range, −86% to +19%). According to RANO, the best volumetric response was SD in 81% (56/69), MR in 13% (9/69) and PR in 6% (4/69). Transient enlargement occurred in only 6% (4/69) post RT but would have represented 60% (3/5) of cases with progressive disease if not accounted for. Transient enlargement was characterized by a mean maximum volumetric increase of +181% (range, +24% to +389 %) with all cases occurring in the first year post-RT (range, 4.1–10.3 months). Transient enlargement was significantly more frequent with SRS or hypofractionation than with conventional fractionation (25% vs. 2%, p = 0.015). Five-year volumetric control was 97.8% if transient enlargement was recognized but 92.9% if not accounted for. Transient enlargement/pseudoprogression in the first year following SRS and hypofractionated RT represents an important differential diagnosis, especially because of the high volumetric control achieved with stereotactic RT. Meningioma enlargement during subsequent post-RT follow-up and after conventional fractionation should raise suspicion for tumor progression. <
Keywords: meningioma; volumetric analysis; segmentation; transient enlargement; pseudoprogression; stereotactic radiotherapy; radiosurgery; response assessment

Treatment of posttraumatic syringomyelia: evidence from a systematic review - Kleindienst, Andrea; Laut, Francisco Marin; Roeckelein, Verena; Buchfelder, Michael; Dodoo-Schittko, Frank (Acta Neurochirurgica, 2020)
Background: Following spinal cord injury (SCI), the routine use of magnetic resonance imaging (MRI) resulted in an incremental diagnosis of posttraumatic syringomyelia (PTS). However, facing four decades of preferred surgical treatment of PTS, no clear consensus on the recommended treatment exists. We review the literature on PTS regarding therapeutic strategies, outcomes, and complications. Methods: We performed a systematic bibliographic search on (“spinal cord injuries” [Mesh] AND “syringomyelia” [Mesh]). English language literature published between 1980 and 2020 was gathered, and case reports and articles examining syrinx due to other causes were excluded. The type of study, interval injury to symptoms, severity and level of injury, therapeutic procedure, duration of follow-up, complications, and outcome were recorded. Results: Forty-three observational studies including 1803 individuals met the eligibility criteria. The time interval from SCI to the diagnosis of PTS varied between 42 and 264 months. Eighty-nine percent of patients were treated surgically (n = 1605) with a complication rate of 26%. Symptoms improved in 43% of patients postoperatively and in 2% treated conservatively. Stable disease was documented in 50% of patients postoperatively and in 88% treated conservatively. The percentage of deterioration was similar (surgery 16%, 0.8% dead; conservative 10%). Detailed analysis of surgical outcome with regard to symptoms revealed that pain, motor, and sensory function could be improved in 43 to 55% of patients while motor function deteriorated in around 25%. The preferred methods of surgery were arachnoid lysis (48%) and syrinx drainage (31%). Conclusion: Even diagnosing PTS early in its evolution with MRI, to date, no satisfactory standard treatment exists, and the present literature review shows similar outcomes, regardless of the treatment modality. Therefore, PTS remains a neurosurgical challenge. Additional research is required using appropriate study designs for improving treatment options.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Etiology; Hydromyelia; Spinal cord injury; Syringomyelia; Trauma; Treatment

Treatment of Primary Hypophysitis in Germany - Honegger, Juergen; Buchfelder, Michael; Schlaffer, Sven-Martin; Droste, Michael; Werner, Sandy; Strasburger, Christian; Stoermann, Sylvere; Schopohl, Jochen; Kacheva, Stella; Deutschbein, Timo; Stalla, Guenter; Flitsch, Joerg; et al. (Journal of Clinical Endocrinology and Metabolism, 2015)
The best treatment of primary hypophysitis (PrHy) is a matter of debate.Our main objective was to analyze the treatment practice for PrHy in Germany and to compare the outcome of the main treatment options.The Pituitary Working Group of the German Society of Endocrinology conducted a nationwide retrospective cross-sectional cohort study.Seventy-six patients with PrHy were eligible for the study.Clinical and endocrinological outcomes, side effects and complications of therapy, initial response, and recurrence rates were assessed. Outcome depending on the treatment modality was evaluated.For mere observation, regression of space-occupying lesions was observed in 46%, unchanged size in 27%, and progression reported in 27%. Pituitary function improved in 27% of patients during observation. Deterioration of pituitary function was only found in patients with progressive lesions. The initial response to glucocorticoid pulse therapy was most favorable, with early failure in only 3%. However, the overall failure and recurrence rate was 41%. Recurrence rate was not related to duration of steroid administration. Side effects of steroids occurred in 63%. The surgical approach was transsphenoidal in 94%. The histological subtype was lymphocytic hypophysitis in 70% and granulomatous hypophysitis in 30%. Progression or recurrence was observed in 25% after surgical treatment.Glucocorticoid pulse therapy is associated with a high recurrence rate. Evidence suggests that surgery is not able to prevent recurrence. Considering the favorable results of observation, conservative management is recommended in PrHy unless symptoms are severe or progressive.
EVALuna2:22870

Treatment of severe traumatic brain injury in German pediatric intensive care units—a survey of current practice - Regensburger, Adrian; Konrad, V.; Trollmann, Regina; Eyüpoglu, Ilker Yasin; Huebner, H.; Zierk, Jakob; Voelkl, T. M. K.; Fahlbusch, F. B. (Childs Nervous System, 2019)
Purpose: German pediatric guidelines for severe traumatic brain injury (TBI) management expired in 2011. Thus, divergent evidence-based institutional protocols are predominantly being followed. We performed a survey of current Pediatric Intensive Care Unit (PICU) management of isolated severe TBI in Germany to reveal potential varying practices. Methods: Seventy German PICUs were invited to join an anonymous online survey from February to May 2017. Twenty-nine participants (41.4%) successfully completed the survey (17 university hospitals and 12 district hospitals). The majority of items were polar (yes/no) or scaled (e.g., never - always). Main topics were imaging, neurosurgery, neuromonitoring, adjuvant therapy, and medication. Severity of TBI was defined via Glasgow Coma Scale. Results: The majority of respondents (93.1%) had internal TBI standards, and patients were mainly administered to interdisciplinary trauma units. The use of advanced neuromonitoring techniques, intracranial hypertension management, and drug treatment differed between PICUs. Routine administration of hypertonic saline in TBI-associated cerebral edema was performed by 3.4%, while it was never an option for 31.0% of the participants. Prophylactic anticonvulsive therapy was restrictively performed. If indicated, the main anticonvulsive drugs used were phenobarbital and levetiracetam. Neuroendocrine follow-up was recommended/performed by 58.6% of the PICUs. Conclusions: This survey provides an overview of the current PICU practices of isolated severe TBI management in Germany and demonstrates a wide instrumental and therapeutical range, revealing an unmet need for the revised national guideline and further (international) clinical trials for the treatment of severe TBI in pediatrics.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Adjuvant therapy; ICP; Neuroimaging; Neuromonitoring

Treatment with Cyclic AMP Activators Reduces Glioblastoma Growth and Invasion as Assessed by Two-Photon Microscopy - Wartchow, Krista Mineia; Schmid, Benjamin; Tripal, Philipp; Stadlbauer, Andreas; Buchfelder, Michael; Goncalves, Carlos-Alberto; Kleindienst, Andrea (Cells, 2021)
(1) Background: Despite progress in surgery and radio-chemotherapy of glioblastoma (GB), the prognosis remains very poor. GB cells exhibit a preference for hypoxia to maintain their tumor-forming capacity. Enhancing oxidative phosphorylation-known as the anti-Warburg effect-with cyclic AMP activators has been demonstrated to drive GB cells from proliferation to differentiation thereby reducing tumor growth in a cell culture approach. Here we re-evaluate this treatment in a more clinically relevant model. (2) Methods: The effect of treatment with dibutyryl cyclic AMP (dbcAMP, 1 mM) and the cAMP activator forskolin (50µM) was assessed in a GB cell line (U87GFP+, 104 cells) co-cultured with mouse organotypic brain slices providing architecture and biochemical properties of normal brain tissue. Cell viability was determined by propidium-iodide, and gross metabolic effects were excluded in the extracellular medium. Tumor growth was quantified in terms of area, volume, and invasion at the start of culture, 48 h, 7 days, and 14 days after treatment. (3) Results: The tumor area was significantly reduced following dbcAMP or forskolin treatment (F2,249 = 5.968, p = 0.0029). 3D volumetric quantification utilizing two-photon fluorescence microscopy revealed that the treated tumors maintained a spheric shape while the untreated controls exhibited the GB typical invasive growth pattern. (4) Conclusions: Our data demonstrate that treatment with a cAMP analog/activator reduces GB growth and invasion.
CRIS-Team Scopus Importer:2021-04-16
Keywords: 2-photon-microscopy; glioblastoma; oxidative phosphorylation; treatment; Warburg effect

Treatment with the Neurotrophic Protein S100 Calcium-Binding Protein B Increases Synaptogenesis after Traumatic Brain Injury - Baecker, Justus; Wartchow, Krista; Sehm, Tina; Ghoochani, Ali; Buchfelder, Michael; Kleindienst, Andrea (Journal of Neurotrauma, 2019)
Release of neurotrophic and growth factors such as S100 calcium-binding protein B (S100B) yields an endogenous repair mechanism following traumatic brain injury (TBI). Although nanomolar S100B concentrations enhance hippocampal progenitor cell proliferation, neuronal differentiation, and cognitive recovery, micromolar concentrations may foster inflammatory effects counteracting neuroplasticity. The purpose of the present study was to investigate the effect of S100B on synaptogenesis and microglial activation following experimental TBI. Male Sprague-Dawley rats (n = 40) were subjected to lateral fluid percussion or sham injury, and S100B (50 ng/h) or phosphate buffered saline (PBS) was infused into the lateral ventricle for 7 days using osmotic micropumps. The animals were euthanized on day 5 or, 5 weeks post-injury, and 5 mu m sections, 100 mu m apart (bregma -3.3 to -5.6mm) were analyzed histologically. Cell proliferation was assessed injecting the mitotic marker Bromodeoxyuridine (BrdU) on day 2. S100B enhanced significantly the synaptophysin (SYN) expression and microglial activation (ectodysplasin [ED1]) in the hippocampus in TBI and uninjured sham animals. The glial activation (glial fibrillary acidic protein [GFAP], S100B immunoreactive cells), axonal injury (APP) and cell death (terminal deoxynucleotidyl transferase dUTP nick end labeling [TUNEL]) were not altered. Triple-labelling with BrdU, NeuN, and SYN confirmed a significant participation of S100B in hippocampal synaptogenesis in TBI and uninjured sham animals. Our results demonstrate that S100B augments hippocampal neuro- and synaptogenesis in TBI and uninjured sham animals, thereby improving cognitive function as demonstrated earlier. The S100B-induced microglial activation does not counteract this effect within the first 5weeks. Further studies are required to elucidate respective cellular signaling mechanisms and possible long-term effects.
CRIS-Team WoS Importer:2019-11-26

Typing of inflammatory lesions of the pituitary - Warmbier, J.; Luedecke, D. K.; Flitsch, J.; Buchfelder, Michael; Fahlbusch, R.; Knappe, U. J.; Kreutzer, J.; Buslei, R.; Bergmann, M.; Heppner, F.; Glatzel, M.; Saeger, W. (Pituitary, 2021)
Inflammatory pituitary lesions account for 1.8% of all specimens from the German Pituitary Tumor Registry. They occure in 0.5% of the autoptical specimens and in 2.2% of the surgical cases. Women are significantly more often affected than men and are often younger when first diagnosed. In general, primary and secondary inflammation can be distinguished, with secondary types occurring more frequently (75.1%) than idiopathic inflammatory lesions (15.4%). In primary inflammation, the lymphocytic type is more common (88.5%) than the granulomatous type of hypophysitis (11.5%). The most common causes of secondary inflammation are Rathke’s cleft cysts (48.6%), followed by tumors (17.4%) such as the craniopharyngioma (9.1%), adenoma (5.5%) or germinoma (2.0%). More causes are tumor-like lesions (7.1%) such as xanthogranuloma (3.5%) or Langerhans histiocytosis (3.5%), abscesses (5.5%), generalized infections (5.1%), spreaded inflammations (4.7%) and previous surgeries (4.0%). In 1.6% of all specimens the reason for the inflammation remains unclear. The described classification of hypophysitis is important for specific treatment planning after surgery.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Classification; Hypophysitis; Pathology; Pituitary

Ultra-early Detection of Microcirculatory Injury as Predictor of Developing Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Gölitz, Philipp; Rösch, Julie; Roessler, Karl; Knossalla, Frauke; Dörfler, Arnd; Hölter, Philip (Clinical Neuroradiology, 2018)
Purpose Delayed cerebral ischemia (DCI) still remains amajor complication after subarachnoid hemorrhage (SAH). The aim of our study was to evaluate whether flow analysis of admission digital subtraction angiography (DSA) using parametric color coding (PCC), apostprocessing algorithm, allows ultra-early identification of SAH patients at risk for developing subsequent symptomatic vasospasm. Methods In this study 52patients who suffered SAH from aneurysm rupture, were retrospectively enrolled. Of the patients 26 developed DCI and angiographically proven cerebral vasospasm and 26age, gender-and clinical status-matched SAH patients without DCI served as controls. Using PCC, the following flow parameters were calculated: cerebral circulation time (CirT), cortical relative time to peak (rTTP) and microvascular transit time (TT). Results Mean cerebral CirT and cortical rTTP were longer in the DCI group (6.42s +/- 1.54 and 3.16s +/- 0.86, respectively) than in the non-DCI group (5.77s +/- 1.86 and 3.11s +/- 1.41, respectively), but without statistical significance. The mean microvascular TT was statistically significantly (p = 0.04) longer in the DCI group (3.19s +/- 0.78) than in the non-DCI group (2.67s +/- 0.73). Conclusion Angiographic flow analysis might be suitable for ultra-early detection and quantitative assessment of microcirculatory injury in SAH patients, predictive of developing subsequent DCI. Prolonged microvascular TT seems to be asignificant independent factor positively associated with DCI development. Identifying SAH patients at risk for DCI ultra-early after ictus might contribute to initiate prophylactic therapies before clinical deterioration.
EVALuna2:34933

Ultra-High-Field 7 T Magnetic Resonance Imaging Including Dynamic and Static Contrast-Enhanced T1-Weighted Imaging Improves Detection of Secreting Pituitary Microadenomas - Eisenhut, Felix; Schlaffer, Sven-Martin; Hock, Stefan; Heynold, Elisabeth; Kremenevski, Natalia; Blümcke, Ingmar; Buchfelder, Michael; Dörfler, Arnd; Schmidt, Manuel (Investigative Radiology, 2022)
OBJECTIVE: A prospective preoperative evaluation of 7 T ultra-high-field magnetic resonance imaging (MRI) in patients with suspected pituitary microadenomas for both adenoma detection and intrasellar localization compared with 3 T MRI was carried out. MATERIALS AND METHODS: Patients underwent prospective preoperative standardized 3 and 7 T MRI. A distinct qualitative (lesion detection, intrasellar lesion location) and quantitative (lesion diameters, T1/T2 signal intensity ratio of the lesion to normal pituitary gland tissue) analysis was performed, along with an evaluation of image quality (IQ) regarding overall IQ, anatomical parameters, and artifacts; the findings of the qualitative analysis were compared with intraoperative findings and endocrinological outcomes. RESULTS: Sixteen patients (mean age, 43 ± 16 years; 13 women) with pituitary microadenomas were included. Using 7 T MRI allowed the detection of 15 microadenomas-3 more than 3 T MRI. In addition, 7 T MRI allowed more precise lesion localization with 93.75% (15/16) agreement with intraoperative findings, compared with 75% (12/16) agreement using 3 T MRI. Lesion diameters showed no significant difference between 3 and 7 T MRI. T1 and T2 signal intensity ratio between microadenomas and normal pituitary gland tissue were higher in 7 T MRI than in 3 T MRI. The overall IQ and the IQ of each anatomical parameter of 7 T MRI were rated higher than those of 3 T MRI. No significant differences in susceptibility or head motion artifacts were observed between 3 and 7 T MRI; however, 7 T MRI was more susceptible to pulsation artifacts. CONCLUSION: Ultra-high-field MRI surpasses 3 T MRI in pituitary microadenoma detection and enables more precise delineation with higher correlation with intraoperative findings. Thus, 7 T sellar imaging is a promising option-especially in previously magnetic resonance-negative patients with endocrinologically confirmed hormone oversecretion-and helps reduce the need for invasive diagnostics.
CRIS-Team Scopus Importer:2022-08-12

Ultra-high field MRI of human hippocampi: Morphological and multiparametric differentiation of hippocampal sclerosis subtypes - Gillmann, Clarissa; Coras, Roland; Roessler, Karl; Dörfler, Arnd; Uder, Michael; Blümcke, Ingmar; Bäuerle, Tobias (PLoS ONE, 2018)
The aim of the present study is to differentiate subtypes of hippocampal sclerosis (HS) using ex vivo ultra-high field magnetic resonance imaging (MRI). Included were 14 surgically resected hippocampi of patients with medically intractable temporal lobe epilepsy. The resected hippocampi were histologically categorized into subtypes of hippocampal sclerosis (HS type 1 (n = 10), HS type 2 (n = 2) and no-HS (n = 2)) and subsequently scanned on a preclinical 7T MRI acquiring T2-weighted morphology, relaxometry and diffusion tensor imaging. On the morphological images, the pyramidal cell layer (PCL) of the hippocampus was segmented and the following parameters were derived: T2 signal intensity, T1-, T2- and T2*-relaxation times, apparent diffusion coefficient (ADC), fractional anisotropy (FA) and mean diffusivity (MD). Furthermore, the area of the PCL was determined, as well as the parameter product which refers to the widths of the PCL parallel and perpendicular to the stratum moleculare. Spearman correlation coefficient was used to demonstrate relationships between MR-parameters and type of sclerosis. In comparison to no-HS specimens, the PCL was significantly narrower in HS type 1 and HS type 2 hippocampi. This narrowing affected the entire cornu ammonis sector (CA) 1 in HS type 1, while it was limited to the upper half of CA1 in direction to CA2 in HS type 2. The parameter product median increased from 0.43 to 1.67 and 2.91 mm2 for HS type 1, HS type 2 and no-HS, respectively. Correlation coefficients were significant for the PCL parameters product (0.73), area (0.71), T2*-time (-0.67), FA (0.65) and ADC (0.55). Our initial results suggest that HS type 1, HS type 2 and no-HS subtypes can be distinguished from each other using ex vivo UHF MRI based on T2-weighted morphologic images and the assessment of the parameter product. Upon clinical translation, UHF-MRI may provide a promising technique for the preoperative differentiation of HS subtypes in patients.
EVALuna2:34592

Unaltered Responses of Distal Motor Neurons to Non-Targeted Thoracic Spinal Cord Stimulation in Chronic Pain Patients - Riera, Carolyn; Souza de Oliveira, Daniela; Borutta, Matthias; Regensburger, Martin; Zhao, Yining; Brenner, Steffen; Del Vecchio, Alessandro; Kinfe, Thomas Mehari (Pain and Therapy, 2024)
Introduction: Spinal cord stimulation (SCS) represents an established interventional pain therapeutic; however, the SCS effects of SCS waveforms on motor neuron recruitment of the lower limbs of chronic pain patients remain largely unknown. Methods: We investigated these effects by performing isometric ankle-dorsal flexions at varying force levels under four SCS conditions: SCS Off (1 week), burst SCS (40 Hz), SCS Off (acute), and tonic SCS (130 Hz). Muscle activity was recorded via high-density surface electromyography (64-electrode grid) on the tibialis anterior muscle. Motor unit action (MUs) potentials were analyzed for recruitment and de-recruitment thresholds, discharge rate, inter-spike interval, and common synaptic input. Results: In this prospective study, we included nine patients (five females; four males; mean age 59 years) with chronic pain treated with thoracic (Th7–Th8) epidural spinal stimulation. A total of 97 MUs were found for 15% maximal voluntary torque (MVT) and 83 for 30%MVT, an average of 10.8 ± 3.7 for 15%MVT and 10.4 ± 3.5 for 30%MVT. While a few subject-specific variations were observed, our study suggests that the different SCS frequencies applied do not significantly influence motor unit discharge characteristics in the TA muscle among the participants (p values at 15%MVT were 0.586 (Chi2 = 1.933), 0.737 (Chi2 = 1.267), 0.706 (Chi2 = 1.4) and 0.586 (Chi2 = 1.933), respectively. The p values of the Friedman test at 30%MVT were 0.896 (Chi2 = 0.6), 0.583 (Chi2 = 1.95), 0.896 (Chi2 = 0.6) and 0.256 (Chi2 = 4.05). No significant difference was found for the different stimulation types for the delta (0–5 Hz), alpha (5–12 Hz), and beta (15–30 Hz) bands at both force levels. Conclusions: In summary, we did not observe any changes in motor unit oscillatory activity at any low and high bandwidths, indicating that SCS using different waveforms (tonic/burst) does not significantly influence motor neuron recruitment for non-motor individuals with chronic pain.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Burst/tonic stimulation waveforms; Chronic pain; High-density surface electromyogram (HD-EMG); Motor unit recruitment (MUR); Spinal cord stimulation (SCS)

Understanding glioblastoma at the single-cell level: Recent advances and future challenges - Yabo, Yahaya; Heiland, Dieter Henrik (Plos Biology, 2024)
AU Glioblastoma,: Pleaseconfirmthatallheadinglevelsarerepresentedcorrectly the most aggressive and prevalent form of primary : brain tumor, is characterized by rapid growth, diffuse infiltration, and resistance to therapies. Intrinsic heterogeneity and cellular plasticity contribute to its rapid progression under therapy; therefore, there is a need to fully understand these tumors at a single-cell level. Over the past decade, single-cell transcriptomics has enabled the molecular characterization of individual cells within glioblastomas, providing previously unattainable insights into the genetic and molecular features that drive tumorigenesis, disease progression, and therapy resistance. However, despite advances in single-cell technologies, challenges such as high costs, complex data analysis and interpretation, and difficulties in translating findings into clinical practice persist. As single-cell technologies are developed further, more insights into the cellular and molecular heterogeneity of glioblastomas are expected, which will help guide the development of personalized and effective therapies, thereby improving prognosis and quality of life for patients.
CRIS-Team Scopus Importer:2024-06-14

Vagus nerve stimulation for the management of chronic pain - Russo, Marc A.; Chakravarthy, Krishnan; Kinfe, Thomas Mehari (Elsevier, 2024)
The vagus nerve, a crucial component of the parasympathetic nervous system, plays a pivotal role in regulating autonomic balance. Originating in the brain stem, it serves as a link between the higher brain centers, autonomic nervous system, central and peripheral nervous systems, immune system, and visceral organs through extensive branching and afferent/efferent innervation. Vagus nerve stimulation (VNS) has proven effective in treating refractory epilepsy and treatment-resistant depression, while also showing promise in managing chronic pain. Its potential analgesic effects have been demonstrated in animals, with comparable effects documented in epilepsy patients with implanted VNS devices. Further support comes from experimental pain studies in healthy humans and neuroimaging studies. Potential benefits have also been explored in primary headache disorders, fibromyalgia, visceral and pelvic pain, and other pain conditions using modern noninvasive systems. Proposed mechanisms for the analgesic effects of VNS include activation of the cholinergic antiinflammatory pathway and modulation of spinal nociceptive transmission. Future research may focus on central sensitization states and pain conditions in which widespread brain-immune interaction is involved.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Analgesia; Chronic pain; Inflammation; Nociception; Pain modulation; Vagus nerve stimulation

Vagus nerve stimulation reduces spreading depolarization burden and cortical infarct volume in a rat model of stroke - Lindemann, Jan; Rakers, Cordula; Matuskova, Hana; Simon, Bruce J.; Kinfe, Thomas Mehari; Petzold, Gabor C. (PLoS ONE, 2020)
Cortical spreading depolarization (SD) waves negatively affect neuronal survival and outcome after ischemic stroke. We here aimed to investigate the effects of vagus nerve stimulation (VNS) on SDs in a rat model of focal ischemia. To this end, we delivered non-invasive VNS (nVNS) or invasive VNS (iVNS) during permanent middle cerebral artery occlusion (MCAO), and found that both interventions significantly reduced the frequency of SDs in the cortical peri-infarct area compared to sham VNS, without affecting relative blood flow changes, blood pressure, heart rate or breathing rate. In separate groups of rats subjected to transient MCAO, we found that cortical stroke volume was reduced 72 h after transient MCAO, whereas stroke volume in the basal ganglia remained unchanged. In rats treated with nVNS, motor outcome was improved 2 days after transient MCAO, but was similar to sham VNS animals 3 days after ischemia. We postulate that VNS may be a safe and efficient intervention to reduce the clinical burden of SD waves in stroke and other conditions.
CRIS-Team Scopus Importer:2020-08-07

Validating EEG, MEG and Combined MEG and EEG Beamforming for an Estimation of the Epileptogenic Zone in Focal Cortical Dysplasia - Neugebauer, Frank; Antonakakis, Marios; Unnwongse, Kanjana; Parpaley, Yaroslav; Wellmer, Jörg; Rampp, Stefan; Wolters, Carsten H. (Brain Sciences, 2022)
MEG and EEG source analysis is frequently used for the presurgical evaluation of phar-macoresistant epilepsy patients. The source localization of the epileptogenic zone depends, among other aspects, on the selected inverse and forward approaches and their respective parameter choices. In this validation study, we compare the standard dipole scanning method with two beamformer approaches for the inverse problem, and we investigate the influence of the covariance estimation method and the strength of regularization on the localization performance for EEG, MEG, and combined EEG and MEG. For forward modelling, we investigate the difference between calibrated six-compartment and standard three-compartment head modelling. In a retrospective study, two patients with focal epilepsy due to focal cortical dysplasia type IIb and seizure freedom following le-sionectomy or radiofrequency-guided thermocoagulation (RFTC) used the distance of the localization of interictal epileptic spikes to the resection cavity resp. RFTC lesion as reference for good localization. We found that beamformer localization can be sensitive to the choice of the regularization parameter, which has to be individually optimized. Estimation of the covariance matrix with averaged spike data yielded more robust results across the modalities. MEG was the dominant modality and provided a good localization in one case, while it was EEG for the other. When combining the modalities, the good results of the dominant modality were mostly not spoiled by the weaker modality. For appropriate regularization parameter choices, the beamformer localized better than the standard dipole scan. Compared to the importance of an appropriate regularization, the sensitivity of the localization to the head modelling was smaller, due to similar skull conductivity modelling and the fixed source space without orientation constraint.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Beamformer; EEG; Epilepsy; MEG; Regularization; Source analysis; Validation

Validating EEG source imaging using intracranial electrical stimulation - Unnwongse, Kanjana; Rampp, Stefan; Wehner, Tim; Kowoll, Annika; Parpaley, Yaroslav; Von Lehe, Marec; Lanfer, Benjamin; Rusiniak, Mateusz; Wolters, Carsten; Wellmer, Joerg (Brain Communications, 2022)
To evaluate the spatial accuracy of electrical source imaging (ESI) for known sources, Unnwongse et al. systematically performed ESI of averaged stimulation potentials recorded on simultaneous stereo-EEG and 37-electrode scalp EEG using individual finite element method models to determine the localization error.
CRIS-Team WoS Importer:2023-03-10

Validating EEG source imaging using intracranial electrical stimulation - Unnwongse, K.; Rampp, Stefan; Wehner, T.; Kowoll, A.; Parpaley, Y.; Von Lehe, M.; Lanfer, B.; Rusiniak, M.; Wolters, C.; Wellmer, J. (EPILEPSIA, 2022)
CRIS-Team WoS Importer:2022-09-30

Validation of the Tuebingen CD-25 Inventory as a Measure of Postoperative Health-Related Quality of Life in Patients Treated for Cushing's Disease - Milian, Monika; Kreitschmann-Andermahr, Ilonka; Siegel, Sonja; Kleist, Bernadette; Fuehrer-Sakel, Dagmar; Honegger, Juergen; Buchfelder, Michael; Psaras, Tsambika (Neuroendocrinology, 2015)
To evaluate the construct and criterion validity of the Tuebingen Cushing's disease quality of life inventory (Tuebingen CD-25) for application in patients treated for Cushing's disease (CD).A total of 176 patients with adrenocorticotropin hormone-dependent CD (144 of them female, overall mean age 46.1 ± 13.7 years) treated at 3 large tertiary referral centers in Germany were studied. Construct validity was assessed by hypothesis testing (self-perceived symptom reduction assessment) and contrasted groups (patients with vs. without hypercorticolism). For this purpose, already existing data from 55 CD patients was used, representing the hypercortisolemic group. Criterion validity (concurrent validity) was assessed in relation to the Cushing's quality of life questionnaire (CushingQoL), the Short Form 36 health survey (SF-36), and the body mass index (BMI).Patients with self-perceived remarkable symptom reduction had significant lower Tuebingen CD-25 scores (i.e. better health-related quality of life) than patients with self-perceived insufficient symptom reduction (p < 0.05). Similarly, the mean scores of the Tuebingen CD-25 scales were lower in patients without hypercortisolism (total score 27.0 ± 17.2) compared to those with hypercortisolism (total score 45.3 ± 22.1; each p < 0.05), providing evidence for construct validity. Criterion validity was confirmed by the correlations between the Tuebingen CD-25 total score and the CushingQoL (Spearman's coefficient -0.733), as well as all scales of the SF-36 (Spearman's coefficient between -0.447 and -0.700).The analyses presented in this large-sample study provide robust evidence for the construct and criterion validity of the Tuebingen CD-25.
EVALuna2:22849

Value of Flat-detector Computed Tomography Angiography with Intravenous Contrast Media Injection in the Evaluation and Treatment of Acutely Ruptured Aneurysms of the AcomA complex: A Single Center Experience in 15 Cases - Rösch, Julie; Lang, Stefan; Gölitz, Philipp; Kallmünzer, Bernd; Roessler, Karl; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2018)
Objective To illustrate the added value of flat-detector computed tomography angiography with intravenous contrast media injection (intravenous FDCTA) in the evaluation of complex A1/A2/AcomA aneurysms. Patients and Methods We retrospectively reviewed 15patients with ruptured aneurysms. In each patient, an intravenous FDCTA was performed and its diagnostic value investigated. Results In all patients, FDCTA contributed relevant additional information concerning the anatomy of the A1/A2/AcomA complex and the relationship of the aneurysm neck to these vascular structures, which could not be gained by 2D- and 3D-DSA, and changed the management in 33% of the patients (5 out of 15). In an additional 5cases, knowledge of the detailed anatomy was helpful to plan the exact stent position. Conclusion In case of complex A1/A2/AcomA aneurysms, intravenous FDCTA is an effective option to visualize the exact location of the aneurysm neck and the relationship between the aneurysm and the adjacent vessels. Thus, it is of significant added value in the precise planning of atherapeutic strategy.
EVALuna2:34934

Vascular architecture mapping for early detection of glioblastoma recurrence - Stadlbauer, Andreas; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Zimmermann, Max; Dörfler, Arnd; Heinz, Gertraud; Oberndorfer, Stefan (Neurosurgical Focus, 2019)
OBJECTIVE: Treatment failure and inevitable tumor recurrence are the main reasons for the poor prognosis of glioblastoma (GB). Gross-total resection at repeat craniotomy for GB recurrence improves patient overall survival but requires early and reliable detection. It is known, however, that even advanced MRI approaches have limited diagnostic performance for distinguishing tumor progression from pseudoprogression. The novel MRI technique of vascular architectural mapping (VAM) provides deeper insight into tumor microvascularity and neovascularization. In this study the authors evaluated the usefulness of VAM for the monitoring of GB patients and quantitatively analyzed the features of neovascularization of early- and progressed-stage GB recurrence. METHODS: In total, a group of 115 GB patients who received overall 374 follow-up MRI examinations after standard treatment were retrospectively evaluated in this study. The clinical routine MRI (cMRI) protocol at 3 Tesla was extended with the authors' experimental VAM approach, requiring 2 minutes of extra time for data acquisition. Custom-made MATLAB software was used for calculation of imaging biomarker maps of macrovascular perfusion from perfusion cMRI as well as of microvascular perfusion and architecture from VAM data. Additionally, cMRI data were analyzed by two board-certified radiologists in consensus. Statistical procedures included receiver operating characteristic (ROC) analysis to determine diagnostic performances for GB recurrence detection. RESULTS: Overall, cMRI showed GB recurrence in 89 patients, and in 28 of these patients recurrence was detected earlier with VAM data, by 1 (20 patients) or 2 (8 patients) follow-up examinations, than with cMRI data. The mean time difference between recurrence detection with VAM and cMRI data was 147 days. During this time period the mean tumor volume increased significantly (p < 0.001) from 9.7 to 26.8 cm3. Quantitative analysis of imaging biomarkers demonstrated microvascular but no macrovascular hyperperfusion in early GB recurrence. Therefore, ROC analysis revealed superior diagnostic performance for VAM compared with cMRI. CONCLUSIONS: This study demonstrated that the targeted assessment of microvascular features using the VAM technique provided valuable information about early neovascularization activity in recurrent GB that is complementary to perfusion cMRI and may be helpful for earlier and more precise monitoring of patients suffering from GB. This VAM approach is compatible with existing cMRI protocols. Prospective clinical trials are necessary to investigate the clinical usefulness and potential benefit of increased overall survival with the use of VAM in patients with recurrent GB.
CRIS-Team Scopus Importer:2019-12-13
Keywords: AUC = area under the ROC curve; CA = contrast agent; CBV = cerebral blood volume; CE = contrast enhanced; cMRI = clinical routine MRI; cNAWM = contralateral normal appearing white brain matter; DSC = dynamic susceptibility contrast; EPI = echo-planar imaging; FN = false negative; FP = false positive; GB = glioblastoma; GE = gradient echo; glioblastoma; MRI; MTI = microvessel type indicator; MVD = microvessel density; neovascularization; OS = overall survival; RANO = Response Assessment in Neuro-Oncology; recurrence; ROC = receiver operating characteristic; ROI = region of interest; SE = spin echo; T1W = T1 weighted; TN = true negative; TP = true positive; VAM = vascular architectural mapping; vascular architecture; VHL = vascular hysteresis loop; VSI = vessel size index; µCBV = microvascular CBV

Vascular endothelia growth factor targeted therapy may improve the effect of dendritic cell-based cancer immune therapy - Buchroithner, Johanna; Pichler, Josef; Marosi, Christine; Widhalm, Georg; Seiz-Rosenhagen, Marcel; Novosielski, Martha; Oberndorfer, Stefan; Ruckser, Reinhard; Roessler, Karl; Azizi, Amedeo; Von Campe, Gord; Bordihn, Karin; et al. (International Journal of Clinical Pharmacology and Therapeutics, 2014)
EVALuna2:22843

Vascular Hysteresis Loops and Vascular Architecture Mapping in Patients with Glioblastoma treated with Antiangiogenic Therapy - Stadlbauer, Andreas; Zimmermann, Max; Oberndorfer, Stefan; Dörfler, Arnd; Buchfelder, Michael; Heinz, Gertraud; Roessler, Karl (Scientific Reports, 2017)
In this study, we investigated the variability of vascular hysteresis loop (VHL) shapes and the spatial heterogeneity of neovascularization and microvascular alterations using vascular architecture mapping (VAM) in patients with recurrent glioblastoma during bevacizumab mono-therapy. VAM data were acquired in 13 patients suffering from recurrent glioblastoma prior to and 3 months after bevacizumab treatment onset using a dual contrast agent injections approach as part of routine MRI. Two patients were additionally examined after the first cycle of bevacizumab to check for early treatment response. VHLs were evaluated as biomarker maps of neovascularization activity: microvessel type indicator (MTI) and curvature (Curv) of the VHL-long-axis. Early response to bevacizumab was dominated by reduction of smaller microvasculature (around 10 µm). In the 3-month follow-up, responding tumors additionally showed a reduction in larger microvasculature (>20 µm). VAM biomarker images revealed spatially heterogeneous microvascular alterations during bevacizumab treatment. Responding, non-responding, progressive, and remote-progressive tumor areas were observed. MTI may be useful to predict responding and non-responding tumor regions, and Curv to assess severity of vasogenic edema. Analysis of VHLs in combination with VAM biomarkers may lead to a new perspective on investigating the spatial heterogeneity of neovascularization and microvascular alterations in glioblastoma during antiangiogenic therapy.
EVALuna2:33144

Vascular supply of the metacarpophalangeal joint - Baksa, Gabor; Czeibert, Kalman; Sharp, Veronika; Handschuh, Stephan; Gyebnar, Janos; Barany, Laszlo; Benis, Szabolcs; Nyiri, Gabor; Mandl, Peter; Petnehazy, Ors; Balint, Peter Vince (Frontiers in Medicine, 2022)
Objective: To describe in detail the arterial vasculature of metacarpophalangeal joints 2–5 on cadaver specimens and to compare it to ultrasound imaging of healthy subjects. Methods: Eighteen hands of donated human cadavers were arterially injected and investigated with either corrosion casting or cryosectioning. Each layer of cryosectioned specimens was photographed in high-resolution. Images were then segmented for arterial vessels of the metacarpophalangeal (MCP) joints 2–5. The arterial pattern of the joints was reconstructed from the segmented images and from the corrosion cast specimens. Both hands of ten adult healthy volunteers were scanned focusing on the vasculature of the same joints with high-end ultrasound imaging, including color Doppler. Measurements were made on both cryosectioned arteries and Doppler images. Results: The arterial supply of MCP joints 2–5 divides into a metacarpal and a phalangeal territory, respectively. The metacarpal half receives arteries from the palmar metacarpal arteries or proper palmar digital arteries, while the phalangeal half is supplied by both proper and common palmar digital arteries. Comparing anatomical and ultrasonographic results, we determined the exact anatomic location of normal vessels using Doppler images acquired of healthy joints. All, except three branches, were found with less than 50% frequency using ultrasound. Doppler signals were identified significantly more frequently in MCP joints 2–3 than on 4–5 (p < 0.0001). Similarly, Doppler signals differed in the number of detectable small, intraarticular vessels (p < 0.009), but not that of the large extraarticular ones (p < 0.1373). When comparing measurements acquired by ultrasound and on cadaver vessels, measurements using the former technique were found to be larger in all joints (p < 0.0001). Conclusion: Using morphological and ultrasonographic techniques, our study provides a high-resolution anatomical maps and an essential reference data set on the entire arterial vasculature of healthy human MCP 2–5 joints. We found that Doppler signal could be detected in less than 50% of the vessels of healthy volunteers except three locations. Intraarticular branches were detected with ultrasound imaging significantly more frequently on healthy MCP 2–3 joints, which should be taken into account when inflammatory and normal Doppler signals are evaluated. Our study also provides reference data for future, higher-resolution imaging techniques.
CRIS-Team Scopus Importer:2022-11-18
Keywords: arterial supply; articular; Doppler; metacarpophalangeal joint; rheumatoid arthritis; ultrasound

Ventricular and lumbar cerebrospinal fluid concentrations of Alzheimer's disease biomarkers in patients with normal pressure hydrocephalus and posttraumatic hydrocephalus - Brandner, Sebastian; Thaler, Christian; Lelental, Natalia; Buchfelder, Michael; Kleindienst, Andrea; Maler, Juan Manuel; Kornhuber, Johannes; Lewczuk, Piotr (Journal of Alzheimer's Disease, 2014)
Little information is available on the rostro-caudal concentration gradient of Alzheimer's disease (AD) biomarkers.We studied the concentrations of amyloid-? (A?) peptides 1-42 and 1-40 as well as the Tau and pTau proteins in simultaneously collected ventricular and lumbar cerebrospinal fluid (CSF) samples.The samples were simultaneously collected from the ventricle and the lumbar spinal canal in two groups of patients: 10 subjects being treated for normal pressure hydrocephalus (NPH) by the placement of a ventriculo-peritoneal shunt and 5 patients treated simultaneously with an external ventricular drain and a lumbar CSF drain due to posttraumatic hydrocephalus (PTH).The ventricular-lumbar (V/L) concentration ratio for A?1-40 was 0.81 in NPH patients and 0.71 in PTH patients. The V/L-ratio for A?1-42 was 0.84 in NPH, reflecting significantly higher concentrations in lumbar CSF than in ventricular CSF, and 1.02 in PTH patients. The V/L-ratios for Tau and pTau differed significantly depending on the diagnostic group: the median V/L-ratio for Tau was 6.83 in NPH patients but only 0.97 in PTH patients. The median V/L-ratio for pTau was 2.36 in NPH patients and 0.91 in PTH patients.We conclude that the rostro-caudal concentration gradient for brain-derived proteins (Tau and pTau in this study) depends on the diagnosis and clinical status of the patient, which were largely neglected in the previously postulated models.
EVALuna2:22827

Vestibular Schwannoma Volume and Tumor Growth Correlates with Macrophage Marker Expression - Leisz, Sandra; Klause, Clara Helene; Dos Santos, Tania Vital; Haenel, Pia; Scheer, Maximilian; Simmermacher, Sebastian; Mawrin, Christian; Strauss, Christian; Scheller, Christian; Rampp, Stefan (Cancers, 2022)
Vestibular schwannoma is the most common benign tumor of the cerebellopontine angle and originates from Schwann cells surrounding the vestibulocochlear nerve. Since the size of the VS varies widely, affected patients suffer from symptoms of varying severity. It is often difficult to determine the optimal time for therapy, due to the unpredictability of the growth rate. Despite many investigations on influencing factors, no mechanism responsible for the increase in the growth rate of certain VS has been identified so far. Therefore, the present study investigates the influence of the seven markers: Ki-67, cyclooxygenase 2 (COX2), vascular endothelial growth factor (VEGF), macrophage colony-stimulating factor (M-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), CD163, and CD68 on tumor progression and tumor size in a cohort of 173 VS. The markers were determined by quantitative PCR and correlated with tumor volume and VS growth rate. The analysis showed a significantly negative correlation of the Ki-67, COX2, and VEGF on tumor volume. Moreover, with a higher volume of VS, the expression of the macrophage markers CD68, CD163, and GM-CSF increased significantly. Our results suggest that the increase in VS size is not primarily due to Schwann cell growth but to an infiltration of macrophages. This may have an impact on non-invasive therapy to preserve the hearing function of affected patients.
CRIS-Team Scopus Importer:2022-10-07
Keywords: CD163; CD68; macrophage infiltration; TAM; tumor growth; tumor volume; vestibular schwannoma

Virtual endoscopy assisted pure ventriculoscopic resection of cavernomas occluding foramen of Monroe: Technical note and literature review - Yang, Jia; Zhao, Yining; Xu, Xinghua; Wang, Qun; Li, Fangye; Zhang, Jiashu; Chen, Xiaolei (Journal of Clinical Neuroscience, 2021)
Objective: Cavernomas at Foramen of Monroe (FoM) are rare cases among the intracranial cavernomas. Pure ventriculoscopic removal of cavernoma at FoM through a single burr hole is challenging and rarely reported. Methods: We herein introduced the virtual endoscopy (VE) assisted ventriculoscopic resection to treat the cavernomas at FoM. Two cases diagnosed with cavernomas at FoM, a 31-year-old male patient (case 1) and a 26-year-old male patient (case 2), were included. Both of them suffered from headache, nausea and vomiting. The pre-operative MRI revealed masses at the FoM. We reconstructed the VE on a free and open-source platform (3D Slicer) for the pre-surgical evaluation. And then ventriculoscopic operation through a single burr hole was made to remove the cavernomas at FoM. Results: The VE displayed a 14×19×16 mm lesion in case 1 and an 18×20×29 mm lesion in case 2 and both cases revealed some attachment between the lesions and the periventricular tissue. The ventriculoscopic operations indicated by VE were performed to achieve total resection of the cavernomas without neurological deficit. Conclusions: Although the neuroendoscopic treatment to cavernoma at FoM through a single burr hole was rarely reported among the previous literatures, it was a quite effective and useful method in our cases. And the application of VE before ventriculoscopic operation could help to provide a three-dimensional and panorama view of the intraventricular lesions.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Cavernoma; Foramen of Monroe; Ventriculoscopic operation; Virtual endoscopy

Visualization of CSF Flow with Time-resolved 3D MR Velocity Mapping in Aqueductal Stenosis Before and After Endoscopic Third Ventriculostomy : A Feasibility Study - Brandner, Sebastian; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Dörfler, Arnd; Stadlbauer, Andreas (Clinical Neuroradiology, 2018)
PURPOSE: The aim of this study was to evaluate timed-resolved three-dimensional (3D) magnetic resonance (MR) velocity mapping as a method for investigation of cerebrospinal fluid (CSF) flow changes in patients with aqueductal stenosis (AS) treated by endoscopic third ventriculostomy (ETV). METHODS: The MR velocity mapping was performed in 12 AS patients before and after ETV and in 10 healthy volunteers by using a 3-Tesla MR system. Time-resolved 3D MR velocity mapping data were acquired with a standard 3D phase contrast (PC) sequence with cardiac triggering. Values of mean (vmean) and maximum (vpeak) velocity were measured at several ventricular structures using dedicated software. RESULTS: Of the patients 11 showed a satisfactory clinical improvement after ETV, whereas one patient needed subsequent shunt implantation. All AS patients showed significant hypomotile CSF flow dynamics in the third ventricle when compared to healthy subjects before surgery (p < 0.05). In contrast, CSF flow velocity was increased within the Foramen of Monro in AS patients. After ETV, all AS patients showed a decrease of CSF flow dynamics within the third ventricle. Mean and peak CSF flow velocities through the ventriculostomy were 1.72 ± 0.59 cm/s (vmean) and 3.53 ± 0.79 cm/s (vpeak), respectively after ETV. The patient who needed shunt implantation after ETV had the lowest flow velocities through the ventriculostomy. CONCLUSION: This study demonstrates that timed-resolved 3D MR velocity mapping is a useful imaging investigation for diagnostics and follow-up in patients with AS. This new technique provides an insight into the physiological CSF flow changes related with AS and its treatment.
EVALuna2:212790

Web-based decision support system for patient-tailored selection of antiseizure medication in adolescents and adults: An external validation study - Hadady, Levente; Klivenyi, Peter; Perucca, Emilio; Rampp, Stefan; Fabo, Daniel; Bereczki, Csaba; Rubboli, Guido; Asadi-Pooya, Ali A.; Sperling, Michael R.; Beniczky, Sandor (European Journal of Neurology, 2021)
Background and purpose: Antiseizure medications (ASMs) should be tailored to individual characteristics, including seizure type, age, sex, comorbidities, comedications, drug allergies, and childbearing potential. We previously developed a web-based algorithm for patient-tailored ASM selection to assist health care professionals in prescribing medication using a decision support application (https://epipick.org). In this validation study, we used an independent dataset to assess whether ASMs recommended by the algorithm are associated with better outcomes than ASMs considered less desirable by the algorithm. Methods: Four hundred twenty-five consecutive patients with newly diagnosed epilepsy were followed for at least 1 year after starting an ASM chosen by their physician. Patient characteristics were fed into the algorithm, blinded to the physician's ASM choices and outcome. The algorithm recommended ASMs, ranked in hierarchical groups, with Group 1 ASMs labeled as the best option for that patient. We evaluated retention rates, seizure freedom rates, and adverse effects leading to treatment discontinuation. Survival analysis contrasted outcomes between patients who received favored drugs and those who received lower ranked drugs. Propensity score matching corrected for possible imbalances between the groups. Results: Antiseizure medications classified by the algorithm as best options had a higher retention rate (79.4% vs. 67.2%, p = 0.005), higher seizure freedom rate (76.0% vs. 61.6%, p = 0.002), and lower rate of discontinuation due to adverse effects (12.0% vs. 29.2%, p < 0.001) than ASMs ranked as less desirable by the algorithm. Conclusions: Use of the freely available decision support system is associated with improved outcomes. This drug selection application can provide valuable assistance to health care professionals prescribing medication for individuals with epilepsy.
CRIS-Team Scopus Importer:2021-12-03
Keywords: adolescent; adult; adverse effects; antiepileptic drugs; epilepsy; neuropharmacology

Geriatric Basics for the Neurohospitalist - Heckmann, Josef G.; Kraus, Joerg; Lang, Christoph (Neurohospitalist, 2018)
Due to the increasing age of the population, neurohospitalists are more frequently caring for old and very old people. Fundamental definitions and topics related to geriatric medicine are therefore of particular importance. In this review, common issues encountered in geriatric patients hospitalized on the neurology service are discussed. Focus is put on the geriatric assessment, multiprofessional diagnostic and therapeutic procedures, geriatric syndromes, pharmacotherapy of the aged, delirium, pain, and palliative management as they are relevant for the neurohospitalist. In addition, ethical questions are addressed.
CRIS-Team WoS Importer:2019-02-22

How technology is driving the landscape of epilepsy surgery - Dorfer, Christian; Rydenhag, Bertil; Baltuch, Gordon; Buch, Vivek; Blount, Jeffrey; Bollo, Robert; Gerrard, Jason; Nilsson, Daniel; Rössler, Karl; Rutka, James; Sharan, Ashwini; Spencer, Dennis; et al. (Epilepsia, 2020)
This article emphasizes the role of the technological progress in changing the landscape of epilepsy surgery and provides a critical appraisal of robotic applications, laser interstitial thermal therapy, intraoperative imaging, wireless recording, new neuromodulation techniques, and high-intensity focused ultrasound. Specifically, (a) it relativizes the current hype in using robots for stereo-electroencephalography (SEEG) to increase the accuracy of depth electrode placement and save operating time; (b) discusses the drawback of laser interstitial thermal therapy (LITT) when it comes to the need for adequate histopathologic specimen and the fact that the concept of stereotactic disconnection is not new; (c) addresses the ratio between the benefits and expenditure of using intraoperative magnetic resonance imaging (MRI), that is, the high technical and personnel expertise needed that might restrict its use to centers with a high case load, including those unrelated to epilepsy; (d) soberly reviews the advantages, disadvantages, and future potentials of neuromodulation techniques with special emphasis on the differences between closed and open-loop systems; and (e) provides a critical outlook on the clinical implications of focused ultrasound, wireless recording, and multipurpose electrodes that are already on the horizon. This outlook shows that although current ultrasonic systems do have some limitations in delivering the acoustic energy, further advance of this technique may lead to novel treatment paradigms. Furthermore, it highlights that new data streams from multipurpose electrodes and wireless transmission of intracranial recordings will become available soon once some critical developments will be achieved such as electrode fidelity, data processing and storage, heat conduction as well as rechargeable technology. A better understanding of modern epilepsy surgery will help to demystify epilepsy surgery for the patients and the treating physicians and thereby reduce the surgical treatment gap.
CRIS-Team WoS Importer:2020-04-10

Individually Stabilized, Superparamagnetic Nanoparticles with Controlled Shell and Size Leading to Exceptional Stealth Properties and High Relaxivities - Lassenberger, Andrea; Scheberl, Andrea; Stadlbauer, Andreas; Stiglbauer, Alexander; Helbich, Thomas; Reimhult, Erik (ACS Applied Materials and Interfaces, 2017)
Superparamagnetic iron oxide nanoparticles (SPION) have received immense interest for biomedical applications, with the first clinical application as negative contrast agent in magnetic resonance imaging (MRI). However, the first generation MRI contrast agents with dextran-enwrapped, polydisperse iron oxide nanoparticle clusters are limited to imaging of the liver and spleen; this is related to their poor colloidal stability in biological media and inability to evade clearance by the reticuloendothelial system. We investigate the qualitatively different performance of a new generation of individually PEG-grafted core-shell SPION in terms of relaxivity and cell uptake and compare them to benchmark iron oxide contrast agents. These PEG-grafted SPION uniquely enable relaxivity measurements in aqueous suspension without aggregation even at 9.4 T magnetic fields due to their extraordinary colloidal stability. This allows for determination of the size-dependent scaling of relaxivity, which is shown to follow a d2 dependence for identical core-shell structures. The here introduced core-shell SPION with ∼15 nm core diameter yield a higher R2 relaxivity than previous clinically used contrast agents as well as previous generations of individually stabilized SPION. The colloidal stability extends to control over evasion of macrophage clearance and stimulated uptake by SPION functionalized with protein ligands, which is a key requirement for targeted MRI.
EVALuna2:214810

Transgenerational transduction of MPTP-induced alterations in a Parkinson's disease mouse model - Alvarez-Fischer, D.; Vernik, T.; Vulinovic, F.; Herrmann, A.; Westenberger, A.; Klein, C. (Parkinsonism & related disorders, 2020)
Susceptibility to Parkinson's disease (PD) increases more than threefold in first-degree relatives of PD patients. Using a mouse model, we investigated in a proof-of-principle approach whether toxin exposure of F0 affects the F1 generation. We provide first evidence that disturbance of the nigrostriatal pathway can be transferred to the next generation.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Epigenetic; Neurodegeneration